A20 as a novel prognostic factor for recurrence and patients' survival in oral squamous cell carcinoma - Spörl, Silvia; Erber, Ramona; Gerken, M.; Fischer, R.; Taxis, J.; Meier, J. K.; Geppert, Carol-Immanuel; Hartmann, Arndt; Beckhove, P.; Mackensen, Andreas; Reichert, T.; Spanier, G.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

A20 as a Potential New Tool in Predicting Recurrence and Patient’s Survival in Oral Squamous Cell Carcinoma - Spoerl, Steffen; Erber, Ramona; Gerken, Michael; Taxis, Juergen; Ludwig, Nils; Nieberle, Felix; Biermann, Niklas; Geppert, Carol-Immanuel; Ettl, Tobias; Hartmann, Arndt; Beckhove, Philipp; Reichert, Torsten E.; et al. (Cancers, 2023)
A20, known as a potent inhibitor of NF-κB signaling, has been characterized in numerous clinical as well as preclinical studies. Recently, especially in various malignant diseases, the prognostic and therapeutic relevance of A20 was investigated. In oral squamous cell carcinoma (OSCC) however, the characterization of A20 is uncharted territory. We analyzed a tissue microarray (TMA) of 229 surgically-treated OSCC patients (2003–2013). Immunohistochemical (IHC) stainings were performed for A20 and CD3; additionally, standard haematoxylin-eosin staining was applied. IHC findings were correlated with a comprehensive dataset, comprising clinical and pathohistological information. A20 expression was analyzed in tumor cells as well as in tumor infiltrating lymphocytes (TILs) and correlated with the overall survival (OS) and recurrence-free survival (RFS) using uni- and multivariable Cox regression. The median follow-up time was 10.9 years and the A20 expression was significantly decreased in CD3+ TILs compared to mucosa-infiltrating lymphocytes (MILs). In the Kaplan–Meier analyses, higher A20 expression in TILs was correlated with better OS (p = 0.017) and RFS (p = 0.020). In the multivariable survival analysis, A20 overexpression correlated with improved OS (HR: 0.582; 95% CI 0.388–0.873, p = 0.009) and RFS (HR 0.605; 95% CI 0.411–0.889, p = 0.011). Our results indicate a novel prognostic role for A20 in OSCC. Due to its elevated expression in TILs, further research is highly desirable, which therefore could offer new therapeutic opportunities for patients suffering from OSCC.
CRIS-Team Scopus Importer:2023-02-24
Keywords: A20; oral squamous cell carcinoma; OSCC; tissue microarray; TNFAIP3

Aberrant DNA hypermethylation of SDHC: a novel mechanism of tumor development in Carney triad - Haller, Florian; Moskalev, Evgeny; Faucz, Fabio R.; Barthelmeß, Sarah; Wiemann, Stefan; Bieg, Matthias; Assie, Guillaume; Bertherat, Jerome; Schaefer, Inga-Marie; Otto, Claudia; Rattenberry, Eleanor; Maher, Eamonn R.; et al. (Endocrine-Related Cancer, 2014)
Carney triad (CT) is a rare condition with synchronous or metachronous occurrence of gastrointestinal stromal tumors (GISTs), paragangliomas (PGLs), and pulmonary chondromas in a patient. In contrast to Carney-Stratakis syndrome (CSS) and familial PGL syndromes, no germline or somatic mutations in the succinate dehydrogenase (SDH) complex subunits A, B, C, or D have been found in most tumors and/or patients with CT. Nonetheless, the tumors arising among patients with CT, CSS, or familial PGL share a similar morphology with loss of the SDHB subunit on the protein level. For the current study, we employed massive parallel bisulfite sequencing to evaluate DNA methylation patterns in CpG islands in proximity to the gene loci of all four SDH subunits. For the first time, we report on a recurrent aberrant dense DNA methylation at the gene locus of SDHC in tumors of patients with CT, which was not present in tumors of patients with CSS or PGL, or in sporadic GISTs with KIT mutations. This DNA methylation pattern was correlated to a reduced mRNA expression of SDHC, and concurrent loss of the SDHC subunit on the protein level. Collectively, these data suggest epigenetic inactivation of the SDHC gene locus with functional impairment of the SDH complex as a plausible alternate mechanism of tumorigenesis in CT.
EVALuna2:6647

Ability of 18F-FDG Positron Emission Tomography Radiomics and Machine Learning in Predicting KRAS Mutation Status in Therapy-Naive Lung Adenocarcinoma - Zhang, Ruiyun; Shi, Kuangyu; Hohenforst-Schmidt, Wolfgang; Steppert, Claus; Sziklavari, Zsolt; Schmidkonz, Christian; Atzinger, Armin; Hartmann, Arndt; Vieth, Michael; Förster, Stefan (Cancers, 2023)
Objective: Considering the essential role of KRAS mutation in NSCLC and the limited experience of PET radiomic features in KRAS mutation, a prediction model was built in our current analysis. Our model aims to evaluate the status of KRAS mutants in lung adenocarcinoma by combining PET radiomics and machine learning. Method: Patients were retrospectively selected from our database and screened from the NSCLC radiogenomic dataset from TCIA. The dataset was randomly divided into three subgroups. Two open-source software programs, 3D Slicer and Python, were used to segment lung tumours and extract radiomic features from 18F-FDG-PET images. Feature selection was performed by the Mann–Whitney U test, Spearman’s rank correlation coefficient, and RFE. Logistic regression was used to build the prediction models. AUCs from ROCs were used to compare the predictive abilities of the models. Calibration plots were obtained to examine the agreements of observed and predictive values in the validation and testing groups. DCA curves were performed to check the clinical impact of the best model. Finally, a nomogram was obtained to present the selected model. Results: One hundred and nineteen patients with lung adenocarcinoma were included in our study. The whole group was divided into three datasets: a training set (n = 96), a validation set (n = 11), and a testing set (n = 12). In total, 1781 radiomic features were extracted from PET images. One hundred sixty-three predictive models were established according to each original feature group and their combinations. After model comparison and selection, one model, including wHLH_fo_IR, wHLH_glrlm_SRHGLE, wHLH_glszm_SAHGLE, and smoking habits, was validated with the highest predictive value. The model obtained AUCs of 0.731 (95% CI: 0.619 0.843), 0.750 (95% CI: 0.248 1.000), and 0.750 (95% CI: 0.448 1.000) in the training set, the validation set and the testing set, respectively. Results from calibration plots in validation and testing groups indicated that there was no departure between observed and predictive values in the two datasets (p = 0.377 and 0.861, respectively). Conclusions: Our model combining 18F-FDG-PET radiomics and machine learning indicated a good predictive ability of KRAS status in lung adenocarcinoma. It may be a helpful non-invasive method to screen the KRAS mutation status of heterogenous lung adenocarcinoma before selected biopsy sampling.
CRIS-Team Scopus Importer:2023-10-27
Keywords: KRAS; lung adenocarcinoma; machine learning; PET; radiomic features

A case of multiple familial trichoepitheliomas responding to treatment with the Hedgehog signaling pathway inhibitor vismodegib - Baur, Vera; Papadopoulos, Thomas; Kazakov, Dmitry; Agaimy, Abbas; Hartmann, Arndt; Isbary, Georg; Wirtz, Ralph M.; Schultz, Erwin S. (Virchows Archiv, 2018)
Multiple familial trichoepitheliomas (MFT) is an autosomal dominantly inherited disease characterized by multiple skin appendage tumors. We describe a patient showing a continuous spectrum of follicular differentiated neoplasms including classical trichoepitheliomas but also infiltrative growing and finally metastasizing malignant follicular differentiated tumors. Germline mutation analysis revealed a nonsense mutation in the cylindromatosis (CYLD) gene. Gene expression analysis by real-time PCR of tumor tissue showed overexpression of glioma-associated oncogene Gli1 mRNA. Treatment with the Hedgehog pathway inhibitor vismodegib resulted in a significant regression of the highly differentiated trichoepitheliomas. Gli upregulation is indicative of an active Hedgehog signaling pathway. We hypothesize that its upregulation is indirectly caused by CYLD mutation which promotes tumor development. Vismodegib treatment could thus provide a new treatment option for patients with this debilitating disorder.
EVALuna2:34604

Accelerated Partial Breast Irradiation: Identification of High Risk Tumors in Early Hormone Receptor-positive Breast Cancer by Macrophage Shift Classification - Schnellhardt, S.; Erber, Ramona; Büttner-Herold, Maike; Rosahl, M. -C; Ott, Oliver; Strnad, Vratislav; Beckmann, Matthias; King, L.; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Accelerated partial breast irradiation: Macrophage polarisation shift classification identifies high-risk tumours in early hormone receptor-positive breast cancer - Schnellhardt, Sören; Erber, Ramona; Büttner-Herold, Maike; Rosahl, Marie Charlotte; Ott, Oliver; Strnad, Vratislav; Beckmann, Matthias; King, Lillian; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Cancers, 2020)
Studies have demonstrated correlations between accumulations of tumour-associated macrophages (TAMs), especially of M2-like phenotype, and increased mortality in advanced breast cancer. We investigated the prognostic potential of both main macrophage phenotypes in early hormone receptor-positive (HR+) breast cancer. The studied cohort of 136 patients participated in an institutional APBI phase II trial. Patient selection was characterized by HR+, small tumour size and no metastasis. Tissue microarrays from pre-RT resection samples were double stained for CD68/CD163 using immunohistochemistry. CD68+/CD163− cells were considered M1-like macrophages and CD68+/CD163+ was representative of M2-like macrophages. M1 and M2 macrophage densities were analysed semi-automatically in the stromal and intraepithelial tumour compartment. Low M1 and high M2 densities were strongly associated with decreased disease-free survival (DFS). Combined TAM phenotype densities were studied after defining a macrophage shift classification: M1-shifted (M1 high, M2 low) and non-shifted (M1 low, M2 low; M1 high, M2 high) tumours entailed a favourable outcome. In contrast, M2-shifted (M1 low, M2 high) TAM populations were associated with extremely reduced DFS. Thus, the full predictive potential of TAMs was revealed in a combined analysis of both phenotypes. The M2-shifted subgroup of tumours is classified as high-risk and probably not suitable for partial breast irradiation.
CRIS-Team Scopus Importer:2020-02-25
Keywords: Accelerated partial breast irradiation; CD163; CD68; Early breast cancer; Hormone receptor-positive; Prognosis; Tumour associated macrophages

Accuracy of colposcopic findings in detecting vaginal intraepithelial neoplasia: a retrospective study - Stuebs, F. A.; Adler, W.; Beckmann, Matthias; Gaß, Paul; Hartmann, Arndt; Mehlhorn, G.; Renner, S. K.; Schulmeyer, Carla; Strehl, J.; Koch, Matthias (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Accuracy of colposcopic findings in detecting vaginal intraepithelial neoplasia: a retrospective study - Stuebs, Frederik A.; Koch, Martin; Mehlhorn, Grit; Gaß, Paul; Schulmeyer, Carla; Hartmann, Arndt; Strehl, Johanna; Adler, Werner; Beckmann, Matthias; Renner, Stefan (Archives of Gynecology and Obstetrics, 2020)
Purpose: Malignancies of the vagina are rare, but colposcopy-directed biopsies play a major role in detecting vaginal intraepithelial lesions. Data of accuracy in detecting neoplasia of the vagina are very rare compared to accuracy in detecting cervical neoplasia. The aim of this study was to evaluate the accuracy of colposcopy-directed biopsy in comparison with clinical findings of the examiner. Methods: The accuracy of colposcopy-directed biopsy was compared with the clinical finding in relation to the patient’s age and the examiner’s level of training. This was done in combination with PAP-smear, HPV-test results, and the history of other malignancies of the lower genital tract. The data were collected between January 2014 and February 2018 at the certified Dysplasia Unit of the University Hospital Erlangen. Results: In total, 253 biopsies from 253 women from the vagina were obtained. The overall accuracy of biopsy in comparison with clinical finding was 52.17% for all entities—benign lesions, low-grade squamous intraepithelial lesions (LSILs), high-grade squamous intraepithelial lesions (HSILs), and vaginal carcinoma. The accuracy for detecting HSIL was 82.46% (47/57), with an underdiagnosis rate of 15.79% and an overdiagnosis rate of 1.79%. Conclusion: With a sensitivity of over 80%, colposcopy-directed biopsy plays an important role in detecting vaginal–HSIL. A highly experienced practitioner is increasing the sensitivity in detecting vaginal–HSIL. Careful examination is required in women with a history of HSIL of the lower genital tract or with simultaneous neoplasia because they are of greater risk of developing vaginal malignancies. The combination of careful clinical work up, PAP-smear, HPV-testing, and colposcopy-guided biopsy is crucial in detecting vaginal–HSIL.
CRIS-Team Scopus Importer:2020-02-04
Keywords: Colposcopy-directed biopsy; High-grade squamous intraepithelial lesion (HSIL); Vaginal cancer; Vaginal intraepithelial neoplasia (VaIN)

Accuracy of colposcopy-directed biopsy in detecting early cervical neoplasia: a retrospective study - Stuebs, Frederik A.; Schulmeyer, Carla E.; Mehlhorn, Grit; Gaß, Paul; Kehl, Sven; Renner, Simone K.; Renner, Stefan; Geppert, Carol-Immanuel; Adler, Werner; Hartmann, Arndt; Beckmann, Matthias; Koch, Martin (Archives of Gynecology and Obstetrics, 2019)
PurposeColposcopy-directed biopsy is a cornerstone method for diagnosing cervical intraepithelial neoplasia. The aim of this study was to evaluate the accuracy of colposcopy-directed biopsy in comparison with definitive surgery.MethodsThe accuracy of colposcopy-directed biopsy was compared with the final histology in relation to different types of transformation zone (TZ), the patient's age, and the examiner's level of training.ResultsThe overall accuracy of biopsy in comparison with definitive surgery was 71.9% for all entitiesbenign lesions, low-grade squamous intraepithelial lesions, high-grade squamous intraepithelial lesions (HSILs), and cervical carcinomawith an underdiagnosis rate of 11.8% and an overdiagnosis rate of 16.5%. The accuracy for detecting HSIL was 88% (401/455), with an underdiagnosis rate of 10.5% and overdiagnosis rate of 1.3%. The accuracy rates for detecting HSIL in women with TZ1, TZ2, or TZ3 were 92.2, 90.5, and 76.5%, respectively. The accuracy rates for detecting HSIL in the different age groups were 93.1% (age 0-34), 83.6% (age 34-55), and 80% (age 55 or older).ConclusionsA combination of the colposcopic findings, cytology, human papillomavirus testing, and colposcopy-directed biopsy is necessary for the correct diagnosis of HSIL. The accuracy rate depends on the TZ and the patient's age. The examiner's level of training does not have any substantial influence on the accuracy.
CRIS-Team WoS Importer:2019-03-08

Accuracy of radiological tumour size assessment and the risk for re-excision in a cohort of primary breast cancer patients - Meier-Meitinger, Martina; Rauh, Claudia; Adamietz, B.; Fasching, Peter; Schwab, Siegfried; Häberle, Lothar; Hein, Alexander; Bayer, Christian M.; Bani, Mayada; Lux, Michael P.; Hartmann, Arndt; Wachter, David Lukas; et al. (Ejso, 2012)
Background: Re-operations after breast conserving surgery (BCS) are necessary, when specimen margins are not free of breast cancer cells. This study explored the accuracy of preoperative tumour size assessment and its influence on the rate of re-excisions and mastectomies. Methods: The study included 1591 patients with invasive breast cancer, who were planned for BCS. Patient, staging and tumor characteristics were evaluated concerning their influence on re-excision and mastectomy rates. Patient and tumor characteristics comprised histopathological tumour size, HER2 status, multifocality, in situ component, grading (G), nodal status and hormone receptor (HR) status. Staging characteristics included deviation from pathological tumour size as measured by clinical examination, sonography and mammography. Results: In 1316 patients (83%) sufficient treatment was possible with one operation. 275 patients (17%) had to undergo at least one further surgery as a result of positive specimen margins. In 138 patients (9%) mastectomy was ultimately necessary. In patients with a positive HER2 status, a larger tumour size, underestimation by ultrasound, an in situ component and multifocality, the risk for a re-operation was about doubled. Tumour size deviation in the mammogram or the clinical tumour size assessment did not have significant influence to the re-excision rates. Conclusion: Tumour size and accurate presurgical assessment of the tumour size itself are independent predictors for the need of a second surgery or even a mastectomy in patients for whom a primary BCS was planned. © 2011 Elsevier Ltd. All rights reserved.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Breast cancer; Mastectomy; Re-excision; Tumour size; Ultrasound

Accuracy of vulvoscopic findings in detecting early vulvar neoplasia - Stuebs, F. A.; Mehlhorn, G.; Gaß, Paul; Schulmeyer, Carla; Adler, Werner; Strehl, J.; Hartmann, Arndt; Beckmann, Matthias; Renner, S. K.; Koch, Matthias (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

A Consensus Molecular Classification of Muscle-invasive Bladder Cancer - Kamoun, Aurélie; Reyniès, Aurélien de; Allory, Yves; Sjödahl, Gottfrid; Gordon Robertson, A.; Seiler, Roland; Hoadley, Katherine A.; Groeneveld, Clarice S.; Al-Ahmadie, Hikmat; Choi, Woonyoung; Castro, Mauro A.A.; Fontugne, Jacqueline; et al. (European Urology, 2019)
Background: Muscle-invasive bladder cancer (MIBC) is a molecularly diverse disease with heterogeneous clinical outcomes. Several molecular classifications have been proposed, but the diversity of their subtype sets impedes their clinical application. Objective: To achieve an international consensus on MIBC molecular subtypes that reconciles the published classification schemes. Design, setting, and participants: We used 1750 MIBC transcriptomic profiles from 16 published datasets and two additional cohorts. Outcome measurements and statistical analysis: We performed a network-based analysis of six independent MIBC classification systems to identify a consensus set of molecular classes. Association with survival was assessed using multivariable Cox models. Results and limitations: We report the results of an international effort to reach a consensus on MIBC molecular subtypes. We identified a consensus set of six molecular classes: luminal papillary (24%), luminal nonspecified (8%), luminal unstable (15%), stroma-rich (15%), basal/squamous (35%), and neuroendocrine-like (3%). These consensus classes differ regarding underlying oncogenic mechanisms, infiltration by immune and stromal cells, and histological and clinical characteristics, including outcomes. We provide a single-sample classifier that assigns a consensus class label to a tumor sample's transcriptome. Limitations of the work are retrospective clinical data collection and a lack of complete information regarding patient treatment. Conclusions: This consensus system offers a robust framework that will enable testing and validation of predictive biomarkers in future prospective clinical trials. Patient summary: Bladder cancers are heterogeneous at the molecular level, and scientists have proposed several classifications into sets of molecular classes. While these classifications may be useful to stratify patients for prognosis or response to treatment, a consensus classification would facilitate the clinical use of molecular classes. Conducted by multidisciplinary expert teams in the field, this study proposes such a consensus and provides a tool for applying the consensus classification in the clinical setting.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Consensus; Molecular taxonomy; Muscle-invasive bladder cancer; Transcriptomic classifier

Addition of triple negativity of breast cancer as an indicator for germline mutations in predisposing genes increases sensitivity of clinical selection criteria - Hoyer, Juliane; Vasileiou, Georgia; Uebe, Steffen; Wunderle, Marius; Kraus, Cornelia; Fasching, Peter; Thiel, Christian; Hartmann, Arndt; Beckmann, Matthias; Lux, Michael P.; Reis, André (BMC Cancer, 2018)
BACKGROUND: Breast cancer is the most common cancer in women. 12-15% of all tumors are triple-negative breast cancers (TNBC). So far, TNBC has been mainly associated with mutations in BRCA1. The presence of other predisposing genes seems likely since DNA damage repair is a complex process that involves several genes. Therefore we investigated if mutations in other genes are involved in cancer development and whether TNBC is an additional indicator of mutational status besides family history and age of onset. METHODS: We performed a germline panel-based screening of 10 high and low-moderate penetrance breast cancer susceptibility genes (BRCA1, BRCA2, ATM, CDH1, CHEK2, NBN, PALB2, RAD51C, RAD51D and TP53) in 229 consecutive individuals affected with TNBC unselected for age, family history or bilateral disease. Within this cohort we compared the number of mutation carriers fulfilling clinical selection criteria with the total number of carriers identified. RESULTS: Age at diagnosis ranged from 23 to 80 years with an average age of 50.2 years. In 57 women (24.9%) we detected a pathogenic mutation, with a higher frequency (29.7%) in the group manifesting cancer before 60 years. Deleterious BRCA1 mutations occurred in 14.8% of TNBC patients. These were predominantly recurrent frameshift mutations (24/34, 70.6%). Deleterious BRCA2 mutations occurred in 5.7% of patients, all but one (c.1813dupA) being unique. While no mutations were found in CDH1 and TP53, 10 mutations were detected in one of the six other predisposition genes. Remarkably, neither of the ATM, RAD51D, CHEK2 and PALB2 mutation carriers had a family history. Furthermore, patients with non-BRCA1/2 mutations were not significantly younger than mutation negative women (p = 0.3341). Most importantly, among the 57 mutation carriers, ten (17.5%) would be missed using current clinical testing criteria including five (8%) with BRCA1/2 mutations. CONCLUSIONS: In summary, our data confirm and expand previous studies of a high frequency of germline mutations in genes associated with ineffective repair of DNA damage in women with TNBCs. Neither age of onset, contralateral disease nor family history were able to discern all mutation positive individuals. Therefore, TNBC should be considered as an additional criterion for panel based genetic testing.
EVALuna2:34811

A deep-learning workflow to predict upper tract urothelial carcinoma protein-based subtypes from H&E slides supporting the prioritization of patients for molecular testing - Angeloni, Miriam; van Doeveren, Thomas; Lindner, Sophia; Volland, Patrick; Schmelmer, Jorina; Foersch, Sebastian; Matek, Christian; Stöhr, Robert; Geppert, Carol-Immanuel; Heers, Hendrik; Wach, Sven; Taubert, Helge; et al. (Journal of Pathology: Clinical Research, 2024)
Upper tract urothelial carcinoma (UTUC) is a rare and aggressive, yet understudied, urothelial carcinoma (UC). The more frequent UC of the bladder comprises several molecular subtypes, associated with different targeted therapies and overlapping with protein-based subtypes. However, if and how these findings extend to UTUC remains unclear. Artificial intelligence-based approaches could help elucidate UTUC's biology and extend access to targeted treatments to a wider patient audience. Here, UTUC protein-based subtypes were identified, and a deep-learning (DL) workflow was developed to predict them directly from routine histopathological H&E slides. Protein-based subtypes in a retrospective cohort of 163 invasive tumors were assigned by hierarchical clustering of the immunohistochemical expression of three luminal (FOXA1, GATA3, and CK20) and three basal (CD44, CK5, and CK14) markers. Cluster analysis identified distinctive luminal (N = 80) and basal (N = 42) subtypes. The luminal subtype mostly included pushing, papillary tumors, whereas the basal subtype diffusely infiltrating, non-papillary tumors. DL model building relied on a transfer-learning approach by fine-tuning a pre-trained ResNet50. Classification performance was measured via three-fold repeated cross-validation. A mean area under the receiver operating characteristic curve of 0.83 (95% CI: 0.67–0.99), 0.8 (95% CI: 0.62–0.99), and 0.81 (95% CI: 0.65–0.96) was reached in the three repetitions. High-confidence DL-based predicted subtypes showed significant associations (p < 0.001) with morphological features, i.e. tumor type, histological subtypes, and infiltration type. Furthermore, a significant association was found with programmed cell death ligand 1 (PD-L1) combined positive score (p < 0.001) and FGFR3 mutational status (p = 0.002), with high-confidence basal predictions containing a higher proportion of PD-L1 positive samples and high-confidence luminal predictions a higher proportion of FGFR3-mutated samples. Testing of the DL model on an independent cohort highlighted the importance to accommodate histological subtypes. Taken together, our DL workflow can predict protein-based UTUC subtypes, associated with the presence of targetable alterations, directly from H&E slides.
CRIS-Team Scopus Importer:2024-03-29
Keywords: deep-learning; digital pathology; immunohistochemistry; protein-based subtypes; targeted therapy; upper tract urothelial carcinoma; whole slide images

Adult type granulosa cell tumor of the testis with a heterologous sarcomatous component: case report and review of the literature - Schubert, Thomas E. O.; Stoehr, Robert; Hartmann, Arndt; Schoene, Sabrina; Loebelenz, Mathias; Mikuz, Gregor (Diagnostic Pathology, 2014)
Adult testicular granulosa cell tumors are rare sex cord- stromal tumors of which only 45 have been previously reported. As compared with their ovarian counterparts, these tumors may follow a more aggressive course because the proportion of malignant cases is higher. We report here a unique case of a 78-year Caucasian with a left sided adult type granulosa cell tumor with a heterologous sarcomatous tumor component. A heterologous sarcomatous component has occasionally been observed in ovarian tumors but never in testicular granulosa cell tumors. The sarcomatous component showed a higher number of mitotic figures (1/Hpf) and a marked proliferation rate (up to 50% Ki 67 positive cells) compared with the granulosa type tumor component. CD 99 and the progesterone receptor were positive in both tumor components, inhibin and calretinin only in the granulosa cells, and pancytokeratin only in the sarcomatouse one. Key words: testis - ovary - granulosa cells - sarcoma - inhibin Runing title: testicular sarcomatous granulosa tumor.The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/6959043481207016.
EVALuna2:6605

A gene signature derived from the loss of cdkn1a (P21) is associated with CMS4 colorectal cancer - Bueno-Fortes, Santiago; Muenzner, Julienne K.; Berral-Gonzalez, Alberto; Hampel, Chuanpit; Lindner, Pablo; Berninger, Alexandra; Hübner, Kerstin; Kunze, Philipp; Bäuerle, Tobias; Erlenbach-Wünsch, Katharina; Sánchez-Santos, José Manuel; Hartmann, Arndt; et al. (Cancers, 2022)
The epithelial–mesenchymal transition (EMT) is associated with tumor aggressiveness and increased invasion, migration, metastasis, angiogenesis, and drug resistance. Although the HCT116 p21-/- cell line is well known for its EMT-associated phenotype, with high Vimentin and low E-cadherin protein levels, the gene signature of this rather intermediate EMT-like cell line has not been determined so far. In this work, we present a robust molecular and bioinformatics analysis, to reveal the associated gene expression profile and its correlation with different types of colorectal cancer tumors. We compared the quantitative signature obtained with the NanoString platform with the expression profiles of colorectal cancer (CRC) Consensus Molecular Subtypes (CMS) as identified, and validated the results in a large independent cohort of human tumor samples. The expression signature derived from the p21-/- cells showed consistent and reliable numbers of upregulated and downregulated genes, as evaluated with two machine learning methods against the four CRC subtypes (i.e., CMS1, 2, 3, and 4). High concordance was found between the upregulated gene signature of HCT116 p21-/- cells and the signature of the CMS4 mesenchymal subtype. At the same time, the upregulated gene signature of the native HCT116 cells was similar to that of CMS1. Using a multivariate Cox regression model to analyze the survival data in the CRC tumor cohort, we selected genes that have a predictive risk power (with a significant gene risk incidence score). A set of genes of the mesenchymal signature was proven to be significantly associated with poor survival, specifically in the CMS4 CRC human cohort. We suggest that the gene signature of HCT116 p21-/- cells could be a suitable metric for mechanistic studies regarding the CMS4 signature and its functional consequences in CRC. Moreover, this model could help to discover the molecular mechanisms of intermediate EMT, which is known to be associated with extraordinarily high stemness and drug resistance.
CRIS-Team Scopus Importer:2022-01-14
Keywords: CAM model; CDKN1A; Colorectal cancer; Consensus molecular subtypes (CMS); Epithelial–mesenchymal transition (EMT); HCT116 cells; Intermediate EMT; SNAI2

AGR3 in breast cancer: prognostic impact and suitable serum-based biomarker for early cancer detection - Garczyk, Stefan; Von Stillfried, Saskia; Antonopoulos, Wiebke; Hartmann, Arndt; Schrauder, Michael G.; Fasching, Peter; Anzeneder, Tobias; Tannapfel, Andrea; Ergoenenc, Yavuz; Knuechel, Ruth; Rose, Michael; Dahl, Edgar (PLoS ONE, 2015)
Blood-based early detection of breast cancer has recently gained novel momentum, as liquid biopsy diagnostics is a fast emerging field. In this study, we aimed to identify secreted proteins which are up-regulated both in tumour tissue and serum samples of breast cancer patients compared to normal tissue and sera. Based on two independent tissue cohorts (n = 75 and n = 229) and one serum cohort (n = 80) of human breast cancer and healthy serum samples, we characterised AGR3 as a novel potential biomarker both for breast cancer prognosis and early breast cancer detection from blood. AGR3 expression in breast tumours is significantly associated with oestrogen receptor ? (P<0.001) and lower tumour grade (P<0.01). Interestingly, AGR3 protein expression correlates with unfavourable outcome in low (G1) and intermediate (G2) grade breast tumours (multivariate hazard ratio: 2.186, 95% CI: 1.008-4.740, P<0.05) indicating an independent prognostic impact. In sera analysed by ELISA technique, AGR3 protein concentration was significantly (P<0.001) elevated in samples from breast cancer patients (n = 40, mainly low stage tumours) compared to healthy controls (n = 40). To develop a suitable biomarker panel for early breast cancer detection, we measured AGR2 protein in human serum samples in parallel. The combined AGR3/AGR2 biomarker panel achieved a sensitivity of 64.5% and a specificity of 89.5% as shown by receiver operating characteristic (ROC) curve statistics. Thus our data clearly show the potential usability of AGR3 and AGR2 as biomarkers for blood-based early detection of human breast cancer.
EVALuna2:6803

A humanized mouse identifies the bone marrow as a niche with low therapeutic IgG activity - Lux, Anja; Seeling, Michaela; Baerenwaldt, Anne; Lehmann, Birgit; Schwab, Inessa; Repp, Roland; Meidenbauer, Norbert; Mackensen, Andreas; Hartmann, Arndt; Heidkamp, Gordon Frederik; Dudziak, Diana; Nimmerjahn, Falk (Cell Reports, 2014)
Genetic differences between humans and in vivo model systems, including mice and nonhuman primates, make it difficult to predict the efficacy of immunoglobulin G (IgG) activity in humans and understand the molecular and cellular mechanisms underlying that activity. To bridge this gap, we established a small-animal model system that allowed us to study human IgG effector functions in the context of an intact human immune system without the interference of murine Fc? receptors expressed on mouse innate immune effector cells in vivo. Using a model of B cell depletion with different human IgG variants that recognize CD20, we show that this humanized mouse model can provide unique insights into the mechanism of human IgG activity in vivo. Importantly, these studies identify the bone marrow as a niche with low therapeutic IgG activity.
EVALuna2:6588

ALK Rearrangements Characterize 2 Distinct Types of Salivary Gland Carcinomas Clinicopathologic and Molecular Analysis of 4 Cases and Literature Review - Agaimy, Abbas; Baneckova, Martina; Ihrler, Stephan; Müller, Sarina Katrin; Franchi, Alessandro; Hartmann, Arndt; Stöhr, Robert; Skalova, Alena (American Journal of Surgical Pathology, 2021)
The majority of salivary gland carcinomas are characterized by recurrent gene fusions that proved highly valuable diagnostically, but only rarely of therapeutic impact. Most of these fusion-positive carcinomas belong to the low-grade or intermediategrade biological category. To date, only 5 cases of salivary gland carcinomas carrying an oncogenic ALK fusion have been reported in 4 recent studies, but their phenotypic spectrum and their nosological classification remain uncharacterized. We herein describe in detail the clinicopathologic and molecular features of 4 ALK-fusion-positive salivary carcinomas and review previously reported cases to assess if they could be classified into a defined World Health Organization (WHO) category. Patients were 3 men and 1 woman aged from 67 to 79 years (median: 70 y). All tumors originated in the parotid gland. Their size ranged from 1.1 to 3 cm (mean, 2 cm). Three tumors were de novo high-grade salivary duct carcinomas (SDCs) and 1 was a low-grade intercalated-type intraductal carcinoma. Histologically, high-grade tumors were predominantly solid, composed of intimately admixed basal (CK5+, androgen-) and luminal (CK5-, androgen+) components. The remarkable basal component showed squamoid basophilic pattern imparting an adenosquamous-like appearance in all cases. Conventional apocrine intraductal high-grade carcinoma was noted in 1 case. Prominent intraductal growth of the solid basal component (highlighted by p63 staining) was seen in all cases. The tumor cells expressed CK7 (3/3), mammaglobin (3/3, 1 focal), GATA3 (3/3, 1 focal), variably CK5 (3/3), and focally the androgen receptor (1/3), but lacked expression of HER2/neu, SOX10, MUC4, TTF1, FS100, and Napsin A. The low-grade tumor showed classic histologic and immunophenotypic features of intercalated-type non-invasive intraductal carcinoma. Molecular profiling showed rearrangements involving exon 20 of ALK in all cases, confirmed by ALK immunohistochemistry (IHC and FISH). The fusion partner was EML4 (n= 2) and STRN (n= 1) in high-grade tumors and EML4 in the intraductal carcinoma. Two patients with high-grade tumors developed progressive disease (1 died at 9 mo; 1 alive under palliative therapy at 5 mo). This series and a review of 5 published cases indicate that ALK rearrangements characterize 2 distinct subsets of salivary gland carcinomas in the spectrum of high-grade androgen-poor, basal-like SDC (total reported: 5 cases) and low-grade intercalated-type intraductal carcinomas (4 cases). Given the therapeutic relevance of ALK fusions, inclusion of ALK IHC in any atypical-looking or androgen-poor SDC and in high-grade adenocarcinoma-not otherwise specified is recommended. Absence of aberrant ALK expression in genetically characterized secretory (n= 15) and intraductal (n= 9) carcinomas lacking ALK fusions underlines the value of ALK IHC as a diagnostic screening method for identifying potential cases.
CRIS-Team WoS Importer:2021-08-27

Alterations in key signaling pathways in sinonasal tract melanoma. A molecular genetics and immunohistochemical study of 90 cases and comprehensive review of the literature - Chlopek, Malgorzata; Lasota, Jerzy; Thompson, Lester D. R.; Szczepaniak, Magdalena; Kuzniacka, Alina; Hincza, Kinga; Kubicka, Kamila; Kaczorowski, Maciej; Newford, Michael; Liu, Yalan; Agaimy, Abbas; Biernat, Wojciech; et al. (Modern Pathology, 2022)
Sinonasal mucosal melanoma is a rare tumor arising within the nasal cavity, paranasal sinuses, or nasopharynx (sinonasal tract). This study evaluated 90 cases diagnosed in 29 males and 61 females with median age 68 years. Most tumors involved the nasal cavity and had an epithelioid morphology. Spectrum of research techniques used in this analysis includes targeted-DNA and -RNA next-generation sequencing, Sanger sequencing, fluorescence in situ hybridization and immunohistochemistry. Sinonasal melanomas were commonly driven by RAS (38/90, 42%), especially NRAS (n = 36) mutations and rarely (4/90, 4%) displayed BRAF pathogenic variants. BRAF/RAS mutants were more frequent among paranasal sinuses (10/14, 71%) than nasal (26/64, 41%) tumors. BRAF/RAS-wild type tumors occasionally harbored alterations of the key components and regulators of Ras-MAPK signaling pathway: NF1 mutations (1/17, 6%) or NF1 locus deletions (1/25, 4%), SPRED1 (3/25, 12%), PIK3CA (3/50, 6%), PTEN (4/50, 8%) and mTOR (1/50, 2%) mutations. These mutations often occurred in a mutually exclusive manner. In several tumors some of which were NRAS mutants, TP53 was deleted (6/48, 13%) and/or mutated (5/90, 6%). Variable nuclear accumulation of TP53, mirrored by elevated nuclear MDM2 expression was seen in >50% of cases. Furthermore, sinonasal melanomas (n = 7) including RAS/BRAF-wild type tumors (n = 5) harbored alterations of the key components and regulators of canonical WNT-pathway: APC (4/90, 4%), CTNNB1 (3/90, 3%) and AMER1 (1/90, 1%). Both, TERT promoter mutations (5/53, 9%) and fusions (2/40, 5%) were identified. The latter occurred in BRAF/RAS-wild type tumors. No oncogenic fusion gene transcripts previously reported in cutaneous melanomas were detected. Eight tumors including 7 BRAF/RAS-wild type cases expressed ADCK4::NUMBL cis-fusion transcripts. In summary, this study documented mutational activation of NRAS and other key components and regulators of Ras-MAPK signaling pathway such as SPRED1 in a majority of sinonasal melanomas.
CRIS-Team Scopus Importer:2022-09-02

A multicenter comparison of PD-L1 protein and mRNA expression in urothelial bladder cancer by immunohistochemistry and RT-qPCR (Checkpoint-Typer(C)): A round robin test by the BRIDGE-Consortium Germany - Eckstein, Markus; Wirtz, R.; Pfannstil, C.; Wach, S.; Stoehr, R.; Breyer, J.; Erlmeier, F.; Guenes, C.; Nitschke, K.; Weichert, W.; Otto, W.; Keck, Bastian; et al. (2018)
EVALuna2:34065

A multicenter round robin test of PD-L1 expression assessment in urothelial bladder cancer by immunohistochemistry and RT-qPCR with emphasis on prognosis prediction after radical cystectomy - Eckstein, Markus; Wirtz, Ralph M.; Pfannstil, Carolin; Wach, Sven; Stoehr, Robert; Breyer, Johannes; Erlmeier, Franziska; Günes, Cagatay; Nitschke, Katja; Weichert, Wilko; Otto, Wolfgang; Keck, Bastian; et al. (Oncotarget, 2018)
Background: Immunohistochemical PD-L1 assessment is currently used to identify responders towards checkpoint inhibitors although it is limited by inter-observer effects. Here, we conducted a multi-center round robin test to prove the possibility of assessing the PD-L1 status by gene expression to avoid inter-observer effects. Patients and methods: Gene expression of PD-L1 was analyzed in a total of 294 samples (14 cases non-muscle invasive and muscle-invasive bladder cancer; MIBC) in seven centers by a RT-qPCR kit and compared with immunohistochemical scoring of three pathologists (DAKO, 22c3). Both assays were compared towards prognosis prediction in a cohort of 88 patients with MIBC. Results: PD-L1 gene expression revealed very high inter center correlation (centrally extracted RNA: r = 0.68-0.98, p ≤ 0.0076; locally extracted RNA: r = 0.81-0.98, p ≤ 0.0014). IHC Inter-observer concordance was moderate to substantial for immune cells (IC), fair for combined IC/ tumor cell (TC) (IC: κ = 0.50-0.61; IC + TC: κ = 0.50), and fair for TC scoring (κ = 0.26-0.35). Gene expression assessment resulted in more positive cases (9/14 cases positive vs. 6/14 cases [IHC]) which could be validated in the independent cohort. Positive mRNA status was associated with significantly better overall and disease-specific survival (5-year OS: 50% vs. 26%, p = 0.0042, HR = 0.48; 5 year DSS: 65% vs. 40%, p = 0.012, HR = 0.49). The 1% IHC IC cut-off also revealed significant better OS (5 year OS: 58% vs. 31%, p = 0.036, HR = 0.62). Conclusion: Gene expression showed very high inter-center agreement. Gene expression assessment also resulted in more positive cases and revealed better prognosis prediction. PD-L1 mRNA expression seems to be a reproducible and robust tool for PD-L1 assessment.
EVALuna2:34268

Analysis of androgen receptor mRNA expression in urothelial carcinoma of the bladder - Sikic, D.; Wirtz, R.; Wach, S.; Dyrskjot, L.; Erben, P.; Bolenz, C.; Breyer, J.; Otto, W.; Hoadley, K.; Lerner, S.; Eckstein, Markus; Hartmann, Arndt; et al. (2018)
EVALuna2:34064

Analysis of CXCL9, PD1 and PD-L1 mRNA in stage T1 non-muscle invasive bladder cancer and their association with prognosis - Kubon, Jennifer; Sikic, Danijel; Eckstein, Markus; Weyerer, Veronika; Stöhr, Robert; Neumann, Angela; Keck, Bastian; Wullich, Bernd; Hartmann, Arndt; Wirtz, Ralph M.; Taubert, Helge; Wach, Sven (Cancers, 2020)
Non-muscle invasive bladder cancer (NMIBC), which is characterized by a recurrence rate of approximately 30% and very long treatment times, remains a major unresolved problem for patients and the health care system. The immunological interplay between tumor cells and the immune environment is important for tumor development. Therefore, we analyzed the mRNA of three immune markers, CXCL9, PD1 and PD-L1, in NMIBC by qRT-PCR. The results were subsequently correlated with clinicopathological parameters and prognostic data. Altogether, as expected, higher age was an independent prognostic factor for overall survival (OS) and disease-specific survival (DSS), but not for recurrence-free survival (RFS). Lower CXCL9 mRNA was observed in multivariate Cox’s regression analysis to be an independent prognostic parameter for reduced OS (relative risk; RR = 2.08; p = 0.049), DSS (RR = 4.49; p = 0.006) and RFS (RR = 2.69; p = 0.005). In addition, PD-L1 mRNA was an independent prognostic factor for DSS (RR = 5.02; p = 0.042) and RFS (RR = 2.07; p = 0.044). Moreover, in univariate Cox’s regression analysis, the stratification of patients revealed that low CXCL9 or low PD1 mRNA was associated with reduced RFS in the younger patient group (≤71 years), but not in the older patient group (>71 years). In addition, low CXCL9 or low PD-L1 was associated with shorter RFS in patients with higher tumor cell proliferation and in patients without instillation therapy. In conclusion, the characterization of mRNA levels of immune markers differentiates NIMBC patients with respect to prognosis.
CRIS-Team Scopus Importer:2020-10-09
Keywords: CXCL9; PD-L1; PD1; Prognosis; Stage T1 NMIBC

Analysis of Intraoperative Frozen Pancreatic Resection Margin and Prediction of Postoperative Pancreatic Fistula Risk During Pancreatoduodenectomy - Brunner, Maximilian; Kovacevic, Jasna; Krautz, Christian; Merkel, Susanne; Hartmann, Arndt; Grützmann, Robert; Haller, Florian; Weber, Georg (Journal of the American College of Surgeons, 2022)
BACKGROUND: Pancreatic duct diameter and pancreatic texture are important predictive factors for a postoperative pancreatic fistula (POPF) and are assessed intraoperatively by the surgeon. However, surgical evaluation is arbitrary and difficult to objectify, especially in minimally invasive approaches in pancreatic surgery. STUDY DESIGN: We conducted a retrospective analysis of 275 patients that underwent pancreatoduodenectomy from 2012 to 2019 at our institution. Pancreatic duct diameter and pancreatic fibrosis were assessed by histopathologic examination of the pancreatic resection margin using intraoperative frozen sections and correlated with the occurrence of POPF and clinically relevant POPF (CR-POPF). RESULTS: The POPF and CR-POPF rates were 27% and 19%, respectively. Univariate analysis indicated that the indication for surgery, the surgically determined pancreatic duct diameter, and pancreatic texture, as well as the histopathologically determined pancreatic duct diameter and pancreatic fibrosis were significant predictive factors for POPF and CR-POPF. A multivariate analysis revealed histopathologically determined pancreatic duct diameter and pancreatic fibrosis as independent risk factors for POPF (OR [odds ratio] 2.3 [1.1 to 4.5], p = 0.022 and OR 2.4 [1.1 to 5.1], p = 0.023, respectively) and CR-POPF (OR 2.2 [1.1 to 4.8], p = 0.037 and OR 2.6 [1.1 to 6.1], p = 0.036). CONCLUSIONS: Histopathologically determined pancreatic duct diameter and pancreatic fibrosis are quantitatively measurable independent risk factors for POPF and CR-POPF. An intraoperative objective histopathologic evaluation of these parameters using frozen sections could support the surgical assessment of the pancreatic duct diameter and the pancreatic texture.
CRIS-Team Scopus Importer:2022-04-29

Analysis of the prognostic relevance of sex-steroid hormonal receptor mRNA expression in muscle-invasive urothelial carcinoma of the urinary bladder - Erben, Philipp; Sikic, Danijel; Wirtz, Ralph M.; Martini, Thomas; Weis, Cleo-Aron; Breyer, Johannes; Otto, Wolfgang; Keck, Bastian; Hartmann, Arndt; Bolenz, Christian (Virchows Archiv, 2019)
Muscle-invasive urothelial carcinoma of the urinary bladder (UCB) often recurs following radical cystectomy (RC). An altered expression of sex-steroid hormone receptors has been associated with oncological outcomes of UCB and may represent therapeutic targets. Here the expression of different hormone receptors was measured on mRNA levels in patients treated by RC and associated with outcomes. Androgen receptor (AR), estrogen receptor 1 (ESR1), and progesterone receptor (PGR) mRNA expression was assessed by quantitative reverse transcription polymerase chain reaction (RT-qPCR) in RC samples of 87 patients with a median age of 66 (39-88) years. Univariate and multivariate analyses were performed to test associations with pathological and clinical characteristics as well as recurrence-free (RFS) and disease-specific survival (DSS). AR mRNA expression was lower in comparison with ESR1 and PGR expression (p<0.0001). In univariate analysis, high expression levels of AR were associated with reduced RFS (HR 2.8, p=0.015) and DSS (HR 2.8, p=0.010). High AR mRNA expression and a positive lymph node status were independent predictors for reduced RFS (HR 2.5, p=0.0049) and DSS (HR 3.4, p=0.009). In patients with low AR mRNA expression, an increased ESR1 and PGR mRNA expression were associated with reduced RFS and DSS. High expression levels of AR are significantly associated with adverse outcome in patients with muscle-invasive UCB following RC. ESR1 and PGR expression status can further stratify patients with low AR expression into subgroups with significantly reduced RFS and DSS. Therapeutic targeting of AR may influence outcomes in patients with UCB.
CRIS-Team WoS Importer:2019-02-21

Analytical and inter-observer comparability of 4 clinically developed programmed death-ligand 1 (PD-L1) immunohistochemistry assays in advanced clear cell renal cell carcinoma (CCRCC) - Sommer, Ulrich; Eckstein, Markus; Ammann, Johannes; Braunschweig, Till; Macher-Goeppinger, Stephan; Schwamborn, Kristina; Hieke-Schulz, Stefanie; Wullich, Bernd; Wirth, Manfred; Roth, Wilfried; Knuechel, Ruth; Weichert, Wilko; et al. (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2019-10-22

Anamnese, pathologische Originalbefunde, Therapie bezogene Parameter und Krankheitsverlauf: retrospektive Analyse von klinisch basierten Faktoren für die Prognose des tumorspezifischen Überlebens von 378 Patienten mit pT1-Harnblasenkarzinom - Breyer, J.; Otto, Wolfgang; Hartmann, Arndt; Bumes, B.; Bruendl, J.; Gierth, M.; Bertz, Simone; Denzinger, Stefan; Burger, M.; Lausenmeyer, E. M. (Aktuelle Urologie, 2015)
Urothelial carcinoma of the bladder (UBC) at stage pT1 is a heterogenous disease. Established criteria for prognosis prediction are not suitable for every patient. Choosing the right therapeutic strategy for the individual patient thus remains a challenge. The aim of the present study was to identify clinical parameters regarding cancer-specific survival (CSS) in patients with pT1 UBC.A retrospective analysis of clinical parameters of all patients with a pT1 UBC between 1989 and 2012 from a single centre was performed. Treatment consisted of transurethral resection, second resection followed by initially bladder sparing treatment. Anamnestic data, histopathological reports and clinical course were assessed with CSS being defined as primary endpoint. Kaplan-Meier analysis, uni- and multivariate analysis were performed using SPSS (Version 22, IBM).378 patients (78% male, median age 72 years) were included, median follow-up was 35 months. Pathological stage pT1G3 (66 vs. 91%, p<0.001), lack of instillation therapy (66 vs. 83%, p<0.001), presence of a second malignoma (41 vs. 77%, p=0,004), diagnosis after 2000 (75 vs. 76%, p=0,018) and tumour progress (42 vs. 85%, p<0.001) were associated with a worse CSS in univariate and Kaplan-Meier analysis. Multivariate analysis revealed the presence of a second malignoma (HR 2.267; CI 95% 1.143-4.497, p=0.019), pathological stage pT1G3 at initial diagnosis (HR 4.567; CI 95% 2.040-10.22, p<0.001) and tumour progress (HR 3.742; CI 95% 1.544-9.069, p=0.003) as independent negative predictors of CSS. Instillation therapy was a prognostic factor for improved CSS (HR 0.368; CI 95% 0.212-0.638, p<0.001).The present study identified the presence of a second malignoma, pathological stage pT1G3 and tumour progress as negative predictive factors for CSS. Maintenance instillation therapy after reresection was associated with an improved CSS.
EVALuna2:6722

Androgen Receptor mRNA Expression in Urothelial Carcinoma of the Bladder: A Retrospective Analysis of Two Independent Cohorts - Sikic, Danijel; Wirtz, Ralph M.; Wach, Sven; Dyrskjot, Lars; Erben, Philipp; Bolenz, Christian; Breyer, Johannes; Otte, Wolfgang; Hoadley, Katherine A.; Lerner, Seth P.; Eckstein, Markus; Hartmann, Arndt; et al. (Translational Oncology, 2019)
INTRODUCTION: Gender-specific differences have led to the androgen receptor (AR) being considered a possible factor in the pathophysiology of urothelial carcinoma of the bladder (UCB), but the exact role remains unclear. MATERIALS AND METHODS: The association of AR mRNA expression with clinicopathological features was retrospectively analyzed in two previously described cohorts. The first cohort consisted of 41 patients with all stages of UCB treated at Aarhus University Hospital, Denmark. The second cohort consisted of 323 patients with muscle-invasive bladder cancer (MIBC) accumulated by the Cancer Genome Atlas (TCGA) Research Network. RESULTS: AR mRNA expression is significantly higher in non-muscle-invasive bladder cancer (NMIBC) when compared to MIBC (P = .0004), with no relevant changes within the different stages of MIBC. AR mRNA expression was significantly associated with TCGA molecular subtypes (P < .0001). In the total cohort, there was no association between AR expression and gender (P = .23). When analyzed separately, females showed a significantly worse disease-free (P = .03) and overall survival (P = .02) when expressing AR mRNA above median level, while the same was not observed for men. Multivariable Cox's regression analyses revealed AR mRNA expression to be an independent prognostic marker for disease-free survival in women (P = .007). CONCLUSIONS: AR mRNA expression is significantly higher in NMIBC than in MIBC, while high AR mRNA expression is associated with worse survival in females with MIBC. Further studies need to investigate the gender-specific role of AR in UCB.
CRIS-Team WoS Importer:2019-03-22

An Empirical Survey on the Adaption of Neoadjuvant Chemotherapy in Bladder Cancer - Reike, Moritz J.; Reicherz, Alina; Tully, Karl H.; Bahlburg, Henning; Maas, Moritz; Bach, Peter; Klümper, Niklas; Eckstein, Markus; Hartmann, Arndt; Breyer, Johannes; Erben, Philipp; Bolenz, Christian; et al. (Urologia Internationalis, 2024)
Introduction: The aim of the study was to determine the adaption of neoadjuvant chemotherapy (NAC) in patients with muscle-invasive bladder cancer (MIBC) in Germany, Austria, and Switzerland and especially underlying reasons for potential low adherence to guidelines. Methods: We conducted a non-validated survey among 336 urologic departments in Germany, Austria, and Switzerland. RedCap questionnaires were electronically distributed and included 23 items concerning the general NAC administration standards and guideline compliance in patient counseling regarding the actual treatment. Results: The return rate of the questionnaire was 19.1% (63/336). Although 45 departments (71.4%) claim to perform NAC as the standard of care, only 49% of eligible patients actually receive NAC. An advanced disease stage (>cT3) and a high tumor volume were mentioned to support the application of NAC, whereas 35% of responders worry about deterioration of patients preoperative status due to NAC. Furthermore, 26.7% of respondents are concerned about the low extent of survival benefit. Conclusion: Application of NAC in eligible MIBC patients in Germany, Austria, and Switzerland remains low. Although the majority of urologic departments discuss NAC and acknowledge the need for intensified treatment in advanced disease stages, not all eligible patients will actually receive NAC before radical cystectomy.
CRIS-Team Scopus Importer:2024-06-07
Keywords: Bladder cancer; Empirical study; Germany; Neoadjuvant chemotherapy; Radical cystectomy

An integrated multi-omics analysis identifies prognostic molecular subtypes of non-muscle-invasive bladder cancer - Lindskrog, Sia Viborg; Prip, Frederik; Lamy, Philippe; Taber, Ann; Groeneveld, Clarice S.; Birkenkamp-Demtröder, Karin; Jensen, Jørgen Bjerggaard; Strandgaard, Trine; Nordentoft, Iver; Christensen, Emil; Sokac, Mateo; Birkbak, Nicolai J.; et al. (Nature Communications, 2021)
The molecular landscape in non-muscle-invasive bladder cancer (NMIBC) is characterized by large biological heterogeneity with variable clinical outcomes. Here, we perform an integrative multi-omics analysis of patients diagnosed with NMIBC (n = 834). Transcriptomic analysis identifies four classes (1, 2a, 2b and 3) reflecting tumor biology and disease aggressiveness. Both transcriptome-based subtyping and the level of chromosomal instability provide independent prognostic value beyond established prognostic clinicopathological parameters. High chromosomal instability, p53-pathway disruption and APOBEC-related mutations are significantly associated with transcriptomic class 2a and poor outcome. RNA-derived immune cell infiltration is associated with chromosomally unstable tumors and enriched in class 2b. Spatial proteomics analysis confirms the higher infiltration of class 2b tumors and demonstrates an association between higher immune cell infiltration and lower recurrence rates. Finally, the independent prognostic value of the transcriptomic classes is documented in 1228 validation samples using a single sample classification tool. The classifier provides a framework for biomarker discovery and for optimizing treatment and surveillance in next-generation clinical trials.
CRIS-Team Scopus Importer:2021-04-30

An introduction to the WHO 5th edition 2022 classification of testicular tumours - Berney, Daniel M.; Cree, Ian; Rao, Vishal; Moch, Holger; Srigley, John R.; Tsuzuki, Toyonori; Amin, Mahul B.; Comperat, Eva M.; Hartmann, Arndt; Menon, Santosh; Netto, George J.; Rubin, Mark A.; et al. (Histopathology, 2022)
The 5th edition of the World Health Organisation Blue Book was published recently and includes a comprehensive update on testicular tumours. This builds upon the work of the 4th edition, retaining its structure and main nomenclature, including the use of the term ‘germ cell neoplasia in situ’ (GCNIS) for the pre-invasive lesion of most germ cell tumours and division from those not derived from GCNIS. While there have been important developments in understanding the molecular underpinnings of testicular cancer, this updated classification paradigm and approach remains rooted in morphology. Nomenclature changes include replacement of the term ‘primitive neuroectodermal tumour’ by ‘embryonic neuroectodermal tumour’ based on the non-specificity of the former term and to separate these tumours clearly from Ewing sarcoma. Seminoma is placed in a germinoma family of tumours emphasising relation to those tumours at other sites. Criteria for the diagnosis of ‘teratoma with somatic transformation’ have been modified to not include variable field size assessments. The word ‘carcinoid’ has been changed to ‘neuroendocrine tumour’, with most examples in the testis now classified as ‘prepubertal type testicular neuroendocrine tumour’. For sex cord-stromal tumours, the use of mitotic counts per high-power field has been changed to per mm2 for malignancy assessments, and the new entities, ‘signet ring stromal tumour’ and ‘myoid gonadal stromal tumour’, are defined. Well-differentiated papillary mesothelial tumour has now been defined as tumour type with a favourable prognosis. Sertoliform cystadenoma has been removed as an entity from testicular adnexal tumours and placed with Sertoli cell tumours.
CRIS-Team Scopus Importer:2022-07-08
Keywords: classification; Germ Cell Tumour; teratoma; testis; WHO

An ongoing, randomized phase II study of Nivolumab plus Ipilimumab versus standard of care in previously untreated and advanced non-clear cell renal cell carcinoma (SUNIFORECAST) - Ahrens, M.; Escudier, B.; Haanen, J. B. A. G.; Boleti, E.; Goupil, Gross M.; Grimm, M. O.; Negrier, S.; Barthelemy, P.; Gravis, G.; Ivany, P.; Bedke, J.; Castellano, D.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

A novel grading approach predicts worse outcomes in stage pT1 non-muscle-invasive bladder cancer - Haas, Maximilian; Engelmann, Simon U.; Mayr, Roman; Gossler, Christopher; Pickl, Christoph; Kälble, Sebastian; Yang, Yushan; Otto, Wolfgang; Hartmann, Valerie; Burger, Maximilian; Hartmann, Arndt; Breyer, Johannes; et al. (Bju International, 2024)
Objective: To develop a prognostically relevant scoring system for stage pT1 non-muscle-invasive bladder cancer (NMIBC) incorporating tumour budding, growth pattern and invasion pattern because the World Health Organisation grading system shows limited prognostic value in such patients. Patients and Methods: The tissue specimens and clinical data of 113 patients with stage pT1 NMIBC who underwent transurethral resection of bladder tumour were retrospectively investigated. Tumour budding, and growth and invasion patterns were evaluated and categorised into two grade groups (GGs). GGs and other clinical and histopathological variables were investigated regarding recurrence-free survival (RFS), progression-free survival (PFS), cancer-specific survival (CSS) and overall survival (OS) using univariable and multivariable Cox regression analyses. Results: The integration of two tumour budding groups, two growth patterns, and two invasion patterns yielded an unfavourable GG (n = 28; 24.7%) that had a high impact on oncological outcomes. The unfavourable GG was identified as an independent RFS and OS predictor (P = 0.004 and P = 0.046, respectively) and linked to worse PFS (P = 0.001) and CSS (P = 0.001), irrespective of the European Association of Urology risk group. The unfavourable GG was associated with higher rates of BCG-unresponsive tumours (P = 0.006). Study limitations include the retrospective, single-centre design, diverse therapies and small cohort. Conclusions: We present a morphology-based grading system for stage pT1 NMIBC that correlates with disease aggressiveness and oncological patient outcomes. It therefore identifies a highest risk group of stage pT1 NMIBC patients, who should be followed up more intensively or receive immediate radical cystectomy. The grading incorporates objective variables assessable on haematoxylin and eosin slides and immunohistochemistry, enabling an easy-to-use low-cost approach that is applicable in daily routine. Further studies are needed to validate and confirm these results.
CRIS-Team Scopus Importer:2024-03-15
Keywords: bladder cancer; EMT; grade group; NMIBC; tumour budding

A Novel Grading System Based on Tumor Budding and Cell Nest Size Is a Strong Predictor of Patient Outcome in Esophageal Squamous Cell Carcinoma - Jesinghaus, Moritz; Boxberg, Melanie; Konukiewitz, Bjoern; Slotta-Huspenina, Julia; Schlitter, Anna M.; Steiger, Katja; Specht, Katja; Wieczorek, Kathrin; Warth, Arne; Schmidt, Thomas; Hartmann, Arndt; Demir, Ihsan E.; et al. (American Journal of Surgical Pathology, 2017)
The determination of prognosis in patients with esophageal squamous cell carcinoma (ESCC) is primarily based on staging according to the TNM-classification, whereas conventional grading is of minor clinical importance because of its deficiencies in prognostic patient stratification. Recently, a novel, highly prognostic grading scheme based on budding activity and cell nest size has been proposed for squamous cell carcinoma (SCC) of both pulmonary as well as oral origin. In order to investigate the utility and transferability of this approach to ESCC, we evaluated budding activity and cell nest size, as well as other histomorphologic characteristics, in a cohort of 135 primarily resected tumors and correlated the results with clinicopathologic and outcome parameters. High budding activity and small cell nest size showed a strong association with reduced overall, disease-specific, and disease-free survival (P<0.001, respectively) in ESCC. The combination of both markers in a 3-step grading system showed excellent prognostic separation of well-differentiated (G1), moderately differentiated (G2), and poorly differentiated (G3) carcinomas (P<0.001). The hazard ratio for disease-free survival in multivariate analysis under inclusion of stage was 2.97 for G2 and 5.42 for G3 ESCC (P<0.001). World Health Organization-based grading had no prognostic impact. Taken together, our data prove the value of tumor budding and cell nest size as excellent outcome predictors in ESCC and validate the utility of a previously established grading scheme proposed for oral and pulmonary SCC in this tumor entity. Ultimately, these combined efforts may result in a universal grading system for SCC regardless of the site of origin.
EVALuna2:6868

A novel molecular signature identifies mixed subtypes in renal cell carcinoma with poor prognosis and independent response to immunotherapy - Buettner, Florian A.; Winter, Stefan; Stuehler, Viktoria; Rausch, Steffen; Hennenlotter, Joerg; Füssel, Susanne; Zastrow, Stefan; Meinhardt, Matthias; Toma, Marieta; Jeronimo, Carmen; Henrique, Rui; Miranda-Goncalves, Vera; et al. (Genome Medicine, 2022)
Background: Renal cell carcinoma (RCC) is a heterogeneous disease comprising histologically defined subtypes. For therapy selection, precise subtype identification and individualized prognosis are mandatory, but currently limited. Our aim was to refine subtyping and outcome prediction across main subtypes, assuming that a tumor is composed of molecular features present in distinct pathological subtypes.
CRIS-Team WoS Importer:2022-09-23

Anthocyanins Prevent Colorectal Cancer Development in a Mouse Model - Lippert, Elisabeth; Ruemmele, Petra; Obermeier, Florian; Goelder, Stefan; Kunst, Claudia; Rogler, Gerhard; Dunger, Nadja; Messmann, Helmut; Hartmann, Arndt; Endlicher, Esther (Digestion, 2017)
Colorectal cancer is the main leading cause of cancer-related deaths worldwide. Present data suggest that plant-derived anthocyanins have anti-inflammatory and chemopreventive properties. This study was aimed at evaluating the effect of an anthocyanin-rich extract from bilberries on colorectal tumour development and growth in the administration of azoxymethan (AOM)/dextran sodium sulfate (DSS) mouse model.Colonic carcinogenesis was induced by AOM and DSS 3 or 5%, respectively, in 50 female Balb/c mice. Mice received either normal food (controls) or a diet containing either 10 or 1% anthocyanin-rich bilberry extract. Colonoscopy took place at week 4 and 9 after initiation of carcinogenesis. After termination at week 9, colon samples were analysed macroscopically and microscopically.Mice receiving 10% anthocyanins showed significantly (p < 0.004) less reduced colon length (12.1 cm [8.5-14.4 cm]) as compared to controls (11.2 cm [9.8-12.3]) indicating less inflammation. Mice fed with 10% anthocyanin-rich extract revealed significantly less mean tumour numbers (n = 1.2) compared to control (n = 14) and anthocyanin 1% treated mice (n = 10.6, p < 0.001).Anthocyanins prevented the formation and growth of colorectal cancer in AOM/DSS-treated Balb/c mice. Further studies should investigate the mechanisms of how anthocyanins influence the development of colorectal cancer.
EVALuna2:6869

Anti-DNA-IgM Favors the Detection of NET-Associated Extracellular DNA - Wang, Han; Stehr, Antonia; Singh, Jeeshan; Zlatar, Leticija; Hartmann, Arndt; Evert, Katja; Naschberger, Elisabeth; Von Stillfried, Saskia; Boor, Peter; Munoz, Luis Enrique; Knopf, Jasmin; Stürzl, Michael; et al. (International Journal of Molecular Sciences, 2023)
During inflammatory responses, neutrophils enter the sites of attack where they execute various defense mechanisms. They (I) phagocytose microorganisms, (II) degranulate to release cytokines, (III) recruit various immune cells by cell-type specific chemokines, (IV) secrete anti-microbials including lactoferrin, lysozyme, defensins and reactive oxygen species, and (V) release DNA as neutrophil extracellular traps (NETs). The latter originates from mitochondria as well as from decondensed nuclei. This is easily detected in cultured cells by staining of DNA with specific dyes. However, in tissues sections the very high fluorescence signals emitted from the condensed nuclear DNA hamper the detection of the widespread, extranuclear DNA of the NETs. In contrast, when we employ anti-DNA-IgM antibodies, they are unable to penetrate deep into the tightly packed DNA of the nucleus, and we observe a robust signal for the extended DNA patches of the NETs. To validate anti-DNA-IgM, we additionally stained the sections for the NET-markers histone H2B, myeloperoxidase, citrullinated histone H3, and neutrophil elastase. Altogether, we have described a fast one-step procedure for the detection of NETs in tissue sections, which provides new perspectives to characterize neutrophil-associated immune reactions in disease.
CRIS-Team Scopus Importer:2023-03-10
Keywords: anti-DNA-IgM; extracellular DNA; NETs

Anti-TNF alpha/azathioprine therapy modulates the Natural killer cell compartment in pediatric inflammatory bowel disease - Knieling, Ferdinand; Schnell, Alexander; Allabauer, I.; Schwarz, B.; Rechenauer, Tobias; Kaspar, S.; Siebenlist, G.; Rueckel, A.; Hartmann, Arndt; Wahlbuhl-Becker, Mandy; Hoerning, A. (EUROPEAN JOURNAL OF IMMUNOLOGY, 2019)
CRIS-Team WoS Importer:2019-10-08

A partial epithelial-mesenchymal transition signature for highly aggressive colorectal cancer cells that survive under nutrient restriction - Pastorino, Gil; Sheraj, Ilir; Hübner, Kerstin; Ferrero, Giulio; Kunze, Philipp; Hartmann, Arndt; Hampel, Chuanpit; Husnugil, Hepsen Hazal; Maiuthed, Arnatchai; Gebhart, Florian; Schlattmann, Fynn; Gulec Taskiran, Aliye Ezgi; et al. (Journal of Pathology, 2024)
Partial epithelial-mesenchymal transition (p-EMT) has recently been identified as a hybrid state consisting of cells with both epithelial and mesenchymal characteristics and is associated with the migration, metastasis, and chemoresistance of cancer cells. Here, we describe the induction of p-EMT in starved colorectal cancer (CRC) cells and identify a p-EMT gene signature that can predict prognosis. Functional characterisation of starvation-induced p-EMT in HCT116, DLD1, and HT29 cells showed changes in proliferation, morphology, and drug sensitivity, supported by in vivo studies using the chorioallantoic membrane model. An EMT-specific quantitative polymerase chain reaction (qPCR) array was used to screen for deregulated genes, leading to the establishment of an in silico gene signature that was correlated with poor disease-free survival in CRC patients along with the CRC consensus molecular subtype CMS4. Among the significantly deregulated p-EMT genes, a triple-gene signature consisting of SERPINE1, SOX10, and epidermal growth factor receptor (EGFR) was identified. Starvation-induced p-EMT was characterised by increased migratory potential and chemoresistance, as well as E-cadherin processing and internalisation. Both gene signature and E-cadherin alterations could be reversed by the proteasomal inhibitor MG132. Spatially resolving EGFR expression with high-resolution immunofluorescence imaging identified a proliferation stop in starved CRC cells caused by EGFR internalisation. In conclusion, we have gained insight into a previously undiscovered EMT mechanism that may become relevant when tumour cells are under nutrient stress, as seen in early stages of metastasis. Targeting this process of tumour cell dissemination might help to prevent EMT and overcome drug resistance. © 2024 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.
CRIS-Team Scopus Importer:2024-01-26
Keywords: consensus molecular subtype 4; E-cadherin processing; EGFR internalisation; intermediate EMT; partial EMT; prognosis; proteasome; starvation

A Pleomorphic Puzzle: Heterogeneous Pulmonary Vascular Occlusions in Patients with COVID-19 - Singh, Jeeshan; Herrmann, Irmgard; Mahajan, Aparna; Schauer, Christine; Shan, Xiaomei; Hartmann, Arndt; Rieker, Ralf; Evert, Katja; Falkeis, Christina; Naschberger, Elisabeth; von Stillfried, Saskia; Boor, Peter; et al. (International Journal of Molecular Sciences, 2022)
Vascular occlusions in patients with coronavirus diseases 2019 (COVID-19) have been frequently reported in severe outcomes mainly due to a dysregulation of neutrophils mediating neutrophil extracellular trap (NET) formation. Lung specimens from patients with COVID-19 have previously shown a dynamic morphology, categorized into three types of pleomorphic occurrence based on histological findings in this study. These vascular occlusions in lung specimens were also detected using native endogenous fluorescence or NEF in a label-free method. The three types of vascular occlusions exhibit morphology of DNA rich neutrophil elastase (NE) poor (type I), NE rich DNA poor (type II), and DNA and NE rich (type III) cohort of eleven patients with six males and five females. Age and gender have been presented in this study as influencing variables linking the occurrence of several occlusions with pleomorphic contents within a patient specimen and amongst them. This study reports the categorization of pleomorphic occlusions in patients with COVID-19 and the detection of these occlusions in a label-free method utilizing NEF.
CRIS-Team Scopus Importer:2022-12-23
Keywords: age; COVID-19; gender; immunothrombosis; native endogenous fluorescence; occlusions; pleomorphism; SARS-CoV-2

A Possible Distinct Molecular Subtype (Quintuple-Wildtype) of Metastatic Colorectal Cancer in First-Line Anti-EGFR Therapy with Cetuximab Plus FOLFIRI - Palliative Precision Therapy and a Multidisciplinary Treatment Approach: Interim Analysis of the IVOPAK II Trial with Early Results - Wein, Axel; Stöhr, Robert; Kersting, Stephan; Siebler, Jürgen; Merkel, Susanne; Busse, Daniel; Wolff, Kerstin; Ostermeier, Nicola; Neufert, Clemens; Vitali, Francesco; Eckstein, Markus; Roth, Jan-Peter; et al. (Oncology, 2021)
Objective: The study aimed to prospectively evaluate a new molecular biomarker panel (KRAS, NRAS, BRAF, PIK3CA, and ERBB2) for palliative first-line treatment of colorectal cancer (CRC), including a multidisciplinary treatment approach. The rate of secondary metastasis resections was assessed. Patients and Methods: A total of 40 patients with definitively nonresectable metastatic CRC were enrolled from 10 centers before the interim analysis (June 2019) of the IVOPAK II trial (Interdisciplinary Care with Quality Control in Palliative Treatment of Colorectal Cancer). After determination of 5 molecular biomarkers in the tumor (KRAS, exons 2-4; NRAS, exons 2-4; BRAF V600E; PIK3CA; and ERBB2), patients in the IVOPAK II study received FOLFIRI plus cetuximab for all-RAS/quintuple-wildtype disease and FOLFIRI plus bevacizumab in the case of RAS mutations. The current article presents the early description of the clinical outcome of the interim analysis of IVOPAK II comparing the all-RAS/quintuple-wildtype and RAS-mutations populations, including a multidisciplinary-treated case report of a quintuple-wildtype patient. Results: The quintuple-wildtype population treated with FOLFIRI plus cetuximab in first-line exhibited a significantly higher response rate and enhanced early tumor shrinkage in the interim analysis than the RAS-mutations population, as well as a high rate of secondary metastatic resections. Conclusion: Initial results of this new biomarker panel (quintuple-wildtype) are promising for anti-EGFR therapy with cetuximab plus doublet chemotherapy (FOLFIRI) in first-line treatment of metastatic CRC. These results warrant confirmation with higher case numbers in the IVOPAK II trial.
CRIS-Team WoS Importer:2021-11-05

A prediction model for pathological complete response after neoadjuvant chemotherapy of HER2-negative breast cancer patients - Häberle, Lothar; Erber, Ramona; Gaß, Paul; Hein, Alexander; Jud, Sebastian; Langemann, Hanna; Rauh, C.; Hack, Caroline; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; Beckmann, Matthias; Lux, Michael P.; et al. (ANNALS OF ONCOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-08

A prospective, open-label, multicenter, randomized phase II trial: Sequential therapy with BEvacizumab, RAd001 (Everolimus) and AxiTinib in metastatic renal cell carcinoma (mRCC) (BERAT study of the IAG-N) - Hilser, Thomas; Gruenwald, Viktor; Bergmann, Lothar; Goebell, Peter; Strauss, Arne; Meiler, Johannes; Hartmann, Arndt; Ivanyi, Philipp; Bedke, Jens (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

A Prospectivly Randomized Phase-II Trial of Axitinib versus Everolimus as Second-Line Therapy in Metastatic Renal Cell Carcinoma (BERAT Study) - Grünwald, Viktor; Hilser, Thomas; Meiler, Johannes; Goebell, Peter; Ivanyi, Philipp; Strauss, Arne; Hartmann, Arndt; Bedke, Jens; Bergmann, Lothar (Oncology Research and Treatment, 2022)
Introduction: Inhibition of neo-angiogenesis is a cornerstone of medical treatment in metastatic renal cell carcinoma (mRCC). While 1st line therapies were previously dominated by inhibitors of the vascular endothelial growth factor axis, 2nd line options were less clearly defined. We investigated the role of everolimus (EVE) or a tyrosine kinase inhibitor (TKI) in 2nd line treatment of mRCC patients. Methods: Key inclusion criteria were measurable mRCC, ECOG 0-1, IMDC risk: good or intermediate and adequate organ function. Patients who progressed on or were intolerant to bevacizumab + interferon were subject for randomization between TKI and EVE treatment. Cross-over occurred at time of progression during 2nd line treatment. Improvement of 2nd line progression-free survival (PFS) rate (PFR) at 6 months from 50% to 65% was the primary endpoint. Secondary endpoints were PFS, total PFS, objective response rate (ORR), overall survival (OS), safety, and patient reported outcomes. Results: In 2012-2015, a total of 22 patients were included. The study was stopped for poor accrual. Ten patients (46%) were randomized to receive 2nd line treatment with EVE (n = 5) or axitinib (n = 4)/sunitinib (n = 1). ECOG 0 was recorded in 20% (EVE) and 60% (TKI). Severe adverse events occurred in approx. 60% in each arm. ORR was 1/5 (20%) for TKI and 0/5 (0%) for EVE. PFR at 6 months was 20% in each arm. Median PFS was 3.7 months (EVE) and 2.2 months (TKI) (hazard ratio [HR] 1.0 [95% confidence interval [CI]: 0.26-3.85]). The OS was comparable between arms HR 1.12 (95% CI: 0.27-4.61). Conclusion: The rapid change of the treatment landscape, the limited use of bevacizumab and interferon in 1st line and the duration of 1st line treatment jeopardized BERAT trial recruitment. The small number of patients is a major limitation of our trial. Our observation indicated the poor prognosis in progressive patients and the limited efficacy of TKI or mTOR inhibitors in 2nd line treatment.
CRIS-Team Scopus Importer:2022-06-10
Keywords: Axitinib; Bevacizumab; Everolimus; Interferon alpha; Metastatic renal cell carcinoma

Aquaporin 3 Expression Loss in Urothelial Carcinoma: Association with Tumor Invasion Depth, but not with Grading? - Breyer, Johannes; Otto, Wolfgang; Burger, Maximilian; Hartmann, Arndt; Rubenwolf, Peter C. (Bladder Cancer, 2017)
We have previously provided molecular evidence of expression of aquaporin 3 (AQP3) in normal human urothelium and in UBC of various stages. Whereas former studies demonstrated that loss of AQP3 was associated with invasive and high-grade disease and worse progression-free and cancer-specific survival, this report investigates the expression of AQP3 in associated CIS. Contrary to what we had expected, all CIS specimens were shown to exhibit strong AQP3 expression, suggesting loss of AQP3 in UBC is primarily associated with the ability of tumor cells for invasion but not with grading as sign of dedifferentiation.
EVALuna2:34251

A randomised phase II study of Nivolumab plus Ipilimumab versus Standard of care in previously untreated and advanced non-clear cell renal cell carcinoma (SUNIFORECAST) - Ahrens, M.; Scheich, S.; Goekbuget, N.; Boleti, E.; Gruenwald, V.; Escudier, B.; Goebell, Peter; Gschwend, J.; Hartmann, Arndt; Miller, K.; Burkholder, I.; Schmidinger, M.; et al. (2018)
EVALuna2:35902

A Randomized Phase IIa Trial with Temsirolimus versus Sunitinib in Advanced Non-Clear Cell Renal Cell Carcinoma: An Intergroup Study of the CESAR Central European Society for Anticancer Drug Research-EWIV and the Interdisciplinary Working Group on Renal Cell Cancer (IAGN) of the German Cancer Society - Bergmann, Lothar; Grünwald, Viktor; Maute, Luise; Grimm, Marc Oliver; Weikert, Steffen; Schleicher, Jan; Klotz, Theodor; Greiner, Jochen; Flörcken, Anne; Hartmann, Arndt; Gauler, Thomas (Oncology Research and Treatment, 2020)
Background: Non-clear cell renal cell cancers (nccRCC) are rare entities, and the optimal therapy in metastatic disease has still to be defined. Methods: In this small prospectively randomized phase IIa multicenter trial, we investigated temsirolimus (TEM) versus sunitinib (SUN) as first-line therapy in patients with metastatic nccRCC. The patients were randomized 1:1 to either TEM in a dose of 25 mg i.v. once a week or SUN with 50 mg p.o. daily for 4 weeks on and 2 weeks off. Primary endpoint was progression-free survival (PFS). In total, 22 patients were included with predominantly papillary RCC (16/22) followed by chromophobe RCC and others. Results: The male to female ratio was 16:6. The tumor control rate (CR + PR + SD) was 58% for TEM and 90% for SUN-treated patients. There was also a trend for improved PFS with 9.3 versus 13.2 months (HR 1.64; 95% CI 0.65-4.18) in favor of SUN. There was no trend for overall survival. Conclusions: Despite this trial had to be terminated earlier due to low recruitment, the results match the other studies published so far with the mTOR inhibitor everolimus and SUN, which show a trend in favor of SUN for ORR and PFS.
CRIS-Team Scopus Importer:2020-07-10

A Randomized Phase II Study of Nivolumab Plus Ipilimumab Versus Standard of Care in Previously Untreated and Advanced Non-Clear Cell Renal Cell Carcinoma (Suniforecast) - Ahrens, Marit; Escudier, Bernard; Boleti, Ekaterini; Grimm, Marc-Oliver; Goupir, Marine Gross; Barthelemy, Pilippe; Gravis, Gwenaelle; Bedekes, Jens; Ivanyi, Philipp; Panic, Andrej; Zschaebitz, Stefanie; Neyrieru, Sylvie; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

A randomized phase II trial of ipilimumab and nivolumab versus standard of care in previously untreated and advanced non-clear cell renal cell carcinoma (SUNNIFORECAST) - Ahrens, M.; Escudier, B.; Haanen, J.; Gross-Goupil, M.; Boleti, E.; Gravis, G.; Grimm, M. -O.; Negrier, S.; Bedke, J.; Barthelemy, P.; Castellano, D.; Mellado, B.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Arginase expression impedes the resolution of intestinal inflammation by altering the fecal microbiome and the metabolome - Baier, Julia; Gänsbauer, Maximilian; Giessler, Claudia; Arnold, Harald; Muske, Mercedes; Schleicher, Ulrike; Lukassen, Sören; Ekici, Arif Bülent; Rauh, Manfred; Daniel, Christoph; Hartmann, Arndt; Schmid, Benjamin; et al. (Journal of Clinical Investigation, 2020)
Arginase 1 (Arg1), which converts L-arginine into ornithine and urea, exerts pleiotropic immunoregulatory effects. However, the function of Arg1 in inflammatory bowel disease (IBD) remains poorly characterized. Here, we found that Arg1 expression correlated with the degree of inflammation in intestinal tissues from IBD patients. In mice, Arg1 was upregulated in an IL-4-/IL-13- and intestinal microbiota-dependent manner. Tie2-Cre+/-Arg1fl/fl mice lacking Arg1 in hematopoietic and endothelial cells recovered faster from experimental colitis than Arg1-expressing littermates. This correlated with decreased vessel density, compositional changes in intestinal microbiota, diminished infiltration by myeloid cells and an accumulation of intraluminal polyamines that promote epithelial healing. The pro-resolving effect of Arg1-deletion was reduced by an L-arginine-free diet, but rescued by simultaneous deletion of other L-arginine-metabolizing enzymes such as Arg2 or Nos2, demonstrating that protection from colitis requires L-arginine. Fecal microbiota transfers from Tie2-Cre+/-Arg1fl/fl mice into wild-type recipients ameliorated intestinal inflammation while transfers from wild-type littermates into Arg1-deficient mice prevented an advanced recovery from colitis. Thus, an increased availability of L-arginine as well as altered intestinal microbiota and metabolic products account for the accelerated resolution from colitis in the absence of Arg1. Consequently, the metabolism of L-arginine may serve as target for clinical intervention in IBD patients.<br

Assessment of PD-L1 Status in Urothelial Cancer - Bahlinger, Veronika; Hartmann, Arndt; Eckstein, Markus (Urothelial Carcinoma - Methods and Protocols, 2023)
Since 2016, the immunotherapeutic agents targeting PD-1 and PD-L1 are an integral part in first-line and second-line treatment of advanced or metastatic urothelial cancer. By PD-1 and PD-L1 inhibition with these drugs, the immune system is supposed to regain the capacity to actively kill cancer cells. Meanwhile, PD-L1 assessment is prescribed for patients not being eligible for platinum-based chemotherapy in first-line settings in metastatic disease (for monotherapy with atezolizumab or pembrolizumab) and for patients who are intended to receive adjuvant nivolumab treatment following radical cystectomy. Several challenges which are highlighted in this chapter affect PD-L1 testing in daily routine including availability of representative tissue materials, inter-observer variability, and different available PD-L1 immunohistochemistry assays with different analytical properties.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Distinct algorithms; PD-L1 assessment; Urothelial carcinoma

Assessment of prognostic and predictive value of FGFR alterations (FGFRa) in a real-world cohort of patients (pts) with high-risk pT1 non-muscle-invasive bladder cancer (NMIBC) - Breyer, J.; Monga, M.; Mayr, R.; Otto, W.; Burger, M.; Eckstein, Markus; Stöhr, Robert; Erben, P.; Bolenz, C.; Eidt, S.; Sundaram, R.; Baig, M.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-10-30

Assessment of the additional clinical potential of X-ray dark-field imaging for breast cancer in a preclinical setup - Emons, J.; Fasching, Peter; Wunderle, M.; Heindl, F.; Rieger, Jens; Horn, Florian; Pelzer, Georg; Ritter, André; Weber, Thomas; Radicke, M.; Polifka, Iris; Wachter, David Lukas; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Assessment of the additional clinical potential of X-ray dark-field imaging for breast cancer in a preclinical setup - Emons, Julius; Fasching, Peter; Wunderle, Marius; Heindl, Felix; Rieger, Jens; Horn, Florian; Pelzer, Georg; Ritter, André; Weber, Thomas; Radicke, Marcus; Polifka, Iris; Wachter, David; et al. (Therapeutic Advances in Medical Oncology, 2020)
Background: Mammography can identify calcifications up to 50–100 μm in size as a surrogate parameter for breast cancer or ductal carcinoma in situ (DCIS). Microcalcifications measuring <50 µm are also associated with breast cancer or DCIS and are frequently not detected on mammography, although they can be detected with dark-field imaging. This study examined whether additional breast examination using X-ray dark-field imaging can increase the detection rate of calcifications. Advances in knowledge: (1) evaluation of additional modality of breast imaging; (2) specific evaluation of breast calcifications. Implications for patient care: the addition of X-ray dark-field imaging to conventional mammography could detect additional calcifications. Methods: Talbot–Lau X-ray phase–contrast imaging and X-ray dark-field imaging were used to acquire images of breast specimens. The radiation dosage with the technique is comparable with conventional mammography. Three X-ray gratings with periods of 5–10 µm between the X-ray tube and the flat-panel detector provide three different images in a single sequence: the conventional attenuation image, differential phase image, and dark-field image. The images were read by radiologists. Radiological findings were marked and examined pathologically. The results were described in a descriptive manner. Results: A total of 81 breast specimens were investigated with the two methods; 199 significant structures were processed pathologically, consisting of 123 benign and 76 malignant lesions (DCIS or invasive breast cancer). X-ray dark-field imaging identified 15 additional histologically confirmed carcinoma lesions that were visible but not declared suspicious on digital mammography alone. Another four malignant lesions that were not visible on mammography were exclusively detected with X-ray dark-field imaging. Conclusions: Adding X-ray dark-field imaging to digital mammography increases the detection rate for breast cancer and DCIS associated lesions with micrometer-sized calcifications. The use of X-ray dark-field imaging may be able to provide more accurate and detailed radiological classification of suspicious breast lesions. Adding X-ray dark-field imaging to mammography may be able to increase the detection rate and improve preoperative planning in deciding between mastectomy or breast-conserving therapy, particularly in patients with invasive lobular breast cancer.
CRIS-Team Scopus Importer:2020-09-25
Keywords: breast cancer; interferometry; mammography; microcalcifications

Association between breast cancer risk factors and molecular type in postmenopausal patients with hormone receptor-positive early breast cancer - Wunderle, Marius; Pretscher, Jutta; Brucker, Sara Y.; Volz, Bernhard; Hartmann, Arndt; Fießler, Cornelia; Hein, Alexander; Häberle, Lothar; Jud, Sebastian; Lux, Michael P.; Janni, Wolfgang; Löhberg, Christian; et al. (Breast Cancer Research and Treatment, 2019)
PurposeEvidence shows that genetic and non-genetic risk factors for breast cancer (BC) differ relative to the molecular subtype. This analysis aimed to investigate associations between epidemiological risk factors and immunohistochemical subtypes in a cohort of postmenopausal, hormone receptor-positive BC patients.MethodsThe prospective, single-arm, multicenter phase IV PreFace study (Evaluation of Predictive Factors Regarding the Effectivity of Aromatase Inhibitor Therapy) included 3529 postmenopausal patients with hormone receptor-positive early BC. Data on their epidemiological risk factors were obtained from patients' diaries and their medical histories. Data on estrogen receptor, progesterone receptor, and HER2 receptor status were obtained from pathology reports. Patients with incomplete information were excluded. Data were analyzed using conditional inference regression analysis, analysis of variance, and the chi-squared test.ResultsIn a cohort of 3392 patients, the strongest association with the molecular subtypes of BC was found for hormone replacement therapy (HRT) before diagnosis of early BC. The analysis showed that patients who took HRT at diagnosis had luminal A-like BC more often (83.7%) than those who had never taken HRT or had stopped taking it (75.5%). Luminal B-like BC and HER2-positive BC were diagnosed more often in women who had never taken HRT or had stopped taking it (13.3% and 11.2%, respectively) than in women who were taking HRT at diagnosis of BC (8.3% and 8.0%, respectively).ConclusionsThis analysis shows an association between HRT and the distribution of molecular subtypes of BC. However, no associations between other factors (e.g., age at diagnosis, body mass index, smoking status, age at menopause, number of deliveries, age at first delivery, breastfeeding history, or family history) were noted.
CRIS-Team WoS Importer:2019-03-29

Association between mammographic density and pregnancies relative to age and BMI: a breast cancer case-only analysis - Hack, Carolin; Emons, Julius; Jud, Sebastian; Heusinger, Katharina; Adler, Werner; Gaß, Paul; Haeberle, Lothar; Heindl, Felix; Hein, Alexander; Schulz-Wendtland, Rüdiger; Uder, Michael; Hartmann, Arndt; et al. (Breast Cancer Research and Treatment, 2017)
Percentage mammographic density (PMD) is a major risk factor for breast cancer (BC). It is strongly associated with body mass index (BMI) and age, which are themselves risk factors for breast cancer. This analysis investigated the association between the number of full-term pregnancies and PMD in different subgroups relative to age and BMI.Patients were identified in the breast cancer database of the University Breast Center for Franconia. A total of 2410 patients were identified, for whom information on parity, age, and BMI, and a mammogram from the time of first diagnosis were available for assessing PMD. Linear regression analyses were conducted to investigate the influence on PMD of the number of full-term pregnancies (FTPs), age, BMI, and interaction terms between them.As in previous studies, age, number of FTPs, and BMI were found to be associated with PMD in the expected direction. However, including the respective interaction terms improved the prediction of PMD even further. Specifically, the association between PMD and the number of FTPs differed in young patients under the age of 45 (mean decrease of 0.37 PMD units per pregnancy) from the association in older age groups (mean decrease between 2.29 and 2.39 PMD units). BMI did not alter the association between PMD and the number of FTPs.The effect of pregnancies on mammographic density does not appear to become apparent before the age of menopause. The mechanism that drives the effect of pregnancies on mammographic density appears to be counter-regulated by other influences on mammographic density in younger patients.
EVALuna2:14710

Association of germline genetic variants with breast cancer-specific survival in patient subgroups defined by clinic-pathological variables related to tumor biology and type of systemic treatment - Morra, Anna; Escala-Garcia, Maria; Beesley, Jonathan; Keeman, Renske; Canisius, Sander; Ahearn, Thomas U.; Andrulis, Irene L.; Anton-Culver, Hoda; Arndt, Volker; Auer, Paul L.; Augustinsson, Annelie; Freeman, Laura E. Beane; et al. (BREAST CANCER RES, 2021)
Background Given the high heterogeneity among breast tumors, associations between common germline genetic variants and survival that may exist within specific subgroups could go undetected in an unstratified set of breast cancer patients. Methods We performed genome-wide association analyses within 15 subgroups of breast cancer patients based on prognostic factors, including hormone receptors, tumor grade, age, and type of systemic treatment. Analyses were based on 91,686 female patients of European ancestry from the Breast Cancer Association Consortium, including 7531 breast cancer-specific deaths over a median follow-up of 8.1 years. Cox regression was used to assess associations of common germline variants with 15-year and 5-year breast cancer-specific survival. We assessed the probability of these associations being true positives via the Bayesian false discovery probability (BFDP < 0.15). Results Evidence of associations with breast cancer-specific survival was observed in three patient subgroups, with variant rs5934618 in patients with grade 3 tumors (15-year-hazard ratio (HR) [95% confidence interval (CI)] 1.32 [1.20, 1.45], P = 1.4E-08, BFDP = 0.01, per G allele); variant rs4679741 in patients with ER-positive tumors treated with endocrine therapy (15-year-HR [95% CI] 1.18 [1.11, 1.26], P = 1.6E-07, BFDP = 0.09, per G allele); variants rs1106333 (15-year-HR [95% CI] 1.68 [1.39,2.03], P = 5.6E-08, BFDP = 0.12, per A allele) and rs78754389 (5-year-HR [95% CI] 1.79 [1.46,2.20], P = 1.7E-08, BFDP = 0.07, per A allele), in patients with ER-negative tumors treated with chemotherapy. Conclusions We found evidence of four loci associated with breast cancer-specific survival within three patient subgroups. There was limited evidence for the existence of associations in other patient subgroups. However, the power for many subgroups is limited due to the low number of events. Even so, our results suggest that the impact of common germline genetic variants on breast cancer-specific survival might be limited.
CRIS-Team WoS Importer:2021-09-03

Association of KRT20 and KRT5 with response to neoadjuvant chemotherapy in patients diagnosed with muscle invasive bladder cancer - Roghmann, Florian; Reike, Moritz; Wirtz, Ralph; Kriegmair, Maximilian; Erben, Philipp; Tully, Karl; Weyerer, Veronika; Eckstein, Markus; Hartmann, Arndt; Wezel, Felix; Bolenz, Christian; Tannapfel, Andrea; et al. (JOURNAL OF CLINICAL ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-05-22

Association of molecular subtypes with breast cancer risk factors: a case-only analysis - Rauh, Claudia; Gaß, Paul; Heusinger, Katharina; Haeberle, Lothar; Jud, Sebastian; Hein, Alexander; Löhberg, Christian; Lux, Michael P.; Wachter, David; Heimrich, Jutta; Strehl, Johanna D.; Haller, Florian; et al. (European Journal of Cancer Prevention, 2015)
As breast cancer (BC) screening identifies many BCs with a good prognosis, which might be overdiagnosed and therefore overtreated, the identification of subgroups with a high risk for aggressive subtypes might be helpful. The aim of this case-case analysis was to investigate the association between epidemiological risk factors and molecular subtypes in a cohort of BC patients. Epidemiological risk factors for 2587 BC patients were obtained using a structured questionnaire and from the patients' charts. The histopathological information (estrogen and progesterone receptor, HER2 and Ki-67) used in the analysis was retrieved from the original pathology reports. Analyses using conditional inference regression trees were carried out on these data. The strongest influence factor on the distribution of the molecular subtypes was age at first diagnosis of BC. An influence of BMI was also identified in patients aged either more than 42 years or 49.6 years or less. Older patients aged more than 49.6 years and perimenopausal women with a BMI of 32.4 kg/m or less were most likely to develop luminal A-like BC. Young patients aged 42 years or less and perimenopausal patients with a BMI more than 32.4 kg/m more often developed triple-negative BC. The study confirmed that age at diagnosis is an important factor influencing the distribution of molecular subtypes. In the perimenopausal group, it may be postulated that BMI plays a critical role in the pathogenesis of BC, defining a subgroup that is more likely to develop triple-negative BC or luminal B-like disease and another group in which there is a more postmenopausal distribution pattern.
EVALuna2:5482

Association of Plane of Total Mesorectal Excision With Prognosis of Rectal Cancer: Secondary Analysis of the CAO/ARO/AIO-04 Phase 3 Randomized Clinical Trial - Kitz, Julia; Fokas, Emmanouil; Beissbarth, Tim; Stroebel, Philipp; Wittekind, Christian; Hartmann, Arndt; Rueschoff, Josef; Papadopoulos, Thomas; Roesler, Elisabeth; Ortloff-Kittredge, Peter; Kania, Ulrich; Schlitt, Hans; et al. (JAMA Surgery, 2018)
Importance: Previous retrospective studies have shown that surgical quality affects local control in rectal cancer.. Objective: In this secondary end point analysis, we evaluated the prognostic effect of the total mesorectal excision (TME) plane in the CAO/ARO/AIO-04 phase 3 randomized clinical trial. Design, Setting, and Participants: The CAO/ARO/AIO-04 trial enrolled 1236 patients with cT3-4 and/or node-positive rectal adenocarcinoma from 88 centers in Germany between July 25, 2006, and February 26, 2010. Interventions: Patients were randomized to receive treatment with standard fluorouracil-based preoperative chemoradiotherapy (CRT) alone (control arm) or oxaliplatin (experimental arm) followed by TME and adjuvant chemotherapy. Main Outcomes and Measures: The TME quality (mesorectal, intramesorectal, and muscularis propria plane) was prospectively assessed in 1152 operation specimens. An assessment was performed independently by pathologists and surgeons. The results were correlated with clinicopathologic data and the clinical outcome was tested, including multivariable analysis with the Cox regression model. Results: Of 1152 German Caucasian participants, 332 (28.8) were women and the mean age was 63 years. The plane of TME was mesorectal in 930 patients (80.7%), intramesorectal in 169 (14.7%), and muscularis propria in 53 (4.6%). In a univariable analysis, the TME plane was significantly associated with 3-year disease-free survival (mesorectal vs intramesorectal vs muscularis propria, 95% CI, 73.1-78.8 vs 61.6-76.0 vs 55.6-81.3, respectively; P = .01), cumulative incidence of local and distant recurrences (mesorectal vs intramesorectal vs muscularis propria, 95% CI, 2.0-4.5 vs 1.2-8.1 vs 2.5-20.5, respectively; P < .001; and mesorectal vs intramesorectal vs muscularis propria, 95% CI, 17.0-22.4 vs 18.3-32.0 vs 14.2-39.0, respectively; P = .03, respectively), and overall survival (mesorectal vs intramesorectal vs muscularis propria, 95% CI, 88.3-92.3 vs 79.7-91.0 vs 81.6-98.7, respectively; P = .02). In contrast to the pathologist-based evaluation, the assessment of TME plane by the operating surgeon failed to demonstrate prognostic significance for any of these clinical end points. In a multivariable analysis, the plane of surgery (mesorectal vs muscularis propria TME) constituted an independent factor for local recurrence (P = .002). Conclusions and Relevance: This phase 3 randomized clinical trial confirms the long-term clinical effect of TME plane quality on local recurrence, as initially reported in the MRC CR07 study. The data highlight the key role of pathologists and surgeons in the multidisciplinary management of rectal cancer. Trial Registration: ClinicalTrials.gov Identifier: NCT00349076.
EVALuna2:34814

Associations of TACSTD2/TROP2 and NECTIN-4/NECTIN-4 with molecular subtypes, PD-L1 expression, and FGFR3 mutational status in two advanced urothelial bladder cancer cohorts - Bahlinger, Veronika; Branz, Annalena; Strissel, Pamela; Strick, Reiner; Lange, Fabienne; Geppert, Carol-Immanuel; Klümper, Niklas; Hölzel, Michael; Wach, Sven; Taubert, Helge; Sikic, Danijel; Wullich, Bernd; et al. (Histopathology, 2024)
Aims: Treatment options for advanced urothelial carcinoma (aUC) rapidly evolved: besides immunomodulative therapeutic options and inhibitors targeting Fibroblast growth factor receptor (FGFR) alterations, two new antibody-drug conjugates (ADC), sacituzumab govitecan (SG) and enfortumab vedotin (EV), have been approved. However, little is known about the associations of specific aUC properties and the surface target expression of TROP2 and NECTIN-4. Our aim was to characterize associations of TACSTD2/TROP2 and NECTIN-4/NECTIN-4 protein and gene expression with morphomolecular and clinicopathological characteristics of aUC in two large independent cohorts. Methods and results: The TCGA BLCA (n = 405) and the CCC-EMN (n = 247) cohorts were retrospectively analysed. TROP2/TACSTD2 and NECTIN-4/NECTIN-4 are highly expressed at the protein and transcript level in aUC, and their expression status did not correlate with patient survival in both cohorts. NECTIN-4/NECTIN-4 expression was higher in luminal tumours and reduced in squamous aUCs. NECTIN-4 was negative in 10.6% of samples, and 18.4% of samples had low expression (H-score <15). The TROP2 negativity rate amounted to 6.5%. TACSTD2 and NECTIN-4 expression was reduced in neuroendocrine-like and/or protein-based double-negative tumours. TROP2- and NECTIN-4-negative tumours included one sarcomatoid and four neuroendocrine aUC. FGFR3 alterations and PD-L1 expression on tumour and immune cells did not associate with TROP2 or NECTIN-4 expression. Conclusions: TACSTD2/TROP2 and NECTIN-4/NECTIN-4 are widely expressed in aUC, independent of FGFR3 alterations or PD-L1 expression, thus representing a suitable target for ADC treatment in the majority of aUC. The expression loss was associated with aggressive morphomolecular aUC subtypes, i.e. neuroendocrine(-like) and sarcomatoid aUC.
CRIS-Team Scopus Importer:2024-01-19
Keywords: Advanced urothelial carcinoma; membranous expression; NECTIN-4/NECTIN-4; TACSTD2/TROP2; treatment options

A Standard Mammography Unit - Standard 3D Ultrasound Probe Fusion Prototype: First Results - Schulz-Wendtland, Rüdiger; Jud, Sebastian; Fasching, Peter; Hartmann, Arndt; Radicke, Marcus; Rauh, Claudia; Uder, Michael; Wunderle, Marius; Gaß, Paul; Langemann, Hanna; Beckmann, Matthias; Emons, Julius (Geburtshilfe und Frauenheilkunde, 2017)
The combination of different imaging modalities through the use of fusion devices promises significant diagnostic improvement for breast pathology. The aim of this study was to evaluate image quality and clinical feasibility of a prototype fusion device (fusion prototype) constructed from a standard tomosynthesis mammography unit and a standard 3D ultrasound probe using a new method of breast compression.Imaging was performed on 5 mastectomy specimens from patients with confirmed DCIS or invasive carcinoma (BI-RADS ((TM)) 6). For the preclinical fusion prototype an ABVS system ultrasound probe from an Acuson S2000 was integrated into a MAMMOMAT Inspiration (both Siemens Healthcare Ltd) and, with the aid of a newly developed compression plate, digital mammogram and automated 3D ultrasound images were obtained.The quality of digital mammogram images produced by the fusion prototype was comparable to those produced using conventional compression. The newly developed compression plate did not influence the applied x-ray dose. The method was not more labour intensive or time-consuming than conventional mammography. From the technical perspective, fusion of the two modalities was achievable.In this study, using only a few mastectomy specimens, the fusion of an automated 3D ultrasound machine with a standard mammography unit delivered images of comparable quality to conventional mammography. The device allows simultaneous ultrasound - the second important imaging modality in complementary breast diagnostics - without increasing examination time or requiring additional staff.
EVALuna2:6849

Asymmetric Omphalopagus in a Triplet after In Vitro Fertilization: A Rare Case of Conjoined Twinning - Jabari, Samir; Carbon, Roman; Besendörfer, Manuel; Hartmann, Arndt; Rompel, Oliver; Hoerning, Andre; Söder, Stephan (Case Reports in Pediatrics, 2018)
Introduction: Asymmetric omphalopagus is a rare situation of conjoined twinning, in which a grossly defective twin is attached to the thorax and upper abdomen of the main twin. We describe a case of an asymmetric omphalopagus accompanied by a normal triplet after assisted reproductive technology (ART) and tried to further characterize the all aspects of the conjoined twins. Case Presentation: Perioperative diagnostic imaging was carried out followed by an autopsy to evaluate all aspects of the parasite accompanied by histological, immunohistochemical, and molecular biological evaluation. The parasite had well-developed lower extremities as well as upper extremities with a cleft hand syndrome. The sex was nondeterminable, but DNA fingerprinting revealed that both parasite and autosite are monozygotic, so are females. There was no sign of any axial skeleton or central nervous system. We found a rudimentary rectum with a nonpervious anus, a kidney, ureter, urinary bladder, and a blind-ending urethra. The blood supply of the parasite was connected to the vessel system of the autosite. Conclusions: To our knowledge, only two cases of parasitic omphalopagus after ART have been described to date. Altogether, 52 cases have been reported, and in most of them, the parasites were successfully separated.
EVALuna2:34614

ATF2 loss promotes 5-FU resistance in colon cancer cells via activation of the ATR-Chk1 damage response pathway - Yang, Hao; Hübner, Kerstin; Hampel, Chuanpit; Erlenbach-Wünsch, Katharina; Selvamani, Selva Babu; Shukla, Vikas; Geppert, Carol-Immanuel; Hartmann, Arndt; Mahadevan, Vijayalakshmi; Schneider-Stock, Regine (BMC Cancer, 2023)
Background: The role of ATF2 in colon cancer (CC) is controversial. Recently, we reported that low ATF2 expression is characteristic of highly invasive tumors, suggesting that ATF2 might also be involved in therapy resistance. 5-Fluorouracil (5-FU) is the best-known chemotherapeutic drug for CC, but drug resistance affects its curative effect. To date, the role of ATF2 in the 5-FU response remains elusive. Methods/Results: For our study, we had available HCT116 cells (wild-type p53) and HT29 colon tumor cells (mutant p53) and their corresponding CRISPR‒Cas9-generated ATF2-KO clones. We observed that loss of ATF2 triggered dose- and time-dependent 5-FU resistance in HCT116 cells by activating the DNA damage response (DDR) pathway with high p-ATRThr1989 and p-Chk1Ser317 levels accompanied by an increase in the DNA damage marker γ-H2AX in vitro and in vivo using the chicken chorioallantoic membrane (CAM) model. Chk1 inhibitor studies causally displayed the link between DDR and drug resistance. There were contradictory findings in HT29 ATF2-KO cells upon 5-FU exposure with low p-Chk1Ser317 levels, strong apoptosis induction, but no effects on DNA damage. In ATF2-silenced HCT116 p53−/− cells, 5-FU did not activate the DDR pathway. Co-immunoprecipitation and proximity ligation assays revealed that upon 5-FU treatment, ATF2 binds to ATR to prevent Chk1 phosphorylation. Indeed, in silico modelling showed reduced ATR-Chk1 binding when ATF2 was docked into the complex. Conclusions: We demonstrated a novel ATF2 scaffold function involved in the DDR pathway. ATF2-negative cells are highly resistant due to effective ATR/Chk1 DNA damage repair. Mutant p53 seems to overwrite the tumor suppressor function of ATF2.
CRIS-Team Scopus Importer:2023-06-30
Keywords: ATR kinase; CAM model; DDR; DNA repair; γ-H2AX

ATF2 loss promotes tumor invasion in colorectal cancer cells via upregulation of cancer driver TROP2 - Hübner, Kerstin; Erlenbach-Wünsch, Katharina; Prochazka, Jan; Sheraj, Ilir; Hampel, Chuanpit; Mrazkova, Blanka; Michalcikova, Tereza; Tureckova, Jolana; Iatsiuk, Veronika; Weissmann, Anne; Ferrazzi, Fulvia; Kunze, Philipp; et al. (Cellular and Molecular Life Sciences, 2022)
In cancer, the activating transcription factor 2 (ATF2) has pleiotropic functions in cellular responses to growth stimuli, damage, or inflammation. Due to only limited studies, the significance of ATF2 in colorectal cancer (CRC) is not well understood. We report that low ATF2 levels correlated with worse prognosis and tumor aggressiveness in CRC patients. NanoString gene expression and ChIP analysis confirmed trophoblast cell surface antigen 2 (TROP2) as a novel inhibitory ATF2 target gene. This inverse correlation was further observed in primary human tumor tissues. Immunostainings revealed that high intratumoral heterogeneity for ATF2 and TROP2 expression was sustained also in liver metastasis. Mechanistically, our in vitro data of CRISPR/Cas9-generated ATF2 knockout (KO) clones revealed that high TROP2 levels were critical for cell de-adhesion and increased cell migration without triggering EMT. TROP2 was enriched in filopodia and displaced Paxillin from adherens junctions. In vivo imaging, micro-computer tomography, and immunostainings verified that an ATF2(KO)/TROP2(high) status triggered tumor invasiveness in in vivo mouse and chicken xenograft models. In silico analysis provided direct support that ATF2(low)/TROP2(high) expression status defined high-risk CRC patients. Finally, our data demonstrate that ATF2 acts as a tumor suppressor by inhibiting the cancer driver TROP2. Therapeutic TROP2 targeting might prevent particularly the first steps in metastasis, i.e., the de-adhesion and invasion of colon cancer cells.
CRIS-Team WoS Importer:2022-07-29

A three-gene methylation marker panel for the nodal metastatic risk assessment of muscle-invasive bladder cancer - Stubendorff, Beatrice; Wilhelm, Kerstin; Posselt, Kathleen; Catto, James; Hartmann, Arndt; Bertz, Simone; Fuessel, Susanne; Novotny, Vladimir; Toma, Marieta; Gajda, Mieczyslaw; Lehmann, Jan; Wunderlich, Heiko; et al. (Journal of Cancer Research and Clinical Oncology, 2019)
PurposeIn this study, we aimed to identify a DNA methylation pattern suitable for prognosis assessment of muscle-invasive bladder cancer and to investigate metastasis-associated processes regulated by DNA methylation.MethodsGenome-wide methylation analysis was performed on 23 muscle-invasive bladder tumors by microarray analysis. Validation was performed by the qAMP technique in two different patient cohorts (n=32 and n=100). mRNA expression was analyzed in 12 samples. Protein expression was determined using tissue microarrays of 291 patients. Bladder cancer cell lines T24 and 253JB-V were used for functional analyses.ResultsMicroarray analyses revealed KISS1R, SEPT9 and CSAD as putative biomarkers with hypermethylation in node-positive tumors. The combination of the three genes predicted the metastatic risk with sensitivity of 73% and specificity of 71% in cohort 1, and sensitivity of 82% and specificity of 54% in cohort 2. mRNA expression differences were detected for KISS1R (p=0.04). Protein expression of KISS1R was significantly reduced (p<0.001). Knockdown of SEPT9v3 resulted in increased cell migration by 28% (p=0.04) and increased invasion by 22% (p=0.004). KISS1R overexpression resulted in decreased cell migration (25%, p=0.1).ConclusionsWe identified a methylation marker panel suitable to differentiate between patients with positive and negative lymph nodes at time of cystectomy. This enables a risk assessment for patients who potentially benefit from extended lymph node resection as well as from neoadjuvant chemotherapy and could improve the survival rates. Furthermore, we examined the impact of putative markers on tumor behavior. Hence, KISS1R and SEPT9 could represent a starting point for the development of novel therapy approaches.
CRIS-Team WoS Importer:2019-04-12

A TNM-Immune (TNM-I) classification staging system for predicting survival in colon cancer in a multicenter international SITC study - Mlecnik, B.; Bifulco, C.; Marliot, F.; Lugli, A.; Nagtegaal, I.; Hartmann, Arndt; Van Den Eynde, M.; Roehrl, M.; Ohashi, P.; Zavadova, E.; Torigoe, T.; Patel, P.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-08-28

A tribute to Prof. Ondrej Hes, MD, PhD (1968-2022) - Alaghehbandan, Reza; Agaimy, Abbas; Ali, Leila; Alvarado-Cabrero, Isabel; Amin, Mahul B.; Boudova, Ludmila; Calio, Anna; Comperat, Eva M.; Damjanov, Ivan; Daum, Ondrej; Farcas, Mihaela; Gatalica, Zoran; et al. (Modern Pathology, 2022)
CRIS-Team Scopus Importer:2022-12-30

Autologous regulatory T-cell transfer in refractory ulcerative colitis with concomitant primary sclerosing cholangitis - Voskens, Caroline; Stoica, Diane; Rosenberg, Marita; Vitali, Francesco; Zundler, Sebastian; Ganslmayer, Marion; Knott, Heike; Wiesinger, Manuel; Wunder, Jutta; Kummer, Mirko; Siegmund, Britta; Schnoy, Elisabeth; et al. (Gut, 2022)
Objective Ulcerative colitis (UC) is a chronic, debilitating immune-mediated disease driven by disturbed mucosal homeostasis, with an excess of intestinal effector T cells and an insufficient expansion of mucosal regulatory T cells (Tregs). We here report on the successful adoptive transfer of autologous, ex vivo expanded Tregs in a patient with refractory UC and associated primary sclerosing cholangitis (PSC), for which effective therapy is currently not available.
CRIS-Team WoS Importer:2022-04-29

Automatic Detection of Tumor Buds in Pan-Cytokeratin Stained Colorectal Cancer Sections by a Hybrid Image Analysis Approach - Bergler, Matthias; Benz, Michaela; Rauber, David; Hartmann, David; Kötter, Malte; Eckstein, Markus; Schneider-Stock, Regine; Hartmann, Arndt; Merkel, Susanne; Bruns, Volker; Wittenberg, Thomas; Geppert, Carol-Immanuel (Digital Pathology, 2019)
This contribution introduces a novel approach to the automatic detection of tumor buds in a digitalized pan-cytokeratin stained colorectal cancer slide. Tumor buds are representing an invasive pattern and are frequently investigated as a new diagnostic factor for measuring the aggressiveness of colorectal cancer. However, counting the number of buds under the microscope in a high power field by eyeballing is a strenuous, lengthy and error-prone task, whereas an automated solution could save time for the pathologists and enhance reproducibility. We propose a new hybrid method that consists of two steps. First possible tumor bud candidates are detected using a chain of classical image processing methods. Afterwards a convolutional deep neural network is applied to filter and reduce the number of false positive candidates detected in the first step. By comparing the automatically detected buds with a gold standard created by manual annotations, we gain a score of 0.977 for precision and 0.934 for sensitivity in our test sets on over 8.000 tumor buds.

Back to the roots - dermatology in ancient Egyptian medicine - Hartmann, Arndt (Journal der Deutschen Dermatologischen Gesellschaft, 2016)
Although ancient Greek and Roman medicine is generally considered the origin of European medicine, there is evidence in ancient Egyptian texts suggesting a precursor role of ancient Egyptian medicine in this regard. What did Greek and Roman physicians learn from their Egyptian counterparts? Of the medical papyri discovered to date, the largest and most significant - the Ebers papyrus and the Smith papyrus - originate from the beginning of the New Kingdom, however, they were - at least in part - already written during the Old Kingdom. Considering the times, the spectrum of diseases treated as well as the range of conservative and surgical treatment methods was truly astounding. Taking a medical history, performing a thorough manual examination, and assessing clinical findings constituted key components in establishing a diagnosis. Apart from hygienic aspects, skin and hair disorders, the treatment of acute and chronic wounds and injuries as well as cosmetic procedures took on an important role. Even back then, physicians sought to assess inflammatory processes with respect to their cardinal features, implement graded wound therapy, and treat diseases with allopathic drugs. The 'channel theory' prevalent at that time, in which the unimpeded flow of bodily fluids was considered a fundamental prerequisite for health, may likely be regarded as precursor of ancient Greek humoral pathology. The latter became the basis for the subsequently established theory of the four humors, and was thus essential for the entire field of medieval medicine.
EVALuna:33697

BAP1 Loss is a Useful Adjunct to Distinguish Malignant Mesothelioma Including the Adenomatoid-like Variant From Benign Adenomatoid Tumors - Erber, Ramona; Warth, Arne; Muley, Thomas; Hartmann, Arndt; Herpel, Esther; Agaimy, Abbas (Applied Immunohistochemistry & Molecular Morphology, 2020)
Malignant mesothelioma (MM) can show areas closely mimicking reactive mesothelial proliferations or recapitulating benign adenomatoid tumors (ATs) making distinction on occasion impossible on morphologic ground alone, particularly in limited biopsy material. Recently, loss of BAP1 by immunohistochemistry (IHC) has been suggested as a potential marker for identifying MM, but data is still limited. We studied 264 MM cases (257 using tissue microarrays; 7 on conventional slides) and 42 genital ATs for BAP1 immunohistochemical expression. Loss of BAP1 protein expression was observed in 119/211 of MM cases (56.4%). Taken by histologic type, 64.3% of biphasic, 55.4% of epithelioid, and 41.7% of sarcomatoid MM were BAP1-deficient. In contrast, all 42 ATs showed retained BAP1 immunoreactivity. Notably, all 4 MM cases with variable adenomatoid-like features were BAP1-deficient. Surface components of MM of the pleura showed concordant loss as the invasive tumor suggesting a potential role for BAP1 loss for recognizing so-called early mesothelioma. In conclusion, BAP1 loss demonstrated by IHC is seen in more than half of MM cases but none of ATs. Thus, BAP1 IHC represents a potential adjunct for distinguishing MM from benign mesothelial proliferations including in particular "MM with bland adenomatoid-like pattern versus benign ATs" on biopsy material and early mesothelioma with limited invasion.
CRIS-Team WoS Importer:2020-01-07

BDNF is associated with SFRP1 expression in luminal and basal-like breast cancer cell lines and primary breast cancer tissues: a novel role in tumor suppression? - Huth, Laura; Rose, Michael; Kloubert, Veronika; Winkens, Wiebke; Schlensog, Martin; Hartmann, Arndt; Knuechel, Ruth; Dahl, Edgar (PLoS ONE, 2014)
Secreted frizzled related protein 1 (SFRP1) functions as an important inhibitor of the Wnt pathway and is a known tumor suppressor gene, which is epigenetically silenced in a variety of tumors e.g. in breast cancer. However, it is still unclear how SFRP1 exactly affects the Wnt pathway. Our aim was to decipher SFRP1 involvement in biochemical signaling in dependency of different breast cancer subtypes and to identify novel SFRP1-regulated genes. We generated SFRP1 over-expressing in vitro breast cancer models, reflecting the two major subtypes by using basal-like BT20 and luminal-like HER2-positive SKBR3 cells. DNA microarray expression profiling of these models revealed that SFRP1 expression potentially modulates Bone morphogenetic protein- and Smoothened signaling (p<0.01), in addition to the known impact on Wnt signaling. Importantly, further statistical analysis revealed that in dependency of the cancer subtype model SFRP1 may affect the canonical and non-canonical Wnt pathway (p<0.01), respectively. While SFRP1 re-expression generally mediated distinct patterns of transcriptionally induced or repressed genes in BT20 and SKBR3 cells, brain derived neurotrophic factor (BDNF) was identified as a SFRP1 induced gene in both cell lines. Although BDNF has been postulated as a putative oncogene, the co-regulation with SFRP1 indicates a potential suppressive function in breast cancer. Indeed, a positive correlation between SFRP1 and BDNF protein expression could be shown (p<0.001) in primary breast cancer samples. Moreover, TCGA dataset based analysis clearly underscores that BDNF mRNA is down-regulated in primary breast cancer samples predicting a poor prognosis of these patients. In line, we functionally provide evidence that stable BDNF re-expression in basal-like BT20 breast cancer cells blocks tumor cell proliferation. Hence, our results suggest that BDNF might rather mediate suppressive than promoting function in human breast cancer whose mode of action should be addressed in future studies.
EVALuna2:6675

Bedeutung von HPV-Status und p16 für die Prognose des Peniskarzinoms - Mink, Jan Niklas; Khalmurzaev, Oybek; Pryalukhin, Alexey; Hölters, Sebastian; Geppert, Carol-Immanuel; Lohse, Stefan; Bende, Kristóf; Lobo, João; Henrique, Rui; Loertzer, Hagen; Steffens, Joachim; Jerónimo, Carmen; et al. (Aktuelle Urologie, 2023)
BACKGROUND: Penile cancer is a rare but often lethal tumour disease, especially in the metastatic stage. Most data on prognostic factors for penile cancer are based on small patient cohorts, and even meta-analyses are mostly limited in terms of patient numbers. There is a lack of sufficient parameters to predict the metastatic risk of these tumours. Furthermore, the role of the HPV status for the prognosis, and, in this regard, of p16INK4a is still unclear. MATERIAL AND METHODS: In this study, 236 patients from an international multicentre cohort were analysed with regard to histological subtypes, HPV and p16 status, and other clinical parameters. The HPV status was only graded as HPV-positive if HPV was detected by PCR and the p16 status defined by immunochemistry was positive. The statistical analysis was carried out using the Kaplan-Meier method as well as the log-rank test and a univariable and multivariable analysis using the Cox regression model. RESULTS: A positive HPV status was not a significant parameter for either metastasis-free (MFS), tumour-specific (CSS) or overall survival (OS). p16-positive tumours showed a significantly better MFS (p=0.026), which was also confirmed in the subgroup analysis of HPV-negative tumours (p=0.037) without differences in CSS or OS. In the usual type, there was also a trend towards an improved MFS, but without statistical significance (p=0.070). p16-positive tumours were associated with a highly significantly better MFS (hazard ratio 0.3; p=0.004) in the multivariable Cox regression, while patients with a pT1b tumour stage or advanced lymph node metastasis showed a significantly worse survival. In the multivariable analysis of HPV-negative tumours, p16 status was also confirmed as an independent predictor of MFS (Hazard ratio 0.2; p=0.007). CONCLUSION: HPV status alone seems to be lacking prognostic relevance. In contrast, p16 status was confirmed as an independent prognostic factor. Thus, the expression of p16INK4a is associated with a significantly better MFS. Especially in HPV-negative tumours, the p16 status should be evaluated with regard to the prognostic value and thus also with a view to the treatment decision.
CRIS-Team Scopus Importer:2023-08-11

Bericht zur Late-Breaking Session Pathologie und COVID-19 - Boor, P.; Hartmann, Arndt (Pathologe, 2020)
This paper briefly summarizes the late-breaking session “Pathology and COVID-19” that took place at the virtual congress of the German Society of Pathology on June 6, 2020. The lectures tackled a broad variety of aspects, including the German Registry for COVID-19 autopsies (DeRegCOVID), the detection methods of SARS-CoV‑2 in pathological material, the typical lung findings in severe COVID-19 cases, the distinct (micro)vascular changes and the cardiac and gastrointestinal involvement in COVID-19. In summary, in this first scientific meeting in German pathology on the COVID-19 pandemic, it became clear that pathologists in Germany, Austria and Switzerland have reacted very quickly to the pandemic and have established an autopsy program that has led to medically highly relevant findings.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Autopsy registry; Detection methods; Diffuse alveolar damage; SARS-CoV‑2; Thrombi

Beta-HCG elevation as first sign of a malignant somatic transformation of a non-seminomatous germ cell tumor - Peuser, Moritz; Hartmann, Arndt; Schmidt, Daniela; Mackensen, Andreas; Meidenbauer, Norbert (ONCOLOGY RESEARCH AND TREATMENT, 2021)
CRIS-Team WoS Importer:2022-03-25

BiasCorrector: Fast and accurate correction of all types of experimental biases in quantitative DNA methylation data derived by different technologies - Kapsner, Lorenz; Zavgorodnij, Mikhail G.; Majorova, Svetlana P.; Hotz-Wagenblatt, Agnes; Kolychev, Oleg V.; Lebedev, Igor N.; Hoheisel, Jörg D.; Hartmann, Arndt; Bauer, Andrea; Mate, Sebastian; Prokosch, Hans-Ulrich; Haller, Florian; et al. (International Journal of Cancer, 2021)
Quantification of DNA methylation in neoplastic cells is crucial both from mechanistic and diagnostic perspectives. However, such measurements are prone to different experimental biases. Polymerase chain reaction (PCR) bias results in an unequal recovery of methylated and unmethylated alleles at the sample preparation step. Post-PCR biases get introduced additionally by the readout processes. Correcting the biases is more practicable than optimising experimental conditions, as demonstrated previously. However, utilisation of our earlier developed algorithm strongly necessitates automation. Here, we present two R packages: rBiasCorrection, the core algorithms to correct biases; and BiasCorrector, its web-based graphical user interface frontend. The software detects and analyses experimental biases in calibration DNA samples at a single base resolution by using cubic polynomial and hyperbolic regression. The correction coefficients from the best regression type are employed to compensate for the bias. Three common technologies—bisulphite pyrosequencing, next-generation sequencing and oligonucleotide microarrays—were used to comprehensively test BiasCorrector. We demonstrate the accuracy of BiasCorrector's performance and reveal technology-specific PCR- and post-PCR biases. BiasCorrector effectively eliminates biases regardless of their nature, locus, the number of interrogated methylation sites and the detection method, thus representing a user-friendly tool for producing accurate epigenetic results.
CRIS-Team Scopus Importer:2021-06-04
Keywords: BiasCorrector; cancer; DNA methylation; PCR-bias; post-PCR bias

Biofabrication of 3D Alginate-Based Hydrogel for Cancer Research: Comparison of Cell Spreading, Viability, and Adhesion Characteristics of Colorectal HCT116 Tumor Cells - Ivanovska, Jelena; Zehnder, Tobias; Lennert, Pablo; Sarker, Bapi; Boccaccini, Aldo R.; Hartmann, Arndt; Schneider-Stock, Regine; Detsch, Rainer (Tissue Engineering - Part C: Methods, 2016)
Hydrogels are an important class of biomaterials as they could mimic the extracellular matrix (ECM). Among the naturally occurring biopolymers, alginate and gelatin are extensively used for many biomedical applications. For developing biofabrication constructs as three-dimensional (3D) cell culture models, realistic imaging of cell spreading and proliferation inside the hydrogels represents a major challenge. Therefore, we aimed to establish a system that can mimic the structural architecture, composition, and biological functions of the ECM for cancer research approaches. For this, we compared the cell behavior of human colon cancer HCT116 cells in two biofabricated hydrogels as follows: pure alginate and cross-linked alginate-gelatin (ADA-GEL) matrixes. Our data indicate that cells from the ADA-GEL matrix showed highest proliferation and cellular networks through the material. Analyzing the mRNA expression of several integrins of cells cultured inside of the matrix, we showed that mRNA expression of integrin subunits differed based on the cell focal adhesion characteristics. Furthermore, we showed that recultured ADA-GEL immobilized cells do not differ from parental HCT116 cells regarding migration and proliferation capabilities. Comparing adhesion and other phenotypic characteristics of HCT116 tumor cells, we suggest that ADA-GEL hydrogel is a more suitable 3D system than pure alginate and seems to optimally mimic the physiological behavior of the tumor microenvironment. For the first time, we present a functional 3D hydrogel construct for colon cancer cells, which are supporting their physiological cell attachment, spreading, and viability. We strongly believe that it will be applicable as a suitable in vitro 3D tumor model to study different aspects of tumor cell behavior.
EVALuna2:6830

Biological predictors of radiosensitivity in head and neck squamous cell carcinoma - Fiedler, Mathias; Weber, Florian; Hautmann, Matthias G.; Haubner, Frank; Reichert, Torsten E.; Klingelhoeffer, Christoph; Schreml, Stephan; Meier, Johannes K.; Hartmann, Arndt; Ettl, Tobias (Clinical Oral Investigations, 2018)
OBJECTIVES: The aim of this study is to investigate the influence of prognostic biomarkers on radiosensitivity and survival of advanced head and neck squamous cell carcinomas treated by primary (chemo)radiation. MATERIAL AND METHODS: The clinicopathological data and immunohistochemical staining of p16, c-Met, survivin, PD-1, and PD-L1 of 82 primarily (chemo)irradiated patients with head and neck squamous cell carcinoma were analyzed. Associations with local and locoregional radiation response, overall survival (OS), disease-free (DFS), and disease-specific survival (DSS) were assessed. RESULTS: Complete tumor response was associated with increased patient age (p = 0.007), N0-status (p = 0.022), M0-status (p = 0.007), and p16-positivity (p = 0.022). High PD-L1 was associated with M0-status (p = 0.026) and indicated tumor response to irradiation (p = 0.057); survivin expression showed higher rates of response failure (p = 0.073). Low PD-1 was associated with increased T-stage (p = 0.029) and local recurrence (p = 0.014). High PD-1 was strongly correlated with PD-L1-positive tumor infiltrating lymphocytes (p < 0.001). Low PD-L1 showed a significant correlation with high c-Met expression (p = 0.01). Significant predictors for unfavorable univariate survival were incomplete tumor response (DSS, p < 0.001), single radiotherapy (DSS, p = 0.002), M1-status (DSS, p < 0.001), decreased radiation dose (DSS, p = 0.014), high survivin (DSS, p = 0.045), and high c-Met (OS, p < 0.05). Survivin and c-Met also showed prognostic significance in multivariate survival analysis. CONCLUSIONS: P16 and PD-L1 indicate radiosensitivity, whereas survivin and c-Met implicate radioresistance in primarily (chemo)irradiated head and neck squamous cell carcinomas. The role of the PD-1/PD-L1 immune checkpoints in radiation response and survival merits further investigation. CLINICAL RELEVANCE: The findings may improve patient-specific therapy according to individual tumor characteristics.
EVALuna2:34265

Biphasic papillary renal cell carcinoma is a rare morphological variant with frequent multifocality: a study of 28 cases - Trpkov, Kiril; Athanazio, Daniel; Magi-Galluzzi, Cristina; Yilmaz, Helene; Clouston, David; Agaimy, Abbas; Williamson, Sean R.; Brimo, Fadi; Lopez, Jose I.; Ulamec, Monika; Rioux-Leclercq, Nathalie; Kassem, Maysoun; et al. (Histopathology, 2018)
AIMS: To further characterise biphasic squamoid renal cell carcinoma (RCC), a recently proposed variant of papillary RCC. METHODS AND RESULTS: We identified 28 tumours from multiple institutions. They typically showed two cell populations-larger cells with eosinophilic cytoplasm and higher-grade nuclei, surrounded by smaller, amphophilic cells with scanty cytoplasm. The dual morphology was variable (median 72.5% of tumour, range 5-100%); emperipolesis was found in all cases. The male/female ratio was 2:1, and the median age was 55 years (range 39-86 years). The median tumour size was 20 mm (range 9-65 mm). Pathological stage pT1a was found in 21 cases, pT1b in three, and pT3a and pT3b in one each (two not available). Multifocality was found in 32%: multifocal biphasic RCC in one case, biphasic + papillary RCC in two cases, biphasic + clear cell RCC in three cases, biphasic + low-grade urothelial carcinoma of the renal pelvis in one case, and biphasic + Birt-Hogg-Dubé syndrome in one case. Positive immunostains included: PAX8, cytokeratin (CK) 7, α-methylacyl-CoA racemase, epithelial membrane antigen, and vimentin. Cyclin D1 was expressed only in the larger cells. The Ki67 index was higher in the larger cells (median 5% versus ≤1%). Negative stains included: carbonic anhydrase 9, CD117, GATA-3, WT1, CK5/6, and CK20; CD10 and 34βE12 were variably expressed. Gains of chromosomes 7 and 17 were found in two evaluated cases. Follow-up was available for 23 patients (median 24 months, range 1-244 months): 19 were alive without disease, one was alive with recurrence, and one had died of disease (two had died of other causes). CONCLUSIONS: Biphasic papillary RCC is a rare variant of papillary RCC, and is often multifocal.
EVALuna2:34260

Bladder tumor subtype commitment occurs in carcinoma in-situ driven by key signaling pathways including ECM remodeling - Wullweber, Adrian; Strick, Reiner; Lange, Fabienne; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Bertz, Simone; Weyerer, Veronika; Stöhr, Robert; Breyer, J.; Burger, M.; et al. (EUROPEAN UROLOGY, 2021)
CRIS-Team WoS Importer:2021-08-20

Bladder Tumor Subtype Commitment Occurs in Carcinoma In Situ Driven by Key Signaling Pathways Including ECM Remodeling - Wullweber, Adrian; Strick, Reiner; Lange, Fabienne; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Bertz, Simone; Weyerer, Veronika; Stöhr, Robert; Breyer, Johannes; Burger, Maximilian; et al. (Cancer Research, 2021)
Basal and luminal subtypes of invasive bladder tumors have significant prognostic and predictive impacts for patients. However, it remains unclear whether tumor subtype commitment occurs in noninvasive urothelial lesions or in carcinoma in situ (CIS) and which gene pathways are important for bladder tumor progression. To understand the timing of this commitment, we used gene expression and protein analysis to create a global overview of 36 separate tissues excised from a whole bladder encompassing urothelium, noninvasive urothelial lesions, CIS, and invasive carcinomas. Additionally investigated were matched CIS, noninvasive urothelial lesions, and muscle-invasive bladder cancers (MIBC) from 22 patients. The final stage of subtype commitment to either a luminal or basal MIBC occurred at the CIS transition. For all tissues combined, hierarchical clustering of subtype gene expression revealed three subtypes: "luminal," "basal," and a "luminal p53-/extracellular matrix (ECM)-like" phenotype of ECM-related genes enriched in tumor-associated urothelium, noninvasive urothelial lesions, and CIS, but rarely invasive, carcinomas. A separate cohort of normal urothelium from noncancer patients showed significantly lower expression of ECM-related genes compared with tumor-associated urothelium, noninvasive urothelial lesions, and CIS. A PanCancer Progression Panel of 681 genes unveiled pathways specific for the luminal p53-/ECM-like cluster, for example, ECM remodeling, angiogenesis, epithelial-to-mesenchymal transition, cellular discohesion, cell motility involved in tumor progression, and cell proliferation and oncogenic ERBB2/ERBB3 signaling for invasive carcinomas. In conclusion, this study provides insights into bladder cancer subtype commitment and associated signaling pathways, which could help predict therapy response and enhance our understanding of therapy resistance.
CRIS-Team WoS Importer:2021-04-09

BRAF mutation testing in melanoma: results from a German observational multicenter study - Hartmann, Arndt; Schirmacher, Peter; Sterlacci, William; Koch, Winfried; Liesenfeld, David B.; Schif, Birgit; Garbe, Claus (Virchows Archiv, 2019)
Quality control of BRAF mutation testing methods used in routine practice is crucial for optimal treatment selection. In this prospective study, we assessed the impact of patient/sample characteristics on BRAF mutation testing results in patients with melanoma, during clinical practice. Data were collected on routine testing practices and documented mutation status in patients with melanoma stages IIIB, IIIC, or IV across 28 diagnostic pathology centers in Germany. Patient/sample data collected included: patient age, location of primary melanoma and metastases, origin of sample, melanoma subtype, and quality of tissue. Statistical influence of patient/sample characteristics on BRAF mutation rate was assessed using multiple logistic regression analyses and statistical models developed to predict the probability of BRAF mutations for individual patient cohorts. Data/samples from 642 patients with melanoma were analyzed. BRAF mutations were documented in 241/642 patients (37.5%). The primary statistical model to predict BRAF mutation rates included: age (continuous), origin of sample, method of mutation analysis, and quality of tissue. Analyses of post hoc collected data identified major deviations between documented mutation rates included in this study vs. routinely recorded mutation rates for three centers. When samples from these centers were excluded, the influence of testing method was no longer statistically significant. The final model included patient age, origin of sample (including metastasis location), and quality of tissue. Once validated in an independent population, this type of model could allow pathology centers to compare the performance of their testing methods with what would be expected based on patient, tumor, and sample characteristics.
EVALuna2:52992

BRCA mutations and their influence on pathological complete response and prognosis in a clinical cohort of neoadjuvantly treated breast cancer patients - Wunderle, Marius; Gaß, Paul; Häberle, Lothar; Flesch, Vivien M.; Rauh, Claudia; Bani, Mayada; Hack, Carolin; Schrauder, Michael G.; Jud, Sebastian; Emons, Julius; Erber, Ramona; Ekici, Arif Bülent; et al. (Breast Cancer Research and Treatment, 2018)
PURPOSE: BRCA1/2 mutations influence the molecular characteristics and the effects of systemic treatment of breast cancer. This study investigates the impact of germline BRCA1/2 mutations on pathological complete response and prognosis in patients receiving neoadjuvant systemic chemotherapy. METHODS: Breast cancer patients were tested for a BRCA1/2 mutation in clinical routine work and were treated with anthracycline-based or platinum-based neoadjuvant chemotherapy between 1997 and 2015. These patients were identified in the tumor registry of the Breast Center of the University of Erlangen (Germany). Logistic regression and Cox regression analyses were performed to investigate the associations between BRCA1/2 mutation status, pathological complete response, disease-free survival, and overall survival. RESULTS: Among 355 patients, 59 had a mutation in BRCA1 or in BRCA2 (16.6%), 43 in BRCA1 (12.1%), and 16 in BRCA2 (4.5%). Pathological complete response defined as "ypT0; ypN0" was observed in 54.3% of BRCA1/2 mutation carriers, but only in 22.6% of non-carriers. The adjusted odds ratio was 2.48 (95% CI 1.26-4.91) for BRCA1/2 carriers versus non-carriers. Patients who achieved a pathological complete response had better disease-free survival and overall survival rates compared with those who did not achieve a pathological complete response, regardless of BRCA1/2 mutation status. CONCLUSIONS: BRCA1/2 mutation status leads to better responses to neoadjuvant chemotherapy in breast cancer. Pathological complete response is the main predictor of disease-free survival and overall survival, independently of BRCA1/2 mutation status.
EVALuna2:34606

Breast cancer risk - From genetics to molecular understanding of pathogenesis - Fasching, Peter; Ekici, Arif Bülent; Wachter, David Lukas; Hein, Alexander; Bayer, Christian M.; Häberle, Lothar; Löhberg, Christian; Schneider, Michael; Jud, Sebastian; Heusinger, K.; Rübner, Matthias; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Several advancements over the last decade have triggered the developments in the field of breast cancer risk research. One of them is the availability of the human genome sequence along with cheap genotyping possibilities. Another is the globalization of research, which has led to the growth of research collaboration into large international consortia that facilitate the pooling of clinical and genotype data of hundreds of thousands of patients and healthy control individuals. This review concerns with the recent developments in breast cancer risk research and focuses on the discovery of new genetic breast cancer risk factors and their meaning in the context of established non-genetic risk factors. Finally the clinical application is highly dependent on the accuracy of breast cancer risk prediction models, not only for all breast cancer patients, but also for molecular subtypes, preferably for those which are associated with an unfavorable prognosis. Recently risk prediction incorporates all possible risk factors, which include epidemiological risk factors, mammographic density and genetic risk factors. © Georg Thieme Verlag KG Stuttgart• New York•.
CRIS-Team Scopus Importer:2021-07-19
Keywords: BRCA; breast cancer risk; gene-environment interaction; genetic risk factors; prediction models

Breast cancer risk - Genes, environment and clinics Mammakarzinomrisiko - Gene, Umwelt und Klinik - Fasching, Peter; Ekici, Arif Bülent; Adamietz, B. R.; Wachter, David Lukas; Hein, Alexander; Bayer, Christian M.; Häberle, Lothar; Löhberg, Christian; Jud, Sebastian; Heusinger, K.; Rübner, Matthias; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2011)
The information available about breast cancer risk factors has increased dramatically during the last 10 years. In particular, studies of low-penetrance genes and mammographic density have improved our understanding of breast cancer risk. In addition, initial steps have been taken in investigating interactions between genes and environmental factors. This review concerns with actual data on this topic. Several genome-wide association studies (GWASs) with a casecontrol design, as well as large-scale validation studies, have identified and validated more than a dozen single nucleotide polymorphisms (SNPs) associated with breast cancer risk. They are located not only in or close to genes known to be involved in cancer pathogenesis, but also in genes not previously associated with breast cancer pathogenesis, or may even not be related to any genes. SNPs have also been identified that alter the lifetime risk in BRCA mutation carriers. With regard to nongenetic risk factors, studies of postmenopausal hormone replacement therapy (HRT) have revealed important information on how to weigh up the risks and benefits of HRT. Mammographic density (MD) has become an accepted and important breast cancer risk factor. Lifestyle and nutritional considerations have become an integral part of most studies of breast cancer risk, and some improvements have been made in this field as well. More than 10 years after the publication of the first breast cancer prevention studies with tamoxifen, other substances such as raloxifene and aromatase inhibitors have been investigated and have also been shown to have preventive potential. Finally, mammographic screening systems have been implemented in most Western countries during the last decade. These may be developed further by including more individualized methods of predicting the patients breast cancer risk. © Georg Thieme Verlag KG Stuttgart - New York.
CRIS-Team Scopus Importer:2021-07-19
Keywords: BRCA (breast cancer antigen); breast; breast feeding; CAM (Complementary and Alternative medicine); cancer registry; estrogen receptor

Breast MRI at Very Short TE (minTE): Image Analysis of minTE Sequences on Non-Fat-Saturated, Subtracted T1-Weighted Images - Wenkel, Evelyn; Janka, Rolf Matthias; Geppert, Christian; Kämmerer, Nadine; Hartmann, Arndt; Uder, Michael; Hammon, Matthias; Brand, Michael (Röfo-Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2017)
Purpose The aim was to evaluate a minimum echo time (minTE) protocol for breast magnetic resonance imaging (MRI) in patients with breast lesions compared to a standard TE (nTE) time protocol. Methods Breasts of 144 women were examined with a 1.5 Tesla MRI scanner. Additionally to the standard gradient-echo sequence with nTE (4.8 ms), a variant with minimum TE (1.2 ms) was used in an interleaved fashion which leads to a better temporal resolution and should reduce the scan time by approximately 50 %. Lesion sizes were measured and the signal-to-noise ratio (SNR) as well as the contrast-to-noise ratio (CNR) were calculated. Subjective confidence was evaluated using a 3-point scale before looking at the nTE sequences (1 = very sure that I can identify a lesion and classify it, 2 = quite sure that I can identify a lesion and classify it, 3 = definitely want to see nTE for final assessment) and the subjective image quality of all examinations was evaluated using a four-grade scale (1 = sharp, 2 = slight blur, 3 = moderate blur and 4 = severe blur/not evaluable) for lesion and skin sharpness. Lesion morphology and contrast enhancement were also evaluated. Results With minTE sequences, no lesion was rated with "definitely want to see nTE sequences for final assessment". The difference of the longitudinal and transverse diameter did not differ significantly (p > 0.05). With minTE, lesions and skin were rated to be significantly more blurry (p < 0.01 for lesions and p < 0.05 for skin). There was no difference between both sequences with respect to SNR, CNR, lesion morphology, contrast enhancement and detection of multifocal disease. Conclusion Dynamic breast MRI with a minTE protocol is feasible without a major loss of information (SNR, CNR, lesion morphology, contrast enhancement and lesion sizes) and the temporal resolution can be increased by a factor of 2 using minTE sequences. Key points · Increase of temporal resolution for a better in-flow curve.. · Dynamic breast MRI with a shorter TE time is possible without relevant loss of information.. · Possible decrease of the overall scan time.. Citation Format · Wenkel E, Janka R, Geppert C et al. Breast MRI at Very Short TE (minTE): Image Analysis of minTE Sequences on Non-Fat-Saturated, Subtracted T1-Weighted Images. Fortschr Röntgenstr 2017; 189: 137 - 145.
EVALuna2:6843

Breast Tumor Analysis Using Shifted-Excitation Raman Difference Spectroscopy (SERDS) - Gebrekidan, Medhanie; Erber, Ramona; Hartmann, Arndt; Fasching, Peter; Emons, Julius; Beckmann, Matthias; Bräuer, Andreas (Technology in Cancer Research & Treatment, 2018)
We used a shifted-excitation Raman difference spectroscopy method for the ex vivo classification of resected and formalin-fixed breast tissue samples as normal (healthy) tissue, fibroadenoma, or invasive carcinoma. We analyzed 8 tissue samples containing invasive carcinoma that were surrounded by normal tissue and 3 tissue samples with fibroadenoma only. We made various measurement sites on various tissue samples, in total 240 measurements for each type of tissue. Although the acquired raw spectra contain enough information to clearly differentiate between normal and tumor (fibroadenoma and invasive carcinoma) tissue, the differentiation between fibroadenoma and invasive carcinoma was possible only after the shifted-excitation Raman difference spectroscopy isolation of pure Raman spectra from the heavily fluorescence interfered raw spectra. We used 784 and 785 nm as excitation wavelengths for the shifted-excitation Raman difference spectroscopy method. The differences in the obtained pure Raman spectra are assigned to the different chemical compositions of normal breast tissue, fibroadenoma, and invasive breast carcinoma. Principal component analysis and linear discriminant analysis showed excellent classification results in the Raman shift range between 1000 and 1800 cm-1. Invasive breast carcinoma was identified with 99.15% sensitivity, and the absence of invasive carcinoma was identified with 90.40% specificity. Tumor tissue in tumor-containing tissue was identified with 100% sensitivity, and the absence of tumor in no-tumor containing tissue was identified with 100% specificity. As gold standard for the determination of the sensitivity and the specificity, we considered the conventional histopathological classification. In summary, shifted-excitation Raman difference spectroscopy could be potentially very useful to support histopathological diagnosis in breast pathology.
EVALuna2:34855

Can clinicopathological parameters predict for lymph node metastases in ypT0-2 rectal carcinoma? Results of the CAO/ARO/AIO-94 and CAO/ARO/AIO-04 phase 3 trials - Von Den Gruen, Jens Mueller; Hartmann, Arndt; Fietkau, Rainer; Ghadimi, Michael; Liersch, Torsten; Hohenberger, Werner; Weitz, Jurgen; Sauer, Rolf; Wittekind, Christian; Stroebel, Philipp; Roedel, Claus; Fokas, Emmanouil (Radiotherapy and Oncology, 2018)
BACKGROUND: The advent of less radical surgical approaches has generated concern about leaving locoregional lymph node metastases (LNM) unresected that could lead to adverse outcome. We examined the prognostic role of clinicopathological factors for ypN-positivity in patients with ypT0-2 rectal carcinoma treated within the CAO/ARO/AIO-94 and CAO/ARO/AIO-04 randomized phase 3 trials. METHODS: The correlation of clinicopathological factors with ypN-status (ypN0 vs ypN1/2) was examined in n = 776 patients with ypT0-2 rectal carcinoma after preoperative CRT and total mesorectal excision surgery using Pearson's Chi-squared test for categorical variables and Kruskal-Wallis' test for continuous variables. Multivariable analysis was performed using binary logistic regression to identify independent prognosticators for ypN-positivity. RESULTS: Residual LNM (ypN+) were found in 6%, 20.8% and 21.4% of patients with ypT0, ypT1 and ypT2 carcinomas, respectively. Independent prognosticators for LNM were advanced ypT category (p = 0.002) and lymphatic invasion (p = 0.020). In a separate multivariable analysis performed upon exclusion of ypT-category due to multicollinearity with residual tumor diameter (RTD), lymphatic invasion (p = 0.015) and RTD ≥10 mm (p = 0.005) demonstrated strong correlation with LNM. CONCLUSION: Advanced ypT-stage, lymphatic invasion and RTD ≥10 mm were prognostic factors for LNM in patients ypT0-2 rectal carcinoma treated with CRT and surgery within both phase 3 trials. The high incidence of LNM in the ypT1-2 group needs to be taken into consideration in the context of oncological safety and indicate that LE should be advocated with great caution in this patient subgroup. The prognostic pathological factor identified here could help guide decision of LE vs TME after standard CRT.
EVALuna2:34854

Can local excision be safely recommended in patients with ypT0-2 rectal cancer after chemoradiotherapy? Clinicopathological results of the CAO/ARO/AIO-94 and CAO/ARO/AIO-04 randomized phase 3 trials - Von Den Gruen, Mueller J.; Hartmann, Arndt; Fietkau, Rainer; Ghadimi, M.; Liersch, T.; Stroebel, P.; Sauer, Rolf; Roedel, C.; Fokas, E. (2018)
EVALuna2:36508

Case report: Immunovirotherapy as a novel add-on treatment in a patient with thoracic NUT carcinoma - Kloker, Linus D.; Calukovic, Branko; Benzler, Katrin; Golf, Alexander; Böhm, Sebastian; Günther, Sven; Horger, Marius; Haas, Simone; Berchtold, Susanne; Beil, Julia; Carter, Mary E.; Ganzenmueller, Tina; et al. (Frontiers in Oncology, 2022)
NUT carcinoma (NC) is a rare and extremely aggressive form of cancer, usually presenting with intrathoracic or neck manifestations in adolescents and young adults. With no established standard therapy regimen and a median overall survival of only 6.5 months, there is a huge need for innovative treatment options. As NC is genetically driven by a single aberrant fusion oncoprotein, it is generally characterized by a low tumor mutational burden, thus making it immunologically cold and insusceptible to conventional immunotherapy. Recently, we have demonstrated that oncolytic viruses (OVs) are able to specifically infect and lyse NC cells, thereby turning an immunologically cold tumor microenvironment into a hot one. Here, we report an intensive multimodal treatment approach employing for the first time an OV (talimogene laherparepvec (T-VEC); IMLYGIC®) together with the immune checkpoint inhibitor pembrolizumab as an add-on to a basic NC therapy (cytostatic chemotherapy, radiation therapy, epigenetic therapy) in a patient suffering from a large thoracic NC tumor which exhibits an aberrant, unique BRD3:NUTM1 fusion. This case demonstrates for the first time the feasibility of this innovative add-on immunovirotherapy regimen with a profound, repetitive and durable replication of T-VEC that is instrumental in achieving tumor stabilization and improvement in the patient´s quality of life. Further, a previously unknown BRD3:NUTM1 fusion gene was discovered that lacks the extraterminal domain of BRD3.
CRIS-Team Scopus Importer:2022-11-25
Keywords: BRD3; chemotherapy; immunotherapy; NUT carcinoma; NUTM1; T-VEC; virotherapy

CCL2 expression in tumor cells and tumor-infiltrating immune cells shows divergent prognostic potential for bladder cancer patients depending on lymph node stage - Eckstein, Markus; Epple, Elena; Jung, Rudolf; Weigelt, Katrin; Lieb, Verena; Sikic, Danijel; Stöhr, Robert; Geppert, Carol-Immanuel; Weyerer, Veronika; Bertz, Simone; Kehlen, Astrid; Hartmann, Arndt; et al. (Cancers, 2020)
Bladder cancer (BCa) is the ninth most commonly diagnosed cancer worldwide. Although there are several well-established molecular and immunological classifications, markers for tumor cells and immune cells that are associated with prognosis are still needed. The chemokine CC motif ligand 2 (CCL2) could be such a marker. We analyzed the expression of CCL2 by immunohistochemistry (IHC) in 168 muscle invasive BCa samples using a tissue microarray. Application of a single cut-off for the staining status of tumor cells (TCs; positive vs. negative) and immune cells (ICs; ≤6% of ICs vs. >6% of ICs) revealed 57 cases (33.9%) and 70 cases (41.7%) with CCL2-positive TCs or ICs, respectively. IHC results were correlated with clinicopathological and survival data. Positive CCL2 staining in TCs was associated with shorter overall survival (OS), disease-specific survival (DSS), and relapse-free survival (RFS) (p = 0.004, p = 0.036, and p = 0.047; log rank test) and appeared to be an independent prognostic factor for OS (RR = 1.70; p = 0.007; multivariate Cox’s regression analysis). In contrast, positive CCL2 staining in the ICs was associated with longer OS, DSS, and RFS (p = 0.032, p = 0.001, and p = 0.001; log rank test) and appeared to be an independent prognostic factor for DSS (RR = 1.77; p = 0.031; multivariate Cox’s regression analysis). Most interestingly, after separating the patients according to their lymph node status (N0 vs. N1+2), CCL2 staining in the ICs was differentially associated with prognosis. In the N0 group, CCL2 positivity in the ICs was a positive independent prognostic factor for OS (RR = 1.99; p = 0.014), DSS (RR = 3.17; p = 0.002), and RFS (RR = 3.10; p = 0.002), whereas in the N1+2 group, CCL2 positivity was a negative independent factor for OS (RR = 3.44; p = 0.019)) and RFS (RR = 4.47; p = 0.010; all multivariate Cox’s regression analyses). In summary, CCL2 positivity in TCs is a negative prognostic factor for OS, and CCL2 can mark ICs that are differentially associated with prognosis depending on the nodal stage of BCa patients. Therefore, CCL2 staining of TCs and ICs is suggested as a prognostic biomarker for BCa patients.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Bladder cancer; CCL2; Immune cells; Lymph node stage; Prognosis; Tumor cells

CCNE1 and survival of patients with tubo-ovarian high-grade serous carcinoma: An Ovarian Tumor Tissue Analysis consortium study - Kang, Eun Young; Weir, Ashley; Meagher, Nicola S.; Farrington, Kyo; Nelson, Gregg S.; Ghatage, Prafull; Lee, Cheng Han; Riggan, Marjorie J.; Bolithon, Adelyn; Popovic, Gordana; Leung, Betty; Tang, Katrina; et al. (Cancer, 2023)
Background: Cyclin E1 (CCNE1) is a potential predictive marker and therapeutic target in tubo-ovarian high-grade serous carcinoma (HGSC). Smaller studies have revealed unfavorable associations for CCNE1 amplification and CCNE1 overexpression with survival, but to date no large-scale, histotype-specific validation has been performed. The hypothesis was that high-level amplification of CCNE1 and CCNE1 overexpression, as well as a combination of the two, are linked to shorter overall survival in HGSC. Methods: Within the Ovarian Tumor Tissue Analysis consortium, amplification status and protein level in 3029 HGSC cases and mRNA expression in 2419 samples were investigated. Results: High-level amplification (>8 copies by chromogenic in situ hybridization) was found in 8.6% of HGSC and overexpression (>60% with at least 5% demonstrating strong intensity by immunohistochemistry) was found in 22.4%. CCNE1 high-level amplification and overexpression both were linked to shorter overall survival in multivariate survival analysis adjusted for age and stage, with hazard stratification by study (hazard ratio [HR], 1.26; 95% CI, 1.08-1.47, p =.034, and HR, 1.18; 95% CI, 1.05-1.32, p =.015, respectively). This was also true for cases with combined high-level amplification/overexpression (HR, 1.26; 95% CI, 1.09-1.47, p =.033). CCNE1 mRNA expression was not associated with overall survival (HR, 1.00 per 1-SD increase; 95% CI, 0.94-1.06; p =.58). CCNE1 high-level amplification is mutually exclusive with the presence of germline BRCA1/2 pathogenic variants and shows an inverse association to RB1 loss. Conclusion: This study provides large-scale validation that CCNE1 high-level amplification is associated with shorter survival, supporting its utility as a prognostic biomarker in HGSC.
CRIS-Team Scopus Importer:2023-02-17
Keywords: CCNE1 amplification; cyclin E1 expression; high-grade serous carcinoma; ovarian cancer; prognosis

CD8+and Regulatory T cells Differentiate Tumor Immune Phenotypes and Predict Survival in Locally Advanced Head and Neck Cancer - Echarti, Alessia; Hecht, Markus; Büttner-Herold, Maike; Haderlein, Marlen; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Cancers, 2019)
Background: The tumor immune status "inflamed", "immune excluded", and "desert" might serve as a predictive parameter. We studied these three cancer immune phenotypes while using a simple immunohistochemical algorithm. Methods: Pre-treatment tissue samples of 280 patients with locally advanced HNSCC treated with radiochemotherapy were analyzed. A double staining of CD8+ cytotoxic T cells (CTL) and FoxP3+ (Treg) was performed and the cell density was evaluated in the intraepithelial and stromal compartment of the tumor. Results: The classification of tumors as "immune desert" when stromal CTL were <= 50 cells/mm(2), "inflamed" when intraepithelial CTL were > 500 cells/mm(2), and as "excluded" when neither of these definitions met these cut off values allowed the best discrimination regarding overall survival. These groups had median OS periods of 37, 61, and 85 months, respectively. In "immune desert" and "immune excluded" tumors high Treg tended to worsen OS, but in "inflamed" tumors high Treg clearly improved OS. Conclusions: We propose that, in locally advanced HNSCC, the tumor immune state "inflamed", "immune excluded", and "immune desert" can be defined by intraepithelial and stromal CTL. Tregs can further subdivide these groups. The opposing effects of Tregs in the different groups might be the reason for the inconsistency of Tregs prognostic values published earlier.
CRIS-Team WoS Importer:2019-10-25

CD8+ Cytotoxic Immune Infiltrate in Non-Muscle Invasive Bladder Cancer: A Standardized Methodology to Study Association with Clinico-Pathological Features and Prognosis - Masson-Lecomte, Alexandra; Maille, Pascale; Pineda, Silvia; Soyeux, Pascale; Sagrera, Ana; Rava, Marta; Lopez De Maturana, Evangelina; Marquez, Mirari; Tardon, Adonina; Carrato, Alfredo; Kogevinas, Manolis; De La Taille, Alexandre; et al. (Bladder Cancer, 2019)
Background: Major interest lies in the evaluation of immune infiltrate in bladder cancer. CD8+ cytotoxic lymphocytes are key effectors of adaptive immune response. Objectives: The aims of the study were to set up a standardized methodology for CD8+ lymphocytes estimation in NMIBC and investigate how intra-tumoral heterogeneity influences CD8+ immune infiltrate. Methods: We considered 995 NMIBC included in the Spanish Bladder Cancer (SBC)/EPICURO Study. Duplicate 0.6mm TMA spots and paired full sections (FS) for 50 selected cases were double stained with anti-pan cytokeratin antibody and anti-CD8 antibody. Slides were digitalized and CD8+ cells were automatically counted after tissue recognition (tumor vs stroma). Spatial heterogeneity was assessed and a resampling strategy was applied to estimate the proper number of 0.6mm TMA spots providing an adequate CD8+ cell estimate. Association between CD8+ count and expression of urothelial differentiation markers was estimated. Cox regression models were performed to assess association between CD8+ cell count and risk of recurrence and progression. Results: Microscopic examination of full sections showed spatial heterogeneity for CD8+ infiltrates. Simulation analyses demonstrated that 5 TMA regions provided a correct sampling of tumor and stromal compartments in Ta while 2 and 6 TMA regions were necessary in T1, respectively. CD8+ cells infiltration was associated with stage, regardless of the histological compartment analyzed (median CD8+/mm2 were 25/mm2 and 129/mm2 in tumor and stroma respectively in Ta and 111/mm2 and 344/mm2 in T1; p-value=0.006). CD8+ infiltration in tumor compartment was significantly associated with low FGFR3 expression. CD8+/mm2 count in the tumor compartment was not associated with prognosis. Conclusion: Differences identified between Ta and T1 tumours supported the hypothesis that rigorous efforts should be placed in proper study design. These results provide a new framework to investigate microenvironment complexity in bladder cancer.
CRIS-Team Scopus Importer:2019-09-03
Keywords: CD8; methodology; prognosis; Urothelial carcinoma

CDKN2A as transcriptomic marker for muscle-invasive bladder cancer risk stratification and therapy decision-making - Worst, Thomas S.; Weis, Cleo-Aron; Stoehr, Robert; Bertz, Simone; Eckstein, Markus; Otto, Wolfgang; Breyer, Johannes; Hartmann, Arndt; Bolenz, Christian; Wirtz, Ralph M.; Erben, Philipp (Scientific Reports, 2018)
Deletions of the cell cycle control gene CDKN2A are described as progression markers of non-muscle invasive bladder cancer and to be associated with fibroblast growth factor 3 (FGFR3) mutations. The prognostic role of CDKN2A RNA expression in muscle invasive bladder cancer (MIBC) is under discussion. In 80 MIBC patients (m/f 60/20) who underwent radical cystectomy the expression of CDKN2A and FGFR3 was examined with qRT-PCR (test cohort). The MDA cohort (n = 57) and the TCGA cohort (n = 365) served for validation. The expression of drug target genes and TCGA molecular subtypes was correlated with CDKN2A expression. In the test cohort CDKN2Ahigh patients (n = 8; 10.0%) had a significantly shorter recurrence-free (p = 0.018) and disease-specific (p = 0.006) survival compared to the rest of the cohort. A similar stratification was seen in the validation cohorts (CDKN2Ahigh: n = 7, 12.3%, p = 0.001; n = 46, 12.6%, p = 0.011). In the TCGA cohort these patients had a comparably low expression of drug target genes. The expression of CDKN2A significantly differed among TGCA molecular subtypes. 71.7% of CDKN2Ahigh were TCGA basal squamous tumours but also show divergent molecular features compared to this group. In summary CDKN2A RNA expression-based risk stratification of MIBC allows the identification of a CDKN2Ahigh poor prognosis group with low expression of drug target genes.
EVALuna2:34853

Cell-Free DNA Sequencing Reveals Gene Variants in DNA Damage Repair Genes Associated with Prognosis of Prostate Cancer Patients - Lieb, Verena; Abdulrahman, Amer; Weigelt, Katrin; Hauch, Siegfried; Gombert, Michael; Guzman, Juan; Bellut, Laura; Goebell, Peter; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; et al. (Cells, 2022)
In the present study, we further analyzed the data obtained in our previous study, where we investigated the cell-free DNA (cfDNA) of 34 progressive prostate cancer patients via targeted sequencing. Here, we studied the occurrence and prognostic impact of sequence variants according to their clinical pathological significance (CPS) or their functional impact (FI) in 23 DNA damage repair (DDR) genes with a focus on the ATM serine/threonine kinase gene (ATM). All patients had at least one DDR gene with a CPS or FI variant. Kaplan-Meier analysis indicated that the group with a higher number of CPS variants in DDR genes had a shorter time to treatment change (TTC) compared to the group with a lower number of CPS variants (p = 0.038). Analysis of each DDR gene revealed that CPS variants in the ATM gene and FI variants in the nibrin (NBN) gene showed a shorter TTC (p = 0.034 and p = 0.042). In addition, patients with CPS variants in the ATM gene had shorter overall survival (OS; p = 0.022) and disease-specific survival (DSS; p = 0.010) than patients without these variants. Interestingly, patients with CPS variants in seven DDR genes possessed a better OS (p = 0.008) and DSS (p = 0.009), and patients with FI variants in four DDR genes showed a better OS (p = 0.007) and DSS (p = 0.008). Together, these findings demonstrated that the analysis of cfDNA for gene variants in DDR genes provides prognostic information that may be helpful for future temporal and targeted treatment decisions for advanced PCa patients.
CRIS-Team Scopus Importer:2022-12-02
Keywords: ATM; cfDNA; DDR genes; NBN; prognosis; prostate cancer; sequence variants

Cell-free dna variant sequencing using plasma and ar-v7 testing of circulating tumor cells in prostate cancer patients - Lieb, Verena; Bellut, Laura; Abdulrahman, Amer; Weigelt, Katrin; Hauch, Siegfried; Gombert, Michael; Guzman, Juan; Goebell, Peter; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; et al. (Cells, 2021)
Prostate cancer (PCa) is the second most common malignant cancer and is a major cause of morbidity and mortality among men worldwide. There is still an urgent need for biomarkers applicable for diagnosis, prognosis, therapy prediction, or therapy monitoring in PCa. Liquid biopsies, including cell-free DNA (cfDNA) and circulating tumor cells (CTCs), are a valuable source for studying such biomarkers and are minimally invasive. In our study, we investigated the cfDNA of 34 progressive PCa patients, via targeted sequencing, for sequence variants and for the occurrence of CTCs, with a focus on androgen receptor splice variant 7 (AR-V7)-positive CTCs. The cfDNA content was associated with overall survival (OS; p = 0.014), disease-specific survival (DSS; p = 0.004), and time to treatment change (TTC; p = 0.001). Moreover, when considering all sequence variants grouped by their functional impact and allele frequency, a significant association with TTC (p = 0.017) was observed. When investigating only pathogenic or likely pathogenic gene variants, variants of the BRCA1 gene (p = 0.029) and the AR ligand-binding domain (p = 0.050) were associated with a shorter TTC. Likewise, the presence of CTCs was associated with a shorter TTC (p = 0.031). The presence of AR-V7-positive CTCs was associated with TTC (p < 0.001) in Kaplan–Meier analysis. Interestingly, all patients with AR-V7-positive CTCs also carried TP53 point mutations. Altogether, analysis of cfDNA and CTCs can provide complementary information that may support temporal and targeted treatment decisions and may elucidate the optimal choice within the variety of therapy options for advanced PCa patients.
CRIS-Team Scopus Importer:2021-11-26
Keywords: CfDNA; CTCs; Prognosis; prostate cancer; Sequence variants

Cervical intraepithelial neoplasia grade 2/3: development during pregnancy and postpartum - Stübs, Frederik; Mergel, F.; Koch, M. C.; Dietl, Anna; Schulmeyer, Carla; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Gaß, Paul; Mehlhorn, G. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Cervical intraepithelial neoplasia grade 3: development during pregnancy and postpartum - Stübs, Frederik; Mergel, Franziska; Koch, Martin; Dietl, Anna; Schulmeyer, Carla; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Gaß, Paul; Mehlhorn, Grit (Archives of Gynecology and Obstetrics, 2022)
Purpose: The aims of the present study were to evaluate the development of untreated cervical intraepithelial neoplasia (CIN) 3 during pregnancy and to assess persistence, progression, and regression rates postpartum to identify factors associated with regression. Methods: In a tertiary gynecology and obstetrics department, a total of 154 pregnant women with CIN 3 were treated in the dysplasia unit. The follow-up findings were analyzed retrospectively on the basis of histological, cytological, and human papillomavirus (HPV) testing of 154 pregnant women confirmed as having CIN 3 in colposcopically guided biopsies. Results: The rates of persistence, regression, and progression of CIN 3 in these women were 76.1%, 20% and 3.2%, respectively. Data for the delivery mode was available for 126 women. The rate of regression was almost twice as high with vaginal delivery as with cesarean section, at 27.4 vs. 15.2%, whereas the rate of progression was lower with vaginal delivery, at 2.7 vs. 6.5%. Conclusion: The rate of persistence of CIN observed in this study is comparable to that reported in other studies. The study provides strong evidence for greater regression among women who have vaginal deliveries. Careful work-up is recommended postpartum for this group of women in order to rule out persistent CIN 3 or invasive disease.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Cervical dysplasia; High-grade squamous intraepithelial lesion (HSIL); Mode of delivery; Pregnancy; Treatment

Challenging the prognostic impact of the new WHO and TNM classifications with special emphasis on HPV status in penile carcinoma - Hölters, Sebastian; Khalmurzaev, Oybek; Pryalukhin, Alexey; Loertzer, Philine; Janssen, Martin; Heinzelbecker, Julia; Ueberdiek, Stefan; Pfuhl, Thorsten; Smola, Sigrun; Agaimy, Abbas; Geppert, Carol-Immanuel; Loertzer, Hagen; et al. (Virchows Archiv, 2019)
The evidence concerning prognostic parameters for clinical decision-making in penile cancer is either weak or missing. We therefore analysed the prognostic value of the revised TNM and WHO classification systems on relapse and survival with special emphasis on HPV status. We collected clinical data and tissue samples of 121 patients from centres in Germany and Russia. HPV genotyping and p16INK4a immunostaining were performed. The histological subtype and TNM were reclassified by two experienced uropathologists. Survival analyses were performed by Kaplan-Meier estimator and log-rank test. Uni- and multivariable analyses were performed by Cox proportional hazard model and Fisher’s exact test for contingency analysis. HPV status was not found to be an independent prognostic factor. Histological subtypes differ in prognosis with the best outcome found in warty and the worst in basaloid carcinomas. Patients with pT1b defined by poor differentiation or lymphovascular invasion (LVI) had the shortest metastasis-free survival compared with pT1a (log-rank, p = 0.02). Lymph node metastasis and LVI were significantly associated with poor metastasis-free, cancer-specific and overall survival and could be identified as the only independent prognostic parameters. Prognostic value of TNM could not be improved using the 8th versus the 7th edition. In contrast to HPV status, histological subtypes are of prognostic value and should be an essential part of pathologic reports. The impact of the HPV status needs to be analysed in a subtype-specific manner. Parameters describing lymphatic dissemination have the highest impact on prognosis. Inclusion of tumour grade and LVI into a single T-category (pT1b) seems questionable.
CRIS-Team Scopus Importer:2019-08-06
Keywords: HPV; Prognosis; Squamous penile carcinoma

Characterization of esophageal inflammation in patients with achalasia. A retrospective immunohistochemical study - Döhla, Manuel; Leichauer, Katharina; Gockel, Ines; Niebisch, Stefan; Thieme, René; Lundell, Lars; Schumacher, Johannes; Becker, Jessica; Rieker, Ralf; Hartmann, Arndt; Veits, Lothar; Vieth, Michael (Human Pathology, 2019)
CRIS-Team Scopus Importer:2019-05-02
Keywords: Achalasia; Cytotoxic T cells; Esophagus; Inflammation; Regulatory T cells

Characterization of Molecular Subtypes of Paget Disease of the Breast Using Immunohistochemistry and In Situ Hybridization - Wachter, David; wachter, peter wolf; Fasching, Peter; Beckmann, Matthias; Hack, Carolin; Riener, Marc-Oliver; Hartmann, Arndt; Strehl, Johanna D. (Archives of Pathology & Laboratory Medicine, 2018)
CONTEXT: - Paget disease of the breast, in most cases, represents intraepidermal spread of ductal carcinoma in situ. Molecular subtypes of invasive carcinoma of the breast have prognostic and therapeutic significance and show characteristic distribution. Little is known about the distribution of molecular subtypes in Paget disease of the breast. OBJECTIVES: - To examine the distribution of molecular subtypes in Paget disease of the breast and to compare them to concurrent invasive carcinoma of the breast, if present. DESIGN: - We examined 48 cases of Paget disease of the breast with immunohistochemistry and antibodies against estrogen and progesterone receptors, human epidermal growth factor receptor 2 (HER2), and Ki-67, as well as HER2 chromogenic in situ hybridization, to classify the cases into molecular subtypes. Then, we compared the results to the molecular subtypes of associated, invasive carcinoma of the breast, if present. RESULTS: - The HER2 subtype was the most common found in Paget disease of the breast, followed by the luminal B subtype and 2 cases of the triple-negative subtype. The associated, invasive carcinoma cases were most often of the luminal B subtype, followed by the HER2 subtype and the triple-negative subtype. The molecular subtype of Paget disease and invasive carcinoma was congruent in most of the cases. CONCLUSIONS: - Molecular subtypes of invasive carcinoma of the breast can already be detected in Paget disease. The distribution of molecular subtypes of Paget disease and of Paget disease-associated, invasive carcinoma differs from invasive carcinoma without associated Paget disease, with the HER2 subtype overrepresented in Paget disease and associated, invasive carcinoma and the luminal and triple-negative subtypes underrepresented.
EVALuna2:34808

Characterization of PD-1 and PD-L1 Expression in Papillary Renal Cell Carcinoma: Results of a Large Multicenter Study - Erlmeier, Franziska; Steffens, Sandra; Stöhr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Ströbel, Philipp; Becker, Frank; Wülfing, Christian; Barth, Peter; Stöckle, Michael; et al. (Clinical Genitourinary Cancer, 2020)
Background: Programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) play a decisive role as prognostic markers in clear-cell renal cell carcinoma (RCC). To date, the role of PD-1/PD-L1 as a prognostic marker in papillary RCC (pRCC) remains scarce. Patients and Methods: Patients’ sample collection was a joint collaboration of the nationwide PANZAR consortium – a multicenter study. Medical history and tumor specimens were collected from 245 and 129 patients with pRCC types 1 and 2, respectively. Expression of PD-1 and PD-L1 was determined by immunohistochemistry in pRCC and tumor-infiltrating mononuclear cells. Results: Of 374 pRCC specimens, 204 type 1 and 97 type 2 were evaluable for PD-1 and PD-L1 expression analysis. In total, PD-1 and PD-L1 expression were found in 8 (4.9%) of 162 and 12 (7.2%) of 166 evaluable pRCC type 1 specimens. Comparably, PD-1 and PD-L1 expression were found in 2 (2.4%) of 83 and 5 (6.2%) of 81 evaluable pRCC type 2 specimens. Hardly any clinically relevant associations between PD-1 and PD-L1 positivity and clinicopathologic or clinical courses were observed, neither in pRCC type 1 nor type 2. Conclusion: The analysis of a large pRCC cohort from a multicenter consortium revealed no impact of PD-1/PD-L1 expression on prognosis in patients with pRCC with predominantly limited disease status, neither for type 1 nor type 2. However, the impact of PD-1 and PD-L1 in more advanced pRCC disease needs further elucidation. Understanding the impact of programmed cell death protein 1 (PD-1)/programmed death-ligand 1 (PD-L1) expression becomes increasingly important in renal cell carcinoma (RCC) owing to increasing therapeutic implications. However, little is known in non–clear-cell RCC about the relevance of those immune checkpoint surrogates. Here, we suggest that PD-1/PD-L1 expression in papillary RCC does not have prognostic impact, neither for type 1 nor type 2. However, in advanced disease, further evaluation according to PD-1/PD-L1 is warranted.
CRIS-Team Scopus Importer:2020-08-14
Keywords: Non-clear-cell-renal carcinoma; Papillary renal cell; PD-1; PD-L1; Renal cell carcinoma

Characterization of the expression and immunological impact of the transcriptional activator CREB in renal cell carcinoma - Friedrich, Michael; Stoehr, Christine; Jasinski-Bergner, Simon; Hartmann, Arndt; Wach, Sven; Wullich, Bernd; Steven, André; Seliger, Barbara (Journal of Translational Medicine, 2020)
Background: The non-classical human leukocyte antigen (HLA)-G is a strong immunomodulatory molecule. Under physiological conditions, HLA-G induces immunological tolerance in immune privileged tissues, while under pathophysiological situations it contributes to immune escape mechanisms. Therefore, HLA-G could act as a potential immune checkpoint for future anti-cancer immunotherapies. Recent data suggest an aberrant expression of the cAMP response element binding protein (CREB) in clear cell renal cell carcinoma (ccRCC), which is correlated with tumor grade and stage. Furthermore, preliminary reports demonstrated a connection of CREB as a control variable of HLA-G transcription due to CREB binding sites in the HLA-G promoter region. This study investigates the interaction between CREB and HLA-G in different renal cell carcinoma (RCC) subtypes and its correlation to clinical parameters. Methods: The direct interaction of CREB with the HLA-G promoter was investigated by chromatin immunoprecipitation in RCC cell systems. Furthermore, the expression of CREB and HLA-G was determined by immunohistochemistry using a tissue microarray (TMA) consisting of 453 RCC samples of distinct subtypes. Staining results were assessed for correlations to clinical parameters as well as to the composition of the immune cell infiltrate. Results: There exists a distinct expression pattern of HLA-G and CREB in the three main RCC subtypes. HLA-G and CREB expression were the lowest in chromophobe RCC lesions. However, the clinical relevance of CREB and HLA-G expression differed. Unlike HLA-G, high levels of CREB expression were positively associated to the overall survival of RCC patients. A slightly, but significantly elevated number of tumor infiltrating regulatory T cells was observed in tumors of high CREB expression. Whether this small increase is of clinical relevance has to be further investigated. Conclusions: An interaction of CREB with the HLA-G promoter could be validated in RCC cell lines. Thus, for the first time the expression of CREB and its interaction with the HLA-G in human RCCs has been shown, which might be of clinical relevance.
CRIS-Team Scopus Importer:2020-10-23
Keywords: CREB; HLA-G; Immune cell infiltration; Renal cell carcinoma

Chemoradiotherapy plus hyperthermia (CRTH) versus chemoradiotherapy (CRT) alone in neoadjuvant treatment of soft tissue sarcoma: tumor response, treatment toxicity and disease control - Willner, Alexander; Agaimy, Abbas; Fechner, Katja; Ott, Oliver; Denz, Axel; Weissmann, Thomas; Meidenbauer, Norbert; Höfler, Daniel; Gaipl, Udo; Frey, Benjamin; Schmidt, Manfred; Haller, Florian; et al. (International Journal of Hyperthermia, 2023)
Introduction: Neoadjuvant chemotherapy and radiotherapy for the management of soft tissue sarcomas (STS) are still preferably delivered sequentially, with or without concurrent hyperthermia. Concurrent delivery of chemo-, radio- and thermotherapy may produce synergistic effects and reduce chemotherapy-free intervals. The few available studies suggest that concurrent chemoradiation (CRT) has a greater local effect. Data on the efficacy and toxicity of adding hyperthermia to CRT (CRTH) are sparse. Materials and methods: A cohort of 101 patients with STS of the extremities and trunk who received CRT (n = 33) or CRTH (n = 68) before resection of macroscopic tumor (CRT: n = 19, CRTH: n = 49) or re-resection following a non-oncological resection, so called ‘whoops procedure’, (CRT: n = 14, CRTH: n = 19) were included in this retrospective study. CRT consisted of two cycles of doxorubicine (50 mg/m2 on d2) plus ifosfamide (1500 mg/m2 on d1-5, q28) plus radiation doses of up to 60 Gy. Hyperthermia was delivered in two sessions per week. Results: All patients received the minimum dose of 50 Gy. Median doses of ifosfamide and doxorubicin were comparable between CRT (75%/95%) and CRTH (78%/97%). The median number of hyperthermia sessions was seven. There were no differences in acute toxicities. Major wound complications occurred in 15% (CRT) vs. 25% (CRTH) (p = 0.19). In patients with macroscopic disease, the addition of hyperthermia resulted in a tendency toward improved remission: regression ≥90% occurred in 21/48 (CRTH) vs. 4/18 (CRT) patients (p = 0.197). With a median postoperative follow-up of 72 months, 6-year local control and overall survival rates for CRTH vs. CRT alone were 85 vs. 78% (p = 0.938) and 79 vs. 71% (p = 0.215). Conclusions: Both CRT and CRTH are well tolerated with an expected rate of wound complications. The results suggest that adding hyperthermia may improve tumor response.
CRIS-Team Scopus Importer:2023-09-01
Keywords: chemoradiotherapy; chemotherapy; hyperthermia; neoadjuvant; radiotherapy; Sarcoma; soft-tissue sarcoma; toxicity

Circulating micro-RNAs as potential blood-based markers for early stage breast cancer detection - Schrauder, Michael G.; Strick, Reiner; Schulz-Wendtland, Rüdiger; Strissel, Pamela; Kahmann, Laura; Loehberg, Christian R.; Lux, Michael P.; Jud, Sebastian; Hartmann, Arndt; Hein, Alexander; Bayer, Christian M.; Bani, Mayada; et al. (PLoS ONE, 2012)
Introduction: MicroRNAs (miRNAs, miRs) are a class of small, non-coding RNA molecules with relevance as regulators of gene expression thereby affecting crucial processes in cancer development. MiRNAs offer great potential as biomarkers for cancer detection due to their remarkable stability in blood and their characteristic expression in many different diseases. We investigated whether microarray-based miRNA profiling on whole blood could discriminate between early stage breast cancer patients and healthy controls. Methods: We performed microarray-based miRNA profiling on whole blood of 48 early stage breast cancer patients at diagnosis along with 57 healthy individuals as controls. This was followed by a real-time semi-quantitative Polymerase Chain Reaction (RT-qPCR) validation in a separate cohort of 24 early stage breast cancer patients from a breast cancer screening unit and 24 age matched controls using two differentially expressed miRNAs (miR-202, miR-718). Results: Using the significance level of p<0.05, we found that 59 miRNAs were differentially expressed in whole blood of early stage breast cancer patients compared to healthy controls. 13 significantly up-regulated miRNAs and 46 significantly down-regulated miRNAs in our microarray panel of 1100 miRNAs and miRNA star sequences could be detected. A set of 240 miRNAs that was evaluated by radial basis function kernel support vector machines and 10-fold cross validation yielded a specificity of 78.8%, and a sensitivity of 92.5%, as well as an accuracy of 85.6%. Two miRNAs were validated by RT-qPCR in an independent cohort. The relative fold changes of the RT-qPCR validation were in line with the microarray data for both miRNAs, and statistically significant differences in miRNA-expression were found for miR-202. Conclusions: MiRNA profiling in whole blood has potential as a novel method for early stage breast cancer detection, but there are still challenges that need to be addressed to establish these new biomarkers in clinical use. © 2012 Schrauder et al.
CRIS-Team Scopus Importer:2021-07-19

CLEC10A Is a Specific Marker for Human CD1c+ Dendritic Cells and Enhances Their Toll-Like Receptor 7/8-Induced Cytokine Secretion - Heger, Lukas; Balk, Silke; Lühr, Jennifer; Heidkamp, Gordon Frederik; Lehmann, Christian; Hatscher, Lukas; Purbojo, Ariawan; Hartmann, Arndt; Garcia-Martin, Fayna; Nishimura, Shin-Ichiro; Cesnjevar, Robert; Nimmerjahn, Falk; et al. (Frontiers in Immunology, 2018)
Dendritic cells (DCs) are major players for the induction of immune responses. Apart from plasmacytoid DCs (pDCs), human DCs can be categorized into two types of conventional DCs: CD141+ DCs (cDC1) and CD1c+ DCs (cDC2). Defining uniquely expressed surface markers on human immune cells is not only important for the identification of DC subpopulations but also a prerequisite for harnessing the DC subset-specific potential in immunomodulatory approaches, such as antibody-mediated antigen targeting. Although others identified CLEC9A as a specific endocytic receptor for CD141+ DCs, such a receptor for CD1c+ DCs has not been discovered, yet. By performing transcriptomic and flow cytometric analyses on human DC subpopulations from different lymphohematopoietic tissues, we identified CLEC10A (CD301, macrophage galactose-type C-type lectin) as a specific marker for human CD1c+ DCs. We further demonstrate that CLEC10A rapidly internalizes into human CD1c+ DCs upon binding of a monoclonal antibody directed against CLEC10A. The binding of a CLEC10A-specific bivalent ligand (the MUC-1 peptide glycosylated with N-acetylgalactosamine) is limited to CD1c+ DCs and enhances the cytokine secretion (namely TNFα, IL-8, and IL-10) induced by TLR 7/8 stimulation. Thus, CLEC10A represents not only a candidate to better define CD1c+ DCs-due to its high endocytic potential-CLEC10A also exhibits an interesting candidate receptor for future antigen-targeting approaches.
EVALuna2:34257

Clinical and histopathological characterization of penile carcinomas with focus on HPV-status and histological subtype - Mink, Jan; Khalmurzaev, Oybek; Hoelters, Sebastian; Pryalukhin, Alexey; Heinzelbecker, Julia; Lohse, Stefan; Bende, Kristóf; Loertzer, Hagen; Steffens, Joachim; Jeronimo, Carmen; Wunderlich, Heiko; Bohle, Rainer; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Clinical and pathological associations of PTEN expression in ovarian cancer: a multicentre study from the Ovarian Tumour Tissue Analysis Consortium - Martins, Filipe Correia; Couturier, Dominique Laurent; Paterson, Anna; Karnezis, Anthony N.; Chow, Christine; Nazeran, Tayyebeh M.; Odunsi, Adekunle; Gentry-Maharaj, Aleksandra; Vrvilo, Aleksandra; Hein, Alexander; Talhouk, Aline; Osorio, Ana; et al. (British Journal of Cancer, 2020)
Background: PTEN loss is a putative driver in histotypes of ovarian cancer (high-grade serous (HGSOC), endometrioid (ENOC), clear cell (CCOC), mucinous (MOC), low-grade serous (LGSOC)). We aimed to characterise PTEN expression as a biomarker in epithelial ovarian cancer in a large population-based study. Methods: Tumours from 5400 patients from a multicentre observational, prospective cohort study of the Ovarian Tumour Tissue Analysis Consortium were used to evaluate associations between immunohistochemical PTEN patterns and overall survival time, age, stage, grade, residual tumour, CD8+ tumour-infiltrating lymphocytes (TIL) counts, expression of oestrogen receptor (ER), progesterone receptor (PR) and androgen receptor (AR) by means of Cox proportional hazard models and generalised Cochran–Mantel–Haenszel tests. Results: Downregulation of cytoplasmic PTEN expression was most frequent in ENOC (most frequently in younger patients; p value = 0.0001) and CCOC and was associated with longer overall survival in HGSOC (hazard ratio: 0.78, 95% CI: 0.65–0.94, p value = 0.022). PTEN expression was associated with ER, PR and AR expression (p values: 0.0008, 0.062 and 0.0002, respectively) in HGSOC and with lower CD8 counts in CCOC (p value < 0.0001). Heterogeneous expression of PTEN was more prevalent in advanced HGSOC (p value = 0.019) and associated with higher CD8 counts (p value = 0.0016). Conclusions: PTEN loss is a frequent driver in ovarian carcinoma associating distinctly with expression of hormonal receptors and CD8+ TIL counts in HGSOC and CCOC histotypes.
CRIS-Team Scopus Importer:2020-06-26

Clinical behavior of chromophobe renal cell carcinoma is less aggressive than that of clear cell renal cell carcinoma, independent of Fuhrman grade or tumor size - Steffens, Sandra; Roos, Frederik C.; Janssen, Martin; Becker, Frank; Steinestel, Julie; Abbas, Mahmoud; Steinestel, Konrad; Wegener, Gerd; Siemer, Stefan; Thueroff, Joachim W.; Hofmann, Rainer; Stoeckle, Michael; et al. (Virchows Archiv, 2014)
Chromophobe renal cell carcinoma (chRCC) is the third most common subtype of RCC, after clear cell (ccRCC) and papillary RCC. Its lower incidence and frequent exclusion from clinical trials might be why chRCC characteristics have not been extensively studied. The aim of our study was to examine tumor characteristics and long-term prognosis of chRCC compared to ccRCC. We collected 4,210 evaluable patients subjected to surgery for chRCC (n = 176) or ccRCC (n = 4,034) at five centers in Germany (University Hospitals of Hannover, Homburg/Saar, Mainz, Ulm, and Marburg) between 1990 and 2010. Patients with chRCC were significantly younger (mean, 60.1 vs. 62.1 years) and tended to be more frequently female (43.8 vs. 36.5 %). Although Fuhrman grade and median tumor diameter were not significantly different, significantly fewer patients with chRCC than with ccRCC presented with high tumor stage or metastasis at diagnosis (18.5 vs. 43.8 %). Moreover, significantly more chRCC patients were treated with partial nephrectomy (41.5 vs. 26.2 %). Accordingly, 5-year cancer-specific survival (CSS) rates were 83.2 % for chRCC against 75.8 % for ccRCC patients (p = 0.014, log rank). However, in multivariate analysis, chromophobe subtype was not confirmed as a significant positive prognostic factor for RCC (HR 0.88, 95 % CI 0.63-1.24; p = 0.48 Cox regression). This is one of the largest studies to date showing that chRCC is associated with a significantly lower risk of locally invasive tumor growth and metastatic disease than ccRCC. We conclude that the clinical behavior of chRCC is less aggressive than that of ccRCC, independent of Fuhrman grade or tumor size.
EVALuna2:6677

Clinical Characteristics and Prognosis of HER2-0 and HER2-Low-Positive Breast Cancer Patients: Real-World Data from Patients Treated with Neoadjuvant Chemotherapy - Pöschke, Patrik; Fasching, Peter; Adler, Werner; Rübner, Matthias; Beckmann, Matthias; Hack, Carolin; Heindl, Felix; Hartmann, Arndt; Erber, Ramona; Gaß, Paul (Cancers, 2023)
In our study, we observed the long-term survival outcomes investigated for HER2-0 and HER2-low-positive breast cancer patients who received neoadjuvant chemotherapy. Between 1998 and 2020, 10,333 patients with primary breast cancer were treated, including 1373 patients with HER2-0 or HER2-low-positive disease with neoadjuvant chemotherapy. Descriptive analyses were performed, and logistic regression models and survival analyses were calculated for disease-free survival (DFS) and overall survival (OS). Among the 1373 patients, 930 (67.73%) had HER2-low-positive and 443 (32.27%) had HER2-0 tumors. Patients with HER2-0 tumors had a significantly better pathological complete response, 29.25% vs. 20.09%, and pathological complete response/in situ, 31.97% vs. 24.08%, than patients with HER2-low-positive tumors (p < 0.001; p = 0.003), regardless of the hormone receptor (HR) status. No statistically significant differences were observed for the HR-positive (p = 0.315; p = 0.43) or HR-negative subgroups (p = 0.573; p = 0.931). DFS and OS were significantly longer for HR-positive, HER2-low-positive patients (log-rank p = 0.02; p = 0.012). OS was significantly longer for HR-negative, HER2-0 patients (log-rank p = 0.032). No significant DFS differences were found for the HR-negative cohort (log-rank p = 0.232). For the overall cohort, no significant differences were noted between HER2-low-positive and HER2-0 patients, either for DFS (log-rank p = 0.220) or OS (log-rank p = 0.403). These results show different survival outcomes for HER2-0 and HER2-low-positive tumors relative to HR status. These different cohorts can be identified using standardized immunohistochemistry, even retrospectively.
CRIS-Team Scopus Importer:2023-10-20
Keywords: breast cancer; HER2; HER2-0; HER2-low-positive; neoadjuvant therapy; prognosis

Clinical performance of Immunoscore (R) in early colon cancer in the Asian population - Galon, J.; Kawakami, Y.; Torigoe, T.; Wang, Y.; Patel, P. S.; Vora, H.; Mlecnik, B.; Marliot, F.; Bifulco, C. B.; Lugli, A.; Nagtegaal, I. D.; Hartmann, Arndt; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2021-01-15

Clinical Performance of QIAGEN Fibroblast Growth Factor Receptor (FGFR) Assay for the Detection of FGFR Alterations in Erdafitinib-Treated Patients with Metastatic or Locally Advanced, Surgically Unresectable, Urothelial Cancer - Major, C.; Wang, S.; Burgess, M.; English, A.; Sweeney, M.; Hartmann, Arndt (JOURNAL OF MOLECULAR DIAGNOSTICS, 2019)
CRIS-Team WoS Importer:2021-10-18

Clinical Performance of the Consensus Immunoscore in Colon Cancer in the Asian Population from the Multicenter International SITC Study - Mlecnik, Bernhard; Torigoe, Toshihiko; Bindea, Gabriela; Popivanova, Boryana; Xu, Mingli; Fujita, Tomonobu; Hazama, Shoichi; Suzuki, Nobuaki; Nagano, Hiroaki; Okuno, Kiyotaka; Hirohashi, Yoshihiko; Furuhata, Tomohisa; et al. (Cancers, 2022)
BACKGROUND: In this study, we evaluated the prognostic value of Immunoscore in patients with stage I–III colon cancer (CC) in the Asian population. These patients were originally included in an international study led by the Society for Immunotherapy of Cancer (SITC) on 2681 patients with AJCC/UICC-TNM stages I–III CC. METHODS: CD3+ and cytotoxic CD8+ T-lymphocyte densities were quantified in the tumor and invasive margin by digital pathology. The association of Immunoscore with prognosis was evaluated for time to recurrence (TTR), disease-free survival (DFS), and overall survival (OS). RESULTS: Immunoscore stratified Asian patients (n = 423) into different risk categories and was not impacted by age. Recurrence-free rates at 3 years were 78.5%, 85.2%, and 98.3% for a Low, Intermediate, and High Immunoscore, respectively (HR[Low-vs-High] = 7.26 (95% CI 1.75−30.19); p = 0.0064). A High Immunoscore showed a significant association with prolonged TTR, OS, and DFS (p < 0.05). In Cox multivariable analysis stratified by center, Immunoscore association with TTR was independent (HR[Low-vs-Int+High] = 2.22 (95% CI 1.10–4.55) p = 0.0269) of the patient’s gender, T-stage, N-stage, sidedness, and MSI status. A significant association of a High Immunoscore with prolonged TTR was also found among MSS (HR[Low-vs-Int+High] = 4.58 (95% CI 2.27−9.23); p ≤ 0.0001), stage II (HR[Low-vs-Int+High] = 2.72 (95% CI 1.35−5.51); p = 0.0052), low-risk stage-II (HR[Low-vs-Int+High] = 2.62 (95% CI 1.21−5.68); p = 0.0146), and high-risk stage II patients (HR[Low-vs-Int+High] = 3.11 (95% CI 1.39−6.91); p = 0.0055). CONCLUSION: A High Immunoscore is significantly associated with the prolonged survival of CC patients within the Asian population.
CRIS-Team Scopus Importer:2022-10-07
Keywords: Asian; classification; colon cancer; immune response; Immunoscore; MSI; prognostic markers; risk stratification; T cell; tumor microenvironment

Clinical relevance of miR-mediated HLA-G regulation and the associated immune cell infiltration in renal cell carcinoma - Jasinski-Bergner, Simon; Stoehr, Christine; Bukur, Juergen; Massa, Chiara; Braun, Juliane; Huettelmaier, Stefan; Spath, Verena; Wartenberg, Roland; Legal, Wolfgang; Taubert, Helge; Wach, Sven; Wullich, Bernd; et al. (OncoImmunology, 2015)
In human tumors of distinct origin including renal cell carcinoma (RCC), the non-classical human leukocyte antigen G (HLA-G) is frequently expressed, thereby inhibiting the cytotoxic activity of T and natural killer (NK) cells. Recent studies demonstrated a strong post-transcriptional gene regulation of the HLA-G by miR-152, -148A, -148B and -133A. Standard methods were applied to characterize the expression and function of HLA-G, HLA-G-regulatory microRNAs (miRs) and the immune cell infiltration in 453 RCC lesions using a tissue microarray and five RCC cell lines linking these results to clinical parameters. Direct interactions with HLA-G regulatory miRs and the HLA-G 3' untranslated region (UTR) were detected and the affinities of these different miRs to the HLA-G 3'-UTR compared. qPCR analyses and immunohistochemical staining revealed an inverse expression of miR-148A and -133A with the HLA-G protein in situ and in vitro. Stable miR overexpression caused a downregulation of HLA-G protein enhancing the NK and LAK cell-mediated cytotoxicity in in vitro CD107a activation assays revealing a HLA-G-dependent cytotoxic activity of immune effector cells. A significant higher frequency of CD3(+)/CD8(+) T cell lymphocytes, but no differences in the activation markers CD69, CD25 or in the presence of CD56(+), FoxP3(+) and CD4(+) immune cells were detected in HLA-G(+) compared to HLA-G(-) RCC lesions. This could be associated with higher WHO grade, but not with a disease-specific survival. These data suggest a miR-mediated control of HLA-G expression in RCC, which is associated with a distinct pattern of immune cell infiltration.
EVALuna2:6743

Clinical utility of the S3-score for molecular prediction of outcome in non-metastatic and metastatic clear cell renal cell carcinoma - Buettner, Florian; Winter, Stefan; Rausch, Steffen; Hennenlotter, Joerg; Kruck, Stephan; Stenzl, Arnulf; Scharpf, Marcus; Fend, Falko; Agaimy, Abbas; Hartmann, Arndt; Bedke, Jens; Schwab, Matthias; et al. (BMC Medicine, 2018)
BACKGROUND: Stratification of cancer patients to identify those with worse prognosis is increasingly important. Through in silico analyses, we recently developed a gene expression-based prognostic score (S3-score) for clear cell renal cell carcinoma (ccRCC), using the cell type-specific expression of 97 genes within the human nephron. Herein, we verified the score using whole-transcriptome data of independent cohorts and extend its application for patients with metastatic disease receiving tyrosine kinase inhibitor treatment. Finally, we sought to improve the signature for clinical application using qRT-PCR. METHODS: A 97 gene-based S3-score (S397) was evaluated in a set of 52 primary non-metastatic and metastatic ccRCC patients as well as in 53 primary metastatic tumors of sunitinib-treated patients. Gene expression data of The Cancer Genome Atlas (n = 463) was used for platform transfer and development of a simplified qRT-PCR-based 15-gene S3-score (S315). This S315-score was validated in 108 metastatic and non-metastatic ccRCC patients and ccRCC-derived metastases including in part several regions from one metastasis. Univariate and multivariate Cox regression stratified by T, N, M, and G were performed with cancer-specific and progression-free survival as primary endpoints. RESULTS: The S397-score was significantly associated with cancer-specific survival (CSS) in 52 ccRCC patients (HR 2.9, 95% Cl 1.0-8.0, PLog-rank = 3.3 × 10-2) as well as progression-free survival in sunitinib-treated patients (2.1, 1.1-4.2, PLog-rank = 2.2 × 10-2). The qRT-PCR based S315-score performed similarly to the S397-score, and was significantly associated with CSS in our extended cohort of 108 patients (5.0, 2.1-11.7, PLog-rank = 5.1 × 10-5) including metastatic (9.3, 1.8-50.0, PLog-rank = 2.3 × 10-3) and non-metastatic patients (4.4, 1.2-16.3, PLog-rank = 1.6 × 10-2), even in multivariate Cox regression, including clinicopathological parameters (7.3, 2.5-21.5, PWald = 3.3 × 10-4). Matched primary tumors and metastases revealed similar S315-scores, thus allowing prediction of outcome from metastatic tissue. The molecular-based qRT-PCR S315-score significantly improved prediction of CSS by the established clinicopathological-based SSIGN score (P = 1.6 × 10-3). CONCLUSION: The S3-score offers a new clinical avenue for ccRCC risk stratification in the non-metastatic, metastatic, and sunitinib-treated setting.
EVALuna2:34608

Clinical utility of the simplified 15-gene S3-score for prediction of outcome in clear cell renal cell carcinoma - Buettner, F.; Winter, S.; Rausch, S.; Hennenlotter, J.; Kruck, S.; Stenzl, A.; Scharpf, M.; Fend, F.; Agaimy, Abbas; Hartmann, Arndt; Bedke, J.; Schwab, M.; et al. (NAUNYN-SCHMIEDEBERGS ARCHIVES OF PHARMACOLOGY, 2019)
CRIS-Team WoS Importer:2019-02-21

cMET: a prognostic marker in papillary renal cell carcinoma? - Erlmeier, Franziska; Bruecher, Benedict; Stoehr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Ströbel, Philipp; Becker, Frank; Wülfing, Christian; Barth, Peter; Stöckle, Michael; et al. (Human Pathology, 2022)
The tyrosine-protein kinase c-Met plays a decisive role in numerous cellular processes, as a proto-oncogene that supports aggressive tumor behavior. It is still unknown whether c-Met could be relevant for prognosis of papillary RCC (pRCC). Specimen collection was a collaboration of the PANZAR consortium. Patients' medical history and tumor specimens were collected from 197 and 110 patients with type 1 and 2 pRCC, respectively. Expression of cMET was determined by immunohistochemistry. In total, cMET staining was evaluable in of 97 of 197 type 1 and 63 of 110 type 2 pRCC cases. Five-year overall survival revealed no significant difference in dependence of cMET positivity (cMET− vs. cMET+: pRCC type 1: 84.8% vs. 80.3%, respectively [p = 0.303, log-rank]; type 2: 71.4% vs. 64.4%, respectively [p = 0.239, log-rank]). Interestingly, the subgroup analyses showed a significant difference for cMET expression in T stage and metastases of the pRCC type 2 (p = 0.014, p = 0.022, chi-square). The cMET-positive type 2 collective developed more metastases than the cMET-negative cohort (pRCC type 2 M+: cMET−: 2 [4.3%] vs. cMET+: 12 [19%]). cMET expression did not qualify as a prognostic marker in pRCC for overall survival.
CRIS-Team Scopus Importer:2022-02-04
Keywords: cMET; Outcome; Papillary renal cell carcinoma; Prognosis; Survival

c-Met in chromophobe renal cell carcinoma - Erlmeier, Franziska; Ivanyi, Philipp; Hartmann, Arndt; Autenrieth, Michael; Wiedemann, Max; Weichert, Wilko; Steffens, Sandra (Medical Oncology, 2017)
c-Met plays a role as a prognostic marker in clear cell renal cell carcinoma. In addition, recently the tyrosine kinase inhibitor cabozantinib targeting c-Met was approved for the treatment of advanced renal cell carcinoma (RCC). In contrast to clear cell RCC, little is known about c-Met expression patterns in rarer RCC subtypes. The aim of this study was to evaluate the prevalence, distribution and prognostic impact of c-Met expression on chromophobe (ch)RCC. Patients who underwent renal surgery due to chRCC were retrospectively evaluated. Tumor specimens were analyzed for c-Met expression by immunohistochemistry. Expression data were associated with clinicopathological parameters including patient survival. Eighty-one chRCC patients were eligible for analysis. Twenty-four (29.6%) patients showed a high c-Met expression (c-Met(high), staining intensity higher than median). Our results showed an association between c-Met(high) expression and the existence of lymph node metastasis (p = 0.007). No further significant clinicopathological associations with c-Met were identified, also regarding c-Met expression and overall survival. In conclusion, to our knowledge this is the first study evaluating the prognostic impact of c-Met in a considerably large cohort of chRCC. High c-Met expression is associated with the occurrence of lymph node metastasis. This indicates that c-Met might be implicated into metastatic progression in chRCC.
EVALuna2:6842

c-MET Oncogene in Renal Cell Carcinomas - Erlmeier, F.; Weichert, W.; Autenrieth, M.; Ivanyi, P.; Hartmann, Arndt; Steffens, S. (Aktuelle Urologie, 2016)
c-Met plays a significant role in multiple cellular processes. Being encoded by a proto-oncogene, tyrosine kinase supports aggressive tumour behaviour such as tumour invasiveness and formation of metastases. For some subtypes of renal cell carcinoma studies have shown a association between c-Met expression and clinical outcome or prognosis. Therefore, c-Met represents a prognostic marker in renal cell carcinoma.Furthermore, c-MET will play a decisive role as a possible target for targeted therapies in the era of personalised medicine. Especially for RCC, the dual inhibition of VEGF and c-MET tyrosine kinase in cases of metastatic, treatment-resistant tumours is gaining clinical relevance. The role of c-Met has not been fully elucidated for all subtypes of renal cell carcinomas. The relevance of c-Met for the remaining subtypes of renal tumours has yet to be clarified.
EVALuna2:6923

Collecting duct carcinoma versus renal medullary carcinoma: an appeal for nosologic and biological clarity - Amin, Mahul B.; Smith, Steven C.; Agaimy, Abbas; Argani, Pedram; Comperat, Eva Marie; Delahunt, Brett; Epstein, Jonathan I.; Eble, John N.; Grignon, David J.; Hartmann, Arndt; Hes, Ondrej; Hirsch, Michelle S.; et al. (American Journal of Surgical Pathology, 2014)
EVALuna2:6697

Colonic Adenocarcinomas Harboring NTRK Fusion Genes: A Clinicopathologic and Molecular Genetic Study of 16 Cases and Review of the Literature - Lasota, Jerzy; Chłopek, Małgorzata; Lamoureux, Jennifer; Christiansen, Jason; Kowalik, Artur; Wasąg, Bartosz; Felisiak-Gołąbek, Anna; Agaimy, Abbas; Biernat, Wojciech; Canzonieri, Vincenzo; Centonze, Giovanni; Chmielik, Ewa; et al. (American Journal of Surgical Pathology, 2020)
This study was undertaken to determine the frequency, and the clinicopathologic and genetic features, of colon cancers driven by neurotrophic receptor tyrosine kinase (NTRK) gene fusions. Of the 7008 tumors screened for NTRK expression using a pan-Trk antibody, 16 (0.23%) had Trk immunoreactivity. ArcherDx assay detected TPM3-NTRK1 (n=9), LMNA-NTRK1 (n=3), TPR-NTRK1 (n=2) and EML4-NTRK3 (n=1) fusion transcripts in 15 cases with sufficient RNA quality. Patients were predominantly women (median age: 63 y). The tumors involved the right (n=12) and left colon unequally and were either stage T3 (n=12) or T4. Local lymph node and distant metastases were seen at presentation in 6 and 1 patients, respectively. Lymphovascular invasion was present in all cases. Histologically, tumors showed moderate to poor (n=11) differentiation with a partly or entirely solid pattern (n=5) and mucinous component (n=10), including 1 case with sheets of signet ring cells. DNA mismatch repair-deficient phenotype was seen in 13 cases. Tumor-infiltrating CD4/CD8 lymphocytes were prominent in 9 cases. Programmed death-ligand 1 positive tumor-infiltrating immune cells and focal tumor cell positivity were seen in the majority of cases. CDX2 expression and loss of CK20 and MUC2 expression were frequent. CK7 was expressed in 5 cases. No mutations in BRAF, RAS, and PIK3CA were identified. However, other genes of the PI3K-AKT/MTOR pathway were mutated. In several cases, components of Wnt/β-catenin (APC, AMER1, CTNNB1), p53, and TGFβ (ACVR2A, TGFBR2) pathways were mutated. However, no SMAD4 mutations were found. Two tumors harbored FBXW7 tumor suppressor gene mutations. NTRK fusion tumors constitute a distinct but rare subgroup of colorectal carcinomas.
CRIS-Team Scopus Importer:2020-01-21

Colorectal Adenocarcinomas Harboring ALK Fusion Genes: A Clinicopathologic and Molecular Genetic Study of 12 Cases and Review of the Literature. - Lasota, Jerzy; Chlopek, Malgorzata; Wasag, Bartosz; Kowalik, Artur; Christiansen, Jason; Lamoureux, Jennifer; Kuzniacka, Alina; Felisiak-Golabek, Anna; Liu, Yalan; Reyes, Tiffany Ashley R.; Saha, Rishabh; Agaimy, Abbas; et al. (American Journal of Surgical Pathology, 2020)
This study determined the frequency and the clinicopathologic and genetic features of colorectal carcinomas driven by oncogenic fusions of the anaplastic lymphoma kinase gene (ALK). Of the 8150 screened tumors, 12 (0.15%) were immunohistochemically ALK-positive with D5F3 antibody. These cancers harbored CAD-ALK (n=1), DIAPH2-ALK (n=2), EML4-ALK (n=2), LOC101929227-ALK (n=1), SLMAP-ALK (n=1), SPTBN1-ALK (n=4), and STRN-ALK (n=1) fusions, as detected by an RNA-based next-generation sequencing assay. ALK fusion carcinomas were diagnosed mostly in older patients with a 9:3 female predominance (median age: 72 y). All tumors, except a rectal one, occurred in the right colon. Most tumors were stage T3 (n=7) or T4 (n=3). Local lymph node and distant metastases were seen at presentation in 9 and 2 patients. These tumors showed moderate (n=6) or poor (n=3) glandular differentiation, solid medullary growth pattern (n=2), and pure mucinous morphology (n=1). DNA mismatch repair-deficient phenotype was identified in 10 cases. Tumor-infiltrating lymphocytes were prominent in 9 carcinomas. In 4 carcinomas, tumor cells showed strong, focal (n=3), or diffuse programmed death-ligand 1 immunoreactivity. CDX2 expression and loss of CK20 and MUC2 expression were frequent. CK7 was expressed in 5 tumors. Four patients died of disease within 3 years, and 7 were alive with follow-up ranging from 1 to 8 years. No mutations in BRAF, RAS, and in genes encoding components of PI3K-AKT/MTOR pathway were identified. However, 1 tumor had a loss-of-function PTEN mutation. Aberration of p53 signaling, TP53 mutations, and/or nuclear accumulation of p53 protein was seen in 9 cases. ALK fusion colorectal carcinomas are a distinct and rare subtype of colorectal cancers displaying some features of mismatch repair-deficient tumors.
EVALuna2:252946

Combination of 5-fluorouracil and thymoquinone targets stem cell gene signature in colorectal cancer cells - Ndreshkjana, Benardina; Capci Karagöz, Aysun; Klein, Volker; Chanvorachote, Pithi; Muenzner, Julienne K.; Hübner, Kerstin; Steinmann, Sara; Erlenbach-Wuensch, Katharina; Geppert, Carol-Immanuel; Agaimy, Abbas; Ballout, Farah; El-Baba, Chirine; et al. (Cell Death & Disease, 2019)
Cancer stem cells (CSCs) residing in colorectal cancer tissues have tumorigenic capacity and contribute to chemotherapeutic resistance and disease relapse. It is well known that the survival of colorectal CSCs after 5-fluorouracil (5-FU)-based therapy leads to cancer recurrence. Thus CSCs represent a promising drug target. Here, we designed and synthesized novel hybrid molecules linking 5-FU with the plant-derived compound thymoquinone (TQ) and tested the potential of individual compounds and their combination to eliminate colorectal CSCs. Both, Combi and SARB hybrid showed augmented cytotoxicity against colorectal cancer cells, but were non-toxic to organoids prepared from healthy murine small intestine. NanoString analysis revealed a unique signature of deregulated gene expression in response to the combination of TQ and 5-FU (Combi) and SARB treatment. Importantly, two principle stem cell regulatory pathways WNT/ß-Catenin and PI3K/AKT were found to be downregulated after Combi and hybrid treatment. Furthermore, both treatments strikingly eliminated CD133+ CSC population, accompanying the depleted self-renewal capacity by eradicating long-term propagated 3D tumor cell spheres at sub-toxic doses. In vivo xenografts on chicken eggs of SARB-treated HCT116 cells showed a prominent nuclear ß-Catenin and E-cadherin staining. This was in line with the reduced transcriptional activity of ß-Catenin and diminished cell adhesion under SARB exposure. In contrast to 5-FU, both, Combi and SARB treatment effectively reduced the angiogenic capacity of the remaining resistant tumor cells. Taken together, combination or hybridization of single compounds target simultaneously a broader spectrum of oncogenic pathways leading to an effective eradication of colorectal cancer cells.
CRIS-Team Scopus Importer:2019-05-28

Combination of an ultrafast TWIST-VIBE Dixon sequence protocol and diffusion-weighted imaging into an accurate easily applicable classification tool for masses in breast MRI - Peter, Sandra C.; Wenkel, Evelyn; Weiland, Elisabeth; Dietzel, Matthias; Janka, Rolf Matthias; Hartmann, Arndt; Emons, Julius; Uder, Michael; Ellmann, Stephan (European Radiology, 2020)
Objectives: This study aimed to develop a tool for the classification of masses in breast MRI, based on ultrafast TWIST-VIBE Dixon (TVD) dynamic sequences combined with DWI. TVD sequences allow to abbreviate breast MRI protocols, but provide kinetic information only on the contrast wash-in, and because of the lack of the wash-out kinetics, their diagnostic value might be hampered. A special focus of this study was thus to maintain high diagnostic accuracy in lesion classification. Materials and methods: Sixty-one patients who received breast MRI between 02/2014 and 04/2015 were included, with 83 reported lesions (60 malignant). Our institute’s standard breast MRI protocol was complemented by an ultrafast TVD sequence. ADC and peak enhancement of the TVD sequences were integrated into a generalised linear model (GLM) for malignancy prediction. For comparison, a second GLM was calculated using ADC and conventional DCE curve type. The resulting GLMs were evaluated for standard diagnostic parameters. For easy application of the GLMs, nomograms were created. Results: The GLM based on peak enhancement of the TVD and ADC was as equally accurate as the GLM based on conventional DCE and ADC, with no significant differences (sensitivity, 93.3%/93.3%; specificity, 91.3%/87.0%; PPV, 96.6%/94.9%; NPV, 84.0%/83.3%; all, p ≥ 0.315). Conclusions: This study presents a method to integrate ultrafast TVD sequences into a breast MRI protocol, allowing a reduction of the examination time while maintaining diagnostic accuracy. A GLM based on the combination of TVD-derived peak enhancement and ADC provides high diagnostic accuracy, and can be easily applied using a nomogram. Key Points: • Ultrafast TWIST-VIBE Dixon sequence protocols in combination with diffusion-weighted imaging allow to shorten breast MRI examinations, while diagnostic accuracy is maintained. • Integrating peak enhancement from the TWIST-VIBE Dixon sequence and the apparent diffusion coefficient into a generalised linear model provides a comprehensible image evaluation approach. • This approach is further facilitated by nomograms.
CRIS-Team Scopus Importer:2020-02-11
Keywords: Breast cancer; Diagnostic imaging; Diffusion magnetic resonance imaging; Magnetic resonance imaging; Statistical model

Combination of CK20 and Ki-67 Immunostaining Analysis Predicts Recurrence, Progression, and Cancer-Specific Survival in pT1 Urothelial Bladder Cancer - Bertz, Simone; Otto, Wolfgang; Denzinger, Stefan; Wieland, Wolf F.; Burger, Maximilian; Stoehr, Robert; Link, Stefan; Hofstaedter, Ferdinand; Hartmann, Arndt (European Urology, 2014)
The prognostic value of CK20, Ki-67, and p53 has been investigated for non-muscle-invasive urothelial bladder cancers but not for the distinct and clinically challenging subset of pT1 bladder cancers.To evaluate the prognostic value of CK20, Ki-67, and p53 within the largest series of pT1 urothelial bladder cancers.Data from 309 patients with pT1 urothelial bladder cancer from one single urologic centre were collected.Adjuvant instillation of bacillus Calmette-Guérin was performed in each patient. A second resection was performed after 4-8 wk. A total of 76 patients underwent cystectomy.We conducted histomorphologic analysis; immunohistochemistry for CK20, Ki-67, and p53; and univariate and multivariate Cox regression models including recurrence-free survival (RFS), progression-free survival (PFS), and cancer-specific survival (CSS).At a median follow-up of 49 mo, we found recurrence and progression and disease-specific mortality rates of 22.7%, 20.1%, and 15.9%, respectively. CK20 expression was significantly correlated with RFS in multivariate analysis (hazard ratio [HR]: 5.89; 95% confidence interval [CI], 1.44-24.15; p=0.014). In multivariate analysis, Ki-67 was the only marker significantly correlated with PFS (HR: 2.80; 95% CI, 1.45-5.43, p=0.002). Ki-67 (HR: 3.83; 95% CI, 1.59-9.26; p=0.003), and CK20 (HR: 8.44; 95% CI,1.16-61.34; p=0.035) were significantly correlated with CSS in multivariate analysis. The combination of CK20 and Ki-67 showed significantly worse RFS (p=0.026), PFS (p=0.003), and CSS (p<0.001) in tumours with a high proliferation index and abnormal CK20 expression. A retrospective study design was the major limitation of this study.Our present analysis of the largest series of patients with pT1 urothelial bladder cancer published to date found Ki-67 and CK20 to be potential prognostic markers improving the risk stratification of pT1 bladder tumours. They are reliable indicators of biologic aggressiveness and may contribute to decision making on therapeutic strategy for pT1 bladder carcinomas.
EVALuna2:6465

Combination of GP88 Expression in Tumor Cells and Tumor-Infiltrating Immune Cells Is an Independent Prognostic Factor for Bladder Cancer Patients - Eckstein, Markus; Lieb, Verena; Jung, Rudolf; Sikic, Danijel; Weigelt, Katrin; Stöhr, Robert; Geppert, Carol-Immanuel; Weyerer, Veronika; Bertz, Simone; Serrero, Ginette; Yue, Binbin; Hartmann, Arndt; et al. (Cells, 2021)
Urothelial bladder cancer (BCa) is the ninth most commonly diagnosed cancer worldwide and accounts for approximately 3% of global cancer diagnoses. We are interested in prognostic markers that may characterize tumor cells (TCs) and immune cells (ICs) and their relationship in BCa. A potential candidate marker that meets these criteria is progranulin (GP88), which is expressed separately in TCs and ICs. We analyzed GP88 expression by immunohistochemistry (IHC) in 196 muscle-invasive BCa samples using a tissue microarray. The immunoreactive score for GP88 staining in TCs and the percentage of GP88-positive ICs was determined. An easy cutoff for the staining status of TCs (positive vs. negative) and ICs (0% vs. >0%) and, more generally, negative vs. positive GP88 staining could be applied. We detected 93 patients (47.4%) and 92 patients (46.9%) with GP88-positive TCs or ICs, respectively. The IHC results were correlated with clinicopathological and survival data. Positive GP88 staining in TCs appeared to be an independent poor prognostic factor for disease-specific survival (DSS) (RR (relative risk) = 1.74; p = 0.009) and recurrence-free survival (RFS) (RR = 1.92; p = 0.002). In contrast, negative GP88 staining in ICs was an independent negative predictor for overall survival (OS) (RR = 2.18; p < 0.001), DSS (RR = 2.84; p < 0.001) and RFS (RR = 2.91; p < 0.001) in multivariate Cox's regression analysis. When combining GP88 staining in TCs and ICs, a specific combination of GP88-positive TCs and GP88-negative ICs was associated with a 2.54-fold increased risk of death, a 4.21-fold increased risk of disease-specific death and a 4.81-fold increased risk of recurrence compared to GP88-negative TCs and GP88-positive ICs. In summary, GP88 positivity in TCs is a negative prognostic factor for DSS and RFS. In addition, GP88 positivity can mark ICs that are associated with a good prognosis (OS, DSS and RFS). The combination of GP88 staining in TCs and ICs appears to be a significant independent prognostic biomarker in muscle-invasive BCa.
CRIS-Team WoS Importer:2021-08-06

Combination of growth pattern and tumor regression identifies a high-risk group in neoadjuvant treated rectal cancer patients - Jeßberger, Jonas; Erlenbach-Wuensch, Katharina; Posselt, Rebecca; Haderlein, Marlen; Agaimy, Abbas; Fietkau, Rainer; Hartmann, Arndt; Distel, Luitpold (Journal of Digestive Diseases, 2017)
To analyze the prognostic effect of E-cadherin expression, the growth pattern of the tumor and the regression grade in a rectal cancer cohort treated with neoadjuvant radiochemotherapy (RCT).A total of 223 patients with rectal cancer treated with neoadjuvant RCT followed by surgery were included. Altogether 88 biopsies prior to RCT and 213 tumor resections in an average of 55 days post-RCT were investigated. Protein expression of E-cadherin and tumor growth pattern (solid glandular vs single-cell pattern) was assessed by staining tissue microarrays. The regression grade at the invasion front was determined according to the Dworak scale.There was a significant decrease of E-cadherin expression (P = 0.002) and a significant increased single-cell growth (P < 0.001) at the invasion front in tumor samples after RCT compared with primary biopsies of the tumor. A low E-cadherin expression in the biopsy was related to a longer metastasis-free survival (P = 0.033) and tumor-specific survival (P = 0.030). Post-RCT single-cell growth at the tumor invasion front was a prognostic factor for longer tumor-specific survival (P = 0.021). A combination of growth pattern and the Dworak regression grade was an independent prognostic parameter for tumor-specific survival (P = 0.015).Loss of E-cadherin protein expression in the pretreatment biopsy of rectal cancer is associated with fewer metastases and improved survival. Furthermore, the growth pattern in the post-RCT resection specimen has a prognostic value for survival. A combination of growth pattern and tumor regression score (the RegPat score) showed the highest discriminatory power to identify high-risk patients.
EVALuna2:6858

Combined DNA methylation and gene expression profiling in gastrointestinal stromal tumors reveals hypomethylation of SPP1 as an independent prognostic factor - Haller, Florian; Zhang, Jitao David; Moskalev, Evgeny; Braun, Alexander; Otto, Claudia; Geddert, Helene; Riazalhosseini, Yasser; Ward, Aoife; Balwierz, Aleksandra; Schaefer, Inga-Marie; Cameron, Silke; Ghadimi, B. Michael; et al. (International Journal of Cancer, 2015)
Gastrointestinal stromal tumors (GISTs) have distinct gene expression patterns according to localization, genotype and aggressiveness. DNA methylation at CpG dinucleotides is an important mechanism for regulation of gene expression. We performed targeted DNA methylation analysis of 1.505 CpG loci in 807 cancer-related genes in a cohort of 76 GISTs, combined with genome-wide mRNA expression analysis in 22 GISTs, to identify signatures associated with clinicopathological parameters and prognosis. Principal component analysis revealed distinct DNA methylation patterns associated with anatomical localization, genotype, mitotic counts and clinical follow-up. Methylation of a single CpG dinucleotide in the non-CpG island promoter of SPP1 was significantly correlated with shorter disease-free survival. Hypomethylation of this CpG was an independent prognostic parameter in a multivariate analysis compared to anatomical localization, genotype, tumor size and mitotic counts in a cohort of 141 GISTs with clinical follow-up. The epigenetic regulation of SPP1 was confirmed in vitro, and the functional impact of SPP1 protein on tumorigenesis-related signaling pathways was demonstrated. In summary, SPP1 promoter methylation is a novel and independent prognostic parameter in GISTs, and might be helpful in estimating the aggressiveness of GISTs from the intermediate-risk category.
EVALuna2:6650

Combined miR-486 and GP88 (Progranulin) Serum Levels Are Suggested as Supportive Biomarkers for Therapy Decision in Elderly Prostate Cancer Patients - Fichte, Alexander; Neumann, Anna-Dorothea; Weigelt, Katrin; Guzman, Juan; Jansen, Thilo; Keinert, Julia; Serrero, Ginette; Yue, Binbin; Stöhr, Robert; Greither, Thomas; Hartmann, Arndt; Wullich, Bernd; et al. (Life, 2022)
Our study aimed to assess the applicability of miR-486 in combination with soluble GP88 protein as a diagnostic and/or predictive biomarker for prostate cancer (PCa) patients. miR-486 and GP88 levels in serum samples from 136 patients undergoing MRI-guided biopsy of the prostate were assessed by qRT–PCR and ELISA, respectively. Of these, 86 patients received a histologically confirmed diagnosis of PCa. Neither marker showed an association with the diagnosis of cancer. PCa patients were separated based on (i) treatment into patients with active surveillance or patients with any type of curative treatment and (ii) age into elderly (>68 years) patients and younger patients (≤68 years). In elderly patients (N = 41) with the intention of curative treatment at optimized cut-off values, significantly higher GP88 levels (p = 0.018) and lower miR-486 levels (p = 0.014) were observed. The total PSA level and ISUP biopsy grade were used in a baseline model for predicting definitive therapy. The baseline model exhibited an area under the curve (AUC) of 0.783 (p = 0.005). The addition of the serum biomarkers miR-486 and GP88 to the baseline model yielded an improved model with an AUC of 0.808 (p = 0.002). Altogether, combined miR-486 and GP88 serum levels are associated with and are therefore suggested as supportive biomarkers for therapy decisions, particularly in elderly PCa patients.
CRIS-Team Scopus Importer:2022-06-03
Keywords: age; miRNAs; predictive biomarker; progranulin; prostate cancer; serum level

Comparative analysis of human dendritic cell subpopulations in steady state and inflammation - Heger, Lukas; Heidkamp, Gordon Frederik; Lehmann, Christian; Eissing, N.; Söder, Stephan; Hartmann, Arndt; Zenk, J.; Alexiou, Christoph; Schuler, Gerold; Purbojo, Ariawan; Cesnjevar, Robert; Nimmerjahn, Falk; et al. (2017)
EVALuna2:33136

Comparative analysis of human dendritic cell subpopulations in steady state and inflammation - Heger, Lukas; Heidkamp, Gordon Frederik; Lehmann, Christian; Söder, Stephan; Hartmann, Arndt; Alexiou, Christoph; Schuler, Gerold; Purbojo, Ariawan; Cesnjevar, Robert; Nimmerjahn, Falk; Dudziak, Diana (2018)
EVALuna2:34382

Comparative analysis of tumour mutational burden (TMB) prediction methods and its association with determinants of the tumour immune microenvironment of urothelial bladder cancer (UBC) - Eckstein, Markus; Hartmann, Arndt; Strissel, Pamela; Strick, Reiner; Wach, S.; Taubert, Helge; Wullich, Bernd; Geppert, Carol-Immanuel; Weyerer, Veronika; Stöhr, Robert; Rübner, Matthias; Fasching, Peter; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Comparative genomic hybridization shows complex genomic changes of plasmacytoid urothelial carcinoma - Keck, Bastian; Elhnann, Christina; Stoehr, Robert; Weigelt, Katrin; Goebell, Peter; Kunath, Frank; Taubert, Helge; Hartmann, Arndt; Wullich, Bernd; Wach, Sven (Urologic Oncology-Seminars and Original Investigations, 2014)
To describe genomic imbalances in plasmacytoid urothelial carcinoma (PUC), which is a rare and aggressive variant of urothelial carcinoma (UC).In total, 25 formalin-fixed paraffin-embedded PUCs were analyzed by metaphase comparative genomic hybridization. Genomic imbalances were considered to be characteristic if they were detected in >= 20% of the cases. Chromosome regions deviating by >= 3 standard deviations from the average chromosome profile were scored as chromosomal gains or losses. Copy-number variations (CNVs) of CDH1 (16q 22.1), SNAI1 (20q 13.1), CCND1 (11q13.3), ERBB2 (17q12), and FOXO3 (6q21) were validated using quantitative polymerase chain reaction.Chromosomal aberrations were detected in every PUC analyzed, and the average number of aberrations was 10.24 (ranging from 1-15). Characteristic aberrations were gains on 1q (48%), 3p (20%), 6p (32%), 11q (72%), 15q (36%), 16q (44%), 17p (76%), 17q (88%), and 20q (88%) and losses on 2q (24%) 4p (36%), 4q (84%), 5q (44%), 6q (68%), 13q (20%), and Xq (52%). polymerase chain reaction-based analysis of CNV for CCND1 (11q13) showed a deletion in 73% of the cases. CDH1 (16q22) was deleted in 72% and amplified in 5%. ERBB2 (17q12) displayed remarkably few copy-number alterations, with only 14% showing an amplification. SNAI1 (20q13) showed reduced gene copy numbers in 59.1% of the cases, whereas no copy-number gains were detected. FOXO3 (6q21) exhibited the lowest number of copy-number alterations, with 9% of all cases showing an amplification.In PUCs, the frequency of aneuploidy and the complexity of genomic changes per tumor are greater than those described in conventional UC. The aberrations described in PUC involve the same regions that are associated with aggressive biological behavior in conventional UC. Gains on 11q, 17q, 17p, and 20q and losses on 4q and 6q affect most PUCs and seem to harbor important chromosomal regions for PUC carcinogenesis. Large-scale deletions on chromosome 9 were not detected. CNV analysis indicates heterozygous deletion of CDH1 as one underlying mechanism of loss of membranous E-cadherin in PUC. Loss of CCND1 and SNAI1 is a common molecular feature and could contribute to the aggressive biological behavior of PUC.
EVALuna2:6676

Comparative microRNA Profiling of Prostate Carcinomas with Increasing Tumor Stage by Deep Sequencing - Hart, Martin; Nolte, Elke; Wach, Sven; Szczyrba, Jaroslaw; Taubert, Helge; Rau, Tilman; Hartmann, Arndt; Graesser, Friedrich A.; Wullich, Bernd (Molecular Cancer Research, 2014)
MicroRNAs (miRNA) posttranscriptionally regulate gene expression and are important in tumorigenesis. Previous deep sequencing identified the miRNA profile of prostate carcinoma versus nonmalignant prostate tissue. Here, we generated miRNA expression profiles of prostate carcinoma by deep sequencing, with increasing tumor stage relative to corresponding nonmalignant and healthy prostate tissue, and detected clearly changed miRNA expression patterns. The miRNA profiles of the healthy and nonmalignant tissues were consistent with our previous findings, indicating a high fidelity of the method employed. In the tumors, quantitative real-time PCR (qRT-PCR) analysis of 40 paired samples of prostate carcinoma versus normal tissue revealed significant upregulation of miR-20a, miR-148a, miR-200b, and miR-375 and downregulation of miR-143 and miR-145. Hereby, miR-375 increased from normal to organ-confined tumors (pT2 pN0), slightly decreased in tumors with extracapsular growth (pT3 pN0), but was then expressed again at higher levels in lymph node metastasizing (pN1) tumors. The sequencing data for miR-375 were confirmed by Northern blotting and qRT-PCR. The regulation for other selected miRNAs could, however, not be confirmed by qRT-PCR in individual tumor stages. MiR-200b, in addition to miR-200c and miR-375 reduced the expression of SEC23A. Interestingly, miR-375, found by sequencing in pT2 upregulated by us and others in tumor versus normal tissue, and miR-15a, found by sequencing in pT2 and pT3 and in the metastasizing tumors, target the phosphatases PHLPP1 and PHLPP2, respectively. PHLPP1 and PHLPP2 dephosphorylate members of the AKT family of signal transducers, thereby inhibiting cell growth. Coexpression of miR-15a and miR-375 resulted in downregulation of PHLPP1/2 and strongly increased prostate carcinoma cell growth. Implications: These genomic data reveal relevant miRNAs in prostate cancer that may have biomarker and therapeutic potential. Mol Cancer Res; 12(2); 250-63. ©2013 AACR.
EVALuna2:6552

Comparison of Intrinsic PAM50 Gene Expression Analysis and Immunohistochemical Subtypes of Salivary Duct Carcinoma - Erber, Ramona; Stoehr, Robert; Haller, Florian; Haderlein, Marlen; Hartmann, Arndt; Agaimy, Abbas (LABORATORY INVESTIGATION, 2020)
CRIS-Team WoS Importer:2020-03-24

Comparison of PD-L1 mRNA Expression Measured with the CheckPoint Typer® Assay with PD-L1 Protein Expression Assessed with Immunohistochemistry in Non-small Cell Lung Cancer - Erber, Ramona; Stoehr, Robert; Herlein, Stefanie; Giedl, Claudia; Rieker, Ralf; Fuchs, Florian; Ficker, Joachim H.; Hartmann, Arndt; Veltrup, Elke; Wirtz, Ralph M.; Brueckl, Wolfgang M. (Anticancer Research, 2017)
Immunohistochemical (IHC) assessment of programmed death-ligand 1 (PD-L1) in non-small cell lung cancer (NSCLC) has become important since the development of anti-PD-1/-PD-L1 directed drugs. Various PD-L1 antibodies and cut-offs have been used in different trials to predict response to these drugs, thus comparison of those studies is difficult. We compared PD-L1 mRNA expression measured by RT-qPCR with PD-L1 protein expression evaluated by IHC. Moreover, we investigated the impact of different tumour tissue acquisition methods on the reliability of PD-L1 measurement techniques.NSCLC cases (N=22), including n=9 mediastinal lymph node biopsies acquired by endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) and n=5 metastases, were evaluated prospectively for PD-L1 protein on tumor cells (TC) and immune cells (IC) using E1L3N and 28-8 antibodies and PD-L1 mRNA using the CheckPoint TYPER® assay.In primary NSCLC tissues, agreement between PD-L1 mRNA and TC staining using the 28-8 antibody was excellent (?=0.85, p=0.0002). Comparing both PD-L1 antibodies against each other showed a kappa value of 0.58 (p=0.0106). In EBUS-TBNA, PD-L1 mRNA correlated perfectly with the 28-8 antibody (?=1.0, p=0.0023). PD-L1 mRNA levels significantly differed when comparing 28-8 TC staining of tumours >49% with 1-49% and 0% (p=0.0040; p=0.0081, respectively). In metastatic lesions, differences between PD-L1 mRNA and IHC became apparent (?=0.2, p=0.2525).Testing of PD-L1 mRNA and 28-8 IHC showed an excellent agreement in NSCLC samples including mediastinal lymph node biopsies. Since PD-L1 expression in >50% TC detected by 28-8 IHC can be reliably detected by RT-qPCR, quantitative PD-L1 mRNA determination should be considered as an alternative to IHC as there is no interobserver variability in RNA results.
EVALuna2:6916

Comparison of PD-L1 mRNA expression measured with the CheckPointTyper(R) assay with PD-L1 protein expression assessed with immunohistochemistry (IHC) in lung cancer (NSCLC) - Erber, Ramona; Stoehr, R.; Herlein, S.; Fuchs, F.; Veltrup, Elke; Wirtz, Ralph; Hartmann, Arndt (2017)
EVALuna2:34085

Comparison of prognostic and predictive impact of genomic or central grade and immunohistochemical subtypes or IHC4 in HR+/HER2- early breast cancer: WSG-AGO EC-Doc Trial - Gluz, O.; Liedtke, C.; Huober, J.; Peyro-Saint-Paul, H.; Kates, R. E.; Kreipe, H. H.; Hartmann, Arndt; Pelz, E.; Erber, Ramona; Mohrmann, S.; Moebus, V.; Augustin, D.; et al. (Annals of Oncology, 2016)
Potential prognostic and predictive markers in early, intermediate-risk breast cancer (BC) include histological grade, Ki-67, genomic signatures, e.g. genomic grade index (GGI), and intrinsic subtypes. Their prognostic/predictive impact in hormone receptor (HR: ER and/or PR) positive/HER2- BC is controversial. WSG-AGO EC-Doc demonstrated superior event-free survival (EFS) in patients with 1-3 positive lymph node receiving epirubicin/cyclophosphamide-docetaxel (EC-Doc) versus 5-fluoruracil/epirubicin/cyclophosphamide (FEC).In a representative trial subset, we quantify concordance among factors used for clinical chemotherapy indication. We investigate the impact of central histology (n = 772), immunohistochemistry for intrinsic subtyping and IHC4, and dichotomous (GG) or continuous (GGI) genomic grade (n = 472) on patient outcome and benefit from taxane chemotherapy, focusing on HR+/HER2- patients (n = 459).Concordance of local grade (LG) with central (CG) or genomic grade was modest. In HR+/HER2- patients, low (GG-1: 16%), equivocal (GG-EQ: 17%), and high (GG-3: 67%) GG were associated with respective 5-year EFS of 100%, 93%, and 85%. GGI was prognostic for EFS within all LG subgroups and within CG3, whereas IHC4 was prognostic only in CG3 tumors.In unselected and HR+/HER2- patients, CG3 and luminal-A-like subtype entered the multivariate EFS model, but not IHC4 or GG. In the whole population, continuous GGI entered the model [hazard ratio (H.R.) of 75th versus 25th = 2.79; P = 0.01], displacing luminal-A-like subtype; within HR+/HER2- (H.R. = 5.36; P < 0.001), GGI was the only remaining prognostic factor.In multivariate interaction analysis (including central and genomic grade), luminal-B-like subtype [HR+ and (Ki-67 >=20% or HER2+)] was predictive for benefit of EC-Doc versus FEC in unselected but not in HR+/HER2- patients.In the WSG-AGO EC-Doc trial for intermediate-risk BC, CG, intrinsic subtype (by IHC), and GG provide prognostic information. Continuous GGI (but not IHC4) adds prognostic information even when IHC subtype and CG are available. Finally, the high interobserver variability for histological grade and the still missing validation of Ki-67 preclude indicating or omitting adjuvant chemotherapy based on these single factors alone.The WSG-AGO/EC-Doc is registered at ClinicalTrials.gov, NCT02115204.
EVALuna2:6775

Complement Activation via the Lectin and Alternative Pathway in Patients With Severe COVID-19 - Niederreiter, Janina; Eck, Christine; Ries, Tajana; Hartmann, Arndt; Märkl, Bruno; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Frontiers in Immunology, 2022)
Complement plays an important role in the direct defense to pathogens, but can also activate immune cells and the release of pro-inflammatory cytokines. However, in critically ill patients with COVID-19 the immune system is inadequately activated leading to severe acute respiratory syndrome (SARS) and acute kidney injury, which is associated with higher mortality. Therefore, we characterized local complement deposition as a sign of activation in both lungs and kidneys from patients with severe COVID-19. Using immunohistochemistry we investigated deposition of complement factors C1q, MASP-2, factor D (CFD), C3c, C3d and C5b-9 as well as myeloperoxidase (MPO) positive neutrophils and SARS-CoV-2 virus particles in lungs and kidneys from 38 patients who died from COVID-19. In addition, tissue damage was analyzed using semi-quantitative scores followed by correlation with complement deposition. Autopsy material from non-COVID patients who died from cardiovascular causes, cerebral hemorrhage and pulmonary embolism served as control (n=8). Lung injury in samples from COVID-19 patients was significantly more pronounced compared to controls with formation of hyaline membranes, thrombi and edema. In addition, in the kidney tubular injury was higher in these patients and correlated with lung injury (r=0.361*). In autopsy samples SARS-CoV-2 spike protein was detected in 22% of the lungs of COVID-19 patients but was lacking in kidneys. Complement activation was significantly stronger in lung samples from patients with COVID-19 via the lectin and alternative pathway as indicated by deposition of MASP-2, CFD, C3d and C5b9. Deposits in the lung were predominantly detected along the alveolar septa, the hyaline membranes and in the alveolar lumina. In the kidney, complement was significantly more deposited in patients with COVID-19 in peritubular capillaries and tubular basement membranes. Renal COVID-19-induced complement activation occurred via the lectin pathway, while activation of the alternative pathway was similar in both groups. Furthermore, MPO-positive neutrophils were found in significantly higher numbers in lungs and kidneys of COVID-19 patients and correlated with local MASP-2 deposition. In conclusion, in patients who died from SARS-CoV-2 infection complement was activated in both lungs and kidneys indicating that complement might be involved in systemic worsening of the inflammatory response. Complement inhibition might thus be a promising treatment option to prevent deregulated activation and subsequent collateral tissue injury in COVID-19.
CRIS-Team Scopus Importer:2022-03-11
Keywords: autopsy; complement deposition; COVID-19; kidney; lectin pathway; lung

Comprehensive screening for mutations associated with colorectal cancer in unselected cases reveals penetrant and nonpenetrant mutations - Kraus, Cornelia; Rau, Tilman; Lux, Philipp; Erlenbach-Wuensch, Katharina; Loehr, Sabine; Krumbiegel, Mandy; Thiel, Christian; Stoehr, Robert; Agaimy, Abbas; Croner, Roland S.; Stürzl, Michael; Hohenberger, Werner; et al. (International Journal of Cancer, 2015)
Germline mutation testing in patients with colorectal cancer (CRC) is offered only to a subset of patients with a clinical presentation or tumor histology suggestive of familial CRC syndromes, probably underestimating familial CRC predisposition. The aim of our study was to determine whether unbiased screening of newly diagnosed CRC cases with next generation sequencing (NGS) increases the overall detection rate of germline mutations. We analyzed 152 consecutive CRC patients for germline mutations in 18 CRC-associated genes using NGS. All patients were also evaluated for Bethesda criteria and all tumors were investigated for microsatellite instability, immunohistochemistry for mismatch repair proteins and the BRAF*V600E somatic mutation. NGS based sequencing identified 27 variants in 9 genes in 23 out of 152 patients studied (18%). Three of them were already reported as pathogenic and 12 were class 3 germline variants with an uncertain prediction of pathogenicity. Only 1 of these patients fulfilled Bethesda criteria and had a microsatellite instable tumor and an MLH1 germline mutation. The others would have been missed with current approaches: 2 with a MSH6 premature termination mutation and 12 uncertain, potentially pathogenic class 3 variants in APC, MLH1, MSH2, MSH6, MSH3 and MLH3. The higher NGS mutation detection rate compared with current testing strategies based on clinicopathological criteria is probably due to the large genetic heterogeneity and overlapping clinical presentation of the various CRC syndromes. It can also identify apparently nonpenetrant germline mutations complicating the clinical management of the patients and their families.
EVALuna2:6598

Comprehensive Transcriptional Analysis of Early-Stage Urothelial Carcinoma - Hedegaard, Jakob; Lamy, Philippe; Nordentoft, Iver; Algaba, Ferran; Hoyer, Soren; Ulhoi, Benedicte Parm; Vang, Soren; Reinert, Thomas; Hermann, Gregers G.; Mogensen, Karin; Thomsen, Mathilde Borg Houlberg; Nielsen, Morten Muhlig; et al. (Cancer Cell, 2016)
Non-muscle-invasive bladder cancer (NMIBC) is a heterogeneous disease with widely different outcomes. We performed a comprehensive transcriptional analysis of 460 early-stage urothelial carcinomas and showed that NMIBC can be subgrouped into three major classes with basal- and luminal-like characteristics and different clinical outcomes. Large differences in biological processes such as the cell cycle, epithelial-mesenchymal transition, and differentiation were observed. Analysis of transcript variants revealed frequent mutations in genes encoding proteins involved in chromatin organization and cytoskeletal functions. Furthermore, mutations in well-known cancer driver genes (e.g., TP53 and ERBB2) were primarily found in high-risk tumors, together with APOBEC-related mutational signatures. The identification of subclasses in NMIBC may offer better prognostication and treatment selection based on subclass assignment.
EVALuna2:6801

Computer-aided diagnosis in multiparametric mri of the prostate: An open-access online tool for lesion classification with high accuracy - Ellmann, Stephan; Schlicht, Michael; Dietzel, Matthias; Janka, Rolf Matthias; Hammon, Matthias; Saake, Marc; Ganslandt, Thomas; Hartmann, Arndt; Kunath, Frank; Wullich, Bernd; Uder, Michael; Bäuerle, Tobias (Cancers, 2020)
Computer-aided diagnosis (CADx) approaches could help to objectify reporting on prostate mpMRI, but their use in many cases is hampered due to common-built algorithms that are not publicly available. The aim of this study was to develop an open-access CADx algorithm with high accuracy for classification of suspicious lesions in mpMRI of the prostate. This retrospective study was approved by the local ethics commission, with waiver of informed consent. A total of 124 patients with 195 reported lesions were included. All patients received mpMRI of the prostate between 2014 and 2017, and transrectal ultrasound (TRUS)-guided and targeted biopsy within a time period of 30 days. Histopathology of the biopsy cores served as a standard of reference. Acquired imaging parameters included the size of the lesion, signal intensity (T2w images), diffusion restriction, prostate volume, and several dynamic parameters along with the clinical parameters patient age and serum PSA level. Inter-reader agreement of the imaging parameters was assessed by calculating intraclass correlation coefficients. The dataset was stratified into a train set and test set (156 and 39 lesions in 100 and 24 patients, respectively). Using the above parameters, a CADx based on an Extreme Gradient Boosting algorithm was developed on the train set, and tested on the test set. Performance optimization was focused on maximizing the area under the Receiver Operating Characteristic curve (ROCAUC). The algorithm was made publicly available on the internet. The CADx reached an ROCAUC of 0.908 during training, and 0.913 during testing (p = 0.93). Additionally, established rule-in and rule-out criteria allowed classifying 35.8% of the malignant and 49.4% of the benign lesions with error rates of <2%. All imaging parameters featured excellent inter-reader agreement. This study presents an open-access CADx for classification of suspicious lesions in mpMRI of the prostate with high accuracy. Applying the provided rule-in and rule-out criteria might facilitate to further stratify the management of patients at risk.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Artificial intelligence; Computer-aided diagnosis; Machine learning; Prostate cancer; Prostate mpMRI

Concordance Rate of Colposcopy in Detecting Cervical Intraepithelial Lesions - Stübs, Frederik; Dietl, Anna; Behrens, Annika; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Mehlhorn, Grit; Schulmeyer, Carla; Gaß, Paul; Koch, Martin C. (Diagnostics, 2022)
Background: The purpose of this research is to estimate the rate of concordance, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of colposcopy for high-grade squamous lesions and carcinomas (HSIL+). Methods: We conducted a retrospective study of colposcopies performed in the certified Dysplasia Unit in Erlangen between January 2015 and May 2022 (7.5 years). The colposcopic findings were correlated with biopsies obtained during examinations or surgery. Cases without histology were excluded. The primary outcome was the rate of concordance between the colposcopic and histological findings in relation to the type of transformation zone (TZ), examiner's level of experience and age of the patients. Results: A total of 4778 colposcopies in 4001 women were analyzed. The rates of concordance for CIN I/LSIL, CIN II/HSIL, CIN III/HSIL, and carcinoma were 43.4%, 59.5%, 78.5%, and 53.9%, respectively. The rate of concordance was lowest for TZ3 and highest for colposcopists with more than 10 years' experience. Conclusions: Colposcopy is an important, feasible, and effective method. Careful work-up needs to be performed for women with TZ3 who are over 35 years old, as they are at the highest risk of being misdiagnosed. The highest concordance for detecting HSIL+ was seen for colposcopists with >10 years' experience.
CRIS-Team WoS Importer:2022-11-11

Concordance rate of vulvoscopic findings in detecting early vulvar neoplasia - Stuebs, Frederik A.; Mehlhorn, Grit; Gaß, Paul; Schulmeyer, Carla; Adler, Werner; Strehl, Johanna; Hartmann, Arndt; Beckmann, Matthias; Renner, Stefan; Koch, Martin (Gynecologic Oncology, 2020)
Purpose: Colposcopy-guided punch biopsy is a cornerstone method for diagnosing vulvar diseases. The aim of this study was to evaluate the concordance rate of clinical findings in vulvar diseases during examinations, in comparison with colposcopy-directed punch biopsy. We also developed a new classification to simplify the categorization of vulvoscopic findings. Methods: The concordance rate of the clinical findings was compared with the final histology results from punch biopsies. The data were collected between January 2014 and May 2017 at the Erlangen University Hospital. Results: A total of 482 colposcopy-directed punch biopsies of the vulva were obtained in 420 women. The overall concordance rate of the clinical findings in comparison with the histological vulvar punch-biopsy findings was 53.9% for all entities — benign lesions, lichen, low- and high-grade squamous intraepithelial lesions (LSIL/HSILs), and vulvar carcinoma. The concordance rate for detecting LSILs was 64.3% (45/70). The concordance rate for detecting HSILs was 62.3% and for Vulvar carcinoma 65.2%. Conclusions: Punch biopsy of suspicious lesions continues to be a cornerstone in diagnosing HSILs and carcinoma of the vulva. Careful work-up of the vulva is recommended when patients have symptoms such as pruritus or pain. The new classification is more specific for diagnosing lesions in the vulva.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Colposcopy-directed punch biopsy; High-grade squamous intraepithelial lesion (HSIL); Vulvar cancer; Vulvar intraepithelial neoplasia (VIN)

Construction and analysis of tissue microarrays in the era of digital pathology: a pilot study targeting CDX1 and CDX2 in a colon cancer cohort of 612 patients - Nolte, Sarah; Zlobec, Inti; Lugli, Alessandro; Hohenberger, Werner; Croner, Roland; Merkel, Susanne; Hartmann, Arndt; Geppert, Carol-Immanuel; Rau, Tilman (Journal of Pathology: Clinical Research, 2017)
CDX1 and CDX2 are possibly predictive biomarkers in colorectal cancer. We combined digitally-guided (next generation) TMA construction (ngTMA) and the utility of digital image analysis (DIA) to assess accuracy, tumour heterogeneity and the selective impact of different combined intensity-percentage levels on prognosis.CDX1 and CDX2 immunohistochemistry was performed on ngTMAs covering normal tissue, tumour centre and invasive front. The percentages of all epithelial cells per staining intensity per core were analysed digitally. Beyond classical prognosis analysis following REMARK guidelines, we investigated pre-analytical conditions, three different types of heterogeneity (mosaic-like, targeted and haphazard) and influences on cohort segregation and patient selection. The ngTMA-DIA approach produced robust biomarker data with infrequent core loss and excellent on-target punching. The detailed assessment of tumour heterogeneity could - except for a certain diffuse mosaic-like heterogeneity - exclude differences between the invasive front and tumour centre, as well as detect haphazard clonal heterogeneous elements. Moreover, lower CDX1 and CDX2 counts correlated with mucinous histology, higher TNM stage, higher tumour grade and worse survival (p < 0.01, all). Different protein expression intensity levels shared comparable prognostic power and a great overlap in patient selection. The combination of ngTMA with DIA enhances accuracy and controls for biomarker analysis. Beyond the confirmation of CDX1 and CDX2 as prognostically relevant markers in CRC, this study highlights the greater robustness of CDX2 in comparison to CDX1. For the assessment of CDX2 protein loss, cut-points as percentage data of complete protein loss can be deduced as a recommendation.
EVALuna2:15290

Contribution of serum lipids and cholesterol cellular metabolism in lung cancer development and progression - Hartmann, Philipp; Trufa, Denis; Hohenberger, Katja; Tausche, Patrick; Trump, Sonja; Mittler, Susanne; Geppert, Carol-Immanuel; Rieker, Ralf; Schieweck, Oliver; Sirbu, Horia; Hartmann, Arndt; Neurath-Finotto, Susetta (Scientific Reports, 2023)
Neoplasms of the lungs are the leading cause of cancer incidence and mortality worldwide. Although immunotherapy has increased the overall survival of patients with lung cancer, there is the need to improve this treatment. At this regard, blood lipid levels are thought to be linked to cancer risk and thus a preventive intervention through regulation of the nutrition of patients with lung cancer is gaining much attention. In this study, we therefore asked about the contribution of serum lipids and cholesterol cellular metabolism in lung cancer development and progression. We measured different serum lipids and analyzed cholesterol synthesis enzymes 3-hydroxy-3-methyl-glutaryl-CoA reductase (HMGCR) and acetyl-coenzyme A cholesterol acetyltransferase 1 (ACAT1) as well as the cholesterol cellular export protein ATP-binding cassette (ABC) A-1 mRNA by quantitative PCR (qPCR) in the control and tumoral regions of post-surgery lung tissues to analyze the accumulation of cholesterol in cancer cells in a cohort of patients with lung adenocarcinoma (LUAD). We found that triglycerides in serum directly correlated with the body mass index (BMI) in patients with LUAD. By contrast, we found that high-density lipoprotein (HDL) cholesterol inversely correlated with the BMI, C-reactive protein (CRP) and overall survival and total cholesterol inversely correlated with the tumor diameter, serum CRP and overall survival in these LUAD patients. Functionally, the role of cholesterol is indispensable for the growth and development of normal animal cells where it is tightly regulated. Excess of cellular cholesterol regulated by HMGCR is converted to cholesteryl esters by the enzyme ACAT1 and exported extracellularly by the cholesterol transporter ABCA1. Here we found HMGCR and ACAT1 upregulated and ABCA1 downregulated in the lung's tumoral region of our LUAD cohort, indicating cholesterol dysregulated cellular export in lung tumor cells.
CRIS-Team Scopus Importer:2023-04-21

Correction to: Eosinophilic vacuolated tumor (EVT) of kidney demonstrates sporadic TSC/MTOR mutations: next-generation sequencing multi-institutional study of 19 cases (Modern Pathology, (2021), 10.1038/s41379-021-00923-6) - Farcaş, Mihaela; Gatalica, Zoran; Trpkov, Kiril; Swensen, Jeffrey; Zhou, Ming; Alaghehbandan, Reza; Williamson, Sean R.; Magi-Galluzzi, Cristina; Gill, Anthony J.; Tretiakova, Maria; Lopez, Jose I.; Montiel, Delia Perez; et al. (Modern Pathology, 2021)
The original version of this article unfortunately contained a mistake. There was a misspelling in Michael Bonert’s name as well as in his affiliation. The authors apologize for the error. The original article has been corrected.
CRIS-Team Scopus Importer:2021-11-12

Correction to: Multicenter evaluation of an automated, multiplex, RNA-based molecular assay for detection of ALK, ROS1, RET fusions and MET exon 14 skipping in NSCLC (Virchows Archiv, (2024), 10.1007/s00428-024-03778-9) - Melchior, Linea; Hirschmann, Astrid; Hofman, Paul; Bontoux, Christophe; Concha, Angel; Mrabet‑Dahbi, Salima; Vannuffel, Pascal; Watkin, Emmanuel; Putzová, Martina; Scarpino, Stefania; Cayre, Anne; Martin, Paloma; et al. (Virchows Archiv, 2024)
In the original version of this article, the given and family names of the authors were interchanged. The names were displayed correctly in all versions at the time of publication. The original article has been corrected.
CRIS-Team Scopus Importer:2024-05-17

Correction to: Multi-institutional re-evaluation of prognostic factors in chromophobe renal cell carcinoma: proposal of a novel two-tiered grading scheme (Virchows Archiv, (2019), 10.1007/s00428-019-02710-w) - Ohashi, Riuko; Martignoni, Guido; Hartmann, Arndt; Caliò, Anna; Segala, Diego; Stöhr, Christine; Wach, Sven; Erlmeier, Franziska; Weichert, Wilko; Autenrieth, Michael; Schraml, Peter; Rupp, Niels J.; et al. (Virchows Archiv, 2020)
The legends of Figs. 1 and 3 in the published original version of the above article are incorrect.
CRIS-Team Scopus Importer:2020-03-20

Correction to: The natural course of pT2 prostate cancer with positive surgical margin: predicting biochemical recurrence (World Journal of Urology, (2015), 33, 7, (973-979), 10.1007/s00345-015-1510-y) - Karl, A.; Buchner, A.; Tympner, C.; Kirchner, T.; Ganswindt, U.; Belka, C.; Ganzer, R.; Burger, M.; Eder, F.; Hofstädter, F.; Schilling, D.; Sievert, K.; et al. (World Journal of Urology, 2020)
In multivariate analysis, GS of the regular prostatectomy specimen was the only statistically significant parameter for pT2R1 prostate cancer.
CRIS-Team Scopus Importer:2020-02-28

Correlation between referral cytology and in-house colposcopy-guided cytology for detecting early cervical neoplasia - Schulmeyer, Carla; Stübs, Frederik; Gaß, Paul; Renner, Stefan; Hartmann, Arndt; Strehl, Johanna; Mehlhorn, Grit; Geppert, Carol-Immanuel; Adler, Werner; Beckmann, Matthias; Koch, Martin (Archives of Gynecology and Obstetrics, 2019)
Purpose: The current cervical cancer screening program in Germany recommends that the results showing suspected HPV infection should be further examined in specialized colposcopy units. This study aimed to correlate externally documented Pap smear results with in-house colposcopy-guided Pap cytology results and compare colposcopy-guided biopsy and postoperative histopathology results. Methods: Clinical data were analyzed from 3627 examinations in 2844 patients who visited a university certified dysplasia unit from 2014 to 2017; 2212 patients underwent complete assessments, including Pap smear, colposcopy, HPV testing, colposcopy-guided biopsy, and/or surgery. The results were analyzed descriptively. Results: External and in-house Pap results were consistent in 1054 ofthe 2212 patients (47.65%). Referral cytology showed a higher grade than in-house in 456 (20.61%) and a lower grade in 702 (31.74%). Using the histopathological findings as the gold standard, overdiagnosis in the referral cytology was noted in 180 patients (13.19%), underdiagnosis in 263 (19.27%), and concordant findings in 922 (67.55%). For in-house cytology, overdiagnosis was found in 133 patients (10.74%), underdiagnosis in 192 (15.51%), and accurate diagnosis with congruent cytology and histopathology findings in 913 (73.75%). Conclusions: The rate of detection of cervical abnormalities differs significantly depending on whether the examination is performed routinely or in specialized units. Colposcopy-guided Pap smears correlate significantly better with histology than referral cytology results without colposcopic guidance. More severe lesions were also detected more accurately.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Cervical cancer screening; Cervical intraepithelial neoplasia (CIN); Dysplasia; High-grade squamous intraepithelial lesion (HSIL); Low-grade squamous intraepithelial lesion (LSIL); Pap smear; Precancerous lesions of the cervix

Correlation of histological and macroscopic findings in peritoneal endometriosis - Strehl, Johanna; Hackl, Janina; Wachter, David; Klingsiek, Peter; Burghaus, Stefanie; Renner, Stefan; Fasching, Peter; Hartmann, Arndt; Beckmann, Matthias (International Journal of Clinical and Experimental Pathology, 2014)
In the last two decades, a color based concept of disease activity in peritoneal endometriosis has been in use in the clinical context, with red lesions being considered active and black or white lesions being interpreted as less active or dormant.Our aim was to analyze 4 main color categories of peritoneal endometriosis (black, white, red and brown) in one single patient group using histomorphological and immunohistochemical methods.65 endometriosis lesions (30 black, 17 white, 11 brown, 7 red) were resected from 47 premenopausal, nulliparous women which had not received exogenous hormones for at least six months prior to the operation. Specimen workup, histomorphological analysis and immunohistochemical analysis were performed in a standardized manner.The color categories showed a broad overlap in proliferative activity and hormone receptor expression. Differences were found in lesion morphology. Adjacent stromal reaction in particular showed a marked increase from red through brown and black to white lesions. Differences were also seen in gland pattern and gland content.Lesion colors in peritoneal endometriosis seem to be determined by gland content and a varying adjacent stromal reaction and more likely reflect an aging process than different levels of disease activity.
EVALuna2:6566

Corrigendum: Complement activation via the lectin and alternative pathway in patients with severe COVID-19(Front. Immunol., (2022), 13, (835156), 10.3389/fimmu.2022.835156) - Niederreiter, Janina; Eck, Christine; Ries, Tajana; Hartmann, Arndt; Märkl, Bruno; Büttner-Herold, Maike; Amann, Kerstin Ute; Daniel, Christoph (Frontiers in Immunology, 2023)
In the published article, information in the Acknowledgments was mistakenly not included in the publication. A correction has been made to Acknowledgments:
CRIS-Team Scopus Importer:2023-10-20
Keywords: autopsy; complement deposition; COVID-19; kidney; lectin pathway; lung

Corrigendum to "Proposal for a Novel Histological Scoring System as a Potential Grading Approach for Muscle-invasive Urothelial Bladder Cancer Correlating with Disease Aggressiveness and Patient Outcomes" [European Urology Oncology (2023)]. - Eckstein, Markus; Matek, Christian; Wagner, Paul; Erber, Ramona; Büttner-Herold, Maike; Wild, Peter J.; Taubert, Helge; Wach, Sven; Sikic, Danijel; Wullich, Bernd; Geppert, Carol-Immanuel; Compérat, Eva M.; et al. (European Urology Oncology, 2023)
EVALuna2:542094

Co-staining of microRNAs and their target proteins by miRNA in situ hybridization and immunohistofluorescence on prostate cancer tissue microarrays - Eckstein, Markus; Sailer, Verena; Nielsen, Boye Schnack; Wittenberg, Thomas; Wiesmann, Veit; Lieb, Verena; Nolte, Elke; Hartmann, Arndt; Kristiansen, Glen; Wernert, Nicolas; Wullich, Bernd; Taubert, Helge; et al. (Laboratory Investigation, 2019)
The co-expression of miRNAs and their target proteins was studied on tissue microarrays from different prostate cancer (PCa) patients. PCa of primary Gleason pattern 4 (GP4), lymph node metastases of GP4, distant metastases, and normal tissue from the transitional and peripheral zones were co-stained by fluorescent miRNA in situ hybridization (miRisH) and protein immunohistofluorescence (IHF). The miRNAs and corresponding target proteins include the pairs miR-145/ERG, miR-143/uPAR, and miR-375/SEC23A. The fluorescence-stained and scanned tissue microarrays (TMAs) were evaluated by experienced uropathologists. The pair miR-145/ERG showed an exclusive staining for miR-145 in the nuclei of stromal cells, both in tumor and normal tissue, and for ERG in the cytoplasm with/without co-expression in the nucleus of tumor cells. The pair miR-143/uPAR revealed a clear distinction between miR-143 in the nuclei of stromal cells and uPAR staining in the cytoplasm of tumor cells. Metastases (lymph node and distant) however, showed tumor cells with cytoplasmic staining for miR-143/uPAR. In normal tissues, beside the nuclei of the stroma cells, gland cells could also express miR-143 and uPAR in the cytoplasm. miR-375 showed particular staining in the nucleoli of GP4 and metastatic samples, suggesting that nucleoli play a special role in sequestering proteins and miRNAs. Combined miRisH/IHF allows for the study of miRNA expression patterns and their target proteins at the single-cell level.
CRIS-Team Scopus Importer:2019-06-28

COVID-19 effects on the kidney. - Amann, Kerstin Ute; Boor, P.; Wiech, T.; Singh, Jeeshan; Vonbrunn, Eva; Knöll, Antje; Hermann, Maike; Büttner-Herold, Maike; Daniel, Christoph; Hartmann, Arndt (Pathologe, 2021)
Apart from pulmonary disease, acute kidney injury (AKI) is one of the most frequent and most severe organ complications in severe coronavirus disease 2019 (COVID-19). The SARS-CoV‑2 virus has been detected in renal tissue. Patients with chronic kidney disease (CKD) before and on dialysis and specifically renal transplant patients represent a particularly vulnerable population. The increasing number of COVID-19 infected patients with renal involvement led to an evolving interest in the analysis of its pathophysiology, morphology and modes of virus detection in the kidney. Meanwhile, there are ample data from several autopsy and kidney biopsy studies that differ in the quantity of cases as well as in their quality. While the detection of SARS-CoV‑2 RNA in the kidney leads to reproducible results, the use of electron microscopy for visualisation of the virus is difficult and currently critically discussed due to various artefacts. The exact contribution of indirect or direct effects on the kidney in COVID-19 are not yet known and are currently the focus of intensive research.
EVALuna2:421391

COVID-19 effects on the kidney - Amann, Kerstin Ute; Boor, P.; Wiech, T.; Singh, Jeeshan; Vonbrunn, Eva; Knöll, Antje; Hermann, Maike; Büttner-Herold, Maike; Daniel, Christoph; Hartmann, Arndt (Pathologe, 2021)
Apart from pulmonary disease, acute kidney injury (AKI) is one of the most frequent and most severe organ complications in severe coronavirus disease 2019 (COVID-19). The SARS-CoV-2 virus has been detected in renal tissue. Patients with chronic kidney disease (CKD) before and on dialysis and specifically renal transplant patients represent a particularly vulnerable population. The increasing number of COVID-19 infected patients with renal involvement led to an evolving interest in the analysis of its pathophysiology, morphology and modes of virus detection in the kidney. Meanwhile, there are ample data from several autopsy and kidney biopsy studies that differ in the quantity of cases as well as in their quality. While the detection of SARS-CoV-2 RNA in the kidney leads to reproducible results, the use of electron microscopy for visualisation of the virus is difficult and currently critically discussed due to various artefacts. The exact contribution of indirect or direct effects on the kidney in COVID-19 are not yet known and are currently the focus of intensive research.
CRIS-Team WoS Importer:2021-02-19

C-reactive protein flare predicts response to anti-PD-(L)1 immune checkpoint blockade in metastatic urothelial carcinoma - Klümper, Niklas; Sikic, Danijel; Saal, Jonas; Büttner, Thomas; Goldschmidt, Franziska; Jarczyk, Jonas; Becker, Philippe; Zeuschner, Philip; Weinke, Maximilian; Kalogirou, Charis; Breyer, Johannes; Burger, Maximilian; et al. (European Journal of Cancer, 2022)
Purpose: Robust biomarkers to predict response to immune checkpoint blockade (ICB) in metastatic urothelial carcinoma (mUC) are still in demand. Recently, early C-reactive protein (CRP) kinetics and especially the novel CRP flare-response phenomenon has been associated with immunotherapy response. Methods: We conducted a multicentre observational study comprising 154 patients with mUC treated with ICB to evaluate the predictive value of a previously described on-treatment CRP kinetics: CRP flare responders (at least doubling of baseline CRP within the first month after initiation of ICB followed by a decline below baseline within three months), CRP responders (decline in baseline CRP by ≥ 30% within three months without a prior flare) and the remaining patients as CRP non-responders. CRP kinetics groups were correlated with baseline parameters, PD-L1 status, progression-free survival (PFS) and overall survival (OS). Results: Objective response was observed in 57.1% of CRP responders, 45.8% of CRP flare responders and 17.9% of CRP non-responders (P < 0.001). CRP flare response was associated with prolonged PFS and OS (P < 0.001). In multivariable Cox regression analysis, CRP flare responders showed a risk reduction of ∼70% for tumour progression and death compared to CRP non-responders. Subgroup analysis of CRP flare responders revealed that patients with a long-flare response (completed flare-response kinetics ≥6 weeks on-treatment) showed even more favourable outcomes following ICB (HR = 0.18, 95%-CI: 0.07–0.48, P < 0.001). Conclusion: CRP (flare)response robustly predicts immunotherapy response and outcomes in mUC independent of PD-L1 status. Thus, early on-treatment CRP kinetics is a promising low-cost and easy-to-implement biomarker to optimise therapy monitoring in patients with mUC treated with ICB.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Biomarker; Bladder cancer; C-reactive protein; CRP flare; CRP flare-Response; Immune checkpoint blockade; Immunotherapy; Long-flare; Metastatic urothelial carcinoma

CREB1 is affected by the microRNAs miR-22-3p, miR-26a-5p, miR-27a-3p, and miR-221-3p and correlates with adverse clinicopathological features in renal cell carcinoma - Friedrich, Michael; Heimer, Nadine; Stoehr, Christine; Steven, André; Wach, Sven; Taubert, Helge; Hartmann, Arndt; Seliger, Barbara (Scientific Reports, 2020)
The transcription factor cAMP response element-binding protein (CREB1) has been shown to be involved in diverse biological pathways including the regulation of cell proliferation, apoptosis, cell cycle progression, and metastasis. In this context, aberrant expression of CREB1 and the functional consequences are well investigated in a number of hematopoietic and solid tumors. However, CREB1 expression and underlying control mechanisms are only poorly analyzed in renal cell carcinoma (RCC). The present study confirmed a deregulation of CREB1 protein in the clear cell type of RCC (ccRCC) and analysis of in-house ccRCC cell lines suggested a post-transcriptional control. The combination of miRNA enrichment assay, in silico analysis and molecular biological approaches revealed four novel CREB1-regulating miRNAs, namely miR-22-3p, miR-26a-5p, miR-27a-3p, and miR-221-3p. Categorizing RCC samples as CREB1 negative or positive, respectively, the expression of these miRNAs was found to be inversely correlated with CREB1 protein levels. Analyzing 453 consecutive RCC tumors by immunohistochemistry, weakly negative, but significant correlations of CREB1 with tumor stage and grade, vascular invasion (V1) and lymphovascular invasion (L1) were found. In this respect, ccRCC might differ from other solid tumors like esophageal squamous-cell carcinoma or glioma.
CRIS-Team Scopus Importer:2020-05-02

Current pathological and molecular aspects of bladder cancer - Hartmann, Arndt; Schwamborn, K.; Kristiansen, G.; Knuechel-Clarke, R. (Onkologe, 2018)
Background and results. Key data of the World Health Organization (WHO) classification from 2016 for the entity of urinary bladder cancer are summarized in the first part of this article. Unequivocal diagnostic terms in addition to clinical data of the findings in the bladder are an important basis in order to expedite a better molecular genetic understanding of tumors and their formation. At the same time increasing molecular data show the possibilities for definitive statements on subtypes and variants of urothelial cancer up to initial data on therapy response, so that overall substantial progress has been achieved for bladder cancer. Last but not least, greater certainty on the use of immunohistochemical investigations can be deduced from the molecular genetic data. Immunohistochemistry plays an important role in the definition of the urothelial entity (e. g. for metastases) and in the definitive assignment of malignancies and the differentiation from reactive changes, e.g. with the staining of targeted molecules within the immune checkpoint control, immunohistochemistry also provides a predictive component. Conclusion. Novel genetic and proteomic methods are increasingly being used for the diagnostics of urine and tissue of the urinary tract.
EVALuna2:34263

CXCR2 expression on neutrophil granulocytes in peripheral tumor is associated with shorter survival in oral squamous cell carcinoma - Spörl, Silvia; Erber, Ramona; Gerken, M.; Wittenberg, M.; Fischer, R.; Taxis, J.; Hartmann, Arndt; Geppert, Carol-Immanuel; Mamilos, A.; Mackensen, Andreas; Reichert, T.; Spanier, G.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Cytology and High-Risk Human Papillomavirus Test for Cervical Cancer Screening Assessment - Stübs, Frederik; Koch, Martin C.; Dietl, Anna; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Mehlhorn, Grit; Schulmeyer, Carla; Gaß, Paul (Diagnostics, 2022)
Background: A new nationwide screening strategy was implemented in Germany in January 2020. No data are available for women referred to certified dysplasia units for secondary clarification after primary diagnosis by a local physician. We therefore investigated combined testing with Papanicolaou smears and high-risk human papillomavirus (hrHPV) and compared the data with the final histological findings. Methods: Between January 2015 and October 2020, all referred women who underwent colposcopy of the uterine cervix in our certified dysplasia unit were included. Cytology findings were classified using the Munich III nomenclature. Results: A total of 3588 colposcopies were performed in 3118 women, along with Pap smear and hrHPV co-testing, followed by histology. Women with Pap II-p (ASC-US) and a positive hrHPV co-test had a 22.4% risk for cervical intraepithelial neoplasia (CIN) 3/high-grade squamous intraepithelial lesion (HSIL). The risk of CIN 3/HSIL was 83.8% in women with Pap IVa-p (HSIL) and a positive hrHPV co-test. A positive hrHPV co-test increased the risk for HSIL+ (OR 5.942; 95% CI, 4.617 to 7.649; p < 0.001) as compared to a negative hrHPV co-test. Conclusions: The accuracy of Pap smears is comparable with the screening results. A positive hrHPV test increases the risk for HSIL+ fivefold. Colposcopy is necessary to diagnose HSIL+ correctly.
CRIS-Team WoS Importer:2022-08-12

Cytology and HPV Co-Testing for Detection of Vaginal Intraepithelial Neoplasia: A Retrospective Study. - Stübs, Frederik; Dietl, Anna; Koch, Martin C.; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Mehlhorn, Grit; Beckmann, Matthias; Schulmeyer, Carla; Heindl, Felix; Emons, Julius; et al. (Cancers, 2023)
(1) Background: Vaginal intraepithelial neoplasia (VaIN) is a rare premalignant disease caused by persistent human papillomavirus (HPV) infection. Diagnosing VaIN is challenging; abnormal cytology and positive HPV tests are usually the first signs, but published data on their accuracy for detecting it are rare and contradictory. The aim of this study is to compare the results of hrHPV and cytology co-testing with the histological findings of the vagina. (2) Methods: In the certified Dysplasia Unit at Erlangen University Hospital, cytology and HPV samples from the uterine cervix or vaginal wall after hysterectomy were obtained between 2015 and 2023 and correlated with histological findings in biopsies from the vaginal wall. Women without vaginal biopsy findings or concomitant cervical disease were excluded. (3) Results: In all, 279 colposcopies in 209 women were included. The histological results were: benign (n = 86), VaIN I/vLSIL (n = 116), VaIN II/vHSIL (n = 41), VaIN III/vHSIL (n = 33), and carcinoma (n = 3). Accuracy for detecting VaIN was higher in women with previous hysterectomies. Positive HPV testing during colposcopy increased the likelihood for VaIN II/III/vHSIL threefold. The detection rate for VaIN III/vHSIL was 50% after hysterectomy and 36.4% without hysterectomy. (4) Conclusions: Women with risk factors for VaIN, including HPV-16 infection or prior HPV-related disease, need careful work-up of the entire vaginal wall. Hysterectomy for HPV-related disease and a history of cervical intraepithelial neoplasia (CIN) also increased the risk for VaIN II/III/vHSIL.
EVALuna2:540622

Cytology and hrHPV for cervical cancer screening assessment - Stübs, Frederik; Koch, M. C.; Dietl, Anna; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Mehlhorn, G.; Gaß, Paul; Schulmeyer, Carla (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Cytoplasmic p21 Mediates 5-Fluorouracil Resistance by Inhibiting Pro-Apoptotic Chk2 - Maiuthed, Arnatchai; Ninsontia, Chuanpit; Erlenbach-Wuensch, Katharina; Ndreshkjana, Benardina; Muenzner, Julienne K.; Caliskan, Aylin; Ahmed, Husayn P.; Chaotham, Chatchai; Hartmann, Arndt; Roehe, Adriana Vial; Mahadevan, Vijayalakshmi; Chanvorachote, Pithi; et al. (Cancers, 2018)
The oncogenic cytoplasmic p21 contributes to cancer aggressiveness and chemotherapeutic failure. However, the molecular mechanisms remain obscure. Here, we show for the first time that cytoplasmic p21 mediates 5-Fluorouracil (5FU) resistance by shuttling p-Chk2 out of the nucleus to protect the tumor cells from its pro-apoptotic functions. We observed that cytoplasmic p21 levels were up-regulated in 5FU-resistant colorectal cancer cells in vitro and the in vivo Chorioallantoic membrane (CAM) model. Kinase array analysis revealed that p-Chk2 is a key target of cytoplasmic p21. Importantly, cytoplasmic form of p21 mediated by p21T145D transfection diminished p-Chk2-mediated activation of E2F1 and apoptosis induction. Co-immunoprecipitation, immunofluorescence, and proximity ligation assay showed that p21 forms a complex with p-Chk2 under 5FU exposure. Using in silico computer modeling, we suggest that the p21/p-Chk2 interaction hindered the nuclear localization signal of p-Chk2, and therefore, the complex is exported out of the nucleus. These findings unravel a novel mechanism regarding an oncogenic role of p21 in regulation of resistance to 5FU-based chemotherapy. We suggest a possible value of cytoplasmic p21 as a prognosis marker and a therapeutic target in colorectal cancer patients.
EVALuna2:118614

Cytotoxic T-cell-related gene expression signature predicts improved survival in muscle-invasive urothelial bladder cancer patients after radical cystectomy and adjuvant chemotherapy - Eckstein, Markus; Strissel, Pamela; Strick, Reiner; Weyerer, Veronika; Wirtz, Ralph; Pfannstiel, Carolin; Wullweber, Adrian; Lange, Fabienne; Erben, Philipp; Stöhr, Robert; Bertz, Simone; Geppert, Carol-Immanuel; et al. (Journal for ImmunoTherapy of Cancer, 2020)
Background Assessment of the immune status of muscle-invasive bladder cancer (MIBC) has previously shown to be prognostically relevant after treatment with curative intent. We conducted this study to develop a clinically applicable immune gene expression assay to predict prognosis and adjuvant chemotherapy benefit. Patients and methods Gene expression of CD3Z, CD8A and CXCL9, immune cell (IC) populations including stromal tumor infiltrating lymphocytes (sTILs), T-cells, natural killer cells (NK-cells), macrophages, Programmed cell death protein 1 positive (PD-1) IC and tumor subtypes (MD Anderson Cancer Center/MDACC-approach) were assessed in 187 MIBC patients (Comprehensive Cancer Center Erlangen-EMN/CCC-EMN-cohort). A gene expression signature was derived by hierarchical-clustering and validated in The Cancer Genome Atlas (TCGA)-cohort. IC populations in the TCGA cohort were assessed via CIBERSORT. Benefit of platinum-containing adjuvant chemotherapy was assessed in a pooled cohort of 125 patients. Outcome measurements were disease specific survival, disease-free survival and overall survival. Results The gene expression signature of CXCL9, CD3Z and CD8A correlates with quantitative amounts of specific IC populations and sTILs (CCC-EMN: ρ-range: 0.44-0.74; TCGA: ρ-range: 0.56-0.82) and allows stratification of three different inflammation levels (inflamed high, inflamed low, uninflamed). Highly inflamed tumors are preferentially basal subtype and show favorable 5-year survival rates of 67.3% (HR=0.27; CCC-EMN) and 55% (HR=0.41; TCGA). Uninflamed tumors are predominantly luminal subtypes and show low 5-year survival rates of 28% (CCC-EMN) and 36% (TCGA). Inflamed tumors exhibit higher levels of PD-1 and Programmed cell death 1 ligand 1 (PD-L1). Patients undergoing adjuvant platinum-based chemotherapy with 'inflamed high' tumors showed a favorable 5-year survival rate of 64% (HR=0.27; merged CCC-EMN and TCGA cohort). Conclusion The gene expression signature of CD3Z, CD8A and CXCL9 can assess the immune status of MIBC and stratify the survival of MIBC patients undergoing surgery and adjuvant platinum-based chemotherapy. Furthermore, the assay can identify patients with immunological hot tumors with particular high expression of PD-L1 potentially suitable for immunotherapy.
CRIS-Team Scopus Importer:2020-06-05
Keywords: immunology; pathology; urology

DAPK1 loss triggers tumor invasion in colorectal tumor cells - Steinmann, Sara; Kunze, Philipp; Hampel, Chuanpit; Eckstein, Markus; Bertram Bramsen, Jesper; Muenzner, Julienne K.; Carlé, Birgitta-Elisabeth; Ndreshkjana, Benardina; Kemenes, Stephan; Gasparini, Pierluigi; Friedrich, Oliver; Andersen, Claus; et al. (Cell Death & Disease, 2019)
Colorectal cancer (CRC) is one of the leading cancer-related causes of death worldwide. Despite the improvement of surgical and chemotherapeutic treatments, as of yet, the disease has not been overcome due to metastasis to distant organs. Hence, it is of great relevance to understand the mechanisms responsible for metastasis initiation and progression and to identify novel metastatic markers for a higher chance of preventing the metastatic disease. The Death-associated protein kinase 1 (DAPK1), recently, has been shown to be a potential candidate for regulating metastasis in CRC. Hence, the aim of the study was to investigate the impact of DAPK1 protein on CRC aggressiveness. Using CRISPR/Cas9 technology, we generated DAPK1-deficient HCT116 monoclonal cell lines and characterized their knockout phenotype in vitro and in vivo. We show that loss of DAPK1 implemented changes in growth pattern and enhanced tumor budding in vivo in the chorioallantoic membrane (CAM) model. Further, we observed more tumor cell dissemination into chicken embryo organs and increased invasion capacity using rat brain 3D in vitro model. The novel identified DAPK1-loss gene expression signature showed a stroma typical pattern and was associated with a gained ability for remodeling the extracellular matrix. Finally, we suggest the DAPK1-ERK1 signaling axis being involved in metastatic progression of CRC. Our results highlight DAPK1 as an anti-metastatic player in CRC and suggest DAPK1 as a potential predictive biomarker for this cancer type.
CRIS-Team Scopus Importer:2019-12-10

DAPK loss in colon cancer tumor buds: implications for migration capacity of disseminating tumor cells - Ivanovska, Jelena; Zlobec, Inti; Forster, Stefan; Karamitopoulou, Eva; Dawson, Heather; Koelzer, Viktor Hendrik; Agaimy, Abbas; Garreis, Fabian; Söder, Stephan; Laqua, William; Lugli, Alessandro; Hartmann, Arndt; et al. (Oncotarget, 2015)
Defining new therapeutic strategies to overcome therapy resistance due to tumor heterogeneity in colon cancer is challenging. One option is to explore the molecular profile of aggressive disseminating tumor cells. The cytoskeleton-associated Death-associated protein kinase (DAPK) is involved in the cross talk between tumor and immune cells at the invasion front of colorectal cancer. Here dedifferentiated tumor cells histologically defined as tumor budding are associated with a high risk of metastasis and poor prognosis. Analyzing samples from 144 colorectal cancer patients we investigated immunhistochemical DAPK expression in different tumor regions such as center, invasion front, and buds. Functional consequences for tumor aggressiveness were studied in a panel of colon tumor cell lines using different migration, wound healing, and invasion assays. DAPK levels were experimentally modified by siRNA transfection and overexpression as well as inhibitor treatments. We found that DAPK expression was reduced towards the invasion front and was nearly absent in tumor buds. Applying the ECIS system with HCT116 and HCT116 stable lentiviral DAPK knock down cells (HCTshDAPK) we identified an important role for DAPK in decreasing the migratory capacity whereas proliferation was not affected. Furthermore, the migration pattern differed with HCTshDAPK cells showing a cluster-like migration of tumor cell groups. DAPK inhibitor treatment revealed that the migration rate was independent of DAPK's catalytic activity. Modulation of DAPK expression level in SW480 and DLD1 colorectal cancer cells significantly influenced wound closure rate. DAPK seems to be a major player that influences the migratory capability of disseminating tumor cells and possibly affects the dynamic interface between pro- and anti-survival factors at the invasion front of colorectal cancer. This interesting and new finding requires further evaluation.
EVALuna2:4438

Dedifferentiated and Undifferentiated Melanomas: Report of 35 New Cases with Literature Review and Proposal of Diagnostic Criteria - Agaimy, Abbas; Stöhr, Robert; Hornung, Annkathrin; Popp, Judith; Erdmann, Michael; Heinzerling, Lucie; Hartmann, Arndt (American Journal of Surgical Pathology, 2021)
Dedifferentiated melanoma (DM) and undifferentiated melanoma (UM) is defined as a primary or metastatic melanoma showing transition between conventional and undifferentiated components (DM) or lacking histologic and immunophenotypic features of melanoma altogether (UM). The latter is impossible to verify as melanoma by conventional diagnostic tools alone. We herein describe our experience with 35 unpublished cases to expand on their morphologic, phenotypic, and genotypic spectrum, along with a review of 50 previously reported cases (total: 85) to establish the diagnostic criteria. By definition, the dedifferentiated/undifferentiated component lacked expression of 5 routinely used melanoma markers (S100, SOX10, Melan-A, HMB45, Pan-melanoma). Initial diagnoses (known in 66 cases) were undifferentiated/unclassified pleomorphic sarcoma (n=30), unclassified epithelioid malignancy (n=7), pleomorphic rhabdomyosarcoma (n=5), other specific sarcoma types (n=6), poorly differentiated carcinoma (n=2), collision tumor (n=2), atypical fibroxanthoma (n=2), and reactive osteochondromatous lesion (n=1). In only 11 cases (16.6%) was a diagnosis of melanoma considered. Three main categories were identified: The largest group (n=56) comprised patients with a history of verified previous melanoma who presented with metastatic DM or UM. Axillary or inguinal lymph nodes, soft tissue, bone, and lung were mainly affected. A melanoma-compatible mutation was detected in 35 of 48 (73%) evaluable cases: BRAF (n=20; 40.8%), and NRAS (n=15; 30.6%). The second group (n=15) had clinicopathologic features similar to group 1, but a melanoma history was lacking. Axillary lymph nodes (n=6) was the major site in this group followed by the lung, soft tissue, and multiple site involvement. For this group, NRAS mutation was much more frequent (n=9; 60%) than BRAF (n=3; 20%) and NF1 (n=1; 6.6%). The third category (n=14) comprised primary DM (12) or UM (2). A melanoma-compatible mutation was detected in only 7 cases: BRAF (n=2), NF1 (n=2), NRAS (n=2), and KIT exon 11 (n=1). This extended follow-up study highlights the high phenotypic plasticity of DM/UM and indicates significant underrecognition of this aggressive disease among general surgical pathologists. The major clues to the diagnosis of DM and UM are: (1) presence of minimal differentiated clone in DM, (2) earlier history of melanoma, (3) undifferentiated histology that does not fit any defined entity, (4) locations at sites that are unusual for undifferentiated/unclassified pleomorphic sarcoma (axilla, inguinal, neck, digestive system, etc.), (5) unusual multifocal disease typical of melanoma spread, (6) detection of a melanoma-compatible gene mutation, and (7) absence of another genuine primary (eg, anaplastic carcinoma) in other organs.
CRIS-Team Scopus Importer:2021-02-05
Keywords: BRAF; chondrosarcoma; dedifferentiated melanoma; giant cell tumor; KIT; NRAS; osteosarcoma; pleomorphic sarcoma; rhabdomyosarcoma; undifferentiated melanoma

Deep learning-based classification of blue light cystoscopy imaging during transurethral resection of bladder tumors - Ali, Nairveen; Bolenz, Christian; Todenhöfer, Tilman; Stenzel, Arnulf; Deetmar, Peer; Kriegmair, Martin; Knoll, Thomas; Porubsky, Stefan; Hartmann, Arndt; Popp, Jürgen; Kriegmair, Maximilian C.; Bocklitz, Thomas (Scientific Reports, 2021)
Bladder cancer is one of the top 10 frequently occurring cancers and leads to most cancer deaths worldwide. Recently, blue light (BL) cystoscopy-based photodynamic diagnosis was introduced as a unique technology to enhance the detection of bladder cancer, particularly for the detection of flat and small lesions. Here, we aim to demonstrate a BL image-based artificial intelligence (AI) diagnostic platform using 216 BL images, that were acquired in four different urological departments and pathologically identified with respect to cancer malignancy, invasiveness, and grading. Thereafter, four pre-trained convolution neural networks were utilized to predict image malignancy, invasiveness, and grading. The results indicated that the classification sensitivity and specificity of malignant lesions are 95.77% and 87.84%, while the mean sensitivity and mean specificity of tumor invasiveness are 88% and 96.56%, respectively. This small multicenter clinical study clearly shows the potential of AI based classification of BL images allowing for better treatment decisions and potentially higher detection rates.
CRIS-Team Scopus Importer:2021-06-11

Deep learning for diagnosis and survival prediction in soft tissue sarcoma - Foersch, S.; Eckstein, Markus; Wagner, D. C.; Gach, F.; Woerl, A. C.; Geiger, J.; Glasner, C.; Schelbert, S.; Schulz, S.; Porubsky, S.; Kreft, A.; Hartmann, Arndt; et al. (Annals of Oncology, 2021)
Background: Clinical management of soft tissue sarcoma (STS) is particularly challenging. Here, we used digital pathology and deep learning (DL) for diagnosis and prognosis prediction of STS. Patients and methods: Our retrospective, multicenter study included a total of 506 histopathological slides from 291 patients with STS. The Cancer Genome Atlas cohort (240 patients) served as training and validation set. A second, multicenter cohort (51 patients) served as an additional test set. The use of the DL model (DLM) as a clinical decision support system was evaluated by nine pathologists with different levels of expertise. For prognosis prediction, 139 slides from 85 patients with leiomyosarcoma (LMS) were used. Area under the receiver operating characteristic (AUROC) and accuracy served as main outcome measures. Results: The DLM achieved a mean AUROC of 0.97 (±0.01) and an accuracy of 79.9% (±6.1%) in diagnosing the five most common STS subtypes. The DLM significantly improved the accuracy of the pathologists from 46.3% (±15.5%) to 87.1% (±11.1%). Furthermore, they were significantly faster and more certain in their diagnosis. In LMS, the mean AUROC in predicting the disease-specific survival status was 0.91 (±0.1) and the accuracy was 88.9% (±9.9%). Cox regression showed the DLM's prediction to be a significant independent prognostic factor (P = 0.008, hazard ratio 5.5, 95% confidence interval 1.56-19.7) in these patients, outperforming other risk factors. Conclusions: DL can be used to accurately diagnose frequent subtypes of STS from conventional histopathological slides. It might be used for prognosis prediction in LMS, the most prevalent STS subtype in our cohort. It can also help pathologists to make faster and more accurate diagnoses. This could substantially improve the clinical management of STS patients.
CRIS-Team Scopus Importer:2021-08-20
Keywords: artificial intelligence; clinical decision support system; deep learning; digital pathology; prognosis prediction; soft tissue sarcoma

Deep Learning Predicts Molecular Subtype of Muscle-invasive Bladder Cancer from Conventional Histopathological Slides - Woerl, Ann Christin; Eckstein, Markus; Geiger, Josephine; Wagner, Daniel C.; Daher, Tamas; Stenzel, Philipp; Fernandez, Aurélie; Hartmann, Arndt; Wand, Michael; Roth, Wilfried; Foersch, Sebastian (European Urology, 2020)
Background: Muscle-invasive bladder cancer (MIBC) is the second most common genitourinary malignancy, and is associated with high morbidity and mortality. Recently, molecular subtypes of MIBC have been identified, which have important clinical implications. Objective: In the current study, we tried to predict the molecular subtype of MIBC samples from conventional histomorphology alone using deep learning. Design, setting, and participants: Two cohorts of patients with MIBC were used: (1) The Cancer Genome Atlas Urothelial Bladder Carcinoma dataset including 407 patients and (2) our own cohort including 16 patients with treatment-naïve, primary resected MIBC. This resulted in a total of 423 digital whole slide images of tumor tissue to train, validate, and test the deep learning algorithm to predict the molecular subtype. Outcome measurements and statistical analysis: Various accuracy measurements including the area under the receiver operating characteristic curves were used to evaluate the deep learning model. A sliding window approach to visualize classification was used. Class activation maps were used to identify image features that are most relevant to call a specific class. Results and limitations: The deep learning model showed great performance in the prediction of the molecular subtype of MIBC patients from hematoxylin and eosin (HE) slides alone—similar to or better than pathology experts. Using different visualization techniques, we identified new histopathological features that were most relevant to our model. Conclusions: Deep learning can be used to predict important molecular features in MIBC patients from HE slides alone, potentially improving the clinical management of this disease significantly. Patient summary: In patients with bladder cancer, a computer program found changes in the appearance of tumor tissue under the microscope and used these to predict genetic alterations. This could potentially benefit patients. By using a comprehensive deep learning model, we were able to predict the molecular subtype of muscle-invasive bladder cancer from conventional histopathological slides alone, with good to excellent performance.
CRIS-Team Scopus Importer:2020-05-05
Keywords: Deep learning; Histopathology; Molecular subtype; Muscle-invasive bladder cancer

Defined morphological criteria allow reliable diagnosis of colorectal serrated polyps and predict polyp genetics - Rau, Tilman; Agaimy, Abbas; Gehoff, Anastasia; Geppert, Carol-Immanuel; Jung, Klaus; Knobloch, Katharina; Langner, Cord; Lugli, Alessandro; Groenbus-Lurkin, Irene; Nagtegaal, Iris D.; Rueschoff, Josef; Saegert, Xavier; et al. (Virchows Archiv, 2014)
Criteria for the diagnosis of serrated colorectal lesions (hyperplastic polyp, sessile serrated adenoma without or with dysplasia–which we called mixed polyp–and traditional serrated adenoma) for which consensus has been reached should be validated for applicability in daily practice in terms of inter-observer reproducibility and their association with clinical features and (epi)genetic events. A study set was created from a consecutive series of colorectal polyps (n = 1,926) by selecting all sessile serrated adenomas, traditional serrated adenomas and mixed polyps. We added consecutive series of hyperplastic polyps, classical adenomas and normal mucosa samples for a total of 200 specimens. With this series, we conducted an inter-observer study, encompassing ten pathologists with gastrointestinal pathology experience from five European countries, in three rounds in which all cases were microscopically evaluated. An assessment of single morphological criteria was included, and these were correlated with clinical parameters and the mutation status of KRAS, BRAF and PIK3CA and the methylation status of MLH1. Gender, age and localisation were significantly associated with certain types of lesions. Kappa statistics revealed moderate to good inter-observer agreement for polyp classification (? = 0.56 to 0.63), but for single criteria, this varied considerably (? = 0.06 to 0.82). BRAF mutations were frequently found in hyperplastic polyps (86 %, 62/72) and sessile serrated adenomas (80 %, 41/51). KRAS mutations occurred more frequently in traditional serrated adenomas (78 %, 7/9) and less so in classical adenomas (20 %, 10/51). Single morphological criteria for sessile serrated adenomas showed significant correlation with BRAF mutation (all p <= 0.001), and those for classical adenomas or traditional serrated adenoma correlated significantly with KRAS mutation (all p < 0.001). Therefore, single well-defined morphological criteria are predictive for genetic alterations in colorectal polyps.
EVALuna2:6595

DEK-AFF2 Carcinoma of the Sinonasal Region and Skull Base Detailed Clinicopathologic Characterization of a Distinctive Entity - Rooper, Lisa M.; Agaimy, Abbas; Dickson, Brendan C.; Dueber, Julie C.; Eberhart, Charles G.; Gagan, Jeffrey; Hartmann, Arndt; Khararjian, Armen; London, Nyall R.; Macmillan, Christina M.; Palsgrove, Doreen N.; Nix, J. Stephen; et al. (American Journal of Surgical Pathology, 2021)
A novel DEK-AFF2 fusion was recently reported in 4 nonkeratinizing squamous cell carcinomas of the sinonasal region and skull base, including 1 with exceptional response to immunotherapy, but it is not yet clear if this rearrangement defines a unique clinicopathologic category or represents a rare event. This study aims to characterize a larger cohort of carcinomas with DEK-AFF2 fusions to assess whether they truly constitute a distinctive entity. Among 27 sinonasal and skull base nonkeratinizing squamous cell carcinoma that were negative for human papillomavirus and Epstein-Barr virus, RNA sequencing identified DEK-AFF2 fusions in 13 cases (48%). Nine were centered in the nasal cavity, 2 in the middle ear/temporal bone, 1 in the nasopharynx, and 1 in the orbit. These tumors displayed recurrent histologic features including (1) complex endophytic and exophytic, frequently papilloma-like growth, (2) transitional epithelium with eosinophilic to amphophilic cytoplasm, (3) absent or minimal keratinization with occasional compact keratin pearls, (4) monotonous nuclei, and (5) prominent tumor-infiltrating neutrophils or stromal lymphocytes. This appearance not only overlaps with high-grade basaloid sinonasal carcinomas but also with benign papillomas and tumors reported as low-grade papillary Schneiderian carcinoma. However, DEK-AFF2 carcinomas showed frequent local recurrence, cervical lymph node metastases, and distant metastasis with 2 deaths from disease, confirming they are aggressive malignancies despite relatively bland histology. Overall, the distinctive molecular, histologic, and clinical features of DEK-AFF2 carcinomas suggest they represent a unique entity in the sinonasal region. This tumor merits increased pathologic recognition to better understand its prognostic and therapeutic implications.
CRIS-Team WoS Importer:2021-11-26

Description of the EuroTARGET cohort: A European collaborative project on TArgeted therapy in renal cell cancer-GEnetic- and tumor-related biomarkers for response and toxicity - Van Der Zanden, Loes F. M.; Vermeulen, Sita H.; Oskarsdottir, Arna; Maurits, Jake S. F.; Diekstra, Meta H. M.; Ambert, Valentin; Cambon-Thomsen, Anne; Castellano, Daniel; Fritsch, Achim; Garcia Donas, Jesus; Guarch Troyas, Rosa; Guchelaar, Henk-Jan; et al. (Urologic Oncology-Seminars and Original Investigations, 2017)
OBJECTIVE: For patients with metastatic renal cell cancer (mRCC), treatment choice is mainly based on clinical parameters. With many treatments available and the limited response to treatment and associated toxicities, there is much interest in identifying better biomarkers for personalized treatment. EuroTARGET aims to identify and characterize host- and tumor-related biomarkers for prediction of response to tyrosine kinase inhibitor therapy in mRCC. Here, we describe the EuroTARGET mRCC patient cohort. METHODS AND MATERIALS: EuroTARGET is a European collaborative project designed as an observational study for which patients with mRCC were recruited prospectively in 62 centers. In addition, 462 patients with mRCC from previous studies were included. Detailed clinical information (baseline and follow-up) from all patients was entered in web-based case record forms. Blood was collected for germline DNA and pharmacokinetic/pharmacodynamic analyses and, where available, fresh-frozen tumor material was collected to perform tumor DNA, RNA, kinome, and methylome analyses. RESULTS: In total, 1,210 patients with mRCC were included. Of these, 920 received a tyrosine kinase inhibitor as first-line targeted treatment (sunitinib [N = 713, 78%], sorafenib [N = 41, 4%], or pazopanib [N = 166, 18%]) and had at least 6 months of outcome assessment (median follow-up 15.3 months [interquartile range: 8.5-30.2 months]). Germline DNA samples were available from 824 of these patients, fresh-frozen tumor material from 142 patients, fresh-frozen normal kidney tissue from 95 patients, and tissue microarrays created from formalin-fixed paraffin-embedded tumor material from 247 patients. Of the 920 patients, germline DNA variant chip data were successfully generated for 811 patients (Illumina HumanOmniExpress BeadChip). For 80 patients, next-generation exome sequencing of germline and tumor DNA was performed, tumor RNA sequencing was performed for 124 patients, kinome activity measured and processed for 121 patients (PamChip), and methylome data (Illumina Infinium HumanMethylation450 BeadChip) were created for 116 RCC tissues (and 23 normal kidney tissues). For 73 out of the 920 patients, all platform data types were generated. In addition, 40 patients were included in a pharmacokinetic/pharmacodynamic phase IV substudy. CONCLUSIONS: Analysis of EuroTARGET cohort data will contribute to personalization of therapy for patients with mRCC. The extensive clinical data and multiplatform EuroTARGET data will be freely available.
EVALuna2:34249

Detection of microcalcifications in spiral breast computed tomography with photon-counting detector is feasible: A specimen study - Wetzl, Matthias; Wenkel, Evelyn; Balbach, Eva; Dethlefsen, Ebba; Hartmann, Arndt; Emons, Julius; Kuhl, Christiane; Beckmann, Matthias; Uder, Michael; Ohlmeyer, Sabine (Diagnostics, 2021)
The primary objective of the study was to compare a spiral breast computed tomography system (SBCT) to digital breast tomosynthesis (DBT) for the detection of microcalcifications (MCs) in breast specimens. The secondary objective was to compare various reconstruction modes in SBCT. In total, 54 breast biopsy specimens were examined with mammography as a standard reference, with DBT, and with a dedicated SBCT containing a photon-counting detector. Three different reconstruction modes were applied for SBCT datasets (Recon1 = voxel size (0.15 mm)3, smooth kernel; Recon2 = voxel size (0.05 mm)3, smooth kernel; Recon3 = voxel size (0.05 mm)3, sharp kernel). Sensitivity and specificity of DBT and SBCT for the detection of suspicious MCs were analyzed, and the McNemar test was used for comparisons. Diagnostic confidence of the two readers (Likert Scale 1 = not confident; 5 = completely confident) was analyzed with ANOVA. Regarding detection of MCs, reader 1 had a higher sensitivity for DBT (94.3%) and Recon2 (94.9%) compared to Recon1 (88.5%; p < 0.05), while sensitivity for Recon3 was 92.4%. Respectively, reader 2 had a higher sensitivity for DBT (93.0%), Recon2 (92.4%), and Recon3 (93.0%) compared to Recon1 (86.0%; p < 0.05). Specificities ranged from 84.7–94.9% for both readers (p > 0.05). The diagnostic confidence of reader 1 was better with SBCT than with DBT (DBT 4.48 ± 0.88, Recon1 4.77 ± 0.66, Recon2 4.89 ± 0.44, and Recon3 4.75 ± 0.72; DBT vs. Recon1/2/3: p < 0.05), while reader 2 found no differences. Sensitivity and specificity for the detection of MCs in breast specimens is equal for DBT and SBCT when a small voxel size of (0.05 mm)3 is used with an equal or better diagnostic confidence for SBCT compared to DBT.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Breast cancer; Microcalcifications; Reconstruction modes; Spiral breast CT

Determinants Affecting the Clinical Implementation of a Molecularly Informed Molecular Tumor Board Recommendation: Experience from a Tertiary Cancer Center. - Tögel, Lars; Schubart, Christoph; Lettmaier, Sebastian; Neufert, Clemens; Hoyer, Juliane; Wolff, Kerstin; Moskalev, Evgeny; Stöhr, Robert; Agaimy, Abbas; Wiesmann da Silva Reis, André; Wullich, Bernd; Mackensen, Andreas; et al. (Cancers, 2023)
Molecular Tumor Boards (MTBs) converge state-of-the-art next-generation sequencing (NGS) methods with the expertise of an interdisciplinary team consisting of clinicians, pathologists, human geneticists, and molecular biologists to provide molecularly informed guidance in clinical decision making to the treating physician. In the present study, we particularly focused on elucidating the factors impacting on the clinical translation of MTB recommendations, utilizing data generated from gene panel mediated comprehensive genomic profiling (CGP) of 554 patients at the MTB of the Comprehensive Cancer Center Erlangen, Germany, during the years 2016 to 2020. A subgroup analysis of cases with available follow-up data (n = 332) revealed 139 cases with a molecularly informed MTB recommendation, which was successfully implemented in the clinic in 44 (31.7%) of these cases. Here, the molecularly matched treatment was applied in 45.4% (n = 20/44) of cases for ≥6 months and in 25% (n = 11/44) of cases for 12 months or longer (median time to treatment failure, TTF: 5 months, min: 1 month, max: 38 months, ongoing at data cut-off). In general, recommendations were preferentially implemented in the clinic when of high (i.e., tier 1) clinical evidence level. In particular, this was the case for MTB recommendations suggesting the application of PARP, PIK3CA, and IDH1/2 inhibitors. The main reason for non-compliance to the MTB recommendation was either the application of non-matched treatment modalities (n = 30)/stable disease (n = 7), or deteriorating patient condition (n = 22)/death of patient (n = 9). In summary, this study provides an insight into the factors affecting the clinical implementation of molecularly informed MTB recommendations, and careful considerations of these factors may guide future processes of clinical decision making.
EVALuna2:545872
Keywords: Molecular Tumor Board; clinical decision making; precision medicine; molecular pathology; real-world data; cancer care

Development and Validation of a Confocal Laser Endomicroscopy-Based Score for In Vivo Assessment of Mucosal Healing in Ulcerative Colitis Patients - Hundorfean, Gheorghe; Chiriac, Mircea T.; Mihai, Sidonia; Hartmann, Arndt; Mudter, Jonas; Neurath, Markus (Inflammatory Bowel Diseases, 2017)
Background: Endoscopic monitoring is fundamental for evaluating the therapeutic response in IBD, but a validated endomicroscopic mucosal healing (MH) score is not available to date. However, confocal laser endomicroscopy (CLE) might define MH more precisely than conventional endoscopy. The major aim was to establish and validate an MH score for ulcerative colitis (UC), based on CLE. Methods: In an initial pilot study (n = 10), various CLE changes were analyzed for identification of reproducible criteria for establishing a CLE score. Four reproducible CLE criteria were implemented in a following validation study. Subsequently, active UC patients (n = 23, Mayo score ≥6) were prospectively included and underwent colonoscopy with CLE before and after 3 anti-TNF applications. Patients were clinically followed over a period of 3 years. The endomicroscopic MH score (eMHs; range, 0-4) was compared with histopathology and endoscopy scores from the same colonic location. Results: The eMHs showed high sensitivity, specificity, and accuracy values (100% with 95% confidence interval [CI] of 15.81%-100%; 93.75% with 95% CI of 69.77%-99.84%, and 94.44%, respectively). The eMHs showed a good correlation with the histological Gupta score (rs = 0.82, P < 0.0001) and the endoscopic Mayo subscore (rs = 0.81%, P < 0.0001). Sixty percent of therapy responders presented an eMHs <1, which translated into long-lasting clinical remission and reduced hospitalization, steroid, and surgery need. Conclusions: CLE can accurately assess MH based on the newly developed and statistically validated eMHs in UC, and it is superior in predicting the long-lasting clinical outcome based on both descriptive and functional barrier imaging (NCT01417728).
EVALuna2:33794

Diabetes and prognosis in a breast cancer cohort - Schrauder, Michael; Fasching, Peter A.; Häberle, Lothar; Lux, Michael P.; Rauh, Claudia; Hein, Alexander; Bayer, Christian M.; Heusinger, Katharina; Hartmann, Arndt; Strehl, Johanna D.; Wachter, David; Schulz-Wendtland, Rüdiger; et al. (Journal of Cancer Research and Clinical Oncology, 2011)
Purpose: Epidemiological studies indicated that type 2 diabetes mellitus may increase breast cancer risk and mortality. The aim of this retrospective cohort study was to examine the effect of diabetes on the clinical course and the prognosis of early stage breast cancer in relation to tumour and patient characteristics. Methods: The cohort analyzed in this study consisted of 4,056 patients with invasive primary breast cancer. We compared overall survival, distant metastasis-free survival and local recurrence free survival between breast cancer patients with and without diabetes. Results: In our cohort 276 breast cancer patients (6.8%) were affected by diabetes compared to 3,780 patients (93.2%) without diabetes. Women with diabetes were significantly older, had larger tumours, and a higher rate of lymph node involvement. After a follow-up period of 5 years, stratification for age and adjustment for other prognostic factors, overall mortality following breast cancer was significantly higher in diabetic breast cancer patients (hazard ratio, HR 1.92; 95% confidence interval, CI 1.49-2.48). We found no significant differences in distant metastasis-free survival and local recurrence free survival between the two groups, but we found a slightly significant higher rate of distant metastasis in the group of patients with diabetes and oestrogen receptor negative tumours (HR 2.28; CI 1.31-3.97). Conclusion: In this study, patients with diabetes and oestrogen receptor negative breast cancer had a more than 2-fold higher risk for distant metastasis compared to patients without diabetes. Diabetes was also associated with an almost 2-fold increase in mortality within the 5 years follow-up period. © 2010 Springer-Verlag.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Breast cancer; Cohort study; Diabetes mellitus; Distant metastasis; Local recurrence; Survival

Diagnostic and predictive molecular pathology of head and neck neoplasms - Agaimy, Abbas; Weichert, W.; Haller, F.; Hartmann, Arndt (Pathologe, 2018)
As a result of some seminal observations as well as a consequence of increasing use of modern and innovative molecular diagnostic technologies, a variety of new genetic aberrations have been discovered in head and neck neoplasms of different anatomic locations and histogenetic origins. These advances resulted in the establishment of new molecularly defined disease entities. On the other hand, some of these new genetic biomarkers paved the way to potentially promising novel therapeutic opportunities. Diverse old (well known in other entities) and newly discovered translocations and gene fusions represent the leading subgroup of these genetic aberrations. They have been detected not only in malignant epithelial neoplasms (carcinomas) of the salivary glands, but also in carcinomas from other head and neck sites as well as diverse mesenchymal tumors. In addition to these gene fusions, several activating mutations (such as CTNNB1 in sinonasal glomangiopericytoma) as well as inactivating mutations or deletions (like SMARCB1 loss in sinonasal carcinomas) were detected as new molecular markers. In the present review we summarize the relevant molecular alterations in topographically and histopathologically distinct tumors of the head and neck region with emphasis on recently established molecular markers.
EVALuna2:34103

Diagnostic potential of major and trace elements in the serum of bladder cancer patients - Wach, Sven; Weigelt, Katrin; Michalke, Bernhard; Lieb, Verena; Stoehr, Robert; Keck, Bastian; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; Chaudhri, Anwar (Journal of Trace Elements in Medicine and Biology, 2018)
Major and trace elements may play a role in the diagnosis of diseases. In this study, we investigated the concentration of 26 major and trace elements in the serum by inductively coupled plasma (ICP) - optical emission spectrometry (OES) and ICP-sector field-mass spectrometry (sf-MS). We analyzed the serum from a discovery cohort of 6 bladder cancer (BCa) patients and 12 healthy controls as well as from a validation cohort of 21 BCa patients, 29 non-tumor bladder patients (with acute and chronic inflammation) and 18 healthy controls. Patients were recruited after written consent was obtained at one medical center. Serum was prepared from peripheral blood prior to surgical treatment. Differences in the levels of major and trace elements were determined by a nonparametric Mann-Whitney test and Kruskal-Wallis statistics. In the discovery cohort, we measured significantly increased levels of calcium, mercury, potassium, lithium, nickel, phosphorus and strontium and a significantly decreased level of sodium in BCa patients compared with healthy controls. These findings were reassessed in our validation cohort. We measured significantly increased levels of boron, calcium, cadmium, copper, chromium, lead, lithium, potassium, magnesium, nickel, sulfur, strontium, titan, vanadium and zinc and significantly decreased levels of iron and molybdenum. When we studied the concordance for the discovery and validation cohorts, concentrations of five elements were detected as significantly increased in BCa patients compared with healthy controls: calcium, lithium, potassium, nickel, and strontium. Interestingly, the levels of three elements (calcium, potassium and strontium) were also significantly increased in non-tumor bladder patients compared with healthy controls. But no element was significantly altered between non-tumor bladder patients and BCa patients. In summary, we suggest that determination of the elements calcium, lithium, nickel and strontium in the serum could be a new and promising tool for the early diagnosis of BCa.
EVALuna2:32785

Diagnostics and prognostic evaluation in renal cell tumors: the German S3 guidelines recommendations - Junker, Kerstin; Hallscheidt, Peter; Wunderlich, Heiko; Hartmann, Arndt (World Journal of Urology, 2022)
The German guidelines on renal cell carcinoma (RCC) have been developed at highest level of evidence based on systematic literature review. In this paper, we are presenting the current recommendations on diagnostics including preoperative imaging and imaging for stage evaluation as well as histopathological classification. The role of tumor biopsy is further discussed. In addition, different prognostic scores and the status of biomarkers in RCC are critically evaluated.
CRIS-Team Scopus Importer:2022-03-25
Keywords: Imaging; Prognosis; Renal cell carcinoma; S3 guideline; Tumor biopsy

DICER1-Mutated Botryoid Fibroepithelial Polyp of the Parotid Duct: Report of the First Case - Erber, Ramona; Preidl, Raimund; Stöhr, Robert; Haller, Florian; Hartmann, Arndt; Kesting, Marco Rainer; Agaimy, Abbas (Head and Neck Pathology, 2021)
DICER1, a member of the ribonuclease III family, is involved in the biogenesis of microRNAs and, hence, it influences gene expression regulation. DICER1 germline (associated with the inherited DICER1 syndrome) or somatic mutations have been linked to tumorigenesis in histogenetically diverse benign and malignant neoplasms in different organs including pleuropulmonary blastoma, cystic nephroma, embryonal rhabdomyosarcoma, nasal chondromesenchymal hamartoma, poorly differentiated thyroid carcinoma, thyroblastoma, intracranial sarcoma and gonadal Sertoli-Leydig cell tumors in addition to others. Moreover, rare botryoid (giant) fibroepithelial polyps may harbor this mutation. Herein, we describe the first reported case of a DICER1-mutated botryoid fibroepithelial polyp occurring within the parotid duct of a 65-year-old female who has no other features or family history of the DICER1 syndrome. Based on its distinctive morphology, we tested this lesion specifically for DICER1 mutations and confirmed the presence of a pathogenic DICER1 variant with a low allele frequency, consistent with a somatic mutation.
CRIS-Team WoS Importer:2021-07-30

DICER1 mutation-positive Giant Botryoid Fibroepithelial polyp of the urinary bladder mimicking embryonal rhabdomyosarcoma - Eckstein, Markus; Agaimy, Abbas; Woenckhaus, Joachim; Winter, Alexander; Bittmann, Iris; Janzen, Joerg; Bertz, Simone; Haller, Florian; Hartmann, Arndt (Human Pathology, 2018)
Fibroepithelial polyps of the urinary tract are rare lesions. They occur mainly in the upper urinary tract of children. A high disease prevalence has been reported in families with pleuropulmonary blastoma. Here we present a case of a 46-year-old woman who presented with a giant botryoid fibroepithelial polyp of the urinary bladder. Histologically, the lesion showed prominent botryoid features with an embryonal rhabdomyosarcoma-like cambium layer lacking nuclear or cellular atypia. Immunohistochemical analysis ruled out rhabdomyoblastic differentiation. Next generation sequencing was performed on the polyp tissue and revealed two pathogenic mutations in the dicer1 ribonuclease III (DICER1) gene (c.[5439G>T]; p.[Glu1813Asp] and c.[1525C>T]; p.[Arg509*]). The Glu1813Asp DICER1 mutation has been reported in the germline of families with pleuropulmonary blastoma. Thus, our findings support the role of DICER1 mutations in the pathogenesis of fibroepithelial polyps of the urinary tract.
EVALuna2:35238

Die Akkreditierung in der Pathologie und Neuropathologie in Deutschland: Rahmenbedingungen und Voraussetzungen - Curelea, S.; Hartmann, Arndt; Varnai-Haendel, A. (Die Pathologie, 2022)
Accreditation in pathology and neuropathology in Germany is based on the requirements of the DIN EN ISO/IEC 17020 standard, which defines general requirements for the bodies performing inspections. In Germany, the national accreditation body of the Federal Republic of Germany (DAkkS) assumes the official task of accreditation. Evaluation in this area is based on a comprehensive assessment by board-certified pathologists (inspection) and is focused on correct diagnosis. The requirement of the DIN EN ISO 15189 standard on quality and competence in medical laboratories is taken into account. In Germany, more than 100 institutes of pathology and neuropathology have successfully performed the accreditation process. Interest in accreditation has been significantly growing in recent months, especially due to changes in the European law with the "Verordnung EO 2017/746 des Europaischen Parlaments und des Rates vom 05. April 2017 uber Invitro-Diagnostica". However, accreditation is a demanding process that requires very good preparation. Necessary resources for accreditation should be secured before starting the process. Important framework conditions and requirements, but also some challenges that can arise during the accreditation process, are summarized in this article.
CRIS-Team WoS Importer:2022-08-12

Differences and Similarities in the Pattern of Early Metabolic and Morphologic Response after Induction Chemo-Immunotherapy versus Induction Chemotherapy Alone in Locally Advanced Squamous Cell Head and Neck Cancer - Beck, Michael; Semrau, Sabine; Haderlein, Marlen; Gostian, Antoniu-Oreste; Hartwich, Julius; Müller, Sarina Katrin; Kallies, Annett; Geppert, Carol-Immanuel; Schonath, Miriam; Putz, Florian; Gaipl, Udo; Frey, Benjamin; et al. (Cancers, 2022)
Simple Summary There are differences and similarities when assessing the short-term therapeutic response of chemotherapy and chemotherapy plus immunotherapy using imaging techniques, which may be necessary to make treatment decisions in malignant head and neck tumors. After both chemo- and immunochemotherapy, remission becomes measurable in cross-sectional and metabolic diagnostics after only one cycle of therapy, with (18)FDG-PET/CT predicting complete remission of tumor cells in a representative biopsy better than MRI/CT examination in both therapeutic modalities. While complete tumor remission is highly likely (88%) after immunochemotherapy in tumors with low residual activity (<= 40% of initial SUV), this is less common after chemotherapy alone (65%). In metabolic nonresponse with more than 80% residual activity, the probability of complete remission nevertheless is low after chemotherapy alone (6%). After immunochemotherapy, these false nonresponders are common (35%), requiring additional diagnostics by deep biopsy. Cases of pseudoprogression with an increase of SUVmax of more than 125% of the baseline were not observed. Background: In head and neck cancer patients, parameters of metabolic and morphologic response of the tumor to single-cycle induction chemotherapy (IC) with docetaxel, cis- or carboplatin are used to decide the further course of treatment. This study investigated the effect of adding a double immune checkpoint blockade (DICB) of tremelimumab and durvalumab to IC on imaging parameters and their significance with regard to tumor cell remission. Methods: Response variables of 53 patients treated with IC+DICB (ICIT) were compared with those of 104 who received IC alone. Three weeks after one cycle, pathologic and, in some cases, clinical and endoscopic primary tumor responses were evaluated and correlated with a change in 18F-FDG PET and CT/MRI-based maximum-standardized uptake values (SUVmax) before (SUV(max)pre), after treatment (SUV(max)post) and residually (resSUV(max) in % of SUV(max)pre), and in maximum tumor diameter (D-max) before (D(max)pre) and after treatment (D(max)post) and residually (resD). Results: Reduction of SUVmax and D-max occurred in both groups; values were SUV(max)pre: 14.4, SUV(max)post: 6.6, D(max)pre: 30 mm and D(max)post: 23 mm for ICIT versus SUV(max)pre: 16.5, SUV(max)post: 6.4, D(max)pre: 21 mm, and D(max)post: 16 mm for IC alone (all p < 0.05). ResSUV(max) was the best predictor of complete response (IC: AUC: 0.77; ICIT: AUC: 0.76). Metabolic responders with resSUV(max) <= 40% tended to have a higher rate of CR to ICIT (88%; n = 15/17) than to IC (65%; n = 30/46; p = 0.11). Of the metabolic nonresponders (resSUV(max) > 80%), 33% (n = 5/15) achieved a clinical CR to ICIT versus 6% (n = 1/15) to IC (p = 0.01). Conclusions: ICIT and IC quickly induce a response and 18F-FDG PET is the more accurate modality for identifying complete remission. The rate of discrepant response, i.e., pCR with metabolic nonresponse after ICIT was >30%.
CRIS-Team WoS Importer:2022-10-21

Different Diagnostic Methods for Identification of FGFR Alteration in Advanced Urothelial Carcinomas: Proficiency Results Based on Multiple RNA Extraction Kits and Mutation Detection Methods - Weyerer, Veronika; Stoehr, Robert; Juette, Hendrik; Wirtz, Ralph; Eckstein, Markus; Roghmann, Florian; Breyer, Johannes; Porubsky, Stefan; Sikic, Danijel; Bolenz, Christian; Kriegmair, Maximilian; Hartmann, Arndt; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Differential prognostic value of MYC immunohistochemistry in subtypes of papillary renal cell carcinoma - Bellut, Julia; Bertz, Simone; Nolte, Elke; Stoehr, Christine; Polifka, Iris; Lieb, Verena; Herrmann, Edwin; Jung, Rudolf; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge; Wach, Sven (Scientific Reports, 2017)
The histomorphological subtyping of papillary renal cell carcinomas (pRCCs) has improved the predictions of patients' long-term survival. Based on our previous results, we hypothesized that the MYC proto-oncogene would show differential expression in pRCC subtypes. Using a multi-institutional cohort of 204 pRCC patients we assessed the additional value of the immunohistochemical markers MYC, MINA53, and Ki67 in predicting patient's long-term survival. The clinical endpoints were overall survival (OS) and cancer-specific survival (CSS). Nomograms were constructed to predict each patient's risk of death (OS). The incorporation of the MYC staining patterns allowed the stratification of pRCC type 1 patients into better and worse prognostic groups. None of the patients with pRCC type 1 tumors and favorable MYC staining patterns died from tumor-related causes. This prognostic value was independent of the patient's age at surgery, the pathological tumor stage and presence of lymph node invasion. we could show that the immunohistochemical assessment of MYC and the histomorphological subtyping of pRCC stratifies pRCC type 1 tumors with regard to OS and CSS. The determination of the histomorphologic pRCC subtype in combination with the MYC immunohistochemical staining patterns allows a more accurate prediction of patients' individual risk of death.
EVALuna2:33570

Digital pathology imaging and computer-aided diagnostics as a novel tool for standardization of evaluation of aganglionic megacolon (Hirschsprung disease) histopathology - Schilling, Florian; Geppert, Carol-Immanuel; Strehl, Johanna; Hartmann, Arndt; Kürten, Stefanie; Brehmer, Axel; Jabari, Samir (Cell and Tissue Research, 2018)
Based on a recently introduced immunohistochemical panel (Bachmann et al. 2015) for aganglionic megacolon (AM), also known as Hirschsprung disease, histopathological diagnosis, we evaluated whether the use of digital pathology and 'machine learning' could help to obtain a reliable diagnosis. Slides were obtained from 31 specimens of 27 patients immunohistochemically stained for MAP2, calretinin, S100β and GLUT1. Slides were digitized by whole slide scanning. We used a Definiens Developer Tissue Studios as software for analysis. We configured necessary parameters in combination with 'machine learning' to identify pathological aberrations. A significant difference between AM- and non-AM-affected tissues was found for calretinin (AM 0.55% vs. non-AM 1.44%) and MAP2 (AM 0.004% vs. non-AM 0.07%) staining measurements and software-based evaluations. In contrast, S100β and GLUT1 staining measurements and software-based evaluations showed no significant differences between AM- and non-AM-affected tissues. However, no difference was found in comparison of suction biopsies with resections. Applying machine learning via an ensemble voting classifier, we achieved an accuracy of 87.5% on the test set. Automated diagnosis of AM by applying digital pathology on immunohistochemical panels was successful for calretinin and MAP2, whereas S100β and GLUT1 were not effective in diagnosis. Our method suggests that software-based approaches are capable of diagnosing AM. Our future challenge will be the improvement of efficiency by reduction of the time-consuming need for large pre-labelled training data. With increasing technical improvement, especially in unsupervised training procedures, this method could be helpful in the future.
EVALuna2:35208

Discrimination analysis of breast calcifications using x-ray dark-field radiography - Rauch, Thomas; Rieger, Jens; Pelzer, Georg; Horn, Florian; Erber, Ramona; Wunderle, Marius; Emons, Julius; Nabieva, Naiba; Fuhrich, Nicole; Michel, Thilo; Hartmann, Arndt; Fasching, Peter; et al. (Medical Physics, 2020)
Background X-ray dark-field radiography could enhance mammography by providing more information on imaged tissue and microcalcifications. The dark field signal is a measure of small angle scattering and can thus provide additional information on the imaged materials. This information can be useful for material distinction of calcifications and the diagnosis of breast cancer by classifying benign and malign association of these calcifications.
CRIS-Team WoS Importer:2020-03-06

Distinct genetic alterations and luminal molecular subtype in nested variant of urothelial carcinoma - Weyerer, Veronika; Weisser, Rebecca; Moskalev, Evgeny; Haller, Florian; Stöhr, Robert; Eckstein, Markus; Zinnall, Ulrike; Gaisa, Nadine T.; Comperat, Eva; Perren, Aurel; Keck, Bastian; Allory, Yves; et al. (Histopathology, 2019)
Aims Nested variant of urothelial carcinoma (NVUC) is rare, and only a few small series exist. Molecular characteristics and the classifying marker profile as well as therapeutic targets of this specific variant are mostly unknown. The aim of this study was to characterise NVUC at the molecular level in one of the largest cohorts to date. In addition, we applied an immunohistochemical marker panel in order to define the molecular subtype. Methods and results Sixty NVUC cases were collected from different departments. TERT promoter mutation analysis was carried out in all samples using SNaPshot analysis. Targeted sequencing of 48 cancer-related genes by next-generation sequencing (NGS) analysis was performed in a subset of 26 cases. Immunohistochemical markers CD44, CK5, CK14, EGFR, p63, FOXA1, GATA3, CD24 and CK20 were used to elucidate the molecular subtype. A total of 62.5% of NVUC cases harboured a mutation of the TERT promoter. Additionally, TP53, JAK3 and CTNNB1 were among the most frequently mutated genes identified by NGS analysis. Subtyping revealed that all NVUC express luminal markers such as CD24, FOXA1, GATA3 and CK20. Conclusions In summary, NVUC belong to the luminal molecular subtype. Moreover, a subset of NVUC seems to be characterised by mutations of the Wnt and inflammatory pathways, including JAK3 mutations, indicating a different biological background compared to conventional urothelial bladder cancer.
CRIS-Team WoS Importer:2019-11-01

Distinct genetic alterations and luminal molecular subtype in nested variant of urothelial carcinoma - Weyerer, Veronika; Weisser, R.; Moskalev, Evgeny; Haller, Florian; Stoehr, R.; Eckstein, Markus; Zinnall, U.; Gaisa, N. T.; Comperat, E.; Perren, A.; Keck, Bastian; Allory, Y.; et al. (Virchows Archiv, 2019)
CRIS-Team WoS Importer:2019-09-27

DMBT1 expression and neutrophil-to-lymphocyte ratio during necrotizing enterocolitis are influenced by impaired perfusion due to cardiac anomalies. - Diez, Sonja; Besendörfer, Manuel; Weyerer, Veronika; Hartmann, Arndt; Moosmann, Julia; Weiss, Christel; Renner, Marcus; Müller, Hanna (Molecular and Cellular Pediatrics, 2022)
BACKGROUND: Deleted in malignant brain tumors 1 (DMBT1) is involved in innate immunity and epithelial differentiation. It has been proven to play a role in various states of inflammation or hypoxia of fetal gastrointestinal and pulmonary diseases. Discrimination of pathogenesis in necrotizing enterocolitis (NEC) based on cardiac status improves the understanding of NEC in different patient subgroups. We aimed at examining DMBT1 expressions regarding their association with cardiac status leading to impaired intestinal perfusion, intraoperative bacteria proof, and a fulminant course of NEC. METHODS: Twenty-eight patients with NEC were treated surgically between 2010 and 2019 at our institution. DMBT1 expression was examined in intestinal sections using immunohistochemistry to detect DMBT1 protein. Associations of clinical parameters and DMBT1 expression were analyzed. RESULTS: We examined DMBT1 levels in 10 patients without cardiac defects and 18 patients with persisting ductus arteriosus (PDA) and congenital heart defects (CHD). Compared to patients without cardiac malformations, DMBT1 levels tended to score higher in patients with PDA/CHD (p = 0.2113) and were negatively correlated with C-reactive protein in these infants (p = 0.0172; r = - 0.5533). The number of DMBT1-expressing macrophages was elevated in the PDA/CHD-subgroup (p = 0.0399). Ratios of neutrophils and monocytes to lymphocytes were significantly higher in infants with PDA/CHD (p = 0.0319 and 0.0493). DMBT1 expression was significantly associated with positive bacterial culture of intraoperative swabs (p = 0.0252) and DMBT1 expression of the serosa was associated with a fulminant course of NEC (p = 0.0239). CONCLUSIONS: This study demonstrates that DMBT1 expression may be influenced by cardiac anomalies with an impaired intestinal perfusion in the neonatal intestine. NEC in PDA/CHD infants is associated with more DMBT1-positive macrophages and a significantly elevated neutrophil-to-lymphocyte ratio.
EVALuna2:497662
Keywords: DMBT1; Deleted in malignant brain tumors 1; Necrotizing enterocolitis; Congenital heart disease; Neutrophil-to-lymphocyte ratio; Monocyte-to-lymphocyte ratio

DNA demethylation and tri-methylation of H3K4 at the TACSTD2 promoter are complementary players for TROP2 regulation in colorectal cancer cells - Gehring, Annemarie; Hübner, Kerstin; Rani, H.; Erlenbach-Wünsch, Katharina; Merkel, Susanne; Mahadevan, Vijayalakshmi; Grützmann, Robert; Hartmann, Arndt; Schneider-Stock, Regine (Scientific Reports, 2024)
TROP2 is a powerful cancer driver in colorectal cancer cells. Divergent epigenetic regulation mechanisms for the corresponding TACSTD2 gene exist such as miRNAs or DNA methylation. However, the role of TACSTD2 promoter hypermethylation in colorectal cancer has not been investigated yet. In this study, TROP2 expression strongly correlated with promoter methylation in different colorectal tumor cell lines. Treatment with 5-Azacytidine, a DNMT1 inhibitor, led to demethylation of the TACSTD2 promoter accompanied by an increase in TROP2 protein expression. TROP2 expression correlated with promoter methylation in vivo in human colon tumor tissue, thereby verifying promoter methylation as an important factor in the regulation of TROP2 expression in colorectal cancer. When performing a ChIP-Seq analysis in HCT116 and HT29 cells, we found that TACSTD2 promoter demethylation was accompanied by tri-methylation of H3K4. In silico analysis of GSE156613 data set confirmed that a higher binding of histone mark H3K4me3 around the TACSTD2 promoter was found in TACSTD2 high expressing tumors of colon cancer patients compared to the corresponding adjacent tumor tissue. Moreover, the link between TROP2 and the H3K4me3 code was even evident in tumors showing high intratumoral heterogeneity for TROP2 staining. Our data provide novel evidence for promoter demethylation and simultaneous gains of the active histone mark H3K4me3 across CpG-rich sequences, both being complementary mechanisms in the transcriptional regulation of TACSTD2 in colon cancer. The functional consequences of TROP2 loss in colorectal cancer needs to be further investigated.
CRIS-Team Scopus Importer:2024-02-16

Domain Transfer in Histopathology using Multi-ProtoNets with Interactive Prototype Adaptation - Kletzander, Rosalie; Kuritcyn, Petr; Bruns, Volker; Benz, Michaela; Eckstein, Markus; Geppert, Carol-Immanuel; Hartmann, Arndt (Current Directions in Biomedical Engineering, 2023)
Few-shot learning addresses the problem of classification when little data or few labels are available. This is especially relevant in histopathology, where labeling must be carried out by highly trained medical experts. Prototypical Networks promise transferability to new domains by using a pre-Trained encoder and classifying by way of a prototypical representation of each class learned with few samples. We examine the applicability of this approach by attempting domain transfer from colon tissue (for training the encoder) to urothelial tissue. Furthermore, we address the problems arising from representing a class via a small amount of representatives (prototypes) by testing two different prototype calculation strategies. We compare the original "Prototype per Class"(PPC) approach to our "Prototype per Annotation"(PPA) method, which calculates one prototype for each example annotation made by the pathologist. We test the domain transfer capability of our approach on a dataset of 55 whole slide images (WSIs) containing six subtypes of urothelial carcinoma in two granularities: "Superclasses", which combines the tumorous subtypes into a single "tumor"class on top of a aggregated "healthy"and additional "necrosis"class, and "subtypes", which considers all eleven classes separately. We evaluate the classic PPC approach as well as our PPA approach on this data set. Our results show that the adaptation of the Prototypical Network from colon tissue to urothelial tissue was successful, yielding an F1 score of 0.91 for the "superclasses". Furthermore, the PPA approach performs very comparably to the PPC strategy. This makes it a viable alternative that places more value on the intent of the pathologist during annotation.
CRIS-Team Scopus Importer:2023-10-20
Keywords: domain transfer; few-shot learning; histopathology; prototype calculation strategy; Prototypical Networks; urothelial carcinoma

Dose-Response Association of CD8+ Tumor-Infiltrating Lymphocytes and Survival Time in High-Grade Serous Ovarian Cancer - Goode, Ellen L.; Block, Matthew S.; Kalli, Kimberly R.; Vierkant, Robert A.; Chen, Wenqian; Fogarty, Zachary C.; Gentry-Maharaj, Aleksandra; Toloczko, Aleksandra; Hein, Alexander; Bouligny, Aliecia L.; Jensen, Allan; Osorio, Ana; et al. (JAMA Oncology, 2017)
Importance: Cytotoxic CD8+ tumor-infiltrating lymphocytes (TILs) participate in immune control of epithelial ovarian cancer; however, little is known about prognostic patterns of CD8+ TILs by histotype and in relation to other clinical factors. Objective: To define the prognostic role of CD8+ TILs in epithelial ovarian cancer. Design, Setting, and Participants: This was a multicenter observational, prospective survival cohort study of the Ovarian Tumor Tissue Analysis Consortium. More than 5500 patients, including 3196 with high-grade serous ovarian carcinomas (HGSOCs), were followed prospectively for over 24 650 person-years. Exposures: Following immunohistochemical analysis, CD8+ TILs were identified within the epithelial components of tumor islets. Patients were grouped based on the estimated number of CD8+ TILs per high-powered field: negative (none), low (1-2), moderate (3-19), and high (≥20). CD8+ TILs in a subset of patients were also assessed in a quantitative, uncategorized manner, and the functional form of associations with survival was assessed using penalized B-splines. Main Outcomes and Measures: Overall survival time. Results: The final sample included 5577 women; mean age at diagnosis was 58.4 years (median, 58.2 years). Among the 5 major invasive histotypes, HGSOCs showed the most infiltration. CD8+ TILs in HGSOCs were significantly associated with longer overall survival; median survival was 2.8 years for patients with no CD8+ TILs and 3.0 years, 3.8 years, and 5.1 years for patients with low, moderate, or high levels of CD8+ TILs, respectively (P value for trend = 4.2 × 10−16). A survival benefit was also observed among women with endometrioid and mucinous carcinomas, but not for those with the other histotypes. Among HGSOCs, CD8+ TILs were favorable regardless of extent of residual disease following cytoreduction, known standard treatment, and germline BRCA1 pathogenic mutation, but were not prognostic for BRCA2 mutation carriers. Evaluation of uncategorized CD8+ TIL counts showed a near-log-linear functional form. Conclusions and Relevance: This study demonstrates the histotype-specific nature of immune infiltration and provides definitive evidence for a dose-response relationship between CD8+ TILs and HGSOC survival. That the extent of infiltration is prognostic, not merely its presence or absence, suggests that understanding factors that drive infiltration will be the key to unraveling outcome heterogeneity in this cancer.
EVALuna2:34270

Downregulation of Checkpoint Protein Kinase 2 in the Urothelium of Healthy Male Tobacco Smokers - Breyer, Johannes; Denzinger, Stefan; Hartmann, Arndt; Otto, Wolfgang (Urologia Internationalis, 2016)
With this letter to the editor we present for the first time a study on CHEK2 expression in normal urothelium of healthy male smokers, former smokers and non-smokers. We could show a statistically significant downregulation of this DNA repair gene in current smokers compared to non-smokers, suggesting that smoking downregulates CHEK2 in normal urothelium, probably associated with an early step in carcinogenesis of urothelial bladder carcinoma.
EVALuna2:6921

Downregulation of P-cadherin expression in hepatocellular carcinoma induces tumorigenicity - Bauer, Richard; Valletta, Daniela; Bauer, Karin; Thasler, Wolfgang E.; Hartmann, Arndt; Mueller, Martina; Reichert, Torsten E.; Hellerbrand, Claus (International Journal of Clinical and Experimental Pathology, 2014)
P-cadherin is a major contributor to cell-cell adhesion in epithelial tissues, playing pivotal roles in important morphogenetic and differentiation processes and in maintaining tissue integrity and homeostasis. Alterations of P-cadherin expression have been observed during the progression of several carcinomas where it appears to act as tumor suppressive or oncogenic in a context-dependent manner. Here, we found a significant downregulation of P-cadherin in hepatocellular carcinoma (HCC) cell lines and tissues compared to primary human hepatocytes and non-malignant liver tissues. Combined immunohistochemical analysis of a tissue microarray containing matched pairs of HCC tissue and corresponding non-tumorous liver tissue of 69 patients confirmed reduced P-cadherin expression in more than half of the cases. In 35 human HCC tissues, the P-cadherin immunosignal was completely lost which correlated with tumor staging and proliferation. Also in vitro, P-cadherin suppression in HCC cells via siRNA induced proliferation compared to cells transfected with control-siRNA. In summary, downregulation of P-cadherin expression appears to induce tumorigenicity in HCC. Therefore, P-cadherin expression may serve as a prognostic marker and therapeutic target of this highly aggressive tumor.
EVALuna2:6674

Early CRP kinetics predict long-term treatment success and favorable outcomes of anti-PD-(L)1 immune checkpoint blockade in metastatic urothelial carcinoma - Klümper, Niklas; Sikic, Danijel; Saal, Jonas; Buettner, Thomas; Jarczyk, Jonas; Zeuschner, Philip; Weinke, Maximilan; Kalogirou, Charis; Breyer, Johannes; Burger, Maximilian; Nuhn, Philipp; Tully, Karl; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Easy performance of 6-color confocal immunofluorescence with 4-laser line microscopes - Eissing, Nathalie; Heger, Lukas; Baranska, Anna; Cesnjevar, Robert; Büttner, Maike; Söder, Stephan; Hartmann, Arndt; Heidkamp, Gordon Frederik; Dudziak, Diana (Immunology Letters, 2014)
Confocal laser scanning microscopy is an advanced technique for imaging tissue samples in vitro and in vivo at high optical resolution. The development of new fluorochrome variants do not only make it possible to perform multicolor flow cytometry of single cells, but in combination with high resolution laser scanning systems also to investigate the distribution of cells in lymphoid tissues by confocal immunofluorescence analyses, thus allowing the distinction of various cell populations directly in the tissue. Here, we provide a protocol for the visualization of at least six differently fluorochrome-labeled antibodies at the same time using a conventional confocal laser scanning microscope with four laser lines (405 nm, 488 nm, 555 nm, and 639 nm laser wavelength) in both murine and human tissue samples. We further demonstrate that compensation correction algorithms are not necessary to reduce spillover of fluorochromes into other channels when the used fluorochromes are combined according to their specific emission bands and the varying Stokes shift for co-excited fluorochromes with the same laser line.
EVALuna2:6626

EAU-ESMO consensus statements on the management of advanced and variant bladder cancer-an international collaborative multi-stakeholder effort: under the auspices of the EAU and ESMO Guidelines Committees†. - Horwich, A.; Babjuk, M.; Bellmunt, J.; Bruins, H. M.; De Reijke, T. M.; De Santis, M.; Gillessen, Silke; James, Nick; Maclennan, Steven; Palou, J.; Powles, T.; Ribal, M. J.; et al. (Annals of Oncology, 2019)
BACKGROUND: Although guidelines exist for advanced and variant bladder cancer management, evidence is limited/conflicting in some areas and the optimal approach remains controversial. OBJECTIVE: To bring together a large multidisciplinary group of experts to develop consensus statements on controversial topics in bladder cancer management. DESIGN: A steering committee compiled proposed statements regarding advanced and variant bladder cancer management which were assessed by 113 experts in a Delphi survey. Statements not reaching consensus were reviewed; those prioritised were revised by a panel of 45 experts before voting during a consensus conference. SETTING: Online Delphi survey and consensus conference. PARTICIPANTS: The European Association of Urology (EAU), the European Society for Medical Oncology (ESMO), experts in bladder cancer management. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Statements were ranked by experts according to their level of agreement: 1-3 (disagree), 4-6 (equivocal), 7-9 (agree). A priori (level 1) consensus was defined as ≥70% agreement and ≤15% disagreement, or vice versa. In the Delphi survey, a second analysis was restricted to stakeholder group(s) considered to have adequate expertise relating to each statement (to achieve level 2 consensus). RESULTS AND LIMITATIONS: Overall, 116 statements were included in the Delphi survey. Of these, 33 (28%) statements achieved level 1 consensus and 49 (42%) statements achieved level 1 or 2 consensus. At the consensus conference, 22 of 27 (81%) statements achieved consensus. These consensus statements provide further guidance across a broad range of topics, including the management of variant histologies, the role/limitations of prognostic biomarkers in clinical decision making, bladder preservation strategies, modern radiotherapy techniques, the management of oligometastatic disease and the evolving role of checkpoint inhibitor therapy in metastatic disease. CONCLUSIONS: These consensus statements provide further guidance on controversial topics in advanced and variant bladder cancer management until a time where further evidence is available to guide our approach.
EVALuna2:208656

EAU-ESMO Consensus Statements on the Management of Advanced and Variant Bladder Cancer-An International Collaborative Multistakeholder Effort Under the Auspices of the EAU-ESMO Guidelines Committees - Witjes, J. Alfred; Babjuk, Marek; Bellmunt, Joaquim; Bruins, H. Maxim; De Reijke, Theo M.; De Santis, Maria; Gillessen, Silke; James, Nicholas; Maclennan, Steven; Palou, Juan; Powles, Tom; Ribal, Maria J.; et al. (European Urology, 2020)
Background: Although guidelines exist for advanced and variant bladder cancer management, evidence is limited/conflicting in some areas and the optimal approach remains controversial.
CRIS-Team WoS Importer:2020-01-28

Efficacy of anti-PD(L)1 treatment in patients with metastatic urothelial cancer based on mRNA- and protein- based PD-L1 determination: Results from the multicentric, retrospective FOsMIC trial - Jarczyk, J.; Wirtz, R.; Roghmann, F.; Juette, H.; Kriegmair, M. C.; Worst, T. S.; Sikic, D.; Wach, S.; Taubert, Helge; Wullich, Bernd; Weyerer, Veronika; Stöhr, Robert; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Efficacy of neoadjuvant pertuzumab in addition to chemotherapy and trastuzumab in routine clinical treatment of patients with primary breast cancer: a multicentric analysis - Fasching, Peter; Hartkopf, Andreas D.; Gaß, Paul; Häberle, Lothar; Akpolat-Basci, Leyla; Hein, Alexander; Volz, Bernhard; Taran, Florin-Andrei; Nabieva, Naiba; Pott, Birgit; Overkamp, Friedrich; Einarson, Hanna; et al. (Breast Cancer Research and Treatment, 2019)
PurposeNeoadjuvant combination treatment with chemotherapy (CTX), trastuzumab (TZM), and pertuzumab (PTZ) has been shown to result in higher pathological complete response rates (pCR) in comparison with treatment with chemotherapy and trastuzumab (CTX/TZM). This analysis was aimed at real-world validation of these results from prospective randomized trials.MethodsIn a retrospective analysis conducted in the PRAEGNANT network, patients were eligible for inclusion if they had either received neoadjuvant therapy with CTX/TZM or chemotherapy, trastuzumab, and pertuzumab (CTX/TZM/PTZ) and subsequently underwent surgery for their primary breast cancer. The effect of the two neoadjuvant regimens on pCR in addition to commonly applicable predictors of pCR was analyzed in 300 patients from three study sites, using logistic regression analyses with treatment arm, age, clinical tumor stage, grading, and hormone receptor status as predictors.ResultspCR with complete disappearance of all tumor cells was seen in 30.2% (n=58) of patients treated with CTX/TZM and in 52.8% (n=57) of those treated with CTX/TZM/PTZ. CTX/TZM/PTZ was positively associated with pCR (adjusted odds ratio 2.44; 95% CI 1.49-4.02). Mastectomy rates were not influenced by the therapy.ConclusionsThe results of clinical trials were confirmed in this dataset of patients who were treated outside of clinical trials in everyday routine work. pCR rates can be improved by 20% with pertuzumab in routine clinical use.
CRIS-Team WoS Importer:2019-03-15

EGFR Mutation Testing Using Liquid Biopsy Technology for Patients with Advanced EGFR-Mutant NSCLC - Seitz, Jan; Moskalev, Evgeny; Fuchs, Florian; Haller, Florian; Hartmann, Arndt (2018)
EVALuna2:34073

EMT transcription factor ZEB1 alters the epigenetic landscape of colorectal cancer cells - Lindner, Pablo; Paul, Sushmita; Eckstein, Markus; Hampel, Chuanpit; Muenzner, Julienne K.; Erlenbach-Wuensch, Katharina; Ahmed, Husayn P.; Mahadevan, Vijayalakshmi; Brabletz, Thomas; Hartmann, Arndt; Vera, Julio; Schneider-Stock, Regine (Cell Death & Disease, 2020)
Epigenetic deregulation remarkably triggers mechanisms associated with tumor aggressiveness like epithelial–mesenchymal transition (EMT). Since EMT is a highly complex, but also reversible event, epigenetic processes such as DNA methylation or chromatin alterations must be involved in its regulation. It was recently described that loss of the cell cycle regulator p21 was associated with a gain in EMT characteristics and an upregulation of the master EMT transcription factor ZEB1. In this study, in silico analysis was performed in combination with different in vitro and in vivo techniques to identify and verify novel epigenetic targets of ZEB1, and to proof the direct transcriptional regulation of SETD1B by ZEB1. The chorioallantoic-membrane assay served as an in vivo model to analyze the ZEB1/SETD1B interaction. Bioinformatical analysis of CRC patient data was used to examine the ZEB1/SETD1B network under clinical conditions and the ZEB1/SETD1B network was modeled under physiological and pathological conditions. Thus, we identified a self-reinforcing loop for ZEB1 expression and found that the SETD1B associated active chromatin mark H3K4me3 was enriched at the ZEB1 promoter in EMT cells. Moreover, clinical evaluation of CRC patient data showed that the simultaneous high expression of ZEB1 and SETD1B was correlated with the worst prognosis. Here we report that the expression of chromatin modifiers is remarkably dysregulated in EMT cells. SETD1B was identified as a new ZEB1 target in vitro and in vivo. Our study demonstrates a novel example of an activator role of ZEB1 for the epigenetic landscape in colorectal tumor cells.
CRIS-Team Scopus Importer:2020-03-20

En-bloc resection of bladder tumours (ERBT): current and future perspectives - Struck, J. P.; Kramer, M. W.; Merseburger, A. S.; Hartmann, Arndt; Herrmann, T. R. W. (Aktuelle Urologie, 2017)
Limitations inherent in the conventional transurethral resection of bladder tumours, the standard approach for diagnosis and treatment of bladder cancer, are well known: staging errors due to insufficient resection depth as well as intravesical tumour fragmentation, both of which make histopathological evaluation difficult. The purpose of this review is to present recent clinical data on the en-bloc resection of bladder tumours (ERBT), which has been demonstrated to offer a high potential to overcome these limitations. The recent findings show that ERBT provides a good resection quality with varying detection rates for tunica muscularis, which is a surrogate marker for resection quality regarding muscle-invasive tumours. ERBT can be performed using all energy sources. Available data show no relevant difference with regard to perioperative morbidity compared with cTURB. No conclusions can be drawn regarding the impact of ERBT on recurrence as the data are partly controversial. This has to be defined by further studies.
EVALuna2:6865

Endocytoscopy for assessing histologic inflammation in ulcerative colitis: development and prospective validation of the ELECT (ErLangen Endocytoscopy in ColiTis) score (with videos) - Vitali, Francesco; Morgenstern, Nadine; Eckstein, Markus; Atreya, Raja; Waldner, Maximilian; Hartmann, Arndt; Neurath, Markus; Rath, Timo (Gastrointestinal Endoscopy, 2022)
Background and Aims: Apart from endoscopic healing as an established treatment goal in patients with inflammatory bowel disease (IBD), histologic remission is an emerging endpoint that might even better predict disease outcome, especially in ulcerative colitis (UC). Within this study, we aimed to evaluate whether endocytoscopy (EC) as an in vivo contact microscopy technology can accurately assess histologic inflammation and predict the further course of disease in UC patients. Methods: Initially, a new and intuitive EC score reflecting the entire spectrum of microscopic disease activity in UC was consensually developed. Subsequently, this score was independently validated in 46 patients with UC who underwent close-meshed follow-up during which major adverse outcomes (MAOs; defined as disease flare, IBD-related hospitalization, IBD-related surgery, necessity for initiation or escalation therapy) were recorded. Results of EC grading of inflammatory activity were compared against 2 validated histologic scores in UC. Diagnostic performance of endoscopic remission under white-light endoscopy (Mayo Endoscopic Score and Ulcerative Colitis Endoscopic Index of Severity), EC, and histology were compared for the prediction of MAOs. Results: Endocytoscopic assessment of inflammatory activity in UC based on the newly developed ErLangen Endocytoscopy in ColiTis score showed strong correlation with histopathologic scoring (Robarts Histopathology Index, r = .70; Nancy Histologic Index, r = .73) and was superior to white-light endoscopy for grading of microscopic disease activity, with a sensitivity of 88%, specificity of 95.2%, and area under the curve of .916. Furthermore, EC exhibited a high interobserver agreement for in vivo grading of microscopic inflammation and was comparably accurate as histopathology for forecasting the occurrence of MAOs in UC. Conclusions: Endocytoscopic grading of inflammatory activity along a newly developed scoring system enabled real-time histology in UC patients and better predicted clinical outcome in UC patients than endoscopic remission.
CRIS-Team Scopus Importer:2022-12-16

Endogenous Retroviral-K Envelope Is a Novel Tumor Antigen and Prognostic Indicator of Renal Cell Carcinoma - Weyerer, Veronika; Strissel, Pamela; Stohr, Christine; Eckstein, Markus; Wach, Sven; Taubert, Helge; Brandl, Lisa; Geppert, Carol-Immanuel; Wullich, Bernd; Cynis, Holger; Beckmann, Matthias; Seliger, Barbara; et al. (Frontiers in Oncology, 2021)
Renal cell carcinoma (RCC) is one of the ten most common cancers for men and women with an approximate 75% overall 5-year survival. Sixteen histological tumor subtypes exist and the most common are papillary, chromophobe and clear cell renal cell carcinoma (ccRCC) representing 85% of all RCC. Although epigenetically silenced, endogenous retroviral (ERV) genes become activated in tumors and function to ignite immune responses. Research has intensified to understand ERV protein function and their role as tumor antigens and targets for cancer (immune) therapy. ERV-K env is overexpressed and implicated as a therapeutic target for breast cancer, however studies in RCC are limited. In this investigation a human RCC tissue microarray (TMA) (n=374) predominantly consisting of the most common histological tumor subtypes was hybridized with an ERV-K env antibody and correlated with patient clinical data. TMA results showed the highest amount of ERV-K env protein expression and the strongest significant membrane expression in ccRCC versus other RCC subtypes. High ERV-K env total protein expression of all tumor subtypes significantly correlated with low tumor grading and a longer disease specific survival using multivariable analyses. Cell proliferation and invasion were assayed using the kidney cell lines HEK293 with wild-type p53 and a ccRCC cell line MZ1257RC mutated for p53. Transfecting these cell lines with a codon optimized ERV-K113 env overexpressing CMV vector was performed with or without 5'-Aza-2'-deoxycytidine (Aza) treatment to sustain promoter de-methylation. MZ1257RC showed induction of ERV-K113 expression and significantly increased both proliferation and invasion in the presence or absence of Aza. HEK293 cells demonstrated a restriction of ERV-K113 env expression and invasion with no changes in proliferation in the absence of Aza. However, in the presence of Aza despite increased ERV-K113 env expression, an inhibition of HEK293 proliferation and a further restriction of invasion was found. This study supports ERV-K env as a single prognostic indicator for better survival of RCC, which we propose represents a new tumor antigen. In addition, ERV-K env significantly regulates proliferation and invasion depending on p53 status and Aza treatment.
CRIS-Team WoS Importer:2021-05-14
Keywords: tumor antigen; renal cell carcinoma; patient prognosis; p53; ERV-K; invasion; azacytidine; endogenous retrovirus

Endometrial Dating Method Detects Individual Maturation Sequences During the Secretory Phase - Alfer, Joachim; Fattahi, Amir; Bleisinger, Nathalie; Krieg, JÜrgen; Behrens, Rolf; Dittrich, Ralf; Beckmann, Matthias; Hartmann, Arndt; Classen-Linke, Irmgard; Popovici, Roxana M. (In Vivo, 2020)
BACKGROUND/AIM: This study assessed whether a new immunohistochemical dating method allows precise endometrial dating allowing optimal timing for embryo transfer. PATIENTS AND METHODS: A novel method was used for endometrial dating, with parameters including menstrual cycle days, Noyes histological criteria, along with immunohistochemical expression pattern of estrogen and progesterone receptors and proliferation marker Ki-67. Endometrial maturation was analyzed on days +5 to +10 after ovulation or progesterone administration in 217 biopsies from 151 subfertile patients during the secretory phase. RESULTS: Endometrial maturation varied individually, occurring 1.68±1.67 days late. Comparison of histological maturation with clinical days after ovulation showed a delay of about 2 days. CONCLUSION: Endometrial maturation requires 8 days, rather than the expected 6 days, to reach the histological mid-secretory phase. This is not a delay and is also seen in fertile patients. The new analysis method used is superior to that using Noyes criteria alone and provides a better basis for determining conditions for optimal timing of embryo transfers.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Endometrial dating; endometrial receptivity; estrogen receptor; progesterone receptor; window of implantation

Endometrial delay is found to be part of a normal individual dynamic transformation process - Alfer, Joachim; Popovici, Roxana M.; Fattahi, Amir; Krieg, Juergen; Dittrich, Ralf; Beckmann, Matthias; Hartmann, Arndt; Bleisinger, Nathalie (Archives of Gynecology and Obstetrics, 2021)
Purpose: Limited information is clinically available concerning endometrial receptivity; assessing endometrial transformation status is therefore an urgent topic in assisted reproductive technology. This study aimed to investigate individual endometrial transformation rates during the secretory phase in subfertile patients using personal endometrial transformation analysis. Methods: Monitoring was carried out during the secretory phase to obtain endometrial receptivity profiles. For the investigation, two endometrial biopsies were taken within one menstrual cycle. The extended endometrial dating was based on the Noyes criteria, combined with immunohistochemical analyses of hormone receptors and proliferation marker Ki-67. Biopsies were taken mainly at days ovulation (OV, n = 76)/hormone replacement therapy (HRT, n = 58) + 5 and + 10. Results: The results of the two biopsies were correlated with the clinically expected day of the cycle and showed temporal delays or hypercompensations, diverging from the expected cycle days by 0.5–5 days. In comparison with the first biopsies, the transformation rate in the second biopsies showed compensation, augmented delay, or constant transformation in 48.69, 22.37, and 28.94% of cases for ovulation in natural cycles and 56.89, 25.85, and 17.26% for HRT cycles, respectively. Conclusion: The study revealed an individually dynamic transformation process of the endometrium, with the ability to compensate or enlarge an initial “delay”, which is now identified as a normal individual transformation process during the secretory phase. This information is of great importance for the scientific investigation of dynamic changes in endometrial tissue, as well as for the timing of embryo transfers.
CRIS-Team Scopus Importer:2021-07-02
Keywords: Delay; Endometrium; Maturation; Receptivity

Endometriosis as a risk factor for ovarian or endometrial cancer - results of a hospital-based case-control study - Burghaus, Stefanie; Haeberle, Lothar; Schrauder, Michael G.; Heusinger, Katharina; Thiel, Falk; Hein, Alexander; Wachter, David; Strehl, Johanna; Hartmann, Arndt; Ekici, Arif Bülent; Renner, Stefan; Beckmann, Matthias; et al. (BMC Cancer, 2015)
No screening programs are available for ovarian or endometrial cancer. One reason for this is the low incidence of the conditions, resulting in low positive predictive values for tests, which are not very specific. One way of addressing this problem might be to use risk factors to define subpopulations with a higher incidence. The aim of this study was to investigate the extent to which a medical history of endometriosis can serve as a risk factor for ovarian or endometrial cancer.In a hospital-based case-control analysis, the cases represented patients with endometrial or ovarian cancer who were participating in studies aimed at assessing the risk for these diseases. The controls were women between the age of 40 and 85 who were invited to take part via a newspaper advertisement. A total of 289 cases and 1016 controls were included. Using logistic regression models, it was tested whether self-reported endometriosis is a predictor of case-control status in addition to age, body mass index (BMI), number of pregnancies and previous oral contraceptive (OC) use.Endometriosis was reported in 2.1 % of the controls (n = 21) and 4.8 % of the cases (n = 14). Endometriosis was a relevant predictor for case-control status in addition to other predictive factors (OR 2.63; 95 % CI, 1.28 to 5.41).This case-control study found that self-reported endometriosis may be a risk factor for endometrial or ovarian cancer in women between 40 and 85 years. There have been very few studies addressing this issue, and incorporating it into a clinical prediction model would require a more precise characterization of the risk factor of endometriosis.
EVALuna2:6731

Enhanced Acid Sphingomyelinase Activity Drives Immune Evasion and Tumor Growth in Non-Small Cell Lung Carcinoma - Kachler, Katerina; Bailer, Maximilian; Heim, Lisanne; Schumacher, Fabian; Reichel, Martin; Holzinger, Corinna D.; Trump, Sonja; Mittler, Susanne; Monti, Juliana; Trufa, Denis; Rieker, Ralf; Hartmann, Arndt; et al. (Cancer Research, 2017)
The lipid hydrolase enzyme acid sphingomyelinase (ASM) is required for the conversion of the lipid cell membrane component sphingomyelin into ceramide. In cancer cells, ASM-mediated ceramide production is important for apoptosis, cell proliferation, and immune modulation, highlighting ASM as a potential multimodal therapeutic target. In this study, we demonstrate elevated ASM activity in the lung tumor environment and blood serum of patients with non-small cell lung cancer (NSCLC). RNAi-mediated attenuation of SMPD1 in human NSCLC cells rendered them resistant to serum starvation-induced apoptosis. In a murine model of lung adenocarcinoma, ASM deficiency reduced tumor development in a manner associated with significant enhancement of Th1-mediated and cytotoxic T-cell-mediated antitumor immunity. Our findings indicate that targeting ASM in NSCLC can act by tumor cell-intrinsic and -extrinsic mechanisms to suppress tumor cell growth, most notably by enabling an effective antitumor immune response by the host. Cancer Res; 77(21); 5963-76. ©2017 AACR.
EVALuna2:4034

Enhanced expression of BMP6 inhibits hepatic fibrosis in non-alcoholic fatty liver disease - Arndt, Stephanie; Wacker, Eva; Dorn, Christoph; Koch, Andreas; Saugspier, Michael; Thasler, Wolfgang E.; Hartmann, Arndt; Bosserhoff, Anja Katrin; Hellerbrand, Claus (Gut, 2015)
Bone morphogenetic protein 6 (BMP6) has been identified as crucial regulator of iron homeostasis. However, its further role in liver pathology including non-alcoholic fatty liver disease (NAFLD) and its advanced form non-alcoholic steatohepatitis (NASH) is elusive. The aim of this study was to investigate the expression and function of BMP6 in chronic liver disease.BMP6 was analysed in hepatic samples from murine models of chronic liver injury and patients with chronic liver diseases. Furthermore, a tissue microarray comprising 110 human liver tissues with different degree of steatosis and inflammation was assessed. BMP6-deficient (BMP6(-/-)) and wild-type mice were compared in two dietary NASH-models, that is, methionine choline-deficient (MCD) and high-fat (HF) diets.BMP6 was solely upregulated in NAFLD but not in other murine liver injury models or diseased human livers. In NAFLD, BMP6 expression correlated with hepatic steatosis but not with inflammation or hepatocellular damage. Also, in vitro cellular lipid accumulation in primary human hepatocytes induced increased BMP6 expression. MCD and HF diets caused more hepatic inflammation and fibrosis in BMP6(-/-) compared with wild-type mice. However, only in the MCD and not in the HF diet model BMP6(-/-) mice developed marked hepatic iron overload, suggesting that further mechanisms are responsible for protective BMP6 effect. In vitro analysis revealed that recombinant BMP6 inhibited the activation of hepatic stellate cells (HSCs) and reduced proinflammatory and profibrogenic gene expression in already activated HSCs.Steatosis-induced upregulation of BMP6 in NAFLD is hepatoprotective. Induction of BMP6-signalling may be a promising antifibrogenic strategy.
EVALuna2:4714

Enhancer hijacking activates oncogenic transcription factor NR4A3 in acinic cell carcinomas of the salivary glands - Haller, Florian; Bieg, Matthias; Will, Rainer; Koerner, Cindy; Weichenhan, Dieter; Bott, Alexander; Ishaque, Naveed; Lutsik, Pavlo; Moskalev, Evgeny; Müller, Susanna; Baehr, Marion; Woerner, Angelika; et al. (Nature Communications, 2019)
The molecular pathogenesis of salivary gland acinic cell carcinoma (AciCC) is poorly understood. The secretory Ca-binding phosphoprotein (SCPP) gene cluster at 4q13 encodes structurally related phosphoproteins of which some are specifically expressed at high levels in the salivary glands and constitute major components of saliva. Here we report on recurrent rearrangements [t(4;9)(q13;q31)] in AciCC that translocate active enhancer regions from the SCPP gene cluster to the region upstream of Nuclear Receptor Subfamily 4 Group A Member 3 (NR4A3) at 9q31. We show that NR4A3 is specifically upregulated in AciCCs, and that active chromatin regions and gene expression signatures in AciCCs are highly correlated with the NR4A3 transcription factor binding motif. Overexpression of NR4A3 in mouse salivary gland cells increases expression of known NR4A3 target genes and has a stimulatory functional effect on cell proliferation. We conclude that NR4A3 is upregulated through enhancer hijacking and has important oncogenic functions in AciCC.
EVALuna2:35381

Eosinophiles solide und zystisches Nierenzellkarzinom (ESC-NZK) - Hartmann, Arndt; Agaimy, Abbas (Pathologe, 2021)
Despite its descriptive name, eosinophilic, solid, and cystic renal cell carcinoma (ESC-RCC) represents a distinctive epithelial renal tumor entity defined by characteristic clinicopathological and molecular features. ESC-RCC occurs predominantly in women and is characterized in the majority of cases by sporadic (somatic) TSC mutations. A small subset of cases, however, affects patients with TSC germline mutations (tuberous sclerosis syndrome). TSC mutations have therefore been shown to be pathogenetic in this type of tumor. Most tumors present as small (pT1) well circumscribed but not encapsulated lesions with variable macrocystic spaces on their cut surface. Immunohistochemically, their CD117−/CK7−/CK20+ profile is characteristic. Although the tumor cell nuclei of the ESC-RCC occasionally correspond to ISUP/WHO grade 2–3, these tumors are essentially indolent with aggressive cases being only rarely observed. Single case reports have documented effective treatment of aggressive cases with mTOR inhibitors. ESC-RCC needs to be distinguished from a variety of eosinophilic RCC types with secondary cystic changes including cystic SDH-deficient RCC, the recently proposed eosinophilic vacuolated tumor (EVT; also mTOR-related), oncocytoma, and low-grade oncocytic tumor (LOT). The generally indolent behavior and frequent TSC/mTOR alterations in ESC-RCC, EVT, and some LOTs raise the question of whether these lesions represent independent tumor entities or are merely morphological variants on the spectrum of eosinophilic low-grade TSC/mTOR-related neoplasms.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Eosinophilic renal tumors; Human mTOR protein; Kidney neoplasms; TOR serine-threonine kinases; Tuberous sclerosis

Eosinophilic cystitis mimicking bladder cancer—considerations on the management based upon a case report and a review of the literature - Schmitz-Draeger, Bernd J.; Skutetzki, Andreas; Rieker, Ralf J.; Schwab, Siegfried A.; Stöhr, Robert; Bismarck, Ekkehardt; Savov, Orlin; Ebert, Thomas; Benderska-Soeder, Natalya; Hartmann, Arndt (Virchows Archiv, 2021)
The hypereosinophilic syndrome (HES) is a rare disorder characterized by hypereosinophilia and infiltration of various organs with eosinophils. Eosinophilic cystitis (EC), mimicking bladder cancer clinically but also in ultrasound and in radiographic imaging, is one potential manifestation of the HES occurring in adults as well as in children. This case report describes the course of disease in a 57-year-old male presenting with severe gait disorders and symptoms of a low compliance bladder caused by a large retropubic tumor. After extensive urine and serologic examination and histologic confirmation of EC the patient was subjected to medical treatment with cetirizine and prednisolone for 5 weeks. While gait disorders rapidly resolved, micturition normalized only 10 months after initiation of therapy. Based upon this course the authors recommend patience and reluctance concerning radical surgical intervention in EC.• Genetic alterations (e.g., BRAF mutations) may predispose for the disease
CRIS-Team Scopus Importer:2021-03-05
Keywords: Bladder tumor; Eosinophilic cystitis; Hypereosinophilic syndrome; Inflammatory pseudotumor

Eosinophilic vacuolated tumor (EVT) of kidney demonstrates sporadic TSC/MTOR mutations: next-generation sequencing multi-institutional study of 19 cases - Mihaela, Farcas; Zoran, Gatalica; Kiril, Trpkov; Jeffrey, Swensen; Ming, Zhou; Reza, Alaghehbandan; Williamson, Sean R.; Cristina, Magi-Galluzzi; Gill, Anthony J.; Maria, Tretiakova; Lopez, Jose; Delia, Perez Montiel; et al. (Modern Pathology, 2021)
A distinct renal tumor has recently been described as "high-grade oncocytic renal tumor" and "sporadic renal cell carcinoma with eosinophilic and vacuolated cytoplasm". The Genitourinary Pathology Society (GUPS) consensus proposed a unifying name "eosinophilic vacuolated tumor" (EVT) for this emerging entity. In this multi-institutional study, we evaluated 19 EVTs, particularly their molecular features and mutation profile, using next-generation sequencing. All cases were sporadic and none of the patients had a tuberous sclerosis complex. There were 8 men and 11 women, with a mean age of 47 years (median 50; range 15-72 years). Average tumor size was 4.3 cm (median 3.8 cm; range 1.5-11.5 cm). All patients with available follow-up data (18/19) were alive and without evidence of disease recurrence or progression during the follow-up, ranging from 12 to 198 months (mean 56.3, median 41.5 months). The tumors were well circumscribed, but lacked a well-formed capsule, had nested to solid growth, focal tubular architecture, and showed ubiquitous, large intracytoplasmic vacuoles, round to oval nuclei, and prominent nucleoli. Immunohistochemically, cathepsin K, CD117, CD10, and antimitochondrial antigen were expressed in all cases. Other positive stains included: PAX8, AE1/AE3 and CK18. CK7 was typically restricted only to rare scattered cells. Vimentin, HMB45, melan-A, and TFE3 were negative in all cases. All tumors showed retained SDHB. All cases (19/19) showed non-overlapping mutations of the mTOR pathway genes: TSC1 (4), TSC2 (7), and MTOR (8); one case with MTOR mutation showed a coexistent RICTOR missense mutation. Low mutational rates were found in all samples (ranged from 0 to 6 mutations/Mbp). Microsatellite instability and copy number variations were not found in any of the 17 analyzable cases. EVT represents an emerging renal entity that shows a characteristic and readily identifiable morphology, consistent immunohistochemical profile, indolent behavior, and mutations in either TSC1, TSC2, or MTOR genes.
CRIS-Team WoS Importer:2021-09-24

Epigenetic inactivation of ITIH5 promotes bladder cancer progression and predicts early relapse of pT1 high-grade urothelial tumours - Rose, Michael; Gaisa, Nadine T.; Antony, Pia; Fiedler, David; Heidenreich, Axel; Otto, Wolfgang; Denzinger, Stefan; Bertz, Simone; Hartmann, Arndt; Karl, Alexander; Knüchel, Ruth; Dahl, Edgar (Carcinogenesis, 2014)
Inter-?-trypsin inhibitor heavy chain 5 (ITIH5) has been associated with tumour suppression in various cancers. However, its putative role in bladder cancer is completely unknown. Therefore, we initiated a study analysing ITIH5 expression as well as its prognostic and functional impact on human urothelial cancers (UCs). Expression analysis showed a clear down-regulation of ITIH5 mRNA in 61% (n = 45) of UCs, especially in muscle-invasive tumours (P < 0.001). ITIH5 loss in UCs was further evident on protein level (65.5%, n = 55) as detected by immunohistochemistry. DNA methylation analysis demonstrated tumour-specific ITIH5 promoter methylation in 50% of papillary none-invasive pTa (n = 30) and 68% of invasive (n = 28) UCs. Aberrant ITIH5 promoter methylation in bladder tumours was tightly linked (P < 0.001) with loss of ITIH5 mRNA expression, which was furthermore functionally confirmed by demethylation analysis in cell lines. Pyrosequencing analysis revealed that ITIH5 promoter hypermethylation was closely associated with progressive bladder cancers. Subsequently, a large cohort (n = 120) of clinically challenging pT1 high-grade UC was analysed for ITIH5 expression. Of clinical significance, we found an association between loss of ITIH5 expression and unfavourable prognosis of UC patients without distant metastasis at first diagnosis (recurrence-free survival; hazard ratio: 4.35, P = 0.048). Functionally, ITIH5 re-expression in human RT112 bladder cancer cells led to both suppression of cell migration and inhibition of colony spreading. Hence, we provide evidence that down-regulation of ITIH5 by aberrant DNA hypermethylation may provoke invasive phenotypes in human bladder cancer. Moreover, ITIH5 protein might become a prognostic biomarker for relapse risk stratification in high-grade UC patients.
EVALuna2:6568

Epigenetic regulation of the putative breast cancer metastasis suppressor gene SCN4B - Hilgers, L.; Hartmann, Arndt; Fasching, Peter; Villwock, S.; Moll, L.; Roger, S.; Knuechel-Clarke, R.; Steib, F.; Dahl, E. D. (ANNALS OF ONCOLOGY, 2021)
CRIS-Team WoS Importer:2021-05-28

ERBB2 Expression as Potential Risk-Stratification for Early Cystectomy in Patients with pT1 Bladder Cancer and Concomitant Carcinoma in situ - Breyer, Johannes; Otto, Wolfgang; Wirtz, Ralph M.; Wullich, Bernd; Keck, Bastian; Erben, Philipp; Kriegmair, Maximilian C.; Stoehr, Robert; Eckstein, Markus; Laible, Mark; Schlombs, Kornelia; Eidt, Sebastian; et al. (Urologia Internationalis, 2017)
Background/Aims/Objectives: It is difficult to identify patients with a non-muscle-invasive bladder cancer (NMIBC) at stage pT1 with concomitant carcinoma in situ (Cis) who will benefit from an early cystectomy.We retrospectively analyzed clinical data and formalin-fixed paraffin-embedded tissues of patients with NMIBC. Messenger ribonucleic acid (mRNA) expression of progesterone receptor (PGR), estrogen receptor (ESR1), ERBB2, and marker of proliferation Ki-67 (MKI67) was measured by single-step reverse transcription quantitative real-time polymerase chain reaction using RNA-specific TaqMan assays. Relative gene expression was determined by the normalization of 2 reference genes (CALM2, B2M) using the 40 ??CT method and relative gene expression was correlated to the histopathological stage and oncological outcome.Of 302 patients with pT1 NMIBC in the initial transurethral resection of the bladder, 65 had a concomitant Cis. Elevated ERBB2 expression (>40.1) significantly correlated with progress in patients with and without concomitant Cis (p = 0.020 and p = 0.049, respectively). For the subgroup of pT1 with concomitant Cis, elevated ERBB2 expression significantly discriminated between a high-risk group of 55% progression-free survival (PFS) and a low-risk group of 90% PFS after a 5-year follow-up (p = 0.020). Cox-regression analysis revealed ERBB2 expression as the only independent prognostic factor for PFS (p = 0.0037).High mRNA expression of ERBB2 can identify patients with pT1 NMIBC with concomitant Cis, who have a high risk of progression and might benefit from an early cystectomy.
EVALuna2:6879

Erratum to: DAPK plays an important role in panobinostat-induced autophagy and commits cells to apoptosis under autophagy deficient conditions - Gandesiri, Muktheshwar; Chakilam, Saritha; Ivanovska, Jelena; Benderska, Natalya; Ocker, Matthias; Di Fazio, Pietro; Feoktistova, Maria; Gali-Muhtasib, Hala; Rave-Fraenk, Margret; Prante, Olaf; Christiansen, Hans; Leverkus, Martin; et al. (Apoptosis, 2016)
EVALuna2:6627

Erratum to: Eosinophilic, solid, and cystic renal cell carcinoma (ESC-RCC) (Der Pathologe, (2021), 42, 6, (565-570), 10.1007/s00292-021-00998-7) Erratum zu: Eosinophiles solide und zystisches Nierenzellkarzinom (ESC-NZK) (Der Pathologe, (2021), 42, 6, (565-570), 10.1007/s00292-021-00998-7) - Hartmann, Arndt; Agaimy, Abbas (Pathologe, 2021)
CRIS-Team Scopus Importer:2021-11-05

Erratum zu: Testung auf Mismatch-Reparatur-Defizienz und Mikrosatelliteninstabilität: Eine fokussierte Aktualisierung (Die Pathologie, (2023), 44, 5, (301-310), 10.1007/s00292-023-01209-1) - Rüschoff, Josef; Schildhaus, Hans Ulrich; Rüschoff, Jan Hendrik; Jöhrens, Korinna; Bocker-Edmonston, Tina; Dietmaier, Wolfgang; Bläker, Hendrik; Baretton, Gustavo; Horst, David; Dietel, Manfred; Hartmann, Arndt; Klauschen, Frederick; et al. (Die Pathologie, 2023)
CRIS-Team Scopus Importer:2023-09-08

ESR1, ERBB2, and Ki67 mRNA expression predicts stage and grade of non-muscle-invasive bladder carcinoma (NMIBC) - Breyer, Johannes; Wirtz, Ralph M.; Laible, Mark; Schlombs, Kornelia; Erben, Philipp; Kriegmair, Maximilian Christian; Stoehr, Robert; Eidt, Sebastian; Denzinger, Stefan; Burger, Maximilian; Hartmann, Arndt; Otto, Wolfgang (Virchows Archiv, 2016)
Pathological staging and grading are crucial for risk assessment in non-muscle-invasive bladder cancer (NMIBC). Molecular grading might support pathological evaluation and minimize interobserver variability. In this study, the well-established breast cancer markers ESR1, PGR, ERBB2, and MKI67 were evaluated as potential molecular markers to support grading and staging in NMIBC. We retrospectively analyzed clinical data and formalin-fixed paraffin-embedded tissues (FFPE) of patients with NMIBC. Messenger RNA (mRNA) expression of the aforementioned markers was measured by single-step reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) using RNA-specific TaqMan assays. Relative gene expression was determined by normalization to two reference genes (CALM2 and B2M) using the 40(-??CT) method and correlated to histopathological stage and grade. Pathological assessment was performed by an experienced uropathologist. Statistical analysis was performed using the SAS software JMP 9.0.0 version and GraphPad Prism 5.04. Of 381 cases of NMIBC, samples of 100 pTa and 255 pT1 cases were included in the final study. Spearman rank correlation revealed significant correlations between grade and expression of MKI67 (r = 0.52, p < 0.0001), ESR1 (r = 0.25, p < 0.0001), and ERBB2 (r = 0.18, p = 0.0008). In Mann-Whitney tests, MKI67 was significantly different between all grades (p < 0.0001), while ESR1 (p = 0.0006) and ERBB2 (p = 0.027) were significantly different between G2 and G3. Higher expression of MKI67 (r = 0.49; p < 0.0001), ERBB2 (r = 0.22; p < 0.0001), and ESR1 (r = 0.18; p = 0.0009) mRNA was positively correlated with higher stage. MKI67 (p < 0.0001), ERBB2 (p = 0.0058), and PGR (p = 0.0007) were significantly different between pTa and pT1. In NMIBC expression of ESR1, ERBB2 and MKI67 are significantly different between stage and grade. This potentially provides objective parameters for pathological evaluation.
EVALuna2:6820

Europe-side external quality assessment (EQA) of RNA based testing of ER, PR, HER2 and Ki67 in invasive breast cancer - Erber, Ramona; Hartmann, Arndt; Fasching, Peter; Stöhr, Robert; Beckmann, Matthias; Zentgraf, M.; Rübner, Matthias; Hübner, Hanna; Fischer, J.; Guerini Rocco, E.; Viale, G.; Cayre, A.; et al. (ANNALS OF ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-06-26

Evaluation of different diagnostic methods for identification of FGFR alteration in advanced urothelial carcinomas: Proficiency results based on multiple RNA extraction kits and mutation detection methods - Weyerer, Veronika; Stöhr, Robert; Juette, H.; Wirtz, R.; Eckstein, Markus; Roghmann, F.; Breyer, J.; Porubsky, S.; Sikic, D.; Bolenz, C.; Kriegmair, M. C.; Hartmann, Arndt; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Evaluation of FGFR Alteration Status in Urothelial Tumors - Bahlinger, Veronika; Eckstein, Markus; Hartmann, Arndt; Stöhr, Robert (Urothelial Carcinoma - Methods and Protocols, 2023)
FGFR alterations in urothelial carcinoma are key driver alterations of tumorigenesis and are long recognized. In 2019 the Food and Drug Administration (FDA) approved the first pan-FGFR inhibitor, as the first specific targeted therapy in urothelial carcinoma. To receive the drug, alteration testing is required, and only alteration carriers can profit of this new agent. Due to this clinical need of detection and analysis of FGFR, here we describe two distinct and specific analytical methodologies: the SNaPshot analysis of nine FGFR3 point mutations and the QIAGEN therascreen® FGFR RGQ RT-PCR Kit, the FDA-approved companion diagnostic kit.
CRIS-Team Scopus Importer:2023-07-21
Keywords: FGFR testing; Inhibitor; QIAGEN therascreen; SNaPshot analysis; Targeted therapy; Urothelial carcinoma

Evaluation of Gas 6 as a Prognostic Marker in Papillary Renal Cell Carcinoma - Mikuteit, Marie; Zschäbitz, Stefanie; Stoehr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Ströbel, Philipp; Becker, Frank; Wülfing, Christian; Barth, Peter; Stöckle, Michael; et al. (Urologia Internationalis, 2023)
Introduction: Growth arrest-specific protein 6 (Gas 6) is a ligand that plays a role in proliferation and migration of cells. For several tumor entities, high levels of Gas 6 are associated with poorer survival. We examined the prognostic role of Gas 6 in renal cell carcinoma (RCC), especially in papillary RCC (pRCC), which is still unclear. Methods: The patients' sample collection is a joint collaboration of the PANZAR consortium. Patients' medical history and tumor specimens were collected from n = 240 and n = 128 patients with type 1 and 2 pRCC, respectively. Expression of Gas 6 was determined by immunohistochemistry. Results: In total, Gas 6 staining was evaluable in 180 of 240 type 1 and 110 of 128 type 2 pRCC cases. Kaplan-Meier analysis disclosed no significant difference in 5-year overall survival for all pRCC nor either subtype. Also, Gas+ and Gas- groups did not significantly differ in any tumor or patient characteristics. Conclusion: Gas 6 was not found to be an independent prognostic marker in pRCC. Future studies are warranted to determine if Gas 6 plays a role as prognostic marker or therapeutic target in pRCC.
CRIS-Team Scopus Importer:2023-08-11

Evaluation of Potential Targeted Therapy and Molecular Subtype in Large Nested Variant of Urothelial Carcinoma (LNUC) - Weyerer, Veronika; Eckstein, Markus; Comperat, Eva; Juette, Hendrik; Gaisa, Nadine; Allory, Yves; Stoehr, Robert; Wullich, Bernd; Roupret, Morgan; Hartmann, Arndt; Bertz, Simone (LABORATORY INVESTIGATION, 2020)
CRIS-Team WoS Importer:2020-03-24

Evaluation of Prognostic Parameters to Identify Aggressive Penile Carcinomas - Mink, Jan Niklas; Khalmurzaev, Oybek; Pryalukhin, Alexey; Geppert, Carol-Immanuel; Lohse, Stefan; Bende, Kristóf; Lobo, João; Henrique, Rui; Loertzer, Hagen; Steffens, Joachim; Jerónimo, Carmen; Wunderlich, Heiko; et al. (Cancers, 2023)
Background: Advanced penile carcinoma is characterized by poor prognosis. Most data on prognostic factors are based on small study cohorts, and even meta-analyses are limited in patient numbers. Therefore, there is still a lack of evidence for clinical decisions. In addition, the most recent TNM classification is questionable; in line with previous studies, we found that it has not improved prognosis estimation. Methods: We evaluated 297 patients from Germany, Russia, and Portugal. Tissue samples from 233 patients were re-analyzed by two experienced pathologists. HPV status, p16, and histopathological parameters were evaluated for all patients. Results: Advanced lymph node metastases (N2, N3) were highly significantly associated with reductions in metastasis-free (MFS), cancer-specific (CS), and overall survival (OS) rates (p = <0.001), while lymphovascular invasion was a significant parameter for reduced CS and OS (p = 0.005; p = 0.007). Concerning the primary tumor stage, a significant difference in MFS was found only between pT1b and pT1a (p = 0.017), whereas CS and OS did not significantly differ between T categories. In patients without lymph node metastasis at the time of primary diagnosis, lymphovascular invasion was a significant prognostic parameter for lower MFS (p = 0.032). Histological subtypes differed in prognosis, with the worst outcome in basaloid carcinomas, but without statistical significance. HPV status was not associated with prognosis, either in the total cohort or in the usual type alone. Conclusion: Lymphatic involvement has the highest impact on prognosis in penile cancer, whereas HPV status alone is not suitable as a prognostic parameter. The pT1b stage, which includes grading, as well as lymphovascular and perineural invasion in the T stage, seems questionable; a revision of the TNM classification is therefore required.
CRIS-Team Scopus Importer:2023-10-20
Keywords: histological subtype; HPV; p16; penile cancer; prognosis

Evidence for a time-dependent association between FOLR1 expression and survival from ovarian carcinoma: implications for clinical testing. An Ovarian Tumour Tissue Analysis consortium study - Koebel, M.; Madore, J.; Ramus, S. J.; Clarke, B. A.; Pharoah, P. D. P.; Deen, S.; Bowtell, D. D.; Odunsi, K.; Menon, U.; Morrison, C.; Lele, S.; Bshara, W.; et al. (British Journal of Cancer, 2014)
Folate receptor 1 (FOLR1) is expressed in the majority of ovarian carcinomas (OvCa), making it an attractive target for therapy. However, clinical trials testing anti-FOLR1 therapies in OvCa show mixed results and require better understanding of the prognostic relevance of FOLR1 expression. We conducted a large study evaluating FOLR1 expression with survival in different histological types of OvCa.Tissue microarrays composed of tumour samples from 2801 patients in the Ovarian Tumour Tissue Analysis (OTTA) consortium were assessed for FOLR1 expression by centralised immunohistochemistry. We estimated associations for overall (OS) and progression-free (PFS) survival using adjusted Cox regression models. High-grade serous ovarian carcinomas (HGSC) from The Cancer Genome Atlas (TCGA) were evaluated independently for association between FOLR1 mRNA upregulation and survival.FOLR1 expression ranged from 76% in HGSC to 11% in mucinous carcinomas in OTTA. For HGSC, the association between FOLR1 expression and OS changed significantly during the years following diagnosis in OTTA (Pinteraction=0.01, N=1422) and TCGA (Pinteraction=0.01, N=485). In OTTA, particularly for FIGO stage I/II tumours, patients with FOLR1-positive HGSC showed increased OS during the first 2 years only (hazard ratio=0.44, 95% confidence interval=0.20-0.96) and patients with FOLR1-positive clear cell carcinomas (CCC) showed decreased PFS independent of follow-up time (HR=1.89, 95% CI=1.10-3.25, N=259). In TCGA, FOLR1 mRNA upregulation in HGSC was also associated with increased OS during the first 2 years following diagnosis irrespective of tumour stage (HR: 0.48, 95% CI: 0.25-0.94).FOLR1-positive HGSC tumours were associated with an increased OS in the first 2 years following diagnosis. Patients with FOLR1-negative, poor prognosis HGSC would be unlikely to benefit from anti-FOLR1 therapies. In contrast, a decreased PFS interval was observed for FOLR1-positive CCC. The clinical efficacy of FOLR1-targeted interventions should therefore be evaluated according to histology, stage and time following diagnosis.
EVALuna2:6660

Exceptional response to neoadjuvant targeted therapy with the selective RET inhibitor selpercatinib in RET-fusion-associated sarcoma - Schrenk, Karin G.; Weschenfelder, Wolfram; Spiegel, Christian; Agaimy, Abbas; Stöhr, Robert; Hartmann, Arndt; Gassler, Nikolaus; Drescher, Robert; Freesmeyer, Martin; Malouhi, Amer; Buerckenmeyer, Florian; Aschenbach, Rene; et al. (Journal of Cancer Research and Clinical Oncology, 2022)
With the increasing use of next-generation sequencing, highly effective targeted therapies have been emerging as treatment options for several cancer types. Recurrent gene-fusions have been recognized in sarcomas; however, options for targeted therapy remain scarce. Here, we describe a case of a sarcoma, associated with a RET::TRIM33-fusion gene with an exceptional response to a neoadjuvant therapy with the selective RET inhibitor selpercatinib. Resected tumor revealed subtotal histopathologic response. This is the first report of successful targeted therapy with selpercatinib in RET-fusion-associated sarcomas. As new targeted therapies are under development, similar treatment options may become available for sarcoma patients.
CRIS-Team WoS Importer:2023-01-06

Expanding the clinicopathological spectrum of succinate dehydrogenase-deficient renal cell carcinoma with a focus on variant morphologies: a study of 62 new tumors in 59 patients - Fuchs, Talia L.; Maclean, Fiona; Turchini, John; Vargas, A. Cristina; Bhattarai, Selina; Agaimy, Abbas; Hartmann, Arndt; Kao, Chia-Sui; Ellis, Carla; Bonert, Michael; Leroy, Xavier; Kunju, Lakshmi P.; et al. (Modern Pathology, 2021)
Most succinate dehydrogenase (SDH)-deficient renal cell carcinomas (RCCs) demonstrate stereotypical morphology characterized by bland eosinophilic cells with frequent intracytoplasmic inclusions. However, variant morphologic features have been increasingly recognized. We therefore sought to investigate the incidence and characteristics of SDH-deficient RCC with variant morphologies. We studied a multi-institutional cohort of 62 new SDH-deficient RCCs from 59 patients. The median age at presentation was 39 years (range 19-80), with a slight male predominance (M:F = 1.6:1). A relevant family history was reported in 9 patients (15%). Multifocal or bilateral tumors were identified radiologically in 5 patients (8%). Typical morphology was present at least focally in 59 tumors (95%). Variant morphologies were seen in 13 (21%) and included high-grade nuclear features and various combinations of papillary, solid, and tubular architecture. Necrosis was present in 13 tumors, 7 of which showed variant morphology. All 62 tumors demonstrated loss of SDHB expression by immunohistochemistry. None showed loss of SDHA expression. Germline SDH mutations were reported in all 18 patients for whom the results of testing were known. Among patients for whom follow-up data was available, metastatic disease was reported in 9 cases, 8 of whom had necrosis and/or variant morphology in their primary tumor. Three patients died of disease. In conclusion, variant morphologies and high-grade nuclear features occur in a subset of SDH-deficient RCCs and are associated with more aggressive behavior. We therefore recommend grading all SDH-deficient RCCs and emphasize the need for a low threshold for performing SDHB immunohistochemistry in any difficult to classify renal tumor, particularly if occurring at a younger age.
CRIS-Team WoS Importer:2021-12-31

Expansion of IL-23 receptor bearing TNFR2+ T cells is associated with molecular resistance to anti-TNF therapy in Crohn's disease - Schmitt, Heike; Billmeier, Ulrike; Dieterich, Walburga; Rath, Timo; Sonnewald, Sophia; Reid, Stephen; Hirschmann, Simon; Hildner, Kai; Waldner, Maximilian; Mudter, Jonas; Hartmann, Arndt; Grützmann, Robert; et al. (Gut, 2018)
OBJECTIVE: Anti-tumour necrosis factor (TNF) antibodies are successfully used for treatment of Crohn's disease. Nevertheless, approximately 40% of patients display failure to anti-TNF therapy. Here, we characterised molecular mechanisms that are associated with endoscopic resistance to anti-TNF therapy. DESIGN: Mucosal and blood cells were isolated from patients with Crohn's disease prior and during anti-TNF therapy. Cytokine profiles, cell surface markers, signalling proteins and cell apoptosis were assessed by microarray, immunohistochemistry, qPCR, ELISA, whole organ cultures and FACS. RESULTS: Responders to anti-TNF therapy displayed a significantly higher expression of TNF receptor 2 (TNFR2) but not IL23R on T cells than non-responders prior to anti-TNF therapy. During anti-TNF therapy, there was a significant upregulation of mucosal IL-23p19, IL23R and IL-17A in anti-TNF non-responders but not in responders. Apoptosis-resistant TNFR2+IL23R+ T cells were significantly expanded in anti-TNF non-responders compared with responders, expressed the gut tropic integrins α4β7, and exhibited increased expression of IFN-γ, T-bet, IL-17A and RORγt compared with TNFR2+IL23R- cells, indicating a mixed Th1/Th17-like phenotype. Intestinal TNFR2+IL23R+ T cells were activated by IL-23 derived from CD14+ macrophages, which were significantly more present in non-responders prior to anti-TNF treatment. Administration of IL-23 to anti-TNF-treated mucosal organ cultures led to the expansion of CD4+IL23R+TNFR2+ lymphocytes. Functional studies demonstrated that anti-TNF-induced apoptosis in mucosal T cells is abrogated by IL-23. CONCLUSIONS: Expansion of apoptosis-resistant intestinal TNFR2+IL23R+ T cells is associated with resistance to anti-TNF therapy in Crohn's disease. These findings identify IL-23 as a suitable molecular target in patients with Crohn's disease refractory to anti-TNF therapy.
EVALuna2:34305

Explainable convolutional neural networks for assessing head and neck cancer histopathology - Dörrich, Marion; Hecht, Markus; Fietkau, Rainer; Hartmann, Arndt; Iro, Heinrich; Gostian, Antoniu-Oreste; Eckstein, Markus; Kist, Andreas (Diagnostic Pathology, 2023)
Purpose: Although neural networks have shown remarkable performance in medical image analysis, their translation into clinical practice remains difficult due to their lack of interpretability. An emerging field that addresses this problem is Explainable AI. Methods: Here, we aimed to investigate the ability of Convolutional Neural Networks (CNNs) to classify head and neck cancer histopathology. To this end, we manually annotated 101 histopathological slides of locally advanced head and neck squamous cell carcinoma. We trained a CNN to classify tumor and non-tumor tissue, and another CNN to semantically segment four classes - tumor, non-tumor, non-specified tissue, and background. We applied Explainable AI techniques, namely Grad-CAM and HR-CAM, to both networks and explored important features that contributed to their decisions. Results: The classification network achieved an accuracy of 89.9% on previously unseen data. Our segmentation network achieved a class-averaged Intersection over Union score of 0.690, and 0.782 for tumor tissue in particular. Explainable AI methods demonstrated that both networks rely on features agreeing with the pathologist’s expert opinion. Conclusion: Our work suggests that CNNs can predict head and neck cancer with high accuracy. Especially if accompanied by visual explanations, CNNs seem promising for assisting pathologists in the assessment of cancer sections.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Classification; Explainable AI; Head and neck cancer; Histopathology; Semantic segmentation

Explaining and Evaluating Deep Tissue Classification by Visualizing Activations of Most Relevant Intermediate Layers - Mohammed, Aliya; Geppert, Carol-Immanuel; Hartmann, Arndt; Kuritcyn, Petr; Bruns, Volker; Schmid, Ute; Wittenberg, Thomas; Benz, Michaela; Finzel, Bettina (Current Directions in Biomedical Engineering, 2022)
Deep Learning-based tissue classification may support pathologists in analyzing digitized whole slide images. However, in such critical tasks, only approaches that can be validated by medical experts in advance to deployment, are suitable. We present an approach that contributes to making automated tissue classification more transparent. We step beyond broadly used visualizations for last layers of a convolutional neural network by identifying most relevant intermediate layers applying Grad-CAM. A visual evaluation by a pathologist shows that these layers assign relevance, where important morphological structures are present in case of correct class decisions. We introduce a tool that can be easily used by medical experts for such validation purposes for any convolutional neural network and any layer. Visual explanations for intermediate layers provide insights into a neural network's decision for histopathological tissue classification. In future research also the context of the input data must be considered.
Created from Fastlane, Scopus look-up
Keywords: Deep Learning; Digital Pathology; Evaluation; Grad-CAM; Intelligent user interface; XAI

Exploring the MIR143-UPAR Axis for the Inhibition of Human Prostate Cancer Cells In Vitro and In Vivo - Wach, Sven; Brandl, Madeleine; Borchardt, Hannes; Weigelt, Katrin; Lukat, Sabine; Nolte, Elke; Al-Janabi, Omar; Hart, Martin; Grässer, Friedrich; Giedl, Josef; Jung, Rudolf; Stöhr, Robert; et al. (Molecular Therapy - Nucleic Acids, 2019)
MIR143 is pathologically downregulated and may function as a tumor suppressor in prostate cancer. Likewise, the urokinase plasminogen activator receptor (UPAR) is overexpressed in prostate carcinoma, representing a negative prognostic marker and putative therapeutic target gene. In this paper, we establish UPAR as a new direct target of MIR143. Luciferase reporter gene constructs identify one of the two in silico-predicted binding sites as functionally relevant for direct MIR143 binding to the 3′ UTR, and, concomitantly, transfection of MIR143 reduces UPAR protein levels in prostate carcinoma cells in vitro. Inhibitory effects on cell proliferation and colony formation, spheroid growth and integrity, and cell viability are extensively analyzed, and they are compared to direct small interfering RNA (siRNA)-mediated uPAR knockdown or combined microRNA (miRNA)-siRNA treatment. Switching to a therapeutically more relevant in vivo model, we demonstrate tumor-inhibitory effects of MIR143 replacement therapy by systemic treatment of mice bearing subcutaneous PC-3 tumor xenografts with MIR143 formulated in polymeric nanoparticles. This efficient, nanoparticle-mediated delivery of intact MIR143 mediates the marked downregulation of uPAR protein, but not mRNA levels, thus indicating translational inhibition rather than mRNA degradation. In summary, we identify UPAR as a direct target gene of MIR143, and we establish the therapeutic anti-tumor potential of nanoparticle-based MIR143 replacement in prostate cancer.
CRIS-Team Scopus Importer:2019-05-07
Keywords: MIR143; miRNA replacement; PEI nanoparticles; prostate cancer; urokinase plasminogen activator receptor; xenograft

Expression and Localization of Lung Surfactant Proteins in Human Testis - Beileke, Stephanie; Claassen, Horst; Wagner, Walter; Matthies, Cord; Ruf, Christian; Hartmann, Arndt; Garreis, Fabian; Paulsen, Friedrich; Schicht, Martin; Bräuer, Lars (PLoS ONE, 2015)
Surfactant proteins (SPs) have been described in various tissues and fluids including tissues of the nasolacrimal apparatus, airways and digestive tract. Human testis have a glandular function as a part of the reproductive and the endocrine system, but no data are available on SPs in human testis and prostate under healthy and pathologic conditions.The aim of the study was the detection and characterization of the surfactant proteins A, B, C and D (SP-A, SP-B, SP-C, SP-D) in human testis. Additionally tissue samples affected by testicular cancer were investigated.Surfactant proteins A, B, C and D were detected using RT-PCR in healthy testis. By means of Western blot analysis, these SPs were detected at the protein level in normal testis, seminoma and seminal fluid, but not in spermatozoa. Expression of SPs was weaker in seminoma compared to normal testicular tissue. SPs were localized in combination with vimentin immunohistochemically in cells of Sertoli and Leydig.Surfactant proteins seem to be inherent part of the human testis. By means of physicochemical properties the proteins appear to play a role during immunological and rheological process of the testicular tissue. The presence of SP-B and SP-C in cells of Sertoli correlates with their function of fluid secretion and may support transportation of spermatozoa. In seminoma the expression of all SP's was generally weaker compared to normal germ cells. This could lead to a reduction of immunomodulatory and rheology processes in the germ cell tumor.
EVALuna2:4444

Expression and role of the immune checkpoint regulator PD-L1 in the tumor-stroma interplay of pancreatic ductal adenocarcinoma - Daunke, Tina; Beckinger, Silje; Rahn, Sascha; Krüger, Sandra; Heckl, Steffen; Schäfer, Heiner; Wesch, Daniela; Pilarsky, Christian; Eckstein, Markus; Hartmann, Arndt; Röcken, Christoph; Wandmacher, Anna Maxi; et al. (Frontiers in Immunology, 2023)
Introduction: Immune checkpoint inhibitors (ICI), e.g., targeting programmed cell death protein 1-ligand 1 (PD-L1) or its receptor PD-1, have markedly improved the therapy of many cancers but so far failed in pancreatic ductal adenocarcinoma (PDAC). Macrophages represent one of the most abundant immune cell populations within the tumor microenvironment (TME) of PDAC being able to either support or restrain tumor progression depending on their phenotype. To better understand treatment failure of PD-L1/PD-1 inhibitors in PDAC, this study examined PD-L1 expression in the context of a dynamic TME in PDAC with a particular focus on the impact of macrophages. Methods: Formalin-fixed and paraffin embedded tissue samples of primary PDAC tissues and corresponding liver metastases were used for immunohistochemical analyses. Serial sections were stained with antibodies detecting Pan-Cytokeratin, CD68, CD163, CD8, and PD-L1.To investigate whether the PD-1/PD-L1 axis and macrophages contribute to immune escape of PDAC cells, a stroma enriched 3D spheroid coculture model was established in vitro, using different PDAC cell lines and macrophages subtypes as well as CD8+ T cells. Functional and flow cytometry analyses were conducted to characterize cell populations. Results: Immunohistochemical analyses revealed that PD-L1 is mainly expressed by stroma cells, including macrophages and not PDAC cells in primary PDAC tissues and corresponding liver metastases. Notably, high local abundance of macrophages and strong PD-L1 staining were commonly found at invasion fronts of tumoral lesions between CD8+ T cells and tumor cells. In order to investigate whether PD-L1 expressing macrophages impact the response of PDAC cells to treatment with PD-L1/PD-1 inhibitors, we developed a spheroid model comprising two different PDAC cell lines and different ratios of in vitro differentiated primary M1- or M2-like polarized macrophages. In line with our in situ findings, high PD-L1 expression was observed in macrophages rather than PDAC cells, which was further increased by the presence of PDAC cells. The effector phenotype of co-cultured CD8+ T cells exemplified by expression of activation markers and release of effector molecules was rather enhanced by PDAC macrophage spheroids, particularly with M1-like macrophages compared to mono-culture spheroids. However, this was not associated with enhanced PDAC cell death. ICI treatment with either Durvalumab or Pembrolizumab alone or in combination with Gemcitabine hardly affected the effector phenotype of CD8+ T cells along with PDAC cell death. Thus, despite strong PD-L1 expression in macrophages, ICI treatment did not result in an enhanced activation and cytotoxic phenotype of CD8+ T cells. Conclusion: Overall, our study revealed novel insights into the interplay of PDAC cells and macrophages in the presence of ICI.
CRIS-Team Scopus Importer:2023-08-25
Keywords: 3D co-culture; immune checkpoint inhibitor; immune evasion; macrophages; pancreatic cancer; tumor microenvironment

Expression of AR-V7 (Androgen receptor variant 7) protein in granular cytoplasmic structures is an independent prognostic factor in prostate cancer patients - König, Paul; Eckstein, Markus; Jung, Rudolf; Abdulrahman, Amer; Guzman, Juan; Weigelt, Katrin; Serrero, Ginette; Hayashi, Jun; Geppert, Carol-Immanuel; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; et al. (Cancers, 2020)
Prostate cancer (PCa) is the second most common cancer, causing morbidity and mortality among men world-wide. The expression of the androgen receptor (AR) and its splice variants is a crucial factor of prostate cancer biology that has not been comprehensively studied in PCa tumors. The aim of this study was to characterize the protein expression of the AR and its splice variant, AR-V7, and their subcellular distributions in PCa by immunohistochemistry and to correlate the results to the clinicopathological data and prognosis. Immunohistochemical staining for AR and AR-V7 was performed on a tissue microarray (TMA) with specimens from 410 PCa patients using an immunoreactive score (IRS) or only the percentage of AR-V7 staining in cytoplasmic granules. Nuclear or cytoplasmic AR staining was not associated with prognosis. AR-V7 staining was only occasionally observed in the nucleus. However, AR-V7 staining in the cytoplasm or in cytoplasmic granules was associated with relapse-free survival (RFS). AR-V7 staining of the cytoplasm was associated with a shorter RFS, whereas AR-V7 staining of cytoplasmic granules was associated with a longer RFS. In a multivariate Cox’s regression analysis, only negative (<5%) AR-V7 staining of cytoplasmic granules remained an independent prognostic factor for RFS (HR = 5.3; p = 0.006). In a further subgroup analysis by multivariate Cox’s regression analysis, AR-V7 was an independent prognostic factor in the following groups: age ≤ 65 (HR = 9.7; p = 0.029), negative CK20 staining (HR = 7.0; p = 0.008), and positive perineural invasion (HR = 3.7; p = 0.034). Altogether, AR-V7 protein in granular cytoplasmic structures is an independent prognostic factor for RFS in PCa patients.
CRIS-Team Scopus Importer:2020-09-25
Keywords: AR; AR-V7; Gleason score; Perineural invasion; Prognosis; Prostate cancer; Relapse-free survival; RFS

Expression of disialoganglioside GD2 in breast cancer subtypes - Gaß, Paul; Kailayangiri, Sareetha; Hübner, Hanna; Rübner, Matthias; Hartmann, Arndt; Häberle, Lothar; Völkl, Simon; Mackensen, Andreas; Landgraf, Laura; Schulz-Wendtland, Rüdiger; Farwick, Nicole; Roessig, Claudia; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-12-16

Expression of GP88 (Progranulin) Protein Is an Independent Prognostic Factor in Prostate Cancer Patients - Abdulrahman, Amer; Eckstein, Markus; Jung, Rudolf; Guzman, Juan; Weigelt, Katrin; Serrero, Ginette; Yue, Binbin; Geppert, Carol-Immanuel; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; Wach, Sven; et al. (Cancers, 2019)
Prostate cancer, the second most common cancer, is still a major cause of morbidity and mortality among men worldwide. The expression of the survival and proliferation factor progranulin (GP88) has not yet been comprehensively studied in PCa tumors. The aim of this study was to characterize GP88 protein expression in PCa by immunohistochemistry and to correlate the findings to the clinico-pathological data and prognosis. Immunohistochemical staining for GP88 was performed by TMA with samples from 442 PCa patients using an immunoreactive score (IRS). Altogether, 233 cases (52.7%) with negative GP88 staining (IRS < 2) and 209 cases (47.3%) with positive GP88 staining (IRS >= 2) were analyzed. A significant positive correlation was found for the GP88 IRS with the PSA value at prostatectomy and the cytoplasmic cytokeratin 20 IRS, whereas it was negatively associated with follow-up times. The association of GP88 staining with prognosis was further studied by survival analyses (Kaplan-Meier, univariate and multivariate Cox's regression analysis). Increased GP88 protein expression appeared as an independent prognostic factor for overall, disease-specific and relapse-free survival in all PCa patients. Interestingly, in the subgroup of younger PCa patients (<= 65 years), GP88 positivity was associated with a 3.8-fold (p = 0.004), a 6.0-fold (p = 0.008) and a 3.7-fold (p = 0.003) increased risk for death, disease-specific death and occurrence of a relapse, respectively. In the PCa subgroup with negative CK20 staining, GP88 positivity was associated with a 1.8-fold (p = 0.018) and a 2.8-fold increased risk for death and disease-specific death (p = 0.028). Altogether, GP88 protein positivity appears to be an independent prognostic factor for PCa patients.
CRIS-Team WoS Importer:2020-01-28

Expression of Nectin-4 in Chromophobe Renal Cell Carcinoma in a Multicenter Cohort: Early Prognostic and Therapeutic Considerations - Mikuteit, Marie; Zschäbitz, Stefanie; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; Steffens, Sandra; Erlmeier, Franziska (Oncology, 2024)
Introduction: Nectin-4 is a member of the nectin family and a calcium-independent immunoglobulin-like transmembrane protein that contributes to tumor growth and angiogenesis in malignant tumors. A nectin-4-directed antibody drug conjugate, enfortumab vedotin-ejf, has recently been approved for treatment in urothelial cancer and is currently under investigation in other tumor entities such as breast, lung, and prostate cancer. In non-clear cell renal cell carcinoma (RCC), vascular endothelial growth factor (VEGF)- directed tyrosine kinase inhibitors and checkpoint inhibitors are currently treatments of choice. However, due to the rarity of disease treatment recommendations for chromophobe RCC (chRCC) are limited and new therapeutic agents urgently needed. In this study, we investigated the expression and prognostic impact of nectin-4 in a large cohort of chRCC. Methods: Patients who underwent renal surgery due to chRCC were recruited. Clinical data were retrospectively evaluated. Tumor specimen was analyzed for nectin-4 expression by immunohistochemistry. Results: Eighty-one chRCC patients were eligible for analysis. In 15 (18.5%) samples, tumors were positive for nectin-4. No significant associations were found for nectin-4 expression and clinical attributes in patients with chRCC. Kaplan-Meier analysis disclosed a 5-year overall survival for nectin-4- negative and nectin-4-positive tumors of 91.8% versus 100.0% (p = 0.316, log rank). Conclusions: In chRCC, a small subset of tumors expresses nectin-4 potentially amenable to nectin-4-directed treatment. Expression of nectin-4 is not associated with parameters of aggressiveness or survival. Due to the rare incidence of chRCC, further studies with larger cohorts are warranted.
CRIS-Team Scopus Importer:2024-06-07
Keywords: Chromophobe histology; Nectin-4; Renal cell carcinoma; Survival

Expression of nectin-4 in papillary renal cell carcinoma - Zschabitz, Stefanie; Mikuteit, Marie; Stoehr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Stroebel, Philipp; Becker, Frank; Wuelfing, Christian; Barth, Peter; Stoeckle, Michael; et al. (Discover Oncology, 2022)
Background: Nectin-4 contributes to tumor proliferation, lymphangiogenesis and angiogenesis in malignant tumors and is an emerging target in tumor therapy. In renal cell carcinoma (RCC) VEGF-directed tyrosine kinase inhibitors and checkpoint inhibitors are currently treatments of choice. Enfortumab vedotin-ejf (EV) is an antibody drug conjugate that targets Nectin-4. The aim of our study was to investigate the expression of Nectin-4 in a large cohort of papillary RCC specimens. Patients and methods: Specimens were derived from the PANZAR consortium (Erlangen, Heidelberg, Herne, Homburg, Mainz, Mannheim, Marburg, Muenster, LMU Munich, TU Munich, and Regensburg). Clinical data and tissue samples from n = 190 and n = 107 patients with type 1 and 2 pRCC, respectively, were available. Expression of Nectin-4 was determined by immunohistochemistry (IHC). Results: In total, Nectin-4 staining was moderately or strongly positive in of 92 (48.4%) of type 1 and 39 (36.4%) type 2 of pRCC cases. No associations between Nectin-4 expression and age at diagnosis, gender, grading, and TNM stage was found. 5 year overall survival rate was not statistically different in patients with Nectin-4 negative versus Nectin-4 positive tumors for the overall cohort and the pRCC type 2 subgroup, but higher in patient with Nectin-4 positive pRCC type 1 tumors compared to Nectin-4 negative tumors (81.3% vs. 67.8%, p = 0.042). Conclusion: Nectin-4 could not be confirmed as a prognostic marker in pRCC in general. Due to its high abundance on pRCC specimens Nectin-4 is an interesting target for therapeutical approaches e.g. with EV. Clinical trials are warranted to elucidate its role in the pRCC treatment landscape.
CRIS-Team Scopus Importer:2022-10-07
Keywords: Nectin 4; Papillary renal cell carcinoma

Expression of neuroendocrine markers in different molecular subtypes of breast carcinoma - Wachter, David; Hartmann, Arndt; Beckmann, Matthias; Fasching, Peter; Hein, Alexander; Bayer, Christian M.; Agaimy, Abbas (BioMed Research International, 2014)
Carcinomas of the breast with neuroendocrine features are incorporated in the World Health Organization classification since 2003 and include well-differentiated neuroendocrine tumors, poorly differentiated neuroendocrine carcinomas/small cell carcinomas, and invasive breast carcinomas with neuroendocrine differentiation. Neuroendocrine differentiation is known to be more common in certain low-grade histologic special types and has been shown to mainly cluster to the molecular (intrinsic) luminal A subtype.We analyzed the frequency of neuroendocrine differentiation in different molecular subtypes of breast carcinomas of no histologic special type using immunohistochemical stains with specific neuroendocrine markers (chromogranin A and synaptophysin).We found neuroendocrine differentiation in 20% of luminal B-like carcinomas using current WHO criteria (at least 50% of tumor cells positive for synaptophysin or chromogranin A). In contrast, no neuroendocrine differentiation was seen in luminal A-like, HER2 amplified and triple-negative carcinomas. Breast carcinomas with neuroendocrine differentiation presented with advanced stage disease and showed aggressive behavior.We conclude that neuroendocrine differentiation is more common than assumed in poorly differentiated luminal B-like carcinomas. Use of specific neuroendocrine markers is thus encouraged in this subtype to enhance detection of neuroendocrine differentiation and hence characterize the biological and therapeutic relevance of this finding in future studies.
EVALuna2:6612

Expression of PD-1 and CTLA-4 Are Negative Prognostic Markers in Renal Cell Carcinoma - Kahlmeyer, Andreas; Stoehr, Christine; Hartmann, Arndt; Goebell, Peter; Wullich, Bernd; Wach, Sven; Taubert, Helge; Erlmeier, Franziska (Journal of Clinical Medicine, 2019)
Immuno-oncological therapy with checkpoint inhibition (CI) has become a new standard treatment in metastatic renal cell carcinoma (RCC), but the prognostic value of the expression of CI therapy target molecules is still controversial. 342 unselected consecutive RCC tumor samples were analyzed regarding their PD-1, PD-L1, and CTLA-4 expression by immunohistochemistry (IHC). The prognostic values for cancer-specific survival (CSS) and overall survival (OS) were analyzed for those not exposed to CI therapy. The expression of PD-1 in tumor-infiltrating mononuclear cells (TIMC) and PD-L1 in tumor cells was detected in 9.4% and 12.3%, respectively (Immune reactive score (IRS) > 0). Furthermore, PD-L1 expression in TIMC (IRS > 0) and CTLA-4 expression in TIMC (>1% positive cells) was detected in 4.8% and 6.3%. PD-1 expression and CTLA-4 expression were significantly associated with a worse OS and CSS in log rank survival analysis and univariate Cox regression analysis. CTLA-4 expression is a prognostic marker that is independently associated with a worse outcome in multivariate Cox regression analysis in the whole cohort (OS: p = 0.013; CSS: p = 0.048) as well as in a non-metastatic subgroup analysis (OS: p = 0.028; CSS: p = 0.022). Patients with combined CTLA-4 expression and PD-1-expression are at highest risk in OS and CSS. In RCC patients, PD-1 expression in TIMC and CTLA-4 expression in TIMC are associated with a worse OS and CSS. The combination of PD-1 expression in TIMC and CTLA-4 expression in TIMC might identify high risk patients. This is, to our knowledge, the first description of CTLA-4 expression to be a prognostic marker in RCC.
CRIS-Team WoS Importer:2019-06-25

Expression of Prostate-specific Membrane Antigen (PSMA) in Papillary Renal Cell Carcinoma - Overview and Report on a Large Multicenter Cohort - Zschaebitz, Stefanie; Erlmeier, Franziska; Stoehr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Stroebel, Philipp; Becker, Frank; Wuelfing, Christian; Barth, Peter; Stoeckle, Michael; et al. (Journal of Cancer, 2022)
Prostate specific membrane antigen (PSMA) is an emerging diagnostic and therapeutic target in prostate cancer. 68 Ga-PSMA-labeled hybrid imaging is used for the detection of prostate primary tumors and metastases. Therapeutic applications such as Lutetium-177 PSMA radionuclide therapy or bispecific antibodies that target PSMA are currently under investigation within clinical trials. The expression of PSMA, however, is not specific to prostate-tissue. It has been described in the neovascular endothelium of different types of cancer such as breast cancer, and clear cell renal cell carcinoma (ccRCC). The aim of this study was to analyze PSMA expression in papillary RCC (pRCC) type 1 and type 2, the most common non-ccRCC subtypes, and to evaluate the potential of PSMA-targeted imaging and treatment in pRCC. Formalin-fixed, paraffin-embedded tissue samples of primary tumors were analyzed for PSMA expression by immunohistochemistry. Out of n=374 pRCC specimens from the multicenter PANZAR consortium, n=197 pRCC type 1 and n=110 type 2 specimens were eligible for analysis and correlated with clinical data. In pRCC type 1 PSMA staining was positive in 4 of 197 (2.0%) samples whereas none (0/110) of the pRCC type 2 samples were positive for PSMA in this large cohort of pRCC patients. No significant PSMA expression was detected in pRCC. Reflecting current clinical evaluation of PMSA expression in RCC do not encourage further analysis in papillary subtypes.
CRIS-Team WoS Importer:2022-04-15
Keywords: prostate specific membrane antigen; papillary renal cell carcinoma; kidney cancer

Expression of Prostate-specific Membrane Antigen (PSMA) in papillary renal cell carcinoma (pRCC) - Zschaebitz, S.; Erlmeier, Franziska; Stoehr, Christine; Polifka, Iris; Schrader, A. J.; Hartmann, Arndt; Ivanyi, P.; Steffens, S. (ONCOLOGY RESEARCH AND TREATMENT, 2019)
CRIS-Team WoS Importer:2020-10-02

Expression of the Immunohistochemical Markers CK5, CD117, and EGFR in Molecular Subtypes of Breast Cancer Correlated with Prognosis - Schulmeyer, Carla; Fasching, Peter; Häberle, Lothar; Meyer, Julia; Schneider, Michael; Wachter, David; Rübner, Matthias; Pöschke, Patrik; Beckmann, Matthias; Hartmann, Arndt; Erber, Ramona; Gaß, Paul (Diagnostics, 2023)
Molecular-based subclassifications of breast cancer are important for identifying treatment options and stratifying the prognosis in breast cancer. This study aimed to assess the prognosis relative to disease-free survival (DFS) and overall survival (OS) in patients with triple-negative breast cancer (TNBC) and other subtypes, using a biomarker panel including cytokeratin 5 (CK5), cluster of differentiation 117 (CD117), and epidermal growth factor receptor (EGFR). This cohort–case study included histologically confirmed breast carcinomas as cohort arm. From a total of 894 patients, 572 patients with early breast cancer, sufficient clinical data, and archived tumor tissue were included. Using the immunohistochemical markers CK5, CD117, and EGFR, two subgroups were formed: one with all three biomarkers negative (TBN) and one with at least one of those three biomarkers positive (non-TBN). There were significant differences between the two biomarker subgroups (TBN versus non-TBN) in TNBC for DFS (p = 0.04) and OS (p = 0.02), with higher survival rates (DFS and OS) in the non-TBN subgroup. In this study, we found the non-TBN subgroup of TNBC lesions with at least one positive biomarker of CK5, CD117, and/or EGFR, to be associated with longer DFS and OS.
CRIS-Team Scopus Importer:2023-02-24
Keywords: CD117; CK5; early breast cancer; EGFR; prognosis; therapy; triple-negative breast cancer

Expression of the LIM homeobox domain transcription factor ISL1 (Islet-1) is frequent in rhabdomyosarcoma but very limited in other soft tissue sarcoma types - Erlenbach-Wuensch, Katharina; Haller, Florian; Taubert, Helge; Wuerl, Peter; Hartmann, Arndt; Agaimy, Abbas (Pathology, 2014)
The transcription factor ISL1 (islet-1) has emerged as a useful marker for metastatic pancreatic well differentiated neuroendocrine neoplasms, but recent studies showed wider expression in poorly differentiated neuroendocrine carcinomas from different sites as well as poorly differentiated neuroblastoma. Expression of ISL1 in soft tissue sarcomas has not been studied before.We evaluated ISL1 expression in 249 soft tissue tumour specimens from 249 patients and 17 precursor cell lymphoblastic lymphomas (ALL). ISL1 was not detected in any of 63 liposarcomas of different subtypes, 55 leiomyosarcomas, 22 solitary fibrous tumours, 20 undifferentiated pleomorphic/spindle cell sarcomas, 13 small cell synovial sarcomas and 17 ALL cases. Variable nuclear expression was detected in rhabdomyosarcoma (15/25, 60%), rhabdomyoblastic areas of malignant müllerian mixed tumours (5/5), Ewing sarcoma (2/12, very weak) and monophasic fibrous synovial sarcoma (2/29). More extensive staining (moderate to strong) was restricted to rhabdomyosarcoma. Taken by histological subtype, ISL1 was expressed more frequently in alveolar (9/11, 82%) versus non-alveolar (6/14, 43%) rhabdomyosarcoma. ISL1 is commonly expressed in rhabdomyosarcoma, particularly the alveolar subtype and should be distinguished from poorly differentiated neuroendocrine and neuroblastic neoplasms. Awareness of this finding helps to avoid misinterpretation as neuroendocrine neoplasms that would result in inappropriate therapeutic and prognostic consequences.
EVALuna2:6594

Expression of the p53 Inhibitors MDM2 and MDM4 as Outcome Predictor in Muscle-invasive Bladder Cancer - Kriegmair, Maximilian Christian; Balk, Matthias; Wirtz, Ralph; Steidler, Annette; Weis, Cleo-Aron; Breyer, Johannes; Hartmann, Arndt; Bolenz, Christian; Erben, Philipp (Anticancer Research, 2016)
To evaluate the prognostic role of the p53-upstream inhibitors MDM2, MDM4 and its splice variant MDM4-S in patients undergoing radical cystectomy (RC) for muscle-invasive bladder cancer (MIBC).mRNA Expression levels of MDM2, MDM4 and MDM4-S were assessed by quantitative real-time polymerase chain reaction (qRT-PCR) in 75 RC samples. Logistic regression analyses identified predictors of recurrence-free (RFS) and cancer-specific survival (CSS).High expression was found in 42% (MDM2), 27% (MDMD4) and 91% (MDM4-S) of tumor specimens. Increased MDM2 expression was significantly associated with higher tumor stage (p=0.05) and lymphovascular invasion (LVI) (p=0.041). In the univariate analysis, low MDM4 expression (hazard ratio (HR)=5.93; p=0.002; HR=3.00; p=0.047), but not MDM2 (HR=1.63; p=0.222; HR=1.59; p=0.27), were associated with RFS and CSS. In the multivariate analysis, the combination of low MDM4 and high MDM2 was significant for RFS and CSS (HR=14.9; p=0.001; HR=5.63; p=0.019).The combination of MDM2 and MDM4 expression is an independent predictor in patients undergoing RC for MIBC.
EVALuna2:6922

F18-FDG PET/CT imaging early predicts pathologic complete response to induction chemoimmunotherapy of locally advanced head and neck cancer: preliminary single-center analysis of the checkrad-cd8 trial - Beck, Michael; Hartwich, J.; Eckstein, Markus; Schmidt, D.; Gostian, Antoniu-Oreste; Müller-Hübner, Sarina; Rutzner, Sandra; Gaipl, Udo; Von Der Gruen, J.; Illmer, T.; Hautmann, M. G.; Klautke, G.; et al. (Annals of Nuclear Medicine, 2022)
Aim: In the CheckRad-CD8 trial patients with locally advanced head and neck squamous cell cancer are treated with a single cycle of induction chemo-immunotherapy (ICIT). Patients with pathological complete response (pCR) in the re-biopsy enter radioimmunotherapy. Our goal was to study the value of F-18-FDG PET/CT in the prediction of pCR after induction therapy. Methods: Patients treated within the CheckRad-CD8 trial that additionally received FDG- PET/CT imaging at the following two time points were included: 3–14 days before (pre-ICIT) and 21–28 days after (post-ICIT) receiving ICIT. Tracer uptake in primary tumors (PT) and suspicious cervical lymph nodes (LN +) was measured using different quantitative parameters on EANM Research Ltd (EARL) accredited PET reconstructions. In addition, mean FDG uptake levels in lymphatic and hematopoietic organs were examined. Percent decrease (Δ) in FDG uptake was calculated for all parameters. Biopsy of the PT post-ICIT acquired after FDG-PET/CT served as reference. The cohort was divided in patients with pCR and residual tumor (ReTu). Results: Thirty-one patients were included. In ROC analysis, ΔSUVmax PT performed best (AUC = 0.89) in predicting pCR (n = 17), with a decline of at least 60% (sensitivity, 0.77; specificity, 0.93). Residual SUVmax PT post-ICIT performed best in predicting ReTu (n = 14), at a cutpoint of 6.0 (AUC = 0.91; sensitivity, 0.86; specificity, 0.88). Combining two quantitative parameters (ΔSUVmax ≥ 50% and SUVmax PT post-ICIT ≤ 6.0) conferred a sensitivity of 0.81 and a specificity of 0.93 for determining pCR. Background activity in lymphatic organs or uptake in suspected cervical lymph node metastases lacked significant predictive value. Conclusion: FDG-PET/CT can identify patients with pCR after ICIT via residual FDG uptake levels in primary tumors and the related changes compared to baseline. FDG-uptake in LN + had no predictive value. Trial registry: ClinicalTrials.gov identifier: NCT03426657.
CRIS-Team Scopus Importer:2022-05-20
Keywords: FDG-PET/CT; Head neck cancer; HNSCC; Immunotherapy; Induction therapy

FAM13A is associated with non-small cell lung cancer (NSCLC) progression and controls tumor cell proliferation and survival - Eisenhut, Felix; Heim, Lisanne; Trump, Sonja; Mittler, Susanne; Sopel, Nina; Andreev, Katerina; Ferrazzi, Fulvia; Ekici, Arif Bülent; Rieker, Ralf; Springel, Rebekka; Assmann, Vera Elisabeth; Lechmann, Matthias; et al. (OncoImmunology, 2017)
Genome-wide association studies (GWAS) associated Family with sequence similarity 13, member A (FAM13A) with non-small cell lung cancer (NSCLC) occurrence. Here, we found increased numbers of FAM13A protein expressing cells in the tumoral region of lung tissues from a cohort of patients with NSCLC. Moreover, FAM13A inversely correlated with CTLA4 but directly correlated with HIF1? levels in the control region of these patients. Consistently, FAM13A RhoGAP was found to be associated with T cell effector molecules like HIF1? and Tbet and was downregulated in immunosuppressive CD4(+)CD25(+)Foxp3(+)CTLA4(+) T cells. TGF?, a tumor suppressor factor, as well as siRNA to FAM13A, suppressed both isoforms of FAM13A and inhibited tumor cell proliferation. RNA-Seq analysis confirmed this finding. Moreover, siRNA to FAM13A induced TGF? levels. Finally, in experimental tumor cell migration, FAM13A was induced and TGF? accelerated this process by inducing cell migration, HIF1?, and the FAM13A RhoGAP isoform. Furthermore, siRNA to FAM13A inhibited tumor cell proliferation and induced cell migration without affecting HIF1?. In conclusion, FAM13A is involved in tumor cell proliferation and downstream of TGF? and HIF1?, FAM13A RhoGAP is associated with Th1 gene expression and lung tumor cell migration. These findings identify FAM13A as key regulator of NSCLC growth and progression.
EVALuna2:6835

Fast whole-slide cartography in colon cancer histology using superpixels and CNN classification - Wilm, Frauke; Benz, Michaela; Bruns, Volker; Baghdadlian, Serop; Dexl, Jakob; Hartmann, David; Kuritcyn, Petr; Weidenfeller, Martin; Wittenberg, Thomas; Merkel, Susanne; Hartmann, Arndt; Eckstein, Markus; et al. (Journal of Medical Imaging, 2022)
Purpose: Automatic outlining of different tissue types in digitized histological specimen provides a basis for follow-up analyses and can potentially guide subsequent medical decisions. The immense size of whole-slide-images (WSIs), however, poses a challenge in terms of computation time. In this regard, the analysis of nonoverlapping patches outperforms pixelwise segmentation approaches but still leaves room for optimization. Furthermore, the division into patches, regardless of the biological structures they contain, is a drawback due to the loss of local dependencies.
CRIS-Team WoS Importer:2022-05-13

Fatal Encephalitis Associated with Borna Disease Virus 1 - Korn, Klaus; Coras, Roland; Bobinger, Tobias; Herzog, Sibylle M.; Lücking, Hannes; Stoehr, Roland; Huttner, Hagen; Hartmann, Arndt; Enßer, Armin (New England Journal of Medicine, 2018)
EVALuna2:34851

Festschrift in honor of professor Ellen Catharina Zwarthoff - Bangma, Chris; Boormans, Joost; De Jong, Christiaan; Van Kessel, Kim; Zuiverloon, Tahlita; Theodorescu, Dan; Knowles, Margaret; Hartmann, Arndt (Bladder Cancer, 2019)
CRIS-Team WoS Importer:2020-01-17

FGFR3 Mutation Status and FGFR3 Expression in a Large Bladder Cancer Cohort Treated by Radical Cystectomy: Implications for Anti-FGFR3 Treatment? - van Rhijn, Bas W.G.; Mertens, Laura S.; Mayr, Roman; Bostrom, Peter J.; Real, Francisco X.; Zwarthoff, Ellen C.; Boormans, Joost L.; Abas, Cheno; van Leenders, Geert J.L.H.; Götz, Stefanie; Hippe, Katrin; Bertz, Simone; et al. (European Urology, 2020)
Oncogenic fibroblast growth factor receptor 3 (FGFR3) mutations were associated with favorable bladder cancer in a series of 1000 radical cystectomy cases. Moreover, patients with FGFR3 mutant tumors would be more likely to benefit from anti-FGFR3 therapy than patients with overexpression only.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Bladder; Cancer; Cystectomy; Expression; FGFR3; Mutation; Urothelial carcinoma

Fibroblast growth factor receptor (FGFR) alterations in squamous differentiated bladder cancer: a putative therapeutic target for a small subgroup - Baldia, Philipp H.; Maurer, Angela; Heide, Timon; Rose, Michael; Stoehr, Robert; Hartmann, Arndt; Williams, Sarah V.; Knowles, Margaret A.; Knuechel, Ruth; Gaisa, Nadine T. (Oncotarget, 2016)
Although drugable fibroblast growth factor receptor (FGFR) alterations in squamous cell carcinomas (SCC) of various entities are well known, little is known about FGFR modifications in squamous differentiated bladder cancer. Therefore, our study evaluated FGFR1-3 alterations as a putative therapeutic target in this subgroup. We analyzed 73 squamous differentiated bladder cancers (n = 10 pT2, n = 55 pT3, n = 8 pT4) for FGFR1-3 protein expression, FGFR1-3 copy number variations, FGFR3 chromosomal rearrangements (fluorescence in situ hybridization (FISH)) and FGFR3 mutations (SNapShot analysis). Only single cases displayed enhanced protein expression, most frequently FGFR3 overexpression (9.4% (6/64)). FISH showed no amplifications of FGFR1, 2 or 3. Break apart events were only slightly above the cut off in 12.1% (8/66) of cases and no FGFR3-TACC3 rearrangements could be proven by qPCR. FGFR3 mutations (p.S249C) were found in 8.5% (6/71) of tumors and were significantly associated with FGFR3 protein overexpression (p < 0.001), and unfavourable clinical outcome (p = 0.001). Our findings are consistent with the results of the TCGA data set for the "squamous-like" subtype of bladder cancer (n = 85), which revealed reduced overall expression of FGFR1 and FGFR2 in tumors compared to normal tissue, while expression of FGFR3 remained high. In the TCGA "squamous-like" subtype FGFR3 mutations were found in 4.9% and correlated with high FGFR3 RNA expression. Mutations of FGFR1 and FGFR2 were less frequent (2.4% and 1.2%). Hence, our comprehensive study provides novel insights into a subgroup of squamous differentiated bladder tumors that hold clues for novel therapeutic regimens and may benefit from FGFR3-targeted therapies.
EVALuna2:6882

Fibroblast growth factor receptor (FGFR) gene amplifications are rare events in bladder cancer - Fischbach, Anna; Rogler, Anja; Erber, Ramona; Stoehr, Robert; Poulsom, Richard; Heidenreich, Axel; Schneevoigt, Birte-Swantje; Hauke, Sven; Hartmann, Arndt; Knüchel, Ruth; Veeck, Jürgen; Gaisa, Nadine T. (Histopathology, 2015)
Activating point mutations and protein overexpression of fibroblast growth factor receptors (FGFRs), especially FGFR3, are frequent events in bladder cancer. Little is known about gene amplifications, therefore we characterized amplification of FGFR1-3 by fluorescence in-situ hybridization (FISH).Tumours of 153 patients (n = 65 pTa low-grade, n = 15 pTa high-grade, n = 37 pT1, n = 20 pT2, n = 10 pT3, n = 6 pT4) were analysed by FISH for FGFR1-3 copy numbers and screened for FGFR3 mutations and immunohistochemical protein expression. Amplifications of FGFR1 were found in 1.6% (two of 122), FGFR2 in 0.8% (one of 121) and FGFR3 in 3.4% (five of 145). All amplifications were high-level amplifications, not overlapping with polysomy. Amplifications were found in papillary/papillary-invasive tumour parts, and predominantly in tumours with enhanced Ki67 index (>10%), aberrant CK20 expression, and low p53 expression. All FGFR3-amplified samples showed concomitant FGFR3 mutations and FGFR3 protein overexpression. FGFR amplifications were not associated significantly with gender, age, grade or stage in statistical analyses.FGFR amplifications are rare events in bladder cancer, with FGFR3 amplification being the most prevalent (3.4% of cases). Concomitant FGFR3 mutations and protein overexpression indicate that FGFR3-mediated signalling in these tumours would probably be highly active. This patient subgroup may be particularly suited to FGFR-targeted pharmacotherapy.
EVALuna2:6703

Final analysis of the prospective WSG-AGO EC-Doc versus FEC phase III trial in intermediate-risk (pN1) early breast cancer: efficacy and predictive value of Ki67 expression - Nitz, U.; Gluz, O.; Huober, J.; Kreipe, H. H.; Kates, R. E.; Hartmann, Arndt; Erber, Ramona; Scholz, M.; Lisboa, B.; Mohrmann, S.; Moebus, V.; Augustin, D.; et al. (Annals of Oncology, 2014)
Taxane-based adjuvant chemotherapy is standard in node-positive (N+) early breast cancer (BC). The magnitude of benefit in intermediate-risk N+ early BC is still unclear. WSG-AGO epiribicine and cyclophosphamide (EC)-Doc is a large trial evaluating modern taxane-based chemotherapy in patients with 1-3 positive lymph nodes (LNs) only.A total of 2011 BC patients (18-65 years, pN1) were entered into a randomized phase III trial comparing 4 × E90C600 q3w followed by 4 × docetaxel 100 q3w (n = 1008) with the current standard: 6 × F500E100C500 q3w (n = 828) or C600M40F600 d1, 8× q4w (n = 175). Primary end point was event-free survival (EFS); secondary end points were overall survival (OS), toxicity, translational research, and quality of life. Central tumor bank samples were evaluable in a representative collective (n = 772; 40%). Ki-67 was assessed centrally in hormone receptor-positive disease as a surrogate marker for the distinction of luminal A/B-like tumors.Baseline characteristics were well balanced between study arms in both main study and central tumor bank subset. At 59-month median follow-up, superior efficacy of EC-Doc [versus FEC (a combination of 5-fluorouracil, epirubicin, and cyclophosphamide)] was seen in EFS and OS: 5-year EFS: 89.8% versus 87.3% (P = 0.038); 5-year OS: 94.5% versus 92.8% (P = 0.034); both tests one-tailed. EC-Doc caused more toxicity. In hormone receptor-positive (HR)+ disease, only high-Ki-67 tumors (>= 20%) derived significant benefit from taxane-based therapy: hazard ratio = 0.39 (95% CI 0.18-0.82) for EC-Doc versus FEC (test for interaction; P = 0.01).EC-Doc significantly improved EFS and OS versus FEC in intermediate-risk BC (1-3 LNs) within all subgroups as defined by local pathology. In HR+ disease, patients with luminal A-like tumors may be potentially over-treated by taxane-based chemotherapy.ClinicalTrials.gov, NCT02115204.
EVALuna2:6696

Final analysis of the prospective WSG-AGO EC-Doc versus FEC phase III trial in intermediate-risk (pN1) early breast cancer: efficacy and predictive value of Ki67 expression (vol 25, pg 1551, 2014) - Nitz, U.; Gluz, O.; Huober, J.; Kreipe, H. H.; Kates, R. E.; Hartmann, Arndt; Erber, Ramona; Moustafa, Z.; Scholz, M.; Lisboa, B.; Mohrmann, S.; Moebus, V.; et al. (Annals of Oncology, 2017)
EVALuna2:34898

Fine needle aspiration cytology of lymph nodes in breast cancer follow-up is a feasible alternative to watchful waiting and to histology - Hammon, Matthias; Dankerl, Peter; Janka, Rolf Matthias; Wachter, David; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Uder, Michael; Wenkel, Evelyn (BMC Women's Health, 2015)
Early detection of loco-regional breast cancer recurrence improves patients' overall survival, as treatment can be initiated or active treatment can be changed. If a suspicious lymph node is diagnosed during a follow-up exam, surgical excision is often performed. The aim of this study was to evaluate the diagnostic performance of the minor invasive ultrasound-guided fine-needle aspiration cytology (FNAC) in sonomorphologically suspicious lymph nodes in breast cancer follow-up.Between April 2010 and November 2012, we performed ultrasound-guided FNAC in 38 sonographically suspicious lymph nodes of 37 breast cancer follow-up patients. Cytological specimens were evaluated if the sample material was sufficient for diagnosis and if they contained cancer cells. Patients with negative cytology were followed up clinically and sonographically. To evaluate the diagnostic performance we calculated sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) for physical examination, the different sonomorphological malignancy criteria and FNAC.In 36/38 (94.7 %) lymph nodes, the pathologist had enough material to establish a final diagnosis; in 2/38 (5.3 %) lymph nodes, the probe material was non-evaluable during cytology, these 2 were excluded from further statistical evaluation. Cytology revealed malignancy in 21 lymph nodes and showed no evidence for malignancy in 15 lymph nodes. There was no evidence for malignant disease in follow-up exams in the 15 cytologically benign lymph nodes with an average follow-up time of 3 years. The diagnostic performances of physical examination and FNAC were: Sensitivity 52/100 %, specificity 88/100 %, PPV 85/100 %, NPV 60/100 %, respectively.Our preliminary results show that FNAC is a safe and fast diagnostic approach for the evaluation of suspicious lymph nodes in the follow-up of patients with breast cancer and, thus, together with follow-up represents a feasible alternative to surgery.
EVALuna2:6744

First Presentation of idiopathic Mast Cell Activation Syndrome (MCAS) in a Young Person: Association with Histamine and Salicylate Intolerance as well as an important Differential Diagnosis in gastroenterological Problem Patients - Raithel, Martin; Rechenauer, Tobias; Goetze, Thomas; Siebenlist, Gregor; Rueckel, Aline; Baenkler, Hanns-Wolf; Hartmann, Arndt; Haller, Florian; Hoerning, Andre (INTERNIST, 2019)
CRIS-Team WoS Importer:2019-05-17

First report from the German COVID-19 autopsy registry - von Stillfried, Saskia; Bülow, Roman David; Röhrig, Rainer; Boor, Peter; Böcker, Jana; Schmidt, Jens; Tholen, Pauline; Majeed, Raphael; Wienströer, Jan; Weis, Joachim; Bremer, Juliane; Knüchel, Ruth; et al. (The Lancet Regional Health - Europe, 2022)
Background: Autopsies are an important tool in medicine, dissecting disease pathophysiology and causes of death. In COVID-19, autopsies revealed e.g., the effects on pulmonary (micro)vasculature or the nervous system, systemic viral spread, or the interplay with the immune system. To facilitate multicentre autopsy-based studies and provide a central hub supporting autopsy centres, researchers, and data analyses and reporting, in April 2020 the German COVID-19 Autopsy Registry (DeRegCOVID) was launched. Methods: The electronic registry uses a web-based electronic case report form. Participation is voluntary and biomaterial remains at the respective site (decentralized biobanking). As of October 2021, the registry included N=1129 autopsy cases, with 69271 single data points including information on 18674 available biospecimens gathered from 29 German sites. Findings: In the N=1095 eligible records, the male-to-female ratio was 1·8:1, with peaks at 65-69 and 80-84 years in males and >85 years in females. The analysis of the chain of events directly leading to death revealed COVID-19 as the underlying cause of death in 86% of the autopsy cases, whereas in 14% COVID-19 was a concomitant disease. The most common immediate cause of death was diffuse alveolar damage, followed by multi-organ failure. The registry supports several scientific projects, public outreach and provides reports to the federal health authorities, leading to legislative adaptation of the German Infection Protection Act, facilitating the performance of autopsies during pandemics. Interpretation: A national autopsy registry can provide multicentre quantitative information on COVID-19 deaths on a national level, supporting medical research, political decision-making and public discussion. Funding: German Federal Ministries of Education and Research and Health. Hintergrund: Obduktionen sind ein wichtiges Instrument in der Medizin, um die Pathophysiologie von Krankheiten und Todesursachen zu untersuchen. Im Rahmen von COVID-19 wurden durch Obduktionen z.B. die Auswirkungen auf die pulmonale Mikrovaskulatur, das Nervensystem, die systemische Virusausbreitung, und das Zusammenspiel mit dem Immunsystem untersucht. Um multizentrische, auf Obduktionen basierende Studien zu erleichtern und eine zentrale Anlaufstelle zu schaffen, die Obduktionszentren, Forscher sowie Datenanalysen und -berichte unterstützt, wurde im April 2020 das deutsche COVID-19-Autopsieregister (DeRegCOVID) ins Leben gerufen. Methoden: Das elektronische Register verwendet ein webbasiertes elektronisches Fallberichtsformular. Die Teilnahme ist freiwillig und das Biomaterial verbleibt am jeweiligen Standort (dezentrales Biobanking). Im Oktober 2021 umfasste das Register N=1129 Obduktionsfälle mit 69271 einzelnen Datenpunkten, die Informationen über 18674 verfügbare Bioproben enthielten, die von 29 deutschen Standorten gesammelt wurden. Ergebnisse: In den N=1095 ausgewerteten Datensätzen betrug das Verhältnis von Männern zu Frauen 1,8:1 mit Spitzenwerten bei 65-69 und 80-84 Jahren bei Männern und >85 Jahren bei Frauen. Die Analyse der Sequenz der unmittelbar zum Tod führenden Ereignisse ergab, dass in 86 % der Obduktionsfälle COVID-19 die zugrunde liegende Todesursache war, während in 14 % der Fälle COVID-19 eine Begleiterkrankung war. Die häufigste unmittelbare Todesursache war der diffuse Alveolarschaden, gefolgt von Multiorganversagen. Das Register unterstützt mehrere wissenschaftliche Projekte, die Öffentlichkeitsarbeit und liefert Berichte an die Bundesgesundheitsbehörden, was zu einer Anpassung des deutschen Infektionsschutzgesetzes führte und die Durchführung von Obduktionen in Pandemien erleichtert. Interpretation: Ein nationales Obduktionsregister kann multizentrische quantitative Informationen über COVID-19-Todesfälle auf nationaler Ebene liefern und damit die medizinische Forschung, die politische Entscheidungsfindung und die öffentliche Diskussion unterstützen. Finanzierung: Bundesministerien für Bildung und Forschung und für Gesundheit.
CRIS-Team Scopus Importer:2022-02-25
Keywords: Autopsy; Cause of Death; COVID-19; Registry; SARS-CoV-2

Flat intraurothelial lesions of the urinary bladder-do hyperplasia, dysplasia, and atypia of unknown significance need to exist as diagnostic entities? and how to handle in routine clinical practice - Paner, Gladell P.; Smith, Steven C.; Hartmann, Arndt; Agarwal, Piyush K.; Comperat, Eva; Amin, Mahul B. (Modern Pathology, 2022)
Classification of the putative flat preneoplastic and neoplastic lesions of the urothelium with features subthreshold for urothelial carcinoma in situ remains a challenging, indeed, vexing problem in diagnostic surgical pathology. This area, subtending lesions including flat urothelial hyperplasia, urothelial dysplasia, and atypia of unknown significance, has struggled under evolving classifications, changing criteria, and limited clinical actionability, all confounded by the recognized lack of diagnostic reproducibility. Herein, we review the state of the literature around these lesions, reviewing contemporary criteria and definitions, assessing the arguments in favor and against of retaining hyperplasia, dysplasia, and atypia of unknown significance as diagnostic entities. We clarify the intent of the original definitions for dysplasia as a lesion felt to be clearly neoplastic but with morphologic features that fall short of the threshold of urothelial carcinoma in situ. While several pathologists, including some experts in the field, conflate the term dysplasia with urothelial atypia of unknown significance, the latter is defined as a descriptive diagnosis term to express diagnostic uncertainty of a lesion of whether it is clearly reactive or neoplastic. Both molecular studies and clinical needs are considered, as we outline our approach on diagnosing each of these lesions in clinical practice. Recommendations are made to guide consistency and interoperability in future scholarship, and the place of these lesions in context of evolving trends in the field is considered.
CRIS-Team WoS Importer:2022-05-06

Four-and-a-Half LIM-Domain Protein 2 (FHL2) Induces Neuropeptide Y (NPY) in Macrophages in Visceral Adipose Tissue and Promotes Diet-Induced Obesity - Sommer, Judith; Ehnis, Hanna; Seitz, Tatjana; Schneider, Julia; Wild, Andreas; Moceri, Sandra; Buechler, Christa; Bozec, Aline; Weber, Georg; Merkel, Susanne; Beckervordersandforth, Ruth; Steinkasserer, Alexander; et al. (International Journal of Molecular Sciences, 2023)
Obesity is characterized by the expansion of the adipose tissue, usually accompanied by inflammation, with a prominent role of macrophages infiltrating the visceral adipose tissue (VAT). This chronic inflammation is a major driver of obesity-associated comorbidities. Four-and-a-half LIM-domain protein 2 (FHL2) is a multifunctional adaptor protein that is involved in the regulation of various biological functions and the maintenance of the homeostasis of different tissues. In this study, we aimed to gain new insights into the expression and functional role of FHL2 in VAT in diet-induced obesity. We found enhanced FHL2 expression in the VAT of mice with Western-type diet (WTD)-induced obesity and obese humans and identified macrophages as the cellular source of enhanced FHL2 expression in VAT. In mice with FHL2 deficiency (FHL2KO), WTD feeding resulted in reduced body weight gain paralleled by enhanced energy expenditure and uncoupling protein 1 (UCP1) expression, indicative of activated thermogenesis. In human VAT, FHL2 was inversely correlated with UCP1 expression. Furthermore, macrophage infiltration and the expression of the chemokine MCP-1, a known promotor of macrophage accumulation, was significantly reduced in WTD-fed FHL2KO mice compared with wild-type (wt) littermates. While FHL2 depletion did not affect the differentiation or lipid metabolism of adipocytes in vitro, FHL2 depletion in macrophages resulted in reduced expressions of MCP-1 and the neuropeptide Y (NPY). Furthermore, WTD-fed FHL2KO mice showed reduced NPY expression in VAT compared with wt littermates, and NPY expression was enhanced in VAT resident macrophages of obese individuals. Stimulation with recombinant NPY induced not only UCP1 expression and lipid accumulation but also MCP-1 expression in adipocytes. Collectively, these findings indicate that FHL2 is a positive regulator of NPY and MCP-1 expression in macrophages and herewith closely linked to the mechanism of obesity-associated lipid accumulation and inflammation in VAT. Thus, FHL2 appears as a potential novel target to interfere with the macrophage–adipocyte crosstalk in VAT for treating obesity and related metabolic disorders.
CRIS-Team Scopus Importer:2023-11-03
Keywords: adipocytes; FHL2; macrophages; MCP-1; NPY; obesity; thermogenesis

FOXA1 Gene Expression for Defining Molecular Subtypes of Muscle-Invasive Bladder Cancer after Radical Cystectomy - Sikic, Danijel; Eckstein, Markus; Wirtz, Ralph M.; Jarczyk, Jonas; Worst, Thomas S.; Porubsky, Stefan; Keck, Bastian; Kunath, Frank; Weyerer, Veronika; Breyer, Johannes; Otto, Wolfgang; Rinaldetti, Sebastien; et al. (Journal of Clinical Medicine, 2020)
It remains unclear how to implement the recently revealed basal and luminal subtypes of muscle-invasive bladder cancer (MIBC) into daily clinical routine and whether molecular marker panels can be reduced. The mRNA expression of basal (KRT5) and luminal (FOXA1, GATA3, KRT20) markers was measured by reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) and correlated to clinicopathological features, recurrence-free survival (RFS), disease-free survival (DFS), and overall survival (OS) in 80 patients with MIBC who underwent radical cystectomy. Additionally, the correlation of single markers with the basal and non-basal subtypes defined by a 36-gene panel was examined and then validated in the TCGA (The Cancer Genome Atlas) cohort. High expression of FOXA1 (p = 0.0048) and KRT20 (p = 0.0317) was associated with reduced RFS. In the multivariable analysis, only FOXA1 remained an independent prognostic marker for DFS (p = 0.0333) and RFS (p = 0.0310). FOXA1 expression (AUC = 0.79; p = 0.0007) was closest to the combined marker expression (AUC = 0.79; p = 0.0015) in resembling the non-basal subtype defined by the 36-gene panel. FOXA1 in combination with KRT5 may be used to distinguish the basal and non-basal subtypes of MIBC.
CRIS-Team WoS Importer:2020-05-26

FOXM1 overexpression is associated with adverse outcome and predicts response to intravesical instillation therapy in stage pT1 non-muscle-invasive bladder cancer - Breyer, Johannes; Wirtz, Ralph M.; Erben, Philipp; Rinaldetti, Sebastien; Worst, Thomas S.; Stoehr, Robert; Eckstein, Markus; Sikic, Danijel; Denzinger, Stefan; Burger, Maximilian; Hartmann, Arndt; Otto, Wolfgang (Bju International, 2019)
OBJECTIVE: To investigate the role of forkhead box protein M1 (FOXM1) mRNA expression and its prognostic value in stage pT1 non-muscle-invasive bladder cancer (NMIBC). PATIENTS AND METHODS: Clinical data and formalin-fixed paraffin-embedded tissues from transurethral resection of the bladder from patients with stage pT1 NMIBC, treated with an organ-preserving approach, were analysed retrospectively. Total RNA was isolated using commercial RNA extraction kits, and mRNA expression of FOXM1, MKI67, KRT20 and KRT5 was measured by single-step quantitative RT-PCR using RNA-specific TaqMan Assays. Statistical analysis was performed using Spearman's Rho, Wilcoxon or Kruskal-Wallis tests, Kaplan-Meier estimates of recurrence-free (RFS), progression-free (PFS) and cancer-specific survival (CSS) and Cox regression analysis. RESULTS: Data from 296 patients (79.4% men, median age 72 years) were available for the final evaluation. Spearman correlation analysis showed that mRNA expression of FOXM1 was significantly correlated with MKI67 (ρ: 0.6530, P < 0.001) and with the luminal subtype, reflected by the positive correlation with KRT20 (ρ: 0.2113, P < 0.001). Furthermore, there was also a strong correlation of FOXM1 expression with adverse clinical and pathological variables, such as concomitant carcinoma in situ (P = 0.05), multifocal tumours (P = 0.005) and World Health Organization 1973 grade 3 disease (P < 0.001). Kaplan-Meier analysis showed overexpression of FOMX1 to be associated with worse PFS (P = 0.028) and worse CSS (P = 0.015). FOXM1 overexpression was also shown to be a predictive risk factor for CSS (hazard ratio 1.61 [1.13-2.34], L-R chi-squared: 7.19, P = 0.007). FOXM1 overexpression identified a subgroup of patients within the luminal subtype with worse RFS (P = 0.017), PFS (P < 0.001) and CSS (P = 0.015). Patients with low FOXM1 expression had better outcomes, irrespective of instillation therapy, whereas patients with high FOXM1 expression benefitted from intravesical chemotherapy with mitomycin C. CONCLUSION: High FOXM1 expression was associated with adverse clinical and pathological features and worse outcomes, and predicted response to intravesical instillation therapy in patients with stage pT1 NMIBC.
EVALuna2:52993

FOXM1 predicts disease progression in non-muscle invasive bladder cancer - Rinaldetti, Sebastien; Wirtz, Ralph; Worst, Thomas Stefan; Hartmann, Arndt; Breyer, Johannes; Dyrskjot, Lars; Erben, Philipp (Journal of Cancer Research and Clinical Oncology, 2018)
PURPOSE: The proto-oncogene forkhead box M1 (FOXM1) is associated with poor survival in many cancers. The impact of FOXM1 expression on progression-free survival (PFS) of non-muscle invasive bladder cancer (NMIBC) has not yet been investigated. The differential expression of FOXM1 between the different molecular NMIBC subtypes has further been assessed. METHODS: Transcript levels of FOXM1 and MKI67 were determined in 460 NMIBC patients (UROMOL cohort) by RNA-Seq and validated in silico by the Chungbuk and Lund cohort (n = 277). FOXM1 and MKI67 cutoffs were identified by the minimal p value method. Variables were evaluated by multivariable Cox regression analyses in order to identify independent predictors. RESULTS: FOXM1 is an independent predictor for PFS superior to current histological, clinical and molecular staging methods. Patients with high FOXM1 expression have a 6- to 8-fold higher risk of progression in multivariable analysis (p < 0.03). Highest transcript levels were found in the Class 2 and genomically unstable molecular NMIBC subtype (p < 0.03). The proto-oncogene further positively correlated with tumor grade and stage. NMIBCs with high FOXM1 expression showed a PFS advantage when treated with intravesical BCG instillation. CONCLUSION: FOXM1 is a highly prognostic marker for disease progression of NMIBC superior to current histological, clinical and molecular staging methods and MKI67. It is mainly expressed in the Class 2 and genomically unstable molecular bladder cancer subtypes. Its role in drug resistance development makes FOXM1 valuable biomarker for NMIBC risk stratification.
EVALuna2:34602

FOXM1 predicts overall and disease specific survival in muscle-invasive urothelial carcinoma and presents a differential expression between bladder cancer subtypes - Rinaldetti, Sebastien; Wirtz, Ralph Markus; Worst, Thomas Stefan; Eckstein, Markus; Weiss, Cleo Aaron; Breyer, Johannes; Otto, Wolfgang; Bolenz, Christian; Hartmann, Arndt; Erben, Philipp (Oncotarget, 2017)
Forkhead box M1 (FOXM1) is a late cell cycle gene that plays a crucial role in carcinogenesis and chemotherapeutic drug resistance. In this study, the impact of FOXM1 expression on patient outcome was investigated for the first time in formalin fixed and paraffin embedded (FFPE) samples of chemotherapy naïve muscle-invasive bladder cancer (MIBC) patients. Expression analyses were performed on the Mannheim cohort (n=84) and validated on the independent Chungbuk cohort (n=61). In a Cox' proportional hazards model, a distinct FOXM1 expression cut-off dividing both cohorts in a 'high-risk' and 'low-risk' group has been determined. Multivariate analyses showed that FOXM1 is an independent risk factor for outcome prediction superior to the TNM system. The FOXM1 'high-risk' group had a 4- to 7-fold increased risk of death (p<0.03) and presented further an overexpression of MKI67. Recent studies showed that MIBCs can be subclassified in breast cancer-like subtypes: basal, luminal and p53-like. Here we demonstrated that FOXM1 was differentially expressed between MIBC subtypes concordant to its subtype specific expression in breast cancer. Since the proto-oncogene FOXM1 is known to play an important role in cisplatin resistance and to be a promising drug target, this study supports FOXM1 as a crucial biomarker in the personalization of MIBC therapy and urges prospective translational studies.
EVALuna2:6875

Frequency of activating mutations in FGFR2 exon 7 in bladder tumors from patients with early-onset and regular-onset disease - Spiegelberg, Christine; Giedl, Josef; Gaisa, Nadine T.; Rogler, Anja; Riener, Marc-Oliver; Filbeck, Thomas; Burger, Maximilian; Ruemmele, Petra; Hartmann, Arndt; Stoehr, Robert (International Journal of Clinical and Experimental Pathology, 2014)
The FGF/FGFR-system plays an important role in embryogenesis, tissue homeostasis and carcinogenesis. Mutational activation of FGFR2 resulting in aberrant FGFR2 signaling activation is known from both hereditary germ line alterations and somatic mutations in various malignancies (e.g. breast, gastric or ovarian cancer). FGFR2 mutations are mainly located within the hinge between Ig-like domains (exon 7), around the 3rd Ig-like domains and within the kinase domain. For bladder cancer only sparse data on FGFR2 mutations are available. Most interestingly a case of early-onset papillary carcinoma of the bladder showing a FGFR2 p.Pro253Arg mutation in exon 7 in a patient with Apert Syndrome was reported recently. To further evaluate the importance of FGFR2 exon 7 alterations in bladder cancer a cohort of 254 bladder tumors (cohort 1: unselected cases: n=139; cohort 2: early-onset bladder cancer cases (age at time of diagnosis<=45 years): n=115) was analyzed. Sections from formalin-fixed, paraffin-embedded bladder tumors were used for DNA isolation. After precise microdissection exon 7 of the FGFR2 gene was analyzed by direct Sanger sequencing. All cases could be analyzed successfully. Mutations in exon 7 of FGFR2 could not be detected in any of the cases. All tumors showed wild type sequence. Our data demonstrate that the recently reported association between early-onset papillary carcinoma of the bladder with germ line FGFR2 p.Pro253Arg mutation could not be found in our cohorts of sporadic bladder tumors. These results indicate that FGFR2 gene mutations might only play a minor role in bladder carcinogenesis.
EVALuna2:6601

Frequency of GNAS mutation in intramuscular myxoma - Erber, Ramona; Stöhr, Robert; Haller, Florian; Hartmann, Arndt; Agaimy, Abbas (VIRCHOWS ARCHIV, 2019)
CRIS-Team WoS Importer:2019-09-27

Frequency of microsatellite instability (MSI) in upper tract urothelial carcinoma: comparison of the Bethesda panel and the Idylla MSI assay in a consecutively collected, multi-institutional cohort - Kullmann, Friederike; Strissel, Pamela; Strick, Reiner; Stöhr, Robert; Eckstein, Markus; Bertz, Simone; Wullich, Bernd; Sikic, Danijel; Wach, Sven; Taubert, Helge; Olbert, Peter; Heers, Hendrik; et al. (Journal of Clinical Pathology, 2021)
Aims Upper tract urothelial carcinoma (UTUC) is a rare malignancy with a poor prognosis which occurs sporadically or in few cases results from a genetic disorder called Lynch syndrome. Recently, examination of microsatellite instability (MSI) has gained importance as a biomarker: MSI tumours are associated with a better response to immunomodulative therapies. Limited data are known about the prevalence of MSI in UTUC. New detection methods using the fully automated Idylla MSI Assay facilitate analysis of increased patient numbers. Methods We investigated the frequency of MSI in a multi-institutional cohort of 243 consecutively collected UTUC samples using standard methodology (Bethesda panel), along with immunohistochemistry of mismatch repair (MMR) proteins. The same tumour cohort was retested using the Idylla MSI Assay by Biocartis. Results Using standard methodology, 230/243 tumours were detected as microsatellite stable (MSS), 4/243 tumours as MSI and 9/243 samples as invalid. In comparison, the Idylla MSI Assay identified four additional tumours as MSS, equalling 234/243 tumours; 4/243 were classified as MSI and only 5/243 cases as invalid. At the immunohistochemical level, MSI results were supported in all available cases with a loss in MMR proteins. The overall concordance between the standard and the Idylla MSI Assay was 98.35%. Time to result differed between 3 hours for Idylla MSI Assay and 2 days with the standard methodology. Conclusion Our data indicate a low incidence rate of MSI tumours in patients with UTUC. Furthermore, our findings highlight that Idylla MSI Assay can be applied as an alternative method of MSI analysis for UTUC.
CRIS-Team WoS Importer:2021-12-10

Frequency of TERT Promoter Mutations in Prostate Cancer - Stoehr, Robert; Taubert, Helge; Zinnall, Ulrike; Giedl, Josef; Gaisa, Nadine T.; Burger, Maximilian; Ruemmele, Petra; Hurst, Carolyn D.; Knowles, Margaret A.; Wullich, Bernd; Hartmann, Arndt (Pathobiology, 2015)
Recently, recurrent mutations within the core promoter of the human telomerase reverse transcriptase (TERT) gene generating consensus binding sites for ETS transcription factor family members were described in melanomas and other malignancies (e.g. bladder cancer, hepatocellular carcinoma). These mutations were discussed as early drivers for malignant transformation. In prostate cancer (PrCa) TERT expression has been associated with a poor prognosis and higher risk for disease recurrence. The underlying mechanisms for high TERT expression in PrCa have still not been clarified. To date, data on TERT promoter mutation analysis in PrCa are sparse. Therefore, we performed sequence analysis of the core promoter region of the TERT gene in an unselected cohort of prostate tumors.Sections from 167 formalin-fixed, paraffin-embedded and cryopreserved prostate tumors were microdissected and used for DNA isolation. The mutation hotspot region within the TERT core promoter (-260 to +60) was analyzed by direct Sanger sequencing or SNaPshot analysis.All cases were analyzed successfully. Mutations within the core promoter of the TERT gene were not detected in any of the cases with all tumors exhibiting a wild-type sequence.TERT core promoter mutations reported from several other malignancies were not detected in our unselected cohort of PrCa. These data indicate that alterations within the core promoter of the TERT gene do not play an important role in prostate carcinogenesis. © 2015 S. Karger AG, Basel.
EVALuna2:6706

Fumarate Hydratase-deficient Renal Cell Carcinoma Is Strongly Correlated With Fumarate Hydratase Mutation and Hereditary Leiomyomatosis and Renal Cell Carcinoma Syndrome - Trpkov, Kiril; Hes, Ondrej; Agaimy, Abbas; Bonert, Michael; Martinek, Petr; Magi-Galluzzi, Cristina; Kristiansen, Glen; Lueders, Christine; Nesi, Gabriella; Comperat, Eva; Sibony, Mathilde; Berney, Daniel M.; et al. (American Journal of Surgical Pathology, 2016)
Hereditary leiomyomatosis and renal cell carcinoma syndrome-associated renal cell carcinomas (RCC) are difficult to diagnose prospectively. We used immunohistochemistry (IHC) to identify fumarate hydratase (FH)-deficient tumors (defined as FH negative, 2-succinocysteine [2SC] positive) in cases diagnosed as "unclassified RCC, high grade or with papillary pattern," or "papillary RCC type 2," from multiple institutions. A total of 124 tumors (from 118 patients) were evaluated by IHC for FH and 2SC. An FH deficiency was found in 24/124 (19%) cases. An indeterminate result (only 1 marker abnormal) was found in 27/124 (22%) cases. In a tissue microarray of 776 RCCs of different types, only 2 (0.5%) tumors, initially considered papillary type 2, were FH deficient. FH mutations were found in 19/21 FH-deficient tumors (with confirmed germline mutations in 9 of 9 tumors in which germline status could be assessed) and in 1/26 FH-indeterminate tumors identified by IHC. No FH mutations were found in 2/21 FH-deficient RCCs, 25/26 FH-indeterminate RCCs, and 10/10 RCCs demonstrating FH expression by IHC. Patients with FH-deficient RCC had a median age of 44 years (range, 21 to 65 y). Average tumor size was 8.2 cm (range, 0.9 to 18 cm). FH-deficient RCCs were characterized by at least focal macronucleoli and demonstrated 2 or more growth patterns in 93% cases. Papillary was the most common (74%) and dominant (59%) pattern, whereas other common patterns included: solid (44%), tubulocystic (41%), cribriform (41%), and cystic (33%). At presentation, 57% were stage >=pT3, 52% had positive nodes, and 19% had distant metastases. After a mean follow-up of 27 months (range, 1 to 114 mo), 39% of patients were dead of disease, and 26% had disease progression. We conclude that FH and 2SC are useful IHC ancillary tools, which allow recognition of FH-deficient RCC.
EVALuna2:6823

Fumarate hydratase (FH) deficiency in uterine leiomyomas: recognition by histological features versus blind immunoscreening - Siegler, Lisa; Erber, Ramona; Burghaus, Stefanie; Brodkorb, Tobias; Wachter, David; Wilkinson, Nafisa; Bolton, James; Stringfellow, Helen; Haller, Florian; Beckmann, Matthias; Hartmann, Arndt; Agaimy, Abbas (Virchows Archiv, 2018)
Hereditary leiomyomatosis and renal cell carcinoma (HLRCC) syndrome is a rare autosomal dominant disease caused by germline mutations in the fumarate hydratase (FH) gene. Affected individuals develop cutaneous and uterine leiomyomas and aggressive RCC. To date, only few publications described the frequency and morphology of FH-deficient uterine leiomyomas. We reviewed 22 cases collected over 8 years from routine and consultation files based on distinctive histological features. In addition, we screened 580 consecutive uterine leiomyomas from 484 patients, 23 extra-uterine and 8 uterine leiomyosarcomas, and 6 leiomyomas with bizarre nuclei for FH loss using immunohistochemistry (IHC) on tissue microarrays (TMAs). All 22 FH-deficient cases were suspected on H&E sections and confirmed by FH IHC. Patients' ages ranged from 25 to 70 years (median 36). Seventeen patients had multiple nodules (2-14) measuring up to 11.8 cm. None of the patients had stigmata or family history of the HLRCC syndrome. Histologically, all FH-deficient tumors showed consistent and reproducible features as reported previously. FH loss was detected in 2/534 evaluable leiomyomas (0.4%), but in none of leiomyosarcomas. Two of six leiomyomas with bizarre nuclei were FH-deficient. FH-deficient uterine leiomyomas are rare in routine material (= 0.4%). They can be reliably identified or suspected by consistent morphological features. Our data showed predictive morphology to be superior to blind IHC screening for detecting them. The relationship of FH-deficient uterine smooth muscle tumors to the HLRCC syndrome needs further clarification.
EVALuna2:33962

Functional analyses and prognostic significance of SFRP1 expression in bladder cancer - Rogler, Anja; Kendziorra, Emil; Giedl, Josef; Stoehr, Christine; Taubert, Helge; Goebell, Peter; Wullich, Bernd; Stoeckle, Michael; Lehmann, Jan; Petsch, Sabrina; Hartmann, Arndt; Stoehr, Robert (Journal of Cancer Research and Clinical Oncology, 2015)
We previously showed that the Wnt-signaling antagonist SFRP1 (secreted frizzled-related protein 1) is a promising marker in bladder cancer. The aim of this study was to validate the prognostic role and analyze the functional significance of SFRP1.Four bladder cancer cell lines (RT112, RT4, J82 and BFTC905) and one urothelial cell line (UROtsa) were used for functional characterization of SFRP1 expression. Effects on viability, proliferation and wound healing were investigated, and canonical Wnt-pathway activity as well as Wnt-signaling target gene expression was analyzed. Additionally, tissue micro-arrays from two different bladder tumor cohorts were evaluated for SFRP1 expression, and associations with survival and histopathological parameters were analyzed.The cell lines RT112, RT4, J82 and UROtsa showed SFRP1 expression. In BFTC905, SFRP1 expression was inhibited by promoter hypermethylation. Wnt-pathway activity was absent in all cell lines and independent from SFRP1 expression. RT112 and BFTC905 were used for further functional characterization. SFRP1 overexpression resulted in decreased viability and migration in BFTC905 cells. Knockdown of SFRP1 expression in RT112 cells resulted only in marginal effects. In bladder tumors, SFRP1 expression was associated with lower tumor grade, but not with progression in patients with papillary bladder cancer. SFRP1 expressing papillary bladder cancer tumors also demonstrated a tendency to longer overall survival.SFRP1 is reducing malignant potential of BFTC905 cells, but not by regulation of canonical Wnt-signaling pathway. Other pathways, like non-canonical Wnt or the MAPK pathway, could be activated via SFRP1-expression loss. In bladder tumors, SFRP1 has the potential to predict outcome for a subset of papillary bladder tumors.
EVALuna2:6533

Further Evidence of Neuroprotective Effects of Recombinant Human Erythropoietin and Growth Hormone in Hypoxic Brain Injury in Neonatal Mice - Klepper, Simon; Jung, Susan; Dittmann, Lara; Geppert, Carol-Immanuel; Hartmann, Arndt; Beier, Nicole; Trollmann, Regina (International Journal of Molecular Sciences, 2022)
Experimental in vivo data have recently shown complementary neuroprotective actions of rhEPO and growth hormone (rhGH) in a neonatal murine model of hypoxic brain injury. Here, we hypothesized that rhGH and rhEPO mediate stabilization of the blood-brain barrier (BBB) and regenerative vascular effects in hypoxic injury to the developing brain. Using an established model of neonatal hypoxia, neonatal mice (P7) were treated i.p. with rhGH (4000 mu g/kg) or rhEPO (5000 IU/kg) 0/12/24 h after hypoxic exposure. After a regeneration period of 48 h or 7 d, cerebral mRNA expression of Vegf-A, its receptors and co-receptors, and selected tight junction proteins were determined using qRT-PCR and ELISA. Vessel structures were assessed by Pecam-1 and occludin (Ocln) IHC. While Vegf-A expression increased significantly with rhGH treatment (p < 0.01), expression of the Vegfr and TEK receptor tyrosine kinase (Tie-2) system remained unchanged. RhEPO increased Vegf-A (p < 0.05) and Angpt-2 (p < 0.05) expression. While hypoxia reduced the mean vessel area in the parietal cortex compared to controls (p < 0.05), rhGH and rhEPO prevented this reduction after 48 h of regeneration. Hypoxia significantly reduced the Ocln(+) fraction of cortical vascular endothelial cells. Ocln signal intensity increased in the cortex in response to rhGH (p < 0.05) and in the cortex and hippocampus in response to rhEPO (p < 0.05). Our data indicate that rhGH and rhEPO have protective effects on hypoxia-induced BBB disruption and regenerative vascular effects during the post-hypoxic period in the developing brain.
CRIS-Team WoS Importer:2022-08-26

Gene expression and promoter methylation of angiogenic and lymphangiogenic factors as prognostic markers in melanoma - Monteiro, Ana Carolina; Muenzner, Julienne K.; Andrade, Fernando; Rius, Flávia Eichemberger; Ostalecki, Christian; Geppert, Carol-Immanuel; Agaimy, Abbas; Hartmann, Arndt; Fujita, André; Schneider-Stock, Regine; Jasiulionis, Miriam Galvonas (Molecular Oncology, 2019)
The high mortality rate of melanoma is broadly associated with its metastatic potential. Tumor cell dissemination is strictly dependent on vascularization; therefore, angiogenesis and lymphangiogenesis play an essential role in metastasis. Hence, a better understanding of the players of tumor vascularization and establishing them as new molecular biomarkers might help to overcome the poor prognosis of melanoma patients. Here, we further characterized a linear murine model of melanoma progression and showed that the aggressiveness of melanoma cells is closely associated with high expression of angiogenic factors, such as Vegfc, Angpt2, and Six1, and that blockade of the vascular endothelial growth factor pathway by the inhibitor axitinib abrogates their tumorigenic potential in vitro and in the in vivo chicken chorioallantoic membrane assay. Furthermore, analysis of The Cancer Genome Atlas data revealed that the expression of the angiogenic factor ANGPT2 (P-value = 0.044) and the lymphangiogenic receptor VEGFR-3 (P-value = 0.002) were independent prognostic factors of overall survival in melanoma patients. Enhanced reduced representation bisulfite sequencing-based methylome profiling revealed for the first time a link between abnormal VEGFC, ANGPT2, and SIX1 gene expression and promoter hypomethylation in melanoma cells. In patients, VEGFC (P-value = 0.031), ANGPT2 (P-value < 0.001), and SIX1 (P-value = 0.009) promoter hypomethylation were independent prognostic factors of shorter overall survival. Hence, our data suggest that these angio- and lymphangiogenesis factors are potential biomarkers of melanoma prognosis. Moreover, these findings strongly support the applicability of our melanoma progression model to unravel new biomarkers for this aggressive human disease.
CRIS-Team Scopus Importer:2019-06-18
Keywords: angiogenesis; biomarkers; DNA methylation; melanoma; prognosis

Gene Expression in Solitary Fibrous Tumors (SFTs) Correlates with Anatomic Localization and NAB2-STAT6 Gene Fusion Variants - Bieg, Matthias; Moskalev, Evgeny; Will, Rainer; Hebele, Simone; Schwarzbach, Matthias; Schmeck, Sanja; Hohenberger, Peter; Jakob, Jens; Kasper, Bernd; Gaiser, Timo; Ströbel, Philip; Wardelmann, Eva; et al. (American Journal of Pathology, 2021)
Solitary fibrous tumors (SFTs) harbor recurrent NAB2-STAT6 gene fusions, promoting constitutional up-regulation of oncogenic early growth response 1 (EGR1)-dependent gene expression. SFTs with the most common canonical NAB2 exon 4–STAT6 exon 2 fusion variant are often located in the thorax (pleuropulmonary) and are less cellular with abundant collagen. In contrast, SFTs with NAB2 exon 6–STAT6 exon 16/17 fusion variants typically display a cellular round to ovoid cell morphology and are often located in the deep soft tissue of the retroperitoneum and intra-abdominal pelvic region or in the meninges. Here, we employed next-generation sequencing–based gene expression profiling to identify significant differences in gene expression associated with anatomic localization and NAB2-STAT6 gene fusion variants. SFTs with the NAB2 exon 4–STAT6 exon 2 fusion variant showed a transcriptional signature enriched for genes involved in DNA binding, gene transcription, and nuclear localization, whereas SFTs with the NAB2 exon 6–STAT6 exon 16/17 fusion variants were enriched for genes involved in tyrosine kinase signaling, cell proliferation, and cytoplasmic localization. Specific transcription factor binding motifs were enriched among differentially expressed genes in SFTs with different fusion variants, implicating co–transcription factors in the modification of chimeric NGFI-A binding protein 2 (NAB2)-STAT6–dependent deregulation of EGR1-dependent gene expression. In summary, this study establishes a potential molecular biologic basis for clinicopathologic differences in SFTs with distinct NAB2-STAT6 gene fusion variants.
CRIS-Team Scopus Importer:2021-04-02

Generation and characterization of hepatocellular carcinoma cell lines with enhanced cancer stem cell potential - Muenzner, Julienne K.; Kunze, Philipp; Lindner, Pablo; Polaschek, Sandra; Menke, Kira; Eckstein, Markus; Geppert, Carol-Immanuel; Chanvorachote, Pithi; Bäuerle, Tobias; Hartmann, Arndt; Schneider-Stock, Regine (Journal of Cellular and Molecular Medicine, 2018)
Hepatocellular carcinoma (HCC) is one of the most common causes for cancer-related death worldwide with rapidly increasing incidence and mortality rates. As for other types of cancers, also in HCC cancer stem cells (CSCs) are thought to be responsible for tumour initiation, progression and therapy failure. However, as rare subpopulations of tumour tissue, CSCs are difficult to isolate, thus making the development of suitable and reliable model systems necessary. In our study, we generated HepG2 subclones with enriched CSC potential by application of the spheroid formation method and subsequent single-cell cloning. Analyses in several 2D and 3D cell culture systems as well as a panel of functional assays both in vitro and in vivo revealed that the generated subclones displayed characteristic and sustained features of tumour initiating cells as well as highly aggressive properties related to tumour progression and metastasis. These characteristics could clearly be correlated with the expression of CSC markers that might have prognostic value in the clinical HCC setting. Therefore, we conclude that our CSC enriched HepG2 clones certainly represent suitable model systems to study the role of CSCs during HCC initiation, progression and drug resistance.
EVALuna2:34899

Genetic risk factors for ovarian cancer and their role for endometriosis risk - Burghaus, Stefanie; Fasching, Peter; Haeberle, Lothar; Rübner, Matthias; Buechner, Kathrin; Blum, Simon; Engel, Anne; Ekici, Arif Bülent; Hartmann, Arndt; Hein, Alexander; Beckmann, Matthias; Renner, Stefan (Gynecologic Oncology, 2017)
Several genetic variants have been validated as risk factors for ovarian cancer. Endometriosis has also been described as a risk factor for ovarian cancer. Identifying genetic risk factors that are common to the two diseases might help improve our understanding of the molecular pathogenesis potentially linking the two conditions.In a hospital-based case-control analysis, 12 single nucleotide polymorphisms (SNPs), validated by the Ovarian Cancer Association Consortium (OCAC) and the Collaborative Oncological Gene-environment Study (COGS) project, were genotyped using TaqMan® OpenArray(TM) analysis. The cases consisted of patients with endometriosis, and the controls were healthy individuals without endometriosis. A total of 385 cases and 484 controls were analyzed. Odds ratios and P values were obtained using simple logistic regression models, as well as from multiple logistic regression models with adjustment for clinical predictors.rs11651755 in HNF1B was found to be associated with endometriosis in this case-control study. The OR was 0.66 (95% CI, 0.51 to 0.84) and the P value after correction for multiple testing was 0.01. None of the other genotypes was associated with a risk for endometriosis.As rs11651755 in HNF1B modified both the ovarian cancer risk and also the risk for endometriosis, HNF1B may be causally involved in the pathogenetic pathway leading from endometriosis to ovarian cancer.
EVALuna2:6871

Genetic variation at the 8q24.21 renal cancer susceptibility locus affects HIF binding to a MYC enhancer. - Grampp, Steffen; Platt, James L.; Lauer, Victoria; Salama, Rafik; Kranz, Franziska; Neumann, Viviana K.; Wach, Sven; Stoehr, Christine; Hartmann, Arndt; Eckardt, Kai-Uwe; Ratcliffe, Peter J.; Mole, David R.; et al. (Nature Communications, 2016)
Clear cell renal cell carcinoma (ccRCC) is characterized by loss of function of the von Hippel-Lindau tumour suppressor (VHL) and unrestrained activation of hypoxia-inducible transcription factors (HIFs). Genetic and epigenetic determinants have an impact on HIF pathways. A recent genome-wide association study on renal cancer susceptibility identified single-nucleotide polymorphisms (SNPs) in an intergenic region located between the oncogenes MYC and PVT1. Here using assays of chromatin conformation, allele-specific chromatin immunoprecipitation and genome editing, we show that HIF binding to this regulatory element is necessary to trans-activate MYC and PVT1 expression specifically in cells of renal tubular origins. Moreover, we demonstrate that the risk-associated polymorphisms increase chromatin accessibility and activity as well as HIF binding to the enhancer. These findings provide further evidence that genetic variation at HIF-binding sites modulates the oncogenic transcriptional output of the VHL-HIF axis and provide a functional explanation for the disease-associated effects of SNPs in ccRCC.

Genetic variation in mitotic regulatory pathway genes is associated with breast tumor grade - Purrington, Kristen S.; Slettedahl, Seth; Bolla, Manjeet K.; Michailidou, Kyriaki; Czene, Kamila; Nevanlinna, Heli; Bojesen, Stig E.; Andrulis, Irene L.; Cox, Angela; Hall, Per; Carpenter, Jane; Yannoukakos, Drakoulis; et al. (Human Molecular Genetics, 2014)
Mitotic index is an important component of histologic grade and has an etiologic role in breast tumorigenesis. Several small candidate gene studies have reported associations between variation in mitotic genes and breast cancer risk. We measured associations between 2156 single nucleotide polymorphisms (SNPs) from 194 mitotic genes and breast cancer risk, overall and by histologic grade, in the Breast Cancer Association Consortium (BCAC) iCOGS study (n = 39 067 cases; n = 42 106 controls). SNPs in TACC2 [rs17550038: odds ratio (OR) = 1.24, 95% confidence interval (CI) 1.16-1.33, P = 4.2 × 10(-10)) and EIF3H (rs799890: OR = 1.07, 95% CI 1.04-1.11, P = 8.7 × 10(-6)) were significantly associated with risk of low-grade breast cancer. The TACC2 signal was retained (rs17550038: OR = 1.15, 95% CI 1.07-1.23, P = 7.9 × 10(-5)) after adjustment for breast cancer risk SNPs in the nearby FGFR2 gene, suggesting that TACC2 is a novel, independent genome-wide significant genetic risk locus for low-grade breast cancer. While no SNPs were individually associated with high-grade disease, a pathway-level gene set analysis showed that variation across the 194 mitotic genes was associated with high-grade breast cancer risk (P = 2.1 × 10(-3)). These observations will provide insight into the contribution of mitotic defects to histological grade and the etiology of breast cancer.
EVALuna2:6629

Genome-wide association studies of autoimmune vitiligo identify 23 new risk loci and highlight key pathways and regulatory variants - Jin, Ying; Andersen, Genevieve; Yorgov, Daniel; Ferrara, Tracey M.; Ben, Songtao; Brownson, Kelly M.; Holland, Paulene J.; Birlea, Stanca A.; Siebert, Janet; Hartmann, Arndt; Lienert, Anne-Marie; Van Geel, Nanja; et al. (Nature Genetics, 2016)
Vitiligo is an autoimmune disease in which depigmented skin results from the destruction of melanocytes, with epidemiological association with other autoimmune diseases. In previous linkage and genome-wide association studies (GWAS1 and GWAS2), we identified 27 vitiligo susceptibility loci in patients of European ancestry. We carried out a third GWAS (GWAS3) in European-ancestry subjects, with augmented GWAS1 and GWAS2 controls, genome-wide imputation, and meta-analysis of all three GWAS, followed by an independent replication. The combined analyses, with 4,680 cases and 39,586 controls, identified 23 new significantly associated loci and 7 suggestive loci. Most encode immune and apoptotic regulators, with some also associated with other autoimmune diseases, as well as several melanocyte regulators. Bioinformatic analyses indicate a predominance of causal regulatory variation, some of which corresponds to expression quantitative trait loci (eQTLs) at these loci. Together, the identified genes provide a framework for the genetic architecture and pathobiology of vitiligo, highlight relationships with other autoimmune diseases and melanoma, and offer potential targets for treatment.
EVALuna2:19619

Genome-wide association study identifies 25 known breast cancer susceptibility loci as risk factors for triple-negative breast cancer - Purrington, Kristen S.; Slager, Susan; Eccles, Diana; Yannoukakos, Drakoulis; Fasching, Peter A.; Miron, Penelope; Carpenter, Jane; Chang-Claude, Jenny; Martin, Nicholas G.; Montgomery, Grant W.; Kristensen, Vessela; Anton-Culver, Hoda; et al. (Carcinogenesis, 2014)
Triple-negative (TN) breast cancer is an aggressive subtype of breast cancer associated with a unique set of epidemiologic and genetic risk factors. We conducted a two-stage genome-wide association study of TN breast cancer (stage 1: 1529 TN cases, 3399 controls; stage 2: 2148 cases, 1309 controls) to identify loci that influence TN breast cancer risk. Variants in the 19p13.1 and PTHLH loci showed genome-wide significant associations (P < 5 × 10(-) (8)) in stage 1 and 2 combined. Results also suggested a substantial enrichment of significantly associated variants among the single nucleotide polymorphisms (SNPs) analyzed in stage 2. Variants from 25 of 74 known breast cancer susceptibility loci were also associated with risk of TN breast cancer (P < 0.05). Associations with TN breast cancer were confirmed for 10 loci (LGR6, MDM4, CASP8, 2q35, 2p24.1, TERT-rs10069690, ESR1, TOX3, 19p13.1, RALY), and we identified associations with TN breast cancer for 15 additional breast cancer loci (P < 0.05: PEX14, 2q24.1, 2q31.1, ADAM29, EBF1, TCF7L2, 11q13.1, 11q24.3, 12p13.1, PTHLH, NTN4, 12q24, BRCA2, RAD51L1-rs2588809, MKL1). Further, two SNPs independent of previously reported signals in ESR1 [rs12525163 odds ratio (OR) = 1.15, P = 4.9 × 10(-) (4)] and 19p13.1 (rs1864112 OR = 0.84, P = 1.8 × 10(-) (9)) were associated with TN breast cancer. A polygenic risk score (PRS) for TN breast cancer based on known breast cancer risk variants showed a 4-fold difference in risk between the highest and lowest PRS quintiles (OR = 4.03, 95% confidence interval 3.46-4.70, P = 4.8 × 10(-) (69)). This translates to an absolute risk for TN breast cancer ranging from 0.8% to 3.4%, suggesting that genetic variation may be used for TN breast cancer risk prediction.
EVALuna2:6530

Glucose-Restricted Diet Regulates the Tumor Immune Microenvironment and Prevents Tumor Growth in Lung Adenocarcinoma - Gähler, Alexander; Trufa, Denis; Chiriac, Mircea-Teodor; Tausche, Patrick; Hohenberger, Katja; Brunst, Ann-Kathrin; Rauh, Manfred; Geppert, Carol-Immanuel; Rieker, Ralf; Krammer, Susanne; Leberle, Anna; Neurath, Markus; et al. (Frontiers in Oncology, 2022)
BackgroundLung cancer is the second common cancer type in western countries and has a high mortality. During the development and progression of the tumor, the nutrients in its environment play a central role. The tumor cells depend crucially on glucose metabolism and uptake. Tumor cell metabolism is dominated by the Warburg effect, where tumor cells produce large amounts of lactate from pyruvate under aerobic conditions. We thus reasoned that, reducing carbohydrates in the diet might support anti-tumoral effects of current immunotherapy and additionally target tumor immune escape. ObjectivesThe link between reducing carbohydrates to improve current immunotherapy is not clear. We thus aimed at analyzing the effects of different glucose levels on the tumor development, progression and the anti-tumoral immune response. MethodsWe correlated the clinical parameters of our LUAD cohort with different metabolic markers. Additionally, we performed cell culture experiments with A549 tumor cell line under different glucose levels. Lastly, we investigated the effect of low and high carbohydrate diet in an experimental murine model of lung cancer on the tumor progression and different immune subsets. ResultsHere we found a positive correlation between the body mass index (BMI), blood glucose levels, reduced overall survival (OS) and the expression of Insulin-like growth factor-1 receptor (IGF1R) in the lung tumoral region of patients with lung adenocarcinoma (LUAD). Furthermore, increasing extracellular glucose induced IGF1R expression in A549 LUAD cells. Functional studies in a murine model of LUAD demonstrated that, glucose restricted diet resulted in decreased tumor load in vivo. This finding was associated with increased presence of lung infiltrating cytotoxic CD8+ T effector memory (TEM), tissue resident memory T (TRM) and natural killer cells as well as reduced IGFR mRNA expression, suggesting that glucose restriction regulates lung immunity in the tumor microenvironment. ConclusionsThese results indicate that, glucose restricted diet improves lung immune responses of the host and suppresses tumor growth in experimental lung adenocarcinoma. As glucose levels in LUAD patients were negatively correlated to postoperative survival rates, glucose-restricted diet emerges as therapeutic avenue for patients with LUAD.
CRIS-Team WoS Importer:2022-05-27

Gpr126 (Adgrg6) is expressed in cell types known to be exposed to mechanical stimuli - Musa, Gentian; Cazorla-Vázquez, Salvador; van Amerongen, Machteld J.; Stemmler, Marc; Eckstein, Markus; Hartmann, Arndt; Braun, Thomas; Brabletz, Thomas; Engel, Felix (Annals of the New York Academy of Sciences, 2019)
GPR126 (ADGRG6) is an adhesion G protein–coupled receptor that plays an important role in a variety of tissues/organs, such as heart, sciatic nerve, cartilage, and ear. Moreover, GPR126 (ADGRG6) mutations are associated with human diseases, like adolescent idiopathic scoliosis, lung disease, bladder cancer, and intellectual disability. Despite its clinical importance, it remains elusive how GPR126 is activated and mediates signal transduction and what cellular processes depend on GPR126 signaling. Here, we generated a lacZ reporter mouse line to determine endogenous Gpr126 (Adgrg6) expression in a cell type-specific manner during embryonic development, at postnatal day 5 and in adult animals. Our results confirm Gpr126 expression data previously obtained utilizing antibodies and in situ hybridization in embryonic heart and sciatic nerve. In addition, we provide data with cellular resolution for previously described RT-PCR–based data, including lung and bladder. Moreover, new Gpr126-expressing tissues and cell types were identified, such as ureter and acinar secretory cells. Collectively, our data demonstrate that the newly generated lacZ reporter mouse is a suitable model to study Gpr126 expression during development and adulthood, provide detailed insight into Gpr126 expression at the cellular level, and reveal that all identified Gpr126-expressing cells are known to be exposed to mechanical stimuli.
CRIS-Team Scopus Importer:2019-06-28
Keywords: ADGRG6; chondrocytes; endothelium; epithelium

Growth Arrest-Specific 6 in Chromophobe Renal Cell Carcinoma - Mikuteit, Marie; Zschäbitz, Stefanie; Erlmeier, Maximilian; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; Steffens, Sandra; Erlmeier, Franziska (Oncology, 2022)
BACKGROUND: Overexpression of tumor-associated growth arrest-specific protein 6 (Gas6) is found in many tumor entities. The prognostic value of Gas6 in renal cell carcinoma (RCC), especially in non-clear cell RCC, is still unclear. AIM: The aim of the study was to evaluate the prognostic impact of Gas6 expression in a large cohort of patients with chromophobe RCC (chRCC). MATERIAL AND METHODS: Patients who underwent renal surgery due to chRCC were retrospectively evaluated. Tumor specimens were analyzed for Gas6 expression by immunohistochemistry. RESULTS: Eighty-one chRCC patients were eligible for analysis; of these, 24 (29.6%) patients were positive for Gas6. No significant associations were found for Gas6 expression and clinical attributes in patients with chRCC. The Kaplan-Meier analysis revealed no differences in 5-year overall survival for Gas6- compared to Gas6+ (89.6% vs. 100.0%; p = 0.288) tumors. CONCLUSION: In chRCC, Gas6 expression is not associated with survival and other parameters of aggressiveness. Due to the rare incidence of chRCC, further studies with larger cohorts are warranted.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Chromophobe histology; Growth arrest-specific protein 6; Renal cell carcinoma; Survival

Hattori-Zyste – eine seltene Läsion im posterioren Mediastinum - Elsner, Felix; Khamitov, Koblandy; Hinsen, Maximilian; Sirbu, Horia; Hartmann, Arndt (Die Pathologie, 2024)
CRIS-Team Scopus Importer:2024-05-24

Head and neck neoplasms : News from the WHO classification of 2017 - Agaimy, Abbas; Hartmann, Arndt (Pathologe, 2018)
EVALuna2:34261

Healing of the epithelial barrier in the ileum is superior to endoscopic and histologic remission for predicting major adverse outcomes in ulcerative colitis - Rath, Timo; Atreya, Raja; Bodenschatz, Julia; Uter, Wolfgang; Geppert, Carol-Immanuel; Vitali, Francesco; Zundler, Sebastian; Waldner, Maximilian; Hartmann, Arndt; Neurath, Markus (Frontiers in Medicine, 2023)
Background: Achieving endoscopic remission is a key therapeutic goal in patients with ulcerative colitis (UC) that is associated with favorable long-term disease outcomes. Here, we prospectively compared the predictive value of endoscopic and/or histologic remission against ileal barrier healing for predicting long-term disease behavior in a large cohort of UC patients in clinical remission. Methods: At baseline, UC patients in clinical remission underwent ileocolonoscopy with assessment of ileal barrier function by confocal endomicroscopy. Endoscopic and histologic disease activity and ileal barrier healing were scored using validated scores. During subsequent follow-up (FU), patients were closely monitored for clinical disease activity and occurrence of major adverse outcomes (MAO) defined as the following: disease relapse; UC-related hospitalization; UC-related surgery; necessity for initiation or dose escalation of systemic steroids, immunosuppressants, small molecules or biological therapy. Results: Of the 73 UC patients included, 67% experienced MAO during a mean FU of 25 months. The probability of MAO-free survival was significantly higher in UC patients with endoscopic and/or histologic remission compared to patients with endoscopically and/or histologically active disease. Ileal barrier healing on endomicroscopy was highly accurate for predicting the further course of UC and outcompeted endoscopic and histologic remission for predicting MAO-free survival. Conclusion: Ileal barrier healing in clinically remittent UC patients can accurately predict future MAO development and is superior in its predictive capabilities than endoscopic and histologic remission. Ileal barrier healing therefore represents a novel and superior surrogate parameter for stratification of UC patients according to their risk for development of complicated disease behavior. Clinical trial registration: https://classic.clinicaltrials.gov/ct2/show/NCT05157750, identifier NCT05157750.
CRIS-Team Scopus Importer:2023-11-03
Keywords: endoscopy; histology; inflammatory bowel diseases; intestinal barrier; ulcerative colitis

Helicobacter infection and gastric adenoma - Bertz, Simone; Angeloni, Miriam; Drgac, Jan; Falkeis, Christina; Lang-Schwarz, Corinna; Sterlacci, William; Veits, Lothar; Hartmann, Arndt; Vieth, Michael (Microorganisms, 2021)
Background: We aimed to provide insight into the actual frequencies of gastric adenoma types and their association with gastritis status and associated mucosal changes with a focus on Helicobacter infection and the operative link on gastritis assessment (OLGA)/operative link on gastric intestinal metaplasia assessment (OLGIM) staging. Methods: From the archive of the Institute of Pathology in Bayreuth, we collected a consecutive series of 1058 gastric adenomas diagnosed between 1987 and 2017. Clinicopathological parameters retrieved from diagnostic reports included adenoma type and localization, associated mucosal changes in antrum and corpus (i.e., type of gastritis, the extent of intestinal metaplasia and atrophy), gender, date of birth, and date of diagnosis. Results: Intestinal-type adenoma was the most frequent adenoma (89.1%), followed by foveolar-type adenoma (4.3%), pyloric gland adenoma (3.4%), adenomas associated with hereditary tumor syndromes (2.8%), and oxyntic gland adenoma (0.4%). Adenomas were found in the background of Helicobacter pylori (H. pylori) gastritis in 23.9%, Ex-H. pylori gastritis in 36.0%, autoimmune gastritis in 24.8%, chemical reactive gastritis in 7.4%, and others in 0.1%. More than 70% of patients with gastric adenomas had low-risk stages in OLGA and OLGIM. Conclusions: We found a higher frequency of foveolar-type adenoma than anticipated from the literature. It needs to be questioned whether OLGA/OLGIM staging can be applied to all patients.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Autoimmune; Familial adenomatosis coli; Foveolar-type adenoma; Gastric adenoma; Gastritis; Helicobacter; Intestinal tubular adenoma; Oxyntic gland adenoma; Pyloric gland adenoma

Hepatocyte differentiation markers in adenocarcinoma of the prostate: hepatocyte paraffin 1 but not arginase-1 is specifically expressed in a subset of prostatic adenocarcinoma - Giedl, Josef; Buettner-Herold, Maike; Wach, Sven; Wullich, Bernd; Hartmann, Arndt; Agaimy, Abbas (Human Pathology, 2016)
Prostate adenocarcinoma and hepatocellular carcinoma (HCC) are common cancer types. Both may present with bone metastases, and both are known to be CK7/CK20 negative. Thus, diagnosis of less well-differentiated tumors at metastatic sites essentially relies on immunohistochemical confirmation. However, insufficient data exist on the expression status of the main 2 hepatocyte markers hepatocyte paraffin 1 (HepPar-1) and arginase-1 (Arg-1) in prostatic adenocarcinoma. We screened 557 prostate carcinoma cases for expression of these 2 markers using tissue microarrays. Sixty-four of 557 (11.5%) cases showed highly variable expression of HepPar-1 in 1% to 75% of tumor cells with a characteristically strong granular "mitochondrial" pattern. Only 13 cases (2.3%) expressed HepPar-1 in greater than 10% of the tumor cells. No correlation was seen with Gleason grade. On the other hand, 19 (3.4%) of 557 cases showed variable nonspecific cytoplasmic expression of Arg-1 distinct from the specific combined nucleocytoplasmic staining seen in normal liver and in HCC. Specifically, this Arg-1 pattern was seen only using one antibody lot and not another suggesting cross-reactivity. Only a single case showed specific nucleocytoplasmic expression of Arg-1 in the tumor cells. In conclusion, specific granular cytoplasmic staining for HepPar-1 is frequent in prostatic adenocarcinomas (11.5%) but usually focal and limited to less than 5% of tumor cells. This should not be misinterpreted as evidence of HCC, particularly in solid-pattern neoplasms. On the other hand, specific Arg-1 expression is very rare (0.18%), highlighting the value of Arg-1 in distinguishing HepPar-1-positive prostatic carcinoma from HCC at metastatic sites or in cases of liver metastasis from prostate carcinoma.
EVALuna2:6774

HER2 and TOP2A amplification in a hospital-based cohort of breast cancer patients: associations with patient and tumor characteristics - Fasching, Peter A.; Weihbrecht, Sebastian; Haeberle, Lothar; Gasparyan, Armen; Villalobos, Ivonne E.; Ma, Yanling; Ekici, Arif Bülent; Wachter, David; Hartmann, Arndt; Beckmann, Matthias; Slamon, Dennis J.; Press, Michael F. (Breast Cancer Research and Treatment, 2014)
Gene amplification is an important factor for altered gene expression in breast cancers. TOP2A-amplification often occurs concomitantly with HER2 amplification, and it has been suggested to be predictive for the response to anthracycline chemotherapy. This study assessed the correlation between HER2 status and TOP2A co-amplification, the possible association of TOP2A single-nucleotide polymorphisms with the frequency of this co-amplification as well as confirmation of association with outcome. HER2 and TOP2A amplification were analyzed in a tissue microarray from a clinical cohort study. Additionally, a common genetic variant (rs13695) in the TOP2A gene was genotyped in germline DNA. HER2 gene amplification was compared with HER2-IHC findings assessed during clinical routine work, and the association between all the biomarkers analyzed and the clinical outcome was determined. As an exploratory aim, rs13695 genotypes were compared with TOP2A amplification status. HER2 amplification was seen in 101 of 628 (16.1 %) and TOP2A amplification in 32 (5.1 %) cancers. No TOP2A amplification occurred without HER2 co-amplification. HER2 amplification was found in 8, 13.6, and 55.1 % of patients with HER2-IHC 0/1+, 2+, and 3+ tumors, respectively. HER2-IHC was not associated with an effect on the prognosis, but HER2-FISH was. There was an association between the rs13695 genotype and TOP2A amplification status (P = 0.03). Although there was a significant correlation between HER2 status determined by IHC and HER2 by FISH, only HER2 gene amplification status by FISH was correlated with outcome indicating greater utility for FISH in routine clinical settings.
EVALuna2:6613

Hereditary colorectal cancer : An update on genetics and entities in terms of differential diagnosis - Rau, T. T.; Dawson, H.; Hartmann, Arndt; Rueschoff, J. (Pathologe, 2017)
The pathologist can contribute to recognizing hereditary causes of colorectal cancer via morphology. By identifying so-called index patients, it is possible to take preventive measures in affected families. The precise definition of the clinical presentation and the histopathological phenotype help to narrow the spectrum of expected genetic alterations. Novelties within Lynch syndrome include the recognition of EPCAM as a fifth gene locus, as well as the newly defined Lynch-like syndrome with evidence of somatic mismatch repair (MMR) mutations. With regard to polyposis-associated syndromes, the spectrum of polyps, whether serrated, hamartomatous or classic adenoma, is of crucial importance. The resulting differential diagnosis includes (attenuated) familial adenomatous polyposis ([a]FAP), MUTYH-associated polyposis (MAP), polymerase proofreading-associated polyposis (PPAP), phosphatase and tensin homolog (PTEN) hamartoma tumor syndrome (PHTS), Peutz-Jeghers syndrome and juvenile polyposis, each with a specific genetic background.
EVALuna2:6878

Hereditary renal tumors: More common than expected? - Agaimy, Abbas; Hartmann, Arndt (Pathologe, 2016)
Renal cell carcinomas are associated with hereditary tumor syndromes in approximately 5 % of cases. In patients with a hereditary predisposition, tumors show an earlier age of onset, often with a multicentric and bilateral manifestation. While some patients with renal cell carcinoma can be classified into well-characterized kidney cancer syndromes others have a genetic background which is still poorly understood. Most of the specific tumor syndromes are associated with a histopathologically distinct renal cell tumor phenotype. The recognition of patients with hereditary renal cell carcinoma and the identification of individual family members with a higher risk of development of renal tumors is important for early tumor detection and treatment. This manuscript reviews the clinical pathological and molecular findings of hereditary renal cell carcinoma syndromes.
EVALuna2:6783

Heterogeneity-analysis of molecular subtypes of muscle-invasive bladder cancer and their precursor lesions in multiregion mapped whole-organ bladders - Weyerer, Veronika; Lange, Fabienne; Wullweber, Adrian; Stöhr, Robert; Bertz, Simone; Wach, S.; Taubert, Helge; Wullich, Bernd; Sikic, Danijel; Strissel, Pamela; Strick, Reiner; Hartmann, Arndt; et al. (UROLOGIC ONCOLOGY-SEMINARS AND ORIGINAL INVESTIGATIONS, 2020)
CRIS-Team WoS Importer:2021-01-15

High androgen receptor mrna expression is associated with improved outcome in patients with high-risk non-muscle-invasive bladder cancer - Sikic, Danijel; Taubert, Helge; Wirtz, Ralph M.; Breyer, Johannes; Eckstein, Markus; Weyerer, Veronika; Kubon, Jennifer; Erben, Philipp; Bolenz, Christian; Burger, Maximilian; Hartmann, Arndt; Wullich, Bernd; et al. (Life, 2021)
The role of the androgen receptor (AR) in non-muscle-invasive bladder cancer (NMIBC) remains controversial. We retrospectively analyzed the mRNA expression of AR using RT-qPCR in 95 patients with high-risk NMIBC treated with a bladder-sparing approach and correlated AR with clinical data and recurrence-free survival (RFS), cancer-specific survival (CSS), and overall survival (OS). The mRNA expression of AR and KRT5, i.e., the basal-like subtype, was strongly correlated (rs = 0.456; p < 0.001). AR (p = 0.053) and KRT5 (p = 0.029) mRNA expression was negatively correlated with tumor grade. Kaplan–Meier analyses indicated significantly prolonged CSS (p = 0.020) and OS (p = 0.015) and a trend towards longer RFS (p = 0.051) in patients with high AR expression. High KRT5 expression was associated with significantly longer RFS (p = 0.033), CSS (p = 0.029) and OS (p = 0.030), while high KRT20 expression was associated with reduced RFS (p = 0.042). In multivariable analysis, none of the molecular markers was an independent prognostic factor. When performing a substratification with regard to molecular markers and clinicopathological parameters, high AR expression showed improved OS in patients with high KRT20 mRNA expression (p = 0.041). Women showed significantly longer OS in cases with high AR expression (p = 0.011). High AR was associated with significantly improved CSS in males (p = 0.044) and patients with instillation therapy (p = 0.040), while OS was improved regardless of instillation therapy. Younger patients with high AR expression had significantly improved RFS (p = 0.021), CSS (p = 0.014) and OS (p = 0.007). RFS was also improved in patients with high AR and low expression of either KRT5 (p = 0.003) or KRT20 (p = 0.014), but not in patients with high expression of KRT5 or KRT20. In conclusion, high AR mRNA expression is correlated with KRT5 mRNA expression and is associated with an improved outcome in high-risk NMIBC.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Androgen receptor; Bladder cancer; KRT20; KRT5; MRNA; NMIBC; PCR

High Androgen Receptor mRNA Expression Is Independently Associated with Prolonged Cancer-Specific and Recurrence-Free Survival in Stage T1 Bladder Cancer - Sikic, Danijel; Breyer, Johannes; Hartmann, Arndt; Burger, Maximilian; Erben, Philipp; Denzinger, Stefan; Eckstein, Markus; Stohr, Robert; Wach, Sven; Wullich, Bernd; Keck, Bastian; Wirtz, Ralph M.; et al. (Translational Oncology, 2017)
High-risk non-muscle-invasive bladder cancer (NMIBC) remains challenging given the high probability of progression. Given that the androgen receptor (AR) has been discussed as a possible factor in the development and progression of bladder cancer, we investigated the predictive value of AR in stage pT1 NMIBC.We retrospectively analyzed the clinical data and AR mRNA expression in 296 patients with stage pT1 NMIBC who underwent a transurethral resection of the bladder. The mRNA expression of the AR transcript variants 1 (AR1) and 2 (AR2) was measured by reverse transcription quantitative real-time polymerase chain reaction. AR expression was also correlated to KRT5 and KRT20 mRNA expression.Kaplan-Meier analysis indicated that high AR1 mRNA expression >=35.47 is associated with statistically significant better recurrence-free survival (RFS) (P=.0007), progression-free survival (PFS) (P=.0420), and cancer-specific survival (CSS) (P=.0050). Multivariate Cox regression analysis revealed that high AR1 mRNA expression is an independent prognostic marker for RFS (P=.0029) and CSS (P=.0119). Spearman rank correlation revealed a significant positive association between mRNA expression of AR1 and KRT5 (rs: 0.3171, P<.0001) as well as a negative association with multifocal tumors (rs: 0.1478, P<.0109). No association was noted between AR1 expression and tumor grade, concomitant CIS, gender, tumor size, and KRT20 in patients with stage T1 NMIBC.AR mRNA expression can predict RFS and CSS in patients with stage T1 NMIBC. Further studies are necessary to refine the relevance of AR mRNA expression compared with immunohistochemically detectable AR expression.
EVALuna2:6884

High CDKN2A/p16 and Low FGFR3 Expression Predict Progressive Potential of Stage pT1 Urothelial Bladder Carcinoma - Breyer, Johannes; Wirtz, Ralph M.; Erben, Philipp; Worst, Thomas S.; Stoehr, Robert; Eckstein, Markus; Bertz, Simone; Sikic, Danijel; Denzinger, Stefan; Burger, Maximilian; Hartmann, Arndt; Otto, Wolfgang (Clinical Genitourinary Cancer, 2018)
BACKGROUND: A recent study on the comprehensive genomic profile of advanced urothelial bladder cancer (UBC) showed cyclin-dependent kinase inhibitor 2A (CDKN2A) and fibroblast growth factor receptor 3 (FGFR3) as the most often clinically relevant genomic alterations. Therefore, the prognostic role of FGFR3 and CDKN2A/p16 for pT1 UBC was studied. PATIENTS AND METHODS: Clinical data and formalin-fixed paraffin-embedded tissues of pT1 UBC treated with an organ-preserving approach was analyzed retrospectively. Total RNA was isolated using commercial RNA extraction kits and mRNA expression of CDKN2A/p16 and FGFR3 was measured using single step reverse transcription quantitative real time polymerase chain reaction using RNA-specific TaqMan assays. RESULTS: Data from 296 patients (79.4% male; median age: 72 years) could be used for the final evaluation. Spearman correlation revealed a statistically significant negative correlation between mRNA expression of CDKN2A/p16 and FGFR3. There was a positive correlation between CDKN2A/p16 and G3 tumors (ρ = 0.1875; P = .0012) and associated carcinoma in situ (ρ = 0.1703, P = .0033) and a negative correlation between FGFR3 and these factors (ρ = -0.2791, P < .0001 and ρ = -0.2182, P = .0002). High CDKN2A/p16 expression (≥38.04) and low FGFR3 expression (<39.14) were statistically significantly associated with worse progression-free survival (PFS; P = .0194 and P = .0089). Multivariate Cox regression analysis could identify patients with low FGFR3 and high CDKN2A/p16 expression (log rank (LR) χ2 = 10.69; P = .0048) as well as tumor size ≥3 cm (LR χ2 = 6.03; P = .0141) as independent predictors for PFS. CONCLUSION: High expression of CDKN2A/p16 and low expression of FGFR3 show a correlation with established prognostic features for non-muscle-invasive bladder cancer and can predict progression of stage pT1 UBC.
EVALuna2:33956

High expression of ERBB2 is an independent risk factor for reduced recurrence-free survival in patients with stage T1 non-muscle-invasive bladder cancer - Sikic, Danijel; Eckstein, Markus; Weyerer, Veronika; Kubon, Jennifer; Breyer, Johannes; Roghmann, Florian; Kunath, Frank; Keck, Bastian; Erben, Philipp; Hartmann, Arndt; Wirtz, Ralph M.; Wullich, Bernd; et al. (Urologic Oncology-Seminars and Original Investigations, 2021)
Introduction: Molecular markers associated with breast cancer are assumed to be associated with outcome in non-muscle-invasive bladder cancer (NMIBC). Materials and methods: We retrospectively investigated the association of the mRNA expression of estrogen receptor 1 (ESR1) and 2 (ESR2), progesterone receptor (PGR), MKI67, and HER2 (ERBB2) with recurrence-free (RFS), cancer-specific (CSS), and overall survival (OS) in 80 patients with stage T1 NMIBC. Results: High expression of ESR2 (P = 0.003), ERBB2 (P < 0.001), and MKI67 (P = 0.029) was associated with shorter RFS. Only high ERBB2 was an independent prognostic factor for reduced RFS (HR = 2.98; P = 0.009). When sub stratifying the cohort, high ESR2 was associated with reduced RFS (P < 0.001), CSS (P = 0.037) and OS (P = 0.006) in patients without instillation therapy. High ESR2 was associated with reduced CSS (P = 0.018) and OS (P = 0.029) in females and with shorter RFS in both sexes (males: P = 0.035; females: P = 0.010). Patients with high ERBB2 showed reduced CSS (P = 0.011) and OS (P = 0.042) in females and reduced CSS (P = 0.012) in those without instillation, while RFS was significantly reduced irrespective of sex or instillation. Conclusion: High mRNA expression of ERBB2 is an independent predictor of reduced RFS in patients with stage T1 NMIBC. High ERBB2 and ESR2 are associated with reduced outcomes, especially in females and patients without instillation therapy.
CRIS-Team Scopus Importer:2021-08-06
Keywords: ERBB2; Estrogen receptor; HER2; Non-muscle-invasive bladder cancer; Urothelial carcinoma

High PDL1 mRNA expression predicts better survival of stage pT1 non-muscle-invasive bladder cancer (NMIBC) patients - Breyer, Johannes; Wirtz, Ralph M.; Otto, Wolfgang; Erben, Philipp; Worst, Thomas S.; Stoehr, Robert; Eckstein, Markus; Denzinger, Stefan; Burger, Maximilian; Hartmann, Arndt (Cancer Immunology, Immunotherapy, 2018)
INTRODUCTION AND OBJECTIVES: Checkpoint inhibition has emerged as new therapeutic option in muscle-invasive bladder cancer. The objective of the present study was to evaluate the prognostic role of PD1 and PDL1 expression in non-muscle-invasive bladder cancer (NMIBC) and establish an objective measuring method using RNA quantification. MATERIALS AND METHODS: We retrospectively analyzed clinical data and formalin-fixed paraffin-embedded tissues (FFPE) of patients with stage pT1 NMIBC who underwent transurethral resection of the bladder. mRNA expression of PD1, PDL1 and CD3 was measured by single step RT-qPCR and correlated to clinicopathological parameters, recurrence-free survival (RFS), progression-free survival (PFS) and carcinoma-specific survival (CSS). RESULTS: We have analyzed 334 patients with NMIBC at stage pT1 for mRNA analysis. Data from 296 patients (79% male, median age: 72 years) could be used. Spearman correlation revealed significant associations between mRNA expressions of PD1/PDL1 (ρ: 0.6024, p < 0.0001), CD3/PDL1 (ρ: 0.5728, p < 0.0001) and CD3/PD1 (ρ: 0.7005, p < 0.0001). Kaplan-Meier analysis revealed that high PDL1 mRNA expression (≥ 33.83) is a favorable prognostic factor with regard to better RFS (p = 0.0018), PFS (p = 0.021) and CSS (p = 0.012). Multivariate Cox-regression analysis proved PDL1 expression to be an independent prognosticator for RFS [HR 0.48 (0.31-0.72), p = 0.0005], PFS [HR 0.45 (0.24-0.80), p = 0.0059] and CSS [HR 0.31 (0.13-0.67), p = 0.0021]. CONCLUSION: High mRNA expression of PDL1 predicts improved RFS, PFS and CSS of pT1 NMIBC. Following prospective validation, this objective measurement of PD-L1 might help stratify patients with NMIBC for immunotherapy and identify patients who might benefit from early cystectomy.
EVALuna:33789

High proliferation rate and TNM stage but not histomorphological subtype are independent prognostic markers for overall survival in papillary renal cell carcinoma - Polifka, Iris; Agaimy, Abbas; Herrmann, Edwin; Spath, Verena; Trojan, Lutz; Stoeckle, Michael; Becker, Frank; Stroebel, Philipp; Muelfing, Christian; Schrader, Andres J.; Barth, Peter; Staehler, Michael; et al. (Human Pathology, 2019)
Papillary renal cell carcinoma (PRCC) is currently divided in 2 subtypes. We reviewed a large cohort of PRCC and correlated subtype, morphological features and diagnostic marker expression with overall survival (OS) to uncover differences between the 2 subtypes. Three hundred seventy-six renal tumors initially diagnosed as PRCC with clinical and survival data were collected from the participating centers. Two hundred forty-six tumors were classified as PRCC1 (65.4%) and 130 as PRCC2 (34.6%) and graded according to the 2016 World Health Organization/Intemational Society of Urological Pathology grading system. Morphological features (abundant cytoplasm, necrosis, fibrous stroma, foamy macrophages and psammoma bodies) were noted. Immunohistochemical stains (MIB1, p53, Racemase, EMA, CK7, CK20, E-Cadherin) were performed using tissue microarrays. chi(2)-Tests, log-rank tests and uni- and multivariate Cox regression analysis were performed. Both subtypes displayed different morphological features and immunohistochemical profiles: abundant cytoplasm was more frequent in PRCC2, while foamy macrophages were more common in PRCC1. Abundant cytoplasm and presence of psammoma bodies were associated with poorer OS. PRCC1 showed more frequent CK7 expression, PRCC2 more frequent E-Cadherin, p53 and higher MIB1 expression (>15%). Expression of Racemase and CK7 was associated with better OS, while high MIB1 (>15%) was associated with poorer OS. In multivariate analysis, the only independent predictors of OS were proliferation (MIB1), tumor stage, metastasis and age at surgery. Subtype was not an independent prognostic factor. Therefore, PRCC subtype on its own is not suitable for estimating survival. More data focusing on PRCC tumor biology is needed to define prognostic subgroups, especially in PRCC2. (C) 2018 Elsevier Inc. All rights reserved.
CRIS-Team WoS Importer:2019-03-06

High stroma T-cell infiltration is associated with better survival in stage pT1 bladder cancer - Hülsen, Sabine; Lippolis, Eleonora; Ferrazzi, Fulvia; Otto, Wolfgang; Distel, Luitpold; Fietkau, Rainer; Denzinger, Stefan; Breyer, Johannes; Burger, Maximilian; Bertz, Simone; Eckstein, Markus; Ebner, Annette; et al. (International Journal of Molecular Sciences, 2020)
Stage pT1 bladder cancer (BC) shows highly diverse outcomes. Predictive markers are required to stratify patients for personalized treatment. The present study aimed to validate immune response quantification as a prognostic marker. Patients with pT1 BC (n = 167) treated by transurethral resection of the bladder (TURB) were enrolled. Formaldehyde-fixed paraffin-embedded material was stained for CD3 and CD8. Corresponding T cells were counted in three regions with the highest immune response. Numbers of tertiary lymphoid structures (TLS) and lymphocyte aggregates (LA) were quantified. High CD3+ stroma T-cell infiltration was associated with improved survival (p = 0.045), especially in the G3 subgroup (p = 0.01). Cluster with higher immune response showed less recurrence (p = 0.034) and favorable overall survival (OS) (p = 0.019). In contrast, higher CD3+ and CD8+ tumor T-cell infiltration seemed to have a negative impact on prognosis. TLS and LA were more frequently observed in G3 tumors, indicating an increased antitumoral immune response. We proved the role of immune cell infiltration and showed that higher infiltration numbers of CD3+ (not CD8+) lymphocytes in the stroma are associated with favorable outcome. Immune cell quantification could be used as a marker to help stratify patients’ risk and therefore, to optimize patients’ management and follow-up examination as well as possible therapies.
CRIS-Team Scopus Importer:2020-11-20
Keywords: CD8; Immunoscore; Progression; PT1 bladder cancer; Survival; Tumor-infiltrating lymphocytes (TILs); CD3

Histologische Subtypen des Nierenzellkarzinoms: Übersicht und neue Entwicklungen - Polifka, Iris; Agaimy, Abbas; Moch, H.; Hartmann, Arndt (Pathologe, 2021)
Background: The classification of renal cell carcinoma (RCC) has changed remarkably in recent years. Objectives: This is a short overview of the classification of RCC, focusing on new developments. Materials and Methods: A literature search was performed resulting in an overview of the classification of RCC. Emerging entities were discussed in detail. Results: Apart from the RCC subtypes in the WHO classification of 2016, several emerging entities came up over the last few years that are characterized by typical morphology, immunophenotype, and especially specific genetic alterations. Conclusion: Precise classification of RCC is the key to better prognostic assessment with potential tumor-specific therapy and plays an important role in the recognition of possible association with hereditary tumor syndromes.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Fumarate hydratase; Genetic predisposition to disease; Immunophenotyping; Prognosis; Succinatdehydrogenase B (SDHB)

Histology of Luminal Breast Cancer - Erber, Ramona; Hartmann, Arndt (Breast Care, 2020)
Background: Invasive breast cancer (IBC) can be categorized into prognostic and predictive molecular subtypes (including luminal breast cancer) using gene expression profiling. Luminal IBC comprises a variety of histological subtypes with varying clinical and pathological features. Summary: IBC of no special subtype is the most common histological subtype in general and likewise within luminal IBC. Classical invasive lobular breast cancer, typically clustering into luminal subgroup, is characterized by discohesive growth and loss of E-cadherin expression. Infrequent, morphologically distinct luminal IBC subtypes are tubular, invasive cribriform, mucinous, and invasive micropapillary carcinomas. Breast carcinoma with apocrine differentiation, with characteristic expression of androgen receptor (AR), often clusters into the luminal AR category. Rarely, neuroendocrine neoplasms of the breast can be seen. IBC of the male breast usually matches with the luminal subtype. Key Messages: Independently from histological subtypes, invasive breast cancer (IBC) can be divided into molecular subtypes based on mRNA gene expression levels. Using this molecular subtyping, risk scores based on gene expression profiling (established for hormone receptor-positive, HER2-negative IBC), grading, and Ki-67 index, prognosis of patients with luminal breast cancer and response to chemotherapy can be predicted. In routine diagnostics, the expression of estrogen receptor (ER) and progesterone receptor (PR), HER2 status, and the proliferation rate (Ki-67) are used to determine a surrogate (molecular-like) subtype. Within luminal(-like) IBC, no special subtype and invasive lobular breast carcinoma are the most common histological subtypes. Other rare histological subtypes (e.g., tubular carcinoma) should be recognized due to their distinct clinical and pathological features.
CRIS-Team Scopus Importer:2020-07-31

HLA-E expression and its clinical relevance in human renal cell carcinoma - Seliger, Barbara; Jasinski-Bergner, Simon; Quandt, Dagmar; Stoehr, Christine; Bukur, Juergen; Wach, Sven; Legal, Wolfgang; Taubert, Helge; Wullich, Bernd; Hartmann, Arndt (Oncotarget, 2016)
The non-classical human leukocyte antigen E (HLA-E) expression is frequently overexpressed in tumor diseases, transplants and virus-infected cells and represents an immunomodulatory molecule by binding to the receptors CD94/NKG2A, -B and -C on NK and T cells. Due to its immune suppressive features HLA-E expression might represent an important mechanism of tumors to escape immune surveillance. While an aberrant expression of the non-classical HLA-G antigen in human renal cell carcinoma (RCC) has been demonstrated to be associated with a worse outcome of patients and reduced sensitivity to immune effector cell-mediated cytotoxicity, the expression and function of HLA-E has not yet been analyzed in this tumor entity. Higher levels of HLA-E transcripts were detected in all RCC cell lines and tumor lesions, which were tested in comparison to normal kidney epithelium. Immunohistochemical staining of a tissue microarray (TMA) using the HLA-E-specific monoclonal antibody TFL-033 recognizing the cytoplasmic HLA-E ?-chain as monomer revealed a heterogeneous HLA-E expression in RCC lesions with the highest frequency in chromophobe RCC when compared to other RCC subtypes. HLA-E expression did not correlate with the frequency of CD3+, CD4+, CD8+ and FoxP3+ immune cell infiltrations, but showed an inverse correlation with infiltrating CD56+ cells. In contrast to HLA-G, HLA-E expression in RCCs was not statistically significant associated with a decreased disease specific survival. These data suggest that HLA-E overexpression frequently occurs in RCC and correlates with reduced immunogenicity.
EVALuna2:6816

HLA-G and HLA-F protein isoform expression in breast cancer patients receiving neoadjuvant treatment - Würfel, Franziska; Hübner, Hanna; Häberle, Lothar; Gaß, Paul; Hein, Alexander; Jud, Sebastian; Hack, Carolin; Wunderle, Marius; Schulz-Wendtland, Rüdiger; Erber, Ramona; Hartmann, Arndt; Ekici, Arif Bülent; et al. (Scientific Reports, 2020)
The immunosuppressive human leukocyte antigens HLA-G and HLA-F are expressed on trophoblast and malignant cells. Four membrane-bound and three soluble HLA-G protein isoforms have been described, which have different immunosuppressive potentials. HLA-F has three transcript variants, resulting in three different protein isoforms. The aim of this study was to evaluate the prognostic and predictive value of HLA-G and HLA-F protein isoform expression patterns in patients with breast cancer. Core biopsies were taken at diagnosis in patients with HER2+ (n = 28), luminal B-like (n = 49) and triple-negative (n = 38) breast cancers who received neoadjuvant chemotherapy. Expression levels of HLA-F and -G were correlated with the pathological complete response (pCR). Protein expression was determined by Western blot analysis, using two antibodies for each HLA, specific for different isoforms. The protein expression of HLA isoforms did not significantly differ between breast cancer subtypes. However, some initial indications were found for an association between the soluble HLA-G6 protein isoform and pCR in HER2+ breast cancer. The study provides preliminary evidence for the evaluation of HLA-G isoform expression, in particular HLA-G6, as a possible new marker for pCR in HER2+ breast cancer.
CRIS-Team Scopus Importer:2020-10-02

HMGA2-WIF1 Rearrangements Characterize a Distinctive Subset of Salivary Pleomorphic Adenomas With Prominent Trabecular (Canalicular Adenoma-like) Morphology - Agaimy, Abbas; Ihrler, Stephan; Baneckova, Martina; Martineau, Valerie Costes; Mantsopoulos, Konstantinos; Hartmann, Arndt; Iro, Heinrich; Stöhr, Robert; Skalova, Alena (American Journal of Surgical Pathology, 2022)
Most of salivary gland neoplasms (benign and malignant) are characterized by recurrent gene fusions. Pleomorphic adenoma (PA), the most frequent salivary gland tumor, is driven by chromosomal rearrangements involving PLAG1 mapped to 8q12 and HMGA2 mapped to 12q13-15 in most cases. Multiple fusion partners have been identified including CTNNB1, FGFR1, LIFR, CHCHD7 and TCEA for PLAG1 fusions and NFIB, WIF1 and FHIT for HMGA2 fusions. To date, no data exist on the morphology of the few reported HMGA2-WIF1-rearranged PAs. We present 28 major salivary gland adenomas displaying distinctive trabecular and canalicular morphology associated with recurrent genotype. Patients were 15 females and 13 males aged 43 to 87 (median: 65). All tumors originated from the parotid. Their size range was 1 to 4 cm (mean: 2.3). Histologically, all tumors showed elongated or columnar cells arranged into bilayered to multilayered communicating and branching strands and trabeculae in a manner similar to canalicular adenoma of minor salivary glands or trabecular myoepithelioma with variable solid confluent intercalated duct-like areas. Fifteen tumors were exclusively canalicular/trabecular while 13 had intermingled or well-demarcated conventional (chondromyxoid) PA component comprising 5 to >50% of the tumor. The monomorphic areas expressed uniformly CK7 (28/28), vimentin (21/21), S100 (24/24), SOX10 (16/17) and variably p63 (8/21) and mammaglobin (6/16) but were negative with p40 (0/24), smooth muscle actin (0/24) and MUC4 (0/16). Targeted RNA sequencing revealed HMGA2 fusions in 14/16 (87%) assessable cases. Fusion partner was WIF1 (12), RPSAP52 (1) and HELB (1). Separate testing of the 2 components in 1 hybrid tumor showed same HMGA2/WIF1 fusion. HMGA2 immunohistochemistry was homogeneously positive in all cases including the 2 fusion-negative cases. A control cohort of 12 genuine canalicular adenomas revealed no HMGA2 fusions (0/4) and lacked HMGA2 immunoreactivity (0/12). This study highlights a distinctive variant in the spectrum of PA characterized by prominent trabecular and canalicular adenoma-like morphology. Our data confirm that canalicular adenomas in major salivary glands (either monomorphic or part of hybrid tumors) are distinct from canalicular adenoma of minor salivary glands. Their uniform genotype irrespective of presence or absence of a conventional PA component argues for classifying those tumors lacking a conventional PA component as "monomorphic variants of PA" rather than canalicular/basal cell adenomas, intercalated duct adenoma, trabecular myoepithelioma or true hybrid tumors.
CRIS-Team WoS Importer:2022-01-21

Homozygous G/G variant of SNP309 in the human MDM2 gene is associated with earlier tumor onset in Caucasian female renal cell carcinoma patients - Stoehr, Christine; Stoehr, R.; Wenners, A.; Hartmann, Arndt; Bertz, Simone; Spath, V.; Walter, B.; Junker, K.; Moch, H.; Hinze, R.; Denzinger, S.; Bond, E. E.; et al. (Oncogenesis, 2016)
Human mouse double minute 2 (Mdm2) plays an essential role in the regulation of the tumor suppressor p53. The G/G variant of SNP309 was shown to increase Mdm2 mRNA/protein expression and to be associated with an increased risk and earlier onset of different cancers in Asian populations. However, the frequency and impact of these G/G variants have not been studied in Caucasian renal cell carcinoma (RCC) patients. Therefore, we analyzed an unselected German cohort of 197 consecutive RCC patients and detected the G/G variant in 18 (9.1%) patients, the G/T variant in 116 (58.9%) patients and the T/T variant in 63 (32.0%) patients. Studying the association between age at tumor onset and SNP309 genotypes, no correlation was detected in the entire RCC cohort or among the male RCC patients. However, the female G/G patients (median age 59.5 years) were diagnosed 13.5 years earlier than the T/T females (median age 73 years). When separating all females into two groups at their median age (68 years), 7 and 1 patients with the G/G variant and 9 and 13 patients with the T/T variant were noted in these age groups (P=0.024). To study the age dependency of tumor onset further, a second, age-selected cohort of 205 RCC patients was investigated, which comprised especially young and old patients. Interestingly, the G/G type occurred more often at lower tumor stages and tumor grades compared with higher stages (P=0.039 and 0.004, respectively). In females, the percentage of the G/G variant was only slightly higher in the younger age group, whereas in males, the percentage of the G/G variant was remarkably higher in the younger age group (19.4% vs 8.0%). In summary, female Caucasian RCC patients with the MDM2 SNP309 G/G genotype showed significantly earlier tumor onset than patients with the wild-type T/T genotype.
EVALuna2:6760

Hormone replacement therapy and prognosis in ovarian cancer patients - Hein, Alexander; Thiel, Falk; Bayer, Christian M.; Fasching, Peter; Häberle, Lothar; Lux, Michael P.; Renner, Stefan; Jud, Sebastian; Schrauder, Michael G.; Müller, Andreas; Wachter, David; Strehl, Johanna; et al. (European Journal of Cancer Prevention, 2013)
Estrogen exposure has at least a moderate effect on the risk for ovarian cancer, and antiestrogen therapy may be helpful in treating the disease. It is known from breast cancer that previous hormone replacement therapy (HRT) may influence the molecular profile and prognostic behavior of these tumors. The aim of this study was therefore to investigate the influence of previous HRT on the prognosis in a cohort of patients with invasive epithelial ovarian cancer. Among 547 patients who were treated for ovarian malignancies at a single institution from 1995 to 2008, a total of 244 postmenopausal patients with epithelial cancer and under the age of 75 were identified for whom information about HRT before the onset of the disease was available. HRT was correlated with tumor and patient characteristics. Analyses of overall survival and progression-free survival were carried out using Cox proportional hazards models. Age, tumor stage, and resection status correlated significantly with HRT in the univariate analysis. Patients with previous HRT were more likely to have a lower stage, to be younger, and to have optimal debulking. With regard to survival, HRT had a positive effect on overall survival, specifically in the subgroup of patients with optimal debulking. No correlation was seen in relation to progression-free survival. Sex hormone exposure through HRT may influence the behavior of ovarian cancers after the onset of the disease. This study supports the hypothesis that ovarian cancer is a hormonally influenced tumor. © 2012 Lippincott Williams & Wilkins.
CRIS-Team Scopus Importer:2021-07-19
Keywords: estrogen; hormone replacement therapy; ovarian cancer; pathogenesis; prognosis

Hormone Therapy and its Effect on the Prognosis in Breast Cancer Patients - Rauh, C.; Schuetz, F.; Rack, B.; Stickeler, E.; Klar, M.; Orlowska-Volk, M.; Windfuhr-Blum, M.; Heil, J.; Rom, J.; Sohn, C.; Andergassen, U.; Jueckstock, J.; et al. (Geburtshilfe und Frauenheilkunde, 2015)
Introduction: Use of hormone therapy (HT) has declined dramatically in recent years. Some studies have reported that HT use before a diagnosis of breast cancer (BC) may be a prognostic factor in postmenopausal patients. This study aimed to examine the prognostic relevance of HT use before BC diagnosis. Methods: Four BC cohort studies in Germany were pooled, and 4492 postmenopausal patients with HT use data were identified. Patient data and tumor characteristics were compared between users and nonusers, along with overall survival (OS), distant metastasis-free survival (DMFS), and local recurrence-free survival (LRFS). Cox proportional hazards models were stratified by study center and adjusted for age at diagnosis, tumor stage, grading, nodal status, and hormone receptors. Results: Women with HT use before the diagnosis of BC were more likely to have a lower tumor stage, to be estrogen receptor-negative, and to have a lower grading. With regard to prognosis there were effects seen for OS, DMFS and LRFS, specifically in the subgroup of women with a positive hormone receptor. In these subgroups, BC patients had a better prognosis with previous HT use. Conclusions: HT use before a diagnosis of BC is associated with a more favorable prognosis in women with a positive hormone receptor status. It may be recommended that the prognostic factor HT should be documented and analyzed as a confounder for prognosis in studies of postmenopausal hormone-responsive breast cancers.
EVALuna2:6745

HPV16-L1-specific antibody response is associated with clinical remission of high-risk HPV-positive early dysplastic lesions - Mehlhorn, Grit; Hautmann, Simone K.; Koch, Martin; Strehl, Johanna D.; Hartmann, Arndt; Hilfrich, Ralf; Beckmann, Matthias; Griesser, Henrik (Anticancer Research, 2014)
The present study was aimed at clarifying if use of a rapid human papillomavirus type 16 L1-specific antibody test could be used to improve clinical management of high-risk HPV-positive low-grade squamous intraepithelial lesion (LSIL)/high-grade squamous intraepithelial lesion (HSIL).The study was nested within a prospective study of 801 patients with early dysplastic high-risk HPV-positive lesions to examine the prognostic significance of HPV-L1 protein detection. Serum samples of 87 patients were tested with a rapid HPV16-L1-specific antibody test. The results were correlated with the clinical outcome during 66 months of follow-up.A combined analysis of the 22 antibody-positive women showed that 17 were also L1 protein-positive, and 5 were L1 capsid protein-negative. An HPV-specific immune competence strongly correlates with clinical remission of low-grade squamous intraepithelial lesion (76.6%). For L1 antigen and HPV16-L1 antibody double-positive women, the risk of progression to cervical intraepithelial neoplasia grade 3 was low (5.8%).The rapid anti-HPV16-L1 test could be a promising tool to improve risk assessment and appropriate clinical management of high-risk HPV-positive early dysplastic lesions.
EVALuna2:6623

Human CD22-transgenic, primary murine lymphoma challenges immunotherapies in organ-specific tumor microenvironments - Gsottberger, Franziska; Brandl, Carolin; Wendland, Kerstin; Petkovic, Srdjan; Emmerich, Charlotte; Erber, Ramona; Geppert, Carol-Immanuel; Hartmann, Arndt; Mackensen, Andreas; Nitschke, Lars; Müller, Fabian (International Journal of Molecular Sciences, 2021)
Targeted immunotherapies have greatly changed treatment of patients with B cell malignancies. To further enhance immunotherapies, research increasingly focuses on the tumor microenvironment (TME), which differs considerably by organ site. However, immunocompetent mouse models of disease to study immunotherapies targeting human molecules within organ-specific TME are surprisingly rare. We developed a myc-driven, primary murine lymphoma model expressing a human-mouse chimeric CD22 (h/mCD22). Stable engraftment of three distinct h/mCD22+ lymphoma was established after subcutaneous and systemic injection. However, only systemic lymphoma showed immune infiltration that reflected human disease. In this model, myeloid cells supported lymphoma growth and showed a phenotype of myeloid-derived suppressor cells. The human CD22-targeted immunotoxin Moxetumomab was highly active against h/mCD22+ lymphoma and similarly reduced infiltration of bone marrow and spleen of all three models up to 90-fold while efficacy against lymphoma in lymph nodes varied substantially, highlighting relevance of organ-specific TME. As in human aggressive lymphoma, anti-PD-L1 as monotherapy was not efficient. However, anti-PD-L1 enhanced efficacy of Moxetumomab suggesting potential for future clinical application. The novel model system of h/mCD22+ lymphoma provides a unique platform to test targeted immunotherapies and may be amenable for other human B cell targets such as CD19 and CD20.
CRIS-Team Scopus Importer:2021-10-08
Keywords: CD22; Checkpoint molecule; Immunotoxin; Lymphoma microenvironment; MDSCs; Mouse model; Myc-driven lymphoma; Myeloid derived suppressor cells; PD-L1; Tumor microenvironment

Human lymphoid organ dendritic cell identity is predominantly dictated by ontogeny, not tissue microenvironment - Heidkamp, Gordon Frederik; Sander, Jil; Lehmann, Christian; Heger, Lukas; Eissing, Nathalie; Baranska, Anna; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Lux, Anja; Söder, Stephan; Hartmann, Arndt; et al. (Science immunology, 2016)
In mice, conventional and plasmacytoid dendritic cells (DCs) derive from separate hematopoietic precursors before they migrate to peripheral tissues. Moreover, two classes of conventional DCs (cDC1 and cDC2 DCs) and one class of plasmacytoid DCs (pDCs) have been shown to be transcriptionally and functionally distinct entities. In humans, these three DC subtypes can be identified using the cell surface markers CD1c (cDC2), CD141 (cDC1), and CD303 (pDCs), albeit it remains elusive whether DC functionality is mainly determined by ontogeny or the tissue microenvironment. By phenotypic and transcriptional profiling of these three DC subtypes in different human tissues derived from a large number of human individuals, we demonstrate that DC subpopulations in organs of the lymphohematopoietic system (spleen, thymus, and blood) are strongly defined by ontogeny rather than by signals from the microenvironment. In contrast, DC subsets derived from human lung or skin differed substantially, strongly arguing that DCs react toward modulatory signals from tissue microenvironments. Collectively, the data obtained in this study may serve as a major resource to guide further studies into human DC biology during homeostasis and inflammatio
EVALuna2:6852

Human lymphoid organ dendritic cell identity is predominantly dictated by ontogeny, not tissue microenvironment - Heidkamp, Gordon Frederik; Sander, J.; Lehmann, C. H. K.; Heger, Lukas; Eissing, N.; Baranska, A.; Lühr, Jennifer; Hoffmann, Alana; Reimer, Katharina; Lux, Anja; Söder, Stephan; Hartmann, Arndt; et al. (2017)
EVALuna2:33137

Human papilloma virus genotype distribution in women with premalignant or malignant lesions of the uterine cervix - Stübs, Frederik; Gaß, Paul; Dietl, Anna; Schulmeyer, Carla; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Koch, Martin (Archives of Gynecology and Obstetrics, 2021)
Objective: Cervical cancer is caused by persistent infection with high-risk human papillomavirus (hrHPV). Cytology-based national screening programs have reduced the incidence and mortality of cervical cancer. Different hrHPV subtypes have different carcinogenic potentials. This study evaluated the distribution of different types of hrHPV relative to age in cervical cancer and its precursor lesions. Methods: HPV testing was performed between November 2018 and February 2020 using the Abbott RealTime high-risk HPV assay on an Abbott m2000sp instrument. This assay separately detects HPV-16, HPV-18, and a pool of 12 additional hrHPV types (HPV-31, -33, -35, -39, -45, -51, -52, -56, -58, -59, -66, and -68). Results: The study included 652 women with HPV samples and biopsies of the cervix or histology samples obtained during surgery. In all, 30.8% (95% CI, 27.3–34.6%) were HPV-negative. Among HPV-positive women, HPV-16, HPV-18, and “HPV other” types were found in 33.5, 4.4, and 49.4%, respectively. Cervical intraepithelial neoplasia (CIN) 3/high-grade squamous intraepithelial lesions (HSILs) in women ≤ 34 years were positive for HPV-16 in 54.5% of cases and in those ≥ 35 years in 45.4% of cases. Among women with cervical cancer, 75.8% were infected with HPV-16 or had coinfection with HPV-16 and “HPV other”. Conclusions: HPV-16 is the most common type of hrHPV in HSIL + lesions. It is more common in women diagnosed with CIN 3/HSIL who are aged ≤ 35 and is decreasing with age. Therefore, women age ≥ 35 with persistent infection with this type of hrHPV need careful surveillance, as they are at high risk of progression to cervical cancer.
CRIS-Team Scopus Importer:2021-02-19
Keywords: Age-distribtuion of HPV; Cervical cancer; Colposcopy; HPV-distribution; HSIL

Hypoxia drives glucose transporter 3 expression through hypoxia-inducible transcription factor (HIF)-mediated induction of the long noncoding RNA NICI - Lauer, Victoria; Grampp, Steffen; Platt, James; Lafleur, Veronique; Lombardi, Olivia; Choudhry, Hani; Kranz, Franziska; Hartmann, Arndt; Wullich, Bernd; Yamamoto, Atsushi; Coleman, Mathew L.; Ratcliffe, Peter J.; et al. (Journal of Biological Chemistry, 2020)
Hypoxia-inducible transcription factors (HIFs) directly dictate the expression of multiple RNA species including novel and as yet uncharacterized long noncoding transcripts with unknown function. We used pan-genomic HIF-binding and transcriptomic data to identify a novel long noncoding RNA Noncoding Intergenic Co-Induced transcript (NICI) on chromosome 12p13.31 which is regulated by hypoxia via HIF-1 promoter-binding in multiple cell types. CRISPR/Cas9-mediated deletion of the hypoxia-response element revealed co-regulation of NICI and the neighboring protein-coding gene, solute carrier family 2 member 3 (SLC2A3) which encodes the high-affinity glucose transporter 3 (GLUT3). Knockdown or knockout of NICI attenuated hypoxic induction of SLC2A3, indicating a direct regulatory role of NICI in SLC2A3 expression, which was further evidenced by CRISPR/Cas9-VPR-mediated activation of NICI expression. We also demonstrate that regulation of SLC2A3 is mediated through transcriptional activation rather than posttranscriptional mechanisms because knockout of NICI leads to reduced recruitment of RNA polymerase 2 to the SLC2A3 promoter. Consistent with this we observe NICI-dependent regulation of glucose consumption and cell proliferation. Furthermore, NICI expression is regulated by the von Hippel-Lindau (VHL) tumor suppressor and is highly expressed in clear cell renal cell carcinoma (ccRCC), where SLC2A3 expression is associated with patient prognosis, implying an important role for the HIF/NICI/SLC2A3 axis in this malignancy.
CRIS-Team Scopus Importer:2020-04-07
Keywords: ChIP; ChIP-sequencing (ChIP-Seq); glucose transport; GLUT3; hypoxia; hypoxia-inducible factor (HIF); long noncoding RNA (long ncRNA; lncRNA)

Identification and diagnostic performance of a small RNA within the PCA3 and BMCC1 gene locus that potentially targets mRNA - Drayton, Ross M.; Rehman, Ishtiaq; Clarke, Raymond; Zhao, Zhongming; Pang, Karl; Miah, Saiful; Stoehr, Robert; Hartmann, Arndt; Blizard, Sheila; Lavin, Martin; Bryant, Helen E.; Martens-Uzunova, Elena S.; et al. (Cancer Epidemiology Biomarkers & Prevention, 2015)
PCA3 is a long noncoding RNA (lncRNA) with unknown function, upregulated in prostate cancer. LncRNAs may be processed into smaller active species. We hypothesized this for PCA3.We computed feasible RNA hairpins within the BMCC1 gene (encompassing PCA3) and searched a prostate transcriptome for these. We measured expression using qRT-PCR in three cohorts of prostate cancer tissues (n = 60), exfoliated urinary cells (n = 484 with cancer and n = 166 controls), and in cell lines (n = 22). We used in silico predictions and RNA knockup to identify potential mRNA targets of short transcribed RNAs.We predicted 13 hairpins, of which PCA3-shRNA2 was most abundant within the prostate transcriptome. PCA3-shRNA2 is located within intron 1 of PCA3 and appears regulated by androgens. Expression of PCA3-shRNA2 was upregulated in malignant prostatic tissues, exfoliated urinary cells from men with prostate cancer (13-273 fold change; t test P < 0.003), and closely correlated to PCA3 expression (r = 0.84-0.93; P < 0.001). Urinary PCA3-shRNA2 (C-index, 0.75-0.81) and PCA3 (C-index, 0.78) could predict the presence of cancer in most men. PCA3-shRNA2 knockup altered the expression of predicted target mRNAs, including COPS2, SOX11, WDR48, TEAD1, and Noggin. PCA3-shRNA2 expression was negatively correlated with COPS2 in patient samples (r = -0.32; P < 0.001).We identified a short RNA within PCA3, whose expression is correlated to PCA3, which may target mRNAs implicated in prostate biology.This short RNA is stable ex vivo, suggesting a role as a robust biomarker. We identify cytoplasmic enrichment of this RNA and potential targeting of mRNAs implicated in prostate carcinogenesis.
EVALuna2:6667

Identification of DAPK as a scaffold protein for the LIMK/cofilin complex in TNF-induced apoptosis - Ivanovska, Jelena; Tregubova, Alexandra; Mahadevan, Vijayalakshmi; Chakilam, Saritha; Gandesiri, Muktheshwar; Benderska, Natalya; Ettle, Benjamin; Hartmann, Arndt; Söder, Stephan; Ziesche, Elisabeth; Fischer, Thomas; Lautscham, Lena; et al. (International Journal of Biochemistry and Cell Biology, 2013)
The role of cytoskeleton-associated proteins during TNF-induced apoptosis is not fully understood. A potential candidate kinase that might connect TNF signalling to actin reorganization is the death-associated protein kinase (DAPK). To identify new DAPK interaction partners in TNF-induced apoptosis, we performed a peptide array screen. We show that TNF-treatment enhanced the phosphorylation of LIMK at threonine508 and its downstream target cofilin at serine3 (p-cofilin(Ser3)). Modulation of DAPK activity and expression by DAPK inhibitor treatment, siRNA knockdown, and overexpression affected the phosphorylation of both proteins. We propose a 3D structural model where DAPK functions as a scaffold for the LIMK/cofilin complex and triggers a closer interaction of both proteins under TNF stimulation. Upon TNF a striking redistribution of LIMK, DAPK, and cofilin to the perinuclear compartment was observed. The pro-apoptotic DAPK/LIMK/cofilin multiprotein complex was abrogated in detached cells, indicating that its signaling was no longer needed if cells committed to apoptosis. P-cofilin(Ser3) was strongly accumulated in cells with condensed chromatin, pronounced membrane blebs and Annexin V up-regulation. From studying different cofilin(Ser3) mutants we suggest that p-cofilin(Ser3) is an indicator of TNF-induced apoptosis. Collectively, our findings identify a novel molecular cytoskeleton-associated mechanism in TNF-induced DAPK-dependent apoptosis.

Identification of Disparities in Personalized Cancer Care—A Joint Approach of the German WERA Consortium - Lüke, Florian; Haller, Florian; Utpatel, Kirsten; Krebs, Markus; Meidenbauer, Norbert; Scheiter, Alexander; Spörl, Silvia; Heudobler, Daniel; Sparrer, Daniela; Kaiser, Ulrich; Keil, Felix; Schubart, Christoph; et al. (Cancers, 2022)
(1) Background: molecular tumor boards (MTBs) are crucial instruments for discussing and allocating targeted therapies to suitable cancer patients based on genetic findings. Currently, limited evidence is available regarding the regional impact and the outreach component of MTBs; (2) Methods: we analyzed MTB patient data from four neighboring Bavarian tertiary care oncology centers in Würzburg, Erlangen, Regensburg, and Augsburg, together constituting the WERA Alliance. Absolute patient numbers and regional distribution across the WERA-wide catchment area were weighted with local population densities; (3) Results: the highest MTB patient numbers were found close to the four cancer centers. However, peaks in absolute patient numbers were also detected in more distant and rural areas. Moreover, weighting absolute numbers with local population density allowed for identifying so-called white spots—regions within our catchment that were relatively underrepresented in WERA MTBs; (4) Conclusions: investigating patient data from four neighboring cancer centers, we comprehensively assessed the regional impact of our MTBs. The results confirmed the success of existing collaborative structures with our regional partners. Additionally, our results help identifying potential white spots in providing precision oncology and help establishing a joint WERA-wide outreach strategy.
CRIS-Team Scopus Importer:2022-11-04
Keywords: cancer care; MTB; outcomes research; outreach; patient access; precision oncology; real world data

Identification of miRNA-mRNA Modules in Colorectal Cancer Using Rough Hypercuboid Based Supervised Clustering - Paul, Sushmita; Lakatos, Petra; Hartmann, Arndt; Schneider-Stock, Regine; Vera, Julio (Scientific Reports, 2017)
Differences in the expression profiles of miRNAs and mRNAs have been reported in colorectal cancer. Nevertheless, information on important miRNA-mRNA regulatory modules in colorectal cancer is still lacking. In this regard, this study presents an application of the RH-SAC algorithm on miRNA and mRNA expression data for identification of potential miRNA-mRNA modules. First, a set of miRNA rules was generated using the RH-SAC algorithm. The mRNA targets of the selected miRNAs were identified using the miRTarBase database. Next, the expression values of target mRNAs were used to generate mRNA rules using the RH-SAC. Then all miRNA-mRNA rules have been integrated for generating networks. The RH-SAC algorithm unlike other existing methods selects a group of co-expressed miRNAs and mRNAs that are also differentially expressed. In total 17 miRNAs and 141 mRNAs were selected. The enrichment analysis of selected mRNAs revealed that our method selected mRNAs that are significantly associated with colorectal cancer. We identified novel miRNA/mRNA interactions in colorectal cancer. Through experiment, we could confirm that one of our discovered miRNAs, hsa-miR-93-5p, was significantly up-regulated in 75.8% CRC in comparison to their corresponding non-tumor samples. It could have the potential to examine colorectal cancer subtype specific unique miRNA/mRNA interactions.
EVALuna2:6844

Identification of novel microRNAs regulating HLA-G expression and investigating their clinical relevance in renal cell carcinoma - Jasinski-Bergner, Simon; Reches, Adi; Stoehr, Christine; Massa, Chiara; Gonschorek, Evamaria; Huettelmaier, Stefan; Braun, Juliane; Wach, Sven; Wullich, Bernd; Spath, Verena; Wang, Ena; Marincola, Francesco M.; et al. (Oncotarget, 2016)
The non-classical human leukocyte antigen G (HLA-G) is expressed at a high frequency in renal cell carcinoma (RCC) and is associated with a higher tumor grade and a poor clinical outcome. This might be caused by the HLA-G-mediated inhibition of the cytotoxicity of T and NK cells. Therefore a selective targeting of HLA-G might represent a powerful strategy to enhance the immunogenicity of RCC lesions. Recent studies identified a number of HLA-G-regulating microRNAs (miRs) and demonstrated an inverse expression of some of these miRs with HLA-G in RCC in vitro and in vivo. However, it was postulated that further miRs might exist contributing to the tightly controlled selective HLA-G expression.By application of a miR enrichment assay (miTRAP) in combination with in silico profiling two novel HLA-G-regulatory miRs, miR-548q and miR-628-5p, were identified. Direct interactions of both miRs with the 3' untranslated region of HLA-G were confirmed with luciferase reporter gene assays. In addition, qPCR analyses and immunohistochemical staining revealed an inverse, expression of miR-628-5p, but not of miR-548q to the HLA-G protein in primary RCC lesions and cell lines. Stable overexpression of miR-548q and miR-628-5p caused a downregulation of HLA-G mRNA and protein. This leads in case of miR-548q to an enhanced NK cell-mediated HLA-G-dependent cytotoxicity, which could be reverted by ILT2 blockade suggesting a control of the immune effector cell activity at least by this miR. The identification of two novel HLA-G-regulatory miRs extends the number of HLA-G-relevant miRs tuning the HLA-G expression and might serve as future therapeutic targets.
EVALuna2:6802

Identifying fibroblast growth factor receptor genetic alterations using RNA-based assays in patients with metastatic or locally advanced, surgically unresectable, urothelial carcinoma who may benefit from erdafitinib treatment - Wang, Songbai; Burgess, Mike; Major, Christopher; English, Alistair; Sweeney, Maranna; Hartmann, Arndt (Journal of Pathology: Clinical Research, 2020)
Erdafitinib, a pan-fibroblast growth factor receptor (FGFR) inhibitor received accelerated approval from the US Food and Drug Administration (FDA) for locally advanced or metastatic urothelial carcinoma (mUC) in adult patients with specific FGFR3/2 genetic alterations who progressed during or after >= 1 line of prior platinum-containing chemotherapy (PCC), including within 12 months of neoadjuvant or adjuvant PCC. Concordance between the clinical trial assay (CTA) used in a phase 2 study and QIAGEN's therascreen (R) FGFR kit (a two-step, multiplex, real-time, RT-PCR assay), the FDA-approved companion diagnostic (CDx) with erdafitinib, was evaluated in this bridging study. Study samples included 100 CTA-confirmed FGFR-positive samples from 100 erdafitinib-treated mUC patients, plus 200 CTA-confirmed FGFR-negative samples from the phase 2 study. The primary objective was met if the lower bound of 95% CI of objective response rate (ORR) in CDx-confirmed patients with FGFR alterations was >25%. Demographics were similar between the bridging study and CTA-screened patients. In total, 292 of 300 samples (97.3%) with valid CDx results showed high analytical concordance versus CTA (percent agreement [95% CI]: positive percent agreement, 87.2 [79.0; 92.5]; negative percent agreement, 97.0 [93.5; 98.6]; overall percent agreement, 93.8 [90.5; 96.1]). Investigator-assessed ORR in the 81 CDx-identified, erdafitinib-treated patients who tested positive for both assays was 45.7% (95% CI: 35.3%; 56.5%) versus 40.4% (95% CI: 30.7%; 50.1%) for CTA and met the criteria for primary objective. High ORR and clinical concordance to CTA suggest that QIAGEN's CDx can reliably select mUC patients who would potentially benefit from erdafitinib treatment.
CRIS-Team WoS Importer:2020-05-02

Idiopathic Mast Cell Activation Syndrome With Associated Salicylate Intolerance - Rechenauer, Tobias; Raithel, Martin; Goetze, Thomas; Siebenlist, Gregor; Rueckel, Aline; Baenkler, Hanns-Wolf; Hartmann, Arndt; Haller, Florian; Hoerning, Andre (Frontiers in Pediatrics, 2018)
Idiopathic mast cell activation syndrome can be a rare cause for chronic abdominal pain in children. It remains a diagnosis by exclusion that can be particularly challenging due to the vast variety of possible clinical manifestations. We present a 13-year-old boy who suffered from a multitude of unspecific complaints over a long period of time. In this case, an assessment of mast cell-derived metabolites and immunohistochemical analysis of bioptic specimen was worthwhile. After ruling out, primary (oncologic) and secondary causes for mast cell activation, pharmacologic treatment adapted to the patient's salicylate intolerance resulted in a major relief of symptoms.
EVALuna2:34101

IDKK1 inhibits canonical Wnt signaling in human papillomavirus-positive penile cancer cells - Bley, Isabelle Ariane; Zwick, Anabel; Hans, Muriel Charlotte; Thieser, Katrin; Wagner, Viktoria; Ludwig, Nicole; Khalmurzaev, Oybek; Matveev, Vsevolod Borisovich; Loertzer, Philine; Pryalukhin, Alexey; Hartmann, Arndt; Geppert, Carol-Immanuel; et al. (Translational Oncology, 2022)
Penile squamous cell cancer (PSCC) is the most frequent penile malignant disease. Infections with human papillomaviruses (HPV) are a major etiologic driver of PSCC. However, the molecular details of the underlying carcinogenesis are understudied because of rare clinical specimens and missing cell lines. Here, we investigated if the expression of high-risk HPV16 oncogenes causes an augmentation of the Wnt pathway using unique HPV-positive penile cancer (PeCa) cell lines in monolayer and organotypic 3D raft cultures as well as tissue micro arrays containing clinical tissue specimens. The HPV oncoproteins enhanced the expression of Leucine-rich repeat-containing G-protein coupled receptor 6 (LGR6) and the HPV-positive PeCa cells expressed a signature of Wnt target and stemness-associated genes. However, the notable lack of nuclear β-catenin in vitro and in situ raised the question if the enhanced expression of Wnt pathway factors is tantamount to an active Wnt signaling. Subsequent TOP-flash reporter assays revealed Wnt signaling as absent and not inducible by respective Wnt ligands in PeCa cell lines. The HPV-positive PeCa cells and especially HPV-positive PeCa specimens of the tumor core expressed the Wnt antagonist and negative feedback-regulator Dickkopf1 (DKK1). Subsequent neutralization experiments using PeCa cell line-conditioned media demonstrated that DKK1 is capable to impair ligand-induced Wnt signaling. While gene expression analyses suggested an augmented and active canonical Wnt pathway, the respective signaling was inhibited due to the endogenous expression of the antagonist DKK1. Subsequent TMA stainings indicated Dkk1 as linked with HPV-positivity and metastatic disease progression in PeCa suggesting potential as a prognostic marker.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Dickkopf1; HPV; Penile cancer; Stemness; Wnt pathway; β-catenin

IFN-γ-driven intratumoral microenvironment exhibits superior prognostic effect compared with an IFN-α-driven microenvironment in patients with colon carcinoma - Grenz, Sandra; Naschberger, Elisabeth; Merkel, Susanne; Britzen-Laurent, Nathalie; Schaal, Ute; Konrad, Andreas; Aigner, Michael; Rau, Tilman; Hartmann, Arndt; Croner, Roland S.; Hohenberger, Werner; Stürzl, Michael (American Journal of Pathology, 2013)
Interferon (IFN)-α and IFN-γ are cytokines with potent immunomodulating and anti-tumor activities. It is unknown which of the two IFNs may be more potent in the regulation of an anti-tumorigenic response in colorectal carcinoma or whether both cytokines cooperate. We, therefore, established human myxovirus resistance protein A and human guanylate-binding protein-1 as markers for the differential detection of IFN-α- and IFN-γ-driven tumor micromilieus, respectively. In vitro studies with different cultures of tumor cells from colorectal carcinoma and stroma cells showed that the expression of myxovirus resistance protein A was exclusively induced by IFN-α, whereas guanylate-binding protein-1 was strongly induced by IFN-γ and only weakly by IFN-α. This expression pattern was used to distinguish cell activation caused by the two cytokines in a clinical cohort of patients with colon carcinoma (n = 378). Patients with primary tumors expressing only guanylate-binding protein-1 exhibited the highest cancer-specific 5-year survival (94.0%, P = 0.006) compared with those expressing both factors (90.3%, P = 0.006), myxovirus resistance protein A alone (83.5%, P = 0.096), or none (72.8%). Our study describes a successful proof-of-principle approach that complex cytokine interaction networks can be dissected in human tissues and demonstrates that an IFN-γ-driven tumor microenvironment exhibits a superior prognostic effect compared with an IFN-α-driven tumor microenvironment in colon carcinoma. © 2013 American Society for Investigative Pathology.
Created from Fastlane, Scopus look-up

IL-20 controls resolution of experimental colitis by regulating epithelial IFN/STAT2 signalling - Chiriac, Mircea-Teodor; Hracsko, Zsuzsanna; Günther, Claudia; Gonzalez Acera, Miguel; Atreya, Raja; Stolzer, Iris; Wittner, Leonie; Dressel, Anja; Schickedanz, Laura; Gámez Belmonte, Maria de los Reyes; Erkert, Lena; Hundorfean, Gheorghe; et al. (Gut, 2023)
Objective: We sought to investigate the role of interleukin (IL)-20 in IBD and experimental colitis. Design: Experimental colitis was induced in mice deficient in components of the IL-20 and signal transducer and activator of transcription (STAT)2 signalling pathways. In vivo imaging, high-resolution mini-endoscopy and histology were used to assess intestinal inflammation. We further used RNA-sequencing (RNA-Seq), RNAScope and Gene Ontology analysis, western blot analysis and co-immunoprecipitation, confocal microscopy and intestinal epithelial cell (IEC)-derived three-dimensional organoids to investigate the underlying molecular mechanisms. Results were validated using samples from patients with IBD and non-IBD control subjects by a combination of RNA-Seq, organoids and immunostainings. Results: In IBD, IL20 levels were induced during remission and were significantly higher in antitumour necrosis factor responders versus non-responders. IL-20RA and IL-20RB were present on IECs from patients with IBD and IL-20-induced STAT3 and suppressed interferon (IFN)-STAT2 signalling in these cells. In IBD, experimental dextran sulfate sodium (DSS)-induced colitis and mucosal healing, IECs were the main producers of IL-20. Compared with wildtype controls, Il20-/-, Il20ra-/- and Il20rb-/- mice were more susceptible to experimental DSS-induced colitis. IL-20 deficiency was associated with increased IFN/STAT2 activity in mice and IFN/STAT2-induced necroptotic cell death in IEC-derived organoids could be markedly blocked by IL-20. Moreover, newly generated Stat2ΔIEC mice, lacking STAT2 in IECs, were less susceptible to experimental colitis compared with wildtype controls and the administration of IL-20 suppressed colitis activity in wildtype animals. Conclusion: IL-20 controls colitis and mucosal healing by interfering with the IFN/STAT2 death signalling pathway in IECs. These results indicate new directions for suppressing gut inflammation by modulating IL-20-controlled STAT2 signals.
CRIS-Team Scopus Importer:2023-11-17
Keywords: experimental colitis; inflammatory bowel disease; interferon; interleukins; signal transduction

IL-23 is centrally involved in mediating molecular resistance to anti-TNF therapy in Crohn's disease patients - Schmitt, H.; Billmeier, Ulrike; Dieterich, Walburga; Rath, T.; Sonnewald, Sophia; Reid, Stephen; Hirschmann, S.; Hildner, Kai; Waldner, Maximilian; Mudter, J.; Hartmann, Arndt; Grützmann, Robert; et al. (2018)
EVALuna2:34077

IL-9 and its receptor are predominantly involved in the pathogenesis of UC - Nalleweg, Nancy; Chiriac, Mircea Teodor; Podstawa, Eva; Lehmann, Christian; Rau, Tilman; Atreya, Raja; Krauss, Ekaterina; Hundorfean, Gheorghe; Fichtner-Feigl, Stefan; Hartmann, Arndt; Becker, Christoph; Mudter, Jonas (Gut, 2015)
Several pathogenic roles attributed over the past two decades to either T helper (Th)1 or Th2 cells are increasingly becoming associated with interleukin (IL)-17 and most recently IL-9 signalling. However, the implication of IL-9 in IBD has not been addressed so far.We investigated the expression of IL-9 and IL-9R by using peripheral blood, biopsies and surgical samples. We addressed the functional role of IL-9 signalling by analysis of downstream effector proteins. Using Caco-2 cell monolayers we followed the effect of IL-9 on wound healing.IL-9 mRNA expression was significantly increased in inflamed samples from patients with UC as compared with controls. CD3(+) T cells were major IL-9-expressing cells and some polymorphonuclear leucocytes (PMN) also expressed IL-9. IL-9 was co-localised with the key Th9 transcription factors interferon regulatory factor 4 and PU.1. Systemically, IL-9 was abundantly produced by activated peripheral blood lymphocytes, whereas its receptor was overexpressed on gut resident and circulating PMN. IL-9 stimulation of the latter induced IL-8 production in a dose-dependent manner and rendered PMN resistant to apoptosis suggesting a functional role for IL-9R signalling in the propagation of gut inflammation. Furthermore, IL-9R was overexpressed on gut epithelial cells and IL-9 induced STAT5 activation in these cells. Moreover, IL-9 inhibited the growth of Caco-2 epithelial cell monolayers in wound healing experiments.Our results provide evidence that IL-9 is predominantly involved in the pathogenesis of UC suggesting that targeting IL-9 might become a therapeutic option for patients with UC.
EVALuna2:1839

Immune Cell-Associated Protein Expression Helps to Predict Survival in Muscle-Invasive Urothelial Bladder Cancer Patients after Radical Cystectomy and Optional Adjuvant Chemotherapy - Taubert, Helge; Eckstein, Markus; Epple, Elena; Jung, Rudolf; Weigelt, Katrin; Lieb, Verena; Sikic, Danijel; Stöhr, Robert; Geppert, Carol-Immanuel; Weyerer, Veronika; Bertz, Simone; Kehlen, Astrid; et al. (Cells, 2021)
Bladder cancer (BCa) is the tenth most commonly diagnosed malignant cancer worldwide. Although adjuvant chemotherapy following radical cystectomy is a common therapy for muscle invasive bladder cancer patients, no applicable biomarkers exist to predict which patients will benefit from chemotherapy. In this study, we examined three immune cell markers, the chemokine CC motif ligand 2 (CCL2), the pan macrophage marker cluster of differentiation 68 (CD68) and the M2 macrophage marker cluster of differentiation 163 (CD163), using immunohistochemistry to determine their predictive value for the chemotherapy response in different nodal stage (pN0 vs. pN1 + 2) and tumor stage subgroups (pT2 vs. pT3 + 4). The prognosis was studied in terms of the overall survival (OS), disease-specific survival (DSS), and recurrence-free-survival (RFS) in 168 muscle invasive BCa patients. Chemotherapy was associated with a poorer prognosis in patients with a higher expression of the immune markers CCL2 (RFS), CD68 (DSS and RFS), and CD163 (DSS and RFS) in the N0 group and with poorer survival in patients with a higher expression of the immune markers CCL2 (OS, DSS, and RFS), CD68 (OS, DSS, and RFS), and CD163 (OS, DSS, and RFS) in the pT2 group when compared with treatments without chemotherapy. In contrast, chemotherapy was associated with a better prognosis in patients with a low expression of the immune markers CCL2 (DSS and RFS), CD68 (OS, DSS, and RFS), and CD163 (OS) in the N1 + 2 group. In addition, chemotherapy was associated with improved survival in patients with a low expression of the immune marker CD68 (OS and DSS) and there was a trend for a better prognosis in patients with a low expression of CD163 (OS) in the pT3 + 4 group compared to patients not treated with chemotherapy. Interestingly, CD68 appeared to be the most applicable immune marker to stratify patients by the outcome of chemotherapy in the nodal stage and tumor stage groups. Overall, we suggest that, in addition to the clinical factors of tumor stage and nodal stage, it is also meaningful to consider the abundance of immune cells, such as macrophages, to better predict the response to chemotherapy for BCa patients after radical treatment.
CRIS-Team Scopus Importer:2021-02-12
Keywords: bladder cancer; CCL2; CD163; CD68; chemotherapy; immune cells; nodal stage; tumor stage

Immune Cell Gene Expression Signature is Associated with Improved Outcome in Muscle-Invasive Urothelial Bladder Cancer Patients Treated with Radical Cystectomy - Eckstein, Markus; Strissel, Pamela; Strick, Reiner; Weyerer, Veronika; Wirtz, Ralph M.; Pfannstiel, Carolin; Wullweber, Adrian; Lange, Fabienne; Erben, Philipp; Stöhr, Robert; Bertz, Simone; Geppert, Carol-Immanuel; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2020)
CRIS-Team WoS Importer:2020-03-20

Immunohistochemical analysis of sex hormone receptors in squamous changes of the urothelium. - Seitz, Julia; Hoegel, Josef; Eckstein, Markus; Lieb, Verena; Wullich, Bernd; Hartmann, Arndt; Rieker, Ralf (International Journal of Clinical and Experimental Pathology, 2022)
OBJECTIVE: Squamous cell transformation of the urinary bladder urothelium has various causes, symptoms, and few treatment options. The aim of this study was to analyze and compare the expression of sex hormone receptors in non-keratinized and keratinized squamous metaplasia (NKSM, KSM), squamous cell carcinoma (SCC), and healthy urothelium with regard to possible therapeutic approaches. METHODS: Biopsies from 26 patients with urothelial NKSM, KSM, and SCC were analyzed retrospectively. Tissue microarrays (TMA) of formalin-fixed paraffin-embedded (FFPE) bladder biopsies were stained with hematoxylin and eosin followed by immunohistochemical analysis with specific antibodies against estrogen, progesterone, and androgen receptors (ER, PR, AR) and assessment using the immunoreactive score. Statistical evaluations included the Wilcoxon signed-rank test and the Wilcoxon rank-sum test in the form of permutation tests. RESULTS: Of the 15 women and 11 men included in this explorative study, 17 had metaplasia: 15 (six men, nine women) had NKSM and two KSM (both men). A total of nine patients (three men, six women) had keratinized SCC or urothelial carcinoma with squamous differentiation. The comparison between normal urothelial cells and metaplasia showed a significantly stronger expression in the metaplastic tissue (P=0.0374). The invasive carcinoma showed significantly less PR than the extracellular matrix of the healthy urothelium (P=0.0026). Expression of AR was nearly absent in healthy and metaplastic urothelium. CONCLUSION: There appears to be an association between squamous metaplasia of the bladder mucosa and sex steroid hormone receptor expression, especially estrogen receptors. Topical hormone therapy should be considered.
EVALuna2:512116

Immunohistochemical analysis of sex hormone receptors in squamous changes of the urothelium - Seitz, Julia; Hogel, Josef; Eckstein, Markus; Lieb, Verena; Wullich, Bernd; Hartmann, Arndt; Rieker, Ralf (International Journal of Clinical and Experimental Pathology, 2022)
Objective: Squamous cell transformation of the urinary bladder urothelium has various causes, symptoms, and few treatment options. The aim of this study was to analyze and compare the expression of sex hormone receptors in non-keratinized and keratinized squamous metaplasia (NKSM, KSM), squamous cell carcinoma (SCC), and healthy urothelium with regard to possible therapeutic approaches. Methods: Biopsies from 26 patients with urothelial NKSM, KSM, and SCC were analyzed retrospectively. Tissue microarrays (TMA) of formalin-fixed paraffinembedded (FFPE) bladder biopsies were stained with hematoxylin and eosin followed by immunohistochemical analysis with specific antibodies against estrogen, progesterone, and androgen receptors (ER, PR, AR) and assessment using the immunoreactive score. Statistical evaluations included the Wilcoxon signed-rank test and the Wilcoxon rank-sum test in the form of permutation tests. Results: Of the 15 women and 11 men included in this explorative study, 17 had metaplasia: 15 (six men, nine women) had NKSM and two KSM (both men). A total of nine patients (three men, six women) had keratinized SCC or urothelial carcinoma with squamous differentiation. The comparison between normal urothelial cells and metaplasia showed a significantly stronger expression in the metaplastic tissue (P=0.0374). The invasive carcinoma showed significantly less PR than the extracellular matrix of the healthy urothelium (P=0.0026). Expression of AR was nearly absent in healthy and metaplastic urothelium. Conclusion: There appears to be an association between squamous metaplasia of the bladder mucosa and sex steroid hormone receptor expression, especially estrogen receptors. Topical hormone therapy should be considered.
CRIS-Team WoS Importer:2022-09-30

Immunohistochemical and molecular characterizations in urothelial carcinoma of bladder in patients less than 45 years - Weyerer, Veronika; Schneckenpointner, Roland; Filbeck, Thomas; Burger, Maximilian; Hofstaedter, Ferdinand; Wild, Peter J.; Fine, Samson W.; Humphrey, Peter A.; Dehner, Louis P.; Amin, Mahul B.; Rueschoff, Josef; Boltze, Carsten; et al. (Journal of Cancer, 2017)
Bladder tumours in early-onset patients are rare and seem to exhibit unique clinicopathological features. Only few studies have investigated somatic alterations in this specific age of onset group and evidence is accumulating of a distinct molecular behaviour of early-onset bladder tumours. We collected the largest cohort of early-onset tumours of patients 45 years old or younger and aimed to test genomic alterations typically found in bladder cancer. Tumours of 118 early-onset patients were compared with a consecutive group of 113 cases. Immunohistochemistry of TP53, CK20 and Ki-67 was carried out. Molecular analysis was conducted to test for loss of heterozygosity of chromosome 9 and 17, as well as TP53 and FGFR3 mutations. Fisher´s exact and chi-squared test were appropriately used. No differences in grade/stage characteristics were observed. Overexpressed TP53 was differentially distributed between the two groups. TP53 nuclear accumulation was significantly more frequent in early-onset papillomas, PUNLMPs and pTa low-grade tumours compared to the consecutive cohort (p=0.005). Moreover, chromosome 9 deletions (29.5% vs. 44.6%) and FGFR3 mutations (34.5% vs. 63.7%) were less often detected in early-onset patients (p=0.05 and p<0.0001). By comparing the largest cohort of early-onset bladder cancer patients with an unselected group, we demonstrated that the typical molecular features are not independent of age at diagnosis. Our study supports the hypothesis of a distinct biological behaviour in early-onset tumours.
EVALuna2:6841

Immunohistochemical expression of IMP3 and p53 in inflammatory lesions and neoplastic lesions of the gastric mucosa - Strehl, Johanna D.; Hoegel, Josef; Hornicek, Ines; Hartmann, Arndt; Riener, Marc-Oliver (International Journal of Clinical and Experimental Pathology, 2014)
Expression of the oncofetal protein insulin like growth factor II messenger ribonucleic acid binding protein 3 (IMP3) has been shown to differentiate between benign and malignant lesions in several tissues. Our aim was to assess the immunohistochemical expression of IMP3 in inflammatory and neoplastic lesions of the gastric mucosa and to determine whether IMP3, alone or in combination with p53, could be used for identifying neoplasia of the gastric mucosa.IMP3 and p53 immunohistochemistry was performed on 57 cases of gastritis, 28 cases of dysplasia of the gastric mucosa and 63 cases of gastric carcinomas. Focal IMP3 positivity was detected in 86% of non-neoplastic lesions of the gastric mucosa. Using a simple product score (PS), 96% of non-neoplastic lesions of the gastric mucosa were assessed as IMP3(PS) negative. None of the low-grade dysplasia but 83% of high-grade dysplasia were IMP3(PS) positive. Gastric carcinomas showed IMP3(PS) positivity in 65%. Adding p53 to the diagnostic panel increased sensitivity significantly.High-grade dysplasia and gastric carcinomas can be distinguished from low-grade dysplasia and inflammatory lesions of the gastric mucosa with a high specificity and good sensitivity using a combination of the immunohistochemical markers IMP3 and p53.
EVALuna2:6602

Immunohistochemical expression of the hepatocyte growth factor in chromophobe renal cell carcinoma - Erlmeier, Maximilian; Mikuteit, Marie; Zschaebitz, Stefanie; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; Steffens, Sandra; Erlmeier, Franziska (BMC Urology, 2023)
Background: The prognostic value of Hepatocyte growth factor (HGF) in non-clear cell renal cell carcinoma (RCC) is still unclear. The aim of this study is to evaluate the prognostic impact of HGF expression in a large cohort of chromophobe RCC (chRCC). Methods: Patients who underwent renal surgery due to chRCC were recruited. Clinical data was retrospectively evaluated. Tumor specimen were analyzed for HGF expression by immunohistochemistry. Results: 81 chRCC patients were eligible for analysis, thereof 37 (45.7%) patients were positive for HGF. No significant associations were found for HGF expression and clinical attributes in patients with chRCC. Kaplan-Meier analysis revealed no differences in 5-year overall survival (OS) for patients with HGF− compared to HGF+ tumors (95.0% versus 90.9%; p = 0.410). Conclusions: In chRCC HGF expression is not associated with parameters of aggressiveness or survival.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Chromophobe histology; HGF; Renal Cell Carcinoma; Survival

Immunohistochemical panel for the diagnosis of Hirschsprung's disease using antibodies to MAP2, calretinin, GLUT1 and S100 - Bachmann, Leonhard; Besendörfer, Manuel; Carbon, Roman; Lux, Philipp; Agaimy, Abbas; Hartmann, Arndt; Rau, Tilman (Histopathology, 2015)
The diagnosis of Hirschsprung's disease is currently based on the identification of aganglionosis and the presence of an increase in acetylcholinesterase-positive hypertrophic nerve fibres in the large bowel submucosa. However, acetylcholinesterase staining is laborious and requires a skilled technician. The aim of this study was to identify a method for diagnosing Hirschsprung's disease reliably using an immunohistochemical panel of recently proposed markers.Sixty-nine specimens from 37 patients were evaluated. MAP2 and calretinin antibodies were shown to stain ganglia reliably in the submucosal and myenteric plexuses of normal tissue. By contrast, reduced staining of ganglia was observed in patients with Hirschsprung's disease. Staining for GLUT1 and S100 was used to evaluate the number and thickness of nerve fibres. Gain of GLUT1 and S100 expression was in contrast to the loss of calretinin and MAP2. Hypertrophic submucosal nerve fibres in Hirschsprung's disease develop a perineurium with a ring-like GLUT1 staining pattern similar in size and intensity to that observed in deeper subserosal tissue.The diagnosis of Hirschsprung's disease using immunohistochemical panels could be as accurate as with conventional frozen section techniques. In particular, the use of a combination of markers for ganglia and hypertrophic nerve fibres highlighting a prominent perineurium in Hirschsprung's disease could be an alternative method.
EVALuna2:6718

Immunohistochemical TP53 expression in atypical fibroxanthoma and their mimics - Erber, Ramona; Hartmann, Arndt; Agaimy, Abbas (VIRCHOWS ARCHIV, 2019)
CRIS-Team WoS Importer:2019-09-27

Immunohistochemiocal subtyping using CK20 and CK5 can identify urothelial carcinomas of the upper urinary tract with a poor prognosis - Sikic, Danijel; Keck, Bastian; Wach, Sven; Taubert, Helge; Wullich, Bernd; Goebell, Peter; Kahlmeyer, Andreas; Olbert, Peter; Isfort, Philipp; Nimphius, Wilhelm; Hartmann, Arndt; Giedl, Josef (PLoS ONE, 2017)
Genome-wide analyses revealed basal and luminal subtypes of urothelial carcinomas of the bladder. It is unknown if this subtyping can also be applied to upper tract urothelial carcinomas.Tumor samples from 222 patients with upper tract urothelial carcinomas who were treated with radical nephroureterectomy were analyzed for the expression of seven basal/luminal immunohistochemical markers (CK5, EGFR, CD44, CK20, p63, GATA3, FOXA1).Hierarchical clustering revealed a basal-like subtype (enrichment of CK5, EGFR and CD44) in 23.9% and a luminal-like subtype (enrichment of CK20, GATA3, p63 and FOXA1) in 13.1% of the patients. In 60.8%, little to no markers were expressed, whereas markers of both subtypes were expressed in 2.2%. By using CK5 and CK20 as surrogate markers for the basal and luminal subtypes, we defined four subtypes of upper tract urothelial carcinomas: (i) exclusively CK20 positive and CK5 negative (CK20+/CK5-), (ii) exclusively CK5 positive and CK20 negative (CK20-/ CK5+), (iii) both markers positive (CK20+/CK5+) and (iv) both markers negative (CK20-/CK5-). A receiver-operator analysis provided the optimal cut-off values for this discrimination. An immunoreactive score >1 for CK5 and >6 for CK20 were defined as positive. In multivariate Cox's regression analysis, the CK20+/CK5- subtype was an independent negative prognostic marker with a 3.83-fold increased risk of cancer-specific death (p = 0.02) compared to the other three subtypes.Immunohistochemical subgrouping of upper tract urothelial carcinomas by analyzing CK5 and CK20 expression can be performed in a routine setting and can identify tumors with a significantly worse cancer-specific survival prognosis.
EVALuna2:6876

Immunoscore feasibility study in routine postsurgical pathologic review for early-stage colon cancer (CC) cases risk-assessment - Belaloui, K.; Malifarge, E.; Bohm, J.; Bossard, C.; Dienstmann, R.; Garcia, S.; Geppert, Carol-Immanuel; Gogenur, I.; Hartmann, Arndt; Hatzibougias, D.; Landolfi, S.; Mishaeli, M.; et al. (ANNALS OF ONCOLOGY, 2018)
CRIS-Team WoS Importer:2019-02-21

Immunoscore predicts significant differences in time to recurrence in stage I colon cancer patients - Galon, J.; Hermitte, F.; Mlecnik, B.; Marliot, F.; Bifulco, C.; Lugli, A.; Nagtegaal, I.; Hartmann, Arndt; Van Den Eynde, M.; Roehrl, M.; Ohashi, P.; Zavadova, E.; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2020-01-07

Immunotherapy in Genitourinary Cancers: Role of Surgical Pathologist for Detection of Immunooncologic Predictive Factors - Bahlinger, Veronika; Hartmann, Arndt; Eckstein, Markus (Advances in Anatomic Pathology, 2023)
Genitourinary malignancies include a broad spectrum of distinct tumor entities occurring in the kidney, the urinary tract, the prostate, the adrenal glands, the penis, and testicles. Each tumor entity presents with unique biological characteristics, especially in terms of immunobiology. The immune landscape of genitourinary malignancies differs between immunoreactive tumors like urothelial carcinoma or carcinomas of the kidney, for which several immunotherapeutic treatment options have been approved in the past years. In contrast, prostate cancer presents with low immunogenicity and previous trials exploring immune checkpoint inhibitors and other immunotherapeutic agents did not proof substantial survival benefits. In this review, we are presenting a streamlined overview on the role of surgical pathologists within the contemporary practice of immune oncology. It includes current indications for pathologic programmed death-ligand 1 (PD-L1) assessment and important pathologic considerations on PD-L1 testing harmonization including interassay and algorithm variabilities. In addition, we will discuss emerging biomarkers beyond PD-L1 and their potential to predict immunotherapy responses including tumor mutational burden, microsatellite instability, gene expression signatures, and histologic factors.
CRIS-Team Scopus Importer:2023-04-21
Keywords: genitourinary tumors; immunotherapy; microsatellite instability; PD-1; PD-L1; tumor mutational burden

Immunotherapy in urothelial carcinoma from a pathologist's perspective - Erlmeier, Franziska; Steffens, Sandra; Hartmann, Arndt (Aktuelle Urologie, 2017)
Immunotherapy with programmed cell death protein-1 (PD-1) antibodies (pembrolizumab and nivolumab) has been approved in Europe for the first-line treatment of several tumour entities, e. g. malignant melanoma. Following the resounding therapeutic success of these antibodies in different types of tumours, their potential in urological tumours has been investigated in several studies. The approval of the PD-1 antibody nivolumab for the treatment of metastasised renal cell carcinoma has set a new milestone in urooncology. This success continued with the approval of the programmed cell death ligand 1 (PD-L1) atezolizumab for advanced urothelial carcinoma in 2016. In addition, several ongoing clinical trials of other checkpoint inhibitors have also shown promising efficacy in advanced urothelial carcinoma. The decision to treat a patient with immunotherapy is based, among other things, on the immunohistochemical staining and evaluation by a pathologist. However, due to the lack of standardised evaluation protocols and detection systems, it is difficult to compare different studies and evaluate the efficacy of the respective antibodies.
EVALuna2:6866

IMP3 and p16 expression in squamous cell carcinoma of the head and neck: A comparative immunohistochemical analysis - Riener, Marc-Oliver; Hoegel, Josef; Iro, Heinrich; Hartmann, Arndt; Agaimy, Abbas (Oncology Letters, 2017)
Expression of p16 has been established as a good surrogate marker for high-risk human papillomavirus (HPV) infection in oropharyngeal squamous cell carcinoma (OPSCC) patients, and it has been associated with an improved prognosis, irrespective of the actual HPV status. Conversely, the human insulin-like growth factor II mRNA binding protein 3 (IMP3) has been related to aggressiveness in several types of tumors. The aim of the present study was to investigate and compare p16 and IMP3 as markers of favorable and unfavorable behavior, respectively, in head and neck SCC (HNSCC), with particular reference to the HPV status. Both markers were analyzed by immunohistochemical analysis of 156 HNSCC samples originating from the oropharynx (n=81), oral cavity (n=44), larynx (n=15), hypopharynx (n=10) and nasopharynx (n=6). The HPV status was examined in a randomly selected representative subcohort (n=38) using polymerase chain reaction. Of the 156 HNSCC samples, 81 (51.9%) and 54 (34.6%) were positive for IMP3 and p16, respectively. IMP3 expression (P=0.022), p16 expression (P<0.001) and the combination of these markers (P<0.001) were significantly associated with tumor site. In particular, 69/81 (85%) OPSCC samples were positive for either one or both markers compared with 36/75 (48%) SCC samples from other sites. p16 expression was significantly associated with HPV infection (P=0.017) and a trend towards a negative association between IMP3 expression and HPV infection was observed (P=0.053). The results of the present study suggested that IMP3 and p16 are more frequently expressed in OPSCC compared with other HNSCCs. The prognostic impact of IMP3 on OPSCC remains to be investigated in a larger series with an extended follow-up period.
EVALuna2:6894

Impact of fibroblast growth factor receptor 1 (FGFR1) amplification on the prognosis of breast cancer patients - Erber, Ramona; Rübner, Matthias; Davenport, Simon; Hauke, Sven; Beckmann, Matthias; Hartmann, Arndt; Häberle, Lothar; Gaß, Paul; Press, Michael F.; Fasching, Peter (Breast Cancer Research and Treatment, 2020)
Purpose: Various aberrations in the fibroblast growth factor receptor genes FGFR1, FGFR2, and FGFR3 are found in different cancers, including breast cancer (BC). This study analyzed the impact of FGFR amplification on the BC prognosis. Methods: The study included 894 BC patients. The amplification rates of FGFR1, FGFR2, and FGFR3 were evaluated on tissue microarrays using fluorescence in situ hybridization (FISH). Associations between these parameters and prognosis were analyzed using multivariate Cox regression analyses. Results: FGFR1 FISH was assessable in 503 samples, FGFR2 FISH in 447, and FGFR3 FISH in 562. The FGFR1 amplification rate was 6.6% (n = 33). Increased FGFR2 copy numbers were seen in 0.9% (n = 4); only one patient had FGFR3 amplification (0.2%). Most patients with FGFR1 amplification had luminal B-like tumors (69.7%, n = 23); only 32.6% (n = 153) of patients without FGFR1 amplification had luminal B-like BC. Other patient and tumor characteristics appeared similar between these two groups. Observed outcome differences between BC patients with and without FGFR1 amplification did not achieve statistical significance; however, there was a trend toward poorer distant metastasis-free survival in BC patients with FGFR1 amplification (HR = 2.08; 95% CI 0.98 to 4.39, P = 0.05). Conclusion: FGFR1 amplification occurs most frequently in patients with luminal B-like BC. The study showed a nonsignificant correlation with the prognosis, probably due to the small sample size. Further research is therefore needed to address the role of FGFR1 amplifications in early BC patients. FGFR2 and FGFR3 amplifications are rare in patients with primary BC.
CRIS-Team Scopus Importer:2020-09-04
Keywords: Amplification; Breast cancer; FGFR1; FGFR2; FGFR3; FISH; Prognosis

Impact of spatially heterogeneous trop‐2 expression on prognosis in oral squamous cell carcinoma - Erber, Ramona; Spoerl, Steffen; Mamilos, Andreas; Krupar, Rosemarie; Hartmann, Arndt; Rübner, Matthias; Taxis, Juergen; Wittenberg, Mareike; Reichert, Torsten E.; Spanier, Gerrit; Spörl, Silvia (International Journal of Molecular Sciences, 2022)
Oral cancer often presents with aggressive behavior and a high risk of recurrence and metastasis. For oral squamous cell carcinoma (OSCC), which is the most frequent histological subtype, therapy strategies include surgery, radiation therapy, chemotherapy, immune checkpoint inhibitors, and EGFR inhibitors. Recently, a Trop‐2 antibody‐drug conjugate (ADC) has been approved in the United States of America for the treatment of advanced triple‐negative breast cancer. However, this ADC has also been tested in other solid tumors including head & neck squamous cell carcinoma. The prognostic impact of Trop‐2 has already been reported for several cancers. We studied the prognostic influence of Trop‐2 protein expression on OSCC patients’ survival. The cohort comprised n = 229 OSCC patients with available archived tumor tissue and corresponding non‐neoplastic oral mucosa tissue. Using immunohistochemistry, we investigated Trop‐2 expression in both the central and peripheral regions of each tumor and in corresponding non‐neoplastic oral mucosa. In patients suffering from OSCC with combined high central and low peripheral Trop‐2 expression, five‐year overall survival (OS) was 41.2%, whereas 55.6% of OSCC patients who presented lower central and/or higher peripheral tumoral Trop‐2 expression were alive after five years (p = 0.075). In multivariate Cox regression, the expression pattern of high central tumoral and lower peripheral Trop‐2 expression was significantly correlated with impaired OS (HR = 1.802, 95%‐CI: 1.134–2.864; p = 0.013) and recurrence‐free survival (RFS) (HR = 1.633, 95%‐CI: 1.042–2.560; p = 0.033), respectively, when adjusting for co‐variables. Hence, Trop‐2 may serve as an independent prognostic biomarker in OSCC. In subsequent studies, the pathophysiological meaning of downregulated Trop‐2 expression in the OSCC periphery has to be analyzed.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Antibody‐drug conjugates; Biomarker; Head and neck cancer; Immunohistochemistry; Oral squamous cell carcinoma; Prognosis; TACSTD2; Trop‐2; Tumor associated calcium signal transducer 2

Impact of the Corona Pandemic on Cervical Cancer Screening Assessment - Stübs, Frederik; Behrens, Annika; Seibold, Anja; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Koch, Martin C.; Mehlhorn, Grit; Beckmann, Matthias; Theuser, Anna Katharin; Schulmeyer, Carla; et al. (In Vivo, 2024)
BACKGROUND/AIM: The global impact of the COVID-19 pandemic resulted in disruptions to healthcare systems throughout the world. The numbers of cytology examinations, human papillomavirus (HPV) tests, and women referred for colposcopy decreased in many countries. There have been no reports on cervical cancer screening in Germany. This study aimed to describe changes in the numbers of colposcopies, cytology examinations, HPV tests, and histological results during the pandemic compared to the pre-pandemic years in order to evaluate the impact of the COVID-19 pandemic on cervical cancer screening. PATIENTS AND METHODS: The numbers of colposcopies, cytology examinations, HPV tests, and histologic results were analyzed retrospectively for the period January 2018 to December 2022. The 2 years period before the pandemic (2018 and 2019) were compared with the 3 years period of the pandemic (2020-2022). RESULTS: In total, 6,518 colposcopies were performed in 5,579 women. The numbers of colposcopies, cytology examinations, and high-risk HPV (hrHPV) tests increased during the pandemic years. The number of biopsies per year taken was stable (range=450-554). The relative numbers of cervical intraepithelial neoplasia (CIN) III/HSIL findings were stable, while the numbers of cervical cancers identified increased slightly from 15 (6.6%) in 2018 to 22 (7.4%) in 2022. CONCLUSION: Increases in numbers of women examined and colposcopies were observed in the years 2021 and 2022 during the pandemic, in comparison to the preceding years. These also led to increases in the figures for cytology, hrHPV, histology, and operations. The onset of the pandemic occurred in the same year as a newly organized screening program started in Germany. The increases might therefore be due to the newly organized screening system.
CRIS-Team Scopus Importer:2024-03-15
Keywords: cervical cancer; cervical cancer screening; cervical dysplasia; COVID-19 pandemic; High-grade squamous intraepithelial lesion (HSIL)

Impaired T-bet-pSTAT1? and perforin-mediated immune responses in the tumoral region of lung adenocarcinoma - Andreev, Katerina; Trufa, Denis; Siegemund, Raphaela; Rieker, Ralf; Hartmann, Arndt; Schmidt, Joachim; Sirbu, Horia; Finotto, Susetta (British Journal of Cancer, 2015)
In spite of modern therapies for non-small-cell lung cancer (NSCLC), prognosis for many patients is still poor and survival rates are low. Immunotherapy is the possibility to improve the lung immune response surrounding the tumour. However, this approach requires detailed understanding of the local immune-responses of NSCLC patients.We analysed samples from three different regions within the lungs of NSCLC patients, whereas we distinguished between patients suffering from adenocarcinoma and squamous cell carcinoma. Expression of type 1 T helper (Th1)/type 1 cytotoxic (Tc1) factors was assessed by quantitative real-time PCR, western blot analyses or immunohistochemistry. Cytotoxic cell activity of CD8(+) T cells was determined via co-culture with autologous tumour cells and apoptosis assay.We found decreased levels of the transcription factor T-box expressed in T cells (T-bet or Tbx21) and of the downstream activated IFN-?-dependent pSTAT1? isoform in the lung tumour areas of patients with NSCLC as compared with tumour-free control regions. In these patients, reduced T-bet and pSTAT1? levels were found associated with increased immunosuppressive markers like cytotoxic T lymphocyte-associated protein 4, programmed cell death 1 and with a suppression of the Th1 cell cytokine production and Tc1 cell activity.These findings confirm a central role of T-bet in targeted immunotherapy for patients with NSCLC.
EVALuna2:6728

Impairment of α-tubulin and F-actin interactions of GJB3 induces aneuploidy in urothelial cells and promotes bladder cancer cell invasion - Liu, Junnan; Wang, Xue; Jiang, Wencheng; Azoitei, Anca; Eiseler, Tim; Eckstein, Markus; Hartmann, Arndt; Stilgenbauer, Stephan; Elati, Mohamed; Hohwieler, Meike; Kleger, Alexander; John, Axel; et al. (Cellular & Molecular Biology Letters, 2024)
Background: We have previously identified an unsuspected role for GJB3 showing that the deficiency of this connexin protein induces aneuploidy in human and murine cells and accelerates cell transformation as well as tumor formation in xenograft models. The molecular mechanisms by which loss of GJB3 leads to aneuploidy and cancer initiation and progression remain unsolved. Methods: GJB3 expression levels were determined by RT-qPCR and Western blot. The consequences of GJB3 knockdown on genome instability were assessed by metaphase chromosome counting, multinucleation of cells, by micronuclei formation and by the determination of spindle orientation. Interactions of GJB3 with α-tubulin and F-actin was analyzed by immunoprecipitation and immunocytochemistry. Consequences of GJB3 deficiency on microtubule and actin dynamics were measured by live cell imaging and fluorescence recovery after photobleaching experiments, respectively. Immunohistochemistry was used to determine GJB3 levels on human and murine bladder cancer tissue sections. Bladder cancer in mice was chemically induced by BBN-treatment. Results: We find that GJB3 is highly expressed in the ureter and bladder epithelium, but it is downregulated in invasive bladder cancer cell lines and during tumor progression in both human and mouse bladder cancer. Downregulation of GJB3 expression leads to aneuploidy and genomic instability in karyotypically stable urothelial cells and experimental modulation of GJB3 levels alters the migration and invasive capacity of bladder cancer cell lines. Importantly, GJB3 interacts both with α-tubulin and F-actin. The impairment of these interactions alters the dynamics of these cytoskeletal components and leads to defective spindle orientation. Conclusion: We conclude that deregulated microtubule and actin dynamics have an impact on proper chromosome separation and tumor cell invasion and migration. Consequently, these observations indicate a possible role for GJB3 in the onset and spreading of bladder cancer and demonstrate a molecular link between enhanced aneuploidy and invasive capacity cancer cells during tumor cell dissemination. Graphical Abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-07-12
Keywords: Chromosomal imbalance; Invadopodia; Metastasis; MIBC; Spindle orientation

Implementation of double immune checkpoint blockade increases response rate to induction chemotherapy in head and neck cancer - Semrau, Sabine; Gostian, Antoniu Oreste; Traxdorf, Maximilian; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Hautmann, Matthias; Klautke, Gunther; Laban, Simon; Brunner, Thomas; Tamaskovics, Bálint; et al. (Cancers, 2021)
To determine whether a single dose of double immune checkpoint blockade (induction chemoimmunotherapy (ICIT)) adds benefit to induction single-cycle platinum doublet (induction chemotherapy (IC)) in locally advanced head and neck squamous cell carcinoma (HNSCC), patients treated with cisplatin 30 mg/m2 d1-3 and docetaxel 75 mg/m2 d1 combined with durvalumab 1500 mg fixed dose d5 and tremelimumab 75 mg fixed dose d5 (ICIT) within the CheckRad-CD8 trial were compared with a retrospective cohort receiving the same chemotherapy (IC) without immunotherapy. The endpoint of this analysis was the complete response rate (CR). A total of 53 patients were treated with ICIT and 104 patients with IC only. CR rates were 60.3% for ICIT and 40.3% for IC (p = 0.018). In the total population (n = 157), the most important predictor to achieve a CR was treatment type (OR: 2.21 for ICIT vs. IC; p = 0.038, multivariate analysis). The most diverse effects in CR rates between ICIT and IC were observed in younger (age ≤ 60) patients with HPV-positive OPSCCs (82% vs. 33%, p = 0.176), while there was no difference in older patients without HPV-positive OPSCCs (53% vs. 48%). The analysis provides initial evidence that ICIT could result in higher CR rates than IC. Young patients with HPV-positive OPSCCs may have the greatest benefit from additional immune checkpoint inhibitors.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Combined modality therapy; Double immune checkpoint inhibition; Head and neck neoplasms; HPV-positive OPSCC; Immunotherapy; Induction therapy; Organ preservation

Improved Bladder Tumor RNA Isolation from Archived Tissues Using Methylene Blue for Normalization, Multiplex RNA Hybridization, Sequencing and Subtyping - Köhler, Stefanie; Brandl, Lisa; Strissel, Pamela; Glossner, Laura; Ekici, Arif Bülent; Angeloni, Miriam; Ferrazzi, Fulvia; Bahlinger, Veronika; Hartmann, Arndt; Beckmann, Matthias; Eckstein, Markus; Strick, Reiner (International Journal of Molecular Sciences, 2022)
Methylene blue (MB) is a dye used for histology with clinical importance and intercalates into nucleic acids. After MB staining of formalin fixed paraffin embedded (FFPE) muscle invasive bladder cancer (MIBC) and normal urothelium, specific regions could be microdissected. It is not known if MB influences RNA used for gene expression studies. Therefore, we analyzed MIBC using five different RNA isolation methods comparing patient matched FFPE and fresh frozen (FF) tissues pre-stained with or without MB. We demonstrate a positive impact of MB on RNA integrity with FF tissues using real time PCR with no interference of its chemical properties. FFPE tissues showed no improvement of RNA integrity, which we propose is due to formalin induced nucleotide crosslinks. Using direct multiplex RNA hybridization the best genes for normalization of MIBC and control tissues were identified from 34 reference genes. In addition, 5SrRNA and 5.8SrRNA were distinctive reference genes detecting <200 bp fragments important for mRNA analyses. Using these normalized RNAs from MB stained MIBC and applying multiplex RNA hybridization and mRNA sequencing, a minimal gene expression panel precisely identified luminal and basal MIBC tumor subtypes, important for diagnosis, prognosis and chemotherapy response.
CRIS-Team WoS Importer:2022-09-30

Improved HER2 Tumor Segmentation with Subtype Balancing Using Deep Generative Networks - Öttl, Mathias; Steenpaß, Jana; Rübner, Matthias; Geppert, Carol-Immanuel; Qiu, Jingna; Wilm, Frauke; Hartmann, Arndt; Beckmann, Matthias; Fasching, Peter; Maier, Andreas; Erber, Ramona; Breininger, Katharina (Proceedings - International Symposium on Biomedical Imaging, 2023)
Tumor segmentation in histopathology images is often complicated by its composition of different histological subtypes and class imbalance. Oversampling subtypes with low prevalence features is not a satisfactory solution since it eventually leads to overfitting. We propose to create synthetic images with semantically-conditioned deep generative networks and to combine subtype-balanced synthetic images with the original dataset to achieve better segmentation performance. We show the suitability of Generative Adversarial Networks (GANs) and especially diffusion models to create realistic images based on subtype-conditioning for the use case of HER2-stained histopathology. Additionally, we show the capability of diffusion models to conditionally inpaint HER2 tumor areas with modified subtypes. Combining the original dataset with the same amount of diffusion-generated images increased the tumor Dice score from 0.833 to 0.854 and almost halved the variance between the HER2 subtype recalls. These results create the basis for more reliable automatic HER2 analysis with lower performance variance between individual HER2 subtypes.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Diffusion Models; Generative Models; HER2; Histopathology; Segmentation; Subtypes

Improving detection of carcinoma in situ in bladder cancer: urinary cytology vs the Xpert® BC Monitor - Haas, Maximilian; Kriegmair, Maximilian C.; Breyer, Johannes; Sikic, Danijel; Wezel, Felix; Roghmann, Florian; Brehmer, Mirco; Wirtz, Ralph M.; Jarczyk, Jonas; Erben, Philipp; Bahlinger, Veronika; Goldschmidt, Franziska; et al. (Bju International, 2024)
Objective: To investigate and compare the performance of urinary cytology and the Xpert BC Monitor test in the detection of bladder cancer in various clinically significant patient cohorts, including patients with carcinoma in situ (CIS), in a prospective multicentre setting, aiming to identify potential applications in clinical practice. Patients and Methods: A total of 756 patients scheduled for transurethral resection of bladder tumour (TURBT) were prospectively screened between July 2018 and December 2020 at six German University Centres. Central urinary cytology and Xpert BC Monitor tests were performed prior to TURBT. The diagnostic performance of urinary cytology and the Xpert BC Monitor was evaluated according to sensitivity (SN), specificity (SC), negative predictive value (NPV) and positive predictive value (PPV). Statistical comparison of urinary cytology and the Xpert BC Monitor was conducted using the McNemar test. Results: Of 756 screened patients, 733 (568 male [78%]; median [interquartile range] age 72 [62–79] years) were included. Bladder cancer was present in 482 patients (65.8%) with 258 (53.5%) high-grade tumours. Overall SN, SC, NPV and PPV were 39%, 93%, 44% and 92% for urinary cytology, and 75%, 69%, 59% and 82% for the Xpert BC Monitor. In patients with CIS (concomitant or solitary), SN, SC, NPV and PPV were 59%, 93%, 87% and 50% for urinary cytology, and 90%, 69%, 95% and 50% for the Xpert BC Monitor. The Xpert BC Monitor missed four tumours (NPV = 98%) in patients with solitary CIS, while potentially avoiding 63.3% of TURBTs in inconclusive or negative cystoscopy and a negative Xpert result. Conclusion: Positive urinary cytology may indicate bladder cancer and should be taken seriously. The Xpert BC Monitor may represent a useful diagnostic tool for correctly identifying patients with solitary CIS and unsuspicious or inconclusive cystoscopy.
CRIS-Team Scopus Importer:2024-05-17
Keywords: bladder cancer; carcinoma in situ; cytology; NMIBC; urine marker; Xpert

Inactivating Mutations of RB1 and TP53 Correlate With Sarcomatous Histomorphology and Metastasis/Recurrence in Gastrointestinal Stromal Tumors - Merten, Larissa; Agaimy, Abbas; Moskalev, Evgeny; Giedl, Josef; Kayser, Claudia; Geddert, Helene; Schaefer, Inga-Marie; Cameron, Silke; Werner, Martin; Stroebel, Philip; Hartmann, Arndt; Haller, Florian (American Journal of Clinical Pathology, 2016)
Loss-of-function mutations in TP53 and CDKN2A have been found at varying frequencies in gastrointestinal stromal tumors (GISTs), while no mutations of RB1 have been reported to date. The aim of the current study was to determine the mutation frequency of TP53, RB1, and CDKN2A in GISTs.A cohort of 83 primary untreated GISTs was analyzed for mutations in TP53, RB1, and CDKN2A by massive parallel sequencing. Tumors with mutations in TP53 and RB1 were analyzed by fluorescence in situ hybridization for the corresponding gene loci.Two GISTs harbored inactivating mutations in RB1, and two other GISTs displayed inactivating mutations in TP53 All four tumors were KIT mutant high-risk tumors with highly cellular sarcomatous histomorphology and variable combinations of plump spindle cells to epithelioid highly atypical cells and high mitotic activity. Three of these patients developed recurrent or metastatic disease, while the fourth patient showed tumor rupture intraoperatively. The combined overall frequency of TP53 and RB1 mutations was 13% considering high-risk or malignant GISTs.TP53 and RB1 mutations seem to be restricted to high-risk/malignant GISTs and occur at an equal although relatively low frequency.
EVALuna2:6897

Increased angiogenesis and FGFR protein expression indicate a favourable prognosis in bladder cancer - Bertz, Simone; Abee, Christine; Schwarz-Furlan, Stephan; Alfer, Joachim; Hofstaedter, Ferdinand; Stoehr, Robert; Hartmann, Arndt; Gaumann, Andreas K. A. (Virchows Archiv, 2014)
Compared to other members of the fibroblast growth factor receptor (FGFR) family, only few studies investigate FGFR3 in tumour angiogenesis. We investigated the connection between angiogenesis and FGF/FGFR expression including FGFR3 mutation status in urothelial carcinomas. Immunohistochemistry was performed in invasive and non-invasive urothelial cancers of 61 patients. Protein expression of CD31, factor VIII (FVIII), FGF-1/2, FGFR1, FGFR3 and FGFR4 and FGFR3 mutation status were evaluated. Morphometric assessment of angiogenesis including microvessel count (MVC) and vascular surface area (VSA) was analysed. Correlation and survival analyses (overall survival (OS) and disease-free survival (DFS)) with univariate and multivariate analyses were performed. CD31 values (MVC and VSA) significantly correlated with OS and DFS. OS and DFS were significantly better in patients with FGFR3 overexpression. Multivariate analysis revealed FGFR3 protein expression and tumour grading (WHO classification 2004) as independent prognostic factors of OS and VSA of CD31 and FGFR3 protein expression of DFS. FGFR3 mutation status was correlated with VSA measured by FVIII. FGFR3 may be able to induce a pro-angiogenic phenotype in urothelial carcinomas and significantly influence prognosis. Consequently, FGFR3 is a potential therapeutic target also from the angiogenesis perspective.
EVALuna2:6661

Increased expression of c-Jun in nonalcoholic fatty liver disease - Dorn, Christoph; Engelmann, Julia C.; Saugspier, Michael; Koch, Andreas; Hartmann, Arndt; Mueller, Martina; Spang, Rainer; Bosserhoff, Anja; Hellerbrand, Claus (Laboratory Investigation, 2014)
Overnutrition is the major cause of nonalcoholic fatty liver disease (NAFLD) and its advanced form nonalcoholic steatohepatitis (NASH). We aimed to develop and characterize a murine model, which resembles both the pathology and nutritional situation, of NASH patients in Western societies. Mice were fed with a NASH-inducing diet (ND) containing sucrose, cholesterol and fats rich in saturated fatty acids in a composition, which mimics Western food. After 12 weeks, ND-fed mice revealed obesity and impaired glucose tolerance. In the liver, ND-feeding led to marked steatosis, hepatocellular damage, inflammation and beginning fibrosis. Transcriptome-wide gene expression analysis and search for over-represented transcription factor target sites among the differentially expressed genes identified activator protein-1 (AP-1) as the most likely factor to cause the transcriptional changes in ND livers. Combining differentially expressed gene and protein-protein interaction network analysis identified c-Jun as hub in the largest connected deregulated sub-network in ND livers. Accordingly, ND livers revealed c-Jun-phosphorylation and nuclear translocation. Moreover, hepatic c-Jun expression was enhanced in ND-fed mice. Combined tissue microarray technology and immunohistochemical analysis confirmed enhanced hepatic c-Jun levels in NAFLD patients, which correlated with inflammation, and notably, with the degree of hepatic steatosis. In summary, our new mouse model shows important pathological changes also found in human NASH and indicates c-Jun/AP-1 activation as critical regulator of hepatic alterations. Abundance of c-Jun in NAFLD likely facilitates development and progression of NASH.
EVALuna2:6603

Increased expression of OLFM4 and lysozyme during necrotizing enterocolitis in neonates: an observational research study - Diez, Sonja; Renner, Marcus; Bahlinger, Veronika; Hartmann, Arndt; Besendörfer, Manuel; Müller, Hanna (BMC Pediatrics, 2022)
Background: In neonatal patients with necrotizing enterocolitis (NEC) the inflammatory response is mediated by a plurality of different proteins. The proteins olfactomedin 4 (OLFM4) and lysozyme (LYZ) are part of the intestinal mucosal defense and especially OLFM4 has rarely been evaluated in neonatal gastrointestinal diseases. The aim of this study was to analyze whether expression levels of both proteins of innate immunity, OLFM4 and lysozyme, were increased during NEC in neonates. Methods: Intestinal tissues of patients with NEC were examined with immunohistochemical staining of formalin-fixed and paraffin-embedded sections of resected tissue using antibodies against OLFM4 and lysozyme. Staining-positive tissues were semi-quantitatively scored from 0 (no staining), 1 (weak staining), 2 (moderate staining) to 3 (highly intense staining) by two individual investigators. Intestinal tissue of infants with volvulus was used as a control as other intestinal tissue without major inflammation was not available. Results: Both applied antibodies against OLFM4 showed different staining patterns with higher staining intensity of the antibody OLFM4 (D1E4M). OLFM4 (median score of the antibody OLFM4 (D1E4M): 3.0) and lysozyme (median score: 3.0) are highly expressed in intestinal and immune cells during NEC. Expression of OLFM4 and lysozyme in the control samples with volvulus was observable but significantly lower (median score of the antibody OLFM4 (D1E4M): 1.25; median score of the antibody against LYZ: 2.0; p = 0.033 and p = 0.037, respectively). Conclusions: Both proteins, OLFM4 and lysozyme, may play a role in the pathogenesis of NEC in neonatal patients, but the exact mechanisms of OLFM4 and lysozyme function and their role in immunological responses have not yet been resolved in detail. These observations add new insights as basis for further large-scale population research.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Inflammation; Lysozyme; Necrotizing enterocolitis; Neonatal gastrointestinal diseases; OLFM4

Increased expression of the Th17-IL-6R/pSTAT3/BATF/Ror?T-axis in the tumoural region of adenocarcinoma as compared to squamous cell carcinoma of the lung - Balabko, Liubov; Andreev, Katerina; Burmann, Nadine; Schubert, Melanie; Mathews, Martina; Trufa, Denis; Reppert, Sarah; Rau, Tilmann; Schicht, Martin; Sirbu, Horia; Hartmann, Arndt; Finotto, Susetta (Scientific Reports, 2014)
Here we describe increased expression of IL6R in the tumoural region of lung tissue from patients affected by lung adenocarcinoma as compared to squamous cell lung carcinoma. Moreover, here we found increased IL6R in the tumour free part of the lung. By using a murine model of lung adenocarcinoma, we discovered that few lung tumour cells expressed IL-6R and CD4+CD25+Foxp-3+ T regulatory cells down-regulated IL-6R in the tumour bearing lungs. Downstream of IL-6R, the Th17 lineage-specification factors: Signal transducer and activator of transcription 3 (STAT3), Basic leucine zipper transcription factor, BATF and a protein encoded by the RORC in human (RAR-related orphan receptor C) (ROR?T), were also found induced in the tumoural region of lung tissue from patients affected by lung adenocarcinoma as compared to those carrying squamous cell carcinoma. Moreover, pSTAT3 protein was found phosphorylated and auto-phosphorylated in the tumoural region of patients with adeno cell carcinoma of the lung as compared to the tumoural region of patients with squamous cell carcinoma of the lung. Intranasal application of anti-IL-6R antibodies in a murine model of lung adenocarcinoma, induced T regulatory cell markers such as Foxp3, Ctla4, Icos, Il10, Il21, Folr4 and Lag3 and inhibited Rorc in lung adenocarcinoma.
EVALuna2:4416

Increased Proliferation as Independent Predictor of Disease Recurrence in Initial Stage pTa Urothelial Bladder Cancer - Breyer, Johannes; Shalekenov, Sanzhar; Aziz, Atiqullah; Van Rhijn, Bastiaan W. G.; Bruendl, Johannes; Lausenmeyer, Eva; Schaefer, Julius; Denzinger, Stefan; Giedl, Christian; Burger, Maximilian; Hartmann, Arndt; Evert, Matthias; et al. (Bladder Cancer, 2017)
OBJECTIVES: To investigate the predictive impact of the proliferation biomarker Ki-67 on the clinical course of patients with initial stage pTa urothelial carcinoma of the bladder (UCB). METHODS: We retrospectively analyzed all patients treated by transurethral resection of bladder tumors (TUR-B) for UCB between 1992-2004 in a single-center. Disease recurrence (≥pTa UCB) and absent tumor in histopathology, assessed by TUR-B with a non-malignant result for endoscopic suspect bladder lesion displayed endpoints. Immunohistochemical (IHC) analysis of formalin-fixed and paraffin-embedded tissue blocks was performed with an immunostainer using a primary antibody for Ki-67. Semiquantitative evaluation of Ki-67 was performed by three reviewers. Increased proliferation was defined with a cut-off value of ≥50%. Uni- and multivariable binary regression analyses were applied to address prediction of disease recurrence. RESULTS: 215 patients (84% male, median age 69 years at first diagnosis) were evaluable and included to the study. 89 patients stayed disease-free (41%), 126 patients showed recurrence (59%). Recurrence rates of patients with Ki-67 expression <10%, 10-24%, 25-49% and ≥50% were 14.8% vs. 30.8% vs. 63.9% and 80.7%, respectively (p < 0.001). In Kaplan-Meier analysis patients with increased proliferation ≥50% showed a statistically significant worse 10-year recurrence-free survival (19% vs. 57%, p < 0.001). Multivariable regression analysis revealed instillation treatment (p = 0.001) and high proliferation of Ki-67 (p < 0.001) to be independent predictors of recurrence in stage pTa UCB. CONCLUSIONS: High proliferation with Ki-67 expression ≥50% was strongly associated with worse recurrence-free survival in patients with initial stage pTa UCB. Stage pTa UCB patients with increased Ki-67 expression should undergo a strictly follow-up regime comparable to stage pT1 bladder carcinoma, while at least patients with Ki-67 expression <10% might be feasible for more liberate follow-up regime after evaluation of our data in randomized, prospective and multicenter studies.
EVALuna2:34255

Increasing Biomarker Guidance in the Treatment of Urothelial Carcinoma: Systematic Review of International Clinical Trials - Bolenz, Christian; Kunath, Frank; Zengerling, Friedemann; Wezel, Felix; Schmidt, Stefanie; Hartmann, Arndt; Eckstein, Markus (Urologia Internationalis, 2023)
Purpose: Precision oncology requires biomarker testing from tumor tissue for clinical decision-making and selection of targeted therapies. We systematically evaluated the role of tissue biomarker testing within interventional clinical trials for locally advanced and metastatic urothelial carcinoma (UC). Methods: A systematic search within the publicly available ClinicalTrials.gov database was performed for the period 1995 to January 2020. We searched for all interventional studies on systemic treatments for advanced UC. Two investigators independently screened the records and extracted the data for statistical analyses. Results: We included 356 studies out of 827 initial records in the final analysis. The overall number of interventional trials in UC patients significantly increased during the past 25 years. Forty-three studies (12.1%) required specific biomarker testing as a prerequisite for inclusion. Of the remaining 313 trials, explorative biomarkers of interest were studied in 83 studies (23.3%). In trials with obligate biomarker testing as a precondition for study inclusion, only 3 studies (7%) required an actual fresh pretreatment biopsy, while the majority of studies did not state any tissue requirements (55.8%) or accepted archival tissue samples (37.3%). Among studies without biomarker prerequisites, freshly obtained tissue samples were required in 16.3% of studies evaluating immune checkpoint inhibition and 5.7% evaluating targeted therapy. The collection of archival tissue was allowed in 67.4% and 20% of studies evaluating immune checkpoint inhibitors and targeted therapies, respectively. Conclusion: There has been an increase in the number of studies using biomarker-guided interventions for the treatment of advanced UC over the past 25 years. Studies investigating druggable targets in actual UC biopsies immediately before treatment are still rare. Standardized criteria for tissue-based biomarker testing may further accelerate personalized treatment of patients with advanced UC.
CRIS-Team WoS Importer:2023-02-03

Individual dynamics of uterine natural killer cells in natural and stimulated cycles monitored using a new endometrial dating method - Alfer, Joachim; Fattahi, Amir; Bleisinger, Nathalie; Antoniadis, Sophia; Krieg, Jurgen; Dittrich, Ralf; Beckmann, Matthias; Hartmann, Arndt; Popovici, Roxana M.; Tremellen, Kelton (American Journal of Reproductive Immunology, 2022)
Problem It is important to evaluate the dynamics of uterine natural killer (uNK) cells in hormone replacement therapy (HRT) cycles, given their potential role in implantation and the common usage of HRT cycles with in vitro fertilization (IVF). Method of study A total of 132 subfertile patients were evaluated during the secretory phase of either natural ovulation (OV) or HRT cycles, with two biopsies taken on approximately days 5 and 10 after ovulation/progesterone administration in a single menstrual cycle. Immunohistochemical Personal Endometrial Maturation Analysis (PEMA) was used to better quantify secretory-phase endometrial development, in combination with subsequent evaluation of uNK cell density. Results uNK cell density increased rapidly from the early to mid-secretory phase, with mean uNK densities of 113 and 117 per mm(2) in first biopsies and 315 and 387 per mm(2) in second biopsies for OV and HRT cycles, respectively. After reassessment of endometrial development with PEMA, the first and second biopsies in HRT and OV cycles were histologically dated to developmental ranges between days 15-20 (first biopsy) and days 19-25 (second biopsy). Conclusion Subfertile women showed variable endometrial development in PEMA assessment, with uNK cell density correlating with the dating results. Overall, comparable levels of uNK cell density were observed in OV and HRT cycles. Importantly, uNK cell density depends on the histological maturation stage, with similar low coefficients of determination. This observation suggests that aberrant uNK cell results more likely reflect displaced endometrial maturation, rather than an intrinsic anomaly in uNK cell trafficking.
CRIS-Team WoS Importer:2022-09-30

Induction chemoimmunotherapy followed by CD8+ immune cell-based patient selection for chemotherapy-free radioimmunotherapy in locally advanced head and neck cancer - Hecht, Markus; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Klautke, Gunther; Laban, Simon; Hautmann, Matthias Günther; Brunner, Thomas B.; Tamaskovics, Bálint; Hinke, Axel; Zhou, Jianguo; et al. (Journal for ImmunoTherapy of Cancer, 2022)
Purpose The first aim of the trial is to study feasibility of combined programmed death protein ligand 1/cytotoxic T-lymphocyte-associated protein 4 inhibition concomitant to radiotherapy. In addition, efficacy of the entire treatment scheme consisting of induction chemoimmunotherapy followed by chemotherapy-free radioimmunotherapy (RIT) after intratumoral CD8 +immune cell-based patient selection will be analyzed. Methods Patients with stage III-IVB head and neck squamous cell carcinoma were eligible for this multicenter phase II trial. Treatment consisted of a single cycle of cisplatin 30 mg/m² days 1-3, docetaxel 75 mg/m² day 1, durvalumab 1500 mg fix dose day 5 and tremelimumab 75 mg fix dose day 5. Patients with increased intratumoral CD8 +immune cell density or pathological complete response (pCR) in the rebiopsy entered RIT up to a total dose of 70 Gy. Patients received further three cycles of durvalumab/tremelimumab followed by eight cycles of durvalumab mono (every 4 weeks). The intended treatment for patients not meeting these criteria was standard radiochemotherapy outside the trial. Primary endpoint was a feasibility rate of patients entering RIT to receive treatment until at least cycle 6 of immunotherapy of ≥80%. Results Between September 2018 and May 2020, 80 patients were enrolled (one excluded). Out of these, 23 patients had human papilloma virus (HPV)-positive oropharyngeal cancer. Median follow-up was 17.2 months. After induction chemoimmunotherapy 41 patients had pCR and 31 had increased intratumoral CD8 +immune cells. Of 60 patients entering RIT (primary endpoint cohort), 10 experienced imiting toxic (mainly hepatitis) and four discontinued for other reasons, resulting in a feasibility rate of 82%. The RIT cohort (n=60) had a progression-free survival (PFS) rate at one and 2 years of 78% and 72%, respectively, and an overall survival rate at one and 2 years of 90% and 84%, respectively. Patients with HPV-positive oropharyngeal cancers had greater benefit from RIT with a 2-year PFS rate of 94% compared with 64% for HPV-negative oropharyngeal cancers and other locations. In the entire study cohort (n=79) the 2-year PFS rate was 68% (91% for HPV-positive oropharynx vs 59% for others). Toxicity grade 3-4 mainly consisted of dysphagia (53%), leukopenia (52%) and infections (32%). Conclusions The trial met the primary endpoint feasibility of RIT. Induction chemo-immunotherapy followed by chemotherapy-free RIT after intratumoral CD8 +immune cell-based patient selection has promising PFS. Trial registration number The trial was registered with ClinicalTrials.gov (identifier: NCT03426657). The trial was conducted as investigator-sponsored trial (IST).
CRIS-Team Scopus Importer:2022-02-11
Keywords: radioimmunotherapy

Induction of pulmonary HLA-G expression by SARS-CoV-2 infection - Seliger, Barbara; Jasinski-Bergner, Simon; Massa, Chiara; Mueller, Anja; Biehl, Katharina; Yang, Bo; Bachmann, Michael; Jonigk, Danny; Eichhorn, Philip; Hartmann, Arndt; Wickenhauser, Claudia; Bauer, Marcus (Cellular and Molecular Life Sciences, 2022)
The non-classical human leukocyte antigen (HLA)-G exerts immune-suppressive properties modulating both NK and T cell responses. While it is physiologically expressed at the maternal-fetal interface and in immune-privileged organs, HLA-G expression is found in tumors and in virus-infected cells. So far, there exists little information about the role of HLA-G and its interplay with immune cells in biopsies, surgical specimen or autopsy tissues of lung, kidney and/or heart muscle from SARS-CoV-2-infected patients compared to control tissues. Heterogeneous, but higher HLA-G protein expression levels were detected in lung alveolar epithelial cells of SARS-CoV-2-infected patients compared to lung epithelial cells from influenza-infected patients, but not in other organs or lung epithelia from non-viral-infected patients, which was not accompanied by high levels of SARS-CoV-2 nucleocapsid antigen and spike protein, but inversely correlated to the HLA-G-specific miRNA expression. High HLA-G expression levels not only in SARS-CoV-2-, but also in influenza-infected lung tissues were associated with a high frequency of tissue-infiltrating immune cells, but low numbers of CD8(+) cells and an altered expression of hyperactivation and exhaustion markers in the lung epithelia combined with changes in the spatial distribution of macrophages and T cells. Thus, our data provide evidence for an involvement of HLA-G and HLA-G-specific miRNAs in immune escape and as suitable therapeutic targets for the treatment of SARS-CoV-2 infections.
CRIS-Team WoS Importer:2022-11-18

Inflammatory biomarkers and bladder cancer prognosis: a systematic review - Masson-Lecomte, Alexandra; Rava, Marta; Real, Francisco X.; Hartmann, Arndt; Allory, Yves; Malats, Nuria (European Urology, 2014)
Host immune response has an impact on tumour development and progression. There is interest in the use of inflammatory biomarkers (InfBMs) in cancer care. Although several studies assessing the potential prognostic value of InfBMs in cancer have been published in the past decades, they have had no impact on the management of patients with urothelial bladder carcinoma (UBC).To review and summarise the scientific literature on the prognostic value of tumour, serum, urine, and germline DNA InfBMs on UBC.A systematic review of the literature was performed searching the Medline and Embase databases for original articles published between January 1975 and November 2013. The main inclusion criterion was the provision of a survival analysis (Kaplan-Meier and/or Cox) according to the Reporting Recommendations for Tumor Marker Prognostic Studies guidelines for the assessment of prognostic markers. We focused on markers assessed at least twice in the literature. Findings are reported following Preferred Reporting Items for Systematic Reviews and Meta-analysis guidelines.Overall, 34 publications, mostly retrospective, fulfilled the main inclusion criterion. Main limitations of these studies were missing relevant information about design or analysis and heterogeneous methodology used. Inflammatory cells, costimulatory molecules in tumour cells, and serum cytokines showed prognostic significance, mainly in univariable analyses. High C-reactive protein values were consistently reported as an independent prognostic factor for mortality in invasive UBC.There is a dearth of studies on InfBMs in UBC compared with other tumour types. Evidence suggests that InfBMs may have an impact on the management of patients with UBC. Currently, methodological drawbacks of the studies limit the translational potential of results.In this review, we analysed studies evaluating the impact of inflammatory response on bladder cancer progression. Despite methodological limitations, some inflammatory biomarkers should be further analysed because they hold promise to improve patient care.
EVALuna2:6672

Influence of Family History of Breast or Ovarian Cancer on Pathological Complete Response and Long-Term Prognosis in Breast Cancer Patients Treated with Neoadjuvant Chemotherapy - Wunderle, Marius; Häberle, Lothar; Hein, Alexander; Jud, Sebastian; Lux, Michael P.; Hack, Carolin; Emons, Julius; Heindl, Felix; Nabieva, Naiba; Löhberg, Christian; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; et al. (Breast Care, 2020)
Purpose: In breast cancer, a pathological complete response (pCR) has been described as generally resulting in a favorable prognosis. However, there are subgroups, such as patients with a mutation in BRCA1 or BRCA2,in which the effect of pCR on the prognosis is suspected to be weaker. Patients with a family history of breast and/or ovarian cancer may therefore react differently in relation to pCR and prognosis, and this is investigated in this study. Patients and Methods: Breast cancer patients were identified from a clinical breast cancer registry. The study subjects had been treated with neoadjuvant chemotherapy from 2001 to 2018 and their pathological and clinical information as well as medical family history were available. They were considered to have a positive family history if they had at least 1 first-degree relative with breast and/or ovarian cancer. Multivariate logistic regression analyses were performed to study the association between family history, pCR (ypT0; ypN0), and disease-free survival (DFS). Results: Of 1,480 patients, 228 (15.4%) had a positive family history. The pCR rates were 24.9% in all patients, and 24.4% and 27.6% in those without/with a family history, respectively. Family history was not associated with a higher pCR rate (adjusted odds ratio [OR] 1.23; 95% confidence interval [CI] 0.85-1.76; p = 0.27) or a different disease-free survival (DFS; adjusted hazard ratio [HR] 1.15; 95% CI 0.88-1.52; p = 0.30). pCR did not affect the prognosis differently in relation to family history. Conclusions: In this retrospective analysis, family history was not associated with pCR and DFS. pCR improved survival, independently of family history.
CRIS-Team Scopus Importer:2020-07-24
Keywords: Breast cancer; Family history; Neoadjuvant chemotherapy; Ovarian cancer; Pathological complete response; Prognosis

Influence of the Family Anamnesis of Breast or Ovarian Cancer on the pathological Complete Remission and the Prognosis in Patients with Breast Cancer after neoadjuvant Chemotherapy - Gaß, Paul; Haberle, L.; Hein, Alexander; Jud, Sebastian; Lux, M. P.; Hack, Caroline; Emons, J.; Heindl, Felix; Nabieva, Naiba; Löhberg, Christian; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Inhibition of integrin αvβ6 sparks T-cell antitumor response and enhances immune checkpoint blockade therapy in colorectal cancer - Busenhart, Philipp; Montalban-Arques, Ana; Katkeviciute, Egle; Morsy, Yasser; Van Passen, Chiara; Hering, Larissa; Atrott, Kirstin; Lang, Silvia; Garzon, Jesus Francisco Glaus; Naschberger, Elisabeth; Hartmann, Arndt; Rogler, Gerhard; et al. (Journal for ImmunoTherapy of Cancer, 2022)
Background Integrin αvβ6 is a heterodimeric cell surface protein whose cellular expression is determined by the availability of the integrin β6 subunit (ITGB6). It is expressed at very low levels in most organs during tissue homeostasis but shows highly upregulated expression during the process of tumorigenesis in many cancers of epithelial origin. Notably, enhanced expression of integrin αvβ6 is associated with aggressive disease and poor prognosis in numerous carcinoma entities. Integrin αvβ6 is one of the major physiological activators of transforming growth factor-β (TGF-β), which has been shown to inhibit the antitumor T-cell response and cause resistance to immunotherapy in mouse models of colorectal and mammary cancer. In this study, we investigated the effect of ITGB6 expression and antibody-mediated integrin αvβ6 inhibition on the tumor immune response in colorectal cancer. Methods Using orthotopic and heterotopic tumor cell injection, we assessed the effect of ITGB6 on tumor growth and tumor immune response in wild type mice, mice with defective TGF-β signaling, and mice treated with anti-integrin αvβ6 antibodies. To examine the effect of ITGB6 in human colorectal cancer, we analyzed RNAseq data from the colon adenocarcinoma dataset of The Cancer Genome Atlas (TCGA-COAD). Results We demonstrate that expression of ITGB6 is an immune evasion strategy in colorectal cancer, causing inhibition of the antitumor immune response and resistance to immune checkpoint blockade therapy by activating latent TGF-β. Antibody-mediated inhibition of integrin αvβ6 sparked a potent cytotoxic T-cell response and overcame resistance to programmed cell death protein 1 (PD-1) blockade therapy in ITGB6 expressing tumors, provoking a drastic increase in anti-PD-1 treatment efficacy. Further, we show that the majority of tumors in patients with colorectal cancer express sufficient ITGB6 to provoke inhibition of the cytotoxic T-cell response, indicating that most patients could benefit from integrin αvβ6 blockade therapy. Conclusions These findings propose inhibition of integrin αvβ6 as a promising new therapy for colorectal cancer, which blocks tumor-promoting TGF-β activation, prevents tumor exclusion of cytotoxic T-cells and enhances the efficacy of immune checkpoint blockade therapy.
CRIS-Team Scopus Importer:2022-02-25
Keywords: CD8-positive T-lymphocytes; cytotoxicity; drug evaluation; immunologic; immunotherapy; preclinical; tumor microenvironment

Initial clinical results with a fusion prototype for mammography and three-dimensional ultrasound with a standard mammography system and a standard ultrasound probe - Emons, Julius; Wunderle, Marius; Hartmann, Arndt; Radicke, Marcus; Rauh, Claudia; Uder, Michael; Gaß, Paul; Fasching, Peter; Langemann, Hanna; Beckmann, Matthias; Schulz-Wendtland, Rüdiger; Jud, Sebastian (Acta Radiologica, 2018)
BACKGROUND: Combinations *Equal contributors. of different imaging techniques in fusion devices appear to be associated with improvements in diagnostic assessment. PURPOSE: The aim of this study was to test the feasibility of using an automated standard three-dimensional (3D) ultrasound (US) device fused with standard mammography for the first time in breast cancer patients. MATERIAL AND METHODS: Digital mammograms and 3D automated US images were obtained in 23 patients with highly suspicious breast lesions. A recently developed fusion machine consisting of an ABVS 3D US transducer from an Acuson S2000 machine and a conventional Mammomat Inspiration device (both Siemens Healthcare GmbH, Erlangen, Germany) were used for the purpose. The feasibility of the examinations, imaging coverage, and patients' experience of the procedure were examined. RESULTS: In 15 out of 19 patients, the region of interest (ROI) with the tumor marked in the mammogram was visible on US. The examination was experienced positively by the patients, with no unexpected pain or injury. The examination was time-saving and well tolerated. CONCLUSION: In conclusion, we have shown initial clinical feasibility of an US/radiography fusion prototype with good localization and evaluation of the ROIs. The combined examination was well tolerated. The simultaneous evaluation with mammography and US imaging may be able to improve detection and reduce examiner-related variability.
EVALuna2:34810

In stage pT1 non-muscle-invasive bladder cancer (NMIBC), high KRT20 and low KRT5 mRNA expression identify the luminal subtype and predict recurrence and survival - Breyer, Johannes; Wirtz, Ralph M.; Otto, Wolfgang; Erben, Philipp; Kriegmair, Maximilian C.; Stoehr, Robert; Eckstein, Markus; Eidt, Sebastian; Denzinger, Stefan; Burger, Maximilian; Hartmann, Arndt (Virchows Archiv, 2017)
Differential expression of cytokeratins (CK) is a characteristic feature of chemoresistant luminal (KRT20) and chemosensitive intrinsic aggressive basal (KRT5) subtypes in muscle-invasive bladder cancer (MIBC). We investigated mRNA expression of KRT5 and KRT20 and its predictive value in stage pT1 bladder cancer. In retrospective analysis of clinical data and formalin-fixed paraffin-embedded tissues (FFPE) of patients with stage pT1 NMIBC who underwent transurethral resection of the bladder, a single-step RT-qPCR was used to measure mRNA expression. Furthermore, immunohistochemical (IHC) staining of CK20, panCK, and MIB1 was performed. Valid measurements were obtained from 231 samples out of a series of 284 patients. Spearman correlation revealed significant associations between mRNA and protein expression of KRT20/CK20 (? 0.6096, p < 0.0001) and MKI67/MIB1 (? 0.5467, p < 0.0001). A positive correlation was found between MKI67 and KRT20 expression (? 0.3492, p < 0.0001), while MKI67 and KRT5 were negatively correlated (? -0.1693, p = 0.01). High KRT20 expression (>=40.26) was significantly associated with worse recurrence free survival (RFS) (p = 0.001), progression-free survival (PFS) (p = 0.0003), and cancer specific survival (CSS) (p = 0.0414). The combination of high KRT20 expression and low KRT5 expression (<36.83) was associated with unfavorable RFS (p = 0.0038) and PFS (p = 0.0003) and proved to be the only independent predictor for RFS (p = 0.0055) and PFS (p = 0.0023) in multivariate analysis. KRT20 mRNA determination was superior to CK20 protein estimation with regard to RFS and PFS prediction. KRT20 and KRT5 mRNA quantification can predict recurrence and progression of stage pT1 NMIBC reflecting basal and luminal subtypes of MIBC and is superior to CK20 protein expression determined by IHC.
EVALuna2:6880

Insufficient Angiogenesis: Cause of Abnormally Thin Endometrium in Subfertile Patients? - Alfer, Joachim; Happel, Lars; Dittrich, Ralf; Beckmann, Matthias; Hartmann, Arndt; Gaumann, Andreas; Buck, Volker U.; Classen-Linke, Irmgard (Geburtshilfe und Frauenheilkunde, 2017)
This study investigated subfertile patients with abnormally thin endometrium after infertility treatment. As they had adequate serum concentrations of hormones, an endometrial factor for subfertility was suspected.To elucidate the cause of subfertility, endometrial biopsies were taken in each patient in the late proliferative and mid-secretory phases of one menstrual cycle. Endometrial biopsies from women with normal menstrual cycles and confirmed fertility who were undergoing hysterectomy for benign uterine disease were used as positive controls. The tissue samples were investigated for steroid hormone receptor expression and for the proliferation marker Ki-67. Immunohistochemistry was performed with antibodies against the marker molecules for endometrial receptivity - ? 3 integrin, VEGF, LIF, and CD56 (large granular lymphocytes, LGLs).The steroid hormone receptors for estrogen (E2) and progesterone (P) were expressed normally (at the first biopsy) and were down-regulated (at the second biopsy) within the cycle. Strikingly, all of the marker molecules investigated showed negative or weak and inadequate expression in the mid-secretory phase. Numbers of LGLs remained as low as in the proliferative phase. In contrast, fertile patients were found to express these marker molecules distinctly in the mid-secretory phase.It may be hypothesized that a severe deficiency of these angiogenesis-related marker molecules leads to defective development of the endometrium, which remains thin. Deficient angiogenetic development may thus provide an explanation for the endometrial factor that causes infertility. Further investigations will need to focus on identifying the regulating factors that act between steroid receptor activation and the expression of these marker molecules.
EVALuna2:6870

Integrated Analysis of PTEN and p4EBP1 Protein Expression as Predictors for pCR in HER2-Positive Breast Cancer - Loibl, Sibylle; Darb-Esfahani, Silvia; Huober, Jens; Klimowicz, Alexander; Furlanetto, Jenny; Lederer, Bianca; Hartmann, Arndt; Eidtmann, Holger; Pfitzner, Berit; Fasching, Peter; Tiemann, Katharina; Jackisch, Christian; et al. (Clinical Cancer Research, 2016)
The PI3K/AKT pathway and phosphatase and tensin homolog (PTEN) aberrations are common in breast cancer. We investigated the correlation between phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA), PTEN, p4EBP1 (phosphorylated E4 binding protein 1), and pathologic complete response (pCR) in patients receiving neoadjuvant therapy.We retrospectively evaluated PIK3CA, PTEN, and p4EBP1 protein expression in centrally HER2-positive patients (n = 181) who received epirubicin cyclophosphamide/trastuzumab followed by docetaxel/trastuzumab alone or concomitant/followed by capecitabine within the GeparQuattro study. PTEN was assessed using the automated quantitative immunofluorescence analysis and was analyzed as a dichotomic variable. p4EBP1 was assessed by immunohistochemistry and used as a continuous and dichotomic variable.p4EBP1 was available from 137, PTEN from 108, and PIK3CA genotype from 83 patients. Overall, the pCR rate in PTEN-low tumors was 27.6%, and in PTEN-high tumors, it was 57.1% (P = 0.010). pCR rates were not statistically different between PIK3CA wild-type and mutant (35% vs. 22%) or p4EBP1 IRS <= 4 and IRS > 4 (39% vs. 33%). pCR rate was 57.1% (8/14) in PTEN-high/PIK3CA wild-type and decreased to 15.4% in PTEN-low/PIK3CA-mutant tumors (P = 0.023). In multivariable analysis adjusted for baseline parameters, PTEN independently predicted pCR in the following cohorts: overall [OR, 7.54; 95% confidence interval (CI), 2.03-28.06; P = 0.003], PIK3CA wild-type (OR, 23.81; 95% CI, 1.75-324.05; P = 0.017), p4EBP1 IRS > 4 (OR, 11.53; 95% CI, 1.84-72.24; P = 0.009), and hormone receptor-positive (OR, 40.91; 95% CI, 2.93-570.44; P = 0.006). p4EBP1 was independently predictive for pCR in PIK3CA wild-type tumors (OR, 0.14; 95% CI, 0.03-0.78; P = 0.025).The study showed the potential role of PIK3CA genotype, PTEN, and p4EBP in predicting pCR after anthracycline-taxane-based chemotherapy and anti-HER2 treatment. Clin Cancer Res; 22(11); 2675-83. ©2016 AACR.
EVALuna2:6794

Integration of spatial pd-l1 expression with the tumor immune microenvironment outperforms standard pd-l1 scoring in outcome prediction of urothelial cancer patients - Weyerer, Veronika; Strissel, Pamela; Strick, Reiner; Sikic, Danijel; Geppert, Carol-Immanuel; Bertz, Simone; Lange, Fabienne; Taubert, Helge; Wach, Sven; Breyer, Johannes; Bolenz, Christian; Erben, Philipp; et al. (Cancers, 2021)
Background: Immune therapy has gained significant importance in managing urothelial cancer. The value of PD-L1 remains a matter of controversy, thus requiring an in-depth analysis of its biological and clinical relevance. Methods: A total of 193 tumors of muscle-invasive bladder cancer patients (MIBC) were assessed with four PD-L1 assays. PD-L1 scoring results were correlated with data from a comprehensive digital-spatial immune-profiling panel using descriptive statistics, hierarchical clustering and uni-/multivariable survival analyses. Results: PD-L1 scoring algorithms are heterogeneous (agreements from 63.1% to 87.7%), and stems from different constellations of immune and tumor cells (IC/TC). While Ventana IC5% algorithm identifies tumors with high inflammation and favorable baseline prognosis, CPS10 and the TCarea25%/ICarea25% algorithm identify tumors with TC and IC expression. Spatially organized immune phenotypes, which correlate either with high PD-L1 IC expression and favorable prognosis or constitutive PD-L1 TC expression and poor baseline prognosis, cannot be resolved properly by PD-L1 algorithms. PD-L1 negative tumors with relevant immune infiltration can be detected by sTILs scoring on HE slides and digital CD8+ scoring. Conclusions: Contemporary PD-L1 scoring algorithms are not sufficient to resolve spatially distributed MIBC immune phenotypes and their clinical implications. A more comprehensive view of immune phenotypes along with the integration of spatial PD-L1 expression on IC and TC is necessary in order to stratify patients for ICI.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Bladder cancer; Immune phenotypes; PD-1; PD-L1; TILs; Urothelial cancer

International Opinions on Grading of Urothelial Carcinoma: A Survey Among European Association of Urology and International Society of Urological Pathology Members - Beijert, Irene J.; Cheng, Liang; Liedberg, Fredrik; Plass, Karin; Williamson, Sean R.; Gontero, Paolo; Ribal, Maria J.; Babjuk, Marko; Black, Peter C.; Kamat, Ashish M.; Algaba, Ferran; Berman, David M.; et al. (European Urology Open Science, 2023)
Background: Grade of non–muscle-invasive bladder cancer (NMIBC) is an important prognostic factor for progression. Currently, two World Health Organization (WHO) classification systems (WHO1973, categories: grade 1–3, and WHO2004 categories: papillary urothelial neoplasm of low malignant potential [PUNLMP], low-grade [LG], high-grade [HG] carcinoma) are used. Objective: To ask the European Association of Urology (EAU) and International Society of Urological Pathology (ISUP) members regarding their current practice and preferences of grading systems. Design, setting, and participants: A web-based, anonymous questionnaire with ten questions on grading of NMIBC was created. The members of EAU and ISUP were invited to complete an online survey by the end of 2021. Thirteen experts had previously answered the same questions. Outcome measurements and statistical analysis: The submitted answers from 214 ISUP members, 191 EAU members, and 13 experts were analyzed. Results and limitations: Currently, 53% use only the WHO2004 system and 40% use both systems. According to most respondents, PUNLMP is a rare diagnosis with management similar to Ta-LG carcinoma. The majority (72%) would consider reverting back to WHO1973 if grading criteria were more detailed. Separate reporting of WHO1973-G3 within WHO2004-HG would influence clinical decisions for Ta and/or T1 tumors according the majority (55%). Most respondents preferred a two-tier (41%) or a three-tier (41%) grading system. The current WHO2004 grading system is supported by a minority (20%), whereas nearly half (48%) supported a hybrid three- or four-tier grading system composed of both WHO1973 and WHO2004. The survey results of the experts were comparable with ISUP and EAU respondents. Conclusions: Both the WHO1973 and the WHO2004 grading system are still widely used. Even though opinions on the future of bladder cancer grading were strongly divided, there was limited support for WHO1973 and WHO2004 in their current formats, while the hybrid (three-tier) grading system with LG, HG-G2, and HG-G3 as categories could be considered the most promising alternative. Patient summary: Grading of non–muscle-invasive bladder cancer (NMIBC) is a matter of ongoing debate and lacks international consensus. We surveyed urologists and pathologists of European Association of Urology and International Society of Urological Pathology on their preferences regarding NMIBC grading to generate a multidisciplinary dialogue. Both the “old” World Health Organization (WHO) 1973 and the “new” WHO2004 grading schemes are still used widely. However, continuation of both the WHO1973 and the WHO2004 system showed limited support, while a hybrid grading system composed of both the WHO1973 and the WHO2004 classification system may be considered a promising alternative.
CRIS-Team Scopus Importer:2023-05-19
Keywords: Bladder; Cancer; European Association of Urology; Grading; International Society of Urological Pathology; Survey; WHO1973; WHO2004

International Society of Urological Pathology Expert Opinion on Grading of Urothelial Carcinoma - van der Kwast, Theo; Liedberg, Fredrik; Black, Peter C.; Kamat, Ashish; van Rhijn, Bas W.G.; Algaba, Ferran; Berman, David M.; Hartmann, Arndt; Lopez-Beltran, Antonio; Samaratunga, Hemamali; Varma, Murali; Cheng, Liang (European Urology Focus, 2021)
Context: Grading is the mainstay for treatment decisions for patients with non–muscle-invasive bladder cancer (NMIBC). Objective: To determine the requirements for an optimal grading system for NMIBC via expert opinion. Evidence acquisition: A multidisciplinary working group established by the International Society of Urological Pathology reviewed available clinical, histopathological, and molecular evidence for an optimal grading system for bladder cancer. Evidence synthesis: Bladder cancer grading is a continuum and five different grading systems based on historical grounds could be envisaged. Splitting of the World Health Organization (WHO) 2004 low-grade class for NMIBC lacks diagnostic reproducibility and molecular-genetic support, while showing little difference in progression rate. Subdividing the clinically heterogeneous WHO 2004 high-grade class for NMIBC into intermediate and high risk categories using the WHO 1973 grading is supported by both clinical and molecular-genetic findings. Grading criteria for the WHO 1973 scheme were detailed on the basis of literature findings and expert opinion. Conclusions: Splitting of the WHO 2004 high-grade category into WHO 1973 grade 2 and 3 subsets is recommended. Provision of more detailed histological criteria for the WHO 1973 grading might facilitate the general acceptance of a hybrid four-tiered grading system or—as a preferred option—a more reproducible three-tiered system distinguishing low-, intermediate (high)-, and high-grade NMIBC. Patient summary: Improvement of the current systems for grading bladder cancer may result in better informed treatment decisions for patients with bladder cancer. A three-tiered grading system for non–muscle invasive bladder cancer derived by splitting the heterogeneous World Health Organization (WHO) 2004 high-grade category into WHO 1973 grade 2 and 3 subsets is recommended, as this may result in more informed treatment decisions.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Bladder cancer; Expert opinion; Grading system; Non-muscle invasive bladder cancer; Pathology; WHO 1973; WHO 2004

International Society of Urological Pathology (ISUP) Consensus Conference on Current Issues in Bladder Cancer. Working Group 1: Comparison of Bladder Cancer Grading System Performance. - Downes, Michelle R.; Hartmann, Arndt; Shen, Steven; Tsuzuki, Toyonori; Van Rhijn, Bas W.G.; Bubendorf, Lukas; Van Der Kwast, Theodorus H.; Cheng, Liang (American Journal of Surgical Pathology, 2024)
Grade is a key prognostic factor in determining progression in nonmuscle invasive papillary urothelial carcinomas. The 2 most common grading methods in use worldwide are the World Health Organization (WHO) 2004 and 1973 schemes. The International Society of Urological Pathology (ISUP) organized the 2022 consensus conference in Basel, Switzerland on current issues in bladder cancer and tasked working group 1 to make recommendations for future iterations of bladder cancer grading. For this purpose, the ISUP developed in collaboration with the European Association of Urology a 10-question survey for their memberships to understand the current use of grading schemes by pathologists and urologists and to ascertain the areas of potential improvements. An additional survey was circulated to the ISUP membership for their opinion on interobserver variability in grading, reporting of urine cytology, and challenges encountered in grade assignment. Comprehensive literature reviews were performed on bladder cancer grading prognosis and interobserver variability along with The Paris System for urine cytology. There are notable differences in practice patterns between North American and European pathologists in terms of used grading scheme and diagnosis of papillary urothelial neoplasm of low malignant potential. Areas of common ground include difficulty in grade assignment, a desire to improve grading criteria, and a move towards subclassifying high-grade urothelial carcinomas. The surveys and in-person voting demonstrated a strong preference to refine current grading into a 3-tier scheme with the division of WHO 2004 high grade into clinically relevant categories. More variable opinions were voiced regarding the use of papillary urothelial carcinoma with low malignant potential.
EVALuna2:540670

International validation of the consensus Immunoscore for the classification of colon cancer: a prognostic and accuracy study - Pages, Franck; Mlecnik, Bernhard; Marliot, Florence; Bindea, Gabriela; Ou, Fang-Shu; Bifulco, Carlo; Lugli, Alessandro; Zlobec, Inti; Rau, Tilman T.; Berger, Martin D.; Nagtegaal, Iris D.; Vink-Borger, Elisa; et al. (Lancet, 2018)
BACKGROUND: The estimation of risk of recurrence for patients with colon carcinoma must be improved. A robust immune score quantification is needed to introduce immune parameters into cancer classification. The aim of the study was to assess the prognostic value of total tumour-infiltrating T-cell counts and cytotoxic tumour-infiltrating T-cells counts with the consensus Immunoscore assay in patients with stage I-III colon cancer. METHODS: An international consortium of 14 centres in 13 countries, led by the Society for Immunotherapy of Cancer, assessed the Immunoscore assay in patients with TNM stage I-III colon cancer. Patients were randomly assigned to a training set, an internal validation set, or an external validation set. Paraffin sections of the colon tumour and invasive margin from each patient were processed by immunohistochemistry, and the densities of CD3+ and cytotoxic CD8+ T cells in the tumour and in the invasive margin were quantified by digital pathology. An Immunoscore for each patient was derived from the mean of four density percentiles. The primary endpoint was to evaluate the prognostic value of the Immunoscore for time to recurrence, defined as time from surgery to disease recurrence. Stratified multivariable Cox models were used to assess the associations between Immunoscore and outcomes, adjusting for potential confounders. Harrell's C-statistics was used to assess model performance. FINDINGS: Tissue samples from 3539 patients were processed, and samples from 2681 patients were included in the analyses after quality controls (700 patients in the training set, 636 patients in the internal validation set, and 1345 patients in the external validation set). The Immunoscore assay showed a high level of reproducibility between observers and centres (r=0·97 for colon tumour; r=0·97 for invasive margin; p<0·0001). In the training set, patients with a high Immunoscore had the lowest risk of recurrence at 5 years (14 [8%] patients with a high Immunoscore vs 65 (19%) patients with an intermediate Immunoscore vs 51 (32%) patients with a low Immunoscore; hazard ratio [HR] for high vs low Immunoscore 0·20, 95% CI 0·10-0·38; p<0·0001). The findings were confirmed in the two validation sets (n=1981). In the stratified Cox multivariable analysis, the Immunoscore association with time to recurrence was independent of patient age, sex, T stage, N stage, microsatellite instability, and existing prognostic factors (p<0·0001). Of 1434 patients with stage II cancer, the difference in risk of recurrence at 5 years was significant (HR for high vs low Immunoscore 0·33, 95% CI 0·21-0·52; p<0·0001), including in Cox multivariable analysis (p<0·0001). Immunoscore had the highest relative contribution to the risk of all clinical parameters, including the American Joint Committee on Cancer and Union for International Cancer Control TNM classification system. INTERPRETATION: The Immunoscore provides a reliable estimate of the risk of recurrence in patients with colon cancer. These results support the implementation of the consensus Immunoscore as a new component of a TNM-Immune classification of cancer. FUNDING: French National Institute of Health and Medical Research, the LabEx Immuno-oncology, the Transcan ERAnet Immunoscore European project, Association pour la Recherche contre le Cancer, CARPEM, AP-HP, Institut National du Cancer, Italian Association for Cancer Research, national grants and the Society for Immunotherapy of Cancer.
EVALuna2:34256

Intestinal Barrier Healing Is Superior to Endoscopic and Histologic Remission for Predicting Major Adverse Outcomes in Inflammatory Bowel Disease: The Prospective ERIca Trial - Rath, Timo; Atreya, Raja; Bodenschatz, Julia; Uter, Wolfgang; Geppert, Carol-Immanuel; Vitali, Francesco; Fischer, Sarah; Waldner, Maximilian; Colombel, Jean Frédéric; Hartmann, Arndt; Neurath, Markus (Gastroenterology, 2023)
Background & Aims: Endoscopic and histologic remission have emerged as key therapeutic goals in the management of inflammatory bowel diseases (IBD) that are associated with favorable long-term disease outcomes. Here, we prospectively compared the predictive value of barrier healing with endoscopic and histologic remission for predicting long-term disease behavior in a large cohort of patients with IBD in clinical remission. Methods: At baseline, patients with IBD in clinical remission underwent ileocolonoscopy with assessment of intestinal barrier function by confocal endomicroscopy. Endoscopic and histologic disease activity, as well as barrier healing, was prospectively assessed along established scores. During subsequent follow-up, patients were closely monitored for clinical disease activity and the occurrence of major adverse outcomes (MAOs): disease flares, IBD-related hospitalization or surgery, and initiation or dose escalation of systemic steroids, immunosuppressants, small molecules, or biological therapy. Results: The final analysis included 181 patients, 100 with Crohn's disease [CD] and 81 with ulcerative colitis (UC). During a mean follow-up of 35 (CD) and 25 (UC) months, 73% of patients with CD and 69% of patients with UC experienced at least 1 MAO. The probability of MAO-free survival was significantly higher in patients with IBD with endoscopic remission compared with endoscopically active disease. In addition, histologic remission predicted MAO-free survival in patients with UC but not CD. Barrier healing on endomicroscopy was superior to endoscopic and histologic remission for predicting MAO-free survival in both UC and CD. Conclusions: Barrier healing is associated with decreased risk of disease progression in patients with clinically remittent IBD, with superior predictive performance compared with endoscopic and histologic remission. Analysis of barrier function might be considered as a future treatment target in clinical trials. ClinicalTrials.gov number, NCT05157750.
CRIS-Team Scopus Importer:2023-01-27
Keywords: Confocal Laser Endomicroscopy; Endoscopy; Histology; Inflammatory Bowel Diseases; Intestinal Barrier

Intra-abdominal EWSR1/FUS-CREM-rearranged malignant epithelioid neoplasms: two cases of an emerging aggressive entity with emphasis on misleading immunophenotype - Agaimy, Abbas; Stöhr, Robert; Otto, Mike; Braesen, Jan Hinrich; Pfarr, Nicole; Konukiewitz, Bjoern; Kasajima, Atsuko; Hartmann, Arndt; Kloeppel, Guenter (Virchows Archiv, 2021)
CREB family (CREB1, ATF1, and CREM) gene fusions are defining markers in diverse mesenchymal neoplasms (clear cell sarcoma, angiomatoid fibrous histiocytoma, and others). However, neoplasms harboring EWSR1-CREM/FUS-CREM fusions are rare and poorly characterized. We describe two cases (55-year-old male with 7.5 cm renal mass and 32-year-old female with 5.5 cm mesenteric mass) illustrating their misleading immunophenotypes. Histologically, both showed eosinophilic and focally clear epithelioid cells arranged into sheets, nests, and trabeculae. Immunohistochemistry showed ALK, EMA, and AE1/AE3 immunoreactivity suggesting ALK-rearranged renal cell carcinoma (Case 1) and coexpression of keratin, EMA, synaptophysin, and chromogranin-A, suggesting neuroendocrine neoplasm (Case 2). Targeted RNA sequencing revealed EWSR1-CREM (Case 1) and FUS-CREM (Case 2) fusions. These cases add to the spectrum of CREM fusion-positive intra-abdominal epithelioid neoplasms. Their unusual immunophenotype and unexpected sites represent major pitfalls, underline a wide differential diagnosis, and emphasize the value of molecular testing in correctly diagnosing them.
CRIS-Team Scopus Importer:2021-07-16
Keywords: ALK; CREB; CREM; EWSR1; FUS; Mesentery; Neuroendocrine; Paraganglioma; Primary renal sarcoma; RCC

Intracranial hemorrhage in COVID-19 patients during extracorporeal membrane oxygenation for acute respiratory failure: a nationwide register study report - von Stillfried, Saskia; Bülow, Roman David; Röhrig, Rainer; Meybohm, Patrick; Boor, Peter; Böcker, Jana; Schmidt, Jens; Tholen, Pauline; Majeed, Raphael; Wienströer, Jan; Weis, Joachim; Bremer, Juliane; et al. (Critical Care, 2022)
Background: In severe cases, SARS-CoV-2 infection leads to acute respiratory distress syndrome (ARDS), often treated by extracorporeal membrane oxygenation (ECMO). During ECMO therapy, anticoagulation is crucial to prevent device-associated thrombosis and device failure, however, it is associated with bleeding complications. In COVID-19, additional pathologies, such as endotheliitis, may further increase the risk of bleeding complications. To assess the frequency of bleeding events, we analyzed data from the German COVID-19 autopsy registry (DeRegCOVID). Methods: The electronic registry uses a web-based electronic case report form. In November 2021, the registry included N = 1129 confirmed COVID-19 autopsy cases, with data on 63 ECMO autopsy cases and 1066 non-ECMO autopsy cases, contributed from 29 German sites. Findings: The registry data showed that ECMO was used in younger male patients and bleeding events occurred much more frequently in ECMO cases compared to non-ECMO cases (56% and 9%, respectively). Similarly, intracranial bleeding (ICB) was documented in 21% of ECMO cases and 3% of non-ECMO cases and was classified as the immediate or underlying cause of death in 78% of ECMO cases and 37% of non-ECMO cases. In ECMO cases, the three most common immediate causes of death were multi-organ failure, ARDS and ICB, and in non-ECMO cases ARDS, multi-organ failure and pulmonary bacterial ± fungal superinfection, ordered by descending frequency. Interpretation: Our study suggests the potential value of autopsies and a joint interdisciplinary multicenter (national) approach in addressing fatal complications in COVID-19.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Autopsy; Bleeding events; COVID-19; ECMO; Intracranial bleeding; Registry

Intraductal carcinoma of the prostate is an aggressive form of invasive carcinoma and should be graded - Samaratunga, Hemamali; Delahunt, Brett; Egevad, Lars; Srigley, John R.; Billis, Athanase; Bostwick, David G.; Camparo, Philippe; Cheng, Liang; Clouston, David; Denham, James; Furusato, Bungo; Hartmann, Arndt; et al. (Pathology, 2019)
Infiltration of the prostatic ducts by prostatic adenocarcinoma occurs relatively frequently, being most commonly associated with high grade disease. It is now recognised that intraductal carcinoma of the prostate (IDCP) has an associated poor prognosis and this is reflected in its histological, molecular and immunohistochemical features. The current recommendation of the World Health Organization is that IDCP not be taken into consideration when grading prostate adenocarcinoma. It is apparent that Gleason did not differentiate between IDCP and stromal invasive carcinoma when developing and validating his grading system, and recent studies suggest that the incorporation of IDCP grading into the overall grading of the specimen provides additional prognostic information.
CRIS-Team Scopus Importer:2019-12-27
Keywords: intraductal carcinoma of prostate; ISUP grade; prognosis; Prostate adenocarcinoma

Intraductal carcinoma of the prostate is an aggressive form of invasive carcinoma and should be graded - Samaratunga, Hemamali; Delahunt, Brett; Egevad, Lars; Srigley, John R.; Billis, Athanase; Bostwick, David G.; Camparo, Philippe; Cheng, Liang; Clouston, David; Denham, James; Furusato, Bungo; Hartmann, Arndt; et al. (Pathology, 2020)
Infiltration of the prostatic ducts by prostatic adenocarcinoma occurs relatively frequently, being most commonly associated with high grade disease. It is now recognised that intraductal carcinoma of the prostate (IDCP) has an associated poor prognosis and this is reflected in its histological, molecular and immunohistochemical features. The current recommendation of the World Health Organization is that IDCP not be taken into consideration when grading prostate adenocarcinoma. It is apparent that Gleason did not differentiate between IDCP and stromal invasive carcinoma when developing and validating his grading system, and recent studies suggest that the incorporation of IDCP grading into the overall grading of the specimen provides additional prognostic information.
EVALuna2:212459

Intraductal Papillary Mucinous Neoplasms of Minor Salivary Glands With AKT1 p.Glu17Lys Mutation - Agaimy, Abbas; Müller, Susanna; Bumm, Klaus; Iro, Heinrich; Moskalev, Evgeny; Hartmann, Arndt; Stoehr, Robert; Haller, Florian (American Journal of Surgical Pathology, 2018)
The spectrum of low-grade intraductal papillary proliferations of the salivary glands is heterogenous, and reproducible morphologic diagnostic criteria have not yet been established. Recognized types are sialadenoma papilliferum, inverted ductal papilloma, and intraductal papilloma, but some lesions have been possibly included in the morphologic spectrum of cystadenoma or low-grade intraductal carcinomas. We herein present detailed morphologic, immunophenotypic, and genotypic features of 3 minor salivary gland neoplasms affecting 2 men (aged 65 and 71 y) and 1 woman (aged 78 y). They ranged in size from 1 to 2.5 cm. All tumors showed atypical papillary intraductal growth that presented either as uninodular/unicystic lesions (intraductal papilloma-like; n=2) or as a discontinuous growth along the ductal system in a manner similar to pancreatic intraductal papillary mucinous neoplasm (n=1). Variable cytologic and architectural atypia was observed, ranging from bland intraductal papilloma-like features, to areas mimicking atypical ductal hyperplasia and low-grade ductal carcinoma in situ of the breast. Amplicon-based massive parallel sequencing revealed an identical AKT1 p.Glu17Lys mutation in all 3 cases, but absence of concurring mutations in other genes of the RAS or PI3K pathway. This small series represents the first genetic study on salivary intraductal papillary neoplasms. Our cases showed significant variation in the degree of cytologic and architectural atypia, which overlaps with intraductal papillomas at the one end and with low-grade intraductal carcinoma at the other end of the spectrum, suggesting a disease continuum. As the full biological and morphologic characteristics of these ductal papillary lesions remain to be defined, the noncommitted term "intraductal papillary neoplasms" might be more appropriate. Our novel genetic findings mirror similar activating mutations of AKT1 and other PI3K pathway members in intraductal papillary lesions of the breast and anogenital glands.
EVALuna2:34605

Intraparotid classical and nodular lymphocyte-predominant Hodgkin lymphoma: pattern analysis with emphasis on associated lymphadenoma-like proliferations - Agaimy, Abbas; Wild, Vanessa; Maerkl, Bruno; Wachter, David; Hartmann, Arndt; Rosenwald, Andreas; Ihrler, Stephan (American Journal of Surgical Pathology, 2015)
Most of the lymphoproliferative diseases involving the salivary glands represent indolent non-Hodgkin B-cell lymphoma (marginal zone lymphoma) related to chronic autoimmune sialadenitis (Sjögren disease). Other types of non-Hodgkin lymphomas involve the salivary glands less frequently. On rare occasions, classical Hodgkin lymphoma (CHL) and nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL) present initially as a primary salivary gland mass. We analyzed a series of CHL (n=3) and NLPHL (n=6) presenting initially as parotid gland tumors concerning their pattern (parenchymal vs. intraparotid lymph node) and the presence of salivary inclusions and epithelial proliferations within the lymphoma infiltrate. The pattern of infiltration was determined on hematoxylin and eosin-stained slides assisted by immunostaining for pancytokeratin to highlight lobular salivary gland parenchyma. Patients included 6 male and 3 female individuals with a mean age of 62 years (range, 36 to 88 y). Lymphoma was localized within intraparotid lymph nodes in 8 cases and was limited to salivary parenchyma in 1 case. Parenchymal involvement in nodal-based cases was scored as absent (3) or minimal (5). Salivary inclusions (acini and ductules) within affected lymph nodes were noted in 6 cases (4/5 NLPHLs and 2/3 CHLs). In 3/6 NLPHL cases, salivary inclusions showed variable proliferative changes ranging from prominent lymphoepithelial lesions to cystic and oncocytic (Warthin-like) epithelial changes. Scanty small lymphoepithelial lesions were seen in 1 of the 3 CHL cases. One NLPHL in the intraparotid lymph node was accompanied by prominent lymphoepithelial sialadenitis in the absence of clinical signs of Sjögren disease. This study highlights that a majority of parotid gland Hodgkin lymphomas arise within intraparotid lymph nodes. Frequent entrapment and proliferation of salivary ducts and acini within the lymphoma infiltrate might mimic a variety of benign lymphoepithelial mass-forming lesions (nonsebaceous lymphadenoma, Warthin tumor, and autoimmune sialadenitis). Pancytokeratin stain is helpful for reliable assessment of the background architecture.
EVALuna2:6714

Introducing a novel highly prognostic grading scheme based on tumour budding and cell nest size for squamous cell carcinoma of the uterine cervix - Jesinghaus, Moritz; Strehl, Johanna; Boxberg, Melanie; Bruehl, Frido; Wenzel, Adrian; Konukiewitz, Bjoern; Schlitter, Anna M.; Steiger, Katja; Warth, Arne; Schnelzer, Andreas; Kiechle, Marion; Beckmann, Matthias; et al. (Journal of Pathology: Clinical Research, 2018)
A novel histopathological grading system based on tumour budding and cell nest size has recently been shown to outperform conventional (WHO-based) grading algorithms in several tumour entities such as lung, oral, and oesophageal squamous cell carcinoma (SCC) in terms of prognostic patient stratification. Here, we tested the prognostic value of this innovative grading approach in two completely independent cohorts of SCC of the uterine cervix. To improve morphology-based grading, we investigated tumour budding activity and cell nest size as well as several other histomorphological factors (e.g., keratinization, nuclear size, mitotic activity) in a test cohort (n = 125) and an independent validation cohort (n = 122) of cervical SCC. All parameters were correlated with clinicopathological factors and patient outcome. Small cell nest size and high tumour budding activity were strongly associated with a dismal patient prognosis (p < 0.001 for overall survival [OS], disease-specific survival, and disease-free survival; test cohort) in both cohorts of cervical SCC. A novel grading algorithm combining these two parameters proved to be a highly effective, stage-independent prognosticator in both cohorts (OS: p < 0.001, test cohort; p = 0.001, validation cohort). In the test cohort, multivariate statistical analysis of the novel grade revealed that the hazard ratio (HR) for OS was 2.3 for G2 and 5.1 for G3 tumours compared to G1 neoplasms (p = 0.010). In the validation cohort, HR for OS was 3.0 for G2 and 7.2 for G3 tumours (p = 0.012). In conclusion, our novel grading algorithm incorporating cell nest size and tumour budding allows strongly prognostic histopathological grading of cervical SCC superior to WHO-based grading. Therefore, our data can be regarded as a cross-organ validation of previous results demonstrated for oesophageal, lung, and oral SCC. We suggest this grading algorithm as an additional morphology-based parameter for the routine diagnostic assessment of this tumour entity.
EVALuna2:35627

Isolation of Human Endothelial Cells from Normal Colon and Colorectal Carcinoma - An Improved Protocol - Naschberger, Elisabeth; Regensburger, Daniela; Tenkerian, Clara; Langheinrich, Melanie; Engel, Felix; Geppert, Carol-Immanuel; Hartmann, Arndt; Grützmann, Robert; Schellerer, Vera; Stürzl, Michael (Journal of Visualized Experiments, 2018)
Primary cells isolated from human carcinomas are valuable tools to identify pathogenic mechanisms contributing to disease development and progression. In particular, endothelial cells (EC) constituting the inner surface of vessels, directly participate in oxygen delivery, nutrient supply, and removal of waste products to and from tumors, and are thereby prominently involved in the constitution of the tumor microenvironment (TME). Tumor endothelial cells (TECs) can be used as cellular biosensors of the intratumoral microenvironment established by communication between tumor and stromal cells. TECs also serve as targets of therapy. Accordingly, in culture these cells allow studies on mechanisms of response or resistance to anti-angiogenic treatment. Recently, it was found that TECs isolated from human colorectal carcinoma (CRC) exhibit memory-like effects based on the specific TME they were derived from. Moreover, these TECs actively contribute to the establishment of a specific TME by the secretion of different factors. For example, TECs in a prognostically favorable Th1-TME secrete the anti-angiogenic tumor-suppressive factor secreted protein, acidic and rich in cysteine-like 1 (SPARCL1). SPARCL1 regulates vessel homeostasis and inhibits tumor cell proliferation and migration. Hence, cultures of pure, viable TECs isolated from human solid tumors are a valuable tool for functional studies on the role of the vascular system in tumorigenesis. Here, a new up-to-date protocol for the isolation of primary EC from the normal colon as well as CRC is described. The technique is based on mechanical and enzymatic tissue digestion, immunolabeling, and fluorescence activated cell sorting (FACS)-sorting of triple-positive cells (CD31, VE-cadherin, CD105). With this protocol, viable TEC or normal endothelial cell (NEC) cultures could be isolated from colon tissues with a success rate of 62.12% when subjected to FACS-sorting (41 pure EC cultures from 66 tissue samples). Accordingly, this protocol provides a robust approach to isolate human EC cultures from normal colon and CRC.
EVALuna2:34267

Ki67, chemotherapy response, and prognosis in breast cancer patients receiving neoadjuvant treatment - Fasching, Peter A.; Heusinger, Katharina; Haeberle, Lothar; Niklos, Melitta; Hein, Alexander; Bayer, Christian M.; Rauh, Claudia; Schulz-Wendtland, Rüdiger; Bani, Mayada; Schrauder, Michael; Kahmann, Laura; Lux, Michael P.; et al. (BMC Cancer, 2011)
Background: The pathological complete response (pCR) after neoadjuvant chemotherapy is a surrogate marker for a favorable prognosis in breast cancer patients. Factors capable of predicting a pCR, such as the proliferation marker Ki67, may therefore help improve our understanding of the drug response and its effect on the prognosis. This study investigated the predictive and prognostic value of Ki67 in patients with invasive breast cancer receiving neoadjuvant treatment for breast cancer.Methods: Ki67 was stained routinely from core biopsies in 552 patients directly after the fixation and embedding process. HER2/neu, estrogen and progesterone receptors, and grading were also assessed before treatment. These data were used to construct univariate and multivariate models for predicting pCR and prognosis. The tumors were also classified by molecular phenotype to identify subgroups in which predicting pCR and prognosis with Ki67 might be feasible.Results: Using a cut-off value of > 13% positively stained cancer cells, Ki67 was found to be an independent predictor for pCR (OR 3.5; 95% CI, 1.4, 10.1) and for overall survival (HR 8.1; 95% CI, 3.3 to 20.4) and distant disease-free survival (HR 3.2; 95% CI, 1.8 to 5.9). The mean Ki67 value was 50.6 ± 23.4% in patients with pCR. Patients without a pCR had an average of 26.7 ± 22.9% positively stained cancer cells.Conclusions: Ki67 has predictive and prognostic value and is a feasible marker for clinical practice. It independently improved the prediction of treatment response and prognosis in a group of breast cancer patients receiving neoadjuvant treatment. As mean Ki67 values in patients with a pCR were very high, cut-off values in a high range above which the prognosis may be better than in patients with lower Ki67 values may be hypothesized. Larger studies will be needed in order to investigate these findings further. © 2011 Fasching et al; licensee BioMed Central Ltd.
CRIS-Team Scopus Importer:2021-07-19

KRAS, EGFR, PDGFR-?, KIT and COX-2 status in carcinoma showing thymus-like elements (CASTLE) - Veits, Lothar; Schupfner, Rupert; Hufnagel, Petra; Penzel, Roland; Freitag, Jens; Stroebel, Philipp; Kern, Michael A.; Schroeder, Soeren; Neuhold, Nikolaus; Schmid, Kurt W.; Schirmacher, Peter; Hartmann, Arndt; et al. (Diagnostic Pathology, 2014)
CASTLE (Carcinoma showing thymus-like elements) is a rare malignant neoplasm of the thyroid resembling lymphoepithelioma-like and squamous cell carcinoma of the thymus with different biological behaviour and a better prognosis than anaplastic carcinoma of the thyroid.We retrospectively investigated 6 cases of this very rare neoplasm in order to investigate the mutational status of KRAS, EGFR, PDGFR-? and KIT, as well as the immunohistochemical expression pattern of CD117, EGFR and COX-2, and possibly find new therapeutic targets.Diagnosis was confirmed by a moderate to strong expression of CD5, CD117 and CK5/6, whereas thyroglobulin, calcitonin and TTF-1 were negative in all cases. Tumors were also positive for COX-2 and in nearly all cases for EGFR. In four cases single nucleotide polymorphisms (SNPs) could be detected in exon 12 of the PDGFR-? gene (rs1873778), in three cases SNPs were found in exon 20 of the EGFR gene (rs1050171). No mutations were found in the KIT and KRAS gene.All tumors showed a COX-2 expression as well as an EGFR expression except for one case and a wild-type KRAS status. No activating mutations in the EGFR, KIT and PDGFR-? gene could be detected. Our data may indicate a potential for targeted therapies, but if these therapeutic strategies are of benefit in CASTLE remains to be determined.The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1658499296115016.
EVALuna2:6606

Krt20, krt5, esr1 and erbb2 expression can predict pathologic outcome in patients undergoing neoadjuvant chemotherapy and radical cystectomy for muscle-invasive bladder cancer - Jütte, Hendrik; Reike, Moritz; Wirtz, Ralph M.; Kriegmair, Maximilian; Erben, Philipp; Tully, Karl; Weyerer, Veronika; Eckstein, Markus; Hartmann, Arndt; Eidt, Sebastian; Wezel, Felix; Bolenz, Christian; et al. (Journal of Personalized Medicine, 2021)
Patients with muscle-invasive bladder cancer (MIBC) that underwent neoadjuvant chemotherapy (NAC) prior to radical cystectomy (RC) show improved overall survival, especially those with pathological complete response (pCR). The response to NAC according to molecular subtypes has been discussed. Molecular targets such as estrogen receptor (ESR1) and human epidermal growth factor receptor 2 (ERBB2) play an important role in breast cancer management and have also been associated with urothelial bladder cancer. Hence, the association of Keratin 20 (KRT20) Keratin 5 (KRT5), ESR1, and ERBB2 mRNA expression in MIBC at transurethral resection (TUR-BT) with pCR after NAC was analyzed retrospectively. Formalin-fixed paraffin-embedded tumour tissue samples from TUR-BT of 54 patients (42 males, 12 females, median age of 64) with MIBC were analyzed for KRT20, KRT5, ESR1, and ERBB2 mRNA expression. After NAC, RC was performed, and the specimens were evaluated for pCR. Statistical analyses comprised nonparametric and chi2 testing, partition models, and Spearman correlation analyses. After NAC, 22 out of 54 patients (40.7%) had pCR. Tumours with an elevated expression of markers associated with luminal differentiation (KRT20, ERBB2, ESR1) were associated with a higher chance of pCR (55% vs. 15.8%, p = 0.009). Elevated ERBB2 expression was positively correlated with luminal expression features such as KRT20, and negatively with basal characteristics such as KRT5. Patients with MIBC showing a high expression of ERBB2, ESR1, or KRT20 have a significantly higher chance of pCR following NAC. These findings might improve patient selection for NAC in MIBC.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Bladder cancer; Chemotherapy; Muscle invasive; Risk stratification; Subtype

Langerhans Cell Histiocytosis Associated with Renal Cell Carcinoma Is a Neoplastic Process: Clinicopathologic and Molecular Study of 7 Cases - Agaimy, Abbas; Bonert, Michael; Naqvi, Asghar; Wang, Chunjie; Trpkov, Kiril; Dettmar, Peer; Wintzer, Hanns Olof; Stöhr, Robert; Hes, Ondřej; Williamson, Sean R.; Gibson, Ian W.; Hartmann, Arndt (American Journal of Surgical Pathology, 2020)
Langerhans cell histiocytosis (LCH) is a rare histiocytic disorder composed of Langerhans cells admixed with reactive mononuclear and granulocytic cells, associated with prominent eosinophils. LCH is considered a neoplasm, driven in most cases by oncogenic RAS/RAF/MEK/ERK pathway mutations. The disease predominantly affects children. Urinary system involvement has rarely been reported in a multisystem disease setting. We describe 7 patients who presented with LCH occurring within (6 cases) or after (1 case) a resected clear cell (n=6) or clear cell papillary (n=1) renal cell carcinoma (RCC), identified prospectively in our routine and consultation files (2012 to 2019). The patients included 5 women and 2 men, with a median age of 54 years (range, 39 to 73 y), none with a history of LCH or LCH manifestations before the time of RCC diagnosis. The median size of the RCC was 3.5 cm (range, 1.8 to 8.3 cm). Treatment included partial (5 cases), or radical (2 cases) nephrectomy. All RCCs on gross examination showed at least focal cystic changes and were low grade (World Health Organization [WHO]/International Society of Urologic Pathologists [ISUP] grade 1 to 2). The LCH foci were detected as incidental histological finding within the resected RCC in all six cases and they were limited to few high-power fields (<2 mm2) in 5 of 6 cases, but in the sixth case, they occupied almost the entire clear cell papillary RCC (2 cm nodule). No LCH manifestations were detected in the normal kidney or in perinephric fat. The seventh patient developed LCH within inguinal deep soft tissue followed by systemic manifestations 6 years after clear cell RCC. Langerhans cell immunophenotype was supported by the reactivity for S-100, CD1a, and langerin and by the negative pankeratin. Successful pyrosequencing of microdissected LCH DNA revealed the V600E BRAF mutation in all 6 cases of LCH within RCC. To our knowledge, only 3 similar cases were published since 1980; the only case tested for BRAF mutation showed wild-type BRAF. This is the first study analyzing the morphologic and genetic features of a cohort of LCH associated with RCC. In our experience, these cases may be underrecognized in practice, or may erroneously be diagnosed as RCC dedifferentiation or high-grade sarcomatoid transformation. Finally, the detection of BRAF mutation further confirms that LCH in this setting is indeed a neoplasm, rather than a reactive lesion.
CRIS-Team Scopus Importer:2020-12-04
Keywords: BRAF V600E; concurrent; kidney; Langerhans cell histiocytosis; RCC; renal cell carcinoma

Langerhans Cell Histiocytosis Occurring in a Renal Cell Carcinoma is a Neoplastic Process: Clinicopathologic and Molecular Study of Five Cases - Agaimy, Abbas; Bonert, Michael; Naqvi, Asghar; Wang, Chunjie; Hes, Ondrej; Trpkov, Kiril; Gibson, Ian; Hartmann, Arndt (LABORATORY INVESTIGATION, 2020)
CRIS-Team WoS Importer:2020-03-24

Large nested variant of urothelial carcinoma: a clinicopathological study of 36 cases - Comperat, Eva; Mckenney, Jesse K.; Hartmann, Arndt; Hes, Ondrej; Bertz, Simone; Varinot, Justine; Brimo, Fadi (Histopathology, 2017)
AIMS: The large nested variant of urothelial carcinoma (LNUC) has been added to the World Health Organization (WHO) 2016 classification. Scant data exist, and little is known about its clinical behaviour. MATERIAL AND RESULTS: Cases fulfilling the morphological criteria of LNUC were collected. Pure and mixed cases (i.e. with other patterns of invasive UC) were studied. Immunohistochemical staining with cytokeratin (CK)7, p63, GATA-3, CK20, p53 and Ki-67 was performed. Included were 26 cystectomies (RC) and 10 resections (TURB) belonging to 36 patients with an average age of 66.7 years. Fourteen (39%) were pure LNUCs, and 22 (61%) displayed mixed features. Seventy per cent of the TURBs had pT2 tumours, while 58% of RCs had extravesical disease (≥pT3 and/or ≥pN1), with the rate of advanced disease being higher in mixed (69%) in comparison to pure cases (40%). Similarly, 38% of mixed cases had nodal metastases in comparison to 20% of pure cases. Overall, eight patients (24%) died of disease at a mean interval time of 21.7 months and seven patients (21%) showed recurrence or metastases. Disease progression was significantly higher in mixed cases (55 and 31% in mixed and pure cases, respectively). Positive staining was: CK7 = 87.5%, CK20 = 72%, GATA-3 = 91%, P63 = 100%, p53 = 56% and Ki-67 = mean of 16%. CONCLUSION: Despite the bland cytological appearance and deceptive pattern of invasion of the LNUC, our study validates its fully malignant potential with metastatic spread and tumour-related deaths. Distinguishing mixed from pure LNUCs seems to be of value. LNUCs show comparable immunophenotype to both conventional urothelial carcinoma and the nested variant of urothelial carcinoma.
EVALuna2:34252

Large nested variant of urothelial carcinoma: a prime example of a FGFR3-mutated, luminal tumour - Weyerer, Veronika; Eckstein, Markus; Comperat, E.; Juette, H.; Allory, Y.; Stoehr, R.; Wullich, Bernd; Roupret, M.; Hartmann, Arndt; Bertz, Simone (VIRCHOWS ARCHIV, 2019)
CRIS-Team WoS Importer:2019-09-27

Leukocytosis and Neutrophilia as independent prognostic Biomarkers for clinical Outcome in the randomized Phase III CAO/ARO/AIO-04 Rectal Cancer Study - Diefenhardt, M.; Hofheinz, R-D; Martin, D.; Beissbarth, T.; Arnold, D.; Hartmann, Arndt; Von Der Grun, J.; Grützmann, Robert; Liersch, T.; Stroebel, P.; Grabenbauer, G. G.; Rieger, M.; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2019)
CRIS-Team WoS Importer:2019-06-07

Leukocytosis and neutrophilia as independent prognostic immunological biomarkers for clinical outcome in the CAO/ARO/AIO-04 randomized phase 3 rectal cancer trial - Diefenhardt, Markus; Hofheinz, Ralf Dieter; Martin, Daniel; Beißbarth, Tim; Arnold, Dirk; Hartmann, Arndt; von der Grün, Jens; Grützmann, Robert; Liersch, Torsten; Ströbel, Philipp; Grabenbauer, Gerhard G.; Rieger, Michael; et al. (International Journal of Cancer, 2019)
Peripheral blood leukocytosis and neutrophilia reflect cancer inflammation and have been proposed as prognostic immunological biomarkers in various malignancies. However, previous studies were limited by their retrospective nature and small patient numbers. Baseline peripheral blood leukocytes, neutrophils, hemoglobin, platelets, lactate dehydrogenase and carcinoembryonic antigen (CEA) were correlated with clinicopathologic characteristics, and clinical outcome in 1236 patients with rectal cancer treated with 5-FU-based preoperative chemoradiotherapy (CRT) alone or with oxaliplatin followed by surgery and adjuvant chemotherapy within the CAO/ARO/AIO-04 randomized phase 3 trial. Multivariable analyses were performed using Cox regression models. After a median follow-up of 50 months, baseline leukocytosis remained an independent adverse prognostic factor for disease-free survival (DFS; HR 1.457; 95% CI 1.163–1.825; p = 0.001), distant metastasis (HR 1.696; 95% CI 1.266–2.273; p < 0.001) and overall survival (OS; HR 1.716; 95% CI 1.264–2.329; p = 0.001) in multivariable analysis. Similar significant findings were observed for neutrophilia and high CEA levels. Conversely, treatment-induced leukopenia correlated with favorable DFS (p = 0.037), distant metastasis (p = 0.028) and OS (p = 0.012). Intriguingly, addition of oxaliplatin to 5-FU CRT resulted in a significant DFS improvement only in patients with neutrophilia and leukocytosis (p = 0.028 and p = 0.002). Our findings have important clinical implications and provide high-level evidence on the adverse prognostic role of leukocytes and neutrophils, and the impact of chemotherapy in the context of these biomarkers. These data could help guide patient stratification and should be further validated within prospective studies.
CRIS-Team Scopus Importer:2019-05-07
Keywords: clinical radiotherapeutic studies; clinical trials; colorectal cancer; molecular markers of metastasis and progression; radiochemotherapy

Lipomatous Solitary Fibrous Tumors Harbor Rare NAB2-STAT6 Fusion Variants and Show Up-Regulation of the Gene PPARG, Encoding for a Regulator of Adipocyte Differentiation - Haller, Florian; Schlieben, Lea D.; Ferrazzi, Fulvia; Michal, Michael; Stöhr, Robert; Moskalev, Evgeny; Bieg, Matthias; Bovée, Judith V.M.G.; Ströbel, Philip; Ishaque, Naveed; Grützmann, Robert; Meidenbauer, Norbert; et al. (American Journal of Pathology, 2021)
Solitary fibrous tumors (SFTs) harbor activating NAB2-STAT6 gene fusions. Different variants of the NAB2-STAT6 gene fusion have been associated with distinct clinicopathologic features. Lipomatous SFTs are a morphologic variant of SFTs, characterized by a fat-forming tumor component. Our aim was to evaluate NAB2-STAT6 fusion variants and to further study the molecular genetic features in a cohort of lipomatous SFTs. A hybrid-capture–based next-generation sequencing panel was employed to detect NAB2-STAT6 gene fusions at the RNA level. In addition, the RNA expression levels of 507 genes were evaluated using this panel, and were compared with a control cohort of nonlipomatous SFTs. Notably, 5 of 11 (45%) of lipomatous SFTs in the current series harbored the uncommon NAB2 exon 4–STAT6 exon 4 gene fusion variant, which is observed in only 0.9% to 1.4% of nonlipomatous SFTs. Furthermore, lipomatous SFTs displayed significant differences in gene expression compared with their nonlipomatous counterparts, including up-regulation of the gene peroxisome proliferator activated receptor-γ (PPARG). Peroxisome proliferator activated receptor-γ is a nuclear receptor regulating adipocyte differentiation, providing a possible explanation for the fat-forming component in lipomatous SFTs. In summary, the current study provides a possible molecular genetic basis for the distinct morphologic features of lipomatous SFTs.
CRIS-Team Scopus Importer:2021-06-04

Long noncoding RNA HOTAIR is upregulated in an aggressive subgroup of gastrointestinal stromal tumors (GIST) and mediates the establishment of gene-specific DNA methylation patterns - Bure, Irina; Geer, Sandra; Knopf, Jasmin; Roas, Maike; Henze, Sabine; Stroebel, Philipp; Agaimy, Abbas; Wiemann, Stefan; Hoheisel, Joerg D.; Hartmann, Arndt; Haller, Florian; Moskalev, Evgeny (Genes Chromosomes & Cancer, 2018)
Aberrant alterations of DNA methylation are common events in oncogenesis. The origin of cancer-associated epigenetic defects is of interest for mechanistic understanding of malignant transformation and-in the long run-therapeutic modulation of DNA methylation in a locus-specific manner. Given the ability of certain long noncoding RNAs to operate as an interface between DNA and the epigenetic modification machinery which can interact with DNA methyltransferases, we hypothesized-considering HOTAIR as an example-that this transcript may contribute to gene specificity of DNA methylation. Using gastrointestinal stromal tumors (GISTs, n = 67) as a model, we confirmed upregulation of HOTAIR in tumors with high risk of recurrence and showed high abundance of the transcript in GIST cell lines. HOTAIR knockdown in GIST-T1 cells triggered transcriptional response of genes involved in the organization and disassembly of the extracellular matrix and, notably, induced global locus-specific alterations of DNA methylation patterns. Hypomethylation was induced at a total of 507 CpG sites, whereas 382 CpG dinucleotides underwent gain of methylation upon HOTAIR depletion. Importantly, orchestrated gain or loss of methylation at multiple individual CpG sites was shown for cancer-related DPP4, RASSF1, ALDH1A3, and other targets. Collectively, our data indicate that HOTAIR enables target specificity of DNA methylation in GIST and is capable of dual (hypo- and hypermethylation) regulation by a yet to be defined mechanism. The results further suggest the feasibility of manipulating DNA methylation in a targeted manner and are of interest in the context of epigenetic cancer therapy.
EVALuna2:34849

Long-Term Experience of Chemoradiotherapy Combined with Deep Regional Hyperthermia for Organ Preservation in High-Risk Bladder Cancer (Ta, Tis, T1, T2) - Merten, Ricarda; Ott, Oliver; Haderlein, Marlen; Bertz, Simone; Hartmann, Arndt; Wullich, Bernd; Keck, Bastian; Kühn, Reinhard; Rödel, Claus Michael; Weiss, Christian; Gall, Christine; Uter, Wolfgang; et al. (Oncologist, 2019)
Background: The aim of this study was to evaluate the efficacy and safety of chemoradiotherapy (RCT) combined with regional deep hyperthermia (RHT) of high-risk bladder cancer after transurethral resection of bladder tumor (TUR-BT). Materials and methods: Between 1982 and 2016, 369 patients with pTa, pTis, pT1, and pT2 cN0–1 cM0 bladder cancer were treated with a multimodal treatment after TUR-BT. All patients received radiotherapy (RT) of the bladder and regional lymph nodes. RCT was administered to 215 patients, RCT + RHT was administered to 79 patients, and RT was used in 75 patients. Treatment response was evaluated 4–6 weeks after treatment with TUR-BT. Results: Complete response (CR) overall was 83% (290/351), and in treatment groups was RT 68% (45/66), RCT 86% (178/208), and RCT + RHT 87% (67/77). CR was significantly improved by concurrent RCT compared with RT (odds ratio [OR], 2.32; 95% confidence interval [CI], 1.05–5.12; p =.037), less influenced by hyperthermia (OR, 2.56; 95% CI, 0.88–8.00; p =.092). Overall survival (OS) after RCT was superior to RT (hazard ratio [HR], 0.7; 95% CI, 0.50–0.99; p =.045). Five-year OS from unadjusted Kaplan-Meier estimates was RCT 64% versus RT 45%. Additional RHT increased 5-year OS to 87% (HR, 0.32; 95% CI, 0.18–0.58; p =.0001). RCT + RHT compared with RCT showed a significantly better bladder-preservation rate (HR, 0.13; 95% CI, 0.03–0.56; p =.006). Median follow-up was 71 months. The median number of RHT sessions was five. Conclusion: The multimodal treatment consisted of a maximal TUR-BT followed by RT; concomitant platinum-based chemotherapy combined with RHT in patients with high-grade bladder cancer improves local control, bladder-preservation rate, and OS. It offers a promising alternative to surgical therapies like radical cystectomy. Implications for Practice: Radical cystectomy with appropriate lymph node dissection has long represented the standard of care for muscle-invasive bladder cancer in medically fit patients, despite many centers reporting excellent long-term results for bladder preserving strategies. This retrospective analysis compares different therapeutic modalities in bladder-preservation therapy. The results of this study show that multimodal treatment consisting of maximal transurethral resection of bladder tumor followed by radiotherapy, concomitant platinum-based chemotherapy combined with regional deep hyperthermia in patients with Ta, Tis, T1–2 bladder carcinomas improves local control, bladder-preservation rate, and survival. More importantly, these findings offer a promising alternative to surgical therapies like radical cystectomy. The authors hope that, in the future, closer collaboration between urologists and radiotherapists will further improve treatments and therapies for the benefit of patients.
CRIS-Team Scopus Importer:2019-08-13
Keywords: Bladder cancer; Bladder preservation; Chemoradiotherapy; Hyperthermia; Radiotherapy

Long term follow up of through-the-scope balloon dilation as compared to strictureplasty and bowel resection of intestinal strictures in crohn's disease - Krauss, Ekaterina; Agaimy, Abbas; Gottfried, Angelina; Maiss, Juergen; Weidinger, Thomas; Albrecht, Heinz; Hartmann, Arndt; Hohenberger, Werner; Neurath, Markus; Kessler, Hermann; Mudter, Jonas (International Journal of Clinical and Experimental Pathology, 2014)
Ileo-colonic strictures are common complication of Crohn's disease (CD), and may result in repeated endoscopic or surgical therapy with a risk of further complications, such as perforation or short bowel syndrome. Strictures develop as a consequence of tissue remodelling and fibrosis due to chronic inflammation. This study compares the outcome of CD patients undergoing primarily endoscopic treatment with those undergoing surgery at an university hospital.In this study we retrospectively included 88 CD patients with intestinal strictures (37 males, 51 females, mean age 40 years, range 19-65 years) of both our medical and our surgical department, who underwent either surgical or endoscopic therapy between January 2002 and January 2006 with prospective, controlled follow-up, extended till January 2010 (mean follow-up period: 5 years; range 4-8 years). The primary end-point was operation- and symptom-free time. Patients were primarily divided into four groups: only surgical therapy, only endoscopic therapy, endoscopy with subsequent surgery, and initial surgical therapy followed by endoscopic dilations.53% of all patients remained surgery-free with mean follow-up of 49 months; a single endoscopic dilation was sufficient enough in 9 patients to achieve a surgery-free time of 51 months, other patients required up to 5 dilations. The average interval between first and second dilation was 6.5 months, between second and third 10.5 months. In the group of patients with only endoscopic therapy, surgery- and symptom-free time was shorter, as compared to the group of only surgical therapy. We found that stenoses in the surgical group with an average length of 6.5 cm were as expected longer, as compared to the endoscopic group (3 cm, ranging from 2-4 cm). The surgery-free time was 49 months (42-71 months, P = 0.723) with a symptom-free time of 12 months (4.5-46 months, P = 0.921). In the group of only surgically treated patients, 68.4% of the patients had only one stenosis, 18.4% had 2-3 stenoses and 13.2% more than 3 stenoses. In all patients the surgery- and symptoms- free time was 69 months (57-83 months, P = 0.850 and 0.908). The other two groups showed similar results. We found no significant effect of characteristic of stenosis (length, inflammation, the number of stenoses), injection of prednisolone, disease activity at the time of dilation and medication at the time of dilation on the long-term outcome. Importantly, the success of symptom free time correlated with the diameter of the balloon.Endoscopic dilation should be considered as a first-line therapy for short, accessible, fibrotic strictures. Careful patient selection and proper diagnostic imaging pre-procedure are essential requirements for safe and successful treatment. The balloon diameter seems to correlate positively with the long term outcome of dilation. However, at ever shorter intervals between endoscopic interventions, surgery should be discussed as an option for further treatment.
EVALuna2:1853

Long-term outcomes of cyclosporin induction and ustekinumab maintenance combination therapy in patients with steroid-refractory acute severe ulcerative colitis - Vitali, Francesco; Rath, Timo; Klenske, Entcho; Vögele, Anna-Lena; Ganzleben, Ingo; Zundler, Sebastian; Strobel, Deike; Geppert, Carol-Immanuel; Hartmann, Arndt; Neurath, Markus; Atreya, Raja (Therapeutic Advances in Gastroenterology, 2024)
Background: Effective management of patients with acute severe ulcerative colitis (ASUC) is a major challenge and there remains a paucity of available maintenance treatment options after efficacious cyclosporin induction therapy. Objectives: We investigated the long-term effectiveness and safety of cyclosporin and ustekinumab combination therapy in patients with steroid refractory ASUC. Design: Monocentric, prospective study. Methods: We included patients with steroid refractory ASUC with multiple failed prior advanced therapies, who were treated with cyclosporin and ustekinumab combination therapy. Results: Among the 11 included patients, 10 had prior failure to infliximab and 8 failed at least three previous biological therapies. The mean baseline Mayo and Lichtiger scores were 10.9 (9–12) and 13.3 (11–14), respectively. Ustekinumab was initiated 3.2 weeks (1–8) after initiation of cyclosporin treatment and combination therapy was continued for a mean of 11.5 (4–20) weeks. Clinical response was achieved in six patients at week 16 and clinical steroid-free clinical remission in five patients at week 48. Endoscopic remission was achieved in five patients at week 16 and together with histological remission in five patients at week 52. Intestinal ultrasound demonstrated mean bowel wall thickening in the sigmoid colon of 5.5 mm at baseline and 3.5 mm at week 52, respectively. Two patients had to undergo colectomy (mean 4.5 months, range 3–6) and three stopped ustekinumab therapy due to ineffectiveness. Overall, combination therapy was well tolerated. Conclusion: Combination of cyclosporin and ustekinumab therapy allowed nearly half of ASUC patients to reach clinical and endoscopic remission after 52 weeks, warranting further studies. Trial registration: Not applicable.
CRIS-Team Scopus Importer:2024-01-19
Keywords: cyclosporin; proctocolectomy; severe ulcerative colitis; sonography; ustekinumab

Loss of AQP3 protein expression is associated with worse progression-free and cancer-specific survival in patients with muscle-invasive bladder cancer - Rubenwolf, Peter; Thomas, Christian; Denzinger, Stefan; Hartmann, Arndt; Burger, Maximilian; Georgopoulos, Nikolaos T.; Otto, Wolfgang (World Journal of Urology, 2015)
Urothelial carcinoma has recently been shown to express several aquaporins (AQP), with AQP3 being of particular interest as its expression is reduced or lost in tumours of higher grade and stage. Loss of AQP3 expression was associated with worse progression-free survival (PFS) in patients with pT1 bladder cancer. The objective of this study was to investigate the prognostic value of AQP3 expression in patients with muscle-invasive bladder carcinoma (MIBC).Retrospective single-centre analysis of the oncological outcome of patients following radical cystectomy (Cx) due to MIBC. Immunohistochemistry was used to assess AQP3 protein expression in 100 Cx specimens. Expression levels of AQP3 were related to clinicopathological variables. The impact of biomarker expression on progression-free, cancer-specific and overall survival was determined by multivariate Cox regression analysis (MVA).High expression of AQP3 by the tumour was associated with a statistically significantly improved PFS (75 vs. 19 %, p = 0.043) and CSS (75 vs. 18 %, p = 0.030) and, alongside lymph node involvement, was an independent predictor of PFS (HR 2.871, CI 1.066-7.733, p = 0.037), CSS (HR 3.325, CI 1.204-8.774, p = 0.019) and OS (HR 2.001, CI 1.014-3.947) in MVA.Although the results of the study would be strengthened by a larger, more appropriately powered, prospective, multi-institutional study, our findings strongly suggest that AQP3 expression status may represent an independent predictor of PFS and CSS in MIBC and may help select patients in need for (neo-)adjuvant chemotherapy.
EVALuna2:6804

Loss of Dickkopf 3 Promotes the Tumorigenesis of Basal Breast Cancer - Lorsy, Eva; Topuz, Aylin Sophie; Geisler, Cordelia; Stahl, Sarah; Garczyk, Stefan; Von Stillfried, Saskia; Hoss, Mareike; Gluz, Oleg; Hartmann, Arndt; Knuechel, Ruth; Dahl, Edgar (PLoS ONE, 2016)
Dickkopf 3 (DKK3) has been associated with tumor suppression of various tumor entities including breast cancer. However, the functional impact of DKK3 on the tumorigenesis of distinct molecular breast cancer subtypes has not been considered so far. Therefore, we initiated a study analyzing the subtype-specific DKK3 expression pattern as well as its prognostic and functional impact with respect to breast cancer subtypes. Based on three independent tissue cohorts including one in silico dataset (n = 30, n = 463 and n = 791) we observed a clear down-regulation of DKK3 expression in breast cancer samples compared to healthy breast tissue controls on mRNA and protein level. Interestingly, most abundant reduction of DKK3 expression was detected in the highly aggressive basal breast cancer subtype. Analyzing a large in silico dataset comprising 3,554 cases showed that low DKK3 mRNA expression was significantly associated with reduced recurrence free survival (RFS) of luminal and basal-like breast cancer cases. Functionally, DKK3 re-expression in human breast cancer cell lines led to suppression of cell growth possibly mediated by up-regulation of apoptosis in basal-like but not in luminal-like breast cancer cell lines. Moreover, ectopic DKK3 expression in mesenchymal basal breast cancer cells resulted in partial restoration of epithelial cell morphology which was molecularly supported by higher expression of epithelial markers like E-Cadherin and down-regulation of mesenchymal markers such as Snail 1. Hence, we provide evidence that down-regulation of DKK3 especially promotes tumorigenesis of the aggressive basal breast cancer subtype. Further studies decoding the underlying molecular mechanisms of DKK3-mediated effects may help to identify novel targeted therapies for this clinically highly relevant breast cancer subtype.
EVALuna2:6919

Loss of enhancer of zeste homologue 2 (EZH2) at tumor invasion front is correlated with higher aggressiveness in colorectal cancer cells - Böhm, Julian; Muenzner, Julienne Kathrin; Caliskan, Aylin; Ndreshkjana, Benardina; Erlenbach-Wünsch, Katharina; Merkel, Susanne; Croner, Roland; Rau, Tilman; Geppert, Carol-Immanuel; Hartmann, Arndt; Roehe, Adriana Vial; Schneider-Stock, Regine (Journal of Cancer Research and Clinical Oncology, 2019)
Purpose: Enhancer of zeste homolog 2 (EZH2) is associated with epigenetic gene silencing and aggressiveness in many tumor types. However, the prognostic impact of high EZH2 expression is controversially discussed for colorectal cancer. For this reason, we immunohistochemically analyzed EZH2 expression in 105 specimens from colon cancer patients separately for tumor center and invasion front. Methods: All sections from tissue microarrays were evaluated manually and digitally using Definiens Tissue Studio software (TSS). To mirror-image the EZH2 status at the tumor invasion front, we treated HCT116 colon cancer cells with the EZH2 inhibitor 3-Deazaneplanocin A (DZNep) and studied the growth of in ovo xenografts in the chorioallantoic membrane (CAM) assay. Results: We showed a significant decrease in EZH2 expression and the repressive H3K27me3 code at the tumor invasion front as supported by the TSS-constructed heatmaps. Loss of EZH2 at tumor invasion front, but not in tumor center was correlated with unfavorable prognosis and more advanced tumor stages. The observed cell cycle arrest in vitro and in vivo was associated with higher tumor aggressiveness. Xenografts formed by DZNep-treated HCT116 cells showed loosely packed tumor masses, infiltrative growth into the CAM, and high vessel density. Conclusion: The differences in EZH2 expression between tumor center and invasion front as well as different scoring and cutoff values can most likely explain controversial literature data concerning the prognostic value of EZH2. Epigenetic therapies using EZH2 inhibitors have to be carefully evaluated for each specific tumor type, since alterations in cell differentiation might lead to unfavorable results.
CRIS-Team Scopus Importer:2019-07-23
Keywords: CAM assay; Colorectal cancer; EZH2; EZH2 inhibition; Tumor invasion front; Worse prognosis

Loss of expression of the SWI/SNF complex is a frequent event in undifferentiated/dedifferentiated urothelial carcinoma of the urinary tract - Agaimy, Abbas; Bertz, Simone; Cheng, Liang; Hes, Ondrej; Junker, Kerstin; Keck, Bastian; Lopez-Beltran, Antonio; Stoeckle, Michael; Wullich, Bernd; Hartmann, Arndt (Virchows Archiv, 2016)
Loss of the SWI/SNF chromatin remodeling complex has been recently implicated in the pathogenesis of dedifferentiated carcinomas from different organs, but its possible role in undifferentiated urothelial carcinoma (UC) has not been studied to date. In this study, we analyzed by immunohistochemistry 14 undifferentiated UCs (11 from bladder and 3 from renal pelvis) with a nondescript anaplastic or rhabdoid morphology, using commercially available antibodies against the SWI/SNF components SMARCB1 (INI1), SMARCA2, SMARCA4, SMARCC1, SMARCC2, and ARID1A. Patients were eight females and six males aged 40 to 84 years (median, 65). All tumors were muscle-invasive (9 were T3-4). A conventional UC component was seen in eight cases and varied from in situ to papillary. The undifferentiated component comprised 60-100 % of the tumors. Histologically, most tumors showed diffuse dyscohesive or pseudoalveolar growth of variably sized cells with frequent rhabdoid features. Transition from conventional to undifferentiated UC was abrupt, except in one case. The undifferentiated component almost always expressed pan-cytokeratin AE1/AE3 (13/14) and variably vimentin (8/14) and GATA3 (9/14). Complete loss of at least one SWI/SNF subunit limited to the undifferentiated component was detected in 10/14 cases (71 %). SMARCA2 was most frequently lost (six) followed by ARID1A (four), SMARCB1/INI1 (two), SMARCA4 (one), and SMARCC1 (one). This is the first study exploring SWI/SNF expression in undifferentiated UC of the urinary tract. Our results are in line with recent studies reporting involvement of the SWI/SNF complex in the dedifferentiation process of a variety of epithelial neoplasms in different organs, including the urinary tract, and association with aggressive clinical course.
EVALuna2:6799

Loss of EZH2 at tumor invasive front is correlated with higher aggressiveness - Böhm, Julian; Muenzner, Julienne K.; Caliskan, Aylin; Ndreshkjana, Benardina; Erlenbach-Wunsch, Katharina; Merkel, Susanne; Croner, Roland S.; Rau, Tilman T.; Geppert, Carol-Immanuel; Hartmann, Arndt; Vial-Roehe, Adriana; Schneider-Stock, Regine (2018)
EVALuna2:205467

Loss of Fumarate Hydratase and Aberrant Protein Succination Detected With S-(2-Succino)-Cysteine Staining to Identify Patients With Multiple Cutaneous and Uterine Leiomyomatosis and Hereditary Leiomyomatosis and Renal Cell Cancer Syndrome - Llamas-Velasco, Mar; Requena, Luis; Adam, Julie; Frizzell, Norma; Hartmann, Arndt; Mentzel, Thomas (American Journal of Dermatopathology, 2016)
Hereditary leiomyomatosis and renal cell cancer (HLRCC) syndrome is an autosomal dominant disorder caused by heterozygotic germline mutations in fumarate hydratase (FH) with incomplete penetrance, and clinically challenging to diagnose. Immunohistochemical stainings may favor an earlier diagnosis.The authors have tested 31 smooth muscle neoplasms. Ten of the 13 lesions from patients with HLRCC syndrome showed negative FH staining. Most sporadic piloleiomyomas presented strongly positive FH staining although 5 cases were negative. Sensitivity of FH staining in our series is 83.3% but specificity is 75%. Anti-S-(2-succino)-cysteine (2SC) showed the opposite intensity staining pattern and showed great correlation with anti-FH (rho spearman = -0.797). Anti-2SC staining increased the diagnostic accuracy in 19% of the cases.The main limitation of this study is the lack additional clinical data to further classify the cases as the case inclusion was histopathological.Negative FH staining could indicate a high risk of HLRCC but it could also suggest the presence of a syndrome in up to 25% of sporadic cases. Thus, when there is a doubtful case, anti-2SC may be added to exclude the syndrome if a negative staining is found.
EVALuna2:6917

Loss of MTUS1/ATIP expression is associated with adverse outcome in advanced bladder carcinomas: data from a retrospective study - Rogler, Anja; Hoja, Sabine; Giedl, Josef; Ekici, Arif Bülent; Wach, Sven; Taubert, Helge; Goebell, Peter; Wullich, Bernd; Stoeckle, Michael; Lehmann, Jan; Petsch, Sabrina; Hartmann, Arndt; et al. (BMC Cancer, 2014)
Seventy percent of all bladder tumours tend to recur and need intensive surveillance, and a subset of tumours progress to muscle-invasive and metastatic disease. However, it is still difficult to find the adequate treatment for every individual patient as it is a very heterogeneous disease and reliable biomarkers are still missing. In our study we searched for new target genes in the critical chromosomal region 8p and investigated the potential tumour suppressor gene candidate MTUS1/ATIP in bladder cancer.MTUS1 was identified to be the most promising deleted target gene at 8p in aCGH analysis with 19 papillary bladder tumours. A correlation with bladder cancer was further validated using immunohistochemistry of 85 papillary and 236 advanced bladder tumours and in functional experiments. Kaplan-Meier analysis and multivariate Cox-regression addressed overall survival (OS) and disease-specific survival (DSS) as a function of MTUS1/ATIP expression. Bivariate correlations investigated associations between MTUS1/ATIP expression, patient characteristics and histopathology. MTUS1 expression was analysed in cell lines and overexpressed in RT112, where impact on viability, proliferation and migration was measured.MTUS1 protein expression was lost in almost 50% of all papillary and advanced bladder cancers. Survival, however, was only influenced in advanced carcinomas, where loss of MTUS1 was associated with adverse OS and DSS. In this cohort, there was also a significant correlation of MTUS1 expression and histological subtype: positive expression was detected in all micropapillary tumours and aberrant nuclear staining was detected in a subset of plasmocytoid urothelial carcinomas. MTUS1 was expressed in all investigated bladder cell lines and overexpression in RT112 led to significantly decreased viability.MTUS1 is a tumour suppressor gene in cultured bladder cancer cells and in advanced bladder tumours. It might represent one new target gene at chromosome 8p and can be used as an independent prognostic factor for advanced bladder cancer patients. The limitation of the study is the retrospective data analysis. Thus, findings should be validated with a prospective advanced bladder tumour cohort.
EVALuna2:6624

Loss of ORP3 induces aneuploidy and promotes bladder cancer cell invasion through deregulated microtubule and actin dynamics - Wang, Xue; Liu, Junnan; Azoitei, Anca; Eiseler, Tim; Meessen, Sabine; Jiang, Wencheng; Zheng, Xi; Makori, Arika W.; Eckstein, Markus; Hartmann, Arndt; Stilgenbauer, Stephan; Elati, Mohamed; et al. (Cellular and Molecular Life Sciences, 2023)
We have recently shown that loss of ORP3 leads to aneuploidy induction and promotes tumor formation. However, the specific mechanisms by which ORP3 contributes to ploidy-control and cancer initiation and progression is still unknown. Here, we report that ORP3 is highly expressed in ureter and bladder epithelium while its expression is downregulated in invasive bladder cancer cell lines and during tumor progression, both in human and in mouse bladder cancer. Moreover, we observed an increase in the incidence of N-butyl-N-(4-hydroxybutyl)-nitrosamine (BBN)-induced invasive bladder carcinoma in the tissue-specific Orp3 knockout mice. Experimental data demonstrate that ORP3 protein interacts with γ-tubulin at the centrosomes and with components of actin cytoskeleton. Altering the expression of ORP3 induces aneuploidy and genomic instability in telomerase-immortalized urothelial cells with a stable karyotype and influences the migration and invasive capacity of bladder cancer cell lines. These findings demonstrate a crucial role of ORP3 in ploidy-control and indicate that ORP3 is a bona fide tumor suppressor protein. Of note, the presented data indicate that ORP3 affects both cell invasion and migration as well as genome stability through interactions with cytoskeletal components, providing a molecular link between aneuploidy and cell invasion and migration, two crucial characteristics of metastatic cells.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Chromosomal imbalance; Invadopodia; Metastasis; OSBPL3; Spindle orientation; Urothelial carcinoma

Low cytoplasmic and nuclear KPNA2 expression in radiotherapy-treated head and neck squamous cell cancer is associated with an adverse outcome - Erben, Pia; Brunner, Kathrin; Hecht, Markus; Haderlein, Marlen; Buettner-Herold, Maike; Agaimy, Abbas; Fietkau, Rainer; Hartmann, Arndt; Distel, Luitpold (International Journal of Clinical and Experimental Pathology, 2015)
KPNA2 has effects on carcinogenesis, cell differentiation and transcriptional regulation. KPNA2 has been linked to DNA damage repair by its role to import the DNA double strand break repair complex MRN into the nucleus. The aim of our study was to evaluate the prognostic value of KPNA2 expression in both cytoplasmic and nuclear location in patients with HNSCC treated with radio(chemo)therapy.225 patients with HNSCC treated with neoadjuvant, definitive or adjuvant radio(chemo)therapy were included. Immunohistochemical staining was performed on tissue micro arrays to evaluate nuclear and cytoplasmic KPNA2 expression.The median fraction of tumor cells with nuclear KPNA2 expression was 15%. 47% of tumor samples showed positive cytoplasmic staining. Patients with low nuclear as well as negative cytoplasmic expression tended to have an unfavorable prognosis. There was no correlation between nuclear and cytoplasmic KPNA2 expression. Low nuclear combined with negative cytoplasmic KPNA2 had a clearly unfavorable prognostic effect in local failure-free survival (P=0.014), metastasis-free survival (P=0.001) and no evidence of disease (P=0.008). A combination of low nuclear/negative cytoplasmic with high nuclear/high cytoplasmic KPNA2 expression was prognostically unfavorable with regard to tumor specific survival (P=0.021) and to a lower extent to overall survival (P=0.18). In multivariate analysis low nuclear/negative cytoplasmic versus any high KPNA2 (P=0.008) and T-category (P=0.002) proved as independent prognostic variables.The combination of nuclear and cytoplasmic KPNA2 expression is a potential excellent prognostic parameter in HNSCC treated with radio(chemo)therapy.
EVALuna2:6796

Low frequency of HNPCC-associated microsatellite instability and aberrant MMR protein expression in early-onset bladder cancer - Giedl, Josef; Schneckenpointner, Roland; Filbeck, Thomas; Ruemmele, Petra; Hofstaedter, Ferdinand; Burger, Maximilian; Hartmann, Arndt; Stoehr, Robert (American Journal of Clinical Pathology, 2014)
Recently, it was shown that patients with Lynch syndrome due to an MSH2 mutation are at increased risk for the development of bladder cancer. To further this discussion, we screened the largest investigated cohort of patients with early-onset bladder cancer for microsatellite instability (MSI) and mismatch repair (MMR) deficiency to determine a possible role of Lynch syndrome in young patients with bladder cancer.A total of 109 cases of bladder tumors from young patients (aged <45 years) were examined for MSI (Bethesda consensus panel). Expression of MMR proteins (hMLH1, hMSH2, and hMSH6) was evaluated by immunohistochemistry using a tissue microarray. Results were compared with a series of unselected consecutive bladder tumors (n = 95).Regarding the frequency of MSI high (1% vs 0%) or abnormal expression of MMR proteins (2% vs 6.5%), no significant difference between the early-onset and unselected patient group was found.In young patients with bladder tumors, MSI and defects in MMR protein expression were not more frequent than in a series of consecutive bladder tumors. Most bladder tumors in young patients are not to be attributed to Lynch syndrome.
EVALuna2:6663

Low-grade Endometrioid Stromal Sarcoma of the Paratestis: A Novel Report With Molecular Confirmation of JAZF1/SUZ12 Translocation - Agaimy, Abbas; Moskalev, Evgeny; Weisser, Wera; Bach, Thorsten; Haller, Florian; Hartmann, Arndt (American Journal of Surgical Pathology, 2018)
Tumors with Müllerian-like serous or mucinous phenotypes originating in the testis and its adnexa are rare neoplasms that have been increasingly recognized in recent years. Cystadenomas with or without ovarian-type stroma, borderline tumors, and adenocarcinomas are the main documented types. Although a handful cases of putative endometrioid adenocarcinomas have been reported, to our knowledge no case of endometrial stromal-type neoplasm has ever been reported in the literature. A 59-year-old man presented with a 2 cm left intrascrotal mass that was found on sonographic examination to arise from the epididymal tail with prominent vascularization. He was otherwise healthy without significant clinical history, endocrinopathy, or external hormone therapy. His testicular tumor markers (beta-HCG, AFP) were normal. Histologic examination of the resection showed a multinodular tumor closely associated with the epididymis and composed of monotonous rounded to ovoid cells with scanty cytoplasm and prominent spiral-like arterioles and capillaries. Mitotic activity was high. No other tumor component was seen. Immunohistochemistry revealed strong and diffuse expression of vimentin, CD10, estrogen receptor, and progesterone receptor. Molecular examination (performed on paraffin-embedded tumor tissue using a 517 gene fusion next-generation sequencing assay) showed a JAZF1/SUZ12 translocation, which was then confirmed by fluorescence in situ hybridization (FISH). These findings are consistent with a low-grade endometrioid stromal sarcoma originating in the paratestis. This report represents a novel addition to the growing spectrum of Müllerian-analog testicular adnexal neoplasms.
EVALuna2:34099

Lung cancer presenting with central nervous system metastasis: Clinicopathological and molecular analysis of 171 cases - Demleitner, Madeleine; Erlenbach-Wünsch, Katharina; Coras, Roland; Erber, Ramona; Polifka, Iris; Eyüpoglu, Ilker Yasin; Fuchs, Florian; Hartmann, Arndt; Agaimy, Abbas (Annals of Diagnostic Pathology, 2023)
A subset of lung carcinoma presents initially with brain metastasis. Precise subtyping is mandatory for optimized treatment of these advanced aggressive carcinomas. We herein analyzed surgical biopsies from 171 Patients (99 males and 72 females aged 48–96; mean, 72), who presented with brain metastasis of lung cancer. In addition to conventional subtyping, we applied an extended immunohistochemistry (IHC) panel and performed several molecular tests looking for potential therapeutic targets other than EGFR mutations. Non-small cell carcinoma (NSCLC) comprised 157 (91.8 %) of cases: 109 (63.7 %) adenocarcinomas, 27 (15.8 %) squamous cell (SCC), 18 (10.5 %) large cell undifferentiated, 1 (0.6 %) adenosquamous and 2 (1.2 %) unclassified carcinomas. Of the adenocarcinomas, 81.7 % were TTF1+. Notably, 45 % of those TTF1-negative cases expressed HepPar1. SMARCA4 and SMARCA2 loss was observed in 13/171 (7.6 %) and 32/163 (19.6 %) cases, respectively; mainly TTF1- (40.0 %) and HepPar1+ (38.1 %) adenocarcinomas were affected by SMARCA2/4 loss. Loss of at least one mismatch repair (MMR) protein was observed in 3/156 (1.9 %) cases (2 adenocarcinomas and 1 large cell neuroendocrine carcinoma/LCNEC). Limited available data on mutation testing showed a frequency of EGFR mutations of 4.3% and of KRAS mutations of 57%. HER2 expression (2+/3+) was found in 45/166 (27.1 %) of cases with amplification verified by CISH in 18/38 (47.4 % of immunopositive cases and 10.5 % of the whole cohort); all but one were adenocarcinomas. Other genetic abnormalities detected included EML4::ALK rearrangements in 3 (1.8 %; 2 TTF1+ adenocarcinomas and 1 LCNEC) and RET rearrangements in one SCNEC. Variable subsets of tumors revealed amplifications of several potentially therapeutically targetable genes including MYC (30.0 %), MET (10.1 %), HER2 (10 %), FGFR1 (9.6 %), FGFR3 (4.6 %), and FGFR2 (3.4 %). This study highlights a highly heterogeneous molecular background in lung cancer presenting with CNS metastases. These findings highlight the need for individualized tumor testing strategies looking for potential therapeutic targets for this aggressive disease.
CRIS-Team Scopus Importer:2023-01-27
Keywords: ALK; Central nervous system metastasis; Immune therapy; Microsatellite instability; NSCLC; SMARCA4

Lymph node metastases detection in Whole Slide Images using prototypical patterns and transformer-guided multiple instance learning - Heinlein, Lukas; Benz, Michaela; Kuritcyn, Petr; Bruns, Volker; Hartmann, Arndt; Geppert, Carol-Immanuel; Keil, Felix; Evert, Katja; Wittenberg, Thomas (Current Directions in Biomedical Engineering, 2023)
Background: The examination of lymph nodes (LNs) regarding metastases is vital for the staging of cancer patients, which is necessary for diagnosis and adequate treatment selection. Advancements in digital pathology, utilizing Whole-Slide Images (WSIs) and convolutional neural networks (CNNs), pose new opportunities to automate this procedure, thus reducing pathologists' workload while simultaneously increasing the accuracy in metastases detection. Objective: To address the task of LN-metastases detection, the use of weakly supervised transformers are applied for the analysis of WSIs. Methods Materials: As WSIs are too large to be processed as a whole, they are divided into non-overlapping patches, which are converted to feature vectors using a CNN network, pre-trained on HE-stained colon cancer resections. A subset of these patches serves as input for a transformer to predict if a LN contains a metastasis. Hence, selecting a representative subset is an important part of the pipeline. Hereby, a prototype based clustering is employed and different sampling strategies are tested. Finally, the chosen feature vectors are fed into a transformer-based multiple instance learning (MIL) architecture, classifying the LNs into healthy/negative (that is, containing no metastases), or metastatic/positive (that is, containing metastases). The proposed model is trained only on the Camelyon16 training data (LNs from breast cancer patients), and evaluated on the Camelyon16 test set. Results: The trained model achieves accuracies of up to 92.3% on the test data (from breast LNs). While the model struggles with smaller metastases, high specificities of up to 96.9% can be accomplished. Additionally, the model is evaluated on LNs from a different primary tumor (colon), where accuracies between 62.3% and 95.9% could be obtained. Conclusion: The investigated transformer-model performs very good on LN data from the public LN breast data, but the domain transfer to LNs from the colon needs more research.
CRIS-Team Scopus Importer:2023-10-20
Keywords: breast cancer; colon cancer; Lymph node metastases; prototypical patterns; transformer; whole slide image

Machine Learning-assisted immunophenotyping of peripheral blood identifies innate immune cells as best predictor of response to induction chemo-immunotherapy in head and neck squamous cell carcinoma – knowledge obtained from the CheckRad-CD8 trial - Hecht, Markus; Frey, Benjamin; Gaipl, Udo; Tianyu, Xie; Eckstein, Markus; Donaubauer, Anna-Jasmina; Klautke, Gunther; Illmer, Thomas; Fleischmann, Maximilian; Laban, Simon; Hautmann, Matthias G.; Tamaskovics, Bálint; et al. (Neoplasia, 2024)
Purpose: Individual prediction of treatment response is crucial for personalized treatment in multimodal approaches against head-and-neck squamous cell carcinoma (HNSCC). So far, no reliable predictive parameters for treatment schemes containing immunotherapy have been identified. This study aims to predict treatment response to induction chemo-immunotherapy based on the peripheral blood immune status in patients with locally advanced HNSCC. Methods: The peripheral blood immune phenotype was assessed in whole blood samples in patients treated in the phase II CheckRad-CD8 trial as part of the pre-planned translational research program. Blood samples were analyzed by multicolor flow cytometry before (T1) and after (T2) induction chemo-immunotherapy with cisplatin/docetaxel/durvalumab/tremelimumab. Machine Learning techniques were used to predict pathological complete response (pCR) after induction therapy. Results: The tested classifier methods (LDA, SVM, LR, RF, DT, and XGBoost) allowed a distinct prediction of pCR. Highest accuracy was achieved with a low number of features represented as principal components. Immune parameters obtained from the absolute difference (lT2-T1l) allowed the best prediction of pCR. In general, less than 30 parameters and at most 10 principal components were needed for highly accurate predictions. Across several datasets, cells of the innate immune system such as polymorphonuclear cells, monocytes, and plasmacytoid dendritic cells are most prominent. Conclusions: Our analyses imply that alterations of the innate immune cell distribution in the peripheral blood following induction chemo-immuno-therapy is highly predictive for pCR in HNSCC.
CRIS-Team Scopus Importer:2024-01-26
Keywords: Chemotherapy; HNSCC; Immune phenotyping; Immunotherapy; Induction therapy

Machine Learning-Supported Diagnosis of Small Blue Round Cell Sarcomas Using Targeted RNA Sequencing. - Schlieben, Lea D.; Carta, Maria Giulia; Moskalev, Evgeny; Stöhr, Robert; Metzler, Markus; Besendörfer, Manuel; Meidenbauer, Norbert; Semrau, Sabine; Janka, Rolf Matthias; Grützmann, Robert; Wiemann, Stefan; Hartmann, Arndt; et al. (Journal of Molecular Diagnostics, 2024)
Small blue round cell sarcomas (SBRCSs) are a heterogeneous group of tumors with overlapping morphologic features but markedly varying prognosis. They are characterized by distinct chromosomal alterations, particularly rearrangements leading to gene fusions, whose detection currently represents the most reliable diagnostic marker. Ewing sarcomas are the most common SBRCSs, defined by gene fusions involving EWSR1 and transcription factors of the ETS family, and the most frequent non-EWSR1-rearranged SBRCSs harbor a CIC rearrangement. Unfortunately, currently the identification of CIC::DUX4 translocation events, the most common CIC rearrangement, is challenging. Here, we present a machine-learning approach to support SBRCS diagnosis that relies on gene expression profiles measured via targeted sequencing. The analyses on a curated cohort of 69 soft-tissue tumors showed markedly distinct expression patterns for SBRCS subgroups. A random forest classifier trained on Ewing sarcoma and CIC-rearranged cases predicted probabilities of being CIC-rearranged >0.9 for CIC-rearranged-like sarcomas and <0.6 for other SBRCSs. Testing on a retrospective cohort of 1335 routine diagnostic cases identified 15 candidate CIC-rearranged tumors with a probability >0.75, all of which were supported by expert histopathologic reassessment. Furthermore, the multigene random forest classifier appeared advantageous over using high ETV4 expression alone, previously proposed as a surrogate to identify CIC rearrangement. Taken together, the expression-based classifier can offer valuable support for SBRCS pathologic diagnosis.
EVALuna2:565265

Macrophages and dendritic cells as actors in the immune reaction of classical hodgkin lymphoma - Tudor, Christiane; Bruns, Heiko; Daniel, Christoph; Distel, Luitpold; Hartmann, Arndt; Gerbitz, Armin; Büttner, Maike (PLoS ONE, 2014)
The inflammatory infiltrate plays a pivotal role in classical Hodgkin lymphoma (cHL). Here, we focussed on the role of macrophages (M?) and dendritic cells (DC).M? and DC infiltration was investigated in 106 cHL specimens using immunohistochemistry and cytokine expression was analyzed in a subset by real-time PCR. Human peripheral blood-derived monocytes, DC, M? stimulated with GM-CSF (M?GM-CSF, pro-inflammatory M?-1-model) or M-CSF (M?M-CSF, immunomodulatory M?-2-model) were incubated with cHL cell line (L1236, HDLM2) supernatants (SN). DC maturation or M? polarization were investigated by flow cytometry. Furthermore, the impact of DC or M? on cHL cell proliferation was analyzed by BrdU/CFSE assay.In cHL tissues mature myeloid (m)DC and M? predominated. High numbers of CD83+ mDC and low numbers of CD163+ M? were associated with improved disease specific survival. In numerous cHL specimens increased levels of both pro- and anti-inflammatory cytokines and of IL13 and GM-CSF were observed compared to reactive lymphadenopathies. Maturation of DC and induction and maintenance of an immunomodulatory M? phenotype were promoted by SN derived from cHL cell lines. TNF? neutralization in SN resulted in a significant inhibition of mDC maturation. DC and pro-inflammatory M? inhibited the proliferation of cHL cells.Adopting an immunomodulatory phenotype is a potential mechanism for how M? promote immune evasion in cHL. Mature DC, in contrast, might participate in antitumoral immunit
EVALuna2:6630

Magnification endoscopy with optical chromoendoscopy for in vivo assessment of histological inflammation in patients with inflammatory bowel disease - Klenske, E.; Atreya, Raja; Hartmann, Arndt; Fischer, Sören; Hirschmann, Simon; Zundler, Sebastian; Iacucci, M.; Neurath, Markus; Rath, Timo (JOURNAL OF CROHNS & COLITIS, 2019)
CRIS-Team WoS Importer:2019-03-20

Magnification endoscopy with optical chromoendoscopy shows strong correlation with histologic inflammation in patients with inflammatory bowel disease - Klenske, Entcho; Atreya, Raja; Hartmann, Arndt; Fischer, Sören; Hirschmann, Simon; Zundler, Sebastian; Iaccuci, Marietta; Neurath, Markus; Rath, Timo (Endoscopy International Open, 2019)
Background and study aims Apart from mucosal healing as an established treatment goal in inflammatory bowel diseases (IBD), recent evidence suggests that histologic healing may become another key prognostic parameter in IBD patients. We aimed to evaluate whether magnification endoscopy with optical chromoendoscopy can accurately assess histologic inflammation in IBD patients.
CRIS-Team WoS Importer:2019-09-13

MALDI Mass Spectrometry Imaging—Prognostic Pathways and Metabolites for Renal Cell Carcinomas - Erlmeier, Franziska; Sun, Na; Shen, Jian; Feuchtinger, Annette; Buck, Achim; Prade, Verena M.; Kunzke, Thomas; Schraml, Peter; Moch, Holger; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; et al. (Cancers, 2022)
High mass resolution matrix-assisted laser desorption/ionization (MALDI) mass spectrometry imaging (MSI) is a suitable method for biomarker detection for several tumor entities. Renal cell carcinoma (RCC) is the seventh most common cancer type and accounts for more than 80% of all renal tumors. Prognostic biomarkers for RCC are still missing. Therefore, we analyzed a large, multicenter cohort including the three most common RCC subtypes (clear cell RCC (ccRCC), papillary RCC (pRCC) and chromophobe RCC (chRCC)) by MALDI for prognostic biomarker detection. MALDI-Fourier-transform ion cyclotron resonance (FT-ICR)-MSI analysis was performed for renal carcinoma tissue sections from 782 patients. SPACiAL pipeline was integrated for automated co-registration of histological and molecular features. Kaplan–Meier analyses with overall survival as endpoint were executed to determine the metabolic features associated with clinical outcome. We detected several pathways and metabolites with prognostic power for RCC in general and also for different RCC subtypes.
CRIS-Team Scopus Importer:2022-04-15
Keywords: chromophobe renal cell carcinoma; clear-cell renal cell carcinoma; mass spectrometry imaging; metabolomics; papillary renal cell carcinoma

Malignant teratoid tumor of the thyroid gland: an aggressive primitive multiphenotypic malignancy showing organotypical elements and frequent DICER1 alterations—is the term “thyroblastoma” more appropriate? - Agaimy, Abbas; Witkowski, Leora; Stöhr, Robert; Cuenca, Joseph Christopher Castillo; González-Muller, Carlos Alberto; Brütting, Alfred; Bährle, Markus; Mantsopoulos, Konstantinos; Amin, Randa M.S.; Hartmann, Arndt; Metzler, Markus; Amr, Samir S.; et al. (Virchows Archiv, 2020)
Primary thyroid teratomas are exceedingly rare. Mature and immature variants recapitulate their gonadal counterparts (predilection for infants/children, triphasic germ layer differentiation, and favorable outcome). On the other hand, the so-called malignant teratomas affect predominantly adults and elderly, are highly aggressive, and, according to a few published cases, harbor DICER1 mutations. We describe three highly aggressive sporadic malignant teratoid thyroid tumors in 2 females (17 and 45 years) and one male (17 years). Histology showed triphasic neoplasms composed of solid nests of small primitive monomorphic cells embedded in a cellular stroma with primitive immature rhabdomyosarcoma-like (2) or pleomorphic sarcoma-like (1) phenotype. The third component was represented by TTF1+/PAX8+ primitive teratoid epithelial tubules reminiscent of primitive thyroid follicles and/or Wilms tumor, admixed with scattered respiratory- or enteric-type tubules, neuroepithelial rosettes, and fetal-type squamoid nests. Foci of cartilage were seen in two cases, but none contained mature organoid adult-type tissue or skin adnexa. SALL4 was expressed in the small cell (2) and stromal (1) component. Other germ cell markers were negative. Molecular testing revealed a known “hotspot” pathogenic DICER1 mutation in two cases. In addition, case 1 had a missense TP53 variant. This type of thyroid malignancy is distinct from genuine teratomas. The immunoprofile suggests primitive thyroid- or branchial cleft-like differentiation. Given that “blastoma” is a well-accepted terminology in the spectrum of DICER1-associated malignancies, the term “thyroblastoma” might be more convenient for these malignant teratoid tumors of the thyroid gland. Relationship of thyroblastoma to the DICER1 syndrome remains to be addressed.
CRIS-Team Scopus Importer:2020-06-16
Keywords: DICER1; Germ cell tumor; Head and neck; Malignant teratoma; Rhabdomyosarcoma; Teratocarcinosarcoma; Thyroblastoma; Thyroid

Mammographic Density and Prediction of Nodal Status in Breast Cancer Patients - Hack, Carolin; Häberle, Lothar; Geisler, K.; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; Fasching, Peter; Uder, Michael; Wachter, David; Jud, Sebastian; Löhberg, Christian; Lux, Michael P.; Rauh, Claudia; et al. (Geburtshilfe und Frauenheilkunde, 2013)
Aim: Nodal status remains one of the most important prognostic factors in breast cancer. The cellular and molecular reasons for the spread of tumor cells to the lymph nodes are not well understood and there are only few predictors in addition to tumor size and multifocality that give an insight into additional mechanisms of lymphatic spread. Aim of our study was therefore to investigate whether breast characteristics such as mammographic density (MD) add to the predictive value of the presence of lymph node metastases in patients with primary breast cancer. Methods: In this retrospective study we analyzed primary, metastasis-free breast cancer patients from one breast center for whom data on MD and staging information were available. A total of 1831 patients were included into this study. MD was assessed as percentage MD (PMD) using a semiautomated method and two readers for every patient. Multiple logistic regression analyses with nodal status as outcome were used to investigate the predictive value of PMD in addition to age, tumor size, Ki-67, estrogen receptor (ER), progesterone receptor (PR), grading, histology, and multi-focality. Results: Multifocality, tumor size, Ki-67 and grading were relevant predictors for nodal status. Adding PMD to a prediction model which included these factors did not significantly improve the prediction of nodal status (p = 0.24, likelihood ratio test). Conclusion: Nodal status could be predicted quite well with the factors multifocality, tumor size, Ki-67 and grading. PMD does not seem to play a role in the lymphatic spread of tumor cells. It could be concluded that the amount of extracellular matrix and stromal cell content of the breast which is reflected by MD does not influence the probability of malignant breast cells spreading from the primary tumor to the lymph nodes. © Georg Thieme Verlag KG Stuttgart · New York.
CRIS-Team Scopus Importer:2023-03-08
Keywords: breast cancer; estrogen receptor; Ki-67; mammographic density; nodal status; progesterone receptor

Mammographic Density and Prognosis in Patients with primary Breast Cancer - Loss of Risk with increasing Age - Heindl, Felix; Fasching, Peter; Hein, Alexander; Hack, Caroline; Heusinger, K.; Gaß, Paul; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; Erber, Ramona; Beckmann, Matthias; Meyer, J.; Häberle, Lothar; et al. (GEBURTSHILFE UND FRAUENHEILKUNDE, 2020)
CRIS-Team WoS Importer:2020-10-30

Mammographic density and prognosis in primary breast cancer patients - Heindl, Felix; Fasching, Peter; Hein, Alexander; Hack, Carolin; Heusinger, Katharina; Gaß, Paul; Pöschke, Patrik; Stübs, Frederik; Schulz-Wendtland, Rüdiger; Hartmann, Arndt; Erber, Ramona; Beckmann, Matthias; et al. (BREAST, 2021)
Purpose: Mammographic density (MD) is one of the strongest risk factors for breast cancer (BC). However, the influence of MD on the BC prognosis is unclear. The objective of this study was therefore to investigate whether percentage MD (PMD) is associated with a difference in disease-free or overall survival in primary BC patients. Methods: A total of 2525 patients with primary, metastasis-free BC were followed up retrospectively for this analysis. For all patients, PMD was evaluated by two readers using a semi-automated method. The association between PMD and prognosis was evaluated using Cox regression models with disease-free survival (DFS) and overall survival (OS) as the outcome, and the following adjustments: age at diagnosis, year of diagnosis, body mass index, tumor stage, grading, lymph node status, hormone receptor and HER2 status. Results: After median observation periods of 9.5 and 10.0 years, no influence of PMD on DFS (p = 0.46, likelihood ratio test (LRT)) or OS (p = 0.22, LRT), respectively, was found. In the initial unadjusted analysis higher PMD was associated with longer DFS and OS. The effect of PMD on DFS and OS disappeared after adjustment for age and was caused by the underlying age effect. Conclusions: Although MD is one of the strongest independent risk factors for BC, in our collective PMD is not associated with disease-free and overall survival in patients with BC.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Breast cancer; Breast cancer risk; Mammographic breast density; Mammographic density; Prognosis

Mammographic density is the main correlate of tumors detected on ultrasound but not on mammography - Haeberle, Lothar; Fasching, Peter; Brehm, Barbara; Heusinger, Katharina; Jud, Sebastian; Löhberg, Christian; Hack, Carolin; Preuss, Caroline; Lux, Michael P.; Hartmann, Arndt; Vachon, Celine M.; Meier-Meitinger, Martina; et al. (International Journal of Cancer, 2016)
Although mammography screening programs do not include ultrasound examinations, some diagnostic units do provide women with both mammography and ultrasonography. This article is concerned with estimating the risk of a breast cancer patient diagnosed in a hospital-based mammography unit having a tumor that is visible on ultrasound but not on mammography. A total of 1,399 women with invasive breast cancer from a hospital-based diagnostic mammography unit were included in this retrospective study. For inclusion, mammograms from the time of the primary diagnosis had to be available for computer-assisted assessment of percentage mammographic density (PMD), as well as Breast Imaging Reporting and Data System (BIRADS) assessment of mammography. In addition, ultrasound findings were available for the complete cohort as part of routine diagnostic procedures, regardless of any patient or imaging characteristics. Logistic regression analyses were conducted to identify predictors of mammography failure, defined as BIRADS assessment 1 or 2. The probability that the visibility of a tumor might be masked at diagnosis was estimated using a regression model with the identified predictors. Tumors were only visible on ultrasound in 107 cases (7.6%). PMD was the strongest predictor for mammography failure, but age, body mass index and previous breast surgery also influenced the risk, independently of the PMD. Risk probabilities ranged from 1% for a defined low-risk group up to 40% for a high-risk group. These findings might help identify women who should be offered ultrasound examinations in addition to mammography.
EVALuna2:6818

Management of Cervical Intraepithelial Neoplasia in Pregnant Women - Stübs, Frederik; Koch, Martin C.; Dietl, Anna; Schulmeyer, Carla; Behrens, Annika; Seibold, Anja; Adler, Werner; Geppert, Carol-Immanuel; Hartmann, Arndt; Knöll, Antje; Beckmann, Matthias; Gaß, Paul; et al. (Anticancer Research, 2023)
BACKGROUND/AIM: The aims of the present study were to evaluate the accuracy of colposcopic findings, investigate the way in which untreated cervical intraepithelial neoplasia (CIN) 2/3 develops during pregnancy, and identify factors associated with regression, persistence, or progression rates. PATIENTS AND METHODS: In a tertiary gynecology and obstetrics department, 655 pregnant women were seen for colposcopy. The most common reason for referral was abnormal cytology findings. The follow-up findings were analyzed retrospectively on the basis of colposcopic findings and cytological and histological tests. RESULTS: The rate of accuracy for major colposcopic findings was 89.2%. Among the colposcopic findings considered "suspicious for invasion" were invasive carcinoma in 42.9% and CIN 3 in 57.1%. The persistence of CIN 3 postpartum was 80% and the rate of progression 4.1%. The rate of regression for CIN 3 was 21.9%. For CIN 2, the rate of persistence was 37.5%, with a regression rate of 31.3%. The rate of regression was higher after vaginal delivery in comparison with caesarean section. CONCLUSION: The accuracy rate of colposcopy is comparatively high, at 89.2%. This might be because pregnant women are seen by more experienced examiners in our dysplasia unit. The rate of progression is comparable with that in other studies. Vaginal delivery increases the regression rate. The newborns' birth weight or birth week did not affect the rates of regression or persistence.
CRIS-Team Scopus Importer:2023-07-07
Keywords: cervical dysplasia; High-grade squamous intraepithelial lesion (HSIL); mode of delivery; pregnancy; treatment

Mass Spectrometry Imaging Differentiates Chromophobe Renal Cell Carcinoma and Renal Oncocytoma with High Accuracy - Kriegsmann, Mark; Casadonte, Rita; Maurer, Nadine; Stoehr, Christine; Erlmeier, Franziska; Moch, Holger; Junker, Klaus; Zgorzelski, Christiane; Weichert, Wilko; Schwamborn, Kristina; Deininger, Soeren-Oliver; Gaida, Matthias; et al. (Journal of Cancer, 2020)
Background: While subtyping of the majority of malignant chromophobe renal cell carcinoma (cRCC) and benign renal oncocytoma (rO) is possible on morphology alone, additional histochemical, immunohistochemical or molecular investigations are required in a subset of cases. As currently used histochemical and immunohistological stains as well as genetic aberrations show considerable overlap in both tumors, additional techniques are required for differential diagnostics. Mass spectrometry imaging (MSI) combining the detection of multiple peptides with information about their localization in tissue may be a suitable technology to overcome this diagnostic challenge.
CRIS-Team WoS Importer:2020-09-11

Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry Imaging: Diagnostic Pathways and Metabolites for Renal Tumor Entities - Erlmeier, Franziska; Sun, Na; Shen, Jian; Feuchtinger, Annette; Buck, Achim; Prade, Verena M.; Kunzke, Thomas; Schraml, Peter; Moch, Holger; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; et al. (Oncology, 2023)
Background: Correct tumor subtyping of primary renal tumors is essential for treatment decision in daily routine. Most of the tumors can be classified based on morphology alone. Nevertheless, some diagnoses are difficult, and further investigations are needed for correct tumor subtyping. Besides histochemical investigations, high-mass-resolution matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) can detect new diagnostic biomarkers and hence improve the diagnostic. Patients and Methods: Formalin-fixed paraffin embedded tissue specimens from clear cell renal cell carcinoma (ccRCC, n = 552), papillary renal cell carcinoma (pRCC, n = 122), chromophobe renal cell carcinoma (chRCC, n = 108), and renal oncocytoma (rO, n = 71) were analyzed by high-mass-resolution MALDI fourier-transform ion cyclotron resonance (FT-ICR) MSI. The SPACiAL pipeline was executed for automated co-registration of histological and molecular features. Pathway enrichment and pathway topology analysis were performed to determine significant differences between RCC subtypes. Results: We discriminated the four histological subtypes (ccRCC, pRCC, chRCC, and rO) and established the subtype-specific pathways and metabolic profiles. rO showed an enrichment of pentose phosphate, taurine and hypotaurine, glycerophospholipid, amino sugar and nucleotide sugar, fructose and mannose, glycine, serine, and threonine pathways. ChRCC is defined by enriched pathways including the amino sugar and nucleotide sugar, fructose and mannose, glycerophospholipid, taurine and hypotaurine, glycine, serine, and threonine pathways. Pyrimidine, amino sugar and nucleotide sugar, glycerophospholipids, and glutathione pathways are enriched in ccRCC. Furthermore, we detected enriched phosphatidylinositol and glycerophospholipid pathways in pRCC. Conclusion: In summary, we performed a classification system with a mean accuracy in tumor discrimination of 85.13%. Furthermore, we detected tumor-specific biomarkers for the four most common primary renal tumors by MALDI-MSI. This method is a useful tool in differential diagnosis and biomarker detection.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Chromophobe renal cell carcinoma; Clear cell renal cell carcinoma; Mass spectrometry imaging; Metabolomics; Papillary renal cell carcinoma; Renal oncocytoma

Maximizing the diagnostic information from biopsies in chronic inflammatory bowel diseases: recommendations from the Erlangen International Consensus Conference on Inflammatory Bowel Diseases and presentation of the IBD-DCA score as a proposal for a new index for histologic activity assessment in ulcerative colitis and Crohn's disease - Lang-Schwarz, Corinna; Agaimy, Abbas; Atreya, Raja; Becker, Christoph; Danese, Silvio; Flejou, Jean-Francois; Gassler, Nikolaus; Grabsch, Heike I.; Hartmann, Arndt; Kamaradova, Katerina; Kuehl, Anja A.; Lauwers, Gregory Y.; et al. (Virchows Archiv, 2020)
CRIS-Team WoS Importer:2021-01-22

MCM3 is a novel proliferation marker associated with longer survival for patients with tubo-ovarian high-grade serous carcinoma - Kang, Eun-Young; Millstein, Joshua; Popovic, Gordana; Meagher, Nicola S.; Bolithon, Adelyn; Talhouk, Aline; Chiu, Derek S.; Anglesio, Michael S.; Leung, Betty; Tang, Katrina; Lambie, Neil; Pavanello, Marina; et al. (Virchows Archiv, 2021)
Tubo-ovarian high-grade serous carcinomas (HGSC) are highly proliferative neoplasms that generally respond well to platinum/taxane chemotherapy. We recently identified minichromosome maintenance complex component 3 (MCM3), which is involved in the initiation of DNA replication and proliferation, as a favorable prognostic marker in HGSC. Our objective was to further validate whether MCM3 mRNA expression and possibly MCM3 protein levels are associated with survival in patients with HGSC. MCM3 mRNA expression was measured using NanoString expression profiling on formalin-fixed and paraffin-embedded tissue (N = 2355 HGSC) and MCM3 protein expression was assessed by immunohistochemistry (N = 522 HGSC) and compared with Ki-67. Kaplan-Meier curves and the Cox proportional hazards model were used to estimate associations with survival. Among chemotherapy-naive HGSC, higher MCM3 mRNA expression (one standard deviation increase in the score) was associated with longer overall survival (HR = 0.87, 95% CI 0.81-0.92, p < 0.0001, N = 1840) in multivariable analysis. MCM3 mRNA expression was highest in the HGSC C5.PRO molecular subtype, although no interaction was observed between MCM3, survival and molecular subtypes. MCM3 and Ki-67 protein levels were significantly lower after exposure to neoadjuvant chemotherapy compared to chemotherapy-naive tumors: 37.0% versus 46.4% and 22.9% versus 34.2%, respectively. Among chemotherapy-naive HGSC, high MCM3 protein levels were also associated with significantly longer disease-specific survival (HR = 0.52, 95% CI 0.36-0.74, p = 0.0003, N = 392) compared to cases with low MCM3 protein levels in multivariable analysis. MCM3 immunohistochemistry is a promising surrogate marker of proliferation in HGSC.
CRIS-Team WoS Importer:2021-11-26

Mdm2 SNP309 G-Variant Is Associated with Invasive Growth of Human Urinary Bladder Cancer - Hitzenbichler, Florian; Stoehr, Christine G.; Rogenhofer, Michael; Wieland, Wolf F.; Ruemmele, Petra; Hartmann, Arndt; Stoehr, Robert (Pathobiology, 2014)
Objective: Human mouse double minute 2 (Mdm2) is essential in degrading p53 by acting as an ubiquitin ligase and therefore plays a vital role in cell cycle and survival. The G-variant of the Mdm2 SNP309, which is located within the promoter of the Mdm2 gene, increases expression of Mdm2 and thereby inhibits the p53 pathway. Several studies have investigated the influence of this SNP on disease risk and onset of various malignancies. The impact of Mdm2 SNP309 on bladder cancer is still to be established due to inconsistent data. Methods: In a case-control study we determined the distribution of Mdm2 SNP309 genotypes in 111 patients with an early-onset bladder cancer (diagnosis <45 years of age), in 113 consecutive bladder cancer patients and in a control group consisting of 140 patients without any malignancy. Results: There was no significant association between the allelic distribution of the Mdm2 SNP309 and tumor risk, early onset, gender or grade of the tumor. According to tumor stage we found a significant difference in the distribution of the Mdm2 SNP309 between patients with noninvasive and invasive (>=pT1) tumor growth (p = 0.016). In patients with invasive tumors a significant increase of the G allele was found (T/T vs. T/G + G/G; p = 0.023; OR 2.203, 95% CI 1.111-4.369). Conclusion: These data indicate that the G-variant of the Mdm2 SNP309 might influence the development of a more aggressive tumor phenotype in patients with bladder cancer without affecting the overall tumor risk. © 2013 S. Karger AG, Basel.
EVALuna2:6569

Melanoma-associated leukoderma and vitiligo cannot be differentiated based on blinded assessment by experts in the field - Lommerts, Janny E.; Teulings, Hansje-Eva; Ezzedine, Khaled; Van Geel, Nanja; Hartmann, Arndt; Speeckaert, Reinhart; Spuls, Phyllis I.; Wolkerstorfer, Albert; Luiten, Rosalie M.; Bekkenk, Marcel W. (Journal of the American Academy of Dermatology, 2016)
Melanoma-associated leukoderma (MAL) is a depigmenting disorder that can occur spontaneously in patients with melanoma. The differences in clinical presentation between MAL and vitiligo are not well defined. This may lead to misdiagnosing MAL as vitiligo, resulting in delayed detection of melanoma.The objective of this study was to assess whether experts in the field can distinguish between MAL and vitiligo, and to assess if discriminative features can be identified.We designed an image comparison study in which 4 experts in the field blindly assessed photographs followed by medical history of 11 patients with MAL and 33 with vitiligo.The assessors misdiagnosed 72.7% of MAL cases and marked 80.0% of them as typical vitiligo. The median age at onset of the leukoderma was higher (55 years, P = .001) in MAL. No discriminative features were found.Sampling bias because of inclusion in tertiary referral center is a limitation.The clinical presentation of leukoderma in patients with melanoma resembles that of vitiligo. We propose "melanoma-associated vitiligo" as the more appropriate term for leukoderma in patients with melanoma. Clinicians should be aware that depigmentation in vitiligo can also be caused by melanoma-associated vitiligo and a total body inspection should be performed.
EVALuna2:19617

Mesenchymal tumors of the urinary bladder - Agaimy, Abbas; Hartmann, Arndt (Pathologe, 2016)
Mesenchymal tumors and tumor-like lesions of the urinary bladder are rare. They encompass a heterogeneous group of reactive pseudosarcomatous tumor-like changes and benign neoplastic lesions as well as malignant neoplasms (sarcomas) with variable biological behavior. The well-known differential diagnostic difficulties related to these conditions are mainly due to their rarity and thus limited experience and familiarity with their histological features and due to the significant morphological overlap between fully benign reactive conditions and aggressive malignant neoplasms. The distinction between them may on occasion represent a real challenge and is associated with several pitfalls. This overview summarizes the clinicopathological and differential diagnostic aspects of the most important lesions and discuss their differential diagnosis in the light of current knowledge.
EVALuna2:6784

Metabolic and Lipidomic Reprogramming in Renal Cell Carcinoma Subtypes Reflects Regions of Tumor Origin - Schaeffeler, Elke; Büttner, Florian; Reustle, Anna; Klumpp, Verena; Winter, Stefan; Rausch, Steffen; Fisel, Pascale; Hennenlotter, Jörg; Kruck, Stephan; Stenzl, Arnulf; Wahrheit, Judith; Sonntag, Denise; et al. (European Urology Focus, 2018)
BACKGROUND: Renal cell carcinoma (RCC) consists of prognostic distinct subtypes derived from different cells of origin (eg, clear cell RCC [ccRCC], papillary RCC [papRCC], and chromophobe RCC [chRCC]). ccRCC is characterized by lipid accumulation and metabolic alterations, whereas data on metabolic alterations in non-ccRCC are limited. OBJECTIVE: We assessed metabolic alterations and the lipid composition of RCC subtypes and ccRCC-derived metastases. Moreover, we elucidated the potential of metabolites/lipids for subtype classification and identification of therapeutic targets. DESIGN, SETTING, AND PARTICIPANTS: Metabolomic/lipidomic profiles were quantified in ccRCC (n=58), chRCC (n=19), papRCC (n=14), corresponding nontumor tissues, and metastases (n=9) through a targeted metabolomic approach. Transcriptome profiling was performed in corresponding samples and compared with expression data of The Cancer Genome Atlas cohorts (patients with ccRCC, n=452; patients with papRCC, n=260; and patients with chRCC, n=59). OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: In addition to cluster analyses, metabolomic/transcriptomic data were analyzed to evaluate metabolic differences of ccRCC and chRCC using Welch's t test or paired t test as appropriate. Where indicated, p values were adjusted for multiple testing using Bonferroni or Benjamini-Hochberg correction. RESULTS AND LIMITATIONS: Based on their metabolic profiles, RCC subtypes clustered into two groups separating ccRCC and papRCC from chRCC, which mainly reflected the different cells of origin. ccRCC-derived metastases clustered with primary ccRCCs. In addition to differences in certain lipids (lysophosphatidylcholines and sphingomyelins), the coregulation network of lipids differed between ccRCC and chRCC. Consideration of metabolic gene expression indicated, for example, alterations of the polyamine pathway at metabolite and transcript levels. In vitro treatment of RCC cells with the ornithine-decarboxylase inhibitor difluoromethylornithine resulted in reduced cell viability and mitochondrial activity. Further evaluation of clinical utility was limited by the retrospective study design and cohort size. CONCLUSIONS: In summary, we provide novel insight into the metabolic profiles of ccRCC and non-ccRCC, thereby confirming the different ontogeny of RCC subtypes. Quantification of differentially regulated metabolites/lipids improves classification of RCC with an impact on the identification of novel therapeutic targets. PATIENT SUMMARY: Several subtypes of renal cell carcinoma (RCC) with different metastatic potentials and prognoses exist. In the present study, we provide novel insight into the metabolism of these different subtypes, which improves classification of subtypes and helps identify novel targets for RCC therapy.
EVALuna2:34809

Met amplification in non‐small cell lung cancer (Nsclc)— a consecutive evaluation using next‐generation sequencing (ngs) in a real‐world setting - Schubart, Christoph; Stöhr, Robert; Tögel, Lars; Fuchs, Florian; Sirbu, Horia; Seitz, Gerhard; Seggewiss‐bernhardt, Ruth; Leistner, Rumo; Sterlacci, William; Seidl, Christoph; Mugler, Michael; Kapp, Markus; et al. (Cancers, 2021)
In non‐small cell lung cancer (NSCLC), approximately 1–3% of cases harbor an increased gene copy number (GCN) of the MET gene. This alteration can be due to de novo amplification of the MET gene or can represent a secondary resistance mechanism in response to targeted therapies. To date, the gold standard method to evaluate the GCN of MET is fluorescence in situ hybridization (FISH). However, next‐generation sequencing (NGS) is becoming more relevant to optimize therapy by revealing the mutational profile of each NSCLC. Using evaluable n = 205 NSCLC cases of a consecutive cohort, this study addressed the question of whether an amplicon based NGS assay can completely replace the FISH method regarding the classification of MET GCN status. Out of the 205 evaluable cases, only n = 9 cases (43.7%) of n = 16 high‐level MET amplified cases assessed by FISH were classified as amplified by NGS. Cases harboring a MET GCN >10 showed the best concordance when comparing FISH versus NGS (80%). This study confirms that an amplicon‐based NGS assessment of the MET GCN detects high‐level MET amplified cases harboring a MET GCN >10 but fails to detect the various facets of MET gene amplification in the context of a therapy‐induced resistance mechanism.
CRIS-Team Scopus Importer:2021-10-22
Keywords: Amplification; Fluorescence in situ hybridization; MET; MET inhibitor; Next‐generation sequencing; NSCLC; Precision medicine; Resistance mechanism

Metastatic Malignant Melanoma With Complete Loss of Differentiation Markers (Undifferentiated/Dedifferentiated Melanoma): Analysis of 14 Patients Emphasizing Phenotypic Plasticity and the Value of Molecular Testing as Surrogate Diagnostic Marker - Agaimy, Abbas; Specht, Katja; Stoehr, Robert; Lorey, Thomas; Maerkl, Bruno; Niedobitek, Gerald; Straub, Melanie; Hager, Thomas; Reis, Anna-Carinna; Schilling, Bastian; Schneider-Stock, Regine; Hartmann, Arndt; et al. (American Journal of Surgical Pathology, 2016)
Metastatic malignant melanoma is notorious for its phenotypic diversity and loss of differentiation markers. We herein summarized our experience with 14 metastatic melanomas showing complete loss of immunohistochemical melanocytic markers (with or without heterologous differentiation). Patients included 11 men and 3 women aged 24 to 78 years (median, 67 y). Thirteen patients had histologically confirmed primary skin melanoma, and 1 had metastatic melanoma of unknown primary. Undifferentiated metastasis was diagnosed synchronous to primary tumor (n=1), following skin melanoma by 3 months to 9 years (n=11) and preceding it by 1 year (n=1). Sites of undifferentiated metastases were axillary (3), inguinal (1), or submandibular (1) lymph nodes, digestive tract (2), bone/soft tissue (2), lung/pleura (2), and disseminated (n=3). Histology of metastases mimicked undifferentiated pleomorphic or spindle cell sarcoma with variable myxoid and giant cell areas (n=10) and cytokeratin-positive undifferentiated small cell sarcoma (n=1). Three cases showed heterologous dedifferentiation: pleomorphic rhabdomyosarcoma (n=1), teratocarcinosarcoma-like with prominent rhabdomyoblasts (n=1), and adenocarcinoma-like with metaplastic bone (n=1). All cases were negative for S100, melanoma cocktail, HMB45, Melan A, and SOX10. Other markers showed following results: smooth muscle actin (1/14), p16 (1/14), TP53 (2/12), pancytokeratin (4/14), desmin (5/14), h-caldesmon (0/9), and MDM2/CDK4 (0/5). SMARCB1 was intact in 8/8 cases. Genotyping showed BRAF(V600E) mutation (5/14), NRAS mutation (5/14), and BRAF/NRAS wild-type (4/14). In conclusion, undifferentiated/dedifferentiated metastatic melanoma is likely underrecognized and frequently mistaken for undifferentiated sarcoma or other neoplasms. Diagnosis of undifferentiated sarcoma at sites where melanoma metastasis are frequent (eg, inguinal and axillary region) should be made with great caution and warrants exploration of the remote history. Genotyping is a helpful surrogate marker in classifying such difficult cases. In the light of available targeted therapies, recognition of undifferentiated/dedifferentiated metastatic melanoma is mandatory for appropriate treatment.
EVALuna2:6798

Metastatic risk stratification of clear cell renal cell carcinoma patients based on genomic aberrations - Grimm, Julia; Zeuschner, Philip; Janssen, Martin; Wagenpfeil, Stefan; Hartmann, Arndt; Stöhr, Christine; Keck, Bastian; Kahlmeyer, Andreas; Stöckle, Michael; Junker, Kerstin (Genes Chromosomes & Cancer, 2019)
Prognostic markers for the definition of the individual metastatic risk in renal cell carcinoma are still missing. The aim of our study was to establish a total number of specific aberrations (TNSA) genetic score as a new prognostic test for metastatic risk evaluation. Fluorescence in situ hybridization (FISH) was performed on isolated cell nuclei of 100 ccRCCs (50 M1/50 M0) and 100 FFPE sections (second cohort, 32 M1/68 M0). For each chromosomal region (1q21.3, 7q36.3, 9p21.3p24.1, 20q11.21q13.32) cut-off values were determined by receiver-operator curve (ROC)-curve analysis. TNSA was calculated based on the dichotomized specific CNVs. The prognostic significance of CNVs was proven by Cox and logistic regression. TNSA was the best predictor of metastasis and recurrence free survival in both cohorts. We derived an algorithm for risk stratification by combining TNSA and T-category, which increased the prognostic accuracy to 87% (specificity = 86%, sensitivity = 88%). This model divides patients into two risk groups with significantly different RFS, CSS, and OS (P = 3.8×10−5, P = 5×10−6 and P = 3.57×10−8 respectively). The genetic risk model was superior to Leibovich score and was able to identify patients with metachronous metastatic spread which were incorrectly classified as “low” or “intermediate risk.” We present a new tool for individual risk stratification by combining genetic alterations with clinico-pathologic parameters. Interphase FISH proves to be a dependable method for prognostic evaluation in primary tumor tissue on isolated cell nuclei as well as on FFPE sections. Especially in organ-confined tumors the genetic score seems to be an important tool to identify patients at high risk for metastatic disease.
CRIS-Team Scopus Importer:2019-07-12
Keywords: FISH; genomics; metastasis; prognosis; renal cell carcinoma

Methylomes of renal cell lines and tumors or metastases differ significantly with impact on pharmacogenes - Winter, Stefan; Fisel, Pascale; Buettner, Florian; Rausch, Steffen; D'Amico, Debora; Hennenlotter, Joerg; Kruck, Stephan; Nies, Anne T.; Stenzl, Arnulf; Junker, Kerstin; Scharpf, Marcus; Hofmann, Ute; et al. (Scientific Reports, 2016)
Current therapies for metastatic clear cell renal cell carcinoma (ccRCC) show limited efficacy. Drug efficacy, typically investigated in preclinical cell line models during drug development, is influenced by pharmacogenes involved in targeting and disposition of drugs. Here we show through genome-wide DNA methylation profiling, that methylation patterns are concordant between primary ccRCC and macro-metastases irrespective of metastatic sites (rs >= 0.92). However, 195,038 (41%) of all investigated CpG sites, including sites within pharmacogenes, were differentially methylated (adjusted P < 0.05) in five established RCC cell lines compared to primary tumors, resulting in altered transcriptional expression. Exemplarily, gene-specific analyses of DNA methylation, mRNA and protein expression demonstrate lack of expression of the clinically important drug transporter OCT2 (encoded by SLC22A2) in cell lines due to hypermethylation compared to tumors or metastases. Our findings provide evidence that RCC cell lines are of limited benefit for prediction of drug effects due to epigenetic alterations. Similar epigenetic landscape of ccRCC-metastases and tumors opens new avenue for future therapeutic strategies.
EVALuna2:6920

Metric substage according to micro and extensive lamina propria invasion improves prognostics in T1 bladder cancer - Van De Putte, Elisabeth E. Fransen; Otto, Wolfgang; Hartmann, Arndt; Bertz, Simone; Mayr, Roman; Bruendl, Johannes; Breyer, Johannes; Manach, Quentin; Comperat, Eva M.; Boormans, Joost L.; Bosschieter, Judith; Jewett, Michael A. S.; et al. (Urologic Oncology-Seminars and Original Investigations, 2018)
BACKGROUND: Reliable prognosticators for T1 bladder cancer (T1BC) are urgently needed. OBJECTIVE: To compare the prognostic value of 2 substage systems for T1BC in patients treated by transurethral resection (TUR) and adjuvant bacillus Calmette-Guérin therapy. DESIGN, SETTING, AND PARTICIPANTS: The slides of 601 primary T1BCs from four institutes were reviewed by 2 uropathologists and substaged according to 2 classifications: metric substage according to T1 microinvasive (T1m-lamina propria invasion <0.5mm) and T1 extensive invasive (pT1e-invasion ≥ 0.5mm), and according to invasion of the muscularis mucosae (MM) (T1a-invasion above or into MM/T1b). OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Multivariable analyses for progression-free (PFS) and cancer-specific survival (CSS) were performed including substage, size, multiplicity, carcinoma in situ, sex, age, WHO-grade 1973, and WHO-grade 2004 as variables. RESULTS: Median follow-up was 5.9 years (interquartile range: 3.3-9.0). Progression to T2BC was observed in 148 (25%) patients and 94 (16%) died of BC. The MM was not present at the invasion front in 135 (22%) of tumors. Slides were substaged as follows: 213 T1m and 388 T1e and 281 T1a and 320 T1b. On multivariable analysis, T1m/e substage and WHO 1973 grade were the strongest prognosticators for PFS (hazard ratio [HR] = 3.8 and HR = 1.8) and CSS (HR = 2.7 and HR = 2.6), respectively. Other prognostic factors for CSS were age (HR = 1.03), and tumor size (HR = 1.8). Substage according to MM-invasion was not significant. Our study was limited by its retrospective design and that standard re-TUR was not performed if TUR was macroscopically complete and muscularis propria was present in resected specimens. CONCLUSIONS: Metric substaging of T1BC was possible in all cases of 601 T1BC patients and it was a strong independent prognosticator of both PFS and CSS.
EVALuna2:34306

Micropapillary morphology is an indicator of poor prognosis in patients with urothelial carcinoma treated with transurethral resection and radiochemotherapy - Bertz, Simone; Wach, S.; Taubert, Helge; Merten, Ricarda; Krause, F. S.; Schick, S.; Ott, O. J.; Weigert, E.; Dworak, O.; Roedel, C.; Fietkau, Rainer; Wullich, Bernd; et al. (Virchows Archiv, 2016)
Purpose of this study was to evaluate prognostic impact of rare variants of urothelial bladder cancer (BC) after treatment with combined radiochemotherapy (RCT). To this end tumour tissue of 238 patients with urothelial carcinoma (UC) treated with transurethral resection of the bladder (TUR-B) and RCT with curative intent was collected. Histomorphological analysis included re-evaluation and semi-quantitative assessment of rare UC subtypes. Additionally, human epidermal growth factor receptor 2 (HER2) chromogenic in situ hybridisation (CISH) was performed in tumours with a micropapillary component exceeding 30 %. Long-term follow-up was available for 200 patients (range 3-282 months). Variant UC histology was found in 45 of 238 tumours, most frequently micropapillary UC (N = 17) including cases with a small fraction of tumour with micropapillary morphology. The mere presence of micropapillary morphology did not affect prognosis. In tumours with extensive (>=30 %) micropapillary morphology (N = 8) Kaplan-Meier analysis revealed significantly worse cancer specific survival (CSS) (P = 0.002) compared to conventional UC (mean survival times 97 months and 229 months, respectively). Univariate Cox regression analysis of cases with >=30 % micropapillary morphology revealed a hazard ratio of 4.726 (95 % CI 1.629-13.714) for CSS (P = 0.004). CISH revealed HER2 gene amplification in 3/10 tumours with >=30 % micropapillary component. In conclusion, for BC treated with TUR-B and RCT, the presence of micropapillary morphology in more than 30 % of the tumour is an adverse prognostic factor. Further studies are needed to evaluate a potential benefit of different, especially multimodal treatment strategies for micropapillary UC and also other subtypes of UC. Her2 represents a promising therapeutic target in a subset of micropapillary UC.
EVALuna2:6800

Micropapillary urothelial carcinoma: evaluation of HER2 status and immunohistochemical characterization of the molecular subtype - Zinnall, Ulrike; Weyerer, Veronika; Compérat, Eva; Camparo, Philippe; Gaisa, Nadine T.; Knuechel-Clarke, Ruth; Perren, Aurel; Lugli, Alessandro; Toma, Marieta; Baretton, Gustavo; Kristiansen, Glen; Wirtz, Ralph M.; et al. (Human Pathology, 2018)
Comprehensive molecular analyses of urothelial bladder cancer (UBC) have defined distinct subtypes with potential therapeutic implications. In this study, we focused on micropapillary urothelial carcinoma (MPUC), an aggressive, histomorphologically defined rare variant. Apart from genetic alterations shared with conventional UBC alterations of the HER2 gene have been reported in higher frequencies. However, only small cohorts of MPUCs have been analyzed and the real impact is still unclear. We collected a cohort of 94 MPUCs and immunohistochemically tested HER2, basal (CD44, CK5, EGFR, p63) and luminal (CD24, FOXA1, GATA3, CK20) markers to allocate MPUC to a molecular subtype. Additionally, HER2 amplification status was assigned by chromogenic in-situ-hybridization. Sanger sequencing of Exon 4 and 8 was used to test for HER2 mutations. Kruskal-Wallis test was calculated to compare marker distribution between proportions of the MPUC component. 2+/3+ HER2 staining scores were identified in 39.6% of 91 analyzed MPUCs and were not differentially distributed among the proportion of the MPUC component (P=.89). Additionally, CISH analysis revealed 30% of HER2 amplified tumors independently of the MPUC fraction. In 6/90 evaluable MPUCs a p.S310F HER2 mutation was detected. Overexpression of luminal markers was observed in the majority of MPUC. Our investigations of the largest cohort of analyzed MPUC demonstrate that HER2 overexpression and amplifications are common genetic alterations and identification of overexpressed luminal markers allows sub-classification to the luminal subtype. These findings highlight the need of histomorphological recognition of MPUC and analysis of HER2 status and the luminal molecular subtype for potential targeted therapeutic strategies.
EVALuna2:34304

miRNA-26b Overexpression in Ulcerative Colitis-associated Carcinogenesis - Benderska, Natalya; Dittrich, Anna-Lena; Knaup, Sabine; Rau, Tilman; Neufert, Clemens; Wach, Sven; Fahlbusch, Fabian B.; Rauh, Manfred; Wirtz, Ralph M.; Agaimy, Abbas; Srinivasan, Swetha; Mahadevan, Vijayalakshmi; et al. (Inflammatory Bowel Diseases, 2015)
Longstanding ulcerative colitis (UC) bears a high risk for development of UC-associated colorectal carcinoma (UCC). The inflammatory microenvironment influences microRNA expression, which in turn deregulates target gene expression. microRNA-26b (miR-26b) was shown to be instrumental in normal tissue growth and differentiation. Thus, we aimed to investigate the impact of miR-26b in inflammation-associated colorectal carcinogenesis.Two different cohorts of patients were investigated. In the retrospective group, a tissue microarray with 38 samples from 17 UC/UCC patients was used for miR-26b in situ hybridization and quantitative reverse transcription polymerase chain reaction analyses. In the prospective group, we investigated miR-26b expression in 25 fresh-frozen colon biopsies and corresponding serum samples of 6 UC and 15 non-UC patients, respectively. In silico analysis, Ago2-RNA immunoprecipitation, luciferase reporter assay, quantitative reverse transcription polymerase chain reaction examination, and miR-26b mimic overexpression were employed for target validation.miR-26b expression was shown to be upregulated with disease progression in tissues and serum of UC and UCC patients. Using miR-26b and Ki-67 expression levels, an UCC was predicted with high accuracy. We identified 4 novel miR-26b targets (DIP1, MDM2, CREBBP, BRCA1). Among them, the downregulation of the E3 ubiquitin ligase DIP1 was closely related to death-associated protein kinase stabilization along the normal mucosa-UC-UCC sequence. In silico functional pathway analysis revealed that the common cellular pathways affected by miR-26b are highly related to cancerogenesis and the development of gastrointestinal diseases.We suggest that miR-26b could serve as a biomarker for inflammation-associated processes in the gastrointestinal system. Because miR-26b expression is downregulated in sporadic colon cancer, it could discriminate between UCC and the sporadic cancer type.
EVALuna2:1970

Mirna expression characterizes histological subtypes and metastasis in penile squamous cell carcinoma - Ayoubian, Hiresh; Heinzelmann, Joana; Hölters, Sebastian; Khalmurzaev, Oybek; Pryalukhin, Alexey; Loertzer, Philine; Heinzelbecker, Julia; Lohse, Stefan; Geppert, Carol-Immanuel; Loertzer, Hagen; Wunderlich, Heiko; Bohle, Rainer M.; et al. (Cancers, 2021)
Although microRNAs are described as promising biomarkers in many tumor types, little is known about their role in PSCC. Thus, we attempted to identify miRNAs involved in tumor development and metastasis in distinct histological subtypes considering the impact of HPV infection. In a first step, microarray analyses were performed on RNA from formalin-fixed, paraffin-embedded tumor (22), and normal (8) tissue samples. Microarray data were validated for selected miRNAs by qRT-PCR on an enlarged cohort, including 27 tumor and 18 normal tissues. We found 876 significantly differentially expressed miRNAs (p ≤ 0.01) between HPV-positive and HPV-negative tumor samples by microarray analysis. Although no significant differences were detected between normal and tumor tissue in the whole cohort, specific expression patterns occurred in distinct histological subtypes, such as HPV-negative usual PSCC (95 differentially expressed miRNAs, p ≤ 0.05) and HPV-positive basaloid/warty subtypes (247 differentially expressed miRNAs, p ≤ 0.05). Selected miRNAs were confirmed by qRT-PCR. Furthermore, microarray data revealed 118 miRNAs (p ≤ 0.01) that were significantly differentially expressed in metastatic versus non-metastatic usual PSCC. The lower expression levels for miR-137 and miR-328-3p in metastatic usual PSCC were validated by qRT-PCR. The results of this study confirmed that specific miRNAs could serve as potential diagnostic and prognostic markers in single PSCC subtypes and are associated with HPV-dependent pathways.
CRIS-Team Scopus Importer:2021-04-02
Keywords: HPV; Microarray; MiRNA; PSCC

miRNA expression characterizes histological subtypes and metastasis in penile squamous cell carcinoma - Hiresh, A.; Heinzelmann, J.; Hoelters, S.; Khalmurzaev, O.; Pryalukhin, A.; Loertzer, P.; Heinzelbecker, J.; Lohse, S.; Geppert, Carol-Immanuel; Loertzer, H.; Wunderlich, H.; Bohle, R. M.; et al. (EUROPEAN UROLOGY, 2021)
CRIS-Team WoS Importer:2021-08-20

Misleading Germ Cell Phenotype in Pulmonary NUT Carcinoma Harboring the ZNF532-NUTM1 Fusion - Agaimy, Abbas; Haller, Florian; Renner, Andre; Niedermeyer, Jost; Hartmann, Arndt; French, Christopher A. (American Journal of Surgical Pathology, 2022)
NUT carcinoma (aka NUT midline carcinoma) is a rare, still significantly underrecognized aggressive malignancy. Although historically considered a midline malignancy of children and young adults, NUT carcinoma can originate in almost any body site and in any age group. Beside the classic BRD4-NUTM1 fusion, less common fusion partners include BRD3, NSD3, ZNF532, and ZNF592. Other fusions, including CIC, MGA, MXD4, MXD1, and BCORL1 are associated with sarcomas or cancers of unknown histogenesis. Involvement of the Z4 zinc finger protein (ZNF) family members ZNF532 and ZNF592 is exceedingly rare with only 3 recently reported cases. We herein describe a ZNF532-NUTM1-rearranged NUT carcinoma presenting as a 7.5 cm mass in the left lower lung lobe of a 65-year-old woman. Histology revealed undifferentiated monotonous small round cells with focal epithelioid and rhabdoid elements within a variably myxoid stroma. Immunohistochemistry revealed paucity of keratins and variable p63 combined with extensive CD30 and PLAP expression, leading to initial diagnoses of combined small cell carcinoma, CD30-positive unclassified hematolymphoid malignancy and malignant germ cell neoplasm. Negativity for other more specific germ cell markers justified seeking a fourth opinion, which revealed diffuse expression of the NUT antibody. The diagnosis was then confirmed by fluorescence in situ hybridization. Targeted RNA sequencing revealed the ZNF532-NUTM1 fusion. Screening of 7 NUT carcinomas (5 with BRD4-NUTM1 and 2 with NSD3-NUTM1 fusions) for germ cell markers revealed focal SALL4 reactivity in 3 cases (combined with variable AFP expression in 2), but none expressed CD30 or PLAP. An aberrant germ cell immunophenotype should be considered in NUT carcinoma to avoid misinterpretation as genuine germ cell malignancy as both diseases predominantly affect the young population, frequently involve the mediastinum and can be associated with elevated serum AFP.
CRIS-Team WoS Importer:2022-01-28

Mitophagy-associated genes PINK1 and PARK2 are independent prognostic markers of survival in papillary renal cell carcinoma and associated with aggressive tumor behavior - Simon, Adrian Georg; Tolkach, Yuri; Esser, Laura Kristin; Ellinger, Jörg; Stoehr, Christine; Ritter, Manuel; Wach, Sven; Taubert, Helge; Stephan, Carsten; Hartmann, Arndt; Kristiansen, Glen; Branchi, Vittorio; et al. (Scientific Reports, 2020)
The aim of this study was to investigate the mitophagy-related genes PINK1 and PARK2 in papillary renal cell carcinoma and their association with prognosis. In silico data of PINK1 and PARK2 were analyzed in TCGA cohorts of papillary renal cell carcinoma comprising 290 tumors and 33 corresponding non-neoplastic renal tissues. Protein expression data from a cohort of 95 papillary renal cell carcinoma patients were analyzed and associated with clinical-pathological parameters including survival. PINK1 and PARK2 were significantly downregulated in papillary renal cell carcinoma at transcript and protein levels. Reduced transcript levels of PINK1 and PARK2 were negatively associated with overall survival (p < 0.05). At the protein level, PARK2 and PINK1 expression were positively correlated (correlation coefficient 0.286, p = 0.04) and reduced PINK1 protein expression was prognostic for shorter survival. Lower PINK1 protein levels were found in tumors with metastases at presentation and in tumors of higher pT-stages. The multivariate analysis revealed mRNA expression of PINK1 and PARK2 as well as PINK1 protein expression as independent prognostic factors for shorter overall survival. The downregulation of PINK1 is a strong predictor of poor survival in papillary renal cell carcinoma. Immunohistochemical PINK1 expression in resected pRCC should be considered as an additional prognostic marker for routine practice.
CRIS-Team Scopus Importer:2020-11-13

Molecular Characterisation of Urothelial Bladder Cancer: Will it Improve Patient Care? - Erben, P.; Hartmann, Arndt; Bolenz, C. (Aktuelle Urologie, 2015)
Urothelial bladder cancer is characterised by high recurrence and progression rates despite multimodal treatment. Only slight improvements have been achieved during the last decades. The current histopathological classification and clinical risk stratification tools are inaccurate. Hence, a better understanding of the tumour biology is essential for the improvement of patient care. The molecular characterisation of bladder cancer may be translated into useful diagnostic and predictive biomarkers. Many potential therapeutic targets have been identified such as FGFR3 (Fibroblast growth factor receptor 3), HER2 (human epidermal growth factor receptor 2) and PD1/PDL1 (programmed cell death-1). They need validation in clinical trials. We now review the molecular biology of urothelial bladder carcinoma and discuss clinical applications of biomarkers and targeted therapies.
EVALuna2:6754

Molecular characterization of muellerian tumors of the urinary tract - Ortiz-Brüchle, Nadina; Wucherpfennig, Sophie; Rose, Michael; Garczyk, Stefan; Bertz, Simone; Hartmann, Arndt; Reis, Henning; Szarvas, Tibor; Kiss, András; Bremmer, Felix; Golz, Reinhard; Knüchel, Ruth; et al. (Genes, 2021)
In the 2016 WHO classification of genitourinary tumors Muellerian tumors of the urinary tract (MTUT) comprise clear cell adenocarcinomas and endometrioid carcinomas. Since these rare tumors remained understudied, we aimed to characterize their molecular background by performing DNA-and RNA-based targeted panel sequencing. All tumors (n = 11) presented single nucleotide alterations (SNVs), with ARID1A mutations being the most prevalent (5/11, 45%). Besides frequent ARID1A mutations, loss of ARID1A protein is not a suitable marker since protein expression is (partly) preserved also in mutated cases. Copy number alterations (CNVs) were found in 64% of cases (7/11), exclusively gene amplifications. Interestingly, a functionally relevant RSPO2 gene fusion/microdeletion was discovered in the endometrioid adenocarcinoma case. Comparing our findings with mutational profiles of other tumor entities, absence of TERT promoter mutations argues for a non-urothelial origin. No similarities were also found between MTUT and kidney cancers while parallels were observed for specific SNVs with endometrial carcinomas. In conclusion, immunohistochemical PAX8-positivity and lack of TERT promoter mutations could serve as key diagnostic features in difficult cases. Thus, understanding the molecular background of these tumors helps to refine treatment options and offers the possibility of targeted therapies in cases where needed.
CRIS-Team Scopus Importer:2021-07-02
Keywords: ARID1A; Clear cell adenocarcinoma; Endometrioid adenocarcinoma; Muellerian tumors; TERT

Molecular Characterization of Upper Tract Urothelial Carcinoma in the Era of Next-generation Sequencing: A Systematic Review of the Current Literature - Hassler, Melanie R.; Bray, Freddie; Catto, James W.F.; Grollman, Arthur P.; Hartmann, Arndt; Margulis, Vitaly; Matin, Surena F.; Roupret, Morgan; Sfakianos, John P.; Shariat, Shahrokh F.; Faltas, Bishoy M. (European Urology, 2020)
Context: While upper tract urothelial carcinoma (UTUC) share histological appearance with bladder cancer (BC), the former has differences in etiology and clinical phenotype consistent with characteristic molecular alterations. Objective: To systematically evaluate current genomic sequencing and proteomic data examining molecular alterations in UTUC. Evidence acquisition: A systematic review using PubMed, Scopus, and Web of Science was performed in December 2019 according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement. Evidence synthesis: A total of 46 publications were selected for inclusion in this report, including 13 studies assessing genome-wide alterations, 18 studies assessing gene expression or microRNA expression profiles, three studies assessing proteomics, one study assessing genome-wide DNA methylation, and 14 studies evaluating distinct pathway alteration patterns. Differences between sporadic and hereditary UTUC, and between UTUC and BC, as well as molecular profiles associated with exposure to aristolochic acid are highlighted. Molecular pathways relevant to UTUC biology, such as alterations in FGFR3, TP53, or microsatellite instability, are discussed. Our findings are limited by tumor and patient heterogeneity and different platforms used in the studies. Conclusions: Molecular events in UTUC and BC can be shared or distinct. Consequently, molecular subtypes differ according to location. Further work is needed to define the epigenomic and proteomic features of UTUC, and understand the mechanisms by which they shape the clinical behavior of UTUC. Patient summary: We report the current data on the molecular alterations specific to upper tract urothelial carcinoma (UTUC), resulting from novel genomic and proteomic technologies. Although UTUC biology is comparable with that of bladder cancer, the rates and UTUC-enriched alterations support its uniqueness and the need for precision medicine strategies for this rare tumor type. Recent data obtained by high-throughput molecular profiling technologies underscore the distinct molecular alterations found in upper tract urothelial carcinoma (UTUC). UTUC biology shares many features with bladder cancer, but there are important specific distinctions that support the need for UTUC-targeted therapeutic strategies.
CRIS-Team Scopus Importer:2020-06-30
Keywords: Genomics; Molecular alterations; Molecular characterization; Next-generation sequencing; Proteomics; Renal pelvis; RNAseq; Transcriptomics; Ureter; Urothelial carcinoma

Molecular classification of bladder cancer. Possible similarities to breast cancer - Wirtz, R. M.; Fritz, V.; Stoehr, R.; Hartmann, Arndt (Pathologe, 2016)
Therapeutic decisions for breast cancer are increasingly becoming based on subtype-specific gene expression tests. For bladder cancer very similar subtypes have been identified by genome-wide mRNA analysis, which as for breast cancer differ with respect to the prognosis and response to therapy on the basis of their hormone dependency. At the DNA level, however, the type of mutations and their frequencies within the subtypes are strikingly different between bladder and breast cancers. It will be interesting to see whether possible driver mutations can serve as therapeutic targets in both indications. In contrast, the apparent hormone dependency of a substantial number of bladder carcinomas suggests that hormonal and anti-hormonal treatment can be valid therapy options similar to breast cancer. Moreover, gender-specific differences with respect to the incidence and aggressiveness of male compared to female bladder cancers can be explained by hormonal effects. Together with forthcoming immunomodulatory therapies these multiple therapy options raise and give new hope to efficiently combat this aggressive disease.
EVALuna2:6785

Molecular Composition of Genomic TMPRSS2-ERG Rearrangements in Prostate Cancer - Krumbholz, Manuela; Agaimy, Abbas; Stöhr, Robert; Burger, Maximilian; Wach, Sven; Taubert, Helge; Wullich, Bernd; Hartmann, Arndt; Metzler, Markus (Disease Markers, 2019)
There is increasing interest in the use of cell-free circulating tumor DNA (ctDNA) as a serum marker for therapy assessment in prostate cancer patients. Prostate cancer is characterized by relatively low numbers of mutations, and, in contrast to many other common epithelial cancers, commercially available single nucleotide mutation assays for quantification of ctDNA are insufficient for therapy assessment in this disease. However, prostate cancer shares some similarity with translocation-affected mesenchymal tumors (e.g., leukemia and Ewing sarcoma), which are common in pediatric oncology, where chromosomal translocations are used as biomarkers for quantification of the tumor burden. Approximately 50% of prostate cancers carry a chromosomal translocation resulting in generation of the TMPRSS2-ERG fusion gene, which is unique to the tumor cells of each individual patient because of variability in the fusion breakpoint sites. In the present study, we examined the structural preconditions for TMPRSS2-ERG fusion sites in comparison with mesenchymal tumors in pediatric patients to determine whether the sequence composition is suitable for the establishment of tumor-specific quantification assays in prostate cancer patients. Genomic repeat elements represent potential obstacles to establishment of quantification assays, and we found similar proportions of repeat elements at fusion sites in prostate cancer to those reported for mesenchymal tumors, where genomic fusion sequences are established as biomarkers. Our data support the development of the TMPRSS2-ERG fusion gene as a noninvasive tumor marker for therapy assessment, risk stratification, and relapse detection to improve personalized therapy strategies for patients with prostate cancer.
CRIS-Team WoS Importer:2020-01-07

Molecular cross-talk between Y5-receptor and neuropeptide Y drives liver cancer - Dietrich, Peter; Wormser, Laura; Fritz, Valerie; Seitz, Tatjana; de Maria, Monica; Schambony, Alexandra; Kremer, Andreas; Günther, Claudia; Itzel, Timo; Thasler, Wolfgang E.; Teufel, Andreas; Trebicka, Jonel; et al. (Journal of Clinical Investigation, 2020)
Hepatocellular carcinoma (HCC) is clearly age-related and represents one of the deadliest cancer types worldwide. Due to globally increasing risk factors including metabolic disorders, the incidence rates of HCC are still rising. However, the molecular hallmarks of HCC remain poorly understood. Neuropeptide Y (NPY) and NPY-receptors represent a highly conserved, stress-activated system which is involved in diverse cancer-related hallmarks including aging and metabolic alterations, but its impact on liver cancer had been unclear. Here, we observed increased NPY5-receptor (Y5R) expression in HCC which correlated with tumor growth and survival. Furthermore, we found that its ligand NPY was secreted by peri-tumorous hepatocytes. Hepatocyte-derived NPY promoted HCC progression by Y5R-activation. Transforming growth factor beta 1 (TGFβ1) was identified as a regulator of NPY in hepatocytes and induced Y5R in invasive cancer cells. Moreover, NPY-conversion by dipeptidylpeptidase 4 (DPP4) augmented Y5R-activation and function in liver cancer. The TGFβ-NPY-Y5R-axis and DPP4 represent attractive therapeutic targets for controlling liver cancer progression.
EVALuna2:212290
Keywords: Aging; Cancer; Hepatology

Molecular differences between arterial and venous grafts in the first year after coronary artery bypass grafting - Steger, Christina Maria; Hartmann, Arndt; Rieker, Ralf (Histochemistry and Cell Biology, 2020)
Despite commonly used for coronary artery bypass surgery, saphenous vein (SV) grafts have significantly lower patency rates in comparison to internal thoracic artery (ITA) grafts, which might be due to the structural characteristics of the vessel wall but also due to differences in oxidative stress adaptation and molecular signaling and regulation. This human post mortem study included a total of 150 human bypass grafts (75 SV grafts and 75 ITA grafts) obtained from 60 patients divided into five groups due to the time period of implantation: group 1: baseline group without grafting; group 2: 1 day; group 3: > 1 day–1 week; group 4: > 1 week–1 month; group 5: > 1 month–1 year. Pieces of 3 mm length were fixed with formaldehyde, dehydrated, wax embedded, cut into sections of 3 µm thickness, and histologically and immunohistochemically examined. Over the whole time period, we observed a lower neointima formation and a better preserved media in ITA grafts with a higher percentage of TNF-α, PDGFR-α, and VEGF-A in nearly all vessel wall layers, a higher amount of MMP-7, MMP-9, EGFR, and bFGF positive cells in SV grafts and a timely different peak not only between ITA and SV grafts but also within the various vessel wall layers of both graft types. Since most of the examined growth factors, growth factor receptors and cytokines are regulated by MAPKs, our results suggest an activation of different pathways in both vessel graft types immediately after bypass grafting.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Coronary artery bypass grafting; Growth factors; ITA graft; MAPK; SV graft

Molecular Markers Increase Precision of the European Association of Urology Non-Muscle-Invasive Bladder Cancer Progression Risk Groups - Van Kessel, Kim E. M.; Van Der Keur, Kirstin A.; Dyrskjot, Lars; Algaba, Ferran; Welvaart, Naeromy Y. C.; Beukers, Willemien; Segersten, Ulrika; Keck, Bastian; Maurer, Tobias; Simic, Tatjana; Horstmann, Marcus; Grimm, Marc-Oliver; et al. (Clinical Cancer Research, 2018)
Purpose: The European Association of Urology (EAU) guidelines for non-muscle-invasive bladder cancer (NMIBC) recommend risk stratification based on clinicopathologic parameters. Our aim was to investigate the added value of biomarkers to improve risk stratification of NMIBC.Experimental Design: We prospectively included 1,239 patients in follow-up for NMIBC in six European countries. Fresh-frozen tumor samples were analyzed for GATA2, TBX2, TBX3, and ZIC4 methylation and FGFR3, TERT, PIK3CA, and RAS mutation status. Cox regression analyses identified markers that were significantly associated with progression to muscle-invasive disease. The progression incidence rate (PIR = rate of progression per 100 patient-years) was calculated for subgroups.Results: In our cohort, 276 patients had a low, 273 an intermediate, and 555 a high risk of tumor progression based on the EAU NMIBC guideline. Fifty-seven patients (4.6%) progressed to muscle-invasive disease. The limited number of progressors in this large cohort compared with older studies is likely due to improved treatment in the past two decades. Overall, wild-type FGFR3 and methylation of GATA2 and TBX3 were significantly associated with progression (HR = 0.34, 2.53, and 2.64, respectively). The PIR for EAU high-risk patients was 4.25. On the basis of FGFR3 mutation status and methylation of GATA2, this cohort could be reclassified into a good class (PIR = 0.86, 26.2% of patients), a moderate class (PIR = 4.32, 49.7%), and a poor class (PIR = 7.66, 24.0%).Conclusions: We conclude that the addition of selected biomarkers to the EAU risk stratification increases its accuracy and identifies a subset of NMIBC patients with a very high risk of progression. Clin Cancer Res; 24(7); 1586-93. ©2018 AACR.
EVALuna2:34258

Molecular profiling of single circulating tumor cells with diagnostic intention - Polzer, Bernhard; Medoro, Gianni; Pasch, Sophie; Fontana, Francesca; Zorzino, Laura; Pestka, Aurelia; Andergassen, Ulrich; Meier-Stiegen, Franziska; Czyz, Zbigniew T.; Alberter, Barbara; Treitschke, Steffi; Schamberger, Thomas; et al. (Embo Molecular Medicine, 2014)
Several hundred clinical trials currently explore the role of circulating tumor cell (CTC) analysis for therapy decisions, but assays are lacking for comprehensive molecular characterization of CTCs with diagnostic precision. We therefore combined a workflow for enrichment and isolation of pure CTCs with a non-random whole genome amplification method for single cells and applied it to 510 single CTCs and 189 leukocytes of 66 CTC-positive breast cancer patients. We defined a genome integrity index (GII) to identify single cells suited for molecular characterization by different molecular assays, such as diagnostic profiling of point mutations, gene amplifications and whole genomes of single cells. The reliability of > 90% for successful molecular analysis of high-quality clinical samples selected by the GII enabled assessing the molecular heterogeneity of single CTCs of metastatic breast cancer patients. We readily identified genomic disparity of potentially high relevance between primary tumors and CTCs. Microheterogeneity analysis among individual CTCs uncovered pre-existing cells resistant to ERBB2-targeted therapies suggesting ongoing microevolution at late-stage disease whose exploration may provide essential information for personalized treatment decisions and shed light into mechanisms of acquired drug resistance.
EVALuna2:6669

Molecular Subtyping of Invasive Breast Cancer Using a PAM50-Based Multigene Expression Test-Comparison with Molecular-Like Subtyping by Tumor Grade/Immunohistochemistry and Influence on Oncologist's Decision on Systemic Therapy in a Real-World Setting - Erber, Ramona; Angeloni, Miriam; Stöhr, Robert; Lux, Michael P.; Ulbrich-Gebauer, Daniel; Pelz, Enrico; Bankfalvi, Agnes; Schmid, Kurt W.; Walter, Robert F. H.; Vetter, Martina; Thomssen, Christoph; Mayr, Doris; et al. (International Journal of Molecular Sciences, 2022)
In intermediate risk hormone receptor (HR) positive, HER2 negative breast cancer (BC), the decision regarding adjuvant chemotherapy might be facilitated by multigene expression tests. In all, 142 intermediate risk BCs were investigated using the PAM50-based multigene expression test Prosigna (R) in a prospective multicentric study. In 119/142 cases, Prosigna (R) molecular subtyping was compared with local and two central (C1 and C6) molecular-like subtypes relying on both immunohistochemistry (IHC; HRs, HER2, Ki-67) and IHC + tumor grade (IHC+G) subtyping. According to local IHC, 35.4% were Luminal A-like and 64.6% Luminal B-like subtypes (local IHC+G subtype: 31.9% Luminal A-like; 68.1% Luminal B-like). In contrast to local and C1 subtyping, C6 classified >2/3 of cases as Luminal A-like. Pairwise agreement between Prosigna (R) subtyping and molecular-like subtypes was fair to moderate depending on molecular-like subtyping method and center. The best agreement was observed between Prosigna (R) (53.8% Luminal A; 44.5% Luminal B) and C1 surrogate subtyping (Cohen's kappa = 0.455). Adjuvant chemotherapy was suggested to 44.2% and 88.6% of Prosigna (R) Luminal A and Luminal B cases, respectively. Out of all Luminal A-like cases (locally IHC/IHC+G subtyping), adjuvant chemotherapy was recommended if Prosigna (R) testing classified as Prosigna (R) Luminal A at high / intermediate risk or upgraded to Prosigna (R) Luminal B.
CRIS-Team WoS Importer:2022-08-26

Molekularpathologie bei urologischen Tumoren: Empfehlungen der Konsenskonferenz der Internationalen Gesellschaft für Uropathologie (ISUP) 2019 - Hommerding, Oliver; Allory, Yves; Argani, Pedram; Bismar, Tarek A.; Bubendorf, Lukas; Canete-Portillo, Sofía; Chaux, Alcides; Chen, Ying Bei; Cheng, Liang; Cubilla, Antonio L.; Egevad, Lars; Gill, Anthony J.; et al. (Pathologe, 2021)
Comprehensive understanding of molecular principles in cancer and the diversification of oncological therapy promise individual therapeutic concepts, which have not yet found their way into urogenital cancer therapy. In March 2019 the International Society of Urogenital Pathology (ISUP) therefore held a consensus conference on recommendations for molecular diagnostics of genitourinary tumors, which were published in five separate manuscripts and are summarized in this article. In preparation for the conference, a comprehensive survey of current practices for molecular testing of urogenital tumors was carried out by members of the ISUP. At the conference, the results and the corresponding background information were presented by five working groups and recommendations for action for diagnostics were developed. An agreement between 66% of the conference participants was defined as consensus.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Bladder cancer; Kidney cancer; Molecular biomarker; Prostate cancer; Targeted therapy

Morphological subtypes of colorectal low-grade intraepithelial neoplasia: Diagnostic reproducibility, frequency and clinical impact - Lang-Schwarz, Corinna; Büttner-Herold, Maike; Burian, Stephan; Erber, Ramona; Hartmann, Arndt; Jesinghaus, Moritz; Kamarádová, Kateina; Rubio, Carlos A.; Seitz, Gerhard; Sterlacci, William; Vieth, Michael; Bertz, Simone (Journal of Clinical Pathology, 2023)
Aims: Special histomorphological subtypes of colorectal low-grade intraepithelial neoplasia (LGIN) with variable prognostic impact were recently described in patients with inflammatory bowel disease (IBD) referred to as non-conventional dysplasia. However, they can also be found in patients without IBD. We aimed to analyse the reproducibility, frequency and prognostic impact of non-conventional colorectal LGIN in patients with and without IBD. Methods: Six pathologists evaluated 500 specimens of five different LGIN-cohorts from patients with and without IBD. Non-conventional LGIN included hypermucinous, goblet cell-deficient, Paneth cell-rich and crypt cell dysplasia. A goblet cell-rich type and non-conventional LGIN, not otherwise specified were added. Results were compared with the original expert-consented diagnosis from archived pathology records. Results: Four or more pathologists agreed in 86.0% of all cases. Non-conventional LGIN was seen in 44.4%, more frequently in patients with IBD (52%; non-IBD: 39.3%, p=0.005). In patients with IBD non-conventional LGIN associated with more frequent and earlier LGIN relapse (p=0.006, p=0.025), high-grade intraepithelial neoplasia (p=0.003), larger lesion size (p=0.001), non-polypoid lesions (p=0.019) and additional risk factors (p=0.034). Results were highly comparable with expert-consented diagnoses. In patients without IBD, non-conventional LGIN may indicate a higher risk for concurrent or subsequent colorectal carcinoma (CRC, p=0.056 and p=0.061, respectively). Frequencies and association with high-grade intraepithelial neoplasia or CRC varied between the different LGIN subtypes. Conclusions: Non-conventional histomorphology in colorectal LGIN is frequent and highly reproducible. Our results indicate an increased risk for CRC in patients with non-conventional LGIN, probably independent of IBD. We recommend reporting non-conventional LGIN in routine pathology reports.
CRIS-Team Scopus Importer:2023-12-29
Keywords: Histology; Inflammatory Bowel Diseases; Intestine; Large; NEOPLASMS

Morphology of non cutaneous head and neck squamous cell carcinoma - Weichert, W.; Ihrler, S.; Boxberg, M.; Agaimy, Abbas; Mollenhauer, M.; Hartmann, Arndt (Pathologe, 2018)
Head and neck squamous cell carcinoma (HNSCC) is by far the most frequent malignant tumor in this anatomic region. Today, HNSCC is divided into two morphologically, molecularly and clinically fundamentally different entities: conventional and virus-associated (HPV/EBV) neoplasms. Premalignant lesions of nonvirus-associated HNSCC include conventional leukoplakia, dysplasia and proliferative verrucous hyperplasia with an increasing risk for malignant transformation. The morphology of HNSCC comprises a spectrum of growth patterns. In addition, special types of HNSCC must be delineated. Recently, for virus-associated HNSCC, some important clinicopathological specifics have become relevant including a separate staging system for these neoplasms. For non-virus associated HNSCC, new grading procedures have been proposed, which significantly impact on prognosis. These issues will be discussed in this review.
EVALuna2:34262

mRNA-Expression of KRT5 and KRT20 Defines Distinct Prognostic Subgroups of Muscle-Invasive Urothelial Bladder Cancer Correlating with Histological Variants - Eckstein, Markus; Wirtz, Ralph Markus; Gross-Weege, Matthias; Breyer, Johannes; Otto, Wolfgang; Stoehr, Robert; Sikic, Danijel; Keck, Bastian; Eidt, Sebastian; Burger, Maximilian; Bolenz, Christian; Nitschke, Katja; et al. (International Journal of Molecular Sciences, 2018)
Recently, muscle-invasive bladder cancer (MIBC) has been subclassified by gene expression profiling, with a substantial impact on therapy response and patient outcome. We tested whether these complex molecular subtypes of MIBC can be determined by mRNA detection of keratin 5 (KRT5) and keratin 20 (KRT20). Reverse transcriptase quantitative polymerase chain reaction (RT-qPCR) was applied to quantify gene expression of KRT5 and KRT20 using TaqMan (R)-based assays in 122 curatively treated MIBC patients (median age 68.0 years). Furthermore, in silico analysis of the MD Anderson Cancer Center (MDACC) cohort (GSE48277 + GSE47993) was performed. High expression of KRT5 and low expression of KRT20 were associated with significantly improved recurrence-free survival (RFS) and disease-specific survival disease specific survival (DSS: 5-year DSS for KRT5 high: 58%; 5-year DSS for KRT20 high: 29%). KRT5 and KRT20 were associated with rates of lymphovascular invasion and lymphonodal metastasis. The combination of KRT5 and KRT20 allowed identification of patients with a very poor prognosis (KRT20(+)/KRT5(-), 5-year DSS 0%, p < 0.0001). In silico analysis of the independent MDACC cohorts revealed congruent results (5-year DSS for KRT20 low vs. high: 84% vs. 40%, p = 0.042). High KRT20-expressing tumors as well as KRT20(+)/KRT- tumors were significantly enriched with aggressive urothelial carcinoma variants (micropapillary, plasmacytoid, nested).
EVALuna2:35878

MSI status plus immunoscore to select metastatic colorectal cancer patients for immunotherapies - Galon, J.; Mlecnik, B.; Hermitte, F.; Marliot, F.; Bifulco, C.; Lugli, A.; Nagtegaal, I. D.; Hartmann, Arndt; Van Den Eynde, M.; Roehrl, M.; Ohashi, P.; Zavadova, E.; et al. (ANNALS OF ONCOLOGY, 2018)
CRIS-Team WoS Importer:2019-03-06

MSI testing: What is new? What should be considered? German version MSI-Testung: Was ist neu? Was ist zu beachten? - Rüschoff, Josef; Baretton, Gustavo; Bläker, Hendrik; Dietmaier, Wolfgang; Dietel, Manfred; Hartmann, Arndt; Horn, Lars Christian; Jöhrens, Korinna; Kirchner, Thomas; Knüchel, Ruth; Mayr, Doris; Merkelbach-Bruse, Sabine; et al. (Pathologe, 2021)
Based on new trial data regarding immune checkpoint inhibitors (ICIs), the detection of high-grade microsatellite instability (MSI-H) or underlying deficient mismatch repair protein (dMMR) is now becoming increasingly important for predicting treatment response. For the first time, a PD‑1 ICI (pembrolizumab) has been approved by the European Medicines Agency (EMA) for first-line treatment of advanced (stage IV) dMMR/MSI‑H colorectal cancer (CRC). Further indications, such as dMMR/MSI‑H endometrial carcinoma (EC), have already succeeded (Dostarlimab, 2nd line treatment) and others are expected to follow before the end of 2021. The question of optimal testing in routine diagnostics should therefore be re-evaluated. Based on a consideration of the strengths and weaknesses of the widely available methods (immunohistochemistry and PCR), a test algorithm is proposed that allows quality assured, reliable, and cost-effective dMMR/MSI‑H testing. For CRC and EC, testing is therefore already possible at the primary diagnosis stage, in line with international recommendations (NICE, NCCN). The clinician is therefore enabled from the outset to consider not only the predictive but also the prognostic and predispositional implications of such a test when counseling patients and formulating treatment recommendations. As a basis for quality assurance, participation in interlaboratory comparisons and continuous documentation of results (e.g., QuIP Monitor) are strongly recommended.
CRIS-Team Scopus Importer:2021-06-11
Keywords: DNA mismatch repair; Endometrial carcinoma; Immune checkpoint inhibitors; Microsatellite instability; Prognosis

MSI testing What's new? What should be considered? - Rueschoff, Josef; Baretton, Gustavo; Blaeker, Hendrik; Dietmaier, Wolfgang; Dietel, Manfred; Hartmann, Arndt; Horn, Lars-Christian; Joehrens, Korinna; Kirchner, Thomas; Knuechel, Ruth; Mayr, Doris; Merkelbach-Bruse, Sabine; et al. (Pathologe, 2021)
Based on new trial data regarding immune checkpoint inhibitors (ICIs), the detection of high-grade microsatellite instability (MSI-H) or underlying deficient mismatch repair protein (dMMR) is now becoming increasingly important for predicting treatment response. For the first time, a PD-1 ICI (pembrolizumab) has been approved by the European Medicines Agency (EMA) for first-line treatment of advanced (stage IV) dMMR/MSI-H colorectal cancer (CRC). Further indications, such as dMMR/MSI-H endometrial carcinoma (EC), have already succeeded (Dostarlimab, 2nd line treatment) and others are expected to follow before the end of 2021. The question of optimal testing in routine diagnostics should therefore be re-evaluated. Based on a consideration of the strengths and weaknesses of the widely available methods (immunohistochemistry and PCR), a test algorithm is proposed that allows quality assured, reliable, and cost-effective dMMR/MSI-H testing. For CRC and EC, testing is therefore already possible at the primary diagnosis stage, in line with international recommendations (NICE, NCCN). The clinician is therefore enabled from the outset to consider not only the predictive but also the prognostic and predispositional implications of such a test when counseling patients and formulating treatment recommendations. As a basis for quality assurance, participation in interlaboratory comparisons and continuous documentation of results (e.g., QuIP Monitor) are strongly recommended.
CRIS-Team WoS Importer:2021-09-17

Mucosal Mast Cell Distribution in the Gastrointestinal Tract of Children: A Preliminary Study for Establishing Reference Values - Ehrsam, Christoph; Rechenauer, Tobias; Allabauer, Ida; Siebenlist, Gregor; Kaspar, Sonja; Rieger, Daniel; Schmid, Margit; Ruckel, Aline; Wölfle, Joachim; Hartmann, Arndt; Rieker, Ralf; Raithel, Martin; et al. (Journal of Pediatric Gastroenterology and Nutrition, 2022)
Objectives: The physiological number and distribution of mast cells (MCs) in the pediatric gastrointestinal (GI) tract is not well defined and reference values of normality are missing. To define a physiological and disease defining cut-off, a systematic histological exploration of MC distribution from the esophagus to the rectum in healthy as well as in patients with gastrointestinal food allergies (GFA) was performed. Methods: Nine pediatric subjects that exhibited unremarkable histopathological evaluations or underwent endoscopy for surveillance reasons after a previous polypectomy of single colonic juvenile polyps served as reference cohort. In all of these subjects, a chronic inflammatory disease (eg, inflammatory bowel disease, celiac disease) or allergy was excluded. In addition, a group of 15 patients with gastrointestinal complaints suspected to be caused by a GFA were investigated. Immunohistochemistry was performed from all biopsies using CD117 (c-Kit) as a reliable marker to identify MCs in the lamina propria. Results: There were distinct differences of MC counts in all parts of the pediatric GI tract. The highest counts of MCs in both symptomatic patients and control cohort, were found in the duodenum, terminal ileum, cecum and ascending colon. The lowest counts were found in the esophagus. Significant disparities between GFA and healthy subjects were found in the gastric corpus (22.1 +/- 4.0/ high power field [HPF] vs 32.0 +/- 10.1/HPF; P = 0.034) and ascending colon (44.8 +/- 10.4/HPF vs 60.4 +/- 24.3/HPF; P = 0.047). Conclusions: Mucosal MC counts in the pediatric GI tract are higher than previously reported, with a considerable overlap between healthy and GFA patients. These results provide detailed information on distribution and numbers of MCs in pediatric allergic patients while allowing estimates of physiological values in childhood for the first time. With regard to diagnostic procedures in GFA further laboratory parameters have to be integrated.
CRIS-Team WoS Importer:2022-01-07

Multicenter evaluation of an automated, multiplex, RNA-based molecular assay for detection of ALK, ROS1, RET fusions and MET exon 14 skipping in NSCLC - Melchior, Linea; Hirschmann, Astrid; Hofman, Paul; Bontoux, Christophe; Concha, Angel; Mrabet-Dahbi, Salima; Vannuffel, Pascal; Watkin, Emmanuel; Putzová, Martina; Scarpino, Stefania; Cayre, Anne; Martin, Paloma; et al. (Virchows Archiv, 2024)
The current study assessed the performance of the fully automated RT-PCR-based Idylla™ GeneFusion Assay, which simultaneously covers the advanced non-small cell lung carcinoma (aNSCLC) actionable ALK, ROS1, RET, and MET exon 14 rearrangements, in a routine clinical setting involving 12 European clinical centers. The Idylla™ GeneFusion Assay detects fusions using fusion-specific as well as expression imbalance detection, the latter enabling detection of uncommon fusions not covered by fusion-specific assays. In total, 326 archival aNSCLC formalin-fixed paraffin-embedded (FFPE) samples were included of which 44% were resected specimen, 46% tissue biopsies, and 9% cytological specimen. With a total of 179 biomarker-positive cases (i.e., 85 ALK, 33 ROS1, 20 RET fusions and 41 MET exon 14 skipping), this is one of the largest fusion-positive datasets ever tested. The results of the Idylla™ GeneFusion Assay were compared with earlier results of routine reference technologies including fluorescence in situ hybridization, immunohistochemistry, reverse-transcription polymerase chain reaction, and next-generation sequencing, establishing a high sensitivity/specificity of 96.1%/99.6% for ALK, 96.7%/99.0% for ROS1, 100%/99.3% for RET fusion, and 92.5%/99.6% for MET exon 14 skipping, and a low failure rate (0.9%). The Idylla™ GeneFusion Assay was found to be a reliable, sensitive, and specific tool for routine detection of ALK, ROS1, RET fusions and MET exon 14 skipping. Given its short turnaround time of about 3 h, it is a time-efficient upfront screening tool in FFPE samples, supporting rapid clinical decision making. Moreover, expression-imbalance-based detection of potentially novel fusions may be easily verified with other routine technologies without delaying treatment initiation.
CRIS-Team Scopus Importer:2024-05-10
Keywords: ALK fusion; Idylla; MET exon 14 skipping; NSCLC; RET fusion; ROS1 fusion

Multicenter International Society for Immunotherapy of Cancer Study of the Consensus Immunoscore for the Prediction of Survival and Response to Chemotherapy in Stage III Colon Cancer - Mlecnik, Bernhard; Bifulco, Carlo; Bindea, Gabriela; Marliot, Florence; Lugli, Alessandro; Lee, J. Jack; Zlobec, Inti; Rau, Tilman T.; Berger, Martin D.; Nagtegaal, Iris D.; Vink-Borger, Elisa; Hartmann, Arndt; et al. (Journal of Clinical Oncology, 2020)
PURPOSEThe purpose of this study was to evaluate the prognostic value of Immunoscore in patients with stage III colon cancer (CC) and to analyze its association with the effect of chemotherapy on time to recurrence (TTR).METHODSAn international study led by the Society for Immunotherapy of Cancer evaluated the predefined consensus Immunoscore in 763 patients with American Joint Committee on Cancer/Union for International Cancer Control TNM stage III CC from cohort 1 (Canada/United States) and cohort 2 (Europe/Asia). CD3+ and cytotoxic CD8+ T lymphocyte densities were quantified in the tumor and invasive margin by digital pathology. The primary end point was TTR. Secondary end points were overall survival (OS), disease-free survival (DFS), prognosis in microsatellite stable (MSS) status, and predictive value of efficacy of chemotherapy.RESULTSPatients with a high Immunoscore presented with the lowest risk of recurrence, in both cohorts. Recurrence-free rates at 3 years were 56.9% (95% CI, 50.3% to 64.4%), 65.9% (95% CI, 60.8% to 71.4%), and 76.4% (95% CI, 69.3% to 84.3%) in patients with low, intermediate, and high immunoscores, respectively (hazard ratio [HR; high v low], 0.48; 95% CI, 0.32 to 0.71; P = .0003). Patients with high Immunoscore showed significant association with prolonged TTR, OS, and DFS (all P < .001). In Cox multivariable analysis stratified by participating center, Immunoscore association with TTR was independent (HR [high v low], 0.41; 95% CI, 0.25 to 0.67; P = .0003) of patient's sex, T stage, N stage, sidedness, and microsatellite instability status. Significant association of a high Immunoscore with prolonged TTR was also found among MSS patients (HR [high v low], 0.36; 95% CI, 0.21 to 0.62; P = .0003). Immunoscore had the strongest contribution 2 proportion for influencing survival (TTR and OS). Chemotherapy was significantly associated with survival in the high-Immunoscore group for both low-risk (HR [chemotherapy v no chemotherapy], 0.42; 95% CI, 0.25 to 0.71; P = .0011) and high-risk (HR [chemotherapy v no chemotherapy], 0.5; 95% CI, 0.33 to 0.77; P = .0015) patients, in contrast to the low-Immunoscore group (P > .12).CONCLUSIONThis study shows that a high Immunoscore significantly associated with prolonged survival in stage III CC. Our findings suggest that patients with a high Immunoscore will benefit the most from chemotherapy in terms of recurrence risk.
CRIS-Team WoS Importer:2020-11-27

Multicenter International Study of the Consensus Immunoscore for the Prediction of Relapse and Survival in Early-Stage Colon Cancer - Mlecnik, Bernhard; Lugli, Alessandro; Bindea, Gabriela; Marliot, Florence; Bifulco, Carlo; Lee, Jiun Kae Jack; Zlobec, Inti; Rau, Tilman T.; Berger, Martin D.; Nagtegaal, Iris D.; Vink-Börger, Elisa; Hartmann, Arndt; et al. (Cancers, 2023)
Background: The prognostic value of Immunoscore was evaluated in Stage II/III colon cancer (CC) patients, but it remains unclear in Stage I/II, and in early-stage subgroups at risk. An international Society for Immunotherapy of Cancer (SITC) study evaluated the pre-defined consensus Immunoscore in tumors from 1885 AJCC/UICC-TNM Stage I/II CC patients from Canada/USA (Cohort 1) and Europe/Asia (Cohort 2). METHODS: Digital-pathology is used to quantify the densities of CD3+ and CD8+ T-lymphocyte in the center of tumor (CT) and the invasive margin (IM). The time to recurrence (TTR) was the primary endpoint. Secondary endpoints were disease-free survival (DFS), overall survival (OS), prognosis in Stage I, Stage II, Stage II-high-risk, and microsatellite-stable (MSS) patients. RESULTS: High-Immunoscore presented with the lowest risk of recurrence in both cohorts. In Stage I/II, recurrence-free rates at 5 years were 78.4% (95%-CI, 74.4–82.6), 88.1% (95%-CI, 85.7–90.4), 93.4% (95%-CI, 91.1–95.8) in low, intermediate and high Immunoscore, respectively (HR (Hi vs. Lo) = 0.27 (95%-CI, 0.18–0.41); p < 0.0001). In Cox multivariable analysis, the association of Immunoscore to outcome was independent (TTR: HR (Hi vs. Lo) = 0.29, (95%-CI, 0.17–0.50); p < 0.0001) of the patient’s gender, T-stage, sidedness, and microsatellite instability-status (MSI). A significant association of Immunoscore with survival was found for Stage II, high-risk Stage II, T4N0 and MSS patients. The Immunoscore also showed significant association with TTR in Stage-I (HR (Hi vs. Lo) = 0.07 (95%-CI, 0.01–0.61); P = 0.016). The Immunoscore had the strongest (69.5%) contribution χ2 for influencing survival. Patients with a high Immunoscore had prolonged TTR in T4N0 tumors even for patients not receiving chemotherapy, and the Immunoscore remained the only significant parameter in multivariable analysis. CONCLUSION: In early CC, low Immunoscore reliably identifies patients at risk of relapse for whom a more intensive surveillance program or adjuvant treatment should be considered.
CRIS-Team Scopus Importer:2023-02-03
Keywords: colon cancer; early-stage; Immunoscore; predictive biomarkers; prognosis; tumor microenvironment

Multicentric Analytical and Inter-observer Comparability of Four Clinically Developed Programmed Death-ligand 1 Immunohistochemistry Assays in Advanced Clear-cell Renal Cell Carcinoma - Sommer, Ulrich; Eckstein, Markus; Ammann, Johannes; Braunschweig, Till; Macher-Göppinger, Stephan; Schwamborn, Kristina; Hieke-Schulz, Stefanie; Harlow, Greg; Flores, Mike; Wullich, Bernd; Wirth, Manfred; Roth, Wilfried; et al. (Clinical Genitourinary Cancer, 2020)
Background: Previous studies have suggested increased clinical benefit with inhibition of programmed death-ligand 1 (PD-L1)/programmed death-1 in patients with PD-L1–positive locally advanced/metastatic renal cell carcinoma (RCC). We examined the analytical and inter-observer comparability of PD-L1–positivity across 4 clinically developed immunohistochemistry assays in clear-cell RCC (CCRCC). Materials and Methods: Randomly selected archived, formalin-fixed, paraffin-embedded nephrectomy specimens from 201 patients with locally advanced CCRCC were screened using VENTANA SP142. From these, 30 cases were selected based on their tumor-infiltrating immune cell (IC) PD-L1 status (PD-L1-IC–positivity of < 1%, 1%-5%, or > 5%; 10 cases each). These cases were stained for PD-L1 using VENTANA SP142 and SP263, and DAKO 22C3 and 28-8, and scored for PD-L1 expression on IC and tumor cells (TC) by trained readers at 5 sites. Results: Adjusted mean percentages of PD-L1-IC–positivity and PD-L1-TC–positivity varied from 4.0% to 4.9% and from 1.3% to 10.7%, respectively, between assays. Inter-assay differences in PD-L1-IC–positivity were small and non-significant (P = .1938 to .9963); for PD-L1-TC–positivity, significant differences were observed between VENTANA SP142 and the other assays (P ≤ .0001) and between VENTANA SP263 and DAKO 28-8 (P = .0248). Intra-class correlation values showed moderate-to-high inter-reader agreement for each assay for PD-L1-IC–positivity and for 3 assays for PD-L1-TC–positivity. Conclusions: In this first multicenter analytical comparison study of PD-L1 assays in CCRCC, PD-L1–positivity could be assessed reproducibly using all 4 assays for IC and for 3 of the 4 assays for TC.
CRIS-Team Scopus Importer:2020-03-27
Keywords: CCRC; Inter-observer variability; PD-L1; PD-L1 assay; Technical comparability; Uropathology

Multicentric analytical comparability study of programmed death-ligand 1 expression on tumor-infiltrating immune cells and tumor cells in urothelial bladder cancer using four clinically developed immunohistochemistry assays - Schwamborn, Kristina; Ammann, Johannes U.; Knüchel, Ruth; Hartmann, Arndt; Baretton, Gustavo; Lasitschka, Felix; Schirmacher, Peter; Braunschweig, Till; Tauber, Robert; Erlmeier, Franziska; Hieke-Schulz, Stefanie; Weichert, Wilko (Virchows Archiv, 2019)
Programmed death-ligand 1 (PD-L1) expression on tumor cells (TC) or tumor-infiltrating immune cells (IC) correlated in several studies with PD-L1/programmed death-1 (PD-1) checkpoint inhibitor efficacy. Since June 2018, a positive PD-L1 status is required for atezolizumab or pembrolizumab treatment of patients with advanced or metastasized urothelial bladder cancer, who are ineligible for cisplatin-containing therapy. We examined technical comparability and inter-reader agreement of four clinically developed PD-L1 assays in locally advanced disease. Archived, formalin-fixed, paraffin-embedded sections from 30 patients (73.3% cystectomies, 26.7% transurethral resections) were stained by PD-L1 immunohistochemistry using VENTANA SP142, VENTANA SP263, DAKO 22C3, and DAKO 28-8 at two sites per manufacturers’ protocols and scored blinded at five sites for PD-L1 expression on IC (% per tumor area) and TC (%). Small, non-significant inter-assay differences were observed for IC. For TC, SP142 showed significantly lower staining percentages. Pairwise comparisons revealed − 0.3 to 1.6% differences in adjusted means between assays for IC, and for TC, − 10.5 to − 7.8% (SP142 versus others) and − 1.9 to 2.7% (other comparisons). Inter-reader and inter-assay agreement was moderate to high for both IC and TC. Allocation to binary cutoffs (1%, 5%, 10%) showed substantial to high Kappa agreement scores (0.440–0.923) for IC and TC between assays for each reader. This first multicenter study, with five independent readers blinded with respect to the assay used, suggests that all four currently clinically relevant assays are analytically similar for evaluation of PD-L1-stained IC and three (SP263, 22C3, and 28-8) for PD-L1-stained TC. Inter-observer agreement for trained readers in scoring of both IC and TC positivity was generally high.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Immunohistochemistry; PD-L1; Programmed death-ligand 1; Tumor-infiltrating immune cells; Urothelial bladder cancer

Multi-colour FISH in oesophageal adenocarcinoma-predictors of prognosis independent of stage and grade - Geppert, Carol-Immanuel; Ruemmele, P.; Sarbia, M.; Langer, R.; Feith, M.; Morrison, L.; Pestova, E.; Schneider-Stock, Regine; Hartmann, Arndt; Rau, Tilman (British Journal of Cancer, 2014)
Oesophageal adenocarcinoma or Barrett's adenocarcinoma (EAC) is increasing in incidence and stratification of prognosis might improve disease management. Multi-colour fluorescence in situ hybridisation (FISH) investigating ERBB2, MYC, CDKN2A and ZNF217 has recently shown promising results for the diagnosis of dysplasia and cancer using cytological samples.To identify markers of prognosis we targeted four selected gene loci using multi-colour FISH applied to a tissue microarray containing 130 EAC samples. Prognostic predictors (P1, P2, P3) based on genomic copy numbers of the four loci were statistically assessed to stratify patients according to overall survival in combination with clinical data.The best stratification into favourable and unfavourable prognoses was shown by P1, percentage of cells with less than two ZNF217 signals; P2, percentage of cells with fewer ERBB2- than ZNF217 signals; and P3, overall ratio of ERBB2-/ZNF217 signals. Median survival times for P1 were 32 vs 73 months, 28 vs 73 months for P2; and 27 vs 65 months for P3. Regarding each tumour grade P2 subdivided patients into distinct prognostic groups independently within each grade, with different median survival times of at least 35 months.Cell signal number of the ERBB2 and ZNF217 loci showed independence from tumour stage and differentiation grade. The prognostic value of multi-colour FISH-assays is applicable to EAC and is superior to single markers.
EVALuna2:6597

Multi-institutional re-evaluation of prognostic factors in chromophobe renal cell carcinoma: proposal of a novel two-tiered grading scheme - Ohashi, Riuko; Martignoni, Guido; Hartmann, Arndt; Caliò, Anna; Segala, Diego; Stöhr, Christine; Wach, Sven; Erlmeier, Franziska; Weichert, Wilko; Autenrieth, Michael; Schraml, Peter; Rupp, Niels J.; et al. (Virchows Archiv, 2019)
A histological grading system of chromophobe renal cell carcinoma (chRCC) is highly desirable to identify approximately 5–10% of tumors at risk for progression. Validation studies failed to demonstrate a correlation between the four-tiered WHO/ISUP grade and outcome. Previous proposals with three-tiered chromophobe grading systems could not be validated. In this study, the presence of sarcomatoid differentiation, necrosis, and mitosis was analyzed in a Swiss cohort (n = 42), an Italian cohort (n = 103), a German cohort (n = 54), a Japanese cohort (n = 119), and The Cancer Genome Atlas cohort (n = 64). All 3 histological parameters were significantly associated with shorter time to tumor progression and overall survival in univariate analysis. Interobserver variability for identification of these parameters was measured by Krippendorff’s alpha coefficient and showed high concordance for the identification of sarcomatoid differentiation and tumor necrosis, but only low to medium concordance for the identification of mitosis. Therefore, we tested a two-tiered tumor grading system (low versus high grade) based only on the presence of sarcomatoid differentiation and/or necrosis finding in the combined cohorts (n = 382). pT stage, patient’s age (> 65 vs ≤ 65), lymph node and/or distant metastasis, and the two-tiered grading system (low versus high grade) were significantly associated with overall survival and were independent prognostic parameters in multivariate analysis (Cox proportional hazard). This multi-institutional evaluation of prognostic parameters suggests tumor necrosis and sarcomatoid differentiation as reproducible components of a two-tiered chromophobe tumor grading system.
CRIS-Team Scopus Importer:2019-12-03
Keywords: Chromophobe renal cell carcinoma; Kidney; Mitosis; Necrosis; Prognosis; Sarcomatoid differentiation; The Cancer Genome Atlas (TCGA); Tumor grade

Multiphoton Microscopy Reveals DAPK1‐Dependent Extracellular Matrix Remodeling in a Chorioallantoic Membrane (CAM) Model - Kunze, Philipp; Kreiß, Lucas; Novosadová, Vendula; Roehe, Adriana V.; Steinmann, Sara; Prochazka, Jan; Geppert, Carol-Immanuel; Hartmann, Arndt; Schürmann, Sebastian; Friedrich, Oliver; Schneider-Stock, Regine (Cancers, 2022)
Cancer cells facilitate tumor growth by creating favorable tumor micro‐environments (TME), altering homeostasis and immune response in the extracellular matrix (ECM) of surrounding tissue. A potential factor that contributes to TME generation and ECM remodeling is the cytoskeleton‐associated human death‐associated protein kinase 1 (DAPK1). Increased tumor cell motility and de‐adhesion (thus, promoting metastasis), as well as upregulated plasminogen-signaling, are shown when functionally analyzing the DAPK1 ko‐related proteome. However, the systematic investigation of how tumor cells actively modulate the ECM at the tissue level is experimentally challenging since animal models do not allow direct experimental access while artificial in vitro scaffolds cannot simulate the entire complexity of tissue systems. Here, we used the chorioallantoic membrane (CAM) assay as a natural, collagen‐rich tissue model in combination with all‐optical experimental access by multiphoton microscopy (MPM) to study the ECM remodeling potential of colorectal tumor cells with and without DAPK1 in situ and even in vivo. This approach demonstrates the suitability of the CAM assay in combination with multiphoton microscopy for studying collagen remodeling during tumor growth. Our results indicate the high ECM remodeling potential of DAPK1 ko tumor cells at the tissue level and support our findings from proteomics.
CRIS-Team Scopus Importer:2022-05-20
Keywords: collagen; colon cancer; ECM remodeling; MPM; uPAR

Multi-Prototype Few-shot Learning in Histopathology - Deuschel, Jessica; Firmbach, Daniel; Geppert, Carol-Immanuel; Eckstein, Markus; Hartmann, Arndt; Bruns, Volker; Kuritcyn, Petr; Dexl, Jakob; Hartmann, David; Perrin, Dominik; Wittenberg, Thomas; Benz, Michaela (2021 IEEE/CVF INTERNATIONAL CONFERENCE ON COMPUTER VISION WORKSHOPS (ICCVW 2021), 2021)
CRIS-Team WoS Importer:2022-02-25

Multiregion human bladder cancer sequencing reveals tumour evolution, bladder cancer phenotypes and implications for targeted therapy - Heide, Timon; Maurer, Angela; Eipel, Monika; Knoll, Katrin; Geelvink, Mirja; Veeck, Juergen; Knuechel, Ruth; van Essen, Julius; Stoehr, Robert; Hartmann, Arndt; Altmueller, Janine; Graham, Trevor A.; et al. (Journal of Pathology, 2019)
We present an evolutionary analysis of the relative time of genetic events underlying tumorigenesis in human bladder cancers from 10 whole cystectomy specimens using multiregional whole-exome sequencing. We timed bladder cancer drivers, mutational signatures, ploidy and copy number alterations, provided evidence for kataegis and correlated alterations with tumour areas and histological phenotypes. We found that: (1) heterogeneous tumour areas/phenotypes had distinct driver mutations, (2) papillary-invasive tumours divided early into two parallel evolving branches and (3) parallel evolution of subclonal driver mutations occurred. APOBEC mutational signatures were found to be very early events, active in carcinoma in situ, and often remained a dominant source of mutations throughout tumour evolution. Genetic progression from carcinoma in situ followed driver mutations in NA13/FAT1, ZBTB7B or EP300/USP28/KMT2D. Our results point towards a more diverse mutational trajectory of bladder tumorigenesis and underpin the importance of timing of mutational processes and clonal architecture in bladder cancer as important aspects for successful prognostication and therapy. Copyright © 2019 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
CRIS-Team Scopus Importer:2019-05-28
Keywords: bladder cancer; kataegis; phylogenetic analysis; tumour evolution; tumour heterogeneity; tumour phenotype

Multispectral optoacoustic tomography enables assessment of disease activity in paediatric inflammatory bowel disease - Regensburger, Adrian; Eckstein, Markus; Wetzl, Matthias; Raming, Roman; Paulus, Lars-Philip; Bühler, Adrian; Nedoschill, Emmanuel; Danko, Vera; Jüngert, Jörg; Wagner, Alexandra; Schnell, Alexander; Rückel, Aline; et al. (Photoacoustics, 2024)
Multispectral optoacoustic tomography (MSOT) allows non-invasive molecular disease activity assessment in adults with inflammatory bowel disease (IBD). In this prospective pilot-study, we investigated, whether increased levels of MSOT haemoglobin parameters corresponded to inflammatory activity in paediatric IBD patients, too. 23 children with suspected IBD underwent MSOT of the terminal ileum and sigmoid colon with standard validation (e.g. endoscopy). In Crohn‘s disease (CD) and ulcerative colitis (UC) patients with endoscopically confirmed disease activity, MSOT total haemoglobin (HbT) signals were increased in the terminal ileum of CD (72.1 ± 13.0 a.u. vs. 32.9 ± 15.4 a.u., p = 0.0049) and in the sigmoid colon of UC patients (62.9 ± 13.8 a.u. vs. 35.1 ± 16.3 a.u., p = 0.0311) as compared to controls, respectively. Furthermore, MSOT haemoglobin parameters correlated well with standard disease activity assessment (e.g. SES-CD and MSOT HbT (rs =0.69, p = 0.0075). Summarizing, MSOT is a novel technology for non-invasive molecular disease activity assessment in paediatric patients with inflammatory bowel disease.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Multispectral optoacoustic tomography; Optoacoustic imaging; Paediatric inflammatory bowel disease

Multispectral Optoacoustic Tomography for Assessment of Crohn's Disease Activity - Knieling, Ferdinand; Neufert, Clemens; Hartmann, Arndt; Claussen, Jing; Urich, Alexander; Egger, Cornelia; Vetter, Marcel; Fischer, Sarah; Pfeifer, Lukas; Hagel, Alexander; Kielisch, Christian; Görtz, Rüdiger; et al. (New England Journal of Medicine, 2017)
EVALuna2:33821

Multispectral Optoacoustic Tomography in Crohn's disease - A First-in-human Diagnostic Clinical Trial - Knieling, Ferdinand; Hartmann, Arndt; Uter, Wolfgang; Urich, Alexander; Claussen, Jing; Atreya, Raja; Rascher, Wolfgang; Waldner, Maximilian (2017)
EVALuna2:33902

Multispectral Optoacoustic Tomography in Ulcerative Colitis - A First-in-human Diagnostic Clinical Trial - Knieling, Ferdinand; Hartmann, Arndt; Claussen, Jing; Urich, Alexander; Atreya, Raja; Rascher, Wolfgang; Waldner, Maximilian (2017)
EVALuna2:33901

Multistain deep learning for prediction of prognosis and therapy response in colorectal cancer - Foersch, Sebastian; Glasner, Christina; Woerl, Ann-Christin; Eckstein, Markus; Wagner, Daniel-Christoph; Schulz, Stefan; Kellers, Franziska; Fernandez, Aurelie; Tserea, Konstantina; Kloth, Michael; Hartmann, Arndt; Heintz, Achim; et al. (Nature Medicine, 2023)
Although it has long been known that the immune cell composition has a strong prognostic and predictive value in colorectal cancer (CRC), scoring systems such as the immunoscore (IS) or quantification of intraepithelial lymphocytes are only slowly being adopted into clinical routine use and have their limitations. To address this we established and evaluated a multistain deep learning model (MSDLM) utilizing artificial intelligence (AI) to determine the AImmunoscore (AIS) in more than 1,000 patients with CRC. Our model had high prognostic capabilities and outperformed other clinical, molecular and immune cell-based parameters. It could also be used to predict the response to neoadjuvant therapy in patients with rectal cancer. Using an explainable AI approach, we confirmed that the MSDLM’s decisions were based on established cellular patterns of anti-tumor immunity. Hence, the AIS could provide clinicians with a valuable decision-making tool based on the tumor immune microenvironment.
CRIS-Team Scopus Importer:2023-03-03

Mutational frequencies of CD79B and MYD88 vary greatly between primary testicular DLBCL and gastrointestinal DLBCL - Frick, Mareike; Bettstetter, Marcus; Bertz, Simone; Schwarz-Furlan, Stephan; Hartmann, Arndt; Richter, Thomas; Lenze, Dido; Hummel, Michael; Dreyling, Martin; Lenz, Georg; Gaumann, Andreas (Leukemia & Lymphoma, 2018)
EVALuna2:34062

Mutations in BRCA1/2 and Other Panel Genes in Patients With Metastatic Breast Cancer -Association With Patient and Disease Characteristics and Effect on Prognosis - Fasching, Peter; Yadav, Siddhartha; Hu, Chunling; Wunderle, Marius; Häberle, Lothar; Hart, Steven N.; Rübner, Matthias; Polley, Eric C.; Lee, Kun Y.; Gnanaolivu, Rohan D.; Hadji, Peyman; Hübner, Hanna; et al. (Journal of Clinical Oncology, 2021)
PURPOSE: Among patients with metastatic breast cancer (mBC), the frequency of germline mutations in cancer susceptibility genes and the clinical relevance of these mutations are unclear. In this study, a prospective cohort of patients with mBC was used to determine mutation rates for breast cancer (BC) predisposition genes, to evaluate the clinical characteristics of patients with mutations, and to assess the influence of mutations on patient outcome. PATIENTS AND METHODS: Germline DNA from 2,595 patients with mBC enrolled in the prospective PRAEGNANT registry was evaluated for mutations in cancer predisposition genes. The frequencies of mutations in known BC predisposition genes were compared with results from a prospective registry of patients with nonmetastatic BC sequenced using the same QIAseq method and with public reference controls. Associations between mutation status and tumor characteristics, progression-free survival, and overall survival were assessed. RESULTS: Germline mutations in 12 established BC predisposition genes (including BRCA1 and BRCA2) were detected in 271 (10.4%) patients. A mutation in BRCA1 or BRCA2 was seen in 129 patients (5.0%). BRCA1 mutation carriers had a higher proportion of brain metastasis (27.1%) compared with nonmutation carriers (12.8%). Mutations were significantly enriched in PRAEGNANT patients with mBC compared with patients with nonmetastatic BC (10.4% v 6.6%, P < .01). Mutations did not significantly modify progression-free survival or overall survival for patients with mBC. CONCLUSION: Multigene panel testing may be considered in all patients with mBC because of the high frequency of germline mutations in BRCA1/2 and other BC predisposition genes. Although the prognosis of mutation carriers and nonmutation carriers with mBC was similar, differences observed in tumor characteristics have implications for treatment and for future studies of targeted therapies.
CRIS-Team Scopus Importer:2021-06-04

Mutation status of the mediator complex subunit 12 (MED12) in uterine leiomyomas and concurrent/metachronous multifocal peritoneal smooth muscle nodules (leiomyomatosis peritonealis disseminata) - Rieker, Ralf; Agaimy, Abbas; Moskalev, Evgeny; Hebele, Simone; Hein, Alexander; Mehlhorn, Grit; Beckmann, Matthias; Hartmann, Arndt; Haller, Florian (Pathology, 2013)
Aims: The pathogenesis and classification of multicentric smooth muscle tumours with benign appearance and concurrent/metachronous uterine and peritoneal involvement is controversial and may on occasion be diagnostically challenging. Leiomyomatosis peritonealis disseminata (LPD) is a rare condition affecting women of reproductive age, characterised by the occurrence of multiple small peritoneal smooth muscle nodules with bland histology. Methods: We investigated a total of 12 uterine and seven concurrent/metachronous peritoneal smooth muscle nodules with benign appearance from two females for mutations in the mediator complex subunit 12 (MED12), which has recently been identified as the most frequent genetic aberration in uterine leiomyomas. Results: The first case harboured different MED12 mutations in the peritoneal nodules. Mutational status of peritoneal nodules was discordant with that of the uterine leiomyomas. The second case displayed the same MED12 mutation in all five peritoneal nodules, but this mutation was not detected in her current uterine leiomyomas. Conclusions: Our results suggest that smooth muscle neoplasms with benign appearance of the primary and secondary mü llerian system share a similar genetic background of MED12 mutation in combination with oestrogen dependency. Analysis of MED12 mutation status might be a valuable adjunct tool for the future classification of these sometimes diagnostically challenging multicentric tumours. © 2013 Royal College of Pathologists of Australasia.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Leiomyomatosis peritonealis disseminata; MED12; Uterine leiomyoma

NAR score as surrogate for disease-free survival in the CAO/ARO/AIO-04 phase 3 rectal cancer trial - Fokas, E.; Fietkau, Rainer; Hartmann, Arndt; Hohenberger, Werner; Grützmann, Robert; Ghadimi, M.; Liersch, T.; Stroebel, P.; Grabenbauer, G.; Wittekind, C.; Sauer, Rolf; Kaufmann, M.; et al. (2018)
EVALuna2:36513

Neoadjuvant chemoradiation combined with regional hyperthermia in locally advanced or recurrent rectal cancer - Ott, Oliver; Gani, Cihan; Lindner, Lars H.; Schmidt, Manfred; Lamprecht, Ulf; Abdel-Rahman, Sultan; Hinke, Axel; Weissmann, Thomas; Hartmann, Arndt; Issels, Rolf D.; Zips, Daniel; Belka, Claus; et al. (Cancers, 2021)
Background: To prospectively analyze feasibility and pathological complete response (pCR) rates of neoadjuvant chemoradiotherapy combined with regional hyperthermia (RHT) in patients with locally advanced (LARC) or recurrent (LRRC) rectal cancer. Methods: between 2012 and 2018, 111 patients with UICC stage IIB-IV or any locally recurrent rectal cancer were included (HyRec-Trial, ClinicalTrials.gov Identifier: NCT01716949). Patients received radiotherapy with concurrent 5-Fluororuracil (5-FU)/Capecitabine and Oxaliplatin, and RHT. Stage 1 feasibility analysis evaluated dose-limiting toxicities (DLT) after 19 patients, stage 2 after 59 evaluable patients. Analysis of the pCR rate was based on histopathological reports. Results: the feasibility rates for stages 1 and 2 were 90% (17/19) and 73% (43/59), respectively. In the intention-to-treat population the pCR rate was 19% (20/105; 90% confidence interval (CI) 13.0–26.5). In the per-protocol-analysis, complete tumor regression was seen in 28% (18/64) and 38% (3/8) of the patients with LARC and LRRC, respectively. Complete resection rates (R0) among patients with LARC and LRRC who received surgery were 99% (78/84) and 67% (8/12). Conclusions: the intensified neoadjuvant and multimodality treatment schedule was feasible and led to comparable early toxicity rates as described by other trials that used the similar chemoradiation protocol. The presented treatment regimen resulted in a very high pCR rate and appears as a promising option for patients with LRRC.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Complete remission rate; Concurrent chemoradiation; Locally advanced rectal cancer; Locally recurrent rectal cancer; Regional hyperthermia; Tumor regression grading

Neoadjuvant rectal score as individual-level surrogate for disease-free survival in rectal cancer in the CAO/ARO/AIO-04 randomized phase III trial - Fokas, E.; Fietkau, Rainer; Hartmann, Arndt; Hohenberger, Werner; Grützmann, Robert; Ghadimi, M.; Liersch, T.; Stroebel, P.; Grabenbauer, G. G.; Graeven, U.; Hofheinz, R-D; Koehne, C-H; et al. (Annals of Oncology, 2018)
Background: Surrogate end points in rectal cancer after preoperative chemoradiation are lacking as their statistical validation poses major challenges, including confirmation based on large phase III trials. We examined the prognostic role and individual-level surrogacy of neoadjuvant rectal (NAR) score that incorporates weighted cT, ypT and ypN categories for disease-free survival (DFS) in 1191 patients with rectal carcinoma treated within the CAO/ARO/AIO-04 phase III trial. Patients and methods: Cox regression models adjusted for treatment arm, resection status, and NAR score were used in multivariable analysis. The four Prentice criteria (PC1-4) were used to assess individual-level surrogacy of NAR for DFS. Results: After a median follow-up of 50 months, the addition of oxaliplatin to fluorouracil-based chemoradiotherapy (CRT) significantly improved 3-year DFS [75.9% (95% confidence interval [CI] 72.30% to 79.50%) versus 71.3% (95% CI 67.60% to 74.90%); P = 0.034; PC 1) and resulted in a shift toward lower NAR groups (P = 0.034, PC 2) compared with fluorouracil-only CRT. The 3-year DFS was 91.7% (95% CI 88.2% to 95.2%), 81.8% (95% CI 78.4% to 85.1%), and 58.1% (95% CI 52.4% to 63.9%) for low, intermediate, and high NAR score, respectively (P < 0.001; PC 3). NAR score remained an independent prognostic factor for DFS [low versus high NAR: hazard ratio (HR) 4.670; 95% CI 3.106-7.020; P < 0.001; low versus intermediate NAR: HR 1.971; 95% CI 1.303-2.98; P = 0.001] in multivariable analysis. Notwithstanding the inherent methodological difficulty in interpretation of PC 4 to establish surrogacy, the treatment effect on DFS was captured by NAR, supporting satisfaction of individual-level PC 4. Conclusion: Our study validates the prognostic role and individual-level surrogacy of NAR score for DFS within a large randomized phase III trial. NAR score could help oncologists to speed up response-adapted therapeutic decision, and further large phase III trial data sets should aim to confirm trial-level surrogacy.
EVALuna2:34609

Neuropilin-2 and its ligand VEGF-C predict treatment response after transurethral resection and radiochemotherapy in bladder cancer patients - Keck, Bastian; Wach, S.; Taubert, Helge; Zeiler, S.; Ott, O. J.; Kunath, F.; Hartmann, Arndt; Bertz, Simone; Weiss, C.; Hoenscheid, P.; Schellenburg, S.; Roedel, C.; et al. (International Journal of Cancer, 2015)
The standard treatment for invasive bladder cancer is radical cystectomy. In selected patients, bladder-sparing therapy can be performed by transurethral resection (TURBT) and radio-chemotherapy (RCT) or radiotherapy (RT). Our published in vitro data suggest that the Neuropilin-2 (NRP2)/VEGF-C axis plays a role in therapy resistance. Therefore, we studied the prognostic impact of NRP2 and VEGF-C in 247 bladder cancer patients (cN0M0) treated with TURBT and RCT (n = 198) or RT (n = 49) and a follow-up time up to 15 years. A tissue microarray was analyzed by immunohistochemistry. NRP2 expression emerged as a prognostic factor in overall survival (OS; HR: 3.42; 95% CI: 1.48 - 7.86; p = 0.004) and was associated with a 3.85-fold increased risk of an early cancer specific death (95% CI: 0.91 - 16.24; p = 0.066) in multivariate analyses. Cancer specific survival (CSS) dropped from 166 months to 85 months when NRP2 was highly expressed (p = 0.037). Patients with high VEGF-C expression have a 2.29-fold increased risk of shorter CSS (95% CI: 1.03-5.35; p = 0.043) in univariate analysis. CSS dropped from 170 months to 88 months in the case of high VEGF-C expression (p = 0.041). Additionally, NRP2 and VEGF-C coexpression is a prognostic marker for OS in multivariate models (HR: 7.54; 95% CI: 1.57-36.23; p = 0.012). Stratification for muscle invasiveness (T1 vs. T2-T4) confirmed the prognostic role of NRP2 and NRP2/VEGF-C co-expression in patients with T2-T4 but also with high risk T1 disease. In conclusion, immunohistochemistry for NRP2 and VEGF-C has been determined to predict therapy outcome in bladder cancer patients prior to TURBT and RCT.
EVALuna2:6641

Neutrophil extracellular traps drive epithelial‐mesenchymal transition of human colon cancer - Stehr, Antonia; Wang, Guangxia; Demmler, Richard; Stemmler, Marc; Straube, Julia; Tripal, Philipp; Schmid, Benjamin; Geppert, Carol-Immanuel; Hartmann, Arndt; Munoz, Luis Enrique; Schoen, Janina; Völkl, Simon; et al. (Journal of Pathology, 2021)
Neutrophil extracellular traps (NETs) are extracellular structures, composed of nuclear DNA and various proteins released from neutrophils. Evidence is growing that NETs exert manifold functions in infection, immunity, and cancer. Recently, NETs have been detected in colorectal cancer (CRC) tissues but their association with disease progression and putative functional impact on tumourigenesis remained elusive. Using high-resolution stimulated emission depletion (STED) microscopy we showed that citrullinated histone H3 (H3cit) is sufficient to specifically detect citrullinated NETs in colon cancer tissues. Among other evidence this was supported by the close association of H3cit with de-condensed extracellular DNA, the hallmark of NETs. Extracellular DNA was reliably differentiated from nuclear condensed DNA by staining with an anti-DNA-antibody providing a novel and valuable tool to detect NETs in FFPE tissues. Using these markers, the clinical association of NETs has been investigated in a cohort of 85 patients with colon cancer. NETs were frequently detected (n = 37/n = 85, 44%) in colon cancer tissue sections and preferentially localized either only in the tumour centre or both, in the tumour centre and the invasive front. Of note, citrullinated NETs were significantly associated with high histopathologic tumour grades and lymph node metastasis. In vitro, purified NETs induced filopodia formation and cell motility in CRC cell lines. This was associated with increased expression of mesenchymal marker mRNAs (vimentin [VIM], fibronectin [FN1]) and epithelial- mesenchymal transition (EMT) promoting transcription factors (ZEB1 and Slug [SNAI2]) as well as decreased expression of the epithelial markers E-cadherin (CDH1) and EpCAM (EPCAM). These findings indicated that NETs activate an EMT-like process in CRC cells and may contribute to the metastatic progression of CRC.

[New WHO classification 2022: urinary bladder cancer]. - Gaisa, Nadine Therese; Hartmann, Arndt; Knuechel-Clarke, Ruth (Die Pathologie, 2023)
The new World Health Organization (WHO) classification of urogenital tumors is still primarily based on anatomic location, but is also a hierarchical taxonomic classification without separate chapters for tumors of the upper urinary tract and the urethra. It clarifies aspects regarding grading and noninvasive entities. It consolidates the use of the Paris system for urinary cytology as well as various subtypes/special types of neoplasms, and incorporates general concepts of the 5th edition of the WHO blue book. In addition to mesenchymal tumors, well-differentiated neuroendocrine tumors and neuroendocrine carcinomas are addressed in separate chapters. Papillary non-invasive low- and high-grade carcinomas and carcinoma in situ remain, while dysplasia and urothelial proliferation of unknown malignant potential (UPUMP) are no longer treated as separate entities. Former variants of urothelial carcinoma are now called subtypes and aberrant differentiation and special types are more precisely defined.
EVALuna2:536073

N-glycosylation Regulates Intrinsic IFN-γ Resistance in Colorectal Cancer: Implications for Immunotherapy - Krug, Julia; Rodrian, Gabriele; Petter, Katja; Yang, Hai; Khoziainova, Svetlana; Guo, Wei; Benard, Alan; Merkel, Susanne; Gellert, Susan; Maschauer, Simone; Spermann, Monika; Waldner, Maximilian; et al. (Gastroenterology, 2023)
Background & AIMS: Advanced colorectal carcinoma (CRC) is characterized by a high frequency of primary immune evasion and refractoriness to immunotherapy. Given the importance of interferon (IFN)-γ in CRC immunosurveillance, we investigated whether and how acquired IFN-γ resistance in tumor cells would promote tumor growth, and whether IFN-γ sensitivity could be restored. Methods: Spontaneous and colitis-associated CRC development was induced in mice with a specific IFN-γ pathway inhibition in intestinal epithelial cells. The influence of IFN-γ pathway gene status and expression on survival was assessed in patients with CRC. The mechanisms underlying IFN-γ resistance were investigated in CRC cell lines. Results: The conditional knockout of the IFN-γ receptor in intestinal epithelial cells enhanced spontaneous and colitis-associated colon tumorigenesis in mice, and the loss of IFN-γ receptor α (IFNγRα) expression by tumor cells predicted poor prognosis in patients with CRC. IFNγRα expression was repressed in human CRC cells through changes in N-glycosylation, which decreased protein stability via proteasome-dependent degradation, inhibiting IFNγR-signaling. Downregulation of the bisecting N-acetylglucosaminyltransferase III (MGAT3) expression was associated with IFN-γ resistance in all IFN-γ–resistant cells, and highly correlated with low IFNγRα expression in CRC tissues. Both ectopic and pharmacological reconstitution of MGAT3 expression with all-trans retinoic acid increased bisecting N-glycosylation, as well as IFNγRα protein stability and signaling. Conclusions: Together, our results demonstrated that tumor-associated changes in N-glycosylation destabilize IFNγRα, causing IFN-γ resistance in CRC. IFN-γ sensitivity could be reestablished through the increase in MGAT3 expression, notably via all-trans retinoic acid treatment, providing new prospects for the treatment of immune-resistant CRC.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Colon Cancer; IFNGR1; Immune Evasion

Nivolumab Switch Maintenance Therapy After Tyrosine Kinase Inhibitor Induction in Metastatic Renal Cell Carcinoma: A Randomized Clinical Trial by the Interdisciplinary Working Group on Renal Tumors of the German Cancer Society (NIVOSWITCH; AIO-NZK-0116ass) - Grünwald, Viktor; Ivanyi, Philipp; Zschäbitz, Stefanie; Wirth, Manfred; Staib, Peter; Schostak, Martin; Dargatz, Philip; Müller, Lothar; Metz, Michael; Bergmann, Lothar; Steiner, Thomas; Welslau, Martin; et al. (European Urology, 2023)
Background: The role of immune checkpoint inhibitor (ICI) maintenance therapy in metastatic renal cell carcinoma (mRCC) is undefined. Objective: To determine whether switch maintenance therapy with nivolumab improves clinical outcomes in patients with mRCC with tyrosine kinase inhibitor (TKI) sensitivity. Design, setting, and participants: This open-label phase 2 trial randomized patients with a partial response or stable disease after 10–12-wk TKI induction therapy to either TKI or nivolumab maintenance. Key inclusion criteria were measurable disease, clear cell histology, Eastern Cooperative Oncology Group performance status (ECOG PS) 0–2, and adequate organ function. Intervention: Intravenous nivolumab 8 × 240 mg every 2 wk, followed by 480 mg every 4 wk or sunitinib 50 mg (4–2 regimen) or pazopanib 800 mg once daily orally. Outcome measurements and statistical analyses: The primary endpoint was overall survival (OS). Secondary endpoints were the objective response rate (ORR; Response Evaluation Criteria in Solid Tumors v1.1), progression-free survival (PFS), safety (Common Terminology Criteria for Adverse Events v4.03), and patient-reported outcomes (Functional Assessment of Cancer Therapy Kidney Symptom Index). The Kaplan-Meier method, two-sided log-rank tests, and Cox regression models were used for statistical analysis. Results and limitations: Maintenance therapy was nivolumab for 25 patients (51.0%) and TKI for 24 (48.9%). The median age was 65 yr (range 35–79). Nine patients (18.4%) were female, 31 (63.3%) had ECOG PS of 0, and 15 (30.6%) had favorable risk. OS data are immature (17 deaths, 34.7%). The ORR was 20.0% (n = 5) for nivolumab and 52.2% (n = 12) for TKI. PFS was worse with nivolumab (hazard ratio 2.57, 95% confidence interval 1.36–4.89; p = 0.003). Grade ≥3 adverse events occurred in 14 patients (56.0%) with nivolumab and 17 (70.8%) with TKI. A major limitation is early termination of our study. Conclusions: TKI treatment achieved superior ORR and PFS in comparison to nivolumab maintenance therapy. Our data do not indicate a role for nivolumab switch maintenance in mRCC. Patient summary: Patients with metastatic kidney cancer who experienced a tumor response or disease stabilization after a short period of targeted treatment with a tyrosine kinase inhibitor did not benefit from a switch to the immunotherapy drug nivolumab. Patients who continued their original treatment achieved better responses and a longer time without disease progression. This trial is registered on EudraCT as 2016-002170-13 and on ClinicalTrials.gov as NCT02959554.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Metastatic renal cell carcinoma; Nivolumab; Switch maintenance therapy; Tyrosine kinase inhibitor

NLRP3 Inhibition Leads to Impaired Mucosal Fibroblast Function in Patients with Inflammatory Bowel Diseases - Weber, Simone; Sitte, Selina; Vögele, Anna-Lena; Sologub, Ludmilla; Wilfer, Angelika; Rath, Timo; Nägel, Andreas; Zundler, Sebastian; Franchi, Luigi; Opipari, Anthony W.; Sonnewald, Sophia; Reid, Stephen; et al. (Journal of Crohns & Colitis, 2023)
Background and Aims: Inflammatory bowel diseases (IBD) are characterized by mucosal inflammation and sequential fibrosis formation, but the exact role of the hyperactive NLRP3 inflammasome in these processes is unclear. Thus, we studied the expression and function of the NLRP3 inflammasome in the context of inflammation and fibrosis in IBD. Methods: We analysed intestinal NLRP3 expression in mucosal immune cells and fibroblasts from IBD patients and NLRP3-associated gene expression via single-cell RNA sequencing and microarray analyses. Furthermore, cytokine secretion of NLRP3 inhibitor treated blood and mucosal cells, as well as proliferation, collagen production, and cell death of NLRP3 inhibitor treated intestinal fibroblasts from IBD patients were studied. Results: We found increased NLRP3 expression in the inflamed mucosa of IBD patients and NLRP3 inhibition led to reduced IL-1β and IL-18 production in blood cells and diminished the bioactive form of mucosal IL-1β. Single cell analysis identified overlapping expression patterns of NLRP3 and IL-1β in classically activated intestinal macrophages and we also detected NLRP3 expression in CD163+ macrophages. In addition, NLRP3 expression was also found in intestinal fibroblasts from IBD patients. Inhibition of NLRP3 led to reduced proliferation of intestinal fibroblasts, which was associated with a marked decrease in production of collagen type I and type VI in IBD patients. Moreover, NLRP3 inhibition in intestinal fibroblasts induced autophagy, a cellular process involved in collagen degradation. Conclusions: In the presented study, we demonstrate that inhibiting NLRP3 might pave the way for novel therapeutic approaches in IBD, especially to prevent the severe complication of intestinal fibrosis formation.
CRIS-Team Scopus Importer:2023-11-17
Keywords: fibroblasts; fibrosis; IL-18; IL-1β; Inflammatory bowel diseases; mucosal immune system; NLRP3 inflammasome; small molecule inhibitor

Nodular tumour of the Vas deferens with epithelial structures - Wohlschlaeger, J.; Greimelmaier, K.; Ramankulov, A.; Feist, H.; Loch, T.; Hager, T.; Reis, Henning; Schmid, K. W.; Hartmann, Arndt; Agaimy, Abbas (Pathologe, 2021)
CRIS-Team WoS Importer:2021-10-15

No Evidence of Microsatellite Instability and Loss of Mismatch-Repair-Protein Expression in Squamous Cell Carcinoma of the Penis - Stoehr, Robert; Wendler, Olaf Dietrich; Giedl, Josef; Gaisa, Nadine T.; Richter, Georg; Campean, Valentina; Burger, Maximilian; Wullich, Bernd; Bertz, Simone; Hartmann, Arndt (Pathobiology, 2019)
Objective: Microsatellite instability (MSI) and a defective mismatch repair (MMR) system were described as beneficial tumor features for response to immune checkpoint therapy (PD-1 blockade). Meanwhile, the FDA approved PD-1/PD-L1 inhibition treatment for any solid tumor showing MSI and/or defects in the MMR system. For squamous cell carcinoma (SCC) of the penis, no data on the frequency of MSI and altered MMR protein expression are available to date. Therefore, we investigated the MSI status and the expression of MMR proteins in a large cohort of penile SCCs. Methods: The MSI status of 105 archival formalin-fixed, paraffin-embedded penile SCCs was analyzed using the 5 markers of the NCI consensus panel for MIS testing (BAT25, 26, D2S123, D17S250, and D5S346), or, in cases without representative nontumorous tissue using a validated panel of 5 quasimonomorphic mononucleotide repeat markers (BAT 25, 26 and NR21, 24, 27). The expression of the MMR proteins MLH1, MSH2, MSH6, and PMS2 was analyzed using immunohistochemistry and a tissue microarray of a subset of penile SCCs from our cohort (n = 75). Results: Overall, in 96/105 cases, at least 4 microsatellite markers gave interpretable results. None of the cases showed MSI. Immunohistochemistry for MMR proteins was analyzable in 70/75 cases. All cases showed a regular expression of the MMR proteins. Conclusion: MSI and defects in MMR protein expression are not regular features of penile SCC and might not act as biomarkers for PD-1/PD-L1 blockade therapy in penile carcinoma.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Microsatellite instability; Mismatch-repair; Penile cancer; Squamous cell carcinoma; Tissue microarray

Non-Clear Cell Renal Cell Carcinoma - Pathology and Treatment Options - Ahrens, Marit; Scheich, Sebastian; Hartmann, Arndt; Bergmann, Lothar (Oncology Research and Treatment, 2019)
Non-clear cell renal cell carcinomas (nccRCC) are rare diseases with heterogeneous histopathologically and genetically defined entities. The clinical data on optimal systemic treatments of nccRCC is rather limited. In this review, the current World Health Organization (WHO) classification of nccRCC based on histopathologic and genetic findings is reported. Regarding systemic treatment options, the most commonly used agents are mTOR inhibitors like everolimus or temsirolimus, or tyrosine kinase inhibitors like sunitinib. 2 small randomized clinical trials with nccRCC comparing sunitinib with everolimus revealed a trend towards a better progression-free survival (PFS) and overall survival (OS) in favor of sunitinib. In RCC with predominant sarcomatoid features, both chemotherapy and targeted agents are reported without any preference for outcome. For subsequent lines of therapy, some case reports describe promising effects of PD-1 or PD-L1 inhibitors in nccRCC including sarcomatoid subtype and Bellini duct carcinoma. Currently, nccRCCs are treated similarly to clear cell RCC or, whenever possible, within clinical trials. Clinical trials with immune checkpoint inhibitors are ongoing. (c) 2019 S. Karger AG, Basel
CRIS-Team WoS Importer:2019-04-04

Noninferiority of Artificial Intelligence-Assisted Analysis of Ki-67 and Estrogen/Progesterone Receptor in Breast Cancer Routine Diagnostics - Abele, Niklas; Tiemann, Katharina; Krech, Till; Wellmann, Axel; Schaaf, Christian; Länger, Florian; Peters, Anja; Donner, Andreas; Keil, Felix; Daifalla, Khalid; Mackens, Marina; Mamilos, Andreas; et al. (Modern Pathology, 2023)
Image analysis assistance with artificial intelligence (AI) has become one of the great promises over recent years in pathology, with many scientific studies being published each year. Nonetheless, and perhaps surprisingly, only few image AI systems are already in routine clinical use. A major reason for this is the missing validation of the robustness of many AI systems: beyond a narrow context, the large variability in digital images due to differences in preanalytical laboratory procedures, staining procedures, and scanners can be challenging for the subsequent image analysis. Resulting faulty AI analysis may bias the pathologist and contribute to incorrect diagnoses and, therefore, may lead to inappropriate therapy or prognosis. In this study, a pretrained AI assistance tool for the quantification of Ki-67, estrogen receptor (ER), and progesterone receptor (PR) in breast cancer was evaluated within a realistic study set representative of clinical routine on a total of 204 slides (72 Ki-67, 66 ER, and 66 PR slides). This represents the cohort with the largest image variance for AI tool evaluation to date, including 3 staining systems, 5 whole-slide scanners, and 1 microscope camera. These routine cases were collected without manual preselection and analyzed by 10 participant pathologists from 8 sites. Agreement rates for individual pathologists were found to be 87.6% for Ki-67 and 89.4% for ER/PR, respectively, between scoring with and without the assistance of the AI tool regarding clinical categories. Individual AI analysis results were confirmed by the majority of pathologists in 95.8% of Ki-67 cases and 93.2% of ER/PR cases. The statistical analysis provides evidence for high interobserver variance between pathologists (Krippendorff's α, 0.69) in conventional immunohistochemical quantification. Pathologist agreement increased slightly when using AI support (Krippendorff α, 0.72). Agreement rates of pathologist scores with and without AI assistance provide evidence for the reliability of immunohistochemical scoring with the support of the investigated AI tool under a large number of environmental variables that influence the quality of the diagnosed tissue images.
CRIS-Team Scopus Importer:2023-03-31
Keywords: digital pathology; mammary carcinoma; surgical pathology

Non-professional phagocytosis: a general feature of normal tissue cells - Seeberg, Jacob; Loibl, Monika; Moser, Fabian; Schwegler, Manuela; Büttner-Herold, Maike; Daniel, Christoph; Engel, Felix; Hartmann, Arndt; Schlötzer-Schrehardt, Ursula; Goppelt-Strübe, Margarete; Schellerer, Vera; Naschberger, Elisabeth; et al. (Scientific Reports, 2019)
Non-professional phagocytosis by cancer cells has been described for decades. Recently, non-professional phagocytosis by normal tissue cells has been reported, which prompted us to take a closer look at this phenomenon. Non-professional phagocytosis was studied by staining cultured cells with live-cell staining dyes or by staining paraffin-embedded tissues by immunohistochemistry. Here, we report that each of 21 normal tissue cell lines from seven different organs was capable of phagocytosis, including ex vivo cell cultures examined before the 3rd passage as well as the primary and virus-transformed cell lines. We extended our analysis to an in vivo setting, and we found the occurrence of non-professional phagocytosis in healthy skin biopsies immediately after resection. Using dystrophin immunohistochemistry for membrane staining, human post-infarction myocardial tissue was assessed. We found prominent signs of non-professional phagocytosis at the transition zone of healthy and infarcted myocardia. Taken together, our findings suggest that non-professional phagocytosis is a general feature of normal tissue cells.
CRIS-Team Scopus Importer:2019-08-27

Novel criteria for intratumoral budding with prognostic relevance for colon cancer and its histological subtypes - Pour Farid, Pantea; Eckstein, Markus; Merkel, Susanne; Grützmann, Robert; Hartmann, Arndt; Bruns, Volker; Benz, Michaela; Schneider-Stock, Regine; Geppert, Carol-Immanuel (International Journal of Molecular Sciences, 2021)
Peritumoral budding and intratumoral budding (ITB) are important prognostic factors for colorectal cancer patients. Scientists worldwide have investigated the role of budding in tumor progression and its prognosis, but guidelines for reliably identifying tumor buds based on morphology are lacking. In this study, next-generation tissue microarray (ngTMA® ) construction was used for tumor bud evaluation, and highly detailed rule-out annotation was used for tumor definition in pancytokeratin-stained tissue sections. Initially, tissues of 245 colon cancer patients were evaluated with high interobserver reliability, and a concordance of 96% was achieved. It was shown that high ITB scores were associated with poor distant metastasis-free survival (p = 0.006 with a cut-off of ≥10 buds). This cut-off was defined as the best maximum value from one of two/three ngTMA® cores (0.6 mm diameter). ITB in 30 cases of mucinous, medullary, and signet ring cell carcinoma was analyzed for the subsequent determination of differences in tumor bud analyses between those subtypes. In conclusion, blinded randomized punched cores in the tumor center can be useful for ITB detection. It can be assumed that this method is suitable for its adoption in clinical routines.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Histological subtypes; Immunohistochemistry; Medullary carcinoma; Metastasis; Mucinous carcinoma; Next-generation tissue microarray analysis; Prognostic biomarker; Signet ring cell carcinoma; Survival analysis; Tumor budding

NSD3-NUTM1-rearranged carcinoma of the median neck/thyroid bed developing after recent thyroidectomy for sclerosing mucoepidermoid carcinoma with eosinophilia: report of an extraordinary case - Agaimy, Abbas; Tögel, Lars; Stöhr, Robert; Meidenbauer, Norbert; Semrau, Sabine; Hartmann, Arndt; Mantsopoulos, Konstantinos (Virchows Archiv, 2021)
Sclerosing mucoepidermoid carcinoma with eosinophilia (SMECE) is an exceedingly rare low-grade thyroid malignancy of unknown histogenesis. NUT carcinoma is another rare, highly aggressive neoplasm with predilection for the midline, defined by recurrent NUTM1 fusions. The bromodomain family genes (BRD4 or BRD3) and rarely NSD3, ZNF532, or others are known fusion partners. We describe an extraordinary case of a 42-year-old female with a thyroid SMECE treated by thyroidectomy and neck dissection. She presented 6 months later with extensive midline recurrence encasing/compressing the trachea. Biopsy revealed poorly differentiated carcinoma with abrupt squamous differentiation, suggestive of NUT carcinoma. Immunohistochemistry confirmed expression of monoclonal NUT antibody. Targeted RNA sequencing revealed the NSD3-NUTM1 fusion in the NUT carcinoma, but not in the SMECE. This unique case highlights unusual sequential origin of two exceptionally rare entities at same anatomic site and underlines the necessity of sampling unexpectedly aggressive recurrences of otherwise indolent malignancies.
CRIS-Team Scopus Importer:2021-05-07
Keywords: Head and neck; Midline carcinoma; NSD3; NUT carcinoma; NUTM1; Sclerosing mucoepidermoid carcinoma with eosinophilia; Thyroid gland

NTRK Testing Practice in German Pathologies - Weyerer, Veronika; Ortiz-Bruechle, Nadina; Demes, Melanie; Schildgen, Oliver; Haybaeck, Johannes; Westphal, Gabriela; Sander, Philip; Mairinger, Thomas; Goering, Wolfgang; Aigner, Thomas; Siebolts, Udo; Moske, Annika; et al. (MODERN PATHOLOGY, 2021)
CRIS-Team WoS Importer:2021-04-16

Nuclear NR4A2 (Nurr1) Immunostaining is a Novel Marker for Acinic Cell Carcinoma of the Salivary Glands Lacking the Classic NR4A3 (NOR-1) Upregulation - Haller, Florian; Moskalev, Evgeny; Kuck, Sarina; Bieg, Matthias; Winkelmann, Christa; Müller, Susanna; Ihrler, Stephan; Märkl, Bruno; Eils, Roland; Wiemann, Stefan; Iro, Heinrich; Hartmann, Arndt; et al. (American Journal of Surgical Pathology, 2020)
CRIS-Team Scopus Importer:2020-05-22

Nuclear NR4A3 Immunostaining Is a Specific and Sensitive Novel Marker for Acinic Cell Carcinoma of the Salivary Glands - Haller, Florian; Skálová, Alena; Ihrler, Stephan; Märkl, Bruno; Bieg, Matthias; Moskalev, Evgeny; Erber, Ramona; Blank, Susanne; Winkelmann, Christa; Hebele, Simone; Baněčková, Martina; Wiemann, Stefan; et al. (American Journal of Surgical Pathology, 2019)
Recently, we discovered the recurrent genomic rearrangement [t(4;9)(q13;q31)] enabling upregulation of the transcription factor Nuclear Receptor Subfamily 4 Group A Member 3 (NR4A3) through enhancer hijacking as the oncogenic driver event in acinic cell carcinoma (AciCC) of the salivary glands. In the current study, we evaluated the usefulness of NR4A3 immunostaining and NR4A3 fluorescence in situ hybridization (FISH) in the differential diagnosis of AciCC, comparing a total of 64 AciCCs including 17% cases with high-grade transformation, 29 secretory (mammary analog) carcinomas (MASC), and 70 other salivary gland carcinomas. Nuclear NR4A3 immunostaining was a highly specific (100%) and sensitive (98%) marker for AciCC with only 1 negative case, whereas NR4A3 FISH was less sensitive (84%). None of the MASCs or other salivary gland carcinomas displayed any nuclear NR4A3 immunostaining. The recently described HTN3-MSANTD3 gene fusion was observed in 4 of 49 (8%) evaluable AciCCs, all with nuclear NR4A3 immunostaining. In summary, NR4A3 immunostaining is a highly specific and sensitive marker for AciCC, which may be especially valuable in cases with high-grade transformation and in "zymogen granule"-poor examples within the differential diagnostic spectrum of AciCC and MASC.
CRIS-Team Scopus Importer:2019-09-03
Keywords: acinic cell carcinoma; HTN3-MSANTD3; immunohistochemistry; NR4A3; salivary glands; translocation

NUT Carcinoma of the Salivary Glands: Clinicopathologic and Molecular Analysis of 3 Cases and a Survey of NUT Expression in Salivary Gland Carcinomas - Agaimy, Abbas; Fonseca, Isabel; Martins, Carmo; Thway, Khin; Barrette, Ryan; Harrington, Kevin J.; Hartmann, Arndt; French, Christopher A.; Fisher, Cyril (American Journal of Surgical Pathology, 2018)
NUT carcinoma (NC) represents a rare subset of highly aggressive poorly differentiated carcinomas characterized by rearrangement of the NUT (aka NUTM1, nuclear protein in testis) gene, most commonly fused to BRD4. Originally described as a mediastinal/thymic malignancy, NC has been reported at a variety of anatomic regions including the upper and lower aerodigestive tract. To date, only 7 NC cases of probable salivary gland origin have been reported. We herein describe 3 new cases (all affecting the parotid gland) in 2 women (39- and 55-y old) and 1 man (35-y old). Histologic examination showed poorly differentiated neoplasms composed of poorly cohesive small-sized to medium-sized cells with variable squamoid cell component that was focal and abrupt. Immunohistochemistry showed uniform expression of p63 and distinctive punctate expression of the NUT antigen in the tumor cell nuclei. Review of the reported salivary gland NC cases (total, 10) showed a male:female ratio of 1.5:1 and an age range of 12 to 55 years (median, 29 y). Site of the primary tumor was the parotid (7), sublingual (2), and submandibular (1) glands. All presented as rapidly growing masses treated by surgery followed by adjuvant radiotherapy/chemotherapy. Initial nodal status was positive in 8/10. At last follow-up (1 to 24 mo; median, 5 mo), 7/10 patients died of disease at a median of 5.5 months (1 to 24 mo) and only 2 were disease free at 7 and 14 months. Of 9 cases with genetic data, the fusion partner was BRD4 (n=7), non-BRD4/3 (n=1), or undetermined (n=1). None of 306 carcinomas spanning the spectrum of salivary carcinoma types screened by NUT immunohistochemistry was positive. This is the first small series on salivary NC highlighting the importance to include this rare disease in the differential diagnosis of poorly differentiated salivary gland carcinomas and in cases of presumable poorly differentiated carcinoma of unknown origin.
EVALuna2:34302

Optimizing tissue stewardship in non-small cell lung cancer to support molecular characterization and treatment selection: statement from a working group of thoracic pathologists. - Kerr, Keith M.; Bubendorf, Lukas; Lopez-Rios, Fernando; Khalil, Farah; Roy-Chowdhuri, Sinchita; Joubert, Philippe; Hartmann, Arndt; Guerini-Rocco, Elena; Yatabe, Yasushi; Hofman, Paul; Cooper, Wendy A.; Dacic, Sanja (Histopathology, 2024)
Many patients with non-small cell lung cancer do not receive guideline-recommended, biomarker-directed therapy, despite the potential for improved clinical outcomes. Access to timely, accurate, and comprehensive molecular profiling, including targetable protein overexpression, is essential to allow fully informed treatment decisions to be taken. In turn, this requires optimal tissue management to protect and maximize the use of this precious finite resource. Here, a group of leading thoracic pathologists recommend factors to consider for optimal tissue management. Starting from when lung cancer is first suspected, keeping predictive biomarker testing in the front of the mind should drive the development of practices and procedures that conserve tissue appropriately to support molecular characterization and treatment selection.
EVALuna2:542959

Organ manifestations of COVID-19: what have we learned so far (not only) from autopsies? - Jonigk, Danny; Werlein, Christopher; Acker, Till; Aepfelbacher, Martin; Amann, Kerstin Ute; Baretton, Gustavo; Barth, Peter; Bohle, Rainer M.; Buettner, Andreas; Buettner, Reinhard; Dettmeyer, Reinhard; Eichhorn, Philip; et al. (Virchows Archiv, 2022)
The use of autopsies in medicine has been declining. The COVID-19 pandemic has documented and rejuvenated the importance of autopsies as a tool of modern medicine. In this review, we discuss the various autopsy techniques, the applicability of modern analytical methods to understand the pathophysiology of COVID-19, the major pathological organ findings, limitations or current studies, and open questions. This article summarizes published literature and the consented experience of the nationwide network of clinical, neuro-, and forensic pathologists from 27 German autopsy centers with more than 1200 COVID-19 autopsies. The autopsy tissues revealed that SARS-CoV-2 can be found in virtually all human organs and tissues, and the majority of cells. Autopsies have revealed the organ and tissue tropism of SARS-CoV-2, and the morphological features of COVID-19. This is characterized by diffuse alveolar damage, combined with angiocentric disease, which in turn is characterized by endothelial dysfunction, vascular inflammation, (micro-) thrombosis, vasoconstriction, and intussusceptive angiogenesis. These findings explained the increased pulmonary resistance in COVID-19 and supported the recommendations for antithrombotic treatment in COVID-19. In contrast, in extra-respiratory organs, pathological changes are often nonspecific and unclear to which extent these changes are due to direct infection vs. indirect/secondary mechanisms of organ injury, or a combination thereof. Ongoing research using autopsies aims at answering questions on disease mechanisms, e.g., focusing on variants of concern, and future challenges, such as post-COVID conditions. Autopsies are an invaluable tool in medicine and national and international interdisciplinary collaborative autopsy-based research initiatives are essential.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Acute kidney damage; Diffuse alveolar damage; Immune response; SARS-CoV-2

p53 and ovarian carcinoma survival: an Ovarian Tumor Tissue Analysis consortium study - Köbel, Martin; Kang, Eun-Young; Weir, Ashley; Rambau, Peter F.; Lee, Cheng-Han; Nelson, Gregg S.; Ghatage, Prafull; Meagher, Nicola S.; Riggan, Marjorie J.; Alsop, Jennifer; Anglesio, Michael S.; Beckmann, Matthias; et al. (Journal of Pathology: Clinical Research, 2023)
Our objective was to test whether p53 expression status is associated with survival for women diagnosed with the most common ovarian carcinoma histotypes (high-grade serous carcinoma [HGSC], endometrioid carcinoma [EC], and clear cell carcinoma [CCC]) using a large multi-institutional cohort from the Ovarian Tumor Tissue Analysis (OTTA) consortium. p53 expression was assessed on 6,678 cases represented on tissue microarrays from 25 participating OTTA study sites using a previously validated immunohistochemical (IHC) assay as a surrogate for the presence and functional effect of TP53 mutations. Three abnormal expression patterns (overexpression, complete absence, and cytoplasmic) and the normal (wild type) pattern were recorded. Survival analyses were performed by histotype. The frequency of abnormal p53 expression was 93.4% (4,630/4,957) in HGSC compared to 11.9% (116/973) in EC and 11.5% (86/748) in CCC. In HGSC, there were no differences in overall survival across the abnormal p53 expression patterns. However, in EC and CCC, abnormal p53 expression was associated with an increased risk of death for women diagnosed with EC in multivariate analysis compared to normal p53 as the reference (hazard ratio [HR] = 2.18, 95% confidence interval [CI] 1.36-3.47, p = 0.0011) and with CCC (HR = 1.57, 95% CI 1.11-2.22, p = 0.012). Abnormal p53 was also associated with shorter overall survival in The International Federation of Gynecology and Obstetrics stage I/II EC and CCC. Our study provides further evidence that functional groups of TP53 mutations assessed by abnormal surrogate p53 IHC patterns are not associated with survival in HGSC. In contrast, we validate that abnormal p53 IHC is a strong independent prognostic marker for EC and demonstrate for the first time an independent prognostic association of abnormal p53 IHC with overall survival in patients with CCC.
EVALuna2:530730

P53 Codon 72 Polymorphism and Risk for Squamous Cell Carcinoma of the Penis: A Caucasian Case-Control Study - Stoehr, Robert; Weisser, Rebecca; Wendler, Olaf Dietrich; Giedl, Josef; Daifalla, Khalid; Gaisa, Nadine T.; Richter, Georg; Campean, Valentina; Burger, Maximilian; Wullich, Bernd; Hartmann, Arndt (Journal of Cancer, 2018)
Squamous cell carcinoma of the penis is a rare but often aggressive disease. A large proportion of penile cancers are associated with HPV infection, mainly with HPV high-risk subtypes 16 and 18. From other HPV-related malignancies a link between a functional SNP in the p53 gene (rs1042522, p.Arg72Pro) and a higher disease risk in the presence of HPV is documented. The p53 p.Arg72 variant was described as a risk factor for developing a malignancy in combination with the presence of HPV as the p.72Arg variant is more prone to HPV E6 protein-mediated degradation than the p.72Pro variant. For penile carcinoma there are only sparse data available on this topic. We therefore analyzed the distribution of this p53 codon 72 SNP in a cohort of 107 penile cancer patients and a healthy control group (n=194) using Restriction Fragment Length Polymorphism (RFLP) analysis. After DNA isolation a PCR amplicon including the variant nucleotide was generated. Based on the variant nucleotide this amplicon can be cleaved into two parts or remain unaffected by a restriction enzyme. Subsequent electrophoresis allowed the discrimination of SNP alleles in the investigated sample. Comparison of the allelic variants revealed no significant differences in the distribution of this SNP between cases and controls (p=0,622). There was also no difference in SNP distribution between cases with/without HPV infection (p=0,558) or histologic variants (p=0.339). In order to strengthen the impact of our data we performed a combined analysis of all published data on this topic with our results. This ended up in SNP distribution data from 177 cases and 1149 controls. Overall, there were also no significant differences in the allelic distribution of the p53 codon 72 SNP between either cases and controls (p=0,914) or HPV-positive and HPV-negative cases (p=0,486). From this most comprehensive data available to date we conclude that there is no influence of the p53 codon 72 SNP on the risk of development of penile carcinoma in Caucasians even in the presence of HPV.
EVALuna2:34861

Paediatric and adult soft tissue sarcomas with NTRK1 gene fusions: a subset of spindle cell sarcomas unified by a prominent myopericytic/haemangiopericytic pattern - Haller, Florian; Knopf, Jasmin; Ackermann, Andreas; Bieg, Matthias; Kleinheinz, Kortine; Schlesner, Matthias; Moskalev, Evgeny; Will, Rainer; Satir, Ali Abdel; Abdelmagid, Ibtihalat E.; Giedl, Josef; Carbon, Roman; et al. (Journal of Pathology, 2016)
Neoplasms with a myopericytomatous pattern represent a morphological spectrum of lesions encompassing myopericytoma of the skin and soft tissue, angioleiomyoma, myofibromatosis/infantile haemangiopericytoma and putative neoplasms reported as malignant myopericytoma. Lack of reproducible phenotypic and genetic features of malignant myopericytic neoplasms have prevented the establishment of myopericytic sarcoma as an acceptable diagnostic category. Following detection of a LMNA-NTRK1 gene fusion in an index case of paediatric haemangiopericytoma-like sarcoma by combined whole-genome and RNA sequencing, we identified three additional sarcomas harbouring NTRK1 gene fusions, termed 'spindle cell sarcoma, NOS with myo/haemangiopericytic growth pattern'. The patients were two children aged 11 months and 2 years and two adults aged 51 and 80 years. While the tumours of the adults were strikingly myopericytoma-like, but with clear-cut atypical features, the paediatric cases were more akin to infantile myofibromatosis/haemangiopericytoma. All cases contained numerous thick-walled dysplastic-like vessels with segmental or diffuse nodular myxohyaline myo-intimal proliferations of smooth muscle actin-positive cells, occasionally associated with thrombosis. Immunohistochemistry showed variable expression of smooth muscle actin and CD34, but other mesenchymal markers, including STAT6, were negative. This study showed a novel variant of myo/haemangiopericytic sarcoma with recurrent NTRK1 gene fusions. Given the recent introduction of a novel therapeutic approach targeting NTRK fusion-positive neoplasms, recognition of this rare but likely under-reported sarcoma variant is strongly encouraged.
EVALuna2:6792

PALB2, CHEK2 and ATM rare variants and cancer risk: data from COGS - Southey, Melissa C.; Goldgar, David E.; Winqvist, Robert; Pylkas, Katri; Couch, Fergus; Tischkowitz, Marc; Foulkes, William D.; Dennis, Joe; Michailidou, Kyriaki; Van Rensburg, Elizabeth J.; Heikkinen, Tuomas; Nevanlinna, Heli; et al. (Journal of Medical Genetics, 2016)
The rarity of mutations in PALB2, CHEK2 and ATM make it difficult to estimate precisely associated cancer risks. Population-based family studies have provided evidence that at least some of these mutations are associated with breast cancer risk as high as those associated with rare BRCA2 mutations. We aimed to estimate the relative risks associated with specific rare variants in PALB2, CHEK2 and ATM via a multicentre case-control study.We genotyped 10 rare mutations using the custom iCOGS array: PALB2 c.1592delT, c.2816T>G and c.3113G>A, CHEK2 c.349A>G, c.538C>T, c.715G>A, c.1036C>T, c.1312G>T, and c.1343T>G and ATM c.7271T>G. We assessed associations with breast cancer risk (42 671 cases and 42 164 controls), as well as prostate (22 301 cases and 22 320 controls) and ovarian (14 542 cases and 23 491 controls) cancer risk, for each variant.For European women, strong evidence of association with breast cancer risk was observed for PALB2 c.1592delT OR 3.44 (95% CI 1.39 to 8.52, p=7.1×10(-5)), PALB2 c.3113G>A OR 4.21 (95% CI 1.84 to 9.60, p=6.9×10(-8)) and ATM c.7271T>G OR 11.0 (95% CI 1.42 to 85.7, p=0.0012). We also found evidence of association with breast cancer risk for three variants in CHEK2, c.349A>G OR 2.26 (95% CI 1.29 to 3.95), c.1036C>T OR 5.06 (95% CI 1.09 to 23.5) and c.538C>T OR 1.33 (95% CI 1.05 to 1.67) (p<=0.017). Evidence for prostate cancer risk was observed for CHEK2 c.1343T>G OR 3.03 (95% CI 1.53 to 6.03, p=0.0006) for African men and CHEK2 c.1312G>T OR 2.21 (95% CI 1.06 to 4.63, p=0.030) for European men. No evidence of association with ovarian cancer was found for any of these variants.This report adds to accumulating evidence that at least some variants in these genes are associated with an increased risk of breast cancer that is clinically important.
EVALuna2:6832

Pancreatic panniculitis in a patient with pancreatic-type acinar cell carcinoma of the liver–case report and review of literature - Zundler, Sebastian; Erber, Ramona; Agaimy, Abbas; Hartmann, Arndt; Kiesewetter, Franklin; Strobel, Deike; Neurath, Markus; Wildner, Dane (BMC Cancer, 2016)
Pancreatic panniculitis is a rare condition, which has only been described in relation with pancreatic diseases up to now. It is characterized by necrotizing subcutaneous inflammation and is thought to be triggered by adipocyte necrosis due to systemic release of pancreatic enzymes with consecutive infiltration of neutrophils. We present the first case of a patient with pancreatic panniculitis caused by pancreatic-type primary acinar cell carcinoma (ACC) of the liver and without underlying pancreatic disease.A 73-year old Caucasian female patient was referred to our department with painful cutaneous nodules persisting for eight weeks and with marked lipasemia ( 15000 U/l; normal range <60 U/l). Four weeks prior, several liver lesions had been detected. Empiric treatment with steroids did not show any effect. A biopsy of the skin nodules revealed "pancreatic" panniculitis, while abdominal imaging with ultrasound, computed tomography and magnetic resonance imaging detected no abnormal pancreatic findings. Ultrasound-guided biopsy of the liver lesions showed infiltrates of an ACC. The patient died soon thereafter. Autopsy failed to reveal any other primary for the ACC, so that a pancreatic-type ACC of the liver was diagnosed by exclusion. One hundred thirty cases of pancreatic panniculitis published within the last 20 years are reviewed. ACC of the pancreas is the most common underlying neoplastic condition. Patients with associated neoplasm are significantly older, take longer to be diagnosed and have higher lipase levels than patients with underlying pancreatitis. Extrapancreatic pancreatic-type ACC is very rare, but shows the same biological features as ACC of the pancreas. It is believed to develop from metaplastic or ectopic pancreatic tissue. Up to now, no pancreatic panniculitis in extrapancreatic ACC has been described.Pancreatic panniculitis should always be included in the differential diagnosis of lipolytic panniculitic lesions. It can be regarded as a facultative paraneoplastic phenomenon. When suspected, a thorough work-up for identification of the underlying disease is mandatory and extrapancreatic lesions (e.g. liver) should also be considered. While administration of octreotide or steroids can sometimes alleviate symptoms, immediate treatment of the associated condition is the only effective management option.
EVALuna2:2057

Pancreatic undifferentiated rhabdoid carcinoma: KRAS alterations and SMARCB1 expression status define two subtypes - Agaimy, Abbas; Haller, Florian; Frohnauer, Judith; Schaefer, Inga-Marie; Stroebel, Philipp; Hartmann, Arndt; Stoehr, Robert; Kloeppel, Guenter (Modern Pathology, 2015)
Pancreatic undifferentiated carcinoma is a heterogeneous group of neoplasms, including pleomorphic giant cell, sarcomatoid, round cell, and rhabdoid carcinomas, the molecular profiles of which have so far been insufficiently characterized. We studied 14 undifferentiated carcinomas with prominent rhabdoid cells, occurring as advanced tumors in seven females and seven males aged 44-96 years (mean: 65 years). Histologically, 10 tumors qualified as pleomorphic giant cell and 4 as monomorphic anaplastic carcinomas. A glandular component, either in the primary or in the metastases, was seen in 5 out of 14 tumors (4 out of 10 pleomorphic giant cell and 1 out of 4 monomorphic anaplastic subtypes, respectively). Osteoclast-like giant cells were absent. Immunohistochemistry revealed coexpression of cytokeratin and vimentin, and loss of membranous ?-catenin and E-cadherin staining in the majority of cases. Nuclear SMARCB1 (INI1) expression was lost in 4 out of 14 cases (28%), representing all 4 tumors of the monomorphic anaplastic subtype. FISH and mutation testing of KRAS revealed KRAS amplification in 5 out of 13 (38%) and exon 2 mutations in 6 out of 11 (54%) successfully analyzed cases. A strong correlation was found between KRAS alterations (mutation and/or copy number changes) and intact SMARCB1 expression (7 out of 8; 87%). On the other hand, loss of SMARCB1 expression correlated with the absence of KRAS alterations (3 out of 5 cases; 60%). The results suggest that rhabdoid phenotype in pancreatic undifferentiated rhabdoid carcinomas has a heterogeneous genetic background. SMARCB1 loss is restricted to the anaplastic monomorphic subtype and correlates with the absence of KRAS alterations, whereas the pleomorphic giant cell subtype is characterized by KRAS alterations and intact SMARCB1 expression. Recognition and appropriate subtyping of these rare variants might become necessary for future therapeutic strategies.
EVALuna2:6651

Pathogenetic Implications of BRAF Mutation Distribution in Stage IV Melanoma Patients - Baiter, Mirjam; Schuler, Gerold; Hartmann, Arndt; Schneider-Stock, Regine; Heinzerling, Lucie (Dermatology, 2015)
BRAF mutation frequencies in melanoma subtypes have clinical implications and offer pathogenetic clues.To characterize BRAF mutation status in melanoma of unknown primary (MUP) patients, in histological melanoma subtypes and by localization of primary tumors.In 179 patients with stage IV metastatic melanoma, BRAF mutation status, histological subtype and localization of primary (except for 29 MUP patients) were analyzed.BRAF mutations were found in 44.3%, of which 80.5% were BRAF V600E and 19.5% showed non-V600E BRAF mutations. BRAF mutation frequency depended on histological subtype (57.4% superficial spreading melanoma, 54.7% nodular melanoma, 11.1% mucosal melanoma, 28.6% acral lentiginous melanoma) and concerning non-V600E BRAF mutations on localization of primary. In MUP the BRAF mutation pattern resembled superficial spreading and nodular melanomas.BRAF mutation frequencies depend on histological subtype and localization of primary melanoma. Non-V600E BRAF mutations mostly occur in patients with primaries on 'head and neck' as well as 'trunk' but not on 'extremities'.
EVALuna2:6729

Pathologic response after induction chemo-immunotherapy with single or double immune checkpoint inhibition in locally advanced head and neck squamous cell carcinoma (HNSCC): Expansion cohorts of the CheckRad-CD8 trial. - Hecht, Markus; Eckstein, Markus; Kallies, Annett; Klautke, Gunther; Illmer, Thomas; von der Grün, Jens; Laban, Simon; Hautmann, Matthias; Tamaskovics, Bálint; Hinke, Axel; Brunner, Thomas; Frey, Benjamin; et al. (JOURNAL OF CLINICAL ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-11-04

Pathology and molecular pathology of renal cell cancer Pathologie und Molekularpathologie des Nierenzellkarzinoms - Erlmeier, Franziska; Agaimy, Abbas; Hartmann, Arndt; Stöhr, Christine G. (Onkologe, 2019)
Background: The latest edition of the WHO classification of urogenital tumors was published in January 2016. Numerous innovations have been included following the decisions of the consensus conference held in Zurich in March 2015. This review article presents the histopathology and molecular pathology of renal tumors defined in the 2016 WHO classification. Results and conclusions: In recent years knowledge about the morphology and the biological behavior of kidney tumors has steadily improved. In particular, the expanded molecular knowledge and improved data from clinicopathological studies of these tumors have led to the recognition of new entities by the WHO. These include, among others, succinate dehydrogenase B deficiency-associated renal cell carcinoma, hereditary leiomyomatosis-associated renal cell cancer, tubulocystic renal cell carcinoma and clear cell papillary renal cell carcinoma.
CRIS-Team Scopus Importer:2019-05-24
Keywords: Aberration; chromosomal; Mutation; Subtype; Urogenital tumors; WHO classification

Pathology and systemic therapy of non-clear cell renal cell carcinoma: an overview - Bergmann, Lothar; Weber, Sarah; Hartmann, Arndt; Ahrens, Marit (Expert Review of Anticancer Therapy, 2021)
Introduction: Non-clear cell renal cell carcinoma (nccRCC) represents a highly heterogenous group of kidney cancer entities. As most clinical trials predominantly include patients with clear cell RCC (ccRCC), nccRCC treatment guidelines are mainly extrapolated from recommendations in ccRCC. Here, we review and elucidate current data on the pathologic classification and treatment of nccRCC. Areas covered: This article gives an overview of the WHO classification of RCC, showing the histological diversity of nccRCC and focusing particularly on entities first characterized since 2016, their specific molecular behavior and their role as indicators for hereditary cancer syndromes. In this context, we discuss the available data on nccRCC treatment oprtions such as tyrosine kinase inhibitors, mammalian target of rapamycin inhibitors, cytotoxic chemotherapy, and immune checkpoint inhibitors. Expert opinion: Although nccRCCs are relatively uncommon, entities of this type account for a subgroup of up to 20-25% of all RCCs. Advances in histopathology and molecular genetics, together with evidence gained from retrospective and prospective clinical data, have improved understanding of these tumors in recent years. Nevertheless, selective trials of current and novel therapies including new targeted agents in patients with nccRCC are urgently needed to further improve treatment guidelines.
CRIS-Team WoS Importer:2021-08-20

Pathology of familial tumor syndromes - Hartmann, Arndt (Pathologe, 2017)
EVALuna2:6877

Pattern of SMARCB1 (INI1) and SMARCA4 (BRG1) in poorly differentiated endometrioid adenocarcinoma of the uterus: analysis of a series with emphasis on a novel SMARCA4-deficient dedifferentiated rhabdoid variant - Strehl, Johanna D.; Wachter, David; Fiedler, Jutta; Heimerl, Engelbert; Beckmann, Matthias; Hartmann, Arndt; Agaimy, Abbas (Annals of Diagnostic Pathology, 2015)
The role of the switch/sucrose nonfermenting chromatin remodeling complex in the initiation and progression of cancer is emerging. In the female genital tract, only ovarian small cell carcinoma, hypercalcemic type harbors recurrent inactivating SMARCA4 mutations. Otherwise, only rare case reports documented SMARCB1 involvement in endometrial cancer. We analyzed 24 grade 3 uterine endometrioid adenocarcinomas and 2 undifferentiated carcinomas for immunohistochemical expression of SMARCB1 and SMARCA4. All tumors showed high-grade nuclear features with a predominance of solid growth pattern. All cases showed intact nuclear SMARCB1 expression in all tumor cells. However, 1 case of a 78-year-old woman showed complete loss of SMARCA4 in 90% of the tumor with retained expression in 10% of the tumor. The SMARCA4-intact component was a moderate-to-poorly differentiated endometrioid adenocarcinoma. The SMARCA4-deficient dominating component showed solid growth of highly anaplastic undifferentiated large cells with prominent rhabdoid features. None of the 25 SMARCA4-intact cases showed rhabdoid cell morphology. To our knowledge, this is the first systematic study of SMARCB1 and SMARCA4 expression in endometrioid adenocarcinoma of uterus and the first description of a novel SMARCA4-deficient variant of dedifferentiated/undifferentiated endometrial carcinoma. The presence of a differentiated SMARCA4-intact endometrioid component points to a novel pathway of dedifferentiation in endometrioid adenocarcinoma as a consequence of a "second hit." This case further underlines the close link between the "rhabdoid phenotype" and the SWI/SNF pathway.
EVALuna2:6700

Paul Hermanek 08.03.1924-17.09.2020 - Wittekind, Christian; Hofstaedter, Ferdinand; Hartmann, Arndt (Pathologe, 2020)
CRIS-Team WoS Importer:2020-12-25

PBRM1 but not BAP1 deficiency is a frequent feature of multifocal non-cystic low-grade clear cell renal cell carcinoma - Agaimy, Abbas; Trpkov, Kiril; Gao, Yuan; Hartmann, Arndt; Hes, Ondrej (MODERN PATHOLOGY, 2019)
CRIS-Team WoS Importer:2019-08-23

PD-1/PD-L1 expression in chromophobe renal cell carcinoma: An immunological exception? - Erlmeier, Franziska; Hartmann, Arndt; Autenrieth, Michael; Wiedemann, Max; Ivanyi, Philipp; Steffens, Sandra; Weichert, Wilko (Medical Oncology, 2016)
Immune checkpoint inhibitors targeting the inhibitory cross talk between tumor and immune cells have been approved for therapy in renal cell carcinoma (RCC). In contrast to clear cell RCC, little is known on PD-1/PD-L1 expression patterns in rarer RCC subtypes. The aim of this study was to evaluate the prevalence, distribution and prognostic impact of PD-1 and PD-L1 expression in chromophobe (ch)RCC. Patients who underwent renal surgery due to chRCC were retrospectively evaluated. Tumor specimen was analyzed for PD-1 and PD-L1 expression by immunohistochemistry. Expression data were correlated with clinic-pathological parameters including patient survival. Eighty-one chRCC patients were eligible for analysis, thereof 25 (30.9 %) and 11 (13.6 %) patients were positive for PD-1(+) tumor-infiltrating mononuclear cells (TIMCs) and tumoral PD-L1(+) expression, respectively. No significant associations were found for PD-1(+) TIMC or tumoral PD-L1(+) expression and clinical attributes. In addition, no differences in 5- and 10-year overall survival for PD-1(-) TIMC compared to PD-1(+) TIMC (90.5 and 72.2 vs. 100 and 75 %; p = 0.41) and for PD-L1(-) tumors compared to PD-L1(+) tumors (91.9 and 76.4 vs. 100 and 50 %; p = 0.48) were observed. In conclusion, to our knowledge this is the first study to evaluate the prognostic impact of PD-1 and PD-L1 in chRCC. PD-L1 does seem to be expressed in a minority of all chRCC, likewise only a minority of chRCC was infiltrated by PD-1-positive inflammatory cells. Neither PD-1(+) TIMC nor tumoral PD-L1(+) expression was associated with parameters of aggressiveness or survival.
EVALuna2:6819

PD-L1 assessment in urothelial carcinoma: a practical approach - Eckstein, Markus; Cimadamore, Alessia; Hartmann, Arndt; Lopez-Beltran, Antonio; Cheng, Liang; Scarpelli, Marina; Montironi, Rodolfo; Gevaert, Thomas (Annals of Translational Medicine, 2019)
Five programmed death-1 (PD-1)/programmed death-ligand 1 (PD-L1) inhibitors are currently approved for treatment of locally advanced or metastatic urothelial carcinoma of the bladder and the upper urinary tract. Due to restrictions by the FDA and EMA first-line treatment with Atezolizumab and Pembrolizumab in platinum-ineligible patients requires immunohistochemical PD-L1 testing. In the second-line setting all drugs are approved without PD-L1 testing. Used PD-L1 assays in clinical trials include the 28-8 pharmDx (Nivolumab), the 22C3 pharmDx (Pembrolizumab), Ventana SP142 (Atezolizumab), and the Ventana PD-L1 SP263 assays (Durvalumab). Differences in antibodies, needed platforms and testing algorithms have raised questions about interchangeability and comparability among these assays and their diagnostic use. We provide a practical review about the current recommendations, used assays and algorithms of PD-L1 testing in urothelial carcinoma to help oncologists, urologists and pathologists to understand analytical features, differences in antibody assays, differences in scoring algorithms and comparability of various PD-L1 assays. We reviewed and summarized published studies from the last four years (2016-2019) on PD-L1 testing in bladder cancer and present a condensed practical guideline including pre-analytical, analytical and test-specific issues.
CRIS-Team WoS Importer:2019-12-20

PD-L1 is upregulated by radiochemotherapy in rectal adenocarcinoma patients and associated with a favourable prognosis - Hecht, Markus; Buettner-Herold, Maike; Erlenbach-Wuensch, Katharina; Haderlein, Marlen; Croner, Roland; Grützmann, Robert; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (European Journal of Cancer, 2016)
The influence of neoadjuvant radiochemotherapy (RCT) on programmed death-ligand 1 (PD-L1) expression, a predictive marker for programmed cell death protein 1 (PD-1) inhibitor therapy, was studied on tumour and inflammatory cells in rectal adenocarcinoma patients along with its prognostic value.PD-L1 immunohistochemistry was performed on tissue microarrays of 103 pre-RCT biopsies and 159 post-RCT surgical specimens (central tumour, invasive front and normal tissue) of 199 patients. In 63 patients, both samples were available. Proportion and maximum intensity of PD-L1-positive (PD-L1+) cells were evaluated.RCT increased the proportion of PD-L1-expressing cancer cells from 2.1% to 7.8% in the central tumour (p < 0.001) or 9.3% in the invasive front (p < 0.001). Cancer cell PD-L1 on its own could not predict prognosis. High PD-L1 expression on pre-RCT inflammatory cells (maximum intensity: p = 0.048) and post-RCT invasive front inflammatory cells (p = 0.010) correlated with improved no evidence of disease survival. In multivariate analysis, the combination of low PD-L1 in cancer and inflammatory cells was an independent negative prognostic marker for overall survival (OS) pre-RCT (Cox's proportional hazard ratio 0.438, p = 0.045) and in the invasive front post-RCT (Cox's proportional hazard ratio 0.257, p = 0.030).Neoadjuvant RCT is associated with an increased PD-L1 expression in rectal adenocarcinoma patients, which should prompt clinical trials combining radiotherapy and PD-1/PD-L1 pathway blockade. Combined low PD-L1 expression on tumour and inflammatory cells is an independent negative prognostic marker for OS in RCT of rectal adenocarcinoma.
EVALuna2:6814

PD-L2: A prognostic marker in chromophobe renal cell carcinoma? - Erlmeier, Franziska; Weichert, Wilko; Autenrieth, Michael; Wiedemann, Max; Schrader, Andres Jan; Hartmann, Arndt; Ivanyi, Philipp; Steffens, Sandra (Medical Oncology, 2017)
In the context of cancer immunotherapy, PD-1 as well as PD-L1 has been widely studied in renal cell carcinoma (RCC). PD-1 and PD-L1 play a significant role as prognostic markers in clear cell renal cell carcinoma. In contrast, little is known about PD-L2 expression patterns in RCC, especially in rarer subtypes. The aim of this study was to evaluate the prevalence, distribution and prognostic impact of PD-L2 expression in chromophobe (ch)RCC. Eighty-one patients who underwent renal surgery due to chRCC were retrospectively evaluated. Tumor specimens were analyzed for PD-L2 expression by immunohistochemistry. Expression data were associated with clinicopathological parameters and overall survival (OS). Twenty-three (28.4%) patients showed a PD-L2 > median (PD-L2 high) staining intensity. No significant association between clinicopathological parameters and PD-L2 expression was identified. A significant difference between 5- and 10-year OS in dependence of PD-L2 expression was found (PD-L2 low 96.4 and 87.7% vs. PD-L2 high 87.1 and 56%; log rank, p = 0.029). However, in multivariate analysis PD-L2 expression failed to be proofed as an independent prognostic factor. In conclusion, to our knowledge this is the first study evaluating the prognostic impact of PD-L2 in a considerably large cohort of chRCC. Our results showed a significant diminished OS in dependence of PD-L2 expression. This implicates that PD-L2 might play a role as prognostic marker in chRCC demanding further evaluation.
EVALuna2:6873

Pembrolizumab in combination with nab-paclitaxel for the treatment of patients with early-stage triple-negative breast cancer – A single-arm phase II trial (NeoImmunoboost, AGO-B-041) - Fasching, Peter; Hein, Alexander; Kolberg, Hans Christian; Häberle, Lothar; Uhrig, Sabrina; Rübner, Matthias; Belleville, Erik; Hack, Carolin; Fehm, Tanja N.; Janni, Wolfang; Hartmann, Arndt; Erber, Ramona; et al. (European Journal of Cancer, 2023)
Background: Pembrolizumab is approved for the neoadjuvant/adjuvant treatment of early triple-negative breast cancer (TNBC) patients in combination with chemotherapy. The Keynote-522 trial used platinum chemotherapy. As neoadjuvant nab-paclitaxel (nP) is also highly effective in triple-negative breast cancer patients, this study investigates the response to nP-containing neoadjuvant chemotherapy in combination with pembrolizumab. Patients and methods: NeoImmunoboost (AGO-B-041/NCT03289819) is a multicenter, prospective single-arm phase II trial. Patients were treated with 12 weekly cycles of nP followed by four three-weekly cycles of epirubicin/cyclophosphamide. Pembrolizumab was given three-weekly in combination with these chemotherapies. The study was planned for 50 patients. After 25 patients, the study was amended to include a pre-chemotherapy single application of pembrolizumab. The primary aim was pathological complete response (pCR), and the secondary aims were safety and quality of life. Results: Of 50 included patients, 33 (66.0%; 95%confidence interval: 51.2%–78.8%) had a (ypT0/is ypN0) pCR. The pCR rate in the per-protocol population (n = 39) was 71.8% (95%confidence interval: 55.1%–85.0%). The most common adverse events of any grade were fatigue (58.5%), peripheral sensory neuropathy (54.7%) and neutropenia (52.8%). The pCR rate in the cohort of 27 patients with a pre-chemotherapy pembrolizumab dose was 59.3%, and 73.9% in the 23 patients without pre-chemotherapy dose. Conclusions: pCR rates after NACT with nP and anthracycline combined with pembrolizumab are encouraging. With acceptable side-effect profiles, this treatment might be a reasonable alternative to platinum-containing chemotherapy in cases of contraindications. However, without data from randomised trials and long-term follow up, platinum/anthracycline/taxane-based chemotherapy remains the standard combination chemotherapy for pembrolizumab.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Neoadjuvant chemotherapy; PD-L1; Pembrolizumab; Triple-negative

Percent mammographic density and dense area as risk factors for breast cancer - Rauh, C.; Hack, Caroline; Häberle, Lothar; Hein, Alexander; Engel, Anne; Schrauder, Michael G.; Fasching, Peter; Jud, Sebastian; Ekici, Arif Bülent; Loehberg, C. R.; Meier-Meitinger, Martina; Ozan-Mergner, Sevil Julia; et al. (Geburtshilfe und Frauenheilkunde, 2012)
Purpose: Mammographic characteristics are known to be correlated to breast cancer risk. Percent mammographic density (PMD), as assessed by computer-assisted methods, is an established risk factor for breast cancer. Along with this assessment the absolute dense area (DA) of the breast is reported as well. Aim of this study was to assess the predictive value of DA concerning breast cancer risk in addition to other risk factors and in addition to PMD. Methods: We conducted a case control study with hospital-based patients with a diagnosis of invasive breast cancer and healthy women as controls. A total of 561 patients and 376 controls with available mammographic density were included into this study. We describe the differences concerning the common risk factors BMI, parital status, use of hormone replacement therapy (HRT) and menopause between cases and controls and estimate the odds ratios for PMD and DA, adjusted for the mentioned risk factors. Furthermore we compare the prediction models with each other to find out whether the addition of DA improves the model. Results: Mammographic density and DA were highly correlated with each other. Both variables were as well correlated to the commonly known risk factors with an expected direction and strength, however PMD (ρ = 0.56) was stronger correlated to BMI than DA (ρ = 0.11). The group of women within the highest quartil of PMD had an OR of 2.12 (95 % CI: 1.25-3.62). This could not be seen for the fourth quartile concerning DA. However the assessment of breast cancer risk could be improved by including DA in a prediction model in addition to common risk factors and PMD. Conclusions: The inclusion of the parameter DA into a prediction model for breast cancer in addition to established risk factors and PMD could improve the breast cancer risk assessment. As DA is measured together with PMD in the process of computer-assisted assessment of PMD it might be considered to include it as one additional breast cancer risk factor that is obtained from breast imaging. © Georg Thieme Verlag KG Stuttgart · New York.
CRIS-Team Scopus Importer:2021-07-19
Keywords: breast cancer; mammographic density; risk

Perforations after routine biopsy in IBD patients, their management and potential risk reductions by microscopic imaging with endocytoscopy - Klenske, Entcho; Hartmann, Arndt; Atreya, Raja; Neurath, Markus; Rath, Timo (Journal of Gastrointestinal and Liver Diseases, 2020)
CRIS-Team Scopus Importer:2020-09-25

Performance of the Food and Drug Administration/EMA-approved programmed cell death ligand-1 assays in urothelial carcinoma with emphasis on therapy stratification for first-line use of atezolizumab and pembrolizumab - Eckstein, Markus; Erben, Philipp; Kriegmair, Maximilian C.; Worst, Thomas S.; Weiss, Cleo-Aron; Wirtz, Ralph M.; Wach, Sven; Stoehr, Robert; Sikic, Danijel; Geppert, Carol-Immanuel; Weyerer, Veronika; Bertz, Simone; et al. (European Journal of Cancer, 2019)
BACKGROUND: Recently, the Food and Drug Administration (FDA)/European Medicines Agency (EMA) restricted first-line use of atezolizumab and pembrolizumab in patients with metastasised urothelial carcinoma by defining distinct programmed cell death ligand-1 cut-offs. We analysed the diagnostic performance of all FDA/EMA-approved programmed cell death ligand-1 assays with emphasis on new restrictions for first-line treatment with atezolizumab and pembrolizumab. PATIENTS AND METHODS: Two hundred fifty-one urothelial carcinomas were analysed on tissue microarrays with four cores of each tumour. Stains were performed in certified laboratories on Ventana Benchmark Ultra and Dako Link 48 autostainers. Stains were read on an assay-by-assay basis by two trained pathologists. Overall percentage agreement (OPA) was calculated across the preset cut-offs. Positive percentage agreement (PPA) and negative percentage agreement (NPA) were calculated across different scoring algorithms. Venn diagrams were constructed to illustrate discordance according to the recent FDA/EMA guidelines. RESULTS: The Dako 28-8, 22c3 and the Ventana SP263 assays showed high interassay correlation (r-range 0.83-0.91). Interassay correlation between the Ventana SP142 and the three other assays was moderate (r-range 0.66-0.75). OPA of 93.3% was achieved between the Dako 28-8, 22c3 and Ventana SP263 assays. OPA including the SP142 was 84.1%. Pooled PPA and NPA of different scoring algorithms was 89.4% and 95.3% for the Dako 28-8, 22c3 and the SP263 assays, respectively. With the SP142 assay, pooled PPA was 59.1%. The SP142 assay identifies fewer eligible patients for first-line treatment with atezolizumab/pembrolizumab. CONCLUSION: Dako 28-8, 22c3 and SP263 assays show interchangeable performance. The SP142 assay shows divergent staining results. Interassay variability leads to different detection rates of eligible patients for first-line treatment with atezolizumab and pembrolizumab.
EVALuna2:52994

Perspectives, potentials and trends of ex vivo and in vivo optical molecular pathology - Krafft, Christoph; Von Eggeling, Ferdinand; Guntinas-Lichius, Orlando; Hartmann, Arndt; Waldner, Maximilian; Neurath, Markus; Popp, Juergen (Journal of Biophotonics, 2018)
It is pivotal for medical applications, such as noninvasive histopathologic characterization of tissue, to realize label-free and molecule-specific representation of morphologic and biochemical composition in real-time with subcellular spatial resolution. This unmet clinical need requires new approaches for rapid and reliable real-time assessment of pathologies to complement established diagnostic tools. Photonic imaging combined with digitalization offers the potential to provide the clinician the requested information both under in vivo and ex vivo conditions. This report summarizes photonic approaches and their use in combination with image processing, machine learning and augmented virtual reality that might solve current challenges in modern medicine. Details are given for pathology, intraoperative diagnosis in head and neck cancer and endoscopic diagnosis in gastroenterology.
EVALuna2:33796

Phenotypical and molecular distinctness of sinonasal haemangiopericytoma compared to solitary fibrous tumour of the sinonasal tract - Agaimy, Abbas; Barthelmeß, Sarah; Geddert, Helene; Boltze, Carsten; Moskalev, Evgeny; Koch, Michael; Wiemann, Stefan; Hartmann, Arndt; Haller, Florian (Histopathology, 2014)
Sinonasal haemangiopericytoma (SN-HPC) is a rare sinonasal mesenchymal neoplasm of perivascular myoid cell origin. Solitary fibrous tumour (SFT) occurs only very rarely in the sinonasal tract. SFT and soft tissue HPC have been considered a single entity. Recently, recurrent gene fusions involving NAB2-STAT6 resulting in differential expression of STAT6 were characterized as central molecular events in SFT. However, no data exist for NAB2-STAT6 status or STAT6 expression in SN-HPC.We examined six SN-HPCs and two sinonasal SFTs by immunohistochemistry and RT-PCR for NAB2-STAT6 fusions. SN-HPC affected three females and three males (mean age: 72 years). They expressed smooth muscle actin, lacked strong CD34 reactivity and were negative for nuclear STAT6 expression. RT-PCR analysis confirmed the absence of NAB2-STAT6 fusions in all cases. Conversely, both sinonasal SFTs (in males aged 39 and 52 years) displayed classical features of pleuropulmonary and soft-tissue SFTs (uniformly CD34-positive with strong nuclear expression of STAT6). RT-PCR revealed NAB2-STAT6 fusions in both cases.These findings confirm the molecular and phenotypical distinctness of these two entities. While SN-HPC is a site-specific sinonasal neoplasm of as yet unknown molecular pathogenesis, sinonasal SFTs show phenotypical and molecular identity to their pleural/extrapleural counterparts.
EVALuna2:6649

Phosphaturic Mesenchymal Tumors: Clinicopathologic, Immunohistochemical and Molecular Analysis of 22 Cases Expanding their Morphologic and Immunophenotypic Spectrum - Agaimy, Abbas; Michal, Michael; Chiosea, Simion; Petersson, Fredrik; Hadravsky, Ladislav; Kristiansen, Glen; Horch, Raymund E.; Schmolders, Jan; Hartmann, Arndt; Haller, Florian; Michal, Michal (American Journal of Surgical Pathology, 2017)
Phosphaturic mesenchymal tumor (PMT) is a rare neoplasm of uncertain histogenesis that has been linked to tumor-induced osteomalacia (TIO) since 1959. The neoplastic cells produce increased amount of FGF23 which results in TIO via uncontrolled renal loss of phosphate (phosphaturia), and consequently diminished bone mineralization. To date, 300 cases have been reported. Although there is increasing evidence that PMT can be diagnosed by reproducible histopathologic features, firm diagnosis has been often restricted to cases associated with TIO and, hence, diagnosis of "nonphosphaturic variants" remained challenging. Recently, FGFR1/FN1 gene fusions were detected in roughly half of cases. We herein reviewed the clinicopathologic features of 22 PMTs (15 cases not published before), stained them with an extended immunohistochemical marker panel and examined them by fluorescence in situ hybridization for FGFR1 gene fusions. Patients were 12 males and 9 females (one of unknown sex) aged 33 to 83 years (median: 52 y). Lesions affected the soft tissues (n=11), bones (n=6), sinonasal tract (n=4), and unspecified site (n=1). Most lesions originated in the extremities (9 in the lower and 4 in the upper extremities). Acral sites were involved in 10 patients (6 foot/heel, 3 fingers/hands, and 1 in unspecified digit). Phosphaturia and TIO were recorded in 10/11 and 9/14 patients with detailed clinical data, respectively. Limited follow-up (5 mo to 14 y; median: 16 mo) was available for 14 patients. Local recurrence was noted in one patient and metastasis in another patient. Histologically, 11 tumors were purely of conventional mixed connective tissue type, 3 were chondromyxoid fibroma-like, 2 were hemangio-/glomangiopericytoma-like with giant cells, and 1 case each angiomyolipoma-like and reparative giant cell granuloma-like. Four tumors contained admixture of patterns (predominantly cellular with variable conventional component). Immunohistochemistry showed consistent expression of CD56 (11/11; 100%), ERG (19/21; 90%), SATB2 (19/21; 90%), and somatostatin receptor 2A (15/19; 79%), while other markers tested negative: DOG1 (0/17), beta-catenin (0/14), S100 protein (0/14), and STAT6 (0/7). FGFR1 fluorescence in situ hybridization was positive in 8/17 (47%) evaluable cases. These results add to the phenotypic delineation of PMT reporting for the first time consistent expression of SATB2 and excluding any phenotypic overlap with solitary fibrous tumor or sinonasal glomangiopericytoma. The unifying immunophenotype of the neoplastic cells irrespective of the histologic pattern suggests a specific disease entity with diverse morphotypes/variants rather than different neoplasms unified by TIO.
EVALuna2:6834

Piwil 2 expression is correlated with disease-specific and progression-free survival of chemotherapy-treated bladder cancer patients - Taubert, Helge; Wach, Sven; Jung, Rudolf; Pugia, Michael; Keck, Bastian; Bertz, Simone; Nolte, Elke; Stoehr, Robert; Lehmann, Jan; Ohlmann, Carsten-H; Stöckle, Michael; Wullich, Bernd; et al. (Molecular Medicine, 2015)
Piwi-like 2 (Piwil 2) belongs to the family of Argonaute genes/proteins. The expression of Piwil 2 is associated with stem cells. A role in tumorigenesis and/or tumor progression is proposed for different cancers but not yet for bladder cancer (BCa). We investigated the Piwil 2 expression by immunohistochemistry in a cohort of 202 BCa patients treated by cystectomy and adjuvant chemotherapy. The association between Piwil 2 expression and disease-specific (DSS) or progression-free survival (PFS) was calculated using Kaplan Meier analyses and univariate/multivariate Cox's regression hazard models.In a multivariate Cox's regression, Piwil 2 expression, either in the cytoplasm or the nucleus, was significantly associated with DSS and PFS. A weak cytoplasmic staining pattern was associated with poor DSS and tumor progression (RR=2.7; P=0.004 and RR=2.4; P=0.027). Likewise,, absent nuclear Piwil 2 immunoreactivity was associated with poor DSS and tumor progression (RR=2.3; P=0.023 and RR=2.2; P=0.022). BCa patients whose tumors exhibited a combination of weak cytoplasmic and absent nuclear immunoreactivity had a 6-fold increased risk of tumor-related death (P=0.005) compared to patients with strong expression. Considering only patients with high grade G3 tumors, a 7.8-fold risk of tumor-associated death and a 3.6-fold risk of tumor progression were detected independently of the histologic tumor subtype or the chemotherapy regimen. In summary, a combination of weak cytoplasmic and absent nuclear expression of Piwil 2 is significantly associated with an increased risk of DSS and tumor progression. This implicates that Piwil 2 could be a valuable prognostic marker for high-risk BCa patients.
EVALuna2:6705

Piwi-like 1 and-2 protein expression levels are prognostic factors for muscle invasive urothelial bladder cancer patients - Eckstein, Markus; Jung, Rudolf; Weigelt, Katrin; Sikic, Danijel; Stoehr, Robert; Geppert, Carol-Immanuel; Agaimy, Abbas; Lieb, Verena; Hartmann, Arndt; Wullich, Bernd; Wach, Sven; Taubert, Helge (Scientific Reports, 2018)
Piwi-like proteins are essential for stem-cell maintenance and self-renewal in multicellular organisms. We analyzed the expression of Piwi-like 1 and Piwi-like 2 by immunohistochemistry (IHC) in 95 muscle invasive bladder cancer (MIBC) samples using tissue microarray. Application of an immunoreactive score (IRS) revealed 37 and 45 patients who were Piwi-like 1 and -2 positive (IRS > 2). IHC results were correlated with clinico-pathological and survival data. The expression of both proteins was positively correlated with each other, lymph node metastasis and expression of CK20 and GATA 3. A negative correlation for both proteins was detected for disease-specific survival (DSS), recurrence, Ki67/MIB1 proliferation index, and CK5 expression. Detection of Piwi-like 1 protein positivity was associated with poor DSS (P = 0.019; log rank test, Kaplan-Meier analysis), and in multivariate Cox's analysis (adjusted to tumor stage and tumor grade), it was an independent prognostic factor for DSS (RR = 2.16; P = 0.011). Piwi-like 2 positivity was associated with DSS (P = 0.008) and recurrence-free survival (RFS; P = 0.040), and in multivariate Cox's analysis, Piwi-like 2 positivity was an independent prognostic factor for DSS (RR = 2.46; P = 0.004) and RFS (RR = 3.0; P = 0.003). Most interestingly, in the basal type patient subgroup (CK5+/GATA3-), Piwi-like 2 positivity was associated with poorer DSS, OS and RFS (P < 0.001, P = 0.004 and P = 0.05; log rank test). In multivariate analysis, Piwi-like 2 positivity was an independent prognostic factor for DSS (RR = 12.70; P = 0.001), OS (RR = 6.62; = 0.008) and RFS (RR=13.0; P = 0.040). In summary, Piwi-like 1 and -2 positivity are associated with clinico-pathological factors and survival. Both Piwi-like proteins are suggested as biomarkers for MIBC patients.
EVALuna2:35874

Piwi-like 1 and 4 gene transcript levels are associated with clinicopathological parameters in renal cell carcinomas - Al-Janabi, Omar; Wach, Sven; Nolte, Elke; Weigelt, Katrin; Rau, Tilman; Stoehr, Christine; Legal, Wolfgang; Schick, Stefan; Greither, Thomas; Hartmann, Arndt; Wullich, Bernd; Taubert, Helge (Biochimica et Biophysica Acta - Molecular Basis of Disease, 2014)
Piwi-like gene family members (Piwil 1-4) are considered stem cell-associated genes/proteins. These are expressed predominantly in germline cells, but are re-expressed in different tumors. Piwil 1-4 gene expression has not previously been studied and correlated with clinicopathological parameters in renal cell carcinomas (RCC). The Piwil 1-4 transcript levels were analyzed by quantitative real-time PCR in 73 clear cell RCC (ccRCC) tissues and corresponding normal tissues. The transcript levels of Piwil 1, 2 and 4 were strongly and significantly correlated with each other, in both the tumor tissues and the normal tissues (P<0.001; Spearman's rank test). Piwil 4 gene expression was significantly higher in the ccRCC tissues than that in the corresponding normal renal tissues (P<0.001; Wilcoxon signed-rank test). When the ccRCC patient cohort was divided according to the median Piwil 1-4 expression into low- and high-expression groups and according to age into younger (<=64years) and older patient groups (>64years), the younger patients displayed significantly higher levels of Piwil 1 mRNA in comparison to the older patients (P=0.010; Fisher's exact test). Interestingly, Piwil 1 expression was left-right polarized in the normal tissues but not in the tumor tissues (P=0.004; Fisher's exact test). Altogether, associations were determined between the Piwi-like family member expression levels and clinicopathological parameters of ccRCC, suggesting a potential role for these genes/proteins in ccRCC diagnostics and tumorigenesis as well as in renal tissue embryology.
EVALuna2:6563

Piwi-like 1 and piwi-like 2 expression in breast cancer - Erber, Ramona; Meyer, Julia; Taubert, Helge; Fasching, Peter; Wach, Sven; Häberle, Lothar; Gaß, Paul; Schulz-Wendtland, Rüdiger; Landgraf, Laura; Olbricht, Sabrina; Jung, Rudolf; Beckmann, Matthias; et al. (Cancers, 2020)
PIWI-like 1 and PIWI-like 2 play a role in stem cell self-renewal, and enhanced expression has been reported for several tumor entities. However, few studies have investigated PIWI-like 1 and PIWI-like 2 expressions in breast cancer subtypes regarding prognosis. Therefore, we examined protein expression in a large consecutive cohort of breast cancer patients and correlated it to breast cancer subtypes and survival outcome. PIWI-like 1 and PIWI-like 2 expressions were evaluated using immunohistochemistry in a cohort of 894 breast cancer patients, of whom 363 were eligible for further analysis. Percentage and intensity of stained tumor cells were analyzed and an immunoreactive score (IRS) was calculated. The interaction of PIWI-like 1 and PIWI-like 2 showed a prognostic effect on survival. For the combination of high PIWI-like 1 and low PIWI-like 2 expressions, adjusted hazard ratios (HRs) were significantly higher with regard to overall survival (OS) (HR 2.92; 95% confidence interval (CI) 1.24, 6.90), disease-free survival (DFS) (HR 3.27; 95% CI 1.48, 7.20), and distant disease-free survival (DDFS) (HR 7.64; 95% CI 2.35, 24.82). Both proteins were significantly associated with molecular-like and PAM50 subgroups. Combining high PIWI-like 1 and low PIWI-like 2 expressions predicted poorer prognosis and both markers were associated with aggressive molecular subtypes.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Breast cancer; HER2; Luminal A; Luminal B; Molecular breast cancer subtypes; PIWI-like 1; PIWI-like 2; PIWIL1; PIWIL2; TNBC

Piwi-like 1 protein expression is a prognostic factor for renal cell carcinoma patients - Stoehr, Christine; Steffens, Sandra; Polifka, Iris; Jung, Rudolf; Kahlmeyer, Andreas; Ivanyi, Philipp; Weber, Florian; Hartmann, Arndt; Wullich, Bernd; Wach, Sven; Taubert, Helge (Scientific Reports, 2019)
The Piwi-like genes belong to the Argonaute gene family and are conserved in plants, animals and humans. In addition to their essential role in the germ line and as stem cell-associated genes, Piwi-like proteins play a role in different cancer types but have yet to be studied in renal cell carcinoma (RCC). We investigated tissue micro arrays (TMAs) with tumor samples of two independent cohorts of RCC patients (N = 265 and N = 345); we used immunohistochemistry to assess the protein expression of Piwi-like 1. Applying an immunoreactive score (IRS), we found Piwi-like 1 positivity (IRS > 0) in 28.3% and 14.8% of the tumors in cohorts 1 and 2, respectively. Piwi-like 1 positivity was correlated with Fuhrman grade, tumor stage and the presence of distant metastasis (P < 0.005). Moreover, in univariate and multivariate analyses (adjusted to Fuhrman grade and tumor stage), Piwi-like 1 positivity was associated with a shorter cancer-specific survival in the patients in the second cohort. In addition, Piwi-like 1 expression allowed to further distinguish the RCC patients with high Fuhrman grade, high tumor stage, distant metastasis or high pre-operative levels of C-reactive protein, as Piwi-like 1 positivity was associated with a shorter cancer-specific survival in both cohorts. Our data encourage further investigations to enlighten the role of Piwi-like 1 and its function as a marker of poor prognosis in RCC patients.
CRIS-Team WoS Importer:2019-02-22

Polymorphisms in the RANK/RANKL genes and their effect on bone specific prognosis in breast cancer patients - Hein, Alexander; Bayer, Christian M.; Schrauder, Michael G.; Haeberle, Lothar; Heusinger, Katharina; Strick, Reiner; Ruebner, Matthias; Lux, Michael P.; Renner, Stefan; Schulz-Wendtland, Rüdiger; Ekici, Arif Bülent; Hartmann, Arndt; et al. (BioMed Research International, 2014)
The receptor activator of NF-?B (RANK) pathway is involved in bone health as well as breast cancer (BC) pathogenesis and progression. Whereas the therapeutic implication of this pathway is established for the treatment of osteoporosis and bone metastases, the application in adjuvant BC is currently investigated. As genetic variants in this pathway have been described to influence bone health, aim of this study was the prognostic relevance of genetic variants in RANK and RANKL. Single nucleotide polymorphisms in RANK(L) (rs1054016/rs1805034/rs35211496) were genotyped and analyzed with regard to bone metastasis-free survival (BMFS), disease-free survival, and overall survival for a retrospective cohort of 1251 patients. Cox proportional hazard models were built to examine the prognostic influence in addition to commonly established prognostic factors. The SNP rs1054016 seems to influence BMFS. Patients with two minor alleles had a more favorable prognosis than patients with at least one common allele (HR 0.37 (95% CI: 0.17, 0.84)), whereas other outcome parameters remained unaffected. rs1805034 and rs35211496 had no prognostic relevance. The effect of rs1054016(RANKL) adds to the evidence that the RANK pathway plays a role in BC pathogenesis and progression with respect to BMFS, emphasizing the connection between BC and bone health.
EVALuna2:6628

Polypoid Undifferentiated Rhabdoid Carcinoma in the Intestine: A Distinctive Presentation of Metastatic -Mostly Occult -Undifferentiated Non-small Cell Lung Carcinoma Illustrated in a Series of 12 Cases - Agaimy, Abbas; Daum, Ondrej; Michal, Michal; Hartmann, Arndt; Lauwers, Gregory (MODERN PATHOLOGY, 2020)
CRIS-Team WoS Importer:2020-03-24

Pooled analysis of the prognostic relevance of progesterone receptor status in five German cohort studies - Salmen, Jessica; Neugebauer, Julia; Fasching, Peter; Häberle, Lothar; Huober, Jens; Woeckel, Achim; Rauh, Claudia; Schuetz, Florian; Weissenbacher, Tobias; Kost, Bernd; Stickeler, Elmar; Klar, Maximilian; et al. (Breast Cancer Research and Treatment, 2014)
The progesterone receptor (PR) has been increasingly well described as an important mediator of the pathogenesis and progression of breast cancer. The aim of this study was to assess the role of PR status as a prognostic factor in addition to other well-established prognostic factors. Data from five independent German breast cancer centers were pooled. A total of 7,965 breast cancer patients were included for whom information about their PR status was known, as well as other patient and tumor characteristics commonly used as prognostic factors. Cox proportional hazards models were built to compare the predictive value of PR status in addition to age at diagnosis, tumor size, nodal status, grading, and estrogen receptor (ER) status. PR status significantly increased the accuracy of prognostic predictions with regard to overall survival, distant disease-free survival, and local recurrence-free survival. There were differences with regard to its prognostic value relative to subgroups such as nodal status, ER status, and grading. The prognostic value of PR status was greatest in patients with a positive nodal status, negative ER status, and low grading. The PR-status adds prognostic value in addition to ER status and should not be omitted from clinical routine testing. The significantly greater prognostic value in node-positive and high-grade tumors suggests a greater role in the progression of advanced and aggressive tumors.
EVALuna2:6666

Positive fibroblast growth factor receptor 3 immunoreactivity is associated with low-grade non-invasive urothelial bladder cancer - Poyet, Cedric; Hermanns, Thomas; Zhong, Qing; Drescher, Eva; Eberli, Daniel; Burger, Maximilian; Hofstaedter, Ferdinand; Hartmann, Arndt; Stoehr, Robert; Zwarthoff, Ellen C.; Sulser, Tullio; Wild, Peter J. (Oncology Letters, 2015)
In addition to conventional clinicopathological parameters, molecular markers are also required in order to predict the course of disease in patients with urothelial bladder cancer (BC). Little is known about fibroblast growth factor receptor 3 (FGFR3) immunoreactivity and the clinical significance it may possess with regard to BC. The present study aimed to investigate the immunoreactivity of FGFR3 in primary urothelial bladder tumours, with regard to clinicopathological features and FGFR3 mutation status. Tissue microarrays were used to immunohistochemically analyse FGFR3 expression in 255 primary, unselected patients with BC. FGFR3 mutations were detected using SNaPshot analysis. Positive FGFR3 immunoreactivity was identified in 113/207 analysable cases (54.6%), and was significantly associated with FGFR3 mutation (P<0.001), low tumour stage (P<0.001), low histological grade (P<0.001) and a papillary growth pattern (P<0.001). Positive FGFR3 immunostaining (P=0.002) and FGFR3 mutation (P=0.002) were found to be significantly associated with increased disease-specific survival following univariate analysis, demonstrating a median follow-up period of 75 months. Using multivariate analyses, FGFR3 immunoreactivity was found not to be independent of classical pathological parameters. Immunohistochemical expression of FGFR3 is an early occurrence during the carcinogenesis of papillary non-invasive BC. The presence of FGFR3 immunoreactivity in non-invasive papillary urothelial carcinomas may be utilised as an indicator of tumours possessing low-grade features and good prognosis.
EVALuna2:6791

Praktische Aspekte von COVID-19-Obduktionen - Boor, Peter; Eichhorn, Philip; Hartmann, Arndt; Lax, Sigurd F.; Märkl, Bruno; Menter, Thomas; Skok, Kristijan; Slotta-Huspenina, Julia; von Stillfried, Saskia; Tzankov, Alexandar; Weirich, Gregor (Pathologe, 2021)
Background: The COVID-19 pandemic represents a so far unknown challenge for the medical community. Autopsies are important for studying this disease, but their safety was challenged at the beginning of the pandemic. Objectives: To determine whether COVID-19 autopsies can be performed under existing legal conditions and which safety standards are required. Materials and methods: The autopsy procedure undertaken in five institutions in Germany, Austria, and Switzerland is detailed with respect to legal and safety standards. Results: In all institutions the autopsies were performed in technically feasible rooms. The personal equipment consisted of functional clothing including a disposable gown and apron, a surgical cap, eye protection, FFP‑3 masks, and two pairs of gloves. In four institutions, complete autopsies were performed; in one institution the ultrasound-guided biopsy within the postmortal imaging and biopsy program. The latter does not allow the appreciation of gross organ pathology; however, it is able to retrieve standardized biopsies for diagnostic and research purposes. Several scientific articles in highly ranked journals resulted from these autopsies and allowed deep insights into organ damage and conclusions to better understand the pathomechanisms. Viral RNA was frequently detectable in the COVID-19 deceased, but the issue of infectivity remains unresolved and it is questionable if Ct values are greater than 30. Conclusions: With appropriate safeguards, autopsies of people who have died from COVID-19 can be performed safely and are highly relevant to medical research.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Biomedical research; Reference standards; Safety management; SARS-CoV‑2; Ultrasonography

Predicting Triple-Negative Breast Cancer Subtype Using Multiple Single Nucleotide Polymorphisms for Breast Cancer Risk and Several Variable Selection Methods - Häberle, Lothar; Hein, Alexander; Rübner, Matthias; Schneider, Michael; Ekici, Arif Bülent; Gaß, Paul; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Beckmann, Matthias; Lo, Wing-Yee; Schroth, Werner; Brauch, Hiltrud; et al. (Geburtshilfe und Frauenheilkunde, 2017)
Studies of triple-negative breast cancer have recently been extending the inclusion criteria and incorporating additional molecular markers into the selection criteria, opening up scope for targeted therapies. The screening phases required for studies of this type are often prolonged, since the process of determining the molecular subtype and carrying out additional biomarker assessment is time-consuming. Parameters such as germline genotypes capable of predicting the molecular subtype before it becomes available from pathology might be helpful for treatment planning and optimizing the timing and cost of screening phases. This appears to be feasible, as rapid and low-cost genotyping methods are becoming increasingly available. The aim of this study was to identify single nucleotide polymorphisms (SNPs) for breast cancer risk capable of predicting triple negativity, in addition to clinical predictors, in breast cancer patients.This cross-sectional observational study included 1271 women with invasive breast cancer who were treated at a university hospital. A total of 76 validated breast cancer risk SNPs were successfully genotyped. Univariate associations between each SNP and triple negativity were explored using logistic regression analyses. Several variable selection and regression techniques were applied to identify a set of SNPs that together improve the prediction of triple negativity in addition to the clinical predictors of age at diagnosis and body mass index (BMI). The most accurate prediction method was determined by cross-validation.The SNP rs10069690 (TERT, CLPTM1L) was the only significant SNP (corrected p = 0.02) after correction of p values for multiple testing in the univariate analyses. This SNP and three additional SNPs from the genes RAD51B, CCND1, and FGFR2 were selected for prediction of triple negativity. The addition of these SNPs to clinical predictors increased the cross-validated area under the curve (AUC) from 0.618 to 0.625. Age at diagnosis was the strongest predictor, stronger than any genetic characteristics.Prediction of triple-negative breast cancer can be improved if SNPs associated with breast cancer risk are added to a prediction rule based on age at diagnosis and BMI. This finding could be used for prescreening purposes in complex molecular therapy studies for triple-negative breast cancer.
EVALuna2:6850

Prediction of pathological complete response and prognosis in patients with neoadjuvant treatment for triple-negative breast cancer - Gaß, Paul; Lux, Michael P.; Rauh, Claudia; Hein, Alexander; Bani, Mayada; Fießler, Cornelia; Hartmann, Arndt; Häberle, Lothar; Pretscher, Jutta; Erber, Ramona; Wachter, David; Schulz-Wendtland, Rüdiger; et al. (BMC Cancer, 2018)
BACKGROUND: It has been reported that pathological complete response is an important surrogate marker for disease-free survival and overall survival in patients with triple-negative breast cancer. This study investigates predictors of the response to neoadjuvant platinum-based or anthracycline-based treatment, and of the prognosis, in patients with triple-negative breast cancer. METHODS: A total of 121 patients with triple-negative breast cancer received neoadjuvant treatment with either platinum or anthracycline between 2008 and 2013. Pathological complete response was assessed relative to different treatments using logistic regression models with age, clinical tumor stage, grading, and Ki-67 as predictors and interaction terms, to obtain adjusted and subgroup-specific results. The impact of the pathological complete response rate on disease-free survival and overall survival was also analyzed. RESULTS: The pathological complete response rate was higher after platinum/taxane treatment compared with anthracycline/taxane (50.0% vs. 41.8%), but this was not significant in the adjusted analysis (OR 1.44; 95% CI, 0.68 to 3.09). A high histological grade (G3) was a predictor for higher pathological complete response in platinum-based therapy (OR 2.27; 95% CI, 1.00 to 5.30). The effect of neoadjuvant chemotherapy on pathological complete response was significantly different for G1-2 vs. G3 (Pinteraction = 0.013), and additional subgroup-specific differences were noted. Pathological complete response was a predictor for improved disease-free survival and overall survival in both treatment groups, with and without platinum chemotherapy. CONCLUSIONS: This retrospective study of patients with triple-negative breast cancer adds to the evidence that the treatment effect of platinum may be greatest particularly in G3 tumors. In addition, the effect of pathological complete response on the prognosis does not depend on the treatment used.
EVALuna2:34850

Predictive role of HER2/neu, topoisomerase-II-alpha, and tissue inhibitor of metalloproteinases (TIMP-1) for response to adjuvant taxane-based chemotherapy in patients with intermediate-risk breast cancer: results from the WSG-AGO EC-Doc trial - Erber, Ramona; Gluz, Oleg; Brünner, Nils; Kreipe, Hans Heinrich; Pelz, Enrico; Kates, Ronald; Bartels, Annette; Huober, Jens; Mohrmann, Svjetlana; Moustafa, Zehra; Liedtke, Cornelia; Möbus, Volker; et al. (Breast Cancer Research and Treatment, 2015)
Taxane-anthracycline-based adjuvant chemotherapy is standard of care in patients with node-positive breast cancer (BC) but is also associated with severe side effects and significant costs. It is yet unclear, which biomarkers would predict benefit from taxanes and/or general chemoresistance. In this study, we investigate a large cohort of patients with intermediate-risk BC treated within the WSG EC-DOC Trial for the predictive impact of topoisomerase-II-alpha, HER2/neu, and TIMP-1. Tumor tissue was available in a representative cohort of 772 cases of the WSG EC-DOC Trial collective which compared 4xEC-4xDoc versus 6xCEF/CMF. In addition to hormone receptor status and Ki-67, HER2/neu+ and topoisomerase-II-alpha status using fluorescence in situ hybridisation (FISH) and immunohistochemistry, TIMP-1 using immunohistochemistry, and aneuploidy of chromosome 17 using FISH were evaluated and correlated with outcome and taxane benefit. There was significant superiority of EC-Doc over CEF regarding 5-year DFS (90 vs. 80 %, respectively, p = 0.006) particularly in patient subgroups defined by HR+, HER2/neu+, high proliferation (i.e., Ki-67 >= 20 %), patient age >50 years old and normal chromosome 17 status, high TIMP-1 and low topoisomerase-II-alpha protein expression. Significant prognostic factors in multivariate analysis were EC-Doc therapy (HR = 0.61; 95 %CI 0.38-0.986), age <50 years old (HR = 1.682; 95 %CI 1.025-2.579), centrally assessed grade 3 (HR = 4.657; 95 %CI 1.809-11.989), and high Ki-67 (HR = 2.232; 95 %CI 1.209-4.121). Interestingly, we observed a significant interaction between treatment arm (EC-Doc vs. CEF) and high topoisomerase-II-alpha protein expression (HR = 0.427; 95 %CI 0.203-0.900) in multivariate interaction analysis. Despite of univariate predictive effect of HER2/neu status among other factors only topoisomerase-II-alpha protein expression was associated with significant benefit from EC-Doc compared to CEF by multivariate interaction analysis.
EVALuna2:6702

Predictive value of FHIT, p27, and pERK1/ERK2 in salivary gland carcinomas: a retrospective study - Fiedler, Mathias; Renner, Patty; Schubert, Juergen; Weber, Florian; Hartmann, Arndt; Iro, Heinrich; Vielsmeier, Veronika; Bohr, Christopher; Gerken, Michael; Reichert, Torsten E.; Ettl, Tobias (Clinical Oral Investigations, 2019)
Objectives: The aim of this study was to investigate the predictive value of the biomarkers FHIT, p27, and pERK1/ERK2 in salivary gland carcinomas. Material and methods: Immunohistochemical staining of FHIT, p27, and pERK1/ERK2 of 265 patients with salivary gland carcinomas was conducted, and associations with clinico-histopathological data, overall survival, and disease-specific survival were examined. Results: Expression of FHIT (quick score 98.7 vs. 206.4) and p27 (QS 187.3 vs. 244.8) was significantly lower in carcinomas compared to non-tumor control tissue. Loss of FHIT frequently occurred in ACC (55.2%), SDC (68.2%), and SCC (100%). In the totality of tumors, loss of FHIT expression was found in 46.7% (106/227) and was significantly associated with advanced T stage and UICC stage, high-grade histology, loss of p27, PI3K, and survivin. FHIT positivity went along with significantly better overall and disease-specific survival. Negativity of p27 occurred in 28.7% (70/244) of tumors, particularly in SDC (54.4%) and SCC (50%). In the totality of tumors, p27 was associated with advanced patient age, high-grade histology, PI3K, survivin as well as better overall and disease-specific survival (p < 0.05). Positive pERK1/ERK2 expression correlated with positive survivin expression but did not affect overall survival in the totality of tumors. In mucoepidermoid carcinomas, pERK1/ERK2 expression was associated with low-grade malignancy, positive nuclear survivin, and better disease-specific survival. Conclusions: Loss of FHIT and p27 characterizes aggressive tumor growth and unfavorable prognosis in salivary gland cancer. Clinical relevance: The results may help to stratify patient-specific therapies according to individual tumor characteristics.
CRIS-Team Scopus Importer:2019-10-25
Keywords: FHIT; p27; pERK1/ERK2; Salivary gland carcinoma

Predictive value of fibroblast growth factor receptor (FGFR) alterations on anti-PD-(L)1 treatment outcomes in patients (Pts) with advanced urothelial cancer (UC): Pooled analysis of real-world data - Kim, William Y.; Rose, Tracy; Roghmann, Florian; Eckstein, Markus; Jarczyk, Jonas; Zengerling, Friedemann; Sikic, Danijel; Breyer, Johannes; Bolenz, Christian; Hartmann, Arndt; Mayhew, Gregory; Shibata, Yoichiro; et al. (JOURNAL OF CLINICAL ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-05-22

Predictive value of molecular subtyping in NMIBC by RT-qPCR of ERBB2, ESR1, PGR and MKI67 from formalin fixed TUR biopsies - Breyer, Johannes; Wirtz, Ralph Markus; Otto, Wolfgang; Laible, Mark; Schlombs, Kornelia; Erben, Philipp; Kriegmair, Maximilian Christian; Stoehr, Robert; Eidt, Sebastian; Denzinger, Stefan; Burger, Maximilian; Hartmann, Arndt (Oncotarget, 2017)
Expression of ESR1, PGR, HER2 and Ki67 is important for risk stratification and therapy in breast cancer. Hormone receptor expression can also be found in MIBC, reflecting luminal and basal subtypes of breast cancer. Thus the purpose was to investigate on the mRNA expression of the aforementioned markers and their prognostic value in pT1 bladder cancer. Retrospective analysis of clinical data and Formalin-Fixed Paraffin-Embedded tissues (FFPE) of patients with stage pT1 NMIBC who underwent transurethral resection of the bladder was performed. mRNA expression was measured by single step RT-qPCR. Relative gene expression was determined by normalization to two housekeeping genes (CALM2, B2M) using the 40-??CT method. Correlation of mRNA expression with outcome was assessed using Kaplan-Meier analysis and multivariate Cox regression analysis. From overall 302 patients, 255 samples could be analyzed with valid measurements. Subtype distribution was Luminal-A in 11.4%, Luminal-B in 38.8%, triple negative in 36.9% and ERBB2 in 12.9%, respectively. Kaplan-Meier analysis revealed molecular subtyping being statistical significant for RFS (p=0.0408) and PFS (p=0.0039). Luminal-A patients did have the best RFS and PFS. Multivariate analysis revealed molecular subtyping to be significant for PFS (L-R Chi(2) of 11.89, p=0.0078). Elevated expression of HER2 was statistically significant for PFS (p=0.0025) and discriminated among G3 tumors a high risk group (60% PFS) from a low risk risk group (90% PFS) after 5 year follow-up (p<0.001). Expression of ESR1, PGR and HER2 has predictive value in stage pT1 NMIBC and reveals potential therapeutic targets.
EVALuna2:6903

Predictive Value of Multiparametric MRI for Response to Single-Cycle Induction Chemo-Immunotherapy in Locally Advanced Head and Neck Squamous Cell Carcinoma - Hellwig, Konstantin; Ellmann, Stephan; Eckstein, Markus; Wiesmüller, Marco; Rutzner, Sandra; Semrau, Sabine; Frey, Benjamin; Gaipl, Udo; Hartmann, Arndt; Iro, Heinrich; Fietkau, Rainer; Uder, Michael; et al. (Frontiers in Oncology, 2021)
Objectives
CRIS-Team WoS Importer:2021-11-19

Prevalence of an association between coeliac disease and vitiligo - Henker, J.; Hartmann, Arndt (Hautarzt, 2019)
Coeliac disease and vitiligo are immune-mediated disorders that are often associated with other immune-mediated disorders. In a prospective study we included 174 patients with vitiligo between the ages of 3 and 79 years (mean 38.2 years) to investigate whether there is an increased risk for coeliac disease in patients with vitiligo. We determined immunoglobulin A and IgA- and IgG-antibodies against tissue transglutaminase, while also optionally measuring blood count, ferritin, and endomysial-IgA-antibodies. In 3 of 174 (1.7%) vitiligo patients, coeliac disease was diagnosed serologically and by duodenal biopsy. Assuming a coeliac disease prevalence of less than 0.0033%, the incidence is statistically significant. In two other patients with vitiligo, coeliac disease was already known and confirmed with biopsy. If these two patients are included in the calculation, 2.8% (5 von 176) of vitiligo patients have coeliac disease. This value is statistically significant even with a higher coeliac disease prevalence of 0.01. Thus, it is recommended that celiac-disease-specific antibodies also be determined during routine blood workup in vitiligo patients. In case of positive results, a gastroduodenoscopy with biopsy of the small intestine is recommended for diagnosis confirmation. If celiac disease is unlikely, a trial of gluten-free diet for a specific time should nevertheless be discussed with individuals affected by vitiligo because repigmentation appears possible.
CRIS-Team WoS Importer:2019-10-18

Prevalence of SARS-CoV-2 in Pregnant Women Assessed by RT-PCR in Franconia, Germany: First Results of the SCENARIO Study (SARS-CoV-2 prEvalence in pregNAncy and at biRth In FrancOnia) - Hein, Alexander; Kehl, Sven; Häberle, Lothar; Tiemann, Carsten; Peuker, Rebecca; Mereutanu, Denise; Stumpfe, Florian; Faschingbauer, Florian; Meyer-Schlinkmann, Kirstin; Koch, Martin C.; Kainer, Franz; Dammer, Ulf; et al. (Geburtshilfe und Frauenheilkunde, 2022)
Purpose Detection of SARS-CoV-2-infected pregnant women admitted to maternity units during a pandemic is crucial. In addition to the fact that pregnancy is a risk factor for severe COVID-19 and that medical surveillance has to be adjusted in infected women and their offspring, knowledge about infection status can provide the opportunity to protect other patients and healthcare workers against virus transmission. The aim of this prospective observational study was to determine the prevalence of SARS-CoV-2 infection among pregnant women in the hospital setting. Material and Methods All eligible pregnant women admitted to the nine participating hospitals in Franconia, Germany, from 2 June 2020 to 24 January 2021 were included. COVID-19-related symptoms, secondary diseases and pregnancy abnormalities were documented. SARS-CoV-2 RNA was detected by RT-PCR from nasopharyngeal swabs. The prevalence of acute SARS-CoV-2 infection was estimated by correcting the positive rate using the Rogan-Gladen method. The risk of infection for healthcare workers during delivery was estimated using a risk calculator. Results Of 2414 recruited pregnant women, six were newly diagnosed RT-PCR positive for SARS-CoV-2, which yielded a prevalence of SARS-CoV-2 infection of 0.26% (95% CI, 0.10-0.57%). Combining active room ventilation and wearing FFP2 masks showed an estimated reduction of risk of infection for healthcare workers in the delivery room to < 1%. Conclusions The prevalence of newly diagnosed SARS-CoV-2 infection during pregnancy in this study is low. Nevertheless, a systematic screening in maternity units during pandemic situations is important to adjust hygienic and medical management. An adequate hygienic setting can minimise the calculated infection risk for medical healthcare workers during patients' labour.
CRIS-Team Scopus Importer:2022-02-25
Keywords: COVID-19; infection; pregnancy; prevalence; SARS-CoV-2

Primary mixed adeno-neuroendocrine carcinoma (MANEC) of the urinary bladder: a rare entity - Eckstein, Markus; Rasper, Bernd; Busche, Joerg; Stachetzki, Ulf; Wistuba, D. E.; Agaimy, Abbas; Hartmann, Arndt; Bertz, Simone (Aktuelle Urologie, 2017)
A 67-year-old male patient underwent transurethral resection for a bladder tumour at the lower posterior wall found incidentally on imaging for an unrelated disease. The initial histomorphological examination suggested an adenocarcinoma with partial neuroendocrine differentiation. Imaging of the thorax and the abdomen, showed no evidence of another primary tumour. Due to the unusual diagnosis, the case was sent to our department of pathology for expert consultation, which confirmed the diagnosis of a primary mixed adeno-neuroendocrine carcinoma of the bladder (MANEC). Mixed adeno-neuroendocrine carcinomas are rare tumours that mostly occur in the colorectum. To our knowledge, this case is the fifth case report of a MANEC primarily arising in the urinary bladder.
EVALuna2:6854

Primary pseudomyogenic haemangioendothelioma of the testis with a novel POTEI::FOSB gene fusion - Gersmann, Ann Kathrin; Haller, Florian; Behnert, Nina; Richter, Annika; Stöhr, Robert; Hartmann, Arndt; Ströbel, Philipp; Bremmer, Felix (Histopathology, 2022)
CRIS-Team Scopus Importer:2022-06-03
Keywords: POTEI::FOSB; pseudomyogenic haemangioendothelioma; testis

Primary renal synovial sarcoma; a clinicopathological study of 19 cases comparing diagnostic utility of SS18-SSX-specific antibody with TLE1 - Din, N. Ud; Fatima, S.; Hartmann, Arndt; Agaimy, Abbas (HISTOPATHOLOGY, 2021)
CRIS-Team WoS Importer:2021-10-08

Primary results of the phase II CheckRad-CD8 trial: First-line treatment of locally advanced head and neck squamous cell carcinoma (HNSCC) with double checkpoint blockade and radiotherapy dependent on intratumoral CD8+T-cell infiltration. - Hecht, Markus; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Klautke, Gunther; Laban, Simon; Hautmann, Matthias G.; Brunner, Thomas; Tamaskovics, Bálint; Hinke, Axel; Frey, Benjamin; et al. (ASCO 2021 Annual Meeting, 2021)
CRIS-Team WoS Importer:2021-11-26

Primary Results of the phase II CheckRad-CD8 Trial: First-Line Treatment of locally advanced Head and Neck Tumors with double Checkpoint Blockade and Radiotherapy dependent on intratumoral CD8+T-Cell Infiltration - Hecht, Markus; Eckstein, Markus; Rutzner, Sandra; Von Der Gruen, J.; Illmer, T.; Klautke, G.; Laban, S.; Hautmann, M.; Brunner, T.; Tamaskovics, B.; Hinke, A.; Frey, Benjamin; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Primary signet ring stromal tumor of the testis: a study of 13 cases indicating their phenotypic and genotypic analogy to pancreatic solid pseudopapillary neoplasm - Michalova, Kvetoslava; Michal, Michael; Kazakov, Dmitry V.; Sedivcova, Monika; Hes, Ondrej; Hadravsky, Ladislav; Agaimy, Abbas; Tretiakova, Maria; Bacchi, Carlos; Hartmann, Arndt; Kuroda, Naoto; Bulimbasic, Stela; et al. (Human Pathology, 2017)
Primary signet ring stromal tumor of the testis (PSRSTT) is an extremely rare tumor described only twice in the literature. Pancreatic-analogue solid pseudopapillary neoplasm (SPN) of the testis is a recently reported entity with morphological overlap with PSRSTT. We reviewed our files to find all cases of PSRSTT to better characterize this entity. We studied 13 cases of PSRSTTs using histological, immunohistochemical (IHC), and molecular genetic methods and compared the results with pancreatic SPN. Grossly, the size of PSRSTTs ranged from 0.5 to 2 cm (mean 1.1). Microscopically, PSRSTTs predominantly showed a proliferation of low-grade epithelioid cells containing characteristic cytoplasmic vacuole dislodging the nucleus (signet ring cells) separated by fibrous septa into trabeculae and nests. The immunoprofile was characterized by immunoreactivity for ?-catenin, cyclin D1 (nuclear positivity for both antibodies), CD10, vimentin, galectin-3, claudin 7, ?-1-antitrypsin, CD56, and neuron-specific enolase and negativity for chromogranin, inhibin, calretinin, SF-1, NANOG, OCT3/4, and SALL4. In some cases, the IHC panel was restricted because of a limited amount of tissue. Molecular genetic analysis revealed mutations within exon 3 of the CTNNB1 encoding ?-catenin in all analyzable cases. Based on histological similarities between pancreatic SPN and PSRSTT and their identical IHC and molecular genetic features, we assume that both neoplasms share the same pathogenesis, and thus, PSRSTT can be considered as a testicular analogue of pancreatic SPN.
EVALuna2:6892

Proficiency testing of PIK3CA mutations in HR+/HER2-breast cancer on liquid biopsy and tissue - Vollbrecht, Claudia; Hoffmann, Inga; Lehmann, Annika; Merkelbach-Bruse, Sabine; Fassunke, Jana; Wagener-Ryczek, Svenja; Ball, Markus; Dimitrova, Lora; Hartmann, Arndt; Stöhr, Robert; Erber, Ramona; Weichert, Wilko; et al. (Virchows Archiv, 2022)
Precision oncology based on specific molecular alterations requires precise and reliable detection of therapeutic targets in order to initiate the optimal treatment. In many European countries—including Germany—assays employed for this purpose are highly diverse and not prescribed by authorities, making inter-laboratory comparison difficult. To ensure reproducible molecular diagnostic results across many laboratories and different assays, ring trials are essential and a well-established tool. Here, we describe the design and results of the ring trial for the detection of therapeutically relevant PIK3CA hotspot mutations in HR+/HER2-breast cancer tissue and liquid biopsy (LB). For PIK3CA mutation detection in tissue samples, 43 of the 54 participants (80%) provided results compliant with the reference values. Participants using NGS-based assays showed higher success rate (82%) than those employing Sanger sequencing (57%). LB testing was performed with two reference materials differing in the length of the mutated DNA fragments. Most participants used NGS-based or commercial real-time PCR assays (70%). The 167 bp fragments led to a successful PIK3CA mutation detection by only 31% of participants whereas longer fragments of 490 bp were detectable even by non-optimal assays (83%). In conclusion, the first ring trial for PIK3CA mutation detection in Germany showed that PIK3CA mutation analysis is broadly established for tissue samples and that NGS-based tests seem to be more suitable than Sanger sequencing. PIK3CA mutation detection in LB should be carried out with assays specifically designed for this purpose in order to avoid false-negative results.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Alpelisib; Breast cancer; Liquid biopsy; PIK3CA; Proficiency testing

Profiling intratumoral heterogeneity of bladder cancer subtypes at the single-cell level using machine-learning assisted histopathology. - Van Rhijn, Bas; Mertens, Laura; Mayr, Roman; Bostrom, Peter; Marques, Mirari; Van Leenders, Geert; Gotz, Stefanie; Van Der Heijden, Michiel; Jewett, Michael; Real, Francisco; Stöhr, Robert; Zlotta, Alexandre; et al. (CLINICAL CANCER RESEARCH, 2020)
CRIS-Team WoS Importer:2020-08-28

Prognostic and predictive molecular markers for urologic cancers - Hartmann, Arndt; Schlomm, T.; Bertz, Simone; Heinzelmann, J.; Hoelters, S.; Simon, R.; Stoehr, R.; Junker, K. (Urologe, 2014)
Molecular prognostic factors and genetic alterations as predictive markers for cancer-specific targeted therapies are used today in the clinic for many malignancies. In recent years, many molecular markers for urogenital cancers have also been identified. However, these markers are not clinically used yet. In prostate cancer, novel next-generation sequencing methods revealed a detailed picture of the molecular changes. There is growing evidence that a combination of classical histopathological and validated molecular markers could lead to a more precise estimation of prognosis, thus, resulting in an increasing number of patients with active surveillance as a possible treatment option. In patients with urothelial carcinoma, histopathological factors but also the proliferation of the tumor, mutations in oncogenes leading to an increasing proliferation rate and changes in genes responsible for invasion and metastasis are important. In addition, gene expression profiles which could distinguish aggressive tumors with high risk of metastasis from nonmetastasizing tumors have been recently identified. In the future, this could potentially allow better selection of patients needing systemic perioperative treatment. In renal cell carcinoma, many molecular markers that are associated with metastasis and survival have been identified. Some of these markers were also validated as independent prognostic markers. Selection of patients with primarily organ-confined tumors and increased risk of metastasis for adjuvant systemic therapy could be clinically relevant in the future.
EVALuna2:6615

Prognostic and Predictive Value of Fibroblast Growth Factor Receptor Alterations in High-grade Non–muscle-invasive Bladder Cancer Treated with and Without Bacillus Calmette-Guérin Immunotherapy - Mayr, Roman; Eckstein, Markus; Wirtz, Ralph M.; Santiago-Walker, Ademi; Baig, Mahadi; Sundaram, Ramesh; Carcione, Jenna Cody; Stöhr, Robert; Hartmann, Arndt; Bolenz, Christian; Burger, Maximilian; Otto, Wolfgang; et al. (European Urology, 2022)
Background: Limited data are available on the prognostic and predictive value of fibroblast growth factor receptor alterations (FGFRa) relative to clinical outcomes in patients with non–muscle-invasive bladder cancer (NMIBC). Objective: To determine whether FGFRa may be clinically useful in stratifying for treatment response in a real-world cohort of patients with pT1 NMIBC treated and untreated with bacillus Calmette-Guérin (BCG) instillation therapy. Design, setting, and participants: A pooled dataset of matched clinical and genomic data (1992–2015) for pT1 NMIBC patients was assessed by the Bladder Cancer Research Initiative for Drug Targets in Germany consortium. Outcome measurements and statistical analysis: Key efficacy outcomes were recurrence-free survival (RFS), progression-free survival (PFS), and disease-specific survival (DSS), which were estimated by Kaplan-Meier analysis, with hazard ratios calculated using a multivariate Cox proportional-hazard model. Results and limitations: In this retrospective study of 263 patients with high-grade NMIBC, at a median follow-up of 63 mo, 32% showed recurrence and 15% progressed to muscle-invasive bladder cancer. FGFRa were found in 43% of patients, including 39% mutations and 5.7% fusions. FGFRa were associated with lower rates of concomitant carcinoma in situ. Among patients with or without FGFRa, there was no significant difference in PFS, RFS, and DSS in those who were BCG treated or BCG naive, or in the overall population. Limitations include the retrospective design from a single-center setting. Conclusions: In patients with high-risk NMIBC, FGFRa were frequently observed. Patients with FGFRa who often exhibit recurrence/relapse after BCG treatment have a high unmet need. Patient summary: Our retrospective study suggests that fibroblast growth factor receptor alterations (FGFRa) occur frequently in non–muscle-invasive bladder cancer (NMIBC). Outcomes were similar with or without FGFRa in patients with NMIBC, both overall and for standard bacillus Calmette-Guérin (BCG) treatment.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Bacillus Calmette-Guérin; Bladder cancer; FGFR alterations; Fibroblast growth factor receptor; Non–muscle-invasive bladder cancer

Prognostic effect of Ki-67 in common clinical subgroups of patients with HER2-negative, hormone receptor-positive early breast cancer - Fasching, Peter; Gaß, Paul; Häberle, Lothar; Volz, Bernhard; Hein, Alexander; Hack, Carolin; Lux, Michael P.; Jud, Sebastian; Hartmann, Arndt; Beckmann, Matthias; Slamon, Dennis J.; Erber, Ramona (Breast Cancer Research and Treatment, 2019)
Purpose: Several clinical trials have investigated the prognostic and predictive usefulness of molecular markers. With limited predictive value, molecular markers have mainly been used to identify prognostic subgroups in which the indication for chemotherapy is doubtful and the prognosis is favorable enough for chemotherapy to be avoided. However, limited information is available about which groups of patients may benefit from additional therapy. This study aimed to describe the prognostic effects of Ki-67 in several common subgroups of patients with early breast cancer. Methods: This retrospective study analyzed a single-center cohort of 3140 patients with HER2−, hormone receptor-positive breast cancer. Five-year disease-free survival (DFS) rates were calculated for low (< 10%), intermediate (10–19%), and high (≥ 20%) Ki-67 expression levels, as assessed by immunohistochemistry, and for subgroups relative to age, body mass index, disease stage, tumor grade, and (neo-)adjuvant chemotherapy. It was also investigated whether Ki-67 had different effects on DFS in these subgroups. Results: The 5-year DFS rates for patients with low, intermediate, and high levels of Ki-67 expression were 0.90, 0.89, and 0.77, respectively. Ki-67 was able to further differentiate patients with an intermediate prognosis into different prognostic groups relative to common clinical parameters. Patients with stage II breast cancer had 5-year DFS rates of 0.84, 0.88, and 0.79 for low, intermediate, and high levels of Ki-67 expression. Ki-67 had different prognostic effects in subgroups defined by age and tumor grade. Conclusions: Ki-67 may help identify patients in intermediate prognostic groups with an unfavorable prognosis who may benefit from further therapy.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Breast cancer; Ki-67; Molecular marker; Prognosis; Proliferation

Prognostic Impact of a 12-gene Progression Score in Non-muscle-invasive Bladder Cancer: A Prospective Multicentre Validation Study - Dyrskjot, Lars; Reinert, Thomas; Algaba, Ferran; Christensen, Emil; Nieboer, Daan; Hermann, Gregers G.; Mogensen, Karin; Beukers, Willemien; Marquez, Mirari; Segersten, Ulrika; Hoyer, Soren; Ulhoi, Benedicte P.; et al. (European Urology, 2017)
BACKGROUND: Progression of non-muscle-invasive bladder cancer (NMIBC) to muscle-invasive bladder cancer (MIBC) is life-threatening and cannot be accurately predicted using clinical and pathological risk factors. Biomarkers for stratifying patients to treatment and surveillance are greatly needed. OBJECTIVE: To validate a previously developed 12-gene progression score to predict progression to MIBC in a large, multicentre, prospective study. DESIGN, SETTING, AND PARTICIPANTS: We enrolled 1224 patients in ten European centres between 2008 and 2012. A total of 750 patients (851 tumours) fulfilled the inclusion and sample quality criteria for testing. Patients were followed for an average of 28 mo (range 0-76). A 12-gene real-time qualitative polymerase chain reaction assay was performed for all tumours and progression scores were calculated using a predefined formula and cut-off values. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: We measured progression to MIBC using Cox regression analysis and log-rank tests for comparing survival distributions. RESULTS AND LIMITATIONS: The progression score was significantly (p<0.001) associated with age, stage, grade, carcinoma in situ, bacillus Calmette-Guérin treatment, European Organisation for Research and Treatment of Cancer risk score, and disease progression. Univariate Cox regression analysis showed that patients molecularly classified as high risk experienced more frequent disease progression (hazard ratio 5.08, 95% confidence interval 2.2-11.6; p<0.001). Multivariable Cox regression models showed that the progression score added independent prognostic information beyond clinical and histopathological risk factors (p<0.001), with an increase in concordance statistic from 0.82 to 0.86. The progression score showed high correlation (R2=0.85) between paired fresh-frozen and formalin-fixed paraffin-embedded tumour specimens, supporting translation potential in the standard clinical setting. A limitation was the relatively low progression rate (5%, 37/750 patients). CONCLUSIONS: The 12-gene progression score had independent prognostic power beyond clinical and histopathological risk factors, and may help in stratifying NMIBC patients to optimise treatment and follow-up regimens. PATIENT SUMMARY: Clinical use of a 12-gene molecular test for disease aggressiveness may help in stratifying patients with non-muscle-invasive bladder cancer to optimal treatment regimens.
EVALuna2:33571

Prognostic impact of molecular muscle-invasive bladder cancer subtyping approaches and correlations with variant histology in a population-based mono-institutional cystectomy cohort - Weyerer, Veronika; Stöhr, Robert; Bertz, Simone; Lange, Fabienne; Geppert, Carol-Immanuel; Wach, Sven; Taubert, Helge; Sikic, Danijel; Wullich, Bernd; Hartmann, Arndt; Eckstein, Markus (World Journal of Urology, 2021)
Purpose Recently discovered molecular classifications for urothelial bladder cancer appeared to be promising prognostic and predictive biomarkers. The present study was conducted to evaluate the prognostic impact of molecular subtypes assessed by two different methodologies (gene and protein expression), to compare these two approaches and to correlate molecular with histological subtypes in a consecutively collected, mono-institutional muscle-invasive bladder cancer (MIBC) cohort. Methods 193 MIBC were pathologically re-evaluated and molecular subtypes were assessed on mRNA (NanoString technology, modified 21-gene-containing MDACC approach) and protein levels (immuno-histochemical [IHC] analysis of CK5, CK14, CD44, CK20, GATA3 and FOXA1). Descriptive statistical methods and uni-/multi-variable survival models were employed to analyze derived data. Results Neither gene expression nor protein-based subtyping showed significant associations with disease-specific (DSS) or recurrence-free survival (RFS). Agreement between mRNA (reference) and protein-based subtyping amounted 68.6% for basal, 76.1% for luminal and 50.0% for double-negative tumors. Histological subtypes associated with RFS in uni-variable (P = 0.03), but not in multivariable survival analyses. Tumors with variant histology predominantly showed luminal subtypes (gene expression subtyping: 36/55 cases, 65.5%; protein subtyping: 44/55 cases, 80.0%). Squamous differentiation significantly associated with basal subtypes (gene expression subtyping: 44/45 squamous cases, 97.8%; protein subtyping: 36/45 cases, 80.0%). Conclusion In our consecutive cystectomy cohort, neither gene, protein expression-based subtyping, nor histological subtypes associated with DSS or RFS in multi-variably adjusted survival analyses. Application of a limited IHC subtyping marker panel showed high concordance of 83.9% with gene expression-based subtyping, thus underlining the utility for subtyping in pathological routine diagnostics. In addition, histological MIBC subtypes are strong indicators for intrinsic subtypes.
CRIS-Team WoS Importer:2021-07-23

Prognostic impact of PD-1 and its ligands in renal cell carcinoma - Erlmeier, Franziska; Weichert, Wilko; Schrader, Andres Jan; Autenrieth, Michael; Hartmann, Arndt; Steffens, Sandra; Ivanyi, Philipp (Medical Oncology, 2017)
Programmed death-1 receptor (PD-1) and programmed death-1 receptor-ligand (PD-L1) have been suggested to play a role as prognostic markers in clear cell renal cell carcinoma (ccRCC). The association between PD-L1 and prognosis seems to be more robust than for PD-1. Further, preliminary analyses suggest that neither PD-1 nor its ligands play a role as prognostic markers in non-clear cell RCC, while the prognostic role of PD-L2 in ccRCC as well as in non-clear cell RCC remains unclear.
EVALuna2:6874

Prognostic impact of variant histologies in urothelial bladder cancer treated with radical cystectomy - Claps, Francesco; van de Kamp, Maaike W.; Mayr, Roman; Bostrom, Peter J.; Shariat, Shahrokh F.; Hippe, Katrin; Bertz, Simone; Neuzillet, Yann; Sanders, Joyce; Otto, Wolfgang; van der Heijden, Michiel S.; Jewett, Michael A.S.; et al. (Bju International, 2023)
Objectives: To evaluate variant histologies (VHs) for disease-specific survival (DSS) in patients with invasive urothelial bladder cancer (BCa) undergoing radical cystectomy (RC). Materials and Methods: We analysed a multi-institutional cohort of 1082 patients treated with upfront RC for cT1-4aN0M0 urothelial BCa at eight centres. Univariable and multivariable Cox’ regression analyses were used to assess the effect of different VHs on DSS in overall cohort and three stage-based analyses. The stages were defined as ‘organ-confined’ (≤pT2N0), ‘locally advanced’ (pT3-4N0) and ‘node-positive’ (pTanyN1-3). Results: Overall, 784 patients (72.5%) had pure urothelial carcinoma (UC), while the remaining 298 (27.5%) harboured a VH. Squamous differentiation was the most common VH, observed in 166 patients (15.3%), followed by micropapillary (40 patients [3.7%]), sarcomatoid (29 patients [2.7%]), glandular (18 patients [1.7%]), lymphoepithelioma-like (14 patients [1.3%]), small-cell (13 patients [1.2%]), clear-cell (eight patients [0.7%]), nested (seven patients [0.6%]) and plasmacytoid VH (three patients [0.3%]). The median follow-up was 2.3 years. Overall, 534 (49.4%) disease-related deaths occurred. In uni- and multivariable analyses, plasmacytoid and small-cell VHs were associated with worse DSS in the overall cohort (both P = 0.04). In univariable analyses, sarcomatoid VH was significantly associated with worse DSS, while lymphoepithelioma-like VH had favourable DSS compared to pure UC. Clear-cell (P = 0.015) and small-cell (P = 0.011) VH were associated with worse DSS in the organ-confined and node-positive cohorts, respectively. Conclusions: More than 25% of patients harboured a VH at time of RC. Compared to pure UC, clear-cell, plasmacytoid, small-cell and sarcomatoid VHs were associated with worse DSS, while lymphoepithelioma-like VH was characterized by a DSS benefit. Accurate pathological diagnosis of VHs may ensure tailored counselling to identify patients who require more intensive management.
CRIS-Team Scopus Importer:2023-03-03
Keywords: #BladderCancer; #blcsm; #uroonc; #utuc; bladder urothelial carcinoma; prognosis; radical cystectomy; survival; variant histology

Prognostic markers in invasive bladder cancer: FGFR3 mutation status versus P53 and KI-67 expression: a multi-center, multi-laboratory analysis in 1058 radical cystectomy patients - Mertens, Laura S.; Claps, Francesco; Mayr, Roman; Bostrom, Peter J.; Shariat, Shahrokh F.; Zwarthoff, Ellen C.; Boormans, Joost L.; Abas, Cheno; van Leenders, Geert J.L.H.; Götz, Stefanie; Hippe, Katrin; Bertz, Simone; et al. (Urologic Oncology-Seminars and Original Investigations, 2022)
Objectives: To determine the association between the FGFR3 mutation status and immuno-histochemistry (IHC) markers (p53 and Ki-67) in invasive bladder cancer (BC), and to analyze their prognostic value in a multicenter, multi-laboratory radical cystectomy (RC) cohort. Patients and methods: We included 1058 cN0M0, chemotherapy-naive BC patients who underwent RC with pelvic lymph-node dissection at 8 hospitals. The specimens were reviewed by uro-pathologists. Mutations in the FGFR3 gene were examined using PCR-SNaPshot; p53 and Ki-67 expression were determined by standard IHC. FGFR3 mutation status as well as p53 (cut-off>10%) and Ki-67 (cut-off>20%) expression were correlated to clinicopathological parameters and disease specific survival (DSS). Results: pT-stage was
CRIS-Team Scopus Importer:2022-03-04
Keywords: Bladder; Cancer; Cystectomy; FGFR3; Immunohistochemistry; Ki-67; Mutation; p53; Urothelial carcinoma

Prognostic relevance of Ki-67 in the primary tumor for survival after a diagnosis of distant metastasis - Loehberg, Christian R.; Almstedt, Katrin; Jud, Sebastian; Haeberle, Lothar; Fasching, Peter; Hack, Carolin; Lux, Michael P.; Thiel, Falk; Schrauder, Michael G.; Brunner, Michaela; Bayer, Christian M.; Hein, Alexander; et al. (Breast Cancer Research and Treatment, 2013)
Prediction of the prognosis for metastatic breast cancer patients depends on molecular subtypes similar to those found in patients with primary breast cancer. Several studies have shown that estrogen receptor (ER) and progesterone receptor (PR) status determine the course of the disease and the prognosis. As Ki-67 helps to differentiate molecular subtypes in patients with primary breast cancer, the aim of this study was to assess the prognostic relevance of Ki-67 in the primary tumor in relation to its prognostic relevance for patients with metastatic breast cancer. A total of 467 patients with invasive breast cancer were identified in the database of a single breast cancer center, in whom Ki-67 had been assessed in tumor material from the breast at the time of the primary diagnosis and who had developed a metastasis at any time during the subsequent course. For these patients, tumor and patient characteristics were used to determine prognostic factors relative to overall survival after the diagnosis of distant metastases. Ki-67 was added to this model to investigate whether this might improve the prediction of overall survival. In the multivariate Cox model, age at diagnosis, body mass index, nodal status, tumor size, ER and PR status, and time from diagnosis to metastasis were identified as relevant prognostic factors. Adding Ki-67 to the model improved the prediction of overall survival. There was also a significant and relevant interaction with the PR status. In patients with a low-proliferation primary tumor, a high level of PR expression would indicate an extraordinarily good prognosis (HR 0.39; 95 % CI, 0.23-0.66). In patients with higher-proliferation primary tumors, PR status was not capable of differentiating prognostic groups. Ki-67 is useful in addition to known prognostic factors for breast cancer. It is able to indicate a group of women with a poorer prognosis, specifically in the group of patients with PR-positive breast cancer. © 2013 Springer Science+Business Media New York.
CRIS-Team Scopus Importer:2021-07-19
Keywords: Ki-67; Metastatic breast cancer; Progesterone receptor; Prognosis; Proliferation

Prognostic Role of FGFR Alterations and FGFR mRNA Expression in Metastatic Urothelial Cancer Undergoing Checkpoint Inhibitor Therapy - Tully, Karl H.; Jütte, Hendrik; Wirtz, Ralph M.; Jarczyk, Jonas; Santiago-Walker, Ademi; Zengerling, Friedemann; Breyer, Johannes; Sikic, Danijel; Kriegmair, Maximilian C.; von Hardenberg, Jost; Wullich, Bernd; Taubert, Helge; et al. (Urology, 2021)
Objective: To examine the disease-specific survival(DSS) after checkpoint inhibitor(CPI) therapy based on FGFR alterations and FGFR mRNA expression levels in patients with metastatic urothelial cancer(mUCa) within a multi-center cohort. Methods: Within a cohort of 72 patients with mUCa from five academic centers in Germany FGFR alterations, as well as FGFR1-4 mRNA expression levels in tumor samples from the primary tumor or metastatic sites. Spearman rank correlations, logistic regression, as well as Kaplan-Meier survival analyses and univariate Cox proportional hazards regression models were employed to examine the impact of different FGFR patterns on the DSS after CPI treatment. Results: FGFR3 mutations or gene fusions (gene alterations) were detected in 16.9% of all samples. Patients with or without FGFR3 gene alterations did not show different oncological outcomes undergoing CPI treatment. Low expression of FGFR2 mRNA alone, as well as the combination of either low FGFR2mRNA expression and FGFR3 gene alteration or high FGFR3mRNA expression (P = 0.027), identified a subgroup of patients with unfavorable outcomes, comprising 40% of the total cohort. This trend was also observed in univariate Cox proportional hazards regression analysis(FGFR3 gene alteration: Hazard ratio(HR) 5.33, 95%Confidence interval(CI)1.76-15.0, P = 0.004; FGFR3mRNA expression:HR 3.04, 95%CI 1.40-7.13, P = 0.005). Conclusion: Assessment of FGFR mRNA expression identified a high-risk subgroup of patients with mUCa. These patients showing overexpression of FGFR3 mRNA were found to have unfavorable DSS after CPI treatment. Using this approach may be suitable for identifying a patient population with poor response to CPI treatment, which may benefit from early FGFR inhibition.
CRIS-Team Scopus Importer:2021-07-30

Prognostic role of FGFR Mutations and FGFR mRNA expression in metastatic urothelial cancer treated with anti-PD(L1) inhibitors in first and second-line setting - Roghmann, F.; Wirtz, R.; Jarczyk, J.; Kriegmair, M. C.; Worst, T. S.; Sikic, D.; Wach, S.; Taubert, Helge; Wullich, Bernd; Weyerer, Veronika; Stöhr, Robert; Zengerling, F.; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Prognostic Value of Molecular Breast Cancer Subtypes based on Her2, ESR1, PGR and Ki67 mRNA-Expression in Muscle Invasive Bladder Cancer - Kriegmair, M. C.; Wirtz, R. M.; Worst, T. S.; Breyer, J.; Ritter, M.; Keck, Bastian; Boehmer, C.; Otto, W.; Eckstein, Markus; Weis, C. A.; Hartmann, Arndt; Bolenz, C.; et al. (Translational Oncology, 2018)
INTRODUCTION: Gene expression analyses have identified similarities between bladder and breast cancer, where clinical risk stratification is based on Her2, ESR1, PGR and Ki67 expression. The aim of the study was to assess the respective marker gene expression in patients treated with radical cystectomy for muscle-invasive bladder cancer (MIBC) and to evaluate the applicability of breast cancer subtypes for MIBC risk stratification. MATERIALS & METHODS: 102 patients treated with radical cystectomy for MIBC were assessed. Using routine FFPE tissue and an IVD validated kit, mRNA expression was measured by single step RT-qPCR. Partition test were employed to define cut-off values for high or low marker gene expression. Association of expression with outcome was assessed using Kaplan-Meier analysis and multivariate cox regression analysis. Finally, we performed validation of our results in the MD-Anderson cohort (n=57). RESULTS: Cancer specific survival (CSS) was impaired in patients with high gene expression of Her2 (P=0.0009) and ESR1 (P=0.04). In the multivariate regression model Her2 expression remained significant for the prediction of CSS (HR=2.11, CI 1.11-4.21, P=0.024). Furthermore, molecular stratification by breast cancer subgroups was significant (P=0.023) for CSS prediction. Especially the differentiation between Her2-positive and Luminal A (HR=4.41, CI 1.53-18.71, P=0.004) and Luminal B (HR=1.96, CI 0.99-4.08, P=0.053) respectively was an independent prognostic parameter for CSS. External validation resulted in comparable risk stratification with differences in fractional subgroups distribution. CONCLUSION: Gene expression of Her2, ESR1, PGR, Ki67 and corresponding breast cancer subtypes allow a risk-stratification in MIBC, whereby Her2 overexpressing tumors reveal a particularly poor prognosis.
EVALuna2:34058

Prognostic value of O-6-methylguanine-DNA methyltransferase loss in salivary gland carcinomas - Scesnaite, Asta; Jarmalaite, Sonata; Müller, Maximilian; Agaimy, Abbas; Zenk, Johannes; Hartmann, Arndt; Iro, Heinrich; Peters, Brigitte; Schwarz, Susanne; Schneider-Stock, Regine (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2014)
The purpose of this study was to determine the prognostic value of O-6-methylguanine-DNA methyltransferase (MGMT) inactivation in a group of 286 patients with salivary gland carcinoma and matched histologically normal tissues.MGMT promoter methylation was studied in 36 patients with salivary gland carcinoma and 19 histologically matched normal tissues by pyrosequencing. MGMT protein expression was examined in 286 patients with salivary gland carcinomas and histologically matched normal tissues by immunohistochemistry on tissue microarrays. The results were correlated to demographic, clinicopathologic parameters, and disease follow-up data.MGMT hypermethylation was significantly (p = .021) associated with the protein loss. MGMT loss was found in 39.2% of salivary gland carcinomas and was predominant in aggressive tumors (poorly differentiated, grade III, regional lymph node involved). MGMT loss significantly (p = .004) predicted poor clinical outcome of salivary gland carcinomas and defined high-risk subgroups in clinically favorable tumor groups.We suggest that immunohistochemical evaluation of nuclear MGMT protein might serve as a tool for the prediction of overall survival in patients with salivary gland carcinoma.
EVALuna2:6616

Programmed death ligand 1 (PD-L1) in colon cancer and its interaction with budding and tumor-infiltrating lymphocytes (TILs) as tumor-host antagonists - Lang-Schwarz, Corinna; Melcher, Balint; Hartmann, Arndt; Bertz, Simone; Dregelies, Theresa; Lang-Schwarz, Klaus; Vieth, Michael; Sterlacci, William (International Journal of Colorectal Disease, 2021)
Purpose To analyze the role of programmed death ligand 1 (PD-L1) immunohistochemisty in the context of tumor microenvironment in colon cancer (CC) with focus on the interaction between tumor budding and tumor-infiltrating lymphocytes (TILs) and to elucidate its potential value for immunooncologic treatment decisions. Methods Three hundred forty seven patients with CC, stages I to IV, were enrolled. PD-L1 immunohistochemistry was performed using two different antibodies (clone 22C3 pharmDx, Agilent and clone QR1, Quartett). Tumor proportion score (TPS) as well as immune cell score (IC) was assessed. Budding and TILs were assessed according to the criteria of the International Tumor Budding Consensus Conference (ITBCC) and International TILs Working Group (ITWG). Correlation analyses as well as survival analyses were performed. Results PD-L1 positivity significantly correlated with TILs > 5% and MMR deficiency, and PD-L1-positive cases (overall and IC) showed significantly longer overall survival (OS) with both antibodies.The parameters "high grade," "right-sidedness," and "TILS > 5% regardless of MMR status" evolved as potential parameters for additional immunological treatment decisions. Additionally, TPS positivity correlated with low budding. More PD-L1-positive cases were seen in both high TIL groups. The low budding/high TIL group showed longer disease-free survival and longer OS in PD-L1-positive cases. Conclusion Overall, PD-L1 positivity correlated with markers of good prognosis. PD-L1 immunohistochemistry was able to identify parameters as additional potential candidates for immune therapy. Furthermore, it was able to stratify patients within the low budding/high TIL group with significant prognostic impact.
CRIS-Team WoS Importer:2021-07-16

Progranulin (GP88) is an independent prognostic factor for prostate cancer patients - Taubert, Helge; Abdulrahman, Amer; Eckstein, Markus; Jung, Rudolf; Guzman, Juan; Weigelt, Katrin; Serrero, Ginette; Yue, Binbin; Geppert, Carol-Immanuel; Stöhr, Robert; Hartmann, Arndt; Wullich, Bernd; et al. (CANCER RESEARCH, 2020)
CRIS-Team WoS Importer:2021-03-05

Prominent entrapment of respiratory epithelium in primary and metastatic intrapulmonary non-epithelial neoplasms: a frequent morphological pattern closely mimicking adenofibroma and other biphasic pulmonary lesions - Erber, Ramona; Haller, Florian; Hartmann, Arndt; Agaimy, Abbas (Virchows Archiv, 2020)
As one of the most common target organs for hematogenous spread from diverse cancers, biopsy interpretation of lung tumors is complicated by the challenging question of primary versus metastatic and by frequent entrapment of native respiratory glands. Nevertheless, the literature dealing with this issue is surprisingly sparse and no single study has been devoted to this topic. We reviewed 47 surgical lung specimens of non-epithelial neoplasms (38 metastases, mainly from sarcomas and 9 primary lesions) for frequency and pattern of intralesional epithelial entrapment. Respiratory epithelium entrapment was noted in 23/47 (49%) cases (diffuse in 15 and peripheral in 8). Entrapped glands frequently showed prominent regenerative and reactive changes mimicking neoplastic glands. Based on cellularity of the mesenchymal component and the extent, distribution and shape of entrapped respiratory glands, four morphological patterns were recognized: paucicellular sclerosing low-grade neoplasms containing leaflet-like glands indistinguishable from adenofibroma and fibroepithelial hamartomas (n = 11), and biphasic cellular lesions mimicking adenomyoepithelioma (n = 1), biphasic synovial sarcoma (n = 2), and pleuropulmonary blastoma (n = 1). Only a single genuine pulmonary adenofibroma was identified. This study highlights frequent respiratory epithelium entrapment in diverse non-epithelial lung tumors, both primary and metastatic. Recognition of this finding and use of adjunct IHC combined with clinical history should help to avoid misinterpretation as primary pulmonary biphasic neoplasm or as harmless adenofibroma. The vast majority of morphologically defined lung adenofibromas represent adenofibroma-like variants of histogenetically diverse entities so that a diagnosis of adenofibroma should be rendered only very restrictively and then as a diagnosis by exclusion.
CRIS-Team WoS Importer:2020-04-07

Proposal for a Novel Histological Scoring System as a Potential Grading Approach for Muscle-invasive Urothelial Bladder Cancer Correlating with Disease Aggressiveness and Patient Outcomes. - Eckstein, Markus; Matek, Christian; Wagner, Paul; Erber, Ramona; Büttner-Herold, Maike; Wild, Peter J.; Taubert, Helge; Wach, Sven; Sikic, Danijel; Wullich, Bernd; Geppert, Carol-Immanuel; Compérat, Eva M.; et al. (European Urology Oncology, 2024)
BACKGROUND: Grading of muscle-invasive bladder cancer (MIBC) according to the current World Health Organization (WHO) criteria is controversial due to its limited prognostic value. All MIBC cases except a tiny minority are of high grade. OBJECTIVE: To develop a prognostic histological scoring system for MIBC integrating histomorphological phenotype, stromal tumor-infiltrating lymphocytes (sTILs), tumor budding, and growth and spreading patterns. DESIGN, SETTING, AND PARTICIPANTS: Tissue specimens and clinical data of 484 patients receiving cystectomy and lymphadenectomy with curative intent with or without adjuvant chemotherapy. Histomorphological phenotypes, sTILs, tumor budding, and growth and spreading patterns were evaluated and categorized into four grade groups (GGs). GGs were correlated with molecular subtypes, immune infiltration, immune checkpoint expression, extracellular matrix (ECM) remodeling, and epithelial-mesenchymal transition (EMT) activity. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: GGs were associated with overall (OS), disease-specific (DSS), and progression-free (PFS) survival in univariable and multivariable analyses. Association with biological features was analyzed with descriptive statistics. RESULTS AND LIMITATIONS: Integration of two histomorphological tumor groups, three sTILs groups, three tumor budding groups, and four growth/spread patterns yielded four novel GGs that had high significance in the univariable survival analysis (OS, DSS, and PFS). GGs were confirmed as independent prognostic predictors with the greatest effect in the multivariable Cox regression analysis. Correlation with molecular data showed a gradual transition from basal to luminal subtypes from GG1 to GG4; a gradual decrease in survival, immune infiltration, and immune checkpoint activity; and a gradual increase in ECM remodeling and EMT activity. CONCLUSIONS: We propose a novel, prognostically relevant, and biologically based scoring system for MIBC in cystectomies applicable to routine pathological sections. PATIENT SUMMARY: We developed a novel approach to assess the aggressiveness of advanced bladder cancer, which allows improved risk stratification compared with the method currently proposed by the World Health Organization.
EVALuna2:539845

Prostate Adenocarcinoma Grade Group 1: Rationale for Retaining a Cancer Label in the 2022 World Health Organization Classification - Netto, George J.; Amin, Mahul B.; Compérat, Eva M.; Gill, Anthony J.; Hartmann, Arndt; Moch, Holger; Menon, Santosh; Raspollini, Maria R.; Rubin, Mark A.; Srigley, John R.; Hoon Tan, Puay; Tickoo, Satish K.; et al. (European Urology, 2022)
CRIS-Team Scopus Importer:2022-11-25

Protein levels of Piwi-like 1 and-2 protein are prognostic factors for muscle invasive urothelial bladder cancer patients - Eckstein, Markus; Jung, Rudolf; Weigelt, Katrin; Sikic, Danijel; Stöhr, Robert; Geppert, Carol-Immanuel; Agaimy, Abbas; Lieb, Verena; Hartmann, Arndt; Wullich, Bernd; Wach, Sven; Taubert, Helge (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2019-10-22

Pure large nested variant of urothelial carcinoma (Lnuc) is the prototype of an fgfr3 mutated aggressive urothelial carcinoma with luminal-papillary phenotype - Weyerer, Veronika; Eckstein, Markus; Compérat, Eva; Juette, Hendrik; Gaisa, Nadine T.; Allory, Yves; Stöhr, Robert; Wullich, Bernd; Rouprêt, Morgan; Hartmann, Arndt; Bertz, Simone (Cancers, 2020)
Since 2016, large nested urothelial carcinoma (LNUC) has been included within the WHO classification of urothelial tumors. Limited reports with mainly small case series have confirmed the malignant behavior of LNUC despite its bland morphological appearance. We evaluated, for the first time, markers for new immunooncological or targeted therapies including FGFR3 mutational status and PD-L1 status, the frequency of TERT-promoter mutations and the molecular subtype in a cohort of 25 LNUC using SNaPshot analysis and immunohistochemistry. Of the 25 cases, 17 were pure LNUC, with 13 showing an additional exophytic papillary/papillary-like component. Seven mixed LNUCs presented areas of classical nested variant urothelial carcinoma (NVUC) and one showed a component of conventional urothelial carcinoma. Of the 17 evaluable pure LNUCs, 16 were FGFR3-mutated with identical mutations in their concomitant papillary/papillary-like components. An FGFR3 mutation was found in 1/7 evaluable mixed LNUCs combined with NVUC. TERT-promoter mutations were detected in 86.7% pure and 83.3% mixed tumors. Immunohistochemistry revealed a luminal phenotype; PD-L1 was negative in the majority of tumor cells and tumor-associated immune cells. Pure LNUC is a prime example of a luminal, FGFR3-mutated, mostly PD-L1-negative tumor. In contrast, FGFR3 mutations seem to be rare in mixed LNUC, which may indicate a different pathway of tumor development.
CRIS-Team Scopus Importer:2020-04-14
Keywords: FGFR3 mutation; Large nested variant; LNUC; Luminal subtype; Urothelial carcinoma

pVHL/HIF-regulated CD70 expression is associated with infiltration of CD27+ lymphocytes and increased serum levels of soluble CD27 in clear cell renal cell carcinoma - Ruf, Melanie; Mittmann, Christiane; Nowicka, Anna M.; Hartmann, Arndt; Hermanns, Thomas; Poyet, Cedric; Van Den Broek, Maries; Sulser, Tullio; Moch, Holger; Schraml, Peter (Clinical Cancer Research, 2015)
CD70, a member of the TNF ligand superfamily, has been shown frequently overexpressed in clear cell renal cell carcinoma (ccRCC). The mechanisms of CD70's upregulation and its role in ccRCC are unknown.CD70 expression was immunohistochemically analyzed in 667 RCCs and RCC metastases. Von Hippel-Lindau gene (VHL) mutations, expression patterns of VHL protein (pVHL), hypoxia-inducible factor (HIF) ?, and several HIF targets were studied in tissues and cell lines and correlated with CD70 overexpression. Gene promoter analysis was performed to confirm CD70 as HIF target gene. Consecutive tissue sections were immunostained to reveal the relation between CD70-expressing RCCs and tumor-infiltrating lymphocytes positive for the CD70 receptor (CD27). CD70-mediated release of soluble CD27 in RCC was assessed by coculture experiments and sera analysis of patients with RCC.Elevated CD70 expression was seen in 80% of primary tumors and metastases of ccRCC and correlated with dysregulation of the pVHL/HIF pathway. In vitro analyses demonstrated that CD70 upregulation is driven by HIF. Furthermore, CD27(+) lymphocytes preferentially infiltrate CD70-expressing ccRCCs. CD70-dependent release of soluble CD27 in cocultures may explain the high CD27 levels observed in sera of patients with CD70-expressing ccRCC. The combination of lymphocyte infiltration and CD70 expression in RCC was associated with worse patient outcome.Our findings demonstrate that in ccRCC, CD70 expression is regulated by HIF as a consequence of pVHL inactivation. Increased serum levels of CD27 suggest the existence of CD70-expressing ccRCC, thus representing a potential serum marker for patients suffering from this disease.
EVALuna2:6795

RANK and RANKL Expression in Tumors of Patients with Early Breast Cancer - Behrens, Annika; Wurmthaler, Lena; Heindl, Felix; Gaß, Paul; Häberle, Lothar; Volz, Bernhard; Hack, Carolin; Emons, Julius; Erber, Ramona; Hartmann, Arndt; Beckmann, Matthias; Rübner, Matthias; et al. (Geburtshilfe und Frauenheilkunde, 2023)
Introduction The receptor activator of nuclear factor-κB (RANK) pathway was associated with the pathogenesis of breast cancer. Several studies attempted to link the RANK/RANKL pathway to prognosis; however, with inconsistent outcomes. We aimed to further contribute to the knowledge about RANK/RANKL as prognostic factors in breast cancer. Within this study, protein expression of RANK and its ligand, RANKL, in the tumor tissue was analyzed in association with disease-free survival (DFS) and overall survival (OS) in a study cohort of patients with early breast cancer. Patients and Methods 607 samples of female primary and early breast cancer patients from the Bavarian Breast Cancer Cases and Controls Study were analyzed to correlate the RANK and RANKL expression with DFS and OS. Therefore, expression was quantified using immunohistochemical staining of a tissue microarray. H-scores were determined with the cut-off value of 8.5 for RANK and 0 for RANKL expression, respectively. Results RANK and RANKL immunohistochemistry were assessed by H-score. Both biomarkers did not correlate (ρ = -0.04). According to molecular subtypes, triple-negative tumors and HER2-positive tumors showed a higher number of RANK-positive tumors (H-score ≥ 8.5), however, no subtype-specific expression of RANKL could be detected. Higher RANKL expression tended to correlate with a better prognosis. However, RANK and RANKL expression could not be identified as statistically significant prognostic factors within the study cohort. Conclusions Tumor-specific RANK and RANKL expressions are not applicable as prognostic factors for DFS and OS, but might be associated with subtype-specific breast cancer progression.
CRIS-Team Scopus Importer:2023-12-22
Keywords: breast cancer; immunohistochemistry; prognosis; RANK; RANKL

Rapid single-cell physical phenotyping of mechanically dissociated tissue biopsies - Soteriou, Despina; Kubankova, Marketa; Schweitzer, Christine; Lopez Posadas, Rocío; Pradhan, Rashmita; Thoma, Oana-Maria; Györfi, Andrea-Hermina; Matei, Alexandru-Emil; Waldner, Maximilian; Distler, Jörg; Scheuermann, Stefan; Langejuergen, Jens; et al. (Nature Biomedical Engineering, 2023)
A method for the sequential assessment of the physical phenotypes of suspended cells singularized from tissue biopsies by mechanical dissociation allows for rapid diagnoses.
CRIS-Team WoS Importer:2023-05-05

Rare Case Report - Mucoepidermoid Carcinoma (MEC) of the Vulva - Dietl, Anna; Stübs, Frederik; Schulmeyer, Carla; Behrens, Annika; Hartmann, Arndt; Agaimy, Abbas; Beckmann, Matthias; Gaß, Paul (GEBURTSHILFE UND FRAUENHEILKUNDE, 2022)
CRIS-Team WoS Importer:2022-11-04

Recommendations for reporting tumor budding in colorectal cancer based on the International Tumor Budding Consensus Conference (ITBCC) 2016 - Lugli, Alessandro; Kirsch, Richard; Ajioka, Yoichi; Bosman, Fred; Cathomas, Gieri; Dawson, Heather; El Zimaity, Hala; Flejou, Jean-Francois; Hansen, Tine Plato; Hartmann, Arndt; Kakar, Sanjay; Langner, Cord; et al. (Modern Pathology, 2017)
Tumor budding is a well-established independent prognostic factor in colorectal cancer but a standardized method for its assessment has been lacking. The primary aim of the International Tumor Budding Consensus Conference (ITBCC) was to reach agreement on an international, evidence-based standardized scoring system for tumor budding in colorectal cancer. The ITBCC included nine sessions with presentations, a pre-meeting survey and an e-book covering the key publications on tumor budding in colorectal cancer. The 'Grading of Recommendation Assessment, Development and Evaluation' method was used to determine the strength of recommendations and quality of evidence. The following 10 statements achieved consensus: tumor budding is defined as a single tumor cell or a cell cluster consisting of four tumor cells or less (22/22, 100%). Tumor budding is an independent predictor of lymph node metastases in pT1 colorectal cancer (23/23, 100%). Tumor budding is an independent predictor of survival in stage II colorectal cancer (23/23, 100%). Tumor budding should be taken into account along with other clinicopathological features in a multidisciplinary setting (23/23, 100%). Tumor budding is counted on H&E (19/22, 86%). Intratumoral budding exists in colorectal cancer and has been shown to be related to lymph node metastasis (22/22, 100%). Tumor budding is assessed in one hotspot (in a field measuring 0.785 mm2) at the invasive front (22/22, 100%). A three-tier system should be used along with the budding count in order to facilitate risk stratification in colorectal cancer (23/23, 100%). Tumor budding and tumor grade are not the same (23/23, 100%). Tumor budding should be included in guidelines/protocols for colorectal cancer reporting (23/23, 100%). Members of the ITBCC were able to reach strong consensus on a single international, evidence-based method for tumor budding assessment and reporting. It is proposed that this method be incorporated into colorectal cancer guidelines/protocols and staging systems.
EVALuna2:34254

Recording of the regional Origin Areas of Patients from the Molecular Tumor Board to Identify the "white Spots" in the Service Area - A joint Initiative of the Bavarian CCC WERA Alliance - Lueke, F.; Haller, F.; Utpatel, K.; Krebs, M.; Meidenbauer, Norbert; Scheiter, A.; Spörl, Silvia; Heudobler, D.; Keil, F.; Schubart, Christoph; Tögel, Lars; Einhell, S.; et al. (ONCOLOGY RESEARCH AND TREATMENT, 2022)
CRIS-Team WoS Importer:2022-11-18

Recurrent KAT6B/A::KANSL1 Fusions Characterize a Potentially Aggressive Uterine Sarcoma Morphologically Overlapping With Low-grade Endometrial Stromal Sarcoma. - Agaimy, Abbas; Clarke, Blaise A.; Kolin, David L.; Lee, Cheng-Han; Lee, Jen-Chieh; Mccluggage, W. Glenn; Pöschke, Patrik; Stöhr, Robert; Swanson, David; Turashvili, Gulisa; Beckmann, Matthias; Hartmann, Arndt; et al. (American Journal of Surgical Pathology, 2022)
With the widespread application of next-generation sequencing, the genetic landscape of uterine mesenchymal neoplasms has been evolving rapidly to include several recently identified fusion genes. Although chromosomal rearrangements involving the 10q22 and 17q21.31 loci have been reported in occasional uterine leiomyomas decades ago, the corresponding KAT6B::KANSL1 fusion has been only recently identified in 2 uterine tumors diagnosed as leiomyoma and leiomyosarcoma. We herein describe 13 uterine stromal neoplasms carrying a KAT6B::KANSL1 (n=11) and KAT6A::KANSL1 (n=2) fusion. Patient ages ranged from 33 to 81 years (median, 49 y). Tumor size was 2.6 to 23.5 cm (median, 8.2 cm). Nine tumors were myometrium-centered, and 3 had an intracavitary component. Original diagnoses were mostly low-grade endometrial stromal sarcoma (LG-ESS; 10 cases) with atypical features (limited CD10 expression, sex cord-like features, pericytic vasculature, and frequent myxoid changes). Treatment was hysterectomy±bilateral salpingo-oophorectomy (10), myomectomy (1), and curettage (2). Five patients were disease-free at 6 to 34 months, 3 (27%) died of disease at 2 to 47 months, and 3 were alive with disease at 2, 17, and 17 years. Histologically, most tumors showed variable overlap with LG-ESS, but they were generally well-circumscribed lacking the extensive permeative and angioinvasive growth typical of LG-ESS. They were composed of monotonous medium-sized oval and spindle cells arranged into diffuse sheets with prominent spiral-type arterioles and frequent pericytoma-like vascular pattern. Variable myxoid stromal changes were frequent. Mitotic activity ranged from 1 to >20 in 10 HPFs. Immunohistochemistry showed variable expression of CD10 (12/13), estrogen receptor (8/11), progesterone receptor (8/11), smooth muscle actin (9/11), desmin (4/12), h-caldesmon (2/10), calretinin (3/8), inhibin (1/7), WT1 (4/7), cyclin D1 (5/11; diffuse in only 1 case), and pankeratin (5/10). This series characterizes a KAT6B/A::KANSL1 fusion-positive uterine stromal neoplasm within the morphologic spectrum of LG-ESS but with atypical features. The relationship of these neoplasms to genuine LG-ESS remains unclear. This molecular subtype of uterine endometrial stromal sarcoma has the potential for an unfavorable clinical course despite the absence of widely invasive growth; nevertheless, analysis of more cases is necessary to delineate the phenotypic spectrum and biological potential of this tumor.
EVALuna2:504168

Recurrent Mutations within the Amino-Terminal Region of ?-Catenin Are Probable Key Molecular Driver Events in Sinonasal Hemangiopericytoma - Haller, Florian; Bieg, Matthias; Moskalev, Evgeny; Barthelmeß, Sarah; Geddert, Helene; Boltze, Carsten; Diessl, Nicolle; Braumandl, Karin; Brors, Benedikt; Iro, Heinrich; Hartmann, Arndt; Wiemann, Stefan; et al. (American Journal of Pathology, 2015)
Sinonasal hemangiopericytoma (SN-HPC) is an uncommon, site-specific, low-grade mesenchymal neoplasm of probable perivascular myoid cell origin. In contrast to solitary fibrous tumors of soft tissue and sinonasal tract origin, SN-HPCs were recently shown to lack recurrent NAB2-STAT6 fusion variants. Other molecular alterations known to occur in some of soft tissue perivascular myoid cell neoplasms were also absent in SN-HPC; thus, the molecular pathogenesis of SN-HPCs remained unknown. Guided by whole-genome sequencing combined with RNA sequencing of an index case, we analyzed a total of six SN-HPCs for mutations within the amino-terminal region of the gene CTNNB1 (cadherin-associated protein), ? 1, 88 kDa, encoding ?-catenin. All six cases showed missense mutations, with amino acid substitutions clustering at positions 33 to 45, corresponding to the recognition site of the ?-catenin destruction complex. Similar CTNNB1 mutations have been described in a variety of epithelial and mesenchymal neoplasms. These mutations prevent ?-catenin phosphorylation and proteasomal degradation but promote its nuclear accumulation and subsequent increased transcription of Wingless-related integration site target genes. Consistent with these molecular findings, ?-catenin IHC showed consistent diffuse and strong nuclear staining of the tumor cells in all six SN-HPCs. Our results highlight, for the first time, CTNNB1 mutations as the likely initiating molecular events driving SN-HPC tumorigenesis, which places SN-HPC among the growing family of ?-catenin-driven mesenchymal neoplasms.
EVALuna2:6646

Recurrent Somatic PDGFRB Mutations in Sporadic Infantile/Solitary Adult Myofibromas But Not in Angioleiomyomas and Myopericytomas - Agaimy, Abbas; Bieg, Matthias; Michal, Michael; Geddert, Helene; Maerkl, Bruno; Seitz, Jan; Moskalev, Evgeny; Schlesner, Matthias; Metzler, Markus; Hartmann, Arndt; Wiemann, Stefan; Michal, Michal; et al. (American Journal of Surgical Pathology, 2017)
Infantile myofibroma (MF) is an uncommon benign myofibroblastic tumor of infancy and childhood. Solitary adult MF shares similar features with infantile MF. The lesions occur in 3 clinicopathologic settings: solitary, multicentric, and generalized and can be either sporadic or familial. Traditionally, infantile MF has been included in the spectrum of infantile hemangiopericytoma. The recent World Health Organization classification listed MF, angioleiomyoma, and myopericytoma under the general heading of perivascular tumors in the sense of a morphologic spectrum of perivascular myoid cell neoplasms. Although activating germline PDGFRB mutations have recently been linked to familial infantile MF, the molecular pathogenesis of sporadic infantile and adult solitary MF remained unclear. In this study, we analyzed 25 solitary MFs without evidence of familial disease (9 infantile and 16 adult MFs) to address the question whether somatic PDGFRB mutations might be responsible for the sporadic form of the disease. Given the presumed histogenetic link of MF to myopericytoma and angioleiomyoma, we additionally analyzed a control group of 6 myopericytomas and 9 angioleiomyomas for PDGFRB mutations. We detected PDGFRB mutations in 6/8 (75%) analyzable infantile and in 11/16 (69%) adult MFs but in none of the angioleiomyomas or myopericytomas. In 2 infantile MFs, additional sequencing of the germline confirmed the somatic nature of PDGFRB mutations. To our knowledge, this is the first study reporting apparently somatic recurrent PDGFRB mutations as molecular driver events in the majority of sporadic infantile and adult solitary MFs. Our results suggest molecular distinctness of MF as compared with angioleiomyoma/myopericytoma. Investigation of more cases including those with atypical and worrisome features, as well as other mimickers in the heterogenous morphologic spectrum of MF, is mandatory for validating the potential diagnostic value of PDGFRB mutation testing as a possible surrogate in difficult-to-classify lesions.
EVALuna2:6839

Reduced expression of miRNA-27a modulates cisplatin resistance in bladder cancer by targeting the cystine/glutamate exchanger SLC7A11 - Drayton, Ross M.; Dudziec, Ewa; Peter, Stefan; Bertz, Simone; Hartmann, Arndt; Bryant, Helen E.; Catto, James W. F. (Clinical Cancer Research, 2014)
Resistance to cisplatin-based chemotherapy is a major obstacle to bladder cancer treatment. We aimed to identify microRNAs (miRNA) that are dysregulated in cisplatin-resistant disease, ascertain how these contribute to a drug-resistant phenotype, and how this resistance might be overcome.miRNA expression in paired cisplatin-resistant and -sensitive cell lines was measured. Dysregulated miRNAs were further studied for their ability to mediate resistance. The nature of the cisplatin-resistant phenotype was established by measurement of cisplatin/DNA adducts and intracellular glutathione (GSH). Candidate miRNAs were examined for their ability to (i) mediate resistance and (ii) alter the expression of a candidate target protein (SLC7A11); direct regulation of SLC7A11 was confirmed using a luciferase assay. SLC7A11 protein and mRNA, and miRNA-27a were quantified in patient tumor material.A panel of miRNAs were found to be dysregulated in cisplatin-resistant cells. miRNA-27a was found to target the cystine/glutamate exchanger SLC7A11 and to contribute to cisplatin resistance through modulation of GSH biosynthesis. In patients, SLC7A11 expression was inversely related to miRNA-27a expression, and those tumors with high mRNA expression or high membrane staining for SLC7A11 experienced poorer clinical outcomes. Resistant cell lines were resensitized by restoring miRNA-27a expression or reducing SLC7A11 activity with siRNA or with sulfasalazine.Our findings indicate that miRNA-27a negatively regulates SLC7A11 in cisplatin-resistant bladder cancer, and shows promise as a marker for patients likely to benefit from cisplatin-based chemotherapy. SLC7A11 inhibition with sulfasalazine may be a promising therapeutic approach to the treatment of cisplatin-resistant disease.
EVALuna2:6614

Reduced Recurrence Rates Are Associated with Photodynamic Diagnostics Compared to White Light after Extended Transurethral Resection of Bladder Tumors - Marquardt, Alexander; Richterstetter, Mario; Taubert, Helge; Hartmann, Arndt; Wullich, Bernd; Lieb, Verena; Bellut, Laura; Wach, Sven; Apel, Hendrik (Life, 2022)
One pillar in treating non-muscle-invasive bladder cancer (NMIBC) is the complete and high-quality transurethral resection of the primary tumor (TURBT). However, even after a high-quality primary resection, the residual tumor risk is considerable, thus requiring a re-TURBT. Resections performed with the aid of a photodynamic diagnostics report improved recurrence-free survival rates and increased detection rates of carcinoma in situ (CIS). This monocentric retrospective study reports on patients treated with an extended TURBT procedure using conventional white-light cystoscopy or photodynamic diagnostics (PDD). Only patients undergoing a TURBT resection for their primary tumor were included in the statistical analysis. Recurrence-free survival and overall survival were the clinical endpoints. Mann-Whitney U tests and chi-squared tests were used for descriptive intergroup comparisons. The associations with overall survival and recurrence-free survival were determined by univariate and multivariate analyses. The test results were considered significant when p was < 0.05. In comparison to conventional white-light cystoscopy, PDD increased the detection rates of CIS (p = 0.004) and tumor multifocality (p = 0.005) and led to reduced residual tumor incidence at the primary resection site (p < 0.001). Likewise, tumor recurrence rates were reduced in the PDD cohort (p < 0.001). Patient age and the presence of residual tumor at the primary resection site were identified as independent predictors of overall survival. For recurrence-free survival, only the PDD resection method was an independent predictor (HR = 0.43; p < 0.001). In summary, we demonstrated that the utilization of PDD techniques was associated with improved detection rates of CIS and multifocal tumors and with reduced recurrence rates. The extended resection protocol allowed us to determine that PDD resections lead to a reduced residual tumor rate at the initial resection site. This residual tumor state at the resection site, determined by extended TURBT, became an independent predictor of long-term survival. On the other hand, the PDD technique was confirmed as the only independent predictor of recurrence-free survival.
CRIS-Team WoS Importer:2022-06-10

Regulation and function of the atypical cadherin FAT1 in hepatocellular carcinoma - Valletta, Daniela; Czech, Barbara; Spruss, Thilo; Ikenberg, Kristian; Wild, Peter; Hartmann, Arndt; Weiss, Thomas S.; Oefner, Peter J.; Mueller, Martina; Hellerbrand, Claus; Bosserhoff, Anja Katrin (Carcinogenesis, 2014)
In human cancers, giant cadherin FAT1 may function both, as an oncogene and a tumor suppressor. Here, we investigated the expression and function of FAT1 in hepatocellular carcinoma (HCC). FAT1 expression was increased in human HCC cell lines and tissues compared with primary human hepatocytes and non-tumorous liver tissue as assessed by quantitative PCR and western blot analysis. Combined immunohistochemical and tissue microarray analysis showed a significant correlation of FAT1 expression with tumor stage and proliferation. Suppression of FAT1 expression by short hairpin RNA impaired proliferation and migration as well as apoptosis resistance of HCC cells in vitro. In nude mice, tumors formed by FAT1-suppressed HCC cells showed a delayed onset and more apoptosis compared with tumors of control cells. Both hepatocyte growth factor and hypoxia-mediated hypoxia-inducible factor 1 alpha activation were identified as strong inducers of FAT1 in HCC. Moreover, demethylating agents induced FAT1 expression in HCC cells. Hypoxia lead to reduced levels of the methyl group donor S-adenosyl-L-methionine (SAM) and hypoxia-induced FAT1 expression was inhibited by SAM supplementation in HCC cells. Together, these findings indicate that FAT1 expression in HCC is regulated via promotor methylation. FAT1 appears as relevant mediator of hypoxia and growth receptor signaling to critical tumorigenic pathways in HCC. This knowledge may facilitate the rational design of novel therapeutics against this highly aggressive malignancy.
EVALuna2:6668

Regulatory T cells and cytotoxic T cells close to the epithelial–stromal interface are associated with a favorable prognosis - Rudolf, Julian; Büttner-Herold, Maike; Erlenbach-Wuensch, Katharina; Posselt, Rebecca; Jeßberger, Jonas; Haderlein, Marlen; Hecht, Markus; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (OncoImmunology, 2020)
Cytotoxic T cells and regulatory T cells play a crucial role in the outcome of cancer patients. Besides the density of these cells, it was shown recently that the spatial distribution is equally important. Here, we specifically analyzed the spatial distribution of these T cell subtypes at the epithelial–stromal interface in a rectal cancer cohort and its relevance for prognosis. We studied a cohort of 191 patients with advanced rectal cancer treated by radiochemotherapy (RCT). Tissue microarrays were immunohistochemical double-stained by FoxP3+ and CD+. Cell densities were analyzed in the stromal and epithelial compartment. Additionally, an image analysis software calculated the distances of lymphocytes to the epithelial–stromal interface (ESI). CD8+ and FoxP3+ cell counts decreased clearly after RCT with the decrease of FoxP3+ being more pronounced than of CD8+ cells. In the invasive front, short distances of the ESI to CD8+ and to FoxP3+ cells were associated with improved overall survival. Cell counts in the stromal compartment had no influence on prognosis. No correlation between stromal and epithelial lymphocyte densities was observed. The distance of epithelial–stromal interface to CD8+ and FoxP3+ cells was more accurate in predicting prognosis in the stromal compartment of rectal cancer patients than mere cell counts and could thereby be means of better stratifying patients for therapy. This observation will have to be validated in future prospective studies with regard to other tumor entities and its implications for the responsiveness of tumors to new therapeutic modalities.
CRIS-Team Scopus Importer:2020-04-28
Keywords: epithelial–stromal interface; rectal cancer; regulatory T cells; spatial distribution; ﻿cytotoxic T cells

Renal Cell Carcinoma with "Gonadal Sex-cord Stromal tumor-like" Features: Analysis of 5 Cases of Novel Renal Entity - Wang, Gang; Amin, Mahul; Grossmann, Petr; Hayes, Malcolm; Hartmann, Arndt; Agaimy, Abbas; Lopez, Jose; Hes, Ondrej (LABORATORY INVESTIGATION, 2020)
CRIS-Team WoS Importer:2020-03-24

Renal cell tumor with sex-cord/gonadoblastoma-like features: analysis of 6 cases - Wang, Gang; Amin, Mahul B.; Grossmann, Petr; Ptakova, Nikola; Hayes, Malcolm; Hartmann, Arndt; Agaimy, Abbas; Lopez, Jose; Michal, Michal; Hes, Ondrej (Virchows Archiv, 2021)
Renal tumors are one of the most diverse groups of tumors in pathology. Many emerging and important entities have been described recently. Here, we describe a series of renal tumors occurring in adult patients, with distinct histologic features, and with a striking resemblance to gonadal sex cord-stromal tumors. Patients were three males and three females aged 39–82 years; tumor size ranged from 0.9 to 3.6 cm. Five tumors were organ-confined, while one case had a focal perinephric invasion. No aggressive behavior was noted. Microscopically, all the tumors were composed of loose or compact tubular structures with elongated or angulated shapes. The tumor cells were cylindrical or cuboidal, with pale eosinophilic cytoplasm, irregular nuclear membranes, and ISUP/WHO grade 2–3 nuclei. The stroma showed focal or prominent collagen deposition with prominent basement membrane–like material. In all cases, the tumor cells were positive for PAX8, CD10, and vimentin and retained positivity for FH and SDHB. Cathepsin K and AMACR were variably positive. Tumors were negative for HMB45, Melan A, TFE3, SF1, inhibin, calretinin, ER, PR, CD117, OCT3/4, SALL4, ALK, and WT1. Molecular studies showed no abnormalities in TFEB, TFE3, or FH genes. In 3/4 tested cases, mutation of the NF2 gene was present. In all the tested male cases, loss of the Y chromosome was found. In the relatively short follow-up, these tumors appear to have indolent behavior. This study expands the clinicopathologic diversity of renal cell tumors by describing a series of potentially novel tumors morphologically resembling gonadal sex-stromal tumors, with negativity for sex cord-stromal markers. Potential relationship to recently described biphasic hyalinizing psammomatous renal cell carcinoma is discussed.
CRIS-Team Scopus Importer:2021-11-26
Keywords: Biphasic hyalinizing psammomatous renal cell carcinoma; Gonadoblastoma-like; Kidney; NF2 mutation; Renal cell carcinoma; Sex cord-stromal tumor-like

Reply: Intra-patient heterogeneity of BRAF mutation status: fact or fiction? - Heinzerling, Lucie; Schuler, Gerold; Hartmann, Arndt; Schneider-Stock, Regine (British Journal of Cancer, 2014)
EVALuna2:6657

Reply to Jérôme Verine, Christophe Leboeuf and Philippe Ratajczak's letter to the editor re: Jimsgene Sanjmyatav, Sven Hauke, Mieczyslaw Gajda, et al. Establishment of a multicolour fluorescence in situ hybridisation-based assay for subtyping of renal cel - Sanjmyatav, Jimsgene; Hartmann, Arndt; Moch, Holger; Hauke, Sven; Gajda, Mieczyslaw; Meyer, Britta; Pryalukhin, Alexey; Grimm, Marc-Oliver; Junker, Kerstin (European Urology, 2014)
EVALuna2:6671

Reply To Kenneth B. Yatai, Mark J. Dunning, Dennis Wang. Consensus Genomic Subtypes of Muscle-invasive Bladder Cancer: A Step in the Right Direction but Still a Long Way To Go. Eur Urol. In press - Kamoun, Aurélie; de Reyniès, Aurélien; Allory, Yves; Sjödahl, Gottfrid; Robertson, A. Gordon; Seiler, Roland; Hoadley, Katherine A.; Groeneveld, Clarice S.; Al-Ahmadie, Hikmat; Choi, Woonyoung; Castro, Mauro A.A.; Fontugne, Jacqueline; et al. (European Urology, 2020)
CRIS-Team Scopus Importer:2020-02-14

Reply to Yongbao Wei, Haijian Huang, and Liefu Ye's Letter to the Editor re: George J. Netto, Mahul B. Amin, Daniel M. Berney, et al. The 2022 World Health Organization Classification of Tumors of the Urinary System and Male Genital Organs—Part B: Prostate and Urinary Tract Tumors. Eur Urol. 2022;82:469–82. - Rubin, Mark A.; Amin, Mahul B.; Compérat, Eva; Gill, Anthony; Hartmann, Arndt; Menon, Santosh; Raspollini, Maria; Srigley, John; Tan, Puay Hoon; Ticktoo, Satish; Tsuzuki, Toyonori; Turajlic, Samra; et al. (European Urology, 2023)
CRIS-Team Scopus Importer:2022-12-23

Report from the International Society of Urological Pathology (ISUP) Consultation Conference on Molecular Pathology of Urogenital Cancers. II. Molecular Pathology of Bladder Cancer: Progress and Challenges - Warrick, Joshua I.; Knowles, Margaret A.; Yves, Allory; Van Der Kwast, Theo; Grignon, David J.; Kristiansen, Glen; Egevad, Lars; Hartmann, Arndt; Cheng, Liang (American Journal of Surgical Pathology, 2020)
During the 2019 International Society of Urological Pathology Consultation Conference on Molecular Pathology of Urogenital Cancer, the Working Group on Bladder Cancer presented the current status and made recommendations on the diagnostic use of molecular pathology, incorporating a premeeting survey. Bladder cancers are biologically diverse and can be separated into "molecular subtypes," based on expression profiling. These subtypes associate with clinical behavior, histology, and molecular alterations, though their clinical utility has not been demonstrated at present and use in bladder cancer is not recommended. Mutations in the TERT promoter are present in the majority of bladder cancers, including the noninvasive stage of tumor evolution, but not in reactive conditions. Mutational analysis of the TERT promoter thus distinguishes histologically deceptive cancers from their benign mimics in some cases. A minority of pathologists employ this test. FGFR3 mutations are common in bladder cancer, and metastatic urothelial carcinoma (UC) with such mutations frequently responds to erdafitinib, an FGFR inhibitor. Testing for FGFR3 alterations is required before using this drug. Metastatic UC responds to immune-oncology (IO) agents in 20% of cases. These are approved as first and second-line treatments in metastatic UC. Several biological parameters associate with response to IO agents, including tumor mutational burden, molecular subtype, and infiltration by programmed death-ligand 1-positive lymphocytes, detected by immunohistochemistry. Programmed death-ligand 1 immunohistochemistry is mandatory before administering IO agents in the first-line setting. In conclusion, much has been learned about the biology of bladder cancer, and this understanding has improved the care of patients with the disease.
CRIS-Team Scopus Importer:2020-03-10
Keywords: bladder cancer; FGFR3 mutation; immune-oncology; molecular subtypes; PD-L1 immunohistochemistry; TERT promoter

Report From the International Society of Urological Pathology (ISUP) Consultation Conference On Molecular Pathology Of Urogenital Cancers. II. Molecular Pathology of Bladder Cancer: Progress and Challenges. - Warrick, Joshua; Knowles, Margaret A.; Yves, Allory; Van Der Kwast, Theo; Grignon, David J.; Kristiansen, Glen; Egevad, Lars; Hartmann, Arndt; Cheng, Liang (American Journal of Surgical Pathology, 2020)
During the 2019 International Society of Urological Pathology Consultation Conference on Molecular Pathology of Urogenital Cancer, the Working Group on Bladder Cancer presented the current status and made recommendations on the diagnostic use of molecular pathology, incorporating a premeeting survey. Bladder cancers are biologically diverse and can be separated into "molecular subtypes," based on expression profiling. These subtypes associate with clinical behavior, histology, and molecular alterations, though their clinical utility has not been demonstrated at present and use in bladder cancer is not recommended. Mutations in the TERT promoter are present in the majority of bladder cancers, including the noninvasive stage of tumor evolution, but not in reactive conditions. Mutational analysis of the TERT promoter thus distinguishes histologically deceptive cancers from their benign mimics in some cases. A minority of pathologists employ this test. FGFR3 mutations are common in bladder cancer, and metastatic urothelial carcinoma (UC) with such mutations frequently responds to erdafitinib, an FGFR inhibitor. Testing for FGFR3 alterations is required before using this drug. Metastatic UC responds to immune-oncology (IO) agents in 20% of cases. These are approved as first and second-line treatments in metastatic UC. Several biological parameters associate with response to IO agents, including tumor mutational burden, molecular subtype, and infiltration by programmed death-ligand 1-positive lymphocytes, detected by immunohistochemistry. Programmed death-ligand 1 immunohistochemistry is mandatory before administering IO agents in the first-line setting. In conclusion, much has been learned about the biology of bladder cancer, and this understanding has improved the care of patients with the disease.
EVALuna2:421655

Report of the meeting of the working group on uropathology 2014 - Hartmann, Arndt; Knüchel-Clarke, R. (Pathologe, 2014)
EVALuna2:6698

Report of the working group on uropathology of the German Society of Pathology 2015 - Knuechel-Clarke, R.; Hartmann, Arndt (Pathologe, 2015)
EVALuna2:6788

Reproducibility of histopathologic tumor grading in penile cancer–results of a European project - Kakies, Ch.; Lopez-Beltran, A.; Comperat, E.; Erbersdobler, A.; Grobholz, R.; Hakenberg, O. W.; Hartmann, Arndt; Horn, L. -C.; Hoehn, A. K.; Koellermann, J.; Kristiansen, G.; Montironi, R.; et al. (Virchows Archiv, 2014)
Since reliable molecular prognostic parameters for inguinal lymph metastases in penile cancer are not available, tumor grading is often used as a surrogate prognostic tool for the indication of inguinal lymphadenctomy and has been integrated into the current TNM classification for penile cancer. The reliability of tumor grading is under discussion. We examined interobserver grading variability in 90 primary penile carcinomas, assessed by 12 different uropathologists from five European countries. Tumor grading, following the CAP scheme, was compared, and interobserver variability was calculated using kappa statistics. The interobserver variability was high as reflected by an overall low kappa coefficient (mean k = 0.34) and reached a moderate level only in 26.4 % of the cases (range 0.02-0.67). The percentage of G1 tumors assigned ranged from 8.6 to 52.5 %, G2 tumors from 27.1 to 72.6 % and G3 tumors from 11.7 to 48.7 %. Only some observers assigned G4 with a range of 0.6-21.9 %. Subdivision into low and high grade according to UICC and EAU classifications differed significantly (P < 0.001). Low reproducibility of grading in penile carcinomas with the favored method does not allow a reliable prognostication of tumor aggressiveness. Inclusion of histological grading into the TNM classification currently seems not to be a benefit.
EVALuna2:6604

Reproducibility of mRNA-Based Testing of ESR1, PGR, ERBB2, and MKI67 Expression in Invasive Breast Cancer-A Europe-Wide External Quality Assessment - Erber, Ramona; Hartmann, Arndt; Fasching, Peter; Rübner, Matthias; Stöhr, Robert; Beckmann, Matthias; Zentgraf, Miriam; Popp, Verena; Weidler, Jodi; Simon, Iris; Becker, Steffi; Hübner, Hanna; et al. (Cancers, 2021)
Simple Summary Four biomarkers [estrogen receptor (ER), progesterone receptor (PgR), Ki-67, and HER2], are used to stratify breast cancer (BC) into subtypes predictive of therapy response. In a Europe-wide external quality assessment, we compared performance of an mRNA-based method [Xpert(R) Breast Cancer STRAT4 (CE-IVD)] for determining ESR1, PGR, ERBB2, and MKI67 expression against the gold standard [immunohistochemistry (IHC)/HER2 in situ hybridization (ISH)]. The coordinating center (CC) and five European laboratories tested ten breast cancer samples. STRAT4 binary (positive or negative) results of each marker were compared with the gold standard. ESR1 and ERBB2 mRNA results were concordant with IHC/ISH in all single analyses. In contrast, PGR and MKI67 results were discordant in a few cases, which had STRAT4 expression values close to assay cut-offs and immunohistochemically presented heterogeneous low positive PgR and heterogeneous Ki-67. STRAT4 assay may be a reproducible method. However, cases with expression values close to cut-offs should be carefully reviewed. Estrogen receptor (ER), progesterone receptor (PgR), Ki-67, and HER2 immunohistochemistry (IHC) together with HER2 in situ hybridization (ISH) are utilized to classify invasive breast cancer (IBC) into predictive molecular subtypes. As IHC evaluation may be hampered by analytical errors, gene expression assays could offer a reliable alternative. In this first Europe-wide external quality assessment (EQA) study, we investigated performance of mRNA-based Xpert(R) Breast Cancer STRAT4 (CE-IVD) in five European laboratories. The cohort comprised ten pre-therapy IBC core biopsies diagnosed in the coordinating center (CC). STRAT4 binary (positive or negative) mRNA results of each marker (ESR1, PGR, ERBB2, MKI67) were compared with the gold standard IHC/ISH performed by the CC. Sensitivity, specificity, and accuracy of ESR1 and ERBB2 mRNA were 100% for all samples. In contrast, PGR expression was falsely negative for one case by two sites and MKI67 falsely negative for two cases (respectively by four and one sites). These cases had STRAT4 expression values close to assay cut-offs and immunohistochemically presented heterogeneous low positive PgR and heterogeneous Ki-67. Our EQA shows that STRAT4 mRNA assay may be a reproducible method to evaluate ER, PgR, HER2, and Ki-67 status. However, cases with expression values close to assay cut-offs should be carefully reviewed.
CRIS-Team WoS Importer:2021-10-08

Restoration of an academic historical gross pathology collection-refreshed impact on current medical teaching? - Eichhorn, Philip; Andraschke, Udo; Dross, Fritz; Geppert, Carol-Immanuel; Hartmann, Arndt; Rau, Tilman (Virchows Archiv, 2018)
The declaration of Leiden pronounces the demand to conserve pathological-anatomical collections as cultural heritage. Likewise, the Institute of Pathology of the Friedrich-Alexander-University Erlangen-Nuremberg owns macroscopic pathological-anatomical specimens reaching back over 150 years. The purpose of this work is to examine the impact, meaning, and perception of such historical preparations during the current medical curriculum. Additionally, the experiences from the renovation process can be used as a template for other institutes. All preparations were documented, photographed, and catalogued in an electronic database. During a restoration period, a series of didactically suitable specimens were professionally restored. Hereby, the help of a special course of interested students was admitted. In a second step, the specimens were integrated into the regular teaching of students in macroscopic pathology. An evaluation was carried out on two student cohorts with and without historical specimens by means of a questionnaire with 23 items and two free text fields. In total, 1261 specimens were registered covering diseases from almost the complete human body with a strong representation of the cardiovascular, urinary, gastrointestinal, and central nervous systems. Hereby, exceptional rare and untreated cases with medical relevance could be found and stepwise implemented into the curriculum. The student evaluation positively addressed that the courses became livelier and interactive. Furthermore, a more comprehensive overview and a better understanding of the macroscopic pathology were appreciated. However, more self-study time with the specimen was demanded. The authenticity of historical specimens contrasts with the tendency to carry out virtual "online" didactic methods. The stereoscopic view on often untreated and, therefore, unbiased cases enhances a skill-oriented deeper understanding of diseases. In conclusion, historical specimens regain interest and even didactic value, especially in an era of declining autopsy rates.
EVALuna2:34603

Results of the first prototypical Ring Trial of QuIP for PD-L1 Expression in Urothelial Carcinomas - Sommer, Ulrich; Baretton, Gustavo; Hartmann, Arndt; Eckstein, Markus; Schwamborn, Kristina; Weichert, Wilko; Kristiansen, Glen; Wild, Peter; Knuechel-Clarke, Ruth; Schirmacher, Peter; Dietel, Manfred; Joehrens, Korinna (Pathologe, 2020)
CRIS-Team WoS Importer:2020-07-17

Re: Svetlana Avulova, John C. Cheville, Christine M. Lohse, et al. Grading Chromophobe Renal Cell Carcinoma: Evidence for a Four-tiered Classification Incorporating Coagulative Tumor Necrosis. Eur Urol 2021;79:225-31: Two-, Three-, or Four-tiered Grading of Chromophobe Renal Cancer: That's the Question! - Ohashi, Riuko; Hartmann, Arndt; Martignoni, Guido; Moch, Holger (European Urology, 2021)
CRIS-Team Scopus Importer:2021-07-02

Retrospective histological evaluation of orchiectomy specimens following testicular torsion reveals a 10% incidence of reversible injury. Is it time for a change of strategy? - Marcou, Marios; Hartmann, Arndt; Wullich, Bernd; Apel, Hendrik; Hirsch-Koch, Karin (Andrology, 2022)
BackgroundAccording to standard medical practice, immediate orchiectomy is advised in the case of a non-viable testis following testicular torsion. Because of the lack of objective criteria in the evaluation of testicular viability, the fate of the testis solely depends on the discretion and experience of the surgeon. ObjectiveIn this study, we retrospectively reassess the management of patients with testicular torsion in our center, and we ask the question, from a retrospective point of view, of whether the decision to perform orchiectomy has always been correct. Materials and methodsWe retrospectively reviewed all cases of patients with testicular torsion who underwent surgery in our center between 2001 and 2021. All orchiectomy specimens were reevaluated and graded by an experienced pathologist using the Mikuz grading system. ResultsImmediate orchiectomy was performed in 48 of the 136 patients (35%). Five (10.4%) of the 48 orchiectomy specimens were categorized as "grade 1," and 17 (35.4%) were categorized as "grade 2." The time between the onset of symptoms and surgical exploration exceeded 12 h in three of the five patients with a "grade 1" testicular injury, and in one case, it even exceeded 24 h. Discussion"Grade 1" testicular injury is potentially reversible, whereas the fate of a testis with a "grade 2" testicular injury remains unknown. Whether and to what extent partial testicular tissue salvage in a "grade 2" injury is still possible remain unclear. ConclusionsOur results indicate that at least 10% of the testicles removed in our center could, from a retrospective point of view, have been salvaged. Our study further demonstrated that the duration of symptoms is not an absolute indicator of testicular damage and that the decision of whether orchiectomy should be performed, based simply on the subjective macroscopic image of the affected testis, is not always correct.
CRIS-Team WoS Importer:2023-01-20

Rhabdoid and Undifferentiated Phenotype in Renal Cell Carcinoma: Analysis of 32 Cases Indicating a Distinctive Common Pathway of Dedifferentiation Frequently Associated With SWI/SNF Complex Deficiency - Agaimy, Abbas; Cheng, Liang; Egevad, Lars; Feyerabend, Bernd; Hes, Ondrej; Keck, Bastian; Pizzolitto, Stefano; Sioletic, Stefano; Wullich, Bernd; Hartmann, Arndt (American Journal of Surgical Pathology, 2017)
Undifferentiated (anaplastic) and rhabdoid cell features are increasingly recognized as adverse prognostic findings in renal cell carcinoma (RCC), but their molecular pathogenesis has not been studied sufficiently. Recent studies identified alterations in the Switch Sucrose nonfermentable (SWI/SNF) chromatin remodeling complex as molecular mechanisms underlying dedifferentiation and rhabdoid features in carcinomas of different organs. We herein have analyzed 32 undifferentiated RCCs having in common an undifferentiated (anaplastic) phenotype, prominent rhabdoid features, or both, irrespective of the presence or absence of conventional RCC component. Cases were stained with 6 SWI/SNF pathway members (SMARCB1, SMARCA2, SMARCA4, ARID1A, SMARCC1, and SMARCC2) in addition to conventional RCC markers. Patients were 20 males and 12 females aged 32 to 85 years (mean, 59). A total of 22/27 patients with known stage presented with >=pT3. A differentiated component varying from microscopic to major component was detected in 20/32 cases (16 clear cell and 2 cases each chromophobe and papillary RCC). The undifferentiated component varied from rhabdoid dyscohesive cells to large epithelioid to small monotonous anaplastic cells. Variable loss of at least 1 SWI/SNF complex subunit was noted in the undifferentiated/rhabdoid component of 21/32 cases (65%) compared with intact or reduced expression in the differentiated component. A total of 15/17 patients (88%) with follow-up died of metastatic disease (mostly within 1 y). Only 2 patients were disease free at last follow-up (1 and 6 y). No difference in survival, age distribution, or sex was observed between the SWI/SNF-deficient and the SWI/SNF-intact group. This is the first study exploring the role of SWI/SNF deficiency as a potential mechanism underlying undifferentiated and rhabdoid phenotype in RCC. Our results highlight the association between the aggressive rhabdoid phenotype and the SWI/SNF complex deficiency, consistent with studies on similar neoplasms in other organs. Thorough sampling of such tumors that are usually huge and locally advanced is necessary for recognizing the clone of origin and hence for proper subtyping and also for differentiating them from undifferentiated urothelial carcinoma.
EVALuna2:6840

Risk and timing of biochemical recurrence in pT3aN0/Nx prostate cancer with positive surgical margin - A multicenter study - Karl, Alexander; Buchner, Alexander; Tympner, Christiane; Kirchner, Thomas; Ganswindt, Ute; Belka, Claus; Ganzer, Roman; Wieland, Wolf; Eder, Fabian; Hofstaedter, Ferdinand; Schilling, David; Sievert, Karl-Dietrich; et al. (Radiotherapy and Oncology, 2015)
Positive surgical margins (PSM) after radical prostatectomy have been shown to be associated with impaired outcome. In pT3pN0 patients with PSM either immediate radiotherapy or clinical and biological monitoring followed by salvage radiotherapy is recommended by the latest guidelines of the European Association of Urology.A retrospective, multicenter study of eight urological centers was conducted on 536 prostatectomy patients with pT3aN0/NxR1 tumors and no neoadjuvant/adjuvant therapy. A pathological re-review of all prostate specimens was performed. Association of clinical and pathological features with biochemical recurrence (BCR) was analyzed using univariate and multivariate analysis.With 48months median follow-up, BCR occurred in 39.7%. Preoperative PSA value, performance of pelvic lymph node dissection and Gleason score were significantly associated with BCR. In multivariate analysis, Gleason score was the only independent prognostic factor (p<0.001) for BCR. Five-year BCR-free survival rates were 74%, 70%, 38%, and 51% with Gleason score 6, 3+4=7a, 4+3=7b, and 8-10, respectively.In pT3aN0/NxR1 patients with no adjuvant/neoadjuvant treatment, Gleason Score permits independent prediction of the risk for BCR. These findings could help to estimate and discuss the individual risk for BCR with our patients on an individual basis.
EVALuna2:6761

Risk Assessment after Neoadjuvant Chemotherapy in Luminal Breast Cancer Using a Clinicomolecular Predictor - Loibl, Sibylle; Weber, Karsten; Huober, Jens; Krappmann, Kristin; Marme, Frederik; Schem, Christian; Engels, Knut; Pfitzner, Berit Maria; Kuemmel, Sherko; Furlanetto, Jenny; Hartmann, Arndt; Darb-Esfahani, Silvia; et al. (Clinical Cancer Research, 2018)
Purpose: This study aimed to evaluate a modified EPclin test (mEPclin), a combination of EndoPredict (EP) score, post-neoadjuvant pathologic tumor size and nodal status, for predicting the risk of distance recurrence after neoadjuvant chemotherapy (NACT) in patients with residual estrogen receptor (ER)-positive/HER2-negative breast cancer. We also compared the prognostic power of the mEPclin with that of the CPS-EG score.Experimental Design: A total of 428 formalin-fixed, paraffin-embedded tumor samples from GeparTrio and GeparQuattro studies were evaluated for mRNA expression of eight cancer-related and three reference genes. The mEPclin score was computed using a modified algorithm and predefined cut-off values were used to classify each patient at low or high risk. Primary endpoint was disease-free survival (DFS).Results: A higher continuous mEPclin score was significantly associated with increased risk of relapse [HR, 2.16; 95% confidence interval (CI), 1.86-2.51; P < 0.001] and death (HR, 2.28; 95% CI, 1.90-2.75; P < 0.001). Similarly, patients classified at high risk by dichotomous mEPclin showed significantly poorer DFS and overall survival compared with those at low risk. In contrast with CPS-EG, the mEPclin remained significantly prognostic for DFS in multivariate analysis (HR, 2.13; 95% CI, 1.73-2.63; P < 0.001). Combining CPS-EG and other clinicopathological variables with mEPclin yielded a significant improvement of the prognostic power for DFS versus without mEPclin (c-indices: 0.748 vs. 0.660; P < 0.001).Conclusions: The mEPclin score independently predicted the risk of distance recurrence and provided additional prognostic information to the CPS-EG score to assess more accurately the prognosis after NACT in the luminal non-pCR patient population. Therefore, this approach can be used to select patients for additional post-neoadjuvant therapies. Clin Cancer Res; 24(14); 3358-65. ©2018 AACR.
EVALuna2:34607

Risk factors associated with positive surgical margins’ location at radical cystectomy and their impact on bladder cancer survival - Claps, Francesco; Van De Kamp, Maaike W.; Mayr, Roman; Bostrom, Peter J.; Boormans, Joost L.; Eckstein, Markus; Mertens, Laura S.; Boeve, Egbert R.; Neuzillet, Yann; Burger, Maximilian; Pouessel, Damien; Trombetta, Carlo; et al. (World Journal of Urology, 2021)
Purpose: To evaluate the risk factors associated with positive surgical margins' (PSMs) location and their impact on disease-specific survival (DSS) in patients with bladder cancer (BCa) undergoing radical cystectomy (RC). Methods: We analyzed a large multi-institutional cohort of patients treated with upfront RC for non-metastatic (cT1-4aN0M0) BCa. Multivariable binomial logistic regression analyses were used to assess the risk of PSMs at RC for each location after adjusting for clinicopathological covariates. The Kaplan–Meier method was used to estimate DSS stratified by margins’ status and location. Log-rank statistics and Cox’ regression models were used to determine significance. Results: A total of 1058 patients were included and 108 (10.2%) patients had PSMs. PSMs were located at soft-tissue, ureter(s), and urethra in 57 (5.4%), 30 (2.8%) and 21 (2.0%) patients, respectively. At multivariable analysis, soft-tissue PSMs were independently associated with pathological stage T4 (pT4) (Odds ratio (OR) 6.20, p < 0.001) and lymph-node metastases (OR 1.86, p = 0.04). Concomitant carcinoma-in-situ (CIS) was an independent risk factor for ureteric PSMs (OR 6.31, p = 0.003). Finally, urethral PSMs were independently correlated with pT4-stage (OR 5.10, p = 0.01). The estimated 3-years DSS rates were 58.2%, 32.4%, 50.1%, and 40.3% for negative SMs, soft-tissue-, ureteric- and urethral PSMs, respectively (log-rank; p < 0.001). Conclusions: PSMs’ location represents distinct risk factors’ patterns. Concomitant CIS was associated with ureteric PSMs. Urethral and soft-tissue PSM showed worse DSS rates. Our results suggest that clinical decision-making paradigms on adjuvant treatment and surveillance might be adapted based on PSM and their location.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Bladder; Cancer; Cystectomy; Margin; Soft tissue; Ureter; Urethra; Urothelial carcinoma

Risk of penile tumor development in Caucasian individuals is independent of the coding variant rs7208422 in the TMC8 (EVER2) gene - Stöhr, Robert; Wendler, Olaf Dietrich; Giedl, Josef; Richter, Georg; Campean, Valentina; Burger, Maximilian; Bertz, Simone; Hartmann, Arndt; Gaisa, Nadine T.; Wullich, Bernd (Molecular and Clinical Oncology, 2021)
Genetic variation in the transmembrane channel-like (TMC)6/TMC8 region has been linked to beta-type human papillomavirus (HPV) infection and squamous cell carcinoma (SCC) of the skin and the head and neck, alpha-type HPV persistence and progression to cervical cancer. The functional variant rs7208422 of the TMC8 gene was suggested to have a high impact on susceptibility to beta-papillomaviruses and their oncogenic potential and to also have an influence on alpha-type HPV-related disease. The aim of the present study was to evaluate a possible influence of rs7208422 on penile cancer risk, a known alpha-type HPV-related malignancy. Therefore, the distribution of rs7208422 was determined by direct Sanger sequencing of 104 Caucasian penile SCC cases and compared to data of 3,810 controls taken from the literature. HPV detection was performed by usage of GP5+/6+ primers and subtype-specific PCR. It was observed that the distribution of rs7208422 followed the Hardy Weinberg equilibrium in both cases and controls. HPV DNA was detected in 39% of the penile SCC cases. Overall, there was no significant difference in the distribution of rs7208422 neither between cases and controls (P=0.726) nor between HPV-positive and-negative penile SCC cases (P=0.747). There was also no association between rs7208422 genotypes and age of disease onset (P=0.740). In conclusion, the present data argue against a significant impact of rs7208422 on the risk for the development of penile SCC in Caucasians. Even in combination with the HPV status, the SNP appears not to influence the risk of penile SCC in HPV-positive cases.
CRIS-Team WoS Importer:2021-11-26

Risk of postmenopausal hormone therapy and patient history factors for the survival rate in women with endometrial carcinoma - Hein, Alexander; Schneider, Michael; Renner, Stefan; Fasching, Peter; Fießler, Cornelia; Titz, Susanna; Hartmann, Arndt; Beckmann, Matthias; Thiel, Falk C. (Archives of Gynecology and Obstetrics, 2019)
Purpose: Postmenopausal hormone therapy (HT) is known to affect the development of hormone-dependent endometrial carcinoma (type I EC). Several studies on breast and ovarian carcinoma have shown that HT influences the molecular profile and prognostic behavior of these tumors. This study aimed to investigate the influence of prior HT and other risk factors on the prognosis in a cohort of patients with invasive endometrial carcinoma (EC). Methods: Among 525 patients diagnosed with EC between 1987 and 2010, 426 postmenopausal patients were identified. Information regarding HT was available in 287 of these patients, 78 of whom had a history of HT and 209 of whom did not. Both overall survival (OS) and progression-free survival (PFS) were analyzed. In addition to OS and PFS, risk factors such as age at diagnosis, postmenopausal HT, body mass index (BMI), diabetes mellitus, tumor stage, EC type (I or II), and recurrences were analyzed. Results: Relative to HT alone, women with EC and a history of HT had a longer survival than those with no HT. However, the Cox proportional hazards model showed that it was not HT itself, but rather other characteristics in the HT group that were causally associated with longer survival. Conclusions: Age (the older, the worse) and tumor stage (the higher, the worse) were significant influences on overall survival. Patients with HT also had lower BMIs, less diabetes, more type I EC, and fewer recurrences in comparison with the non-HT group. With regard to the PFS, it made no difference whether the patient was receiving HT.
CRIS-Team Scopus Importer:2020-02-21
Keywords: Endometrial carcinoma; Estrogen; Hormone replacement therapy; Hormone therapy; Overall survival; Progesterone; Prognosis; Risk factors

Risk, Prediction and Prevention of Hereditary Breast Cancer - Large-Scale Genomic Studies in Times of Big and Smart Data - Wunderle, Marius; Olmes, Gregor; Nabieva, Naiba; Häberle, Lothar; Jud, Sebastian; Hein, Alexander; Rauh, Claudia; Hack, Carolin; Erber, Ramona; Ekici, Arif Bülent; Hoyer, Juliane; Vasileiou, Georgia; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Over the last two decades genetic testing for mutations in BRCA1 and BRCA2 has become standard of care for women and men who are at familial risk for breast or ovarian cancer. Currently, genetic testing more often also includes so-called panel genes, which are assumed to be moderate-risk genes for breast cancer. Recently, new large-scale studies provided more information about the risk estimation of those genes. The utilization of information on panel genes with regard to their association with the individual breast cancer risk might become part of future clinical practice. Furthermore, large efforts have been made to understand the influence of common genetic variants with a low impact on breast cancer risk. For this purpose, almost 450 000 individuals have been genotyped for almost 500 000 genetic variants in the OncoArray project. Based on first results it can be assumed that - together with previously identified common variants - more than 170 breast cancer risk single nucleotide polymorphisms can explain up to 18% of familial breast cancer risk. The knowledge about genetic and non-genetic risk factors and its implementation in clinical practice could especially be of use for individualized prevention. This includes an individualized risk prediction as well as the individualized selection of screening methods regarding imaging and possible lifestyle interventions. The aim of this review is to summarize the most recent developments in this area and to provide an overview on breast cancer risk genes, risk prediction models and their utilization for the individual patient.
EVALuna2:34612

RNA sequencing of collecting duct renal cell carcinoma suggests an interaction between miRNA and target genes and a predominance of deregulated solute carrier genes - Wach, Sven; Taubert, Helge; Weigelt, Katrin; Hase, Nora; Köhn, Marcel; Misiak, Danny; Hüttelmaier, Stefan; Stöhr, Christine G.; Kahlmeyer, Andreas; Haller, Florian; Vera, Julio; Hartmann, Arndt; et al. (Cancers, 2020)
Collecting duct carcinoma (CDC) is a rare renal cell carcinoma subtype with a very poor prognosis. There have been only a few studies on gene expression analysis in CDCs. We compared the gene expression profiles of two CDC cases with those of eight normal tissues of renal cell carcinoma patients. At a threshold of |log2fold-change| ≥ 1, 3349 genes were upregulated and 1947 genes were downregulated in CDCs compared to the normal samples. Pathway analysis of the deregulated genes revealed that cancer pathways and cell cycle pathways were most prominent in CDCs. The most upregulated gene was keratin 17, and the most downregulated gene was cubilin. Among the most downregulated genes were four solute carrier genes (SLC3A1, SLC9A3, SLC26A7, and SLC47A1). The strongest negative correlations between miRNAs and mRNAs were found between the downregulated miR-374b-5p and its upregulated target genes HIST1H3B, HK2, and SLC7A11 and between upregulated miR-26b-5p and its downregulated target genes PPARGC1A, ALDH6A1, and MARC2. An upregulation of HK2 and a downregulation of PPARGC1A, ALDH6A1, and MARC2 were observed at the protein level. Survival analysis of the cancer genome atlas (TCGA) dataset showed for the first time that low gene expression of MARC2, cubilin, and SLC47A1 and high gene expression of KRT17 are associated with poor overall survival in clear cell renal cell carcinoma patients. Altogether, we identified dysregulated protein-coding genes, potential miRNA-target interactions, and prognostic markers that could be associated with CDC.
CRIS-Team Scopus Importer:2020-01-10
Keywords: Collecting duct carcinoma; RNA sequencing; Solute carrier proteins

Robust Colon Tissue Cartography with Semi-Supervision - Dexl, Jakob; Benz, Michaela; Kuritcyn, Petr; Wittenberg, Thomas; Bruns, Volker; Geppert, Carol-Immanuel; Hartmann, Arndt; Bischl, Bernd; Goschenhofer, Jann (Current Directions in Biomedical Engineering, 2022)
We explore the task of tissue classification for colon cancer histology in a low label regime comparing a semi-supervised and a supervised learning strategy in a series of experiments. Further, we investigate the model robustness w.r.t. distribution shifts in the unlabeled data and domain shifts across different scanners to prove their practicality in a histology context. By utilizing unlabeled data in addition to nl = 1000 labeled tiles per class, we yield a substantial increase in accuracy from 89.9% to 91.4%.
CRIS-Team Scopus Importer:2022-09-30
Keywords: Colon Cancer; Computational Pathology; Model Robustness; Semi-Supervised Learning

Robust Slide Cartography in Colon Cancer Histology: Evaluation on a Multi-scanner Database - Kuritcyn, Petr; Geppert, Carol-Immanuel; Eckstein, Markus; Hartmann, Arndt; Wittenberg, Thomas; Dexl, Jakob; Baghdadlian, Serop; Hartmann, David; Perrin, Dominik; Bruns, Volker; Benz, Michaela (Informatik aktuell, 2021)
CRIS-Team Scopus Importer:2021-04-19

Role of Fibroblast Growth Factors in the Crosstalk of Hepatic Stellate Cells and Uveal Melanoma Cells in the Liver Metastatic Niche - Seitz, Tatjana; John, Nora; Sommer, Judith; Dietrich, Peter; Thasler, Wolfgang E.; Hartmann, Arndt; Evert, Katja; Lang, Sven A.; Boßerhoff, Anja Katrin; Hellerbrand, Claus (International Journal of Molecular Sciences, 2022)
Hepatic metastasis is the critical factor determining tumor-associated mortality in different types of cancer. This is particularly true for uveal melanoma (UM), which almost exclusively metastasizes to the liver. Hepatic stellate cells (HSCs) are the precursors of tumor-associated fibroblasts and support the growth of metastases. However, the underlying mechanisms are widely unknown. Fibroblast growth factor (FGF) signaling is dysregulated in many types of cancer. The aim of this study was to analyze the pro-tumorigenic effects of HSCs on UM cells and the role of FGFs in this crosstalk. Conditioned medium (CM) from activated human HSCs significantly induced proliferation together with enhanced ERK and JNK activation in UM cells. An in silico database analysis revealed that there are almost no mutations of FGF receptors (FGFR) in UM. However, a high FGFR expression was found to be associated with poor survival for UM patients. In vitro, the pro-tumorigenic effects of HSC-CM on UM cells were abrogated by a pharmacological inhibitor (BGJ398) of FGFR1/2/3. The expression analysis revealed that the majority of paracrine FGFs are expressed by HSCs, but not by UM cells, including FGF9. Furthermore, the immunofluorescence analysis indicated HSCs as a cellular source of FGF9 in hepatic metastases of UM patients. Treatment with recombinant FGF9 significantly enhanced the proliferation of UM cells, and this effect was efficiently blocked by the FGFR1/2/3 inhibitor BGJ398. Our study indicates that FGF9 released by HSCs promotes the tumorigenicity of UM cells, and thus suggests FGF9 as a promising therapeutic target in hepatic metastasis.
CRIS-Team Scopus Importer:2022-10-28
Keywords: fibroblast growth factor 9; fibroblast growth factors; hepatic metastasis; hepatic stellate cells; uveal melanoma

Role of Surgical Pathologist for Detection of Predictive Immuno-oncological Factors in Breast Cancer. - Berner, Mandy; Hartmann, Arndt; Erber, Ramona (Advances in Anatomic Pathology, 2023)
Immune checkpoint inhibitors (ICIs) have changed therapy strategies in breast cancer (BC) patients suffering from triple-negative breast cancer (TNBC). For example, in Europe the anti-programmed cell death 1 ligand 1 (PD-L1) ICI Azetolizumab is approved for adult patients with locally advanced or metastasized TNBC (mTNBC), depending on the immunohistochemical (IHC) PD-L1 expression of immune cells in the tumor area [immune cell (IC) score ≥1%); the anti-programmed cell death 1 (PD-1) ICI pembrolizumab is approved for mTNBC if PD-L1 Combined Positive Score (CPS), that is PD-L1 expression on tumor and/or immune cells, is ≥10. For early TNBC, in contrast, neoadjuvant use of pembrolizumab is approved in the United States and Europe independent from PD-L1 IHC expression. The determination of PD-L1 expression in tumor tissue to predict response to ICI therapy requires sensitive immunostaining with appropriate primary antibodies and staining protocols and a standardized and meticulous assessment of PD-L1 IHC stained breast cancer tissue slides. For the selection of the test material and continuous quality control of the dyeing, high standards must be applied. The evaluation is carried out according to various evaluation algorithms (scores). Here, the role of PD-L1 in BC and the currently most relevant PD-L1 assays and scores for TNBC will be explained. Furthermore, other tissue-based biomarkers potentially predictive for ICI therapy response in BC, for example, tumor mutational burden (TMB), will be presented in this review.
EVALuna2:513974

Role of the human ErbB family receptors in urothelial carcinoma of the bladder: mRNA expression status and prognostic relevance - Erben, Philipp; Wezel, Felix; Wirtz, Ralph; Martini, Thomas; Stein, Doron; Weis, Cleo-Aaron; Hartmann, Arndt; Bolenz, Christian (Aktuelle Urologie, 2017)
Background Altered expression of epidermal growth factor (EGF) family (ErbB) receptors in urothelial carcinoma of the urinary bladder (UCB) has been associated with adverse outcomes. Given the limited treatment options in UCB, EGFR and HER2 (ERBB2) represent established therapeutic targets in other entities. We assessed the expression of ErbB family receptors (ERBB1 - 4) on mRNA levels in correlation with histopathological and clinical parameters in patients treated with radical cystectomy (RC). Methods 94 patients (female = 22; male = 72; median age: 66.5 years [range 39 - 88]) with UCB (pT1 - 4) treated with RC were included. Median follow-up was 28.2 months (range 0.6 - 139). ErbB mRNA expression levels were determined after extraction from formalin-fixed, paraffin-embedded tissue. Univariate and multivariate Cox proportional hazard models were performed to assess recurrence-free survival (RFS) and cancer-specific survival (CSS). Results Overexpression was observed in 18 % (ERBB3), 39 % (EGFR), 34 % (HER2, ERBB2) and 30 % (ERBB4) of patients, respectively. Higher pathological stage (p = 0.012), a positive nodal status (p = 0.0002), high ERBB4 (p = 0.012) and high HER2 (ERBB2) levels (p = 0.014) were significantly associated with reduced RFS. A negative lymph node status (p = 0.0003) and low HER2 (ERBB2) (p = 0.042) levels had a favourable prognostic impact on CSS. In multivariate analysis, positive pN stage (p = 0.0011) and high ERBB4 (p = 0.0073) expression were independent predictors of reduced RFS. Higher pN stage (p = 0.0016) was an independent predictor of reduced CSS. Conclusions Higher HER2 (ERBB2) expression is associated with an unfavourable prognosis in patients with UCB. However, it is not an independent predictor when measured on mRNA levels. Further analyses need to clarify which patients may still benefit from HER2 (ERBB2) targeted drugs.
EVALuna2:34253

Role of two single nucleotide polymorphisms in secreted frizzled related protein 1 and bladder cancer risk - Rogler, Anja; Hoja, Sabine; Socher, Eileen; Nolte, Elke; Wach, Sven; Wieland, Wolf; Hofstädter, Ferdinand; Goebell, Peter; Wullich, Bernd; Hartmann, Arndt; Stoehr, Robert (International Journal of Clinical and Experimental Pathology, 2013)
In this study, we determined the genotype distribution of two single nucleotide polymorphisms (SNPs) in secreted frizzled related protein 1 (SFRP1), rs3242 and rs921142, in a Caucasian bladder cancer case-control study. Allelic variants of the SNPs were determined using restriction fragment length polymorphism (RFLP) analysis and partly verified by sequencing analysis. Overall, DNA from 188 consecutive and 215 early-onset bladder cancer patients (≤45 years) as well as from 332 controls was investigated. Potential microRNA binding sites were determined for rs3242, and microRNA expression was analysed in cell lines and tumour specimens. We observed a remarkable distribution difference in rs3242 between bladder cancer patients and healthy controls (p=0.05). Additionally, we found a significant difference in genotype distribution (p=0.032), resulting from the difference of early-onset patients and the control group (p=0.007). The risk allele T showed increased frequency in the early-onset patient group (p=0.002). Genotype-dependent differences of microRNA binding capacity were predicted in SFRP1 mRNA for two microRNAs. Hsa-miR-3646 showed strong expression in cell lines and tumour tissue, whereas hsa-miR-603 exhibited weak expression. The rs921142 SNP showed no significant association with bladder cancer risk. This is the first study to describe an association of the SFRP1 SNP rs3242 and bladder cancer risk as well as the influence of rs3242 on genotype-dependent microRNA capacity on SFRP1 mRNA. The onset of bladder seems to be associated with the increased occurrence of the T-allele in rs3242.
Keywords: Bladder cancer; Microrna; Sfrp1; Snp; Wnt signalling pathway

Safety and efficacy of single cycle induction treatment with cisplatin/docetaxel/ durvalumab/tremelimumab in locally advanced HNSCC: first results of CheckRad-CD8 - Hecht, Markus; Gostian, Antoniu Oreste; Eckstein, Markus; Rutzner, Sandra; von der Grün, Jens; Illmer, Thomas; Hautmann, Matthias Günther; Klautke, Gunther; Laban, Simon; Brunner, Thomas; Hinke, Axel; Becker, Ina; et al. (Journal for ImmunoTherapy of Cancer, 2020)
BACKGROUND: To determine safety and efficacy of single cycle induction treatment with cisplatin/docetaxel and durvalumab/tremelimumab in stage III-IVB head and neck cancer. METHODS: Patients received a single cycle of cisplatin 30 mg/m² on days 1-3 and docetaxel 75 mg/m² on day 1 combined with durvalumab 1500 mg fix dose on day 5 and tremelimumab 75 mg fix dose on day 5. Patients with pathologic complete response (pCR) in the rebiopsy after induction treatment or at least 20% increase of intratumoral CD8+ cell density in the rebiopsy compared with baseline entered radioimmunotherapy with concomitant durvalumab/tremelimumab. The objective of this interim analysis was to analyze safety and efficacy of the chemoimmunotherapy-induction treatment before radioimmunotherapy. RESULTS: A total of 57 patients were enrolled, 56 were treated. Median pretreatment intratumoral CD8+ cell density was 342 cells/mm². After induction treatment, 27 patients (48%) had a pCR in the rebiopsy and further 25 patients (45%) had a relevant increase of intratumoral CD8+ cells (median increase by a factor of 3.0). Adverse event (AE) grade 3-4 appeared in 38 patients (68%) and mainly consisted of leukopenia (43%) and infections (29%). Six patients (11%) developed grade 3-4 immune-related AE. Univariate analysis computed p16 positivity, programmed death ligand 1 immune cell area and intratumoral CD8+ cell density as predictors of pCR. On multivariable analysis, intratumoral CD8+ cell density predicted pCR independently (OR 1.0012 per cell/mm², 95% CI 1.0001 to 1.0022, p=0.016). In peripheral blood CD8+ cells, the coexpression of programmed death protein 1 significantly increased especially in patients with pCR. CONCLUSIONS: Single cycle induction treatment with cisplatin/docetaxel and durvalumab/tremelimumab is feasible and achieves a high biopsy-proven pCR rate.
CRIS-Team Scopus Importer:2020-10-23
Keywords: CD8-Positive T-lymphocytes; clinical trials; combined modality therapy; head and neck neoplasms; Phase II as topic; radioimmunotherapy

Sclerosing epithelioid fibrosarcoma of the kidney: clinicopathologic and molecular study of a rare neoplasm at a novel location - Ohlmann, Carsten-Henning; Brecht, Ines B.; Junker, Kerstin; Van Der Zee, Jill A.; Nistor, Adriana; Bohle, Rainer M.; Stöckle, Michael; Metzler, Markus; Hartmann, Arndt; Agaimy, Abbas (Annals of Diagnostic Pathology, 2015)
Sclerosing epithelioid fibrosarcoma (SEF) is a rare fibrosarcoma variant with specific histomorphology and consistent translocation (EWSR1-CREB3L1/2). To date, 110 cases have been reported; only 15 originated within the abdomen. With only 2 cases reported parallel to our study and one case briefly mentioned in a previous series, primary renal SEF is exceptionally rare but might be underrecognized. We herein describe 2 cases affecting a 23-year-old woman and a 43-year-old man. Tumor size was 22 and 4.2 cm, respectively. Patient 1 developed skeletal and multiple pulmonary metastases. She died of disease 82 months later, despite aggressive multimodality therapy. Patient 2 has no evidence of recurrence or metastasis (8 months after surgery). Histologic examination showed similar appearance with monotonous bland medium-sized epithelioid cells with rounded slightly vesicular nuclei and clear cytoplasm imparting a carcinoma-like appearance set within a highly sclerotic hyaline fibrous stroma. The tumor cells were arranged in nests, single cell cords, trabeculae, or solid sheets with frequent entrapment of renal tubules and glomeruli. Immunohistochemistry showed strong expression of vimentin, bcl2, CD99, and MUC4, whereas cytokeratin and other markers were negative. Fluorescence in situ hybridization showed a translocation involving the EWSR1 gene locus in case 2. Molecular analysis in case 1 was not successful due to poor signal quality. To our knowledge, this is the second report documenting primary renal SEF. Awareness of this entity would help avoid misinterpretation as clear cell carcinoma, sclerosing perivascular epithelioid cell tumor, Xp.11 translocation carcinoma, and other more frequent neoplasms at this site.
EVALuna2:6701

Scoring PD-L1 Expression in Urothelial Carcinoma: An International Multi-Institutional Study on Comparison of Manual and Artificial Intelligence Measurement Model (AIM-PD-L1) Pathology Assessments - Rüschoff, Josef; Kumar, George; Badve, Sunil; Jasani, Bharat; Krause, Emma; Rioux-Leclercq, Nathalie; Rojo, Federico; Martini, Maurizio; Cheng, Liang; Tretiakova, Maria; Mitchell, Catherine; Anders, Robert A.; et al. (Virchows Archiv, 2024)
Assessing programmed death ligand 1 (PD-L1) expression on tumor cells (TCs) using Food and Drug Administration-approved, validated immunoassays can guide the use of immune checkpoint inhibitor (ICI) therapy in cancer treatment. However, substantial interobserver variability has been reported using these immunoassays. Artificial intelligence (AI) has the potential to accurately measure biomarker expression in tissue samples, but its reliability and comparability to standard manual scoring remain to be evaluated. This multinational study sought to compare the %TC scoring of PD-L1 expression in advanced urothelial carcinoma, assessed by either an AI Measurement Model (AIM-PD-L1) or expert pathologists. The concordance among pathologists and between pathologists and AIM-PD-L1 was determined. The positivity rate of ≥ 1%TC PD-L1 was between 20–30% for 8/10 pathologists, and the degree of agreement and scoring distribution for among pathologists and between pathologists and AIM-PD-L1 was similar both scored as a continuous variable or using the pre-defined cutoff. Numerically higher score variation was observed with the 22C3 assay than with the 28–8 assay. A 2-h training module on the 28–8 assay did not significantly impact manual assessment. Cases exhibiting significantly higher variability in the assessment of PD-L1 expression (mean absolute deviation > 10) were found to have patterns of PD-L1 staining that were more challenging to interpret. An improved understanding of sources of manual scoring variability can be applied to PD-L1 expression analysis in the clinical setting. In the future, the application of AI algorithms could serve as a valuable reference guide for pathologists while scoring PD-L1.
CRIS-Team Scopus Importer:2024-04-12
Keywords: Artificial intelligence; Bladder cancer; Pathology; PD-L1

Sebaceous breast carcinoma: report of a rare histological special subtype - Wachter, David; Rauh, C.; Wenkel, Evelyn; Fasching, Peter; Beckmann, Matthias; Hartmann, Arndt (Pathologe, 2014)
We report on a case of sebaceous carcinoma of the breast as a rare histological special subtype of breast cancer. Because these tumors are uncommon, differential diagnostic considerations and the exclusion of Muir-Torre syndrome are emphasized. Finally possible mechanisms of development and therapeutic strategies for this carcinoma are discussed.
EVALuna2:6578

Second-Line Treatment of Advanced Urothelial Cancer with Paclitaxel and Everolimus in a German Phase II Trial (AUO Trial AB 35/09) - Niegisch, Guenter; Retz, Margitta; Thalgott, Mark; Balabanov, Stefan; Honecker, Friedemann; Ohlmann, Carsten Henning; Stoeckle, Michael; Boegemann, Martin; Vom Dorp, Frank; Gschwend, Juergen; Hartmann, Arndt; Ohmann, Christian; et al. (Oncology, 2015)
The efficacy of second-line treatment after failure of platinum-based chemotherapy in patients with advanced urothelial cancer is limited. Based on encouraging preclinical and clinical phase I data, we evaluated the safety and efficacy of the combination of paclitaxel and everolimus in these patients.In this trial, patients having failed to respond to prior platinum-based combination treatment of urothelial cancer were treated with paclitaxel (175 mg/m(2) i.v., 3-weekly) and the mTOR-inhibitor everolimus (10 mg p.o., once daily). The patients were treated until tumor progression or until a maximum of 6 cycles was completed. A one-stage design was used to evaluate the objective response rate (ORR) as the primary endpoint.A total of 27 patients (67% male; median age 63 years) were enrolled. The most frequent grade III/IV toxicities were anemia (28%), peripheral neuropathy (28%), and fatigue (24%). No treatment-related deaths were reported. Complete and partial remissions were observed in 0/24 and 3/24 patients eligible for efficacy analysis, respectively (ORR 13%). Progression-free survival was 2.9 months [95% confidence interval (95% CI) 1.9-4.2], and the median overall survival was 5.6 months (95% CI 4.8-10.2).The combination of paclitaxel and everolimus has not achieved the expected efficacy in second-line treatment of urothelial cancer and should not be further explored.
EVALuna2:6790

Seizure-induced neuronal apoptosis is related to dysregulation of the RNA-edited GluR2 subunit in the developing mouse brain - Jung, Susan; Ballheimer, Yili Elisabeth; Brackmann, Florian; Zoglauer, Daniel; Geppert, Carol-Immanuel; Hartmann, Arndt; Trollmann, Regina (Brain Research, 2020)
Ca2+-permeable AMPA receptors (AMPAR) which crucially modify maturational programs of the developing brain are involved in seizure-induced glutamate excitotoxicity and apoptosis. Regulatory effects on AMPAR subunit composition and RNA-editing in the developing brain and their significance as therapeutic targets are not well understood. Here, we analyzed acute effects of recurrent pilocarpine-induced neonatal seizures on age- and region-specific expression of AMPAR subunits and adenosine deaminases (ADAR) in the developing mouse brain (P10). After recurrent seizure activity and regeneration periods of 6–72 h cerebral mRNA levels of GluR (glutamate receptor subunit) 1, GluR2, GluR3, and GluR4 were unaffected compared to controls. However, ratio of GluR2 and GluR4 to pooled GluR1-4 mRNA concentration significantly decreased in seizure-exposed brains in comparison to controls. After a regeneration period of 24–72 h ADAR1 and ADAR2 mRNA expression was significantly lower in seizure-exposed brains than in those of controls. This was confirmed at the protein level in the hippocampal CA3 region. We observed a regionally increased apoptosis (TUNEL+ and CC3+ cells) in the hippocampus, parietal cortex and subventricular zone of seizure-exposed brains in comparison to controls. Together, present in vivo data demonstrate the maturational age-specific, functional role of RNA-edited GluR2 in seizure-induced excitotoxicity in the developing mouse brain. In response to recurrent seizure activity, we observed reduced expression of GluR2 and the GluR2 mRNA-editing enzymes ADAR1 and ADAR2 accompanied by increased apoptosis in a region-specific manner. Thus, AMPA receptor subtype-specific mRNA editing is assessed as a promising target of novel neuroprotective treatment strategies in consideration of age-related developmental mechanisms.
CRIS-Team Scopus Importer:2020-03-17
Keywords: ADAR; Adenosine deaminases; Apoptosis; Brain injury; Experimental seizure model; Neonatal brain; Neurodegeneration; Neuroprotection; Pilocarpine; RNA editing

Select hyperactivating NLRP3 ligands enhance the TH1-and TH17-inducing potential of human type 2 conventional dendritic cells - Hatscher, Lukas; Lehmann, Christian; Purbojo, Ariawan; Onderka, Constantin; Liang, Chunguang; Hartmann, Arndt; Cesnjevar, Robert; Bruns, Heiko; Gross, Olaf; Nimmerjahn, Falk; Burmazovic, Ivana Ivanovic; Kunz, Meik; et al. (Science Signaling, 2021)
The detection of microorganisms and danger signals by pattern recognition receptors on dendritic cells (DCs) and the consequent formation of inflammasomes are pivotal for initiating protective immune responses. Although the activation of inflammasomes leading to secretion of the cytokine IL-1 is typically accompanied by pyroptosis (an inflammatory form of lytic programmed cell death), some cells can survive and exist in a state of hyperactivation. Here, we found that the conventional type 2 DC (cDC2) subset is the major human DC subset that is transcriptionally and functionally poised for inflammasome formation and response without pyroptosis. When cDC2 were stimulated with ligands that relatively weakly activated the inflammasome, the cells did not enter pyroptosis but instead secreted IL-12 family cytokines and IL-1. These cytokines induced prominent T helper type 1 (TH1) and TH17 responses that were superior to those seen in response to Toll-like receptor (TLR) stimulation alone or to stronger, classical inflammasome ligands. These findings not only define the human cDC2 subpopulation as a prime target for the treatment of inflammasome-dependent inflammatory diseases but may also inform new approaches for adjuvant and vaccine development.
CRIS-Team Scopus Importer:2021-05-14
Keywords: Dendritic cells; cDC2; CD1c; inflammasome; hyperactivation; L18-MDP; T cell differentiation

Select hyperactivating NLRP3 ligands enhance the TH1-and TH17-inducing potential of human type 2 conventional dendritic cells - Heger, Lukas; Hatscher, Lukas; Lehmann, Christian; Purbojo, Ariawan; Onderka, Constantin; Liang, C.; Hartmann, Arndt; Cesnjevar, Robert; Bruns, Heiko; Gross, O.; Nimmerjahn, Falk; Ivanovic-Burmazovic, I.; et al. (EXPERIMENTAL DERMATOLOGY, 2022)
CRIS-Team WoS Importer:2022-03-04

Sensitive allele-specific real-time PCR test for mutations in BRAF codon V600 in skin melanoma - Pisareva, Ekaterina; Gutkina, Nadezhda; Kovalenko, Sergei; Kuehnapfel, Sarah; Hartmann, Arndt; Heinzerling, Lucie; Schneider-Stock, Regine; Lyubchenko, Lyudmila; Shamanin, Vladimir A. (Melanoma Research, 2014)
Mutations at BRAF codon V600 are used as predictive biomarkers for targeted therapy of skin melanoma. Here, a simple sensitive test to detect mutations of BRAF-V600 was developed using real-time PCR with allele-specific primers and TaqMan probes. Two versions of the test using sense and antisense allele-specific primers were designed and evaluated. The test detected 1% mutant allele V600E/K in 10 ng DNA standard made from wild-type human DNA spiked with BRAF-V600E or the V600K plasmid. The test was validated on clinical formalin-fixed paraffin-embedded samples of skin melanoma using pyrosequencing as a reference method. In the clinical samples, we detected the common mutation V600E, as well as the rare mutations V600K, V600E2 (codon GAA), V600E2 K601del, V600D-K601del, and V600R. In comparison with pyrosequencing, both versions of the test had 100% specificity with sensitivities of 97 and 86% for sense and antisense allele-specific primers, respectively. Using the PCR test with sense allele-specific primers, mutations in V600 were found in 33 of 51 Russian patients (64.7%) with cutaneous melanoma. This closed-tube real-time PCR test can be used as a simple and sensitive assay for mutations of BRAF-V600 in cutaneous melanoma.
EVALuna2:6621

Sensitive and specific detection of EML4-ALK rearrangements in non-small cell lung cancer (NSCLC) specimens by multiplex amplicon RNA massive parallel sequencing - Moskalev, Evgeny; Frohnauer, Judith; Merkelbach-Bruse, Sabine; Schildhaus, Hans-Ulrich; Dimmler, Arno; Schubert, Thomas; Boltze, Carsten; Koenig, Helmut; Fuchs, Florian; Sirbu, Horia; Rieker, Ralf J.; Agaimy, Abbas; et al. (Lung Cancer, 2014)
Recurrent gene fusions of anaplastic lymphoma receptor tyrosine kinase (ALK) and echinoderm microtubule-associated protein-like 4 (EML4) have been recently identified in 5% of non-small cell lung cancers (NSCLCs) and are targets for selective tyrosine kinase inhibitors. While fluorescent in situ hybridization (FISH) is the current gold standard for detection of EML4-ALK rearrangements, several limitations exist including high costs, time-consuming evaluation and somewhat equivocal interpretation of results. In contrast, targeted massive parallel sequencing has been introduced as a powerful method for simultaneous and sensitive detection of multiple somatic mutations even in limited biopsies, and is currently evolving as the method of choice for molecular diagnostic work-up of NSCLCs.We developed a novel approach for indirect detection of EML4-ALK rearrangements based on 454 massive parallel sequencing after reverse transcription and subsequent multiplex amplification (multiplex ALK RNA-seq) which takes advantage of unbalanced expression of the 5' and 3' ALK mRNA regions. Two lung cancer cell lines and a selected series of 32 NSCLC samples including 11 cases with EML4-ALK rearrangement were analyzed with this novel approach in comparison to ALK FISH, ALK qRT-PCR and EML4-ALK RT-PCR.The H2228 cell line with known EML4-ALK rearrangement showed 171 and 729 reads for 5' and 3' ALK regions, respectively, demonstrating a clearly unbalanced expression pattern. In contrast, the H1299 cell line with ALK wildtype status displayed no reads for both ALK regions. Considering a threshold of 100 reads for 3' ALK region as indirect indicator of EML4-ALK rearrangement, there was 100% concordance between the novel multiplex ALK RNA-seq approach and ALK FISH among all 32 NSCLC samples.Multiplex ALK RNA-seq is a sensitive and specific method for indirect detection of EML4-ALK rearrangements, and can be easily implemented in panel based molecular diagnostic work-up of NSCLCs by massive parallel sequencing.
EVALuna2:1847

Serrated epithelial colorectal polyps (hyperplastic polyps, sessile serrated adenomas) with perineurial stroma: Clinicopathological and molecular analysis of a new series - Erlenbach-Wuenscha, Katharina; Bihl, Michel; Hartmann, Arndt; Groisman, Gabriel M.; Agaimy, Abbas; Vieth, Michael (Annals of Diagnostic Pathology, 2018)
Serrated colorectal fibroblastic polyps (FPs) are rare benign mucosal lesions composed of serrated epithelial crypts separated and distorted by intimately associated bland spindle cell proliferations with perineurial-like phenotype. We herein describe 21 new FPs affecting 10 females and 9 males aged 45 to 80 yrs. (mean, 62 yrs). Lesions originated in the sigmoid colon/rectosigmoid junction (n = 16), rectum (n = 2), and other parts of the colon (n = 3). Most patients had additional synchronous or metachronous polyps: classical adenomas (12 patients), sessile serrated adenoma/SSA (1 patient), hyperplastic polyps/HPs (7 patients), both HPs and adenomas (6 patients) and colorectal cancer (2 patients). Size of the lesions varied from 1 to 6 mm (mean: 3 mm). Histologically, all lesions were composed of serrated epithelial crypts that were separated and distorted by spindle cell stromal proliferations (consistently EMA+, claudin-1+ and GLUT-1+). The epithelial component displayed features of HPs (n = 17) and SSA (n = 4). Laser-microdissection-guided molecular testing was successful for 13 epithelial and 9 stromal components (9 paired samples). The BRAF V600E mutation was detected in 54% of the epithelial but in none of the stromal components. In conclusion, colorectal FPs represent genuine serrated epithelial polyps corresponding either to HP or (less frequently) SSA and should be better classified as such with a note on the presence of the stromal component. A more concise terminology reflecting their epithelial nature is needed to fulfill the requirements for colorectal cancer risk assessment and hence adopt appropriate follow-up strategies.
EVALuna2:34303

Serum miRNAs Support the Indication for MRI-Ultrasound Fusion-Guided Biopsy of the Prostate in Patients with Low-PI-RADS Lesions - Keck, Bastian; Borkowetz, Angelika; Pöllmann, Julia; Jansen, Thilo; Fischer, Moritz; Fuessel, Susanne; Kahlmeyer, Andreas; Wirth, Manfred; Huber, Johannes; Cavallaro, Alexander Josef; Hammon, Matthias; Platzek, Ivan; et al. (Cells, 2021)
Multiparametric MRI (mpMRI) and targeted biopsy of the prostate enhance the tumor detection rate. However, the prediction of clinically significant prostate cancer (PCa) is still limited. Our study tested the additional value of serum levels of selected miRNAs in combination with clinical and mpMRI information for PCa prediction and classification. A total of 289 patients underwent targeted mpMRI-ultrasound fusion-guided prostate biopsy complemented by systematic biopsy. Serum miRNA levels of miRNAs (miR-141, miR-375, miR-21-5p, miR-320b, miR-210-3p, let-7c, and miR-486) were determined by quantitative PCR. Detection of any PCa and of significant PCa were the outcome variables. The patient age, pre-biopsy PSA level, previous biopsy procedure, PI-RADS score, and serum miRNA levels were covariates for regularized binary logistic regression models. The addition of miRNA expression of miR-486 and let-7c to the baseline model, containing only clinical parameters, increased the predictive accuracy. Particularly in patients with PI-RADS ≤3, we determined a sensitivity for detecting significant PCa (Gleason score ≥ 7a corresponding to Grade group ≥2) of 95.2%, and an NPV for absence of significant PCa of 97.1%. This accuracy could be useful to support patient counseling in selected cases.
CRIS-Team Scopus Importer:2021-06-18
Keywords: diagnosis; microRNA; miRNA; mpMRI; PI-RADS; prostate biopsy; prostate cancer

Shift in prevalence of HPV types in cervical cytology specimens in the era of HPV vaccination - Fischer, Sonja; Bettstetter, Marcus; Becher, Andrea; Lessel, Marlene; Bank, Cyril; Krams, Matthias; Becker, Ingrid; Hartmann, Arndt; Jagla, Wolfgang; Gaumann, Andreas (Oncology Letters, 2016)
The aim of the present population-based cohort study was to analyze the association between the prevalence of 32 types of human papilloma virus (HPV) in 615 female patients with abnormal cervical cytopathology findings. In total, 32 HPV types were screened by DNA array technology. HPV infection was detected in 470 women (76.42%), 419 of whom (89.15%) were infected with >=1 high-risk (HR)-HPV type. HPV16, which is recognized as the main HR-HPV type responsible for the development of cervical cancer, was observed in 32.98% of HPV+ participants, followed by HPV42 (18.09%), HPV31 (17.66%), HPV51 (13.83%), HPV56 (10.00%), HPV53 (8.72%) and HPV66 (8.72%). The prevalence of HR-HPV types, which may be suppressed directly (in the case of HPV16 and 18), or possibly via cross-protection (in the case of HPV31) following vaccination, was considerably lower in participants <=22 years of age (HPV16, 28.57%; HPV18, 2.04%; HPV31, 6.12%), compared with participants 23-29 years of age (HPV16, 45.71%; HPV18, 7.86%; HPV31, 22.86%), who were less likely to be vaccinated. Consequently, the present study hypothesizes that there may be a continuous shift in the prevalence of HPV types as a result of vaccination. Furthermore, the percentage of non-vaccine HR-HPV types was higher than expected, considering that eight HPV types formerly classified as 'low-risk' or 'probably high-risk' are in fact HR-HPV types. Therefore, it may be important to monitor non-vaccine HPV types in future studies, and an investigation concerning several HR-HPV types as risk factors for the development of cervical cancer is required.
EVALuna2:6918

Shifts in Macrophage as a prognostic Biomarker in Patients with luminal Breast Cancer - A Confirmatory Study - Schnellhardt, Sören; Segelhorst, Sarah; Erber, Ramona; Daniel, Christoph; Hartmann, Arndt; Fasching, Peter; Beckmann, Matthias; Fietkau, Rainer; Distel, Luitpold; Rübner, Matthias (STRAHLENTHERAPIE UND ONKOLOGIE, 2021)
CRIS-Team WoS Importer:2021-07-16

Signal decomposition for X-ray dark-field imaging - Käppler, Sebastian; Bayer, Florian; Weber, Thomas; Maier, Andreas; Anton, Gisela; Hornegger, Joachim; Beckmann, Matthias; Fasching, Peter; Hartmann, Arndt; Heindl, Felix; Michel, Thilo; Oezguel, Gueluemser; et al. (MICCAI 2014, 2014)
Grating-based X-ray dark-field imaging is a new imaging modality. It allows the visualization of structures at micrometer scale due to small-angle scattering of the X-ray beam. However, reading darkfield images is challenging as absorption and edge-diffraction effects also contribute to the dark-field signal, without adding diagnostic value. In this paper, we present a novel–and to our knowledge the first–algorithm for isolating small-angle scattering in dark-field images, which greatly improves their interpretability. To this end, our algorithm utilizes the information available from the absorption and differential phase images to identify clinically irrelevant contributions to the dark-field image. Experimental results on phantom and ex-vivo breast data promise a greatly enhanced diagnostic value of dark-field image
EVALuna2:6632

Single cycle induction treatment with cisplatin/docetaxel plus durvalumab/tremelimumab in stage III-IVB head and neck squamous cell cancer (CheckRad-CD8 trial) - Hecht, Markus; Gostian, A-O.; Eckstein, Markus; Rutzner, Sandra; Von Der Gruen, J.; Illmer, T.; Hautmann, M. G.; Brunner, T.; Laban, S.; Klautke, G.; Tamaskovics, B.; Frey, Benjamin; et al. (ANNALS OF ONCOLOGY, 2019)
CRIS-Team WoS Importer:2019-11-08

Single nucleotide polymorphism D1853N of the ATM gene may alter the risk for breast cancer - Schrauder, M.; Frank, S.; Strissel, Pamela; Lux, Michael P.; Bani, Mayada; Rauh, C.; Sieber, Cornel; Heusinger, K.; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Strick, Reiner; Beckmann, Matthias; et al. (Journal of Cancer Research and Clinical Oncology, 2008)
Purpose Various ATM (ataxia telangiectasia-mutated) mutations and polymorphisms have been reported to be associated with an increased breast cancer risk. Recent studies have produced contradictory results regarding the association between ATM genetic variants and breast cancer risk.Materials and methods The common ATM polymorphism 5557G > A (p.D1853N) (rs1801516), previously suggested to be associated with bilateral breast cancer, was analyzed using real-time PCR in 514 unselected patients with breast cancer and 511 age-matched healthy control individuals. DNA was obtained from peripheral blood draw.Results The ATM genotype was weakly associated with the risk for breast cancer (P = 0.04 for the overall test). The odds ratio for women with a heterozygous genotype was 0.70 (95% CI, 0.52-0.94) and for the homozygous variant 0.63 (95% CI, 0.27-1.49). Disease-free survival and overall survival showed no significant association with specific genotypes.Conclusions The results of this study might suggest a minor association between polymorphism 5557G > A and a reduced risk of breast cancer.
Keywords: TM gene variants; polymorphism; breast cancer; DNA damage; epidemiology; association

Sinonasal papillomas: A single centre experience on 137 cases with emphasis on malignant transformation and EGFR/KRAS status in “carcinoma ex papilloma” - Maisch, Saskia; Müller, Sarina Katrin; Traxdorf, Maximilian; Weyerer, Veronika; Stoehr, Robert; Iro, Heinrich; Hartmann, Arndt; Agaimy, Abbas (Annals of Diagnostic Pathology, 2020)
Among the three major histological subtypes of sinonasal papillomas, inverted (ISP) and oncocytic (OSP) sinonasal papillomas tend to undergo malignant transformation to carcinoma. However, criteria determining risk of recurrence and malignant progression have not been established. Recently, EGFR and KRAS mutations were detected to be characteristic for ISP and OSP, respectively. In this study, we analyzed 137 sinonasal papilloma cases (132 ISP and 5 OSP) for clinicopathological characteristics, frequency of recurrences/malignant transformation, and histological types and genetic features of carcinoma ex Schneiderian papilloma. OSP presented at a higher age than ISP (median, 75 vs. 57 years) and affected predominantly females. Overall frequency of recurrences and malignant transformation was 23.1% and 9.5%, respectively. Rates of recurrence (33.3% vs. 22.0%) and malignant transformation (33.3% vs. 8.8%) were higher in OSP compared to ISP, respectively. Carcinomas (n = 10) occurred mostly synchronously, more frequently in females and mainly associated with ISP (n = 9). Squamous cell carcinoma (SCC) was the most frequently associated malignancy. Concordant EGFR (in ISP/associated carcinoma) and KRAS (in the OSP/associated carcinoma) mutations were detected in all successfully analyzed matching papilloma/carcinoma pairs, confirming their shared clonal origin. Results of this large study are in line with recent studies showing frequent EGFR and KRAS mutations in sinonasal carcinoma ex Schneiderian papilloma. As the papilloma component might on occasion be missed on biopsy of synchronous carcinoma ex papilloma, EGFR and KRAS mutation testing represents a promising molecular surrogate for sinonasal “carcinoma ex papilloma”, at the same time offering an opportunity for targeting mutant EGFR in this rare cancer type.
CRIS-Team Scopus Importer:2020-03-27
Keywords: Carcinoma ex papilloma; EGFR; Inverted papilloma; KRAS; Oncocytic papilloma; Schneiderian papilloma; Sinonasal papilloma; Squamous cell carcinoma

Sinonasal tumors : News from the WHO with special reference to mesenchymal entities - Agaimy, Abbas; Haller, F.; Hartmann, Arndt (Pathologe, 2018)
The last two decades have seen significant advances in the pathology of sinonasal tract neoplasms. This was the consequence of the availability of several innovative diagnostic tools, which resulted in a dynamic evolution of entities and splitting of newly defined or conceptualized entities and subtypes that have been included in the spectrum of old heterogeneous diseases. Most of these new tumor subtypes have distinctive demographic, clinicopathologic, and biological characteristics with prognostic and therapeutic implications for individual patients. NUT carcinoma (NUT midline carcinoma) was separated from the spectrum of sinonasal undifferentiated carcinoma (SNUC) and is defined by specific recurrent translocation. On the other hand, the recently described SMARCB1-deficient carcinoma (while probably representing a distinctive clinicopathologic entity) remained as a variant in the SNUC spectrum. A new neoplasm in the spectrum of non-keratinizing carcinomas is the human papillomavirus(HPV)-related adenoid-cystic-like sinonasal carcinoma with its distinctive, albeit diverse, morphology. In the group of small round-cell malignancies, adamantinoma-like Ewing sarcoma has been delineated as an important diagnostic pitfall given its prominent epithelial differentiation. Inclusion of the biphenotypic (myoneural) sinonasal sarcoma (BSS) as a low-grade malignancy defined by recurrent PAX3/MAML3-translocation represents an important feature of the new WHO classification given the distinctive biological behavior of this low-grade non-metastasizing rare entity, which has been uniformly misclassified as a peripheral nerve sheath tumor or leiomyosarcoma in the past. Recognition of CTNNB1 mutations and STAT6/NAB2 gene fusions as defining genetic markers for sinonasal hemangio‑/glomangiopericytoma and solitary fibrous tumors, respectively, represents another important achievement in recent years. This review summarizes the new aspects in the WHO classification and also addresses recently described entities that have not been included in the WHO classification.
EVALuna2:34102

Small renal cell carcinomas–how dangerous are they really? Results of a large multicenter study - Steffens, Sandra; Junker, Kerstin; Roos, Frederik C.; Janssen, Martin; Becker, Frank; Henn, Daniela; Wegener, Gerd; Siemer, Stefan; Hofmann, Rainer; Schrader, Mark; Stoeckle, Michael; Thueroff, Joachim W.; et al. (European Journal of Cancer, 2014)
Modern diagnostic ultrasound and cross-sectional imaging has enabled the detection of increasing numbers of renal tumours. The aim of this study was to investigate the tumour- and patient-specific characteristics and prognosis of small renal cell carcinomas (RCCs) after surgical resection.The study included 2197 patients who underwent surgical resection of histologically confirmed RCC ? 4 cm between 1990 and 2011. Median (mean) follow-up was 56.2 (65.5) months.At the time of surgery, tumours were staged as pT ? 3a in 175 (8.0%) cases, 134 (6.2%) were poorly differentiated and 75 (3.5%) were metastasised. The larger the tumour size, the higher was the risk of presenting with stage pT ? 3a (p<0.001), poor tumour differentiation (p = 0.004), microscopic vascular involvement (p = 0.001) and collecting system invasion (p = 0.03). The 5-year cancer-specific survival (CSS) rate was 93.8% for stage pT1a versus 79.4% for stage pT ? 3a (p<0.001), and it was 93.7% for G1-2 versus 76.8% for G3-4 differentiation (p<0.001). Multivariate analysis identified age in years (hazard ratio (HR) 1.04, p<0.001), metastatic disease (HR 12.5, p < 0.001), tumour differentiation (HR 2.8, p<0.001) and non-clear cell histology (HR 0.51, p = 0.02) as independent prognosticators for CSS in patients with small RCC. Interestingly, the 5-year cancer-specific mortality rate for pT1a N/M0 patients was 5.8%.This large multicenter study has clearly shown that, though most small RCC have a low pathological stage and a good prognosis, there is also a small but significant subgroup of these tumours that are already locally advanced or poorly differentiated.
EVALuna2:6670

SMARCA4 and SMARCA2 deficiency in non-small cell lung cancer: immunohistochemical survey of 316 consecutive specimens - Herpel, Esther; Rieker, Ralf J.; Dienemann, Hendrik; Muley, Thomas; Meister, Michael; Hartmann, Arndt; Warth, Arne; Agaimy, Abbas (Annals of Diagnostic Pathology, 2017)
The chromatin remodeling switch sucrose nonfermentable (SWI/SNF) complex has been increasingly implicated in the pathogenesis and dedifferentiation of neoplasms from several organs with prognostic and potential therapeutic implications. We herein investigated the expression of the SWI/SNF complex catalytic subunits SMARCA4 (BRG1) and SMARCA2 (BRM) in 316 consecutive non-small cell lung cancer (NSCLC) specimens on tissue microarrays (171 adenocarcinomas [ADCAs], 130 squamous cell carcinomas [SCCs], 9 adenosquamous carcinomas, and 6 large cell carcinomas) excluding undifferentiated/giant cell or rhabdoid carcinomas. Complete loss of SMARCA4 was observed in 8 (5.5%) of 146 evaluable pulmonary ADCAs and 6 (5.2%) of 115 evaluable pulmonary SCCs, whereas 9 (6.4%) of 140 ADCAs and 2 (1.7%) of 117 SCCs showed SMARCA2 loss. Two of 6 large cell carcinomas were SMARCA2 deficient. Concurrent loss of both markers was observed in 4 cases (2 ADCAs and 2 SCCs). Of 15 ADCAs with loss of either or both markers, 12 (80%) were TTF1 negative. In conclusion, SMARCA4 and SMARCA2 deficiency is observed in 5.1% and 4.8% of NSCLC, respectively. SMARCB1 expression was intact in all cases. The presence of differentiated histology (glandular or squamous) is a novel aspect among SWI/SNF-deficient carcinomas which in other organs generally are associated with undifferentiated/rhabdoid morphology. The predominance of TTF1 negativity among SWI/SNF-deficient pulmonary ADCA (80%) underlines the need to include these 2 markers in the evaluation of TTF1-negative ADCA of putative pulmonary origin. Given the recently documented potential of SMARCA4 loss as a predictor of chemosensitivity to platinum-based chemotherapy in NSCLC, recognition of the clinicopathological features of SMARCA4-deficient NSCLC in routine surgical pathology practice is recommended.
EVALuna2:6837

SMARCA4-deficient pulmonary adenocarcinoma: clinicopathological, immunohistochemical, and molecular characteristics of a novel aggressive neoplasm with a consistent TTF1neg/CK7pos/HepPar-1pos immunophenotype - Agaimy, Abbas; Fuchs, Florian; Moskalev, Evgeny; Sirbu, Horia; Hartmann, Arndt; Haller, Florian (Virchows Archiv, 2017)
Alterations in SMARCA4, a member of the chromatin remodeling Switch Sucrose Non-Fermentable (SWI/SNF) complex, characterize a subset of non-small cell lung cancer (NSCLC), but detailed morphological and immunophenotypic description of this tumor type is lacking. We describe 20 NSCLC cases found on routine screening not to express SMARCA4 by immunohistochemistry (IHC). These tumors were stained for CK7, TTF1, SMARCA2, SMARCA4, SMARCB1, and HepPar-1 and analyzed for molecular alterations, using a 160 cancer-related gene panel including the full coding sequence of SMARCA4. Patients were eight females and 12 males aged 41 to 76 (median, 60). Of 18 tumors with detailed data, 14 presented with synchronous distant metastases (M1). Histological examination showed predominantly solid adenocarcinoma (n = 15), frankly rhabdoid (n = 3) and mucinous (n = 2) patterns. Except for the rhabdoid cases, all tumors showed at least focal unequivocal glands and lacked squamous differentiation, justifying a diagnosis of adenocarcinoma. IHC showed a distinctive uniform immunophenotype (CK7+/HepPar-1+/TTF1-) in 18/20 cases. Only 2/16 cases showed limited weak expression of neuroendocrine markers. EGFR mutations and EML4-ALK and ROS1 gene rearrangements were not found in any of the examined cases. Next-generation sequencing, using a 160 cancer-related gene panel, revealed concurrent SMARCA4 and TP53 mutations in nine of the 12 (75%) successfully tested cases. Our study highlights (1) the morphological diversity of SMARCA4-deficient lung adenocarcinoma, (2) the consistent absence of expression of TTF1 in the presence of expression of HepPar-1, (3) absence of EGFR driver mutations, and (4) frequent inactivating SMARCA4 mutations as underlying mechanism of the observed SMARCA4 protein loss. SMARCA4-deficient pulmonary adenocarcinoma is emerging as a distinctive, albeit phenotypically heterogeneous molecular subgroup of TTF1-negative NSCLC. Uniform HepPar-1 expression in this subset of NSCLC may represent a diagnostic pitfall and merits further studies to explore the mechanisms involved.
EVALuna2:34083

SMARCA4-deficient undifferentiated carcinoma of the ovary (small cell carcinoma, hypercalcemic type): clinicopathologic and immunohistochemical study of 3 cases - Agaimy, Abbas; Thiel, Falk; Hartmann, Arndt; Fukunaga, Masaharu (Annals of Diagnostic Pathology, 2015)
Small cell carcinoma of the ovary, hypercalcemic type is a very rare aggressive neoplasm of unknown histogenesis, affecting mainly girls and young women. Recently, inactivating mutations in SMARCA4 (BRG1), a member of the switch/sucrose nonfermenting chromatin remodeling complex, has been identified as driver events in most cases. We herein describe 3 cases in 34, 34, and 37-year-old women. Symptoms were mainly abdominal pain and mass. One patient was normocalcemic, and the other 2 had no preoperative serum calcium values available. All patients received radical hysterectomy with salpingo-oophorectomy, lymphadenectomy, and variable multimodality therapy. Two developed abdominal recurrences/metastases and died of disease at 4 and 12 months. One patient was alive without disease 17 months after surgery and radiochemotherapy. Histologic examination showed undifferentiated neoplasms composed of diffuse sheets, nests and cords of noncohesive monomorphic small blue/basaloid cells (classic variant, 1 case), and large undifferentiated/rhabdoid cells with abundant cytoplasm (large cell/rhabdoid variant, 2 case) admixed with minor small cell areas. One case contained rare isolated goblet cells, but true glandular component was absent. All tumors expressed vimentin and variably pancytokeratin and WT1. Nuclear SMARCB1 was intact in all cases (1 case showed small foci with mosaic loss). All tumors showed complete loss of SMARCA4. In conclusion, SMARCA4 immunohistochemistry represents a highly valuable emerging tool in identifying small cell carcinoma of the ovary, hypercalcemic type in routine practice. Distinguishing this aggressive neoplasm from juvenile granulosa cell tumor and other undifferentiated ovarian cancers is mandatory in selecting appropriate chemotherapeutic regimens and would allow better characterization of this entity, for which targeted molecular therapy still remains to be established.
EVALuna2:6715

SMARCB1(INI1)-deficient renal cell carcinoma: medullary and beyond Evolving concepts - Agaimy, Abbas; Hartmann, Arndt (Pathologe, 2021)
During the last decades, the SWI/SNF chromatin-remodeling complex has received enormous recognition as a major player in the molecular pathogenesis of diverse neoplasms. Accordingly, SWI/SNF defects affecting different subunits of the complex became defining genetic features in the nosology of different neoplastic entities. In the kidney, loss of SMARCB1(INI1) as a major component of the SWI/SNF complex has emerged as the defining genetic marker for renal medullary carcinoma and pediatric malignant rhabdoid tumor. Diagnosis of these two rare entities is based on a set of defined demographic, clinicopathological, immunophenotypic, and genetic (SMARCB1 loss) criteria. Moreover, the sickle cell trait is considered a prerequisite for renal medullary carcinoma. Current knowledge illustrates that SMARCB1 loss is encountered in three major tumor categories in the kidney: (1) histologically defined neoplasms that are primarily driven by de novo SMARCB1 loss (renal medullary carcinoma and malignant rhabdoid tumor); (2) SMRACB1-deficient renal cell carcinoma (RCC) with variable non-specific histology ranging from collecting duct-like, papillary high-grade (papillary type 2), or medullary-like (lacking sickle cell trait), to fully undifferentiated; and (3) biphasic (dedifferentiated) RCC showing a variable SMARCB1-deficient undifferentiated component. The latter variant most frequently originates from pre-existing clear cell RCC but may rarely superimpose on papillary or chromophobe RCC. This review summarizes the major defining features of the emerging SMARCB1-deficient renal neoplasms. All SMARCB1-deficient carcinomas have a poor prognosis in common. Therefore, exact diagnosis of these tumors is a prerequisite for studies investigating new therapies.
CRIS-Team WoS Importer:2021-10-15

SMARCB1(INI1)-deficient sinonasal basaloid carcinoma: a novel member of the expanding family of SMARCB1-deficient neoplasms - Agaimy, Abbas; Koch, Michael; Lell, Michael; Semrau, Sabine; Dudek, Wojciech; Wachter, David; Knöll, Antje; Iro, Heinrich; Haller, Florian; Hartmann, Arndt (American Journal of Surgical Pathology, 2014)
Poorly differentiated sinonasal carcinomas are a heterogenous group of aggressive neoplasms that encompasses squamous cell carcinoma including basaloid variant, lymphoepithelial carcinoma, sinonasal undifferentiated carcinoma, and neuroendocrine-type small cell carcinoma. We herein describe 3 cases of a hitherto unreported variant combining features of basaloid carcinoma with variable intermingled rhabdoid cells. Patients were 2 women (aged 28 and 35) and a man (52 y) who presented with sinonasal masses. All had advanced local disease with bone involvement (pT4). None had a history of irradiation or a family history of rhabdoid tumors. Treatment was surgery and adjuvant chemoradiation. One patient developed liver, lung, pleural, and pericardial metastases (63 mo) and is currently (70 mo) alive under palliative treatment. Another developed recurrent cervical lymph node metastases and died of disease 8.5 years later. The youngest patient was disease-free at last follow-up 7 years later. Histologic features were very similar in all 3 cases and showed intimate admixture of compact basaloid cell nests with peripheral palisading, perivascular pseudorosettes, and a few scattered rhabdoid cells. Rhabdoid cells were more extensive in the metastasis in 1 case but formed a minor inconspicuous component in the primary tumors in all cases. Striking features common to all cases were (1) basaloid "blue" appearance at low power, (2) papilloma-like exophytic component, (3) extensive pagetoid surface growth with prominent denuding features, and (4) replacement of underlying mucous glands mimicking an inverted papilloma. Clear-cut origin from benign papilloma and overt squamous differentiation were lacking. Diffuse (2) or partial (1) p16 expression was noted, but all cases lacked human papillomavirus DNA by molecular tests. In situ hybridization was negative for Epstein-Barr virus. Immunohistochemistry showed diffuse expression of pancytokeratin. CK5 and vimentin showed intermingling of CK5/vimentin basaloid and CK5/vimentin rhabdoid cells. Complete loss of nuclear SMARCB1 expression was seen in all cases including also the denuding carcinoma in situ-like surface lesions. To our knowledge, this variant of sinonasal carcinoma has not been reported before. The identical features in all 3 cases suggest a specific disease rather than a nonspecific dedifferentiated phenotype. Awareness of this rare variant and thus reporting of additional cases is necessary for defining its full morphologic and biological spectrum.
EVALuna2:6600

SMARCB1 (INI-1)-deficient Sinonasal Carcinoma: A Series of 39 Cases Expanding the Morphologic and Clinicopathologic Spectrum of a Recently Described Entity - Agaimy, Abbas; Hartmann, Arndt; Antonescu, Cristina R.; Chiosea, Simion I.; El-Mofty, Samir K.; Geddert, Helene; Iro, Heinrich; Lewis, James S.; Markl, Bruno; Mills, Stacey E.; Riener, Marc-Oliver; Robertson, Thomas; et al. (American Journal of Surgical Pathology, 2017)
To more fully characterize the clinical and pathologic spectrum of a recently described tumor entity of the sinonasal tract characterized by loss of nuclear expression of SMARCB1 (INI1), we analyzed 39 SMARCB1-deficient sinonasal carcinomas collected from multiple medical centers. The tumors affected 23 males and 16 females with an age range of 19 to 89 years (median, 52). All patients presented with locally advanced disease (T3, n=5; T4, n=27) involving the sinuses (mainly ethmoid) with variable involvement of the nasal cavity. Thirty patients received surgery and/or radiochemotherapy with curative intent. At last follow-up, 56% of patients died of disease 0 to 102 months after diagnosis (median, 15), 2 were alive with disease, and 1 died of an unrelated cause. Only 9 patients (30%) were alive without disease at last follow-up (range, 11 to 115 mo; median, 26). The original diagnosis of retrospectively identified cases was most often sinonasal undifferentiated carcinoma (n=14) and nonkeratinizing/basaloid squamous cell carcinoma (n=5). Histologically, most tumors displayed either a predominantly basaloid (61%) or plasmacytoid/rhabdoid morphology (36%). The plasmacytoid/rhabdoid form consisted of sheets of tumor cells with abundant, eccentrically placed eosinophilic cytoplasm, whereas similar cells were typically rare and singly distributed in the basaloid variant. Glandular differentiation was seen in a few tumors. None of the cases showed squamous differentiation or surface dysplasia. By immunohistochemistry, the tumors were positive for pancytokeratin (97%), CK5 (64%), p63 (55%), and CK7 (48%); and they were negative for NUT (0%). Epstein-Barr virus and high-risk human papillomavirus was not detected by in situ hybridization. Immunohistochemical loss of SMARCB1 (INI1) expression was confirmed for all 39 tumors. Investigation of other proteins in the SWI/SNF complex revealed co-loss of SMARCA2 in 4 cases, but none were SMARCA4 deficient or ARID1A deficient. Of 27 tumors with SMARCB1 fluorescence in situ hybridization analysis, 14 showed homozygous (biallelic) deletions and 7 showed heterozygous (monoallelic) deletions. SMARCB1-deficient sinonasal carcinoma represents an emerging poorly differentiated/undifferentiated sinonasal carcinoma that (1) cannot be better classified as another specific tumor type, (2) has consistent histopathologic findings (albeit with some variability) with varying proportions of plasmacytoid/rhabdoid cells, and (3) demonstrates an aggressive clinical course. This entity should be considered in any difficult-to-classify sinonasal carcinoma, as correct diagnosis will be mandatory for optimizing therapy and for further delineation of this likely underdiagnosed disease.
EVALuna2:6856

SMARCB1 (INI1)-negative rhabdoid carcinomas of the gastrointestinal tract: clinicopathologic and molecular study of a highly aggressive variant with literature review - Agaimy, Abbas; Rau, Tilman; Hartmann, Arndt; Stoehr, Robert (American Journal of Surgical Pathology, 2014)
Gastrointestinal (GI) neoplasms with rhabdoid features have been reported since 1989 under diverse names (giant cell carcinoma, pleomorphic carcinoma, malignant rhabdoid tumor, adenocarcinoma with rhabdoid features/phenotype, anaplastic carcinoma, etc.), but their clinicopathologic spectrum, SMARCB1 (INI1) status and relationship to common GI carcinomas have not been clarified yet. We describe 2 carcinomas from the stomach and the cecum with exclusive rhabdoid morphology. The patients died of disease at 6 and 10 months, respectively. The tumors coexpressed vimentin, pancytokeratin, and EMA. Both showed complete loss of nuclear SMARCB1/INI1. Molecular analysis (KRAS, EGFR, BRAF, PIK3CA, and microsatellite studies) revealed a CpG-island methylator phenotype in the cecal tumor (CIMP(+)/MLH1(-)/BRAF(V600E)/MSI-H), confirming epithelial origin. The gastric tumor showed poorly differentiated adenocarcinoma in regional nodes, again confirming epithelial derivation. Other genes tested were wild type in both cases. Review of reported cases (total: 39) revealed a glandular component in 33%. Affected sites are: stomach (13), colon (11), small bowel (10), and distal esophagus (5). Of the 34 patients with follow-up >=12 months, 29 (85%) died within 1 year (mean: 4 mo). Molecular tests were performed in 8/39 cases. A CIMP(+)/BRAF(V600E)/MLH1(-) phenotype was found in 3/4 right colon tumors. Loss of nuclear SMARCB1 protein was noted in 3/6 cases tested. This study highlights the heterogeneity of rhabdoid GI neoplasms and supports their epithelial derivation. Rhabdoid phenotype likely represents a common pathway of dedifferentiation with frequent loss of SMARCB1 and highly aggressive course. The CIMP phenotype represents a novel subset of rhabdoid GI carcinomas. This rare variant should be distinguished from proximal-type epithelioid sarcoma and other SMARCB1-deficient mimics.
EVALuna2:6589

Smoking status and PD-L1 mRNA-expression as a predictor of response to neoadjuvant chemotherapy in patients diagnosed with muscle invasive bladder cancer - Reike, Moritz; Juette, Hendrik; Wirtz, Ralph; Erben, Philipp; Tully, Karl; Eckstein, Markus; Weyerer, Veronika; Hartmann, Arndt; Kriegmair, Maximilian; Wezel, Felix; Bolenz, Christian; Tannapfel, Andrea; et al. (JOURNAL OF CLINICAL ONCOLOGY, 2020)
CRIS-Team WoS Importer:2020-05-22

Solitary fibrous tumors/hemangiopericytomas with different variants of the NAB2-STAT6 gene fusion are characterized by specific histomorphology and distinct clinicopathological features - Barthelmeß, Sarah; Geddert, Helene; Boltze, Carsten; Moskalev, Evgeny; Bieg, Matthias; Sirbu, Horia; Brors, Benedikt; Wiemann, Stefan; Hartmann, Arndt; Agaimy, Abbas; Haller, Florian (American Journal of Pathology, 2014)
Recurrent somatic fusions of the two genes, NGFI-A-binding protein 2 (NAB2) and STAT6, located at chromosomal region 12q13, have been recently identified to be presumable tumor-initiating events in solitary fibrous tumors (SFT). Herein, we evaluated a cohort of 52 SFTs/hemangiopericytomas (HPCs) by whole-exome sequencing (one case) and multiplex RT-PCR (all 52 cases), and identified 12 different NAB2-STAT6 fusion variants in 48 cases (92%). All 52 cases showed strong and diffuse nuclear positivity for STAT6 by IHC. We categorized the fusion variants according to their potential functional effects within the predicted fusion protein and found strong correlations with relevant clinicopathological features. Tumors with the most common fusion variant, NAB2ex4-STAT6ex2/3, corresponded to classic pleuropulmonary SFTs with diffuse fibrosis and mostly benign behavior and occurred in older patients (median age, 69 years). In contrast, tumors with the second most common fusion variant, NAB2ex6-STAT6ex16/17, were found in much younger patients (median age, 47 years) and represented typical HPCs from deep soft tissue with a more aggressive phenotype and clinical behavior. In summary, these molecular genetic findings support the concept that classic pleuropulmonary SFT and deep-seated HPC are separate entities that share common features but correlate to different clinical outcome.
EVALuna2:6577

Spatial distribution of FoxP3+ and CD8+ tumour infiltrating T cells reflects their functional activity - Posselt, Rebecca; Erlenbach-Wuensch, Katharina; Haas, Matthias; Jeßberger, Jonas; Buettner-Herold, Maike; Haderlein, Marlen; Hecht, Markus; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Oncotarget, 2016)
Regulatory and cytotoxic T cells are key players in the host's anticancer immune response. We studied the spatial distribution of FoxP+ and CD8+ cells to identify potential interactions.In 202 patients 103 pre-radiochemotherapy biopsies and 153 post-radiochemotherapy tumour specimens of advanced rectal cancer were available and an immunohistochemical double staining of FoxP3+ and CD8+ tumour-infiltrating lymphocytes was performed to investigate cell density and cell-to-cell distances.FoxP3+ cells decreased after radiochemotherapy by a factor of 3 while CD8+ cells remained nearly unchanged. High epithelial (p=0.033) and stromal (p=0.009) FoxP3+ cell density was associated with an improved overall survival. Cell-to-cell distances of randomly distributed cells were simulated and compared to observed cell-to-cell distances. Observed distances shorter than the simulated, random distances were hypothesized to represent FoxP3+ cells actively interacting with CD8+ cells. Epithelial short distances were associated with a favourable prognosis while the opposite was true for the stromal compartment.The analysis of cell-to-cell distances may offer a tool to predict outcome, maybe by identifying functionally active, interacting infiltrating inflammatory cells in different tumour compartments.
EVALuna2:6815

Spatial expression of claudin 18.2 in matched primaries and metastases of tubo-ovarian carcinoma of all subtypes - Wagner, Paul; Gaß, Paul; Pöschke, Patrik; Eckstein, Markus; Gloßner, Laura; Hartmann, Arndt; Beckmann, Matthias; Fasching, Peter; Rübner, Matthias; Emons, Julius; Erber, Ramona (Virchows Archiv, 2024)
Physiologically, claudin 18 splice variant 2 (CLDN18.2) expression is restricted to the gastric epithelium, but its expression has been detected in solid cancers. Zolbetuximab, a chimeric IgG1 antibody targeting CLDN18.2, has demonstrated promising effects in patients suffering from CLDN18.2-positive, HER2-negative locally advanced gastric cancer and is currently being studied further. To date, little is known about CLDN18.2 expression in other histological subtypes of tubo-ovarian carcinoma (TOC) and their matching metastases. Using a cohort of all histological TOC subtypes, we investigated the immunohistochemical (IHC) CLDN18.2 expression in both TOCs (n = 536), their matching metastatic tissue (n = 385) and in 93 metastases without primary. Tissue microarrays comprised both the tumor center and periphery. IHC positivity was defined as biomarker expression of ≥ 75% in tumor cells with moderate-to-strong membranous staining. Overall CLDN18.2 positivity was 4.1% (21/515) in the TOC centers and 3.6% (18/498) in their peripheries. In primaries of mucinous tubo-ovarian carcinoma (MTOC), CLDN18.2 positivity rates were 45% (18/40) and 36.6% (15/41), respectively. Positivity rates for the corresponding metastases were 33% (4/12, center) and 27% (3/11, periphery). The expression was relatively homogenous throughout all tumor sites. With no expression in 99.5% of nonmucinous tumors, CLDN18.2 positivity was almost exclusively seen in the mucinous subtype. In tubo-ovarian carcinoma, CLDN18.2 expression was, with rare exceptions, restricted to the mucinous subtype. Among them, 33% of metastasized MTOCs presented with CLDN18.2 positivity. Hence, CLDN18.2 might display a promising target for personalized therapy in patients with advanced MTOC.
CRIS-Team Scopus Importer:2024-02-16
Keywords: CLDN18.2; Immunohistochemistry; Mucinous tubo-ovarian carcinoma; Targeted therapy; Tubo-ovarian cancer

Spatial Immunephenotypes of Distant Metastases but not Matched Primary Urothelial Carcinomas Predict Response to Immune Checkpoint Inhibition - Erlmeier, Franziska; Klümper, Niklas; Landgraf, Laura; Strissel, Pamela; Strick, Reiner; Sikic, Danijel; Taubert, Helge; Wach, Sven; Geppert, Carol-Immanuel; Bahlinger, Veronika; Breyer, Johannes; Ritter, Manuel; et al. (European Urology, 2022)
Background: The value of programmed cell death ligand-1 (PD-L1) to predict durable responses to immune checkpoint inhibitors (ICIs) in metastatic urothelial carcinoma (mUC) is inconsistent. We hypothesize that the use of archived primary tumor material (PRIM) for PD-L1 testing in clinical trials not properly reflecting the metastatic disease status (MET) contributes to this clinical issue. Objective: To analyze the predictive and prognostic value of PD-L1, spatial immunephenotypes, and major histocompatibility complex class I (MHC-I) determined in patient-matched PRIM/MET. Design, setting, and participants: PD-L1, spatial immunephenotypes, and MHC-I were examined in 154 mUC patients with at least one available pretreatment MET (138 patient-matched PRIM/MET pairs). Outcome measurements and statistical analysis: PD-L1, spatial immunephenotype, and MHC-I status of (patient-matched PRIM and) pretreatment MET were correlated with chemotherapy and ICI response and outcomes. Results and limitations: Discordance rates in patient-matched PRIM/MET were 25/30%, 36%, and 49% for PD-L1 (CPS10/IC5%), immunephenotypes, and MHC-I (loss vs preserved), respectively. Correlations with chemotherapy and ICI responses were observed for immunephenotypes and MHC-I status determined in MET (not for PD-L1 alone), but not in PRIM. In case of ICIs, patients with cytotoxic tumor immune microenvironment (TIME) showed durable responses with disease control rates of 90% and a hazard ratio for disease progression/death of 0.05 (95% confidence interval: 0.01–0.65) versus patients with immunedepleted MET (disease control rate 29%). MET MHC-I status added an incremental value to predict durable ICI responses. Limitations include the partly retrospective design and the lack of MET multisampling on individual patient level. Conclusions: The TIME is subject to substantial dynamics during metastatic evolution. MET immunephenotypes and MHC-I statuses show promising potential to predict chemotherapy and durable ICI responses, while the PRIM TIME does not. Thus, future clinical trials should rather rely on pretreatment MET biopsies reflecting the current immunological disease state than on PRIM. Patient summary: Prediction of chemotherapy and responses to immune checkpoint inhibitors might be possible using representative pretreatment metastatic biopsies.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Immune microenvironment; Immune therapy; Metastatic urothelial cancer; Subtypes; Urothelial cancer

Species-, organ- and cell-type-dependent expression of SPARCL1 in human and mouse tissues. - Klingler, Anika; Regensburger, Daniela; Tenkerian, Clara; Britzen-Laurent, Nathalie; Hartmann, Arndt; Stürzl, Michael; Naschberger, Elisabeth (PLoS ONE, 2020)
SPARCL1 is a matricellular protein with anti-adhesive, anti-proliferative and anti-tumorigenic functions and is frequently downregulated in tumors such as colorectal carcinoma or non-small cell lung cancer. Studies have identified SPARCL1 as an angiocrine tumor suppressor secreted by tumor vessel endothelial cells, thereby exerting inhibitory activity on angiogenesis and tumor growth, in colorectal carcinoma. It is unknown whether SPARCL1 may exert these homeostatic functions in all organs and in other species. Therefore, SPARCL1 expression was comparatively analysed between humans and mice in a systematic manner. Murine Sparcl1 (mSparcl1) is most strongly expressed in the lung; expressed at an intermediate level in most organs, including the large intestine; and absent in the liver. In human tissues, SPARCL1 (hSPARCL1) was detected in all organs, with the strongest expression in the stomach, large intestine and lung, mostly consistent with the murine expression pattern. A striking difference between human and murine tissues was the absence of mSparcl1 expression in murine livers, while human livers showed moderate expression. Furthermore, mSparcl1 was predominantly associated with mural cells, whereas hSPARCL1 was detected in both mural and endothelial cells. Human SPARCL1 expression was downregulated in different carcinomas, including lung and colon cancers. In conclusion, this study revealed species-, organ- and cell-type-dependent expression of SPARCL1, suggesting that its function may not be similar between humans and mice.

Specific types of bladder cancer - Bertz, Simone; Hartmann, Arndt; Knuechel-Clarke, R.; Gaisa, N. T. (Pathologe, 2016)
Bladder cancer shows rare variants and special subtypes with diverse prognostic importance and therefore may necessitate different therapeutic approaches. For pathologists it is important to histologically diagnose and specify such variants. Nested variants of urothelial carcinoma with inconspicuous, well-formed tumor cell nests present with an aggressive course. The plasmacytoid variant, which morphologically resembles plasma cells is associated with a shorter survival time and a high frequency of peritoneal metastasis. Micropapillary urothelial carcinoma with small papillary tumor cell islands within artificial tissue retraction spaces and frequent lymphovascular invasion also has a poor prognosis. Other important rare differential variants listed in the World Health Organization (WHO) classification are microcystic, lymphoepithelioma-like, sarcomatoid, giant cell and undifferentiated urothelial carcinomas. Additionally, there are three special types of bladder cancer: squamous cell carcinoma, adenocarcinoma and small cell neuroendocrine carcinoma of the bladder. These tumors are characterized by pure squamous cell or glandular differentiation and are sometimes less responsive to adjuvant (chemo)therapy. Small cell carcinoma of the bladder mimics the neuroendocrine features of its pulmonary counterpart, shows an aggressive course but is sensitive to (neo-)adjuvant chemotherapy. The morphology and histology of the most important variants and special types are discussed in this review.
EVALuna2:6786

Spread through Air Spaces (STAS) in Solitary Pulmonary Metastases from Colorectal Cancer (CRC) - Haj Khalaf, Mohamed; Sirbu, Horia; Hartmann, Arndt; Agaimy, Abbas; Dudek, Wojciech; Higaze, Mostafa; Rieker, Ralf (Thoracic and Cardiovascular Surgeon, 2022)
Background Spread through air spaces (STAS) is a recently described route of tumor invasion associated with poor prognosis in primary lung cancer. Aim of this study was to investigate the presence of STAS and to assess its prognostic significance in patients undergoing pulmonary metastasectomy (PM) for solitary metastases from colorectal cancer (CRC). Materials and Methods All 49 CRC patients (30 male and 19 female, median age 66 years) who underwent PM between January 2008 and December 2015 were retrospectively analyzed. Results STAS was identified in 26.5% ( n = 13) of resected specimens. Location of pulmonary lesions (central vs. peripheral) was assessed based on the available computed tomography imaging ( n = 47, 96%). STAS was detected in all five patients with central metastases (100%) versus 7 of 42 (17%) with peripheral metastases ( p = 0.0001). Locoregional recurrence occurred in STAS-positive patients ( n = 4 of 13 vs. n = 0 of 36), all STAS-negative patients remained recurrence-free ( p = 0.003). Median number of alveoli with STAS involvement was four (range from 2 to 9). There was statistically positive relationship between the number of alveoli invaded with STAS and locoregional recurrence of metastases ( p = 0.0001). The presence of STAS is not a factor affecting the 5-year overall survival rate ( p = 0.6651). Conclusion We identified STAS as a frequent finding in resected CRC lung metastases and found insignificant association with outcome.
CRIS-Team WoS Importer:2022-10-28

Standardized 18F-FDG PET/CT radiomic features provide information on PD-L1 expression status in treatment-naive patients with non-small cell lung cancer - Zhang, Ruiyun; Hohenforst-Schmidt, Wolfgang; Steppert, Claus; Sziklavari, Zsolt; Schmidkonz, Christian; Atzinger, Armin; Kuwert, Torsten; Klink, Thorsten; Sterlacci, William; Hartmann, Arndt; Vieth, Michael; Foerster, Stefan (Nuklearmedizin-Nuclear Medicine, 2022)
Purpose To study the relationship between standardized 18F-FDG PET/CT radiomic features and clinicopathological variables and programmed death ligand-1 (PD-L1) expression status in non-small cell lung cancer (NSCLC) patients. Methods 58 NSCLC patients with preoperative 18F-FDG PET/CT scans and postoperative results of PD-L1 expression were retrospectively analysed. A standardized, open-source software was used to extract 86 radiomic features from PET and low-dose CT images. Univariate analysis and multivariate logistic regression were used to find independent predictors of PD-L1 expression. The Area Under the Curve (AUC) of receiver operating characteristic (ROC) curve was used to compare the ability of variables and their combination in predicting PD-L1 expression. Results Multivariate logistic regression resulted in the PET radiomic feature GLRLM_LGRE (Odds Rate (OR): 0.300 vs 0.114, 95% confidence interval (CI): 0.096-0.931 vs 0.021-0.616, in NSCLC and adenocarcinoma respectively) and the CT radiomic feature GLZLM_SZE (OR: 3.338 vs 7.504, 95%CI: 1.074-10.375 vs 1.382-40.755, in NSCLC and adenocarcinoma respectively), being independent predictors of PD-L1 status. In NSCLC group, after adjusting for gender and histology, the PET radiomic feature GLRLM_LGRE (OR: 0.282, 95%CI: 0.085-0.936) remained an independent predictor for PD-L1 status. In the adenocarcinoma group, when adjusting for gender the PET radiomic feature GLRLM_LGRE (OR: 0.115, 95%CI: 0.021-0.631) and the CT radiomic feature GLZLM_SZE (OR: 7.343, 95%CI: 1.285-41.965) remained associated with PD-L1 expression. Conclusion NSCLC and adenocarcinoma with PD-L1 expression show higher tumour heterogeneity. Heterogeneity-related 18F-FDG PET and CT radiomic features showed good ability to non-invasively predict PD-L1 expression.
CRIS-Team WoS Importer:2022-07-29

Standardized Procedures for Patients with Dysplasia and Other Diseases of the Cervix, Vulva, and Vagina at a Certified Dysplasia Unit Prior to the Introduction of the Organized Cervical Cancer Screening Program. - Schulmeyer, Carla; Koch, Martin C.; Dietl, Anna; Stübs, Frederik; Behrens, Annika; Renner, Simone K.; Mehlhorn, Grit; Geppert, Carol-Immanuel; Hartmann, Arndt; Beckmann, Matthias; Gaß, Paul (Geburtshilfe und Frauenheilkunde, 2023)
Introduction Gynecologic dysplasia units and dysplasia consultations are obliged to offer diagnosis and treatment in accordance with the guidelines. The organization of the consultation process, management of patient appointments, diagnosis, and treatment algorithms are heterogeneous. The legislation arising from the new Federal Joint Committee decision, dated 22 November 2018, concerning the organized cervical cancer screening program has been in force since 1 January 2020. In this article we provide an overview of the existing structures and interdisciplinary cooperation of specialized dysplasia units incorporated in certified gynecologic cancer center. Materials and Methods We carried out a retrospective database search of data collected prospectively from 1 July 2014 to 31 December 2019 at the dysplasia unit at the Department of Gynecology and Obstetrics, Erlangen University Hospital, which was the first dysplasia unit to be certified in 2014. Results A total of 5594 patients presented at the unit, and 16061 colposcopic, vulvoscopic, and anoscopic examinations were performed. Approximately 4100 examinations of the cervix, vagina, vulva, and anus are carried out each year, 1600 of these were exclusively cervix colposcopies. A total of 12197 cytology results were assessed, as well as 4850 histology results, and 8193 high-risk HPV tests. The quality indicators required by the dysplasia unit for annual recertification were met each year. Conclusion Certified dysplasia units and consultations form the central component in the algorithm for further investigating abnormal screening results; but they are also the first point of contact for a large number of patients with acute or chronic complaints in the genital region.
EVALuna2:542837

STAT3 activation through IL-6/IL-11 in cancer-associated fibroblasts promotes colorectal tumour development and correlates with poor prognosis - Heichler, Christina; Scheibe, Kristina; Schmied, Anabel; Geppert, Carol-Immanuel; Schmid, Benjamin; Wirtz, Stefan; Thoma, Oana Maria; Kramer, Viktoria; Waldner, Maximilian; Büttner, Christian; Farin, Henner; Pešić, Marina; et al. (Gut, 2019)
Objective: Cancer-associated fibroblasts (CAFs) influence the tumour microenvironment and tumour growth. However, the role of CAFs in colorectal cancer (CRC) development is incompletely understood. Design: We quantified phosphorylation of STAT3 (pSTAT3) expression in CAFs of human colon cancer tissue using a tissue microarray (TMA) of 375 patients, immunofluorescence staining and digital pathology. To investigate the functional role of CAFs in CRC, we took advantage of two murine models of colorectal neoplasia and advanced imaging technologies. In loss-of-function and gain-of-function experiments, using genetically modified mice with collagen type VI (COLVI)-specific signal transducer and activator of transcription 3 (STAT3) targeting, we evaluated STAT3 signalling in fibroblasts during colorectal tumour development. We performed a comparative gene expression profiling by whole genome RNA-sequencing of fibroblast subpopulations (COLVI+ vs COLVI-) on STAT3 activation (IL-6 vs IL-11). Results: The analysis of pSTAT3 expression in CAFs of human TMAs revealed a negative correlation of increased stromal pSTAT3 expression with the survival of colon cancer patients. In the loss-of-function and gain-of-function approach, we found a critical role of STAT3 activation in fibroblasts in driving colorectal tumourigenesis in vivo. With different imaging technologies, we detected an expansion of activated fibroblasts in colorectal neoplasias. Comparative gene expression profiling of fibroblast subpopulations on STAT3 activation revealed the regulation of transcriptional patterns associated with angiogenesis. Finally, the blockade of proangiogenic signalling significantly reduced colorectal tumour growth in mice with constitutive STAT3 activation in COLVI+ fibroblasts. Conclusion: Altogether our work demonstrates a critical role of STAT3 activation in CAFs in CRC development.
CRIS-Team Scopus Importer:2019-11-19
Keywords: colorectal cancer

Status der Verfügbarkeit und Anwendung von „next generation sequencing“ (NGS) beim Harnblasenkarzinom – eine Umfrage in der Arbeitsgemeinschaft Uropathologie - Ortiz-Brüchle, N.; Muders, M.; Toma, M.; Esposito, I.; Hartmann, Arndt; Stöhr, Robert; Reis, H.; Wild, P.; Köllermann, J.; Bremmer, F.; Leichsenring, J.; Stenzinger, A.; et al. (Urologe, 2019)
Background: Technical advancement and availability of high-throughput analysis has advanced molecular subtyping of most cancers. Thus, new possibilities for precision oncology have emerged. Aim: Therefore, we aimed to collect data regarding availability and use of next generation sequencing (NGS) for urothelial cancer within the uropathology working group of the German Society of Pathology. Methods: We collected data by questionnaires and additionally asked for sequencing results of bladder cancers in the participating institutions. Results: A total of 13 university-affiliated institutes of pathology took part in the survey. All university institutes offer NGS-based molecular panel diagnostics and provide panels covering between 15 and 170 genes. Altogether, only 20 bladder cancers were sequenced in routine diagnostics and for 10 cancers potential targeted treatment options were available. Discussion: So far, despite availability of NGS diagnostics at university institutes of pathology, only few bladder cancer samples have been sequenced. Based on current data from the molecular subtyping of bladder cancers, we recommend a step-by-step protocol with basic immunohistochemistry analysis and subsequent subtype-dependent analyses, e.g., alterations of the fibroblast growth factor receptors (FGFR) or comprehensive gene panel analyses.
CRIS-Team Scopus Importer:2019-11-05
Keywords: Bladder cancer; Molecular pathology; Next generation sequencing; Precision oncology; Targeted treatment

Subclassification, survival prediction and drug target analyses of chemotherapy-naïve muscle-invasive bladder cancer with a molecular screening - Rinaldetti, Sebastien; Rempel, Eugen; Worst, Thomas Stefan; Eckstein, Markus; Steidler, Annette; Weiss, Cleo Aaron; Bolenz, Christian; Hartmann, Arndt; Erben, Philipp (Oncotarget, 2018)
Background: Transcriptome expression studies identified distinct muscle invasive bladder cancer (MIBC) subtypes closely related with breast cancer subclasses. Here we developed a sensitive quantification method for MIBC subclassification (luminal, basal, p53-like). In addition, the subtype specific expression of drug targets has been investigated. Methods: Absolute quantification (nCounter) of a 64-gene panel was performed on MIBC patients (n=47) treated exclusively with radical cystectomy (RC). In conjunction of 170 MIBCs from 3 independent cohorts, a minimal set of consensus genes has been established. Survival of the consensus subtypes has been assessed by multivariate analysis. Relevant drug targets were tested for their subtype specificity in a clustering independent assessment. Results: A reduced 36-gene panel stably clustered into 3 subtypes throughout the cohorts (luminal, basal, infiltrated). Patients treated by RC only, showed worst 8-year disease specific survival (DSS) for the luminal subtype in contrast to the infiltrated subtype (17% vs. 73%, p=0.011). In multivariate analyses, the risk stratification based on luminal versus not-luminal MIBC proved to be an independent predictor for DSS superior to the TNM system in patients with RC. Drug targets (e.g. ERBB2, FGFR, AR, PDGFRB) showed a distinct subtype attribution. The subtypes based on this nCounter screening could further be validated by the TCGA cohort. Conclusion: This MIBC subtype screening predicted survival and allowed an analysis of subtype specific drug targets, thus being a powerful tool for the translation of personalized MIBC treatment concepts.
EVALuna2:34813

Subtype specific expression and survival prediction of pivotal lncRNAs in muscle invasive bladder cancer - Rinaldetti, Sebastien; Worst, Thomas Stefan; Rempel, Eugen; Kriegmair, Maximilian C.; Hartmann, Arndt; Porubsky, Stefan; Bolenz, Christian; Erben, Philipp (Scientific Reports, 2020)
Comprehensive transcriptome expression analyses of bladder cancer revealed distinct lncRNA clusters with differential molecular and clinical characteristics. In this study, pivotal lncRNAs were assessed for their impact on survival and their differential expression between the molecular bladder cancer subtypes. FFPE samples from chemotherapy-naïve patients with muscle invasive bladder cancer (MIBC) were analyzed on the Nanostring nCounter platform for absolute quantification. An established 36-gene panel was used for molecular subtype classification into basal, luminal and infiltrated MIBC. In a second step, 14 pivotal lncRNAs were assessed for their molecular subtype attribution, and their predictive value in disease-specific survival. In silico validation was performed on a total of 487 MIBC patients (MDA, TGCA and Chungbuk cohort). Several pivotal lncRNAs showed a distinct molecular subtype attribution: e.g. MALAT1 showed a downregulation in the basal subtype (p = 0.009), TUG1 and CBR3AS1 showed an upregulation in the luminal subtype (p ≤ 0.001). High transcript levels of SNHG16, CBR3AS1 and H19 appeared to be predictive for a shorter disease-specific survival. Patients overexpressing putative oncogenes MALAT1 and TUG1 in MIBC tissue presented prolonged survival, suggesting tumor suppressive effects of both lncRNAs. The Nanostring nCounter proved to be a valid platform for the quantification of low-abundance transcripts including lncRNAs.
CRIS-Team Scopus Importer:2020-12-04

Successful Targeting of BRAF V600E Mutation With Vemurafenib in a Treatment-Resistant Extragonadal Nonseminomatous Germ-Cell Tumor - Meintker, Lisa; Haller, Florian; Tögel, Lars; Schmidt, Daniela; Waibel, Heidi; Hartmann, Arndt; Mackensen, Andreas; Meidenbauer, Norbert (JCO Precision Oncology, 2020)

Succinate dehydrogenase (SDH)-deficient renal carcinoma: a morphologically distinct entity: a clinicopathologic series of 36 tumors from 27 patients - Gill, Anthony J.; Hes, Ondrej; Papathomas, Thomas; Sedivcova, Monika; Tan, Puay Hoon; Agaimy, Abbas; Andresen, Per Arne; Kedziora, Andrew; Clarkson, Adele; Toon, Christopher W.; Sioson, Loretta; Watson, Nicole; et al. (American Journal of Surgical Pathology, 2014)
Succinate dehydrogenase (SDH)-deficient renal carcinoma has been accepted as a provisional entity in the 2013 International Society of Urological Pathology Vancouver Classification. To further define its morphologic and clinical features, we studied a multi-institutional cohort of 36 SDH-deficient renal carcinomas from 27 patients, including 21 previously unreported cases. We estimate that 0.05% to 0.2% of all renal carcinomas are SDH deficient. Mean patient age at presentation was 37 years (range, 14 to 76 y), with a slight male predominance (M:F=1.7:1). Bilateral tumors were observed in 26% of patients. Thirty-four (94%) tumors demonstrated the previously reported morphology at least focally, which included: solid or focally cystic growth, uniform cytology with eosinophilic flocculent cytoplasm, intracytoplasmic vacuolations and inclusions, and round to oval low-grade nuclei. All 17 patients who underwent genetic testing for mutation in the SDH subunits demonstrated germline mutations (16 in SDHB and 1 in SDHC). Nine of 27 (33%) patients developed metastatic disease, 2 of them after prolonged follow-up (5.5 and 30 y). Seven of 10 patients (70%) with high-grade nuclei metastasized as did all 4 patients with coagulative necrosis. Two of 17 (12%) patients with low-grade nuclei metastasized, and both had unbiopsied contralateral tumors, which may have been the origin of the metastatic disease. In conclusion, SDH-deficient renal carcinoma is a rare and unique type of renal carcinoma, exhibiting stereotypical morphologic features in the great majority of cases and showing a strong relationship with SDH germline mutation. Although this tumor may undergo dedifferentiation and metastasize, sometimes after a prolonged delay, metastatic disease is rare in the absence of high-grade nuclear atypia or coagulative necrosis.
EVALuna2:6664

SUNNIFORECAST - A phase II study of Nivolumab in combination with Ipilimumab versus Standard of care in advanced or metastatic non-clear cell renal cell carcinoma - Scheich, S.; Ahrens, M.; Goekbuget, N.; Boleti, E.; Burkholder,; Escudier, B. J.; Goebell, Peter; Gruenwald,; Gschwend, J.; Retz, M.; Hartmann, Arndt; Maroto Rey, J. P.; et al. (2018)
EVALuna2:35894

Superpixel Pre-segmentation of HER2 Slides for Efficient Annotation - Öttl, Mathias; Mönius, Jana; Marzahl, Christian; Rübner, Matthias; Geppert, Carol-Immanuel; Hartmann, Arndt; Beckmann, Matthias; Fasching, Peter; Maier, Andreas; Erber, Ramona; Breininger, Katharina (Informatik aktuell, 2022)
Supervised deep learning has shown state-of-the-art performance for medical image segmentation across different applications, including histopathology and cancer research; however, the manual annotation of such data is extremely laborious. In this work, we explore the use of superpixel approaches to compute a pre-segmentation of HER2 stained images for breast cancer diagnosis that facilitates faster manual annotation and correction in a second step. Four methods are compared: standard simple linear iterative clustering (SLIC) as a baseline, a domain adapted SLIC, and superpixels based on feature embeddings of a pretrained ResNet-50 and a denoising autoencoder. To tackle oversegmentation, we propose to hierarchically merge superpixels, based on their content in the respective feature space. When evaluating the approaches on fully manually annotated images, we observe that the autoencoder-based superpixels achieve a 23% increase in boundary F1 score compared to the baseline SLIC superpixels. Furthermore, the boundary F1 score increases by 73% when hierarchical clustering is applied on the adapted SLIC and the autoencoder-based superpixels. These evaluations show encouraging first results for a pre-segmentation for efficient manual refinement without the need for an initial set of annotated training data.<br
CRIS-Team Scopus Importer:2022-05-06

Surgical and oncological outcome after extended lymph node dissection for carcinoma of the stomach and the esophagogastric junction: a retrospective analysis from an experienced single center - Raptis, Dimitrios; Maak, Matthias; Krautz, Christian; Merkel, Susanne; Brunner, Maximilian; Agaimy, Abbas; Hartmann, Arndt; Semrau, Sabine; Ott, Oliver; Fietkau, Rainer; Siebler, Jürgen; Grützmann, Robert; et al. (Archives of Medical Science, 2024)
Introduction: Gastric cancer remains the fourth leading cause of cancer-related death in Europe, while the proportion of adenocarcinomas of the esophagogastric junction has risen by more than one third over recent years. In 2018, 14,700 new cases of gastric cancer were estimated in Germany, while the 5-year relative survival rate is reported to be 33% for women and 30% for men; in the USA almost the same rate was reported, with 31% 5-year survival. Material and methods: Between 2001 and 2014, 590 patients with a diagnosis of gastric cancer underwent surgery in our institution, including 120 Siewert type II/III carcinomas of the esophagogastric junction. All patients underwent distal resection of the stomach, gastrectomy or total gastrectomy combined with transhiatal distal esophageal resection. All operations included D2-D3 lymph node dissection (LND). Data were recorded by the cancer registry of the department of surgery and analyzed retrospectively. Results: The patients were classified according to the TNM (UICC 2010) and Lauren classification. 29% of the patients underwent primary surgery and 31% received neoadjuvant therapy. The median number of harvested lymph nodes was 33 for patients diagnosed with gastric cancer, and 29 for esophagogastric adenocarcinomas, respectively. The anastomotic leak rate was 3%. In this study, the 5-year overall survival rate was 51% concerning gastric carcinomas, 44% for Siewert type II and 47% for Siewert III cancers of the esophagogastric junction. Conclusions: Increased survival with low complication rates were achieved after individualized and multimodal treatment concepts combined with consistently applied extended lymphadenectomy.
CRIS-Team Scopus Importer:2024-04-19
Keywords: D3 dissection; gastric cancer; Siewert II/III

Survival advantage of partial over radical nephrectomy in patients presenting with localized renal cell carcinoma - Roos, Frederik C.; Steffens, Sandra; Junker, Kerstin; Janssen, Martin; Becker, Frank; Wegener, Gerd; Brenner, Walburgis; Steinestel, Julie; Schnoeller, Thomas J.; Schrader, Mark; Hofmann, Rainer; Thueroff, Joachim W.; et al. (BMC Cancer, 2014)
Partial nephrectomy (PN) preserves renal function and has become the standard approach for T1a renal cell carcinoma (RCC). However, there is still an ongoing debate as to which patients will actually derive greater benefit from partial than from radical nephrectomy (RN). The aim of this study was to retrospectively evaluate the impact of the type of surgery on overall survival (OS) in patients with localized RCC.Renal surgery was performed in 4326 patients with localized RCC (pT <= 3a N/M0) at six German tertiary care centers from 1980 to 2010: RN in 2955 cases (68.3%), elective (ePN) in 1108 (25.6%), and imperative partial nephrectomy (iPN) in 263 (6.1%) cases. The median follow-up for all patients was 63 months. Kaplan-Meier and Cox regression analyses were carried out to identify prognosticators for OS.PN was performed significantly more often than RN in patients presenting with lower tumor stages, higher RCC differentiation, and non-clear cell histology. Accordingly, the calculated 5 (10)-year OS rates were 90.0 (74.6)% for ePN, 83.9 (57.5)% for iPN, and 81.2 (64.7)% for RN (p < 0.001). However, multivariate analysis including age, sex, tumor diameter and differentiation, histological subtype, and the year of surgery showed that ePN compared to RN still qualified as an independent factor for improved OS (HR 0.79, 95% CI 0.66-0.94, p = 0.008).Even allowing for the weaknesses of this retrospective analysis, our multicenter study indicates that in patients with localized RCC, PN appears to be associated with better OS than RN irrespective of age or tumor size.
EVALuna2:6665

Survival Prediction of Clear Cell Renal Cell Carcinoma Based on Gene Expression Similarity to the Proximal Tubule of the Nephron - Buettner, Florian; Winter, Stefan; Rausch, Steffen; Reustle, Anna; Kruck, Stephan; Junker, Kerstin; Stenzl, Arnulf; Agaimy, Abbas; Hartmann, Arndt; Bedke, Jens; Schwab, Matthias; Schaeffeler, Elke (European Urology, 2015)
There is evidence that molecular features support subclassification of tumours, thereby improving prediction of patient outcome. Currently, two gene expression signatures (ccA/ccB and ClearCode34) have been established to classify clear cell renal cell carcinoma (ccRCC). Because RCC arises from nephron cell types, we aimed to explore its heterogeneity on a molecular level by comparing gene expression between tumour tissue and nephron regions. Based on genes that differ in expression between nephron regions, expression data of 479 ccRCCs and 212 papillary and 66 chromophobe RCCs from The Cancer Genome Atlas were correlated to those of nephron cell types. Cancer-specific survival (CSS) of ccRCC patients was significantly associated with gene expression similarity to the proximal tubules. Subsequently, a ccRCC risk score (S3-score) was established. Survival analyses indicated that the S3-score was significantly associated with CSS considering all cases of ccRCC, as well as metastatic and nonmetastatic ccRCC. Results could be validated in an independent cohort. The S3-score significantly improved the predictive ability of the ccA/ccB and ClearCode34 signatures, and the clinicopathologic-based stage, size, grade, and necrosis score (p [chi-square] = 1.56E-04). Intratumour heterogeneity of the S3-score was observed in 6 of 10 ccRCCs. In summary, the nephron-based S3-score enables prognostic risk stratification for ccRCC. Further studies are needed to evaluate its clinical utility.We developed a novel risk score for clear cell renal cell carcinoma to identify patients at risk of worse outcome that may improve patient care in the future.
EVALuna2:6770

Susceptibility gene mutations in germline and tumors of patients with HER2-negative advanced breast cancer - Fasching, Peter; Hu, Chunling; Hart, Steven N.; Rübner, Matthias; Polley, Eric C.; Gnanaolivu, Rohan D.; Hartkopf, Andreas D.; Hübner, Hanna; Janni, Wolfgang; Hadji, Peyman; Tesch, Hans; Uhrig, Sabrina; et al. (npj Breast Cancer, 2024)
Germline mutations in BRCA1 and BRCA2 (gBRCA1/2) are required for a PARP inhibitor therapy in patients with HER2-negative (HER2−) advanced breast cancer (aBC). However, little is known about the prognostic impact of gBRCA1/2 mutations in aBC patients treated with chemotherapy. This study aimed to investigate the frequencies and prognosis of germline and somatic BRCA1/2 mutations in HER2- aBC patients receiving the first chemotherapy in the advanced setting. Patients receiving their first chemotherapy for HER2- aBC were retrospectively selected from the prospective PRAEGNANT registry (NCT02338167). Genotyping of 26 cancer predisposition genes was performed with germline DNA of 471 patients and somatic tumor DNA of 94 patients. Mutation frequencies, progression-free and overall survival (PFS, OS) according to germline mutation status were assessed. gBRCA1/2 mutations were present in 23 patients (4.9%), and 33 patients (7.0%) had mutations in other cancer risk genes. Patients with a gBRCA1/2 mutation had a better OS compared to non-mutation carriers (HR: 0.38; 95%CI: 0.17–0.86). PFS comparison was not statistically significant. Mutations in other risk genes did not affect prognosis. Two somatic BRCA2 mutations were found in 94 patients without gBRCA1/2 mutations. Most frequently somatic mutated genes were TP53 (44.7%), CDH1 (10.6%) and PTEN (6.4%). In conclusion, aBC patients with gBRCA1/2 mutations had a more favorable prognosis under chemotherapy compared to non-mutation carriers. The mutation frequency of 5% with gBRCA1/2 mutations together with improved outcome indicates that germline genotyping of all metastatic patients for whom a PARP inhibitor therapy is indicated should be considered.
CRIS-Team Scopus Importer:2024-07-19

Swi/snf alterations in squamous bladder cancers - Achenbach, Fabian; Rose, Michael; Ortiz-Brüchle, Nadina; Seillier, Lancelot; Knüchel, Ruth; Weyerer, Veronika; Hartmann, Arndt; Morsch, Ronja; Maurer, Angela; Ecke, Thorsten H.; Garczyk, Stefan; Gaisa, Nadine T. (Genes, 2020)
Dysfunction of the SWI/SNF complex has been observed in various cancers including urothelial carcinomas. However, the clinical impact of the SWI/SNF complex in squamous-differentiated bladder cancers (sq-BLCA) remains unclear. Therefore, we aimed to analyze potential expression loss and genetic alterations of (putative) key components of the SWI/SNF complex considering the co-occurrence of genetic driver mutations and PD-L1 expression as indicators for therapeutic implications. Assessment of ARID1A, SMARCA2, SMARCA4, SMARCB1/INI1, SMARCC1, SMARCC2 and PBRM1 mutations in a TCGA data set of sq-BLCA (n = 45) revealed that ARID1A was the most frequently altered SWI/SNF gene (15%) while being associated with protein downregulation. Genetic alterations and loss of ARID1A were confirmed by Targeted Next Generation Sequencing (NGS) (3/6) and immunohistochemistry (6/116). Correlation with further mutational data and PD-L1 expression revealed co-occurrence of ARID1A loss and TP53 mutations, while positive correlations with other driver mutations such as PIK3CA were not observed. Finally, a rare number of sq-BLCA samples were characterized by both ARID1A protein loss and strong PD-L1 expression suggesting a putative benefit upon immune checkpoint inhibitor therapy. Hence, for the first time, our data revealed expression loss of SWI/SNF subunits in sq-BLCA, highlighting ARID1A as a putative target of a small subgroup of patients eligible for novel therapeutic strategies.
CRIS-Team Scopus Importer:2020-12-04
Keywords: ARID1A; Immune checkpoint inhibitors; Squamous bladder cancer; SWI/SNF complex

SWI/SNF Complex-deficient Undifferentiated/Rhabdoid Carcinomas of the Gastrointestinal Tract: A Series of 13 Cases Highlighting Mutually Exclusive Loss of SMARCA4 and SMARCA2 and Frequent Co-inactivation of SMARCB1 and SMARCA2 - Agaimy, Abbas; Daum, Ondrej; Maerkl, Bruno; Lichtmannegger, Ines; Michal, Michal; Hartmann, Arndt (American Journal of Surgical Pathology, 2016)
Undifferentiated gastrointestinal tract carcinomas are rare highly aggressive neoplasms with frequent but not obligatory rhabdoid features. Recent studies showed loss of SMARCB1 (INI1), a core subunit of the SWI/SNF chromatin remodeling complex, in 50% of tested cases. However, the molecular pathways underlying histologically similar but SMARCB1-intact cases are unknown. We herein analyzed 13 cases for expression of 4 SWI/SNF complex subunits SMARCB1, SMARCA2, SMARCA4, and ARID1A and the mismatch-repair proteins MLH1, MSH2, MSH6, and PMS2 by immunohistochemistry. Patients included 12 men and 1 woman aged 32 to 81 years (median, 57 y). Site of origin was colon (5), small bowel (2), stomach (3), small+large intestine (1), small intestine+ampulla of Vater (1), and esophagogastric junction (1). All tumors showed anaplastic large to medium-sized cells with variable rhabdoid features, pleomorphic giant cells, and, rarely, spindle cell foci. Abortive gland formation was seen in 3 cases and bona fide glandular component in 1 case. Most cases strongly expressed vimentin and variably pancytokeratin. In total, 12/13 cases (92%) showed loss of at least 1 SWI/SNF component. Loss of SMARCB1 (5/13), SMARCA2 (10/13), SMARCA4 (2/13), and ARID1A (2/13) was observed either in combination or isolated. SMARCA2 loss was isolated in 5 cases and coexisted with lost SMARCB1 in 5 cases (all 5 SMARCB1-deficient tumors showed loss of SMARCA2 as well). Co-inactivation of SMARCB1 and SMARCA4 or of SMARCA2 and SMARCA4 was not observed. Two mismatch-repair-deficient cases (MLH1/PMS2) showed concurrent loss of SMARCB1, SMARCA2, and (one of them) ARID1A. This study illustrates for the first time loss of different components of the SWI/SNF complex other than SMARCB1 in undifferentiated gastrointestinal carcinomas including novel SMARCA4-deficient and SMARCA2-deficient cases. Our results underline the close link between SWI/SNF deficiency and the aggressive rhabdoid phenotype. Frequent loss of SMARCA2 possibly points to fragility/vulnerability of the SWI/SNF complex as a consequence of lost core subunit SMARCB1. The exact molecular mechanisms underlying co-inactivation of different SWI/SNF subunits merit further investigations.
EVALuna2:6797

SWI/SNF-deficient undifferentiated/rhabdoid carcinoma of the gallbladder carrying a POLE mutation in a 30-year-old woman: a case report - Gerber, Tiemo S.; Agaimy, Abbas; Hartmann, Arndt; Habekost, Michael; Roth, Wilfried; Stenzinger, Albrecht; Schirmacher, Peter; Straub, Beate K. (Diagnostic Pathology, 2021)
Background: Undifferentiated carcinoma of the biliary tract are highly aggressive malignancies. In other organs, a subgroup of undifferentiated carcinoma related to SWI/SNF complex–deficiency have been described. Case presentation: A 30-year-old woman presented with rising inflammatory markers (C-reactive protein (CRP)). Ultrasound examination revealed a large tumor of the liver. A computed tomography scan was performed and was primarily interpreted as a tumor-forming liver abscess, possibly caused by gallbladder perforation. Subsequent liver segment resection was performed. Microscopic examination showed an undifferentiated carcinoma with rhabdoid morphology and prominent inflammatory infiltrate in the gallbladder base. With SWI/SNF immunohistochemistry, intact expression of SMARCB1, SMARCA4, ARID1A, but loss of SMARCA2 and PBRM1 was detected. Next-generation-sequencing detected KRAS, PBRM1 and ARID1B mutations, a deleterious splice-site mutation in the POLE-gene and a mutation in the TP53-gene. Conclusions: We were able to demonstrate loss of SMARCA2 expression and mutations characteristic of an SWI/SNF-deficient carcinoma in a tumor derived from the gallbladder. This is the first reported case of an undifferentiated carcinoma with rhabdoid features in the gallbladder carrying a POLE mutation and SWI/SNF-deficiency of PBRM1 and SMARCA2.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Case report; Gallbladder carcinoma; Rhabdoid; SMARCA4; SWI/SNF-deficiency

SWI/SNF protein expression status in fumarate hydratase-deficient renal cell carcinoma: immunohistochemical analysis of 32 tumors from 28 patients - Agaimy, Abbas; Amin, Mahul B.; Gill, Anthony; Popp, Bernt; Reis, André; Berney, Daniel M.; Magi-Galluzzi, Cristina; Sibony, Mathilde; Smith, Steven C.; Suster, Saul; Trpkov, Kiril; Hes, Ondrej; et al. (Human Pathology, 2018)
Fumarate hydratase-deficient renal cell carcinoma (FH-RCC) is a rare, aggressive RCC type, originally described in the setting of hereditary leiomyomatosis and RCC syndrome, which is defined by germline FH gene inactivation. Inactivation of components of the switch/sucrose nonfermentable (SWI/SNF) chromatin remodeling complex is involved in renal medullary carcinoma (SMARCB1/INI1 loss), clear cell RCC (PBRM1 loss), and subsets of dedifferentiated RCC of clear cell, chromophobe, and papillary types (loss of different SWI/SNF components). FH-RCC and SWI/SNF-deficient RCC share anaplastic nuclear features and highly aggressive course. We analyzed 32 FH-RCCs from 28 patients using 7 commercially available SWI/SNF antibodies (SMARCB1/INI1, SMARCA2, SMARCA4, SMARCC1, SMARCC2, PBRM1, and ARID1A). Variable loss of SMARCB1, ARID1A, and SMARCC1 was observed in 1 of 31, 2 of 31, and 1 of 29 evaluable cases, respectively; 3 of these 4 SWI/SNF-deficient tumors had confirmed FH mutations. No correlation of SWI/SNF loss with solid or sarcomatoid features was observed. Two tumors with SMARCB1 and ARID1A deficiency had available SWI/SNF molecular data; both lacked SMARCB1 and ARID1A mutations. The remaining 5 SWI/SNF components were intact in all cases. Especially PBRM1 seems not to be involved in the pathogenesis or progression of FH-RCC. Our data showed that a subset of FH-RCC (12%) have a variable loss of SWI/SNF complex subunits, likely as secondary genetic events. This should not be confused with SWI/SNF-deficient RCC of other types. Evaluation of FH and SWI/SNF together with comprehensive molecular genetic profiling is needed to explore possible prognostic implications of FH/SWI-SNF double deficiency and to better understand the somatic mutation landscape in high-grade RCC.
EVALuna2:34610

Targeted sequencing of FH-deficient uterine leiomyomas reveals biallelic inactivating somatic fumarase variants and allows characterization of missense variants - Popp, Bernt; Erber, Ramona; Kraus, Cornelia; Vasileiou, Georgia; Hoyer, Juliane; Burghaus, Stefanie; Hartmann, Arndt; Beckmann, Matthias; Reis, André; Agaimy, Abbas (Modern Pathology, 2020)
Uterine leiomyomas (ULs) constitute a considerable health burden in the general female population. The fumarate hydratase (FH) deficient subtype is found in up to 1.6% and can occur in hereditary leiomyomatosis and renal cell carcinoma (HLRCC) syndrome. We sequenced 13 FH deficient ULs from a previous immunohistochemical screen using a targeted panel and identified biallelic FH variants in all. In eight, we found an FH point mutation (two truncating, six missense) with evidence for loss of the second allele. Variant allele-frequencies in all cases with a point mutation pointed to somatic variants. Spatial clustering of the identified missense variants in the lyase domain indicated altered fumarase oligomerization with subsequent degradation as explanation for the observed FH deficiency. Biallelic FH deletions in five tumors confirm the importance of copy number loss as mutational mechanism. By curating all pathogenic FH variants and calculating their population frequency, we estimate a carrier frequency of up to 1/2,563. Comparing with the prevalence of FH deficient ULs, we conclude that most are sporadic and estimate 2.7–13.9% of females with an FH deficient UL to carry a germline FH variant. Further prospective tumor/normal sequencing studies are needed to develop a reliable screening strategy for HLRCC in women with ULs.
CRIS-Team Scopus Importer:2020-07-10

Technical validation of an RT-qPCR in vitro diagnostic test system for the determination of breast cancer molecular subtypes by quantification of ERBB2, ESR1, PGR and MKI67 mRNA levels from formalin-fixed paraffin-embedded breast tumor specimens - Laible, Mark; Schlombs, Kornelia; Kaiser, Katharina; Veltrup, Elke; Herlein, Stefanie; Lakis, Sotiris; Stoehr, Robert; Eidt, Sebastian; Hartmann, Arndt; Wirtz, Ralph M.; Sahin, Ugur (BMC Cancer, 2016)
MammaTyper is a novel CE-marked in vitro diagnostic RT-qPCR assay which assigns routinely processed breast cancer specimens into the molecular subtypes Luminal A-like, Luminal B-like (HER2 positive or negative), HER2 positive (non-luminal) and Triple negative (ductal) according to the mRNA expression of ERBB2, ESR1, PGR and MKI67 and the St Gallen consensus surrogate clinical definition. Until now and regarding formalin-fixed, paraffin-embedded material (FFPE), this has been a task mostly accomplished by immunohistochemistry (IHC). However the discrepancy rates of IHC for the four breast cancer biomarkers are frequently under debate, especially for Ki-67 which carries the highest degree of inter- and even intra-observer variability. Herein we describe a series of studies in FFPE specimens which aim to fully validate the analytical performance of the MammaTyper assay, including the site to site reproducibility of the individual marker measurements.Tumor RNA was extracted with the novel RNXtract RNA extraction kit. Synthetic RNA was used to assess the sensitivity of the RNXtract kit. DNA and RNA specific qPCR assays were used so as to determine analyte specificity of RNXtract. For the assessment of limit of blank, limit of detection, analytical measurement range and PCR efficiency of the MammaTyper kit serial dilutions of samples were used. Analytical precision studies of MammaTyper were built around two different real time PCR platforms and involved breast tumor samples belonging to different subtypes analyzed across multiple sites and under various stipulated conditions. The MammaTyper assay robustness was tested against RNA input variations, alternative extraction methods and tumor cell content.Individual assays were linear up to at least 32.33 and 33.56 Cqs (quantification cycles) for the two qPCR platforms tested. PCR efficiency ranged from 99 to 109 %. In qPCR platform 1, estimates for assay specific inter-site standard deviations (SD) were between 0.14 and 0.20 Cqs accompanied by >94 % concordant single marker assignments for all four markers. In platform 2, the inter-site SD estimates were between 0.40 and 0.66 Cqs while the concordance for single marker assignments was >94 % for all four markers. The agreement reached between the two qPCR systems located in one site was 100 % for ERBB2, 96.9 % for ESR1, 97.2 % for PGR and 98.6 % for MKI67. RT-qPCR for individual markers was stable up to a 64-fold dilution for a typical clinical sample. There was no change in assay performance detected at the level of individual markers or subtypes after using different RNA isolation methods. The presence of up to 80 % of surrounding non-tumor tissue including in situ carcinoma did not affect the assay output. Sixteen out of 20 RNXtract eluates yielded more than 50 ng/?l of RNA (average RNA output: 233 ng/?l), whereas DNA contamination per sample was restricted to less than 15 ng/?l. Median recovery rate of RNA extraction was 91.0 %.In this study the performance characteristics of MammaTyper were successfully validated. The various sources of analytical perturbations resulted in negligible variations in individual marker assessments. Therefore, MammaTyper may serve as a technical improvement to current standards for decentralized FFPE-based routine assessment of the commonly used breast cancer biomarkers and for molecular subtyping of breast cancer specimens.
EVALuna2:6753

TERT Core Promotor Mutations in Early-Onset Bladder Cancer - Giedl, Josef; Rogler, Anja; Wild, Andreas; Riener, Marc-Oliver; Filbeck, Thomas; Burger, Maximilian; Ruemmele, Petra; Hurst, Carolyn; Knowles, Margaret; Hartmann, Arndt; Zinnall, Ulrike; Stoehr, Robert (Journal of Cancer, 2016)
Activating mutations in the core promoter of the TERT gene have been described in many different tumor entities. In vitro models showed a two- to fourfold increase in transcriptional activity of the TERT promoter through creation of a consensus binding motif for Ets/TCF transcription factors caused by these mutations. TERT core promoter mutations are the most common mutations in bladder cancer with a frequency between 55.6% and 82.8% described so far, and are independent of stage and grade. Since limited data on molecular alterations of early-onset bladder tumors exists, we assessed the frequency of TERT core promoter mutations in early-onset bladder cancer. Two cohorts of bladder tumors (early-onset patient group; n=144 (age of onset of disease <=45 years); unselected, consecutive group; n=125) were examined for TERT core promoter mutations. After microdissection and extraction of DNA the corresponding hotspot regions in the TERT core promoter were examined by Sanger-sequencing or a SNaPshot approach. A significantly lower frequency of TERT core promoter mutations was found in tumors from the early-onset cohort compared to the consecutive cohort (57.6% vs. 84.8%, p<0.001). Among the early-onset cohort cases younger than the cohort's median age of 39 years at disease onset showed a significantly reduced number of TERT promoter mutations (31/67, 46,3%) than cases aged between 39 and 45 years (52/77, 67.5%; p=0.012). This association was not found in the consecutive cases. Mutation status was independent of tumor stage and grade. We conclude that in tumors from early-onset bladder cancer patients TERT core promoter mutations are not as frequent as in bladder tumors from consecutive cases, but seem to play an important role there as well. In patients below 39 years of age TERT core promoter mutations are a more infrequent event, suggesting different mechanisms of tumorigenesis in these young patients.
EVALuna2:6793

TERT promoter mutation analysis as a surrogate to morphology and immunohistochemistry in problematic spindle cell lesions of the urinary bladder - Bertz, Simone; Stöhr, Robert; Gaisa, Nadine T.; Wullich, Bernd; Hartmann, Arndt; Agaimy, Abbas (Histopathology, 2020)
Aims: Pseudosarcomatous myofibroblastic proliferations (PSMPs) of the urinary bladder are diagnostically challenging. Diagnostic difficulties are mainly due to frequent cytokeratin expression, variable ALK expression and worrisome morphological features suggestive of malignancy. Conversely, sarcomatoid urothelial carcinoma (UC) may show bland inflammatory myofibroblastic tumour (IMT)-like morphology. TERT promoter mutations are characteristic events in urothelial cancers, but have not been studied in PSMPs. Methods and results: We compared histomorphological and immunohistochemical features and TERT promoter status in 16 PSMPs and 18 sarcomatoid UC. In a subset of PSMPs, RNA sequencing was performed. At least focal IMT-like morphology was seen in nine of 17 sarcomatoid UC. Atypical mitoses, differentiated urothelial component and heterologous elements were the most reliable distinguishing histomorphological features of sarcomatoid UC, if present. A panel of immunohistochemistry (IHC) including ALK (clone D5F3), p53 pattern, p63 and GATA3 reliably distinguished PSMP from sarcomatoid UC. GATA3 (P = 0.001) and p53 patterns (mutant versus wild-type; P < 0.001) were differentially expressed between PSMPs and sarcomatoid UC. Diffuse pancytokeratin staining was significantly associated with PSMPs (10 of 13) compared to four of 14 sarcomatoid UCs (P = 0.012). TERT promoter mutations were found in 17 of 18 sarcomatoid UC versus none of 16 PSMPs (P < 0.001). RNA sequencing revealed ALK genetic rearrangements in one of two ALK-positive and one of 10 ALK-negative PSMPs, which revealed a novel FN1/RET gene fusion. Conclusion: Careful histomorphological analysis and differential IHC reliably distinguish the majority of PSMPs and sarcomatoid UC. In equivocal cases, TERT promoter mutation analysis and/or detection of ALK expression/rearrangements are valuable additional diagnostic adjuncts, strongly supporting sarcomatoid UC and PSMP, respectively.
CRIS-Team Scopus Importer:2020-10-02
Keywords: ALK gene rearrangement; inflammatory myofibroblastic tumour; pseudosarcomatous myofibroblastic proliferation; sarcomatoid urothelial carcinoma; TERT promoter mutation

Tert promoter mutation analysis of whole-organ mapping bladder cancers - Weyerer, Veronika; Eckstein, Markus; Strissel, Pamela; Wullweber, Adrian; Lange, Fabienne; Tögel, Lars; Geppert, Carol-Immanuel; Sikic, Danijel; Taubert, Helge; Wach, Sven; Wullich, Bernd; Hartmann, Arndt; et al. (Genes, 2021)
Background: Multifocal occurrence is a main characteristic of urothelial bladder cancer (UBC). Whether urothelial transformation is caused by monoclonal events within the urothelium, or by polyclonal unrelated events resulting in several tumor clones is still under debate. TERT promoter mutations are the most common somatic alteration identified in UBC. In this study, we analyzed different histological tissues from whole-organ mapping bladder cancer specimens to reveal TERT mutational status, as well as to discern how tumors develop. Methods: Up to 23 tissues from nine whole-organ mapping bladder tumor specimens, were tested for TERT promoter mutations including tumor associated normal urothelium, non-invasive urothelial lesions (hyperplasia, dys-plasia, metaplasia), carcinoma in situ (CIS) and different areas of muscle invasive bladder cancers (MIBC). The mutational DNA hotspot region within the TERT promoter was analyzed by SNaPshot analysis including three hot spot regions (−57, −124 or −146). Telomere length was measured by the Relative Human Telomere Length Quantification qPCR Assay Kit. Results: TERT promoter mutations were identified in tumor associated normal urothelium as well as non-invasive urothelial lesions, CIS and MIBC. Analysis of separate regions of the MIBC showed 100% concordance of TERT promoter mutations within a respective whole-organ bladder specimen. Polyclonal events were observed in five out of nine whole-organ mapping bladder cancers housing tumor associated normal urothelium, non-invasive urothelial lesions and CIS where different TERT promoter mutations were found compared to MIBC. The remaining four whole-organ mapping bladders were monoclonal for TERT mutations. No significant differences of telomere length were observed. Conclusions: Examining multiple whole-organ mapping bladders we conclude that TERT promoter mutations may be an early step in bladder cancer carcinogenesis as supported by TERT mutations detected in tumor associated normal urothelium as well as non-invasive urothelial lesions. Since mutated TERT promoter regions within non-invasive urothelial lesions are not sufficient alone for the establishment of cancerous growth, this points to the contribution of other gene mutations as a requirement for tumor development.
CRIS-Team Scopus Importer:2021-02-26
Keywords: Clonality; TERT promoter mutation; Whole-organ mapping bladder tumor

Testing deficient mismatch repair and microsatellite instability: A focused update. German version Testung auf Mismatch-Reparatur-Defizienz und Mikrosatelliteninstabilität: Eine fokussierte Aktualisierung - Rüschoff, Josef; Schildhaus, Hans Ulrich; Rüschoff, Jan Hendrik; Jöhrens, Korinna; Bocker-Edmonston, Tina; Dietmaier, Wolfgang; Bläker, Hendrik; Baretton, Gustavo; Horst, David; Dietel, Manfred; Hartmann, Arndt; Klauschen, Frederick; et al. (Die Pathologie, 2023)
Testing to detect mismatch repair deficiency (dMMR) and high-grade microsatellite instability (MSI-H) has become an integral part of the routine diagnostic workup for colorectal cancer (CRC). While MSI was initially considered to be a possible indicator of a hereditary disposition to cancer (Lynch syndrome, LS), today the prediction of the therapy response to immune checkpoint inhibitors (ICI) is in the foreground. Corresponding recommendations and testing algorithms are available for use in primary diagnosis (reviewed in: Rüschoff et al. 2021). Given the increasing importance for routine use and the expanding indication spectrum of ICI therapies for non-CRCs, such as endometrial, small intestinal, gastric, and biliary tract cancers, an updated review of dMMR/MSI testing is presented. The focus is on the challenges in the assessment of immunohistochemical stains and the value of PCR-based procedures, considering the expanded ICI indication spectrum. A practice-oriented flowchart for everyday diagnostic decision-making is provided that considers new data on the frequency and type of discordances between MMR-IHC and MSI-PCR findings, and the possible role of Next Generation Sequencing in clarifying them. Reference is made to the significance of systematic quality assurance measures (e.g., QuIP MSI portal and multicenter proficiency testing), including regular continued training and education.
CRIS-Team Scopus Importer:2023-08-18
Keywords: Hereditary nonpolyposis colorectal neoplasms; High-throughput nucleotide sequencing; Immune checkpoint inhibitors; Lynch syndrome; MMR immunohistochemistry

Testing for deficient mismatch repair and microsatellite instability: A focused update - Rüschoff, Josef; Schildhaus, Hans Ulrich; Rüschoff, Jan Hendrik; Jöhrens, Korinna; Bocker Edmonston, Tina; Dietmaier, Wolfgang; Bläker, Hendrik; Baretton, Gustavo; Horst, David; Dietel, Manfred; Hartmann, Arndt; Klauschen, Frederick; et al. (Die Pathologie, 2023)
Testing to detect mismatch repair deficiency (dMMR) and high-grade microsatellite instability (MSI-H) has become an integral part of the routine diagnostic workup for colorectal cancer (CRC). While MSI was initially considered to be a possible indicator of a hereditary disposition to cancer (Lynch syndrome, LS), today the prediction of the therapy response to immune checkpoint inhibitors (ICI) is in the foreground. Corresponding recommendations and testing algorithms are available for use in primary diagnosis (reviewed in: Rüschoff et al. 2021).Given the increasing importance for routine use and the expanding indication spectrum of ICI therapies for non-CRCs, such as endometrial, small intestinal, gastric, and biliary tract cancers, an updated review of dMMR/MSI testing is presented. The focus is on the challenges in the assessment of immunohistochemical stains and the value of PCR-based procedures, considering the expanded ICI indication spectrum. A practice-oriented flowchart for everyday diagnostic decision-making is provided that considers new data on the frequency and type of discordances between MMR-IHC and MSI-PCR findings, and the possible role of Next Generation Sequencing in clarifying them. Reference is made to the significance of systematic quality assurance measures (e.g., QuIP MSI portal and multicenter proficiency testing), including regular continued training and education.
CRIS-Team Scopus Importer:2023-12-29
Keywords: Hereditary nonpolyposis colorectal neoplasms; High-throughput nucleotide sequencing; Immune checkpoint inhibitors; Lynch syndrome; MMR immunohistochemistry

TFE3 activation in a TSC1-altered malignant PEComa: challenging the dichotomy of the underlying pathogenic mechanisms - Schmiester, Maren; Dolnik, Anna; Kornak, Uwe; Pfitzner, Berit; Hummel, Michael; Treue, Denise; Hartmann, Arndt; Agaimy, Abbas; Weyerer, Veronika; Lekaj, Anja; Brakemeier, Susanne; Peters, Robert; et al. (Journal of Pathology: Clinical Research, 2020)
Perivascular epithelioid cell tumors (PEComas) form a family of rare mesenchymal neoplasms that typically display myomelanocytic differentiation. Upregulation of mTOR signaling due the inactivation of TSC1/2 (Tuberous Sclerosis 1 and 2) is believed to be a key oncogenic driver in this disease. Recently, a subgroup of PEComas harboring TFE3 (Transcription Factor E3) rearrangements and presenting with a distinctive morphology has been identified. TSC1/2 and TFE3 aberrations are deemed to be mutually exclusive in PEComa, with two different pathogenic mechanisms assumed to lead to tumorigenesis. Here, we challenge this dichotomy by presenting a case of a clinically aggressive TCS1-mutated PEComa displaying a TFE3-altered phenotype. FISH analysis was suggestive of a TFE3 inversion; however, RNA and whole genome sequencing was ultimately unable to identify a fusion involving the gene. However, a copy number increase of the chromosomal region encompassing TFE3 was detected and transcriptome analysis confirmed upregulation of TFE3, which was also seen at the protein level. Therefore, we believe that the TSC1/2-mTOR pathway and TFE3 overexpression can simultaneously contribute to tumorigenesis in PEComa. Our comprehensive genetic analyses add to the understanding of the complex pathogenic mechanisms underlying PEComa and harbor insights for clinical treatment options.
CRIS-Team WoS Importer:2020-11-27

The 2022 World Health Organization Classification of Tumors of the Urinary System and Male Genital Organs-Part B: Prostate and Urinary Tract Tumors. - Netto, George J.; Amin, Mahul B.; Berney, Daniel M.; Compérat, Eva M.; Gill, Anthony J.; Hartmann, Arndt; Menon, Santosh; Raspollini, Maria R.; Rubin, Mark A.; Srigley, John R.; Hoon Tan, Puay; Tickoo, Satish K.; et al. (European Urology, 2022)
The 2022 World Health Organization (WHO) classification of the urinary and male genital tumors was recently published by the International Agency for Research on Cancer. This fifth edition of the WHO "Blue Book" offers a comprehensive update on the terminology, epidemiology, pathogenesis, histopathology, diagnostic molecular pathology, and prognostic and predictive progress in genitourinary tumors. In this review, the editors of the fifth series volume on urologic and male genital neoplasms present a summary of the salient changes introduced to the classification of tumors of the prostate and the urinary tract.
EVALuna2:542933

The 2022 World Health Organization Classification of Tumours of the Urinary System and Male Genital Organs—Part A: Renal, Penile, and Testicular Tumours - Moch, Holger; Amin, Mahul B.; Berney, Daniel M.; Compérat, Eva M.; Gill, Anthony J.; Hartmann, Arndt; Menon, Santosh; Raspollini, Maria R.; Rubin, Mark A.; Srigley, John R.; Hoon Tan, Puay; Tickoo, Satish K.; et al. (European Urology, 2022)
The fifth edition of the World Health Organization (WHO) classification of urogenital tumours (WHO “Blue Book”), published in 2022, contains significant revisions. This review summarises the most relevant changes for renal, penile, and testicular tumours. In keeping with other volumes in the fifth edition series, the WHO classification of urogenital tumours follows a hierarchical classification and lists tumours by site, category, family, and type. The section “essential and desirable diagnostic criteria” included in the WHO fifth edition represents morphologic diagnostic criteria, combined with immunohistochemistry and relevant molecular tests. The global introduction of massive parallel sequencing will result in a diagnostic shift from morphology to molecular analyses. Therefore, a molecular-driven renal tumour classification has been introduced, taking recent discoveries in renal tumour genomics into account. Such novel molecularly defined epithelial renal tumours include SMARCB1-deficient medullary renal cell carcinoma (RCC), TFEB-altered RCC, Alk-rearranged RCC, and ELOC-mutated RCC. Eosinophilic solid and cystic RCC is a novel morphologically defined RCC entity. The diverse morphologic patterns of penile squamous cell carcinomas are grouped as human papillomavirus (HPV) associated and HPV independent, and there is an attempt to simplify the morphologic classification. A new chapter with tumours of the scrotum has been introduced. The main nomenclature of testicular tumours is retained, including the use of the term “germ cell neoplasia in situ” (GCNIS) for the preneoplastic lesion of most germ cell tumours and division from those not derived from GCNIS. Nomenclature changes include replacement of the term “primitive neuroectodermal tumour” by “embryonic neuroectodermal tumour” to separate these tumours clearly from Ewing sarcoma. The term “carcinoid” has been changed to “neuroendocrine tumour”, with most examples in the testis now classified as “prepubertal type testicular neuroendocrine tumour”.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Carcinoma; Classification; Kidney; Penis; Testis; World Health Organization

The Chorioallantoic Membrane Xenograft Assay as a Reliable Model for Investigating the Biology of Breast Cancer - Ranjan, Raphela A.; Muenzner, Julienne K.; Kunze, Philipp; Geppert, Carol-Immanuel; Rübner, Matthias; Hübner, Hanna; Fasching, Peter; Beckmann, Matthias; Bäuerle, Tobias; Hartmann, Arndt; Walther, Wolfgang; Eckstein, Markus; et al. (Cancers, 2023)
The chorioallantoic membrane (CAM) assay is an alternative in vivo model that allows for minimally invasive research of cancer biology. Using the CAM assay, we investigated phenotypical and functional characteristics (tumor grade, mitosis rate, tumor budding, hormone receptor (HR) and HER2 status, Ki-67 proliferation index) of two breast cancer cell lines, MCF-7 and MDA-MB-231, which resemble the HR+ (luminal) and triple-negative breast cancer (TNBC) subgroups, respectively. Moreover, the CAM results were directly compared with murine MCF-7- and MDA-MB-231-derived xenografts and human patient TNBC tissue. Known phenotypical and biological features of the aggressive triple-negative breast cancer cell line (MDA-MB-231) were confirmed in the CAM assay, and mouse xenografts. Furthermore, the histomorphological and immunohistochemical variables assessed in the CAM model were similar to those in human patient tumor tissue. Given the confirmation of the classical biological and growth properties of breast cancer cell lines in the CAM model, we suggest this in vivo model to be a reliable alternative test system for breast cancer research to reduce murine animal experiments.
CRIS-Team Scopus Importer:2023-04-14
Keywords: 3R; alternative in vivo model; CAM model; hormone receptor; HTB-26; MCF-7; MDA-MB-231; mouse xenograft; tumor aggressiveness

The combined serum levels of miR-375 and urokinase plasminogen activator receptor are suggested as diagnostic and prognostic biomarkers in prostate cancer - Wach, Sven; Al-Janabi, Omar; Weigelt, Katrin; Fischer, Kersten; Greither, Thomas; Marcou, Marios; Theil, Gerit; Nolte, Elke; Holzhausen, Hans-Juergen; Stoehr, Robert; Huppert, Verena; Hartmann, Arndt; et al. (International Journal of Cancer, 2015)
This study aimed to assess the applicability of miR-375 in combination with the soluble urokinase plasminogen activator receptor (suPAR) protein as a diagnostic and/or prognostic biomarker for prostate cancer (PCa) patients. miR-375 levels by qRT-PCR and suPAR levels by ELISA were evaluated in serum samples from 146 PCa patients, 35 benign prostate hyperplasia (BPH) patients and 18 healthy controls. Antigen levels of suPAR differed between healthy controls and PCa or BPH patients, whereas miR-375 levels differed between PCa and BPH patients or healthy controls (p < 0.001). Additionally, suPAR levels differed between the Gleason sum groups GS = 7 versus GS > 7, with higher levels in the latter group (p = 0.011), and miR-375 levels were higher in the tumor stage group T3-T4 compared with the T1-T2 group (p = 0.039). A high concentration of suPAR was associated with a poor disease-specific survival (DSS; p = 0.039). The combination of suPAR and miR-375 levels identified a patient group possessing high levels for both parameters. This was associated with a poorer 10-year overall survival (OS) and DSS, with a 6.38-fold increased risk of death and a 7.68-fold increased risk of tumor-related death (p = 0.00026 and p = 0.014; univariate Cox's regression analysis). In a multivariate Cox's regression analysis PCa patients with high levels of suPAR and miR-375 showed a 5.72-fold increased risk of death in OS (p = 0.006). In summary, the differences between the PCa/BPH/healthy control cohorts for either suPAR and miR-375 levels in conjunction with the association of combined high suPAR/miR-375 levels with a poor prognosis suggest a diagnostic and prognostic impact for PCa patients.
EVALuna2:6726

The effect of participation in neoadjuvant clinical trials on outcomes in patients with early breast cancer - Brennan, Meghan; Gaß, Paul; Häberle, Lothar; Wang, Daidong; Hartmann, Arndt; Lux, Michael P.; Beckmann, Matthias; Untch, Michael; Fasching, Peter (Breast Cancer Research and Treatment, 2018)
BACKGROUND: Clinical trials can offer novel and more advanced and/or novel treatments to cancer patients in advance of them being approved and available for all patients. While several studies have examined the effect of clinical trial participation on prognosis, there has been no clear conclusion from these studies. Therefore, we chose to test the influence of trial participation on pathological complete response (pCR) and mastectomy rates after neoadjuvant chemotherapy. METHODS: In this retrospective study, all patients treated with neoadjuvant chemotherapy from 2001 to 2014 were selected. A total of 1038 patients with complete treatment, patient, and tumor characteristics were included. A total of 260 of those were treated in clinical trials. We examined whether study participation status in addition to commonly known predictors for pCR improves prediction of pCR. Similar analyses were conducted for the mastectomy rate outcome measure. Finally, survival analyses were also conducted as part of an exploratory analysis. RESULTS: Study participation was an independent predictor of pCR in addition to commonly known predictors. Adjusted odds ratio (OR) for trial participants versus non-participants was 1.53 (95% CI 1.03-2.28). Additionally, study participation improved the prediction of mastectomy risk. The adjusted OR for trial participants versus non-participants was 0.62 (95% CI 0.42-0.90). Subgroup-specific differences concerning the impact of study participation could not be shown for either pCR or mastectomy rate. Survival comparisons could not be conducted due to large differences in follow-up data in patients participating in clinical trials versus those who did not participate; however, pCR was a predictor of prognosis in both groups. CONCLUSION: Patients taking part in neoadjuvant chemotherapy clinical trials have a higher pCR rate and a lower mastectomy risk than patients not participating in clinical trials for their cancer care. This finding is a supporting factor for trial participation in neoadjuvant chemotherapy trials.
EVALuna2:34852

The EMT transcription factor ZEB1 governs a fitness-promoting but vulnerable DNA replication stress response. - Schuhwerk, Harald; Kleemann, Julia; Gupta, Pooja; van Roey, Ruthger; Armstark, Isabell; Kreileder, Martina; Feldker, Nora; Ramesh, Vignesh; Hajjaj, Yussuf; Fuchs, Kathrin; Mahapatro, Mousumi; Hribersek, Mojca; et al. (Cell Reports, 2022)
The DNA damage response (DDR) and epithelial-to-mesenchymal transition (EMT) are two crucial cellular programs in cancer biology. While the DDR orchestrates cell-cycle progression, DNA repair, and cell death, EMT promotes invasiveness, cellular plasticity, and intratumor heterogeneity. Therapeutic targeting of EMT transcription factors, such as ZEB1, remains challenging, but tumor-promoting DDR alterations elicit specific vulnerabilities. Using multi-omics, inhibitors, and high-content microscopy, we discover a chemoresistant ZEB1-high-expressing sub-population (ZEB1hi) with co-rewired cell-cycle progression and proficient DDR across tumor entities. ZEB1 stimulates accelerated S-phase entry via CDK6, inflicting endogenous DNA replication stress. However, DDR buildups involving constitutive MRE11-dependent fork resection allow homeostatic cycling and enrichment of ZEB1hi cells during transforming growth factor β (TGF-β)-induced EMT and chemotherapy. Thus, ZEB1 promotes G1/S transition to launch a progressive DDR benefitting stress tolerance, which concurrently manifests a targetable vulnerability in chemoresistant ZEB1hi cells. Our study thus highlights the translationally relevant intercept of the DDR and EMT.
EVALuna2:512403

The expression of hematopoietic progenitor cell antigen CD34 is regulated by DNA methylation in a site-dependent manner in gastrointestinal stromal tumours - Bure, Irina; Braun, Alexander; Kayser, Claudia; Geddert, Helene; Schaefer, Inga-Marie; Cameron, Silke; Ghadimi, Michael B.; Stroebel, Philipp; Werner, Martin; Hartmann, Arndt; Wiemann, Stefan; Agaimy, Abbas; et al. (International Journal of Cancer, 2017)
The anatomic site-dependent expression of hematopoietic progenitor cell antigen CD34 is a feature of gastrointestinal stromal tumours (GISTs). The basis for the differential CD34 expression is only incompletely understood. This study aimed at understanding the regulation of CD34 in GISTs and clarification of its site-dependent expression. Two sample sets of primary GISTs were interrogated including 52 fresh-frozen and 134 paraffin-embedded and formalin-fixed specimens. DNA methylation analysis was performed by HumanMethylation450 BeadChip array in three cell lines derived from gastric and intestinal GISTs, and differentially methylated CpG sites were established upstream of CD34. The methylation degree was further quantified by pyrosequencing, and inverse correlation with CD34 mRNA and protein abundance was revealed. The gene's expression could be activated upon induction of DNA hypomethylation with 5-aza-2'-deoxycytidine in GIST-T1 cells. In patient samples, a strong inverse correlation of DNA methylation degree with immunohistochemically evaluated CD34 expression was documented. Both CD34 expression and DNA methylation levels were specific to the tumours' anatomic location and mutation status. A constant decrease in methylation levels was observed ranging from almost 100% hypermethylation in intestinal GISTs from duodenum to hypomethylation in rectum. CD34 was heavily methylated in gastric PDGFRA-mutant GISTs in comparison to hypomethylated KIT-mutant counterparts. Next to CD34 hypermethylation, miR-665 was predicted and experimentally confirmed to target CD34 mRNA in GIST-T1 cells. Our results suggest that CD34 expression in GISTs may undergo a complex control by DNA methylation and miR-665. Differential methylation and expression of CD34 in GISTs along the gastrointestinal tract axis and in tumours that harbour different gain-of-function mutations suggest the origin from different cell populations in the gastrointestinal tract.
EVALuna2:6893

The Fuhrman grading system has no prognostic value in patients with nonsarcomatoid chromophobe renal cell carcinoma - Steffens, Sandra; Janssen, Martin; Roos, Frederik C.; Becker, Frank; Steinestel, Julie; Abbas, Mahmoud; Steinestel, Konrad; Wegener, Gerd; Siemer, Stefan; Thueroff, Joachim W.; Hofmann, Rainer; Stoeckle, Michael; et al. (Human Pathology, 2014)
The prognostic value of the Fuhrman nuclear grading system has been questioned for chromophobe renal cell carcinoma (chRCC) because this subtype frequently displays nuclear and nucleolar pleomorphism. The present study reevaluates this grading system in a series of patients with nonsarcomatoid chRCC. We identified 176 patients (3.6%) with nonsarcomatoid chRCC in a total of 4897 patients who underwent surgery for renal cell carcinoma at 5 centers in Germany between 1990 and 2010. The mean follow-up was 51.1 months. The 3 groups (G1 versus G2 versus G3/4) were comparable in terms of age, sex, tumor diameter, and lymph node metastasis. They only differed significantly in tumor stage (P = .01) and the incidence of synchronous visceral metastasis (P = .04). The 5-year cancer-specific survival rates were 84.4% for G1 (n = 32), 84.3% for G2 (n = 108), and 74.1% for G3/4 tumors (n = 33) (P = .58). Accordingly, multivariate analysis including age, sex, tumor stage, and metastatic disease did not identify Fuhrman grading as an independent predictor of cancer-specific survival in patients with chRCC (P = .4). We were able to demonstrate in a large multicenter cohort that the Fuhrman grading system does not qualify as a prognostic tool in patients with chRCC.
EVALuna2:6673

The HPV and p63 status in penile cancer are linked with the infiltration and therapeutic availability of neutrophils - Bernhard, Muriel Charlotte; Zwick, Anabel; Mohr, Tobias; Gasparoni, Gilles; Khalmurzaev, Oybek; Matveev, Vsevolod Borisovich; Loertzer, Philine; Pryalukhin, Alexey; Hartmann, Arndt; Geppert, Carol-Immanuel; Loertzer, Hagen; Wunderlich, Heiko; et al. (Molecular Cancer Therapeutics, 2021)
Squamous penile cancer displays a rare human papillomavirus (HPV)–associated tumor entity. Investigations on the molecular pathogenesis of HPV-driven penile cancer are impaired by the rareness of clinical specimens and, in particular, are missing relevant cell culture models. Here, we identified in HPV-positive penile cancer cell lines that HPV16 oncoproteins control TP63 expression by modulating critical regulators, while integration into the TP63 open reading frame facilitates oncogene expression. The resulting feed-forward loop leads to elevated p63 levels that in turn enhance the release of the neutrophil-recruiting chemokine CXCL8. Remarkably, elevated CXCL8 amounts lead to the increased surface exposition of the Fc receptor of human IgA antibodies, FcaRI, on neutrophils and correlated with a higher susceptibility to antibody-dependent neutrophil-mediated cytotoxicity (ADCC) using an EGFR-specific IgA2 antibody. IHC staining of tissue microarrays proved that elevated expression of p63 together with neutrophil infiltration were significantly more frequent in HPV-positive penile cancer displaying a higher tumor grade. In summary, we identified a promising marker profile of patients with penile cancer at higher risk for worse prognosis. However, these patients may benefit from immunotherapeutic approaches efficiently engaging neutrophils for tumor cell killing.
CRIS-Team Scopus Importer:2021-02-19

The Human Leukocyte Antigen G as an Immune Escape Mechanism and Novel Therapeutic Target in Urological Tumors - Jasinski-Bergner, Simon; Eckstein, Markus; Taubert, Helge; Wach, Sven; Fiebig, Christian; Strick, Reiner; Hartmann, Arndt; Seliger, Barbara (Frontiers in Immunology, 2022)
The non-classical human leukocyte antigen G (HLA-G) is a potent regulatory protein involved in the induction of immunological tolerance. This is based on the binding of membrane-bound as well as soluble HLA-G to inhibitory receptors expressed on various immune effector cells, in particular NK cells and T cells, leading to their attenuated functions. Despite its restricted expression on immune-privileged tissues under physiological conditions, HLA-G expression has been frequently detected in solid and hematopoietic malignancies including urological cancers, such as renal cell and urothelial bladder carcinoma and has been associated with progression of urological cancers and poor outcome of patients: HLA-G expression protects tumor cells from anti-tumor immunity upon interaction with its inhibitory receptors by modulating both the phenotype and function of immune cells leading to immune evasion. This review will discuss the expression, regulation, functional and clinical relevance of HLA-G expression in urological tumors as well as its use as a putative biomarker and/or potential therapeutic target for the treatment of renal cell carcinoma as well as urothelial bladder cancer.
CRIS-Team Scopus Importer:2022-03-04
Keywords: epithelial bladder cancer; HLA-G; immune cell infiltration; immune evasion; immunotherapy; renal cell carcinoma

The Microphthalmia-Associated Transcription Factor p.E318K Mutation Does Not Play a Major Role in Sporadic Renal Cell Tumors from Caucasian Patients - Stoehr, Christine G.; Walter, Bernhard; Denzinger, Stefan; Ghiorzo, Paola; Sturm, Richard A.; Hinze, Raoul; Moch, Holger; Junker, Kerstin; Hartmann, Arndt; Stoehr, Robert (Pathobiology, 2016)
The transcription factor MITF (microphthalmia-associated transcription factor) is known to induce expression of hypoxia-inducible factor (HIF1-?), which is involved in renal carcinogenesis. The MITF p.E318K mutation leads to deficient SUMOylation of MITF, resulting in enhanced activation of its target genes. A case-control study on melanoma patients who coincidentally were affected by renal cell carcinoma (RCC) has revealed an elevated risk for mutation carriers to be affected by one or both of these malignancies, suggesting a possible role for MITF p.E318K in renal carcinogenesis. The same study described an MITF mutation frequency of 1.5% in a small cohort of sporadic RCC, but comprehensive data on sporadic renal cell tumors are missing. We therefore tested a large cohort of sporadic renal tumors for MITF p.E318K mutation status.Genomic DNA was extracted from 426 formalin-fixed, paraffin-embedded sporadic renal tumors that had been graded according to the 2004 WHO classification of renal tumors and staged according to the 2002 TNM classification. The tumor cohort was enriched with papillary and chromophobe RCC, and also contained benign oncocytomas. DNA was tested for MITF p.E318K by pyrosequencing.Of 403 analyzable tumors, 402 renal tumors were wild-type ones, and only 1 case showed the MITF p.E318K mutation. This tumor was a clear-cell RCC (pT3b N0 M0 G3 according to the TNM classification 2002). The affected patient was male, 61 years old, and had no known coexisting malignancies.The MITF p.E318K mutation does not appear to play a major role in sporadic RCC carcinogenesis, but is possibly restricted to a rare subpopulation of inherited RCC. © 2016 S. Karger AG, Basel.
EVALuna2:6789

The natural course of pT2 prostate cancer with positive surgical margin: predicting biochemical recurrence - Karl, A.; Buchner, A.; Tympner, C.; Kirchner, T.; Ganswindt, U.; Belka, C.; Ganzer, R.; Burger, M.; Eder, F.; Hofstädter, F.; Schilling, D.; Sievert, K.; et al. (World Journal of Urology, 2015)
To predict biochemical recurrence respecting the natural course of pT2 prostate cancer with positive surgical margin (R1) and no adjuvant/neoadjuvant therapy.A multicenter data analysis of 956 patients with pT2R1N0/Nx tumors was performed. Patients underwent radical prostatectomy between 1994 and 2009. No patients received neoadjuvant or adjuvant therapy. All prostate specimens were re-evaluated according to a well-defined protocol. The association of pathological and clinical features, in regard to BCR, was calculated using various statistical tests.With a mean follow-up of 48 months, BCR was found in 25.4 %. In univariate analysis, multiple parameters such as tumor volume, PSA, Gleason at positive margin were significantly associated with BCR. However, in multivariate analysis, Gleason score (GS) of the prostatectomy specimen was the only significant parameter for BCR. Median time to recurrence for GS <= 6 was not reached; 5-year BCR-free survival was 82 %; and they were 127 months and 72 % for GS 3+4, 56 months and 54 % for GS 4 + 3, and 27 months and 32 % for GS 8-10. The retrospective approach is a limitation of our study.Our study provides data on the BCR in pT2R1-PCa without adjuvant/neoadjuvant therapy and thus a rationale for an individual's risk stratification. The data support patients and physicians in estimating the individual risk and timing of BCR and thus serve to personalize the management in pT2R1-PCa.
EVALuna2:6640

The outcome of patients with inflammatory bowel disease-associated colorectal cancer is not worse than that of patients with sporadic colorectal cancer-a matched-pair analysis of survival - Vitali, Francesco; Wein, Axel; Rath, Timo; Eckstein, Markus; Neufert, Clemens; Siebler, Jürgen; Atreya, Raja; Hartmann, Arndt; Hohenberger, Werner; Weber, Klaus; Neurath, Markus; Grützmann, Robert; et al. (International Journal of Colorectal Disease, 2021)
Purpose Patients with inflammatory bowel disease (IBD) have an increased risk for colorectal cancer (CRC). In IBD patients, cancer is often diagnosed in advanced stages and conflicting data on survival compared to sporadic CRC have been reported. The aim of this study was to directly compare clinical characteristics and prognosis of patients with IBD-CRC and sporadic CRC. Methods The clinical and pathological data of 63 patients with IBD-CRC and 3710 patients with sporadic CRC treated at the University Hospital of Erlangen between 1995 and 2015 were compared. Forty-seven M0 patients with IBD were matched with sporadic CRC patients after curative resection (R0) according to tumor localization, stage, sex, and year of treatment. Overall and disease-free survival were compared. Results Sixty-three patients presented IBD-CRC. Fifty were affected with ulcerative colitis (UC) and 13 with Crohn's disease (CD). CRC was diagnosed within 1.45 years since last endoscopic surveillance. Twelve patients (19%) had a diagnosis of primary sclerosing cholangitis. In matched analysis, IBD patients were diagnosed with CRC at younger age compared to sporadic CRC and were more likely to have right-sided CRC (40% versus 23.3%) and rare histological subtypes (19% versus 9.2%). No differences in 5-year overall (78.7 versus 80.9 months) and 5-year disease-free survival (74.5 versus 70.2 months) were noted. Conclusion IBD-CRC patients were younger and more frequently had right-sided carcinomas compared to sporadic CRC. CRC in IBD patients did not show survival difference compared to matched-pair sporadic CRC patients without distant metastases after curative resection. Surveillance might be important for early detection of CRC in IBD patients.
CRIS-Team WoS Importer:2021-12-17

The Prognostic and Predictive Significance of Tumor-Infiltrating Memory T Cells Is Reversed in High-Risk HNSCC - Hartan, Rebekka; Schnellhardt, Sören; Büttner-Herold, Maike; Daniel, Christoph; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Cells, 2022)
Tumor-infiltrating CD45RO+ memory T cells have unanimously been described as a positive prognostic factor in head and neck squamous cell carcinomas (HNSCCs). Here, we investigated the long-term prognostic relevance of CD45RO+ memory T cells in HNSCC with special regard to the influence of clinical characteristics. Pre-treatment biopsy samples from 306 patients with predominantly advanced HNSCC were analyzed. Immunohistochemistry was used to stain tissue microarrays for CD45RO+ memory T cells. CD45RO cell densities were semi-automatically registered and used for survival analysis. High CD45RO+ cell densities were clearly associated with prolonged overall survival (OS) and recurrence-free survival as well as no evidence of disease status after 10 years (p < 0.05). In contrast, the prognostic significance of tumor-infiltrating memory T cells was completely reversed in high-risk groups: in poorly differentiated tumors (G3, G4) and in cases with lymph node involvement (N+), high memory T cell densities correlated with reduced 10-year OS (p < 0.05). In conclusion, an increased density of tumor-infiltrating CD45RO+ cells in HNSCC can be a positive as well as a negative prognostic factor, depending on disease stage and histological grade. Therefore, if CD45RO+ cell density is to be used as a prognostic biomarker, further clinical characteristics must be considered.
CRIS-Team WoS Importer:2022-07-08
Keywords: CD45RO; head and neck cancer; memory T cells; prognostic value; reversal of prognostic value

The prognostic impact of Claudin 6 in papillary renal cell carcinoma - Mikuteit, Marie; Zschäbitz, Stefanie; Stöhr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Ströbel, Philipp; Becker, Frank; Wülfing, Christian; Barth, Peter; Stöckle, Michael; et al. (Pathology Research and Practice, 2022)
Background: Claudins are promising biomarkers for diagnosis and prognosis or targets for treatment. They play a major role in signal transduction and are important in nearly all aspects of tumorigenesis. Claudin 6 is a member of the claudin family and is part of the tight junction molecule. It is reactivated in several cancer types and serves as prognostic marker in, for example, gastric, breast or non small cell lung cancer. The prognostic role of Claudin 6 in renal cell carcinoma (RCC), especially in papillary RCC (pRCC), is still unclear. Patients and Methods: The patients’ sample collection was a joint collaboration of the PANZAR consortium. Patients’ medical history and tumor specimens were collected from n = 240 and n = 128 patients with type 1 and 2 pRCC, respectively. Expression of Claudin 6 was determined by immunohistochemistry. Results: In total, Claudin 6 staining was positive in 55 of 240 type 1 and 30 of 128 type 2 pRCC cases. Kaplan-Meier analysis disclosed an overall survival of 84% for Claudin 6- compared to 78% for Claudin 6 + in pRCC type 1 tumors (p = 0.449, log-rank) and 68% for Claudin 6- compared to 65.4% for Claudin 6 + in pRCC type 2 tumors (p = 0.364, log-rank). Conclusion: In this study, claudin 6 expression showed no significant association regarding overall survival (OS) and therefore did not qualify as a prognostic marker in pRCC. Future studies will have to determine, whether Claudin 6 plays a prognostic role in other RCC entities. In addition, the function of Claudin 6 as a predictive marker for therapeutic approaches has to be evaluated in future studies.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Claudin 6; Papillary renal cell carcinoma; Prognosis; Survival

The Prognostic Impact of PD-L2 in Papillary Renal-Cell Carcinoma. - Mondorf, Yvonne; Mikuteit, Marie; Ivanyi, Philipp; Stoehr, Christine; Herrmann, Edwin; Polifka, Iris; Agaimy, Abbas; Trojan, Lutz; Stroebel, Philipp; Becker, Frank; Wuelfing, Christian; Barth, Peter; et al. (Urologia Internationalis, 2022)
INTRODUCTION: Programmed death-1 ligand (PD-L1) has been often studied in different types of renal-cell carcinoma (RCC). For example, in clear-cell renal carcinoma it is well established that programmed death-1 receptor and PD-L1 are important prognostic markers. In contrast, the role of programmed death-2 ligand (PD-L2) as prognostic marker remains unclear. The aim of this study was to evaluate if PD-L2 expression could play a role as a prognostic marker for papillary RCC (pRCC). METHODS: The patients' sample collection was a joint collaboration of the PANZAR consortium. Patients' medical history and tumor specimens were collected from n = 240 and n = 128 patients with type 1 and 2 pRCC, respectively. Expression of PD-L2 was determined by immunohistochemistry. In total, PD-L2 staining was evaluable in 185 of 240 type 1 and 99 of 128 type 2 pRCC cases. RESULTS: PD-L2 staining was positive in 67 (36.2%) of type 1 and in 31 (31.3%) of type 2 pRCC specimens. The prevalence of PD-L2+ cells was significantly higher in high-grade type 1 tumors (p = 0.019) and in type 2 patients with metastasis (p = 0.002). Kaplan-Meier analysis disclosed significant differences in 5-year overall survival (OS) for patients with PD-L2- compared to PD-L2+ in pRCC type 1 of 88.4% compared to 73.6% (p = 0.039) and type 2 of 78.8% compared to 39.1% % (p < 0.001). However, multivariate analysis did not identify the presence of PD-L2+ cells neither in type 1 nor type 2 pRCC as an independent predictor of poor OS. DISCUSSION/CONCLUSION: PD-L2 expression did not qualify as an independent prognostic marker in pRCC. Future studies will have to determine whether anti-PD-L2-targeted treatment may play a role in pRCC and expression can potentially serve as a predictive marker for these therapeutic approaches.
EVALuna2:505682

The Prognostic Value of FGFR3 Expression in Patients with T1 Non-Muscle Invasive Bladder Cancer - Sikic, Danijel; Taubert, Helge; Breyer, Johannes; Eckstein, Markus; Weyerer, Veronika; Keck, Bastian; Kubon, Jennifer; Otto, Wolfgang; Worst, Thomas S.; Kriegnnair, Maximilian C.; Erben, Philipp; Hartmann, Arndt; et al. (Cancer Management and Research, 2021)
Purpose: Fibroblast growth factor receptor 3 (FGFR3) alterations are frequent in non-muscle-invasive bladder cancer (NMIBC), although current data regarding the prognostic and therapeutic relevance are inconsistent. We analyzed the prognostic role of FGFR3 mRNA expression in stage T1 NMIBC. Patients and Methods: The mRNA expression of FGFR3 and cyclin-dependent kinase inhibitor 2A (CDKN2A) was measured by RT-qPCR in 80 patients with stage T1 NMIBC treated with transurethral resection of the bladder and correlated with clinical data and KRT5 and KRT20 expression, used as surrogate markers for basal and luminal subtypes, respectively. Results: FGFR3 and CDKN2A transcript levels were not correlated. FGFR3 expression was associated with the expression of KRT5 (p=0.002) and KRT20 (p < 0.001). CDKN2A expression was negatively correlated with KRT5 (p=0.030). In Kaplan-Meier analysis and univariable Cox regression analysis, high FGFR3 expression was associated with signifi-cantly reduced recurrence-free survival (RFS) (HR=3.78; p < 0.001) and improved overall survival (OS) (HR=0.50; p=0.043), while high CDKN2A expression was associated with reduced OS (HR=2.34; p=0.034). Patient age was the only clinicopathological parameter associated with reduced OS (HR=2.29; p=0.022). No parameter was an independent prog-nostic factor in multivariable analysis. Next, we stratified the patients depending on their lineage differentiation. In univariable analysis, the prognostic effect of FGFR3 and CDKN2A was observed primarily in patients demonstrating high expression of KRT5 or KRT20, whereas high FGFR3 expression was associated with significantly reduced RFS, irrespective of instillation therapy. Conclusion: Stage T1 NMIBC patients with high FGFR3 expression show shorter RFS but better OS than patients with low FGFR3 expression.
CRIS-Team WoS Importer:2021-09-03

The Prognostic Value of FoxP3+Tumour-Infiltrating Lymphocytes in Rectal Cancer Depends on Immune Phenotypes Defined by CD8+Cytotoxic T Cell Density - Schnellhardt, Sören; Hirneth, Johannes; Büttner-Herold, Maike; Daniel, Christoph; Haderlein, Marlen; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (Frontiers in Immunology, 2022)
Tumour-infiltrating FoxP3+ regulatory T cells have been identified as both positive and negative prognostic factors in colorectal cancer (CRC) and rectal cancer (RC). In this study we investigated whether immune phenotypes, defined by CD8+ cytotoxic T cell density, may influence the prognostic association of FoxP3+ T cell densities in RC. Tissue microarrays from 154 rectal cancer resections were immunohistochemically double stained for CD8 and FoxP3. CD8+ and FoxP3+ cell densities were measured in the stromal and intraepithelial compartment. Stromal FoxP3+ cell densities were not associated with 10-year overall survival (OS). In the "immune-desert" phenotype, defined by very low stromal CD8+ cell density, a high density of stromal FoxP3+ T cells displayed a tendency towards an association with decreased 10-year OS (p = 0.179). In "inflamed" tumours, defined by high intraepithelial CD8+ T cell infiltration, the opposite was the case and high stromal FoxP3+ T cell densities were a positive prognostic factor (p = 0.048). Additionally, patients with an increased FoxP3/CD8 cell density ratio demonstrated a strong trend towards decreased 10-year OS (p = 0.066). These contrasting findings suggest functional heterogeneity within the group of FoxP3+ T cells. They are consistent with experimental studies which reported suppressive and non-suppressive populations of FoxP3+ T cells in CRC. Furthermore, our study demonstrates that CD8 immunohistochemistry may act as an instrument to identify tumours infiltrated by possibly functionally differing FoxP3+ T cell subtypes.
CRIS-Team WoS Importer:2022-02-18

The prominent role of the S100A8/S100A9-CD147 axis in the progression of penile cancer - Mohr, Tobias; Zwick, Anabel; Hans, Muriel Charlotte; Bley, Isabelle Ariane; Braun, Felix Leon; Khalmurzaev, Oybek; Matveev, Vsevolod Borisovich; Loertzer, Philine; Pryalukhin, Alexey; Hartmann, Arndt; Geppert, Carol-Immanuel; Loertzer, Hagen; et al. (Frontiers in Oncology, 2022)
Currently, no established biomarkers are recommended for the routine diagnosis of penile carcinoma (PeCa). The rising incidence of this human papillomavirus (HPV)–related cancer entity highlights the need for promising candidates. The Calprotectin subunits S100A8 and S100A9 mark myeloid-derived suppressor cells in other HPV-related entities while their receptor CD147 was discussed to identify patients with PeCa at a higher risk for poor prognoses and treatment failure. We thus examined their expression using immunohistochemistry staining of PeCa specimens from 74 patients on tissue microarrays of the tumor center, the invasion front, and lymph node metastases. Notably, whereas the tumor center was significantly more intensively stained than the invasion front, lymph node metastases were thoroughly positive for both S100 subunits. An HPV-positive status combined with an S100A8+S100A9+ profile was related with an elevated risk for metastases. We observed several PeCa specimens with S100A8+S100A9+-infiltrating immune cells overlapping with CD15 marking neutrophils. The S100A8+S100A9+CD15+ profile was associated with dedifferentiated and metastasizing PeCa, predominantly of HPV-associated subtype. These data suggest a contribution of neutrophil-derived suppressor cells to the progression of HPV-driven penile carcinogenesis. CD147 was elevated, expressed in PeCa specimens, prominently at the tumor center and in HPV-positive PeCa cell lines. CD147+HPV+ PeCa specimens were with the higher-frequency metastasizing cancers. Moreover, an elevated expression of CD147 of HPV-positive PeCa cell lines correlated negatively with the susceptibility to IgA-based neutrophil-mediated tumor cell killing. Finally, stratifying patients regarding their HPV/S100A8/S100A9/CD15/CD147 profile may help identify patients with progressing cancer and tailor immunotherapeutic treatment strategies.
CRIS-Team Scopus Importer:2022-11-04
Keywords: calprotectin; CD147; HPV-related cancer; myeloid-derived suppressor cells; neutrophils; penile cancer; S100A8; S100A9

Therapy response and prognosis of patients with early breast cancer with low positivity for hormone receptors – An analysis of 2765 patients from neoadjuvant clinical trials - Villegas, Sonia L.; Nekljudova, Valentina; Pfarr, Nicole; Engel, Jutta; Untch, Michael; Schrodi, Simone; Holms, Frank; Ulmer, Hans U.; Fasching, Peter; Weber, Karsten E.; Albig, Christian; Heinrichs, Clemens; et al. (European Journal of Cancer, 2021)
Aim: To evaluate HER2-negative breast cancer (BC) with a low hormone receptor (HR) expression, with regard to pathological complete response (pCR) and survival, in comparison to triple-negative BC (TNBC) and strong HR-positive BC. Methods: We compared negative [oestrogen (ER) and progesterone receptor (PR) <1%], low-positive (ER and/or PR 1–9%) and strong-positive (ER or PR 10–100%) HR-expression in neoadjuvant clinical trial cohorts (n = 2765) of BC patients. End-points were disease-free survival (DFS), distant-disease free survival (DDFS) and overall survival (OS). We performed RNA sequencing on available tumour tissue samples from patients with low-HR expression (n = 38). Results: Ninety-four (3.4%) patients had low HR-positive tumours, 1769 (64.0%) had strong HR-positive tumours, and 902 (32.6%) had TNBC. There were no significant differences in pCR rates between women with low HR-positive tumours (27.7%) and women with TNBC (35.5%). DFS and DDFS were also not different [for DFS, hazard ratio 1.26, 95%-CI (confidence interval) : 0.87–1.83, log-rank test p = 0.951; for DDFS, hazard ratio 1.17, 95%-CI: 0.78–1.76, log-rank test p = 0.774]. Patients with strong HR-positive tumours had a significantly lower pCR rate (pCR 9.4%; odds ratio 0.38, 95%-CI: 0.23–0.63), but better DFS (hazard ratio 0.48, 95%-CI: 0.33–0.70) and DDFS (hazard ratio 0.49, 95%-CI: 0.33–0.74) than patients with low HR-positive tumours. Molecular subtyping (RNA sequencing) of low HR-positive tumours classified these predominantly into a basal subtype (86.8%). Conclusion: Low HR-positive, HER2-negative tumours have a similar clinical behaviour to TNBC showing high pCR rates and poor survival and also a basal-like gene expression signature. Patients with low HR-positive tumours should be regarded as candidates for therapy strategies targeting TNBC.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Breast cancer; Breast neoplasms; Cancer biomarkers; ER-negative PR-negative HER2-negative breast cancer; Hormone-dependent neoplasms; Mammary cancer; Neoadjuvant therapy; Oestrogen receptors; Progesterone receptors; Triple-negative breast cancer

The renal cancer risk allele at 14q24.2 activates a novel hypoxia-inducible transcription factor-binding enhancer of DPF3 expression - Protze, Johanna; Naas, Stephanie; Krüger, René; Stöhr, Christine; Kraus, Andre; Grampp, Steffen; Schiffer, Mario; Hartmann, Arndt; Wullich, Bernd; Schödel, Johannes; Wiesener, Michael (Journal of Biological Chemistry, 2022)
Evolution of clear cell renal cell carcinoma is guided by dysregulation of hypoxia-inducible transcription factor (HIF) pathways following loss of the von Hippel-Lindau tumor suppressor protein. Renal cell carcinoma (RCC)-associated polymorphisms influence HIF–DNA interactions at enhancers of important oncogenes thereby modulating the risk of developing renal cancer. A strong signal of genome-wide association with RCC was determined for the single nucleotide polymorphism (SNP) rs4903064, located on chr14q.24.2 within an intron of DPF3, encoding for Double PHD Fingers 3, a member of chromatin remodeling complexes; however, it is unclear how the risk allele operates in renal cells. In this study, we used tissue specimens and primary renal cells from a large cohort of RCC patients to examine the function of this polymorphism. In clear cell renal cell carcinoma tissue, isolated tumor cells as well as in primary renal tubular cells, in which HIF was stabilized, we determined genotype-specific increases of DPF3 mRNA levels and identified that the risk SNP resides in an active enhancer region, creating a novel HIF-binding motif. We then confirmed allele-specific HIF binding to this locus using chromatin immunoprecipitation of HIF subunits. Consequentially, HIF-mediated DPF3 regulation was dependent on the presence of the risk allele. Finally, we show that DPF3 deletion in proximal tubular cells retarded cell growth, indicating potential roles for DPF3 in cell proliferation. Our analyses suggest that the HIF pathway differentially operates on a SNP-induced hypoxia-response element at 14q24.2, thereby affecting DPF3 expression, which increases the risk of developing renal cancer.
CRIS-Team Scopus Importer:2022-03-18

The role of claudin-6 in chromophobe renal cell carcinoma - Erlmeier, Franziska; Zschäbitz, Stefanie; Mikuteit, Marie; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; Steffens, Sandra (Histology and Histopathology, 2023)
BACKGROUND: The prognostic value of Claudin-6 (CLDN6) in non clear cell renal cell carcinoma (RCC) is still unclear. AIM: To evaluate the prognostic impact of CLDN6 expression in a large cohort of chromophobe RCC (chRCC). MATERIAL AND METHODS: Patients who underwent renal surgery due to chRCC were recruited. Clinical data were retrospectively evaluated. Tumor specimens were analyzed for CLDN6 expression by immunohistochemistry. RESULTS: 81 chRCC patients were eligible for analysis, thereof 10 (12.3%) patients were positive for CLDN6. No significant associations were found for CLDN6 expression and clinical attributes in patients with chRCC. Kaplan-Meier analysis revealed no differences in overall survival (OS) for patients with CLDN6⁻ compared to CLDN6⁺ tumors (87.0% versus 62.5%; p=0.174). CONCLUSION: In chRCC CLDN6 expression is not associated with parameters of aggressiveness or survival. Due to the rare incidence of chRCC further studies with larger cohorts are warranted.
CRIS-Team Scopus Importer:2023-04-14

The role of Signal Transducer and Activator of Transcription protein 5 (STAT5) in non-small cell lung cancer (NSCLC) - Friedrich, Juliane; Heim, Lisanne; Springel, Rebekka; Mittler, Susanne; Gafencu, Dumitrita; Hartmann, Arndt; Sirbu, Horia; Finotto, Susetta (2016)
EVALuna2:25983

The role of STAT3 (signal transducer and activator of transcription 3) in non-small cell lung cancer (NSCLC) - Heim, Lisanne; Andreev, Katerina; Balabko, Ljubov; Trufa, Denis; Sirbu, Horia; Hartmann, Arndt; Finotto, Susetta (2016)
EVALuna2:25984

The synergism of spatial metabolomics and morphometry improves machine learning-based renal tumour subtype classification. - Prade, Verena M.; Sun, Na; Shen, Jian; Feuchtinger, Annette; Kunzke, Thomas; Buck, Achim; Schraml, Peter; Moch, Holger; Schwamborn, Kristina; Autenrieth, Michael; Gschwend, Jurgen E.; Erlmeier, Franziska; et al. (Clinical and Translational Medicine, 2022)
EVALuna2:536086

The TLR9 agonist cobitolimod induces IL10 producing wound healing macrophages and regulatory T cells in ulcerative colitis - Schmitt, Heike; Ulmschneider, Julia; Billmeier, Ulrike; Scarozza, Patrizio; Sonnewald, Sophia; Reid, Stephen; Atreya, Imke; Rath, Timo; Zundler, Sebastian; Langheinrich, Melanie; Schüttler, Jürgen; Hartmann, Arndt; et al. (Journal of Crohns & Colitis, 2020)
BACKGROUND AND AIMS: The topically applied Toll-like receptor 9 (TLR9) agonist cobitolimod is a first-in-class DNA-based oligonucleotide that demonstrated therapeutic efficacy in clinical trials with ulcerative colitis (UC) patients. We here characterized its anti-inflammatory mechanism in UC. METHODS: Luminal cobitolimod administration was evaluated in an experimental DSS-induced colitis model. Cultured blood and mucosal cells from UC patients were treated with cobitolimod and analyzed via microarray, qRT-PCR, ELISA and flow cytometry. Intestinal slides of cobitolimod treated UC patients were analyzed by immunohistochemistry. RESULTS: Cobitolimod administration markedly suppressed experimental colitis activity and microarrays analyses demonstrated mucosal IL10 upregulation and suppression of IL17 signaling pathways. Cobitolimod treatment was associated with significant induction of mucosal IL10+ Tr1 and Treg cells and suppression of Th17 cells. TLR9 knockout mice indicated that cobitolimod requires TLR9 signaling for IL10 induction. In UC patients, mucosal TLR9 levels correlated with severity of inflammation. Cobitolimod inhibited IL17A and IL17F, but increased IL10 and FoxP3 expression in cultured intestinal UC T cells. Cobitolimod-mediated suppression of intestinal IL17+ T cells was abrogated by IL10 blockade. Furthermore, cobitolimod led to heightened IL10 production by wound healing macrophages. Immunohistochemistry in intestinal biopsies of cobitolimod treated UC patients indicated increased presence of IL10+ mononuclear and regulatory T cells, as well as reduction of IL17+ cells. CONCLUSION: Our studies suggest that activation of TLR9 via cobitolimod might represent a novel therapeutic approach in UC, as it suppresses Th17 cells and induces anti-inflammatory IL10+ macrophages and regulatory T cells, thereby modifying the dysregulated intestinal cytokine balance.
EVALuna2:212910
Keywords: Ulcerative colitis; TLR9; cobitolimod

The tumor immune microenvironment drives a prognostic relevance that correlates with bladder cancer subtypes - Pfannstiel, Carolin; Strissel, Pamela; Chiappinelli, Katherine B.; Sikic, Danijel; Wach, Sven; Wirtz, Ralph M.; Wullweber, Adrian; Taubert, Helge; Breyer, Johannes; Otto, Wolfgang; Worst, Thomas; Burger, Maximilian; et al. (Cancer Immunology Research, 2019)
Muscle-invasive bladder cancer (MIBC) represents approximately two-thirds of invasive urothelial bladder cancers (UBC) and has high morbidity and mortality. Men are over 3-fold more frequently affected by UBC than women. Despite intensive efforts to improve patient treatment and outcome, two-thirds of patients with UBC will have a recurrence or disease progression within 5 years. We demonstrated that the quantity and spatial distribution of stromal tumor-infiltrating lymphocytes (sTIL) within the tumor immune microenvironment (TIME) predict stages of tumor inflammation, subtypes, and patient survival and correlate with expression of immune checkpoints in an analysis of 542 patients with MIBC. High sTILs indicated an inflamed subtype with an 80% 5-year DSS, and a lack of immune infiltrates identified an uninflamed subtype with a survival rate of less than 25%. A separate immune evading phenotype with upregulated immune checkpoints associated with poor survival. Within the TIME are tertiary lymphoid structures (TLS), which can mediate antitumor activity via immune cells. High TLS amounts and close tumor distance correlated significantly with an inflamed phenotype and favorable survival. The uninflamed and evasion phenotypes showed lowest TLS numbers, farthest tumor distances, and shortest survival. High inflammation also correlated with increased neoantigen load and mutational burden. Patients treated with adjuvant chemotherapy showed a favorable prognosis, which was dependent on high sTILs. Determination of sTILs and tumor subtypes may stratify therapy success and patient survival, and considering sTILs can easily be quantified using simple morphologic parameters, like hematoxylin and eosin, sTILs can be implemented for predicting patient survival in a routine manner.
CRIS-Team Scopus Importer:2019-06-21

The validation of estrogen receptor 1 mRNA expression as a predictor of outcome in patients with metastatic non-small cell lung cancer - Atmaca, Akin; Al-Batran, Salah-Eddin; Wirtz, Ralph Markus; Werner, Dominique; Zirlik, Sabine; Wiest, Gunther; Eschbach, Corinna; Claas, Silke; Hartmann, Arndt; Ficker, Joachim Hans; Jaeger, Elke; Brueckl, Wolfgang Michael (International Journal of Cancer, 2014)
The prognostic role of estrogen receptors in lung cancer is not validated. Results from patients with early stage non-small lung cancer patients indicate a prognostic role of estrogen receptor 1 (ESR1) mRNA expression in these patients. Automated RNA extraction from paraffin and RT-quantitative PCR was used for evaluation of tumoral ESR1 and progesterone receptor (PGR) mRNA expression. The test cohort consisted of 31 patients with advanced or metastatic non-small cell lung cancer (NSCLC) patients, treated in a first-line registry trial. For validation, 53 patients from a randomized multicentre first-line study with eligible tumor samples were evaluated. There was no significant correlation of ESR1 expression with clinical characteristics. ESR1 high expression was of significant positive prognostic value in the training set with a median overall survival (OS) of 15.9 versus 6.2 months for high versus low ESR1 expression patients (p = 0.0498, HR 0.39). This could be confirmed in the validation cohort with a median OS of 10.9 versus 5.0 months in ESR1 high versus low patients, respectively (p = 0.0321, HR 0.51). In the multivariate analysis adjusted for histological subtype, gender, age and performance status, ESR1 expression remained an independent prognostic parameter for survival in both cohorts. In contrast to ESR1, PGR expression was not able to separate prognostic groups or to predict outcome significantly (for OS; p = 0.94). Our study shows that ESR1 mRNA as assessed by qPCR represents a reliable method for detecting ESR1 expression in NSCLC and that ESR1 expression is an independent prognostic factor in metastatic NSCLC.
EVALuna2:1901

The World Health Organization 1973 classification system for grade is an important prognosticator in T1 non-muscle-invasive bladder cancer - van de Putte, Elisabeth E.Fransen; Bosschieter, Judith; van der Kwast, Theo H.; Bertz, Simone; Denzinger, Stefan; Manach, Quentin; Compérat, Eva M.; Boormans, Joost L.; Jewett, Michael A.S.; Stoehr, Robert; van Leenders, Geert J.L.H.; Nieuwenhuijzen, Jakko A.; et al. (Bju International, 2018)
OBJECTIVES: To compare the prognostic value of the World Health Organization (WHO) 1973 and 2004 classification systems for grade in T1 bladder cancer (T1-BC), as both are currently recommended in international guidelines. PATIENTS AND METHODS: Three uro-pathologists re-revised slides of 601 primary (first diagnosis) T1-BCs, initially managed conservatively (bacille Calmette-Guérin) in four hospitals. Grade was defined according to WHO1973 (Grade 1-3) and WHO2004 (low-grade [LG] and high-grade [HG]). This resulted in a lack of Grade 1 tumours, 188 (31%) Grade 2, and 413 (69%) Grade 3 tumours. There were 47 LG (8%) vs 554 (92%) HG tumours. We determined the prognostic value for progression-free survival (PFS) and cancer-specific survival (CSS) in Cox-regression models and corrected for age, sex, multiplicity, size and concomitant carcinoma in situ. RESULTS: At a median follow-up of 5.9 years, 148 patients showed progression and 94 died from BC. The WHO1973 Grade 3 was negatively associated with PFS (hazard ratio [HR] 2.1) and CSS (HR 3.4), whilst WHO2004 grade was not prognostic. On multivariable analysis, WHO1973 grade was the only prognostic factor for progression (HR 2.0). Grade 3 tumours (HR 3.0), older age (HR 1.03) and tumour size >3 cm (HR 1.8) were all independently associated with worse CSS. CONCLUSION: The WHO1973 classification system for grade has strong prognostic value in T1-BC, compared to the WHO2004 system. Our present results suggest that WHO1973 grade cannot be replaced by the WHO2004 classification in non-muscle-invasive BC guidelines.
EVALuna2:34812

TILGen: A Program to Investigate Immune Targets in Breast Cancer Patients - First Results on the Influence of Tumor-Infiltrating Lymphocytes - Würfel, Franziska; Erber, Ramona; Hübner, Hanna; Hein, Alexander; Lux, Michael P.; Jud, Sebastian; Kremer, Anita; Kranich, Hannah; Mackensen, Andreas; Häberle, Lothar; Hack, Carolin; Rauh, Claudia; et al. (Breast Care, 2018)
Background: Despite advancements in the treatment of primary and metastatic breast cancer, many patients lack a durable response to these treatments. Patients with triplenegative breast cancer (TNBC) and human epidermal growth factor receptor 2(HER2)-positive breast cancer who do not have a pathological complete response (pCR) after neoadjuvant chemotherapy (NACT) have a very poor prognosis. Tumor-infiltrating lymphocytes (TILs) have been identified as a predictive marker for pCR after NACT in TNBC and HER2-positive breast cancer. These patient populations could also be suitable for novel treatment strategies including neoepitope-based therapies. This work analyses the effect of TILs on the pCR in neoadjuvantly treated patients in the TILGen study and presents the procedures aimed at establishing neoepitope-based therapies in this study. Methods: Neoadjuvantly treated HER2positive and TNBC patients were eligible for the presented analysis concerning the association between TILs and pCR. A total of 146 patients could be identified within the TILGen study. TILs were evaluated as percentage of stromal tumor tissue in core biopsies at primary diagnosis. The phenotype 'lymphocyte-predominant breast cancer' (LPBC) was associated with pCR by logistic regression adjusted for estrogen receptor status, progesterone receptor status, HER2 status, age at diagnosis, and grading. Results: LPBC was seen in 24 (16.4%) patients. In this patient group, 66.7% achieved a pCR, while the pCR rate was 32.8% in patients with a low TIL count. The adjusted odds ratio was 6.60 (95% confidence interval 2.02-21.56; p < 0.01). Conclusion: TILs are a strong predictor of pCR in TNBC and HER2-positive breast cancer patients. Implications for the use of this information including the effect on prognosis might help to identify patients most likely to benefit from a neoepitope-based therapy approach. (C) 2018 S. Karger GmbH, Freiburg
EVALuna2:34061
Keywords: Tumor-infiltrating lymphocytes; Response; Neoadjuvant chemotherapy; TILGen study

TILGen study-immunological targets in patients with breast cancer : Influence of tumor-infiltrating lymphocytes - Erber, Ramona; Hartmann, Arndt; Beckmann, Matthias; Mackensen, Andreas; Kremer, Anita; Reimann, Hannah; Hübner, Hanna; Hein, Alexander; Lux, Michael P.; Jud, Sebastian; Häberle, Lothar; Gaß, Paul; et al. (Pathologe, 2018)
BACKGROUND: The interaction of our immune system with breast cancer (BC) cells prompted the investigation of tumor-infiltrating lymphocytes (TILs) and targeted, tumor antigen-specific immunotherapy. OBJECTIVES: Correlation between TILs and pathological complete response (pCR) after neoadjuvant systemic therapy (NACT). Tumor-specific antigens (TSAs) in HER2+ and triple negative BC and establishment of TSA-specific therapies within the interdisciplinary TILGen study. METHODS: Illustration of the TILGen study design. Assessment of TILs and correlation with pCR within this BC study. RESULTS: pCR was achieved in 38.4% (56/146) and associated with estrogen receptor/progesterone receptor negative (ER-/PR-) and HER2+ tumors. Lymphocytic predominant BC (LPBC) was found in 16.4% (24/146), particularly in ER-/PR- (ER-: 27.3% vs. ER+: 9.9%, PR-: 22.3% vs. PR+: 8.2%), large, and poorly differentiated BC. TILs were significantly correlated with pCR in multivariate analysis. In LPBC, pCR was achieved in 66.7%, whereas it was 32.8% in non-LPBC. CONCLUSIONS: First results confirm the influence of the human immune system on the response to NACT in HER2+ and triple negative BC. TSA-specific immunotherapy might improve the outcome in BC patients but there is an urgent need for comprehensive studies to further investigate this issue.
EVALuna2:35097

Time and Resources Needed to Document Patients with Breast Cancer from Primary Diagnosis to Follow-up - Results of a Single-center Study - Lux, Michael P.; Sell, C. S.; Fasching, Peter; Seidl-Ertel, Janine; Bani, Mayada; Schrauder, M. G.; Jud, Sebastian; Löhberg, Christian; Rauh, C.; Hartmann, Arndt; Schulz-Wendtland, Rüdiger; Strnad, Vratislav; et al. (Geburtshilfe und Frauenheilkunde, 2014)
Aim: Certification of breast centers helps improve the quality of care but requires additional resources, particularly for documentation. There are currently no published data on the actual staff costs and financial resources required for such documentation. The aim of this study was to determine the time and resources required to document a patient with primary breast cancer from diagnosis to the end of follow-up, to establish a database for future strategic decisions. Material and Methods: All diagnostic and therapeutic procedures of patients with primary breast cancer were recorded at the University Breast Center of Franconia. All time points for documentation were evaluated using structured interviews. The times required to document a representative number of patients were determined and combined with the staff costs of the different professional groups, to calculate the financial resources required for documentation. Results: A total of 494 time points for documentation were identified. The study also identified 21 departments and 20 different professional groups involved in the documentation. The majority (54 %) of documentation was done by physicians. 62 % of all documentation involved outpatients. The results of different scenarios for the diagnosis, therapy and follow-up of breast cancer patients in a certified breast center showed that the time required for documentation can be as much as 105 hours, costing EUR 4135. Conclusion: This analysis shows the substantial staffing and financial costs required for documentation in certified centers. A multi-center study will be carried out to compare the costs for certified breast centers of varying sizes with the costs of non-certified care facilities.
EVALuna2:6642

Touch Imprint Cytology and Stereotactically-Guided Core Needle Biopsy of Suspicious Breast Lesions: 15-Year Follow-up - Schulz-Wendtland, Rüdiger; Fasching, Peter; Bani, Mayada; Lux, Michael P.; Jud, Sebastian; Rauh, C.; Bayer, C.; Wachter, David; Hartmann, Arndt; Beckmann, Matthias; Uder, Michael; Löhberg, Christian (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: Stereotactically-guided core needle biopsies (CNB) of breast tumours allow histological examination of the tumour without surgery. Touch imprint cytology (TIC) of CNB promises to be useful in providing same-day diagnosis for counselling purposes and for planning future surgery. Having addressed the issue of accuracy of immediate microscopic evaluation of TIC, we wanted to re-examine the usefulness of this procedure in light of the present health care climate of cost containment by incorporating the surgical 15-year follow-up data and outcome. Patients and Methods: From January until December 1996 we performed TIC in core needle biopsies of 173 breast tumours in 169 patients, consisting of 122 malignant and 51 benign tumours. Histology of core needle biopsies was proven by surgical histology in all malignant and in 5 benign tumours. Surgical breast biopsy was not performed in 46 patients with 46 benign lesions, as the histological result from the core needle biopsy and the result of the TIC were in agreement with the suspected diagnosis from the complementary breast diagnostics. A 15-year follow-up of these patients followed in 2013 and follow-up data was collected from 40 women. Results: In the 15-year follow-up of the 40 benign lesions primarily confirmed using CNB and TIC, a diagnostic sensitivity, specificity, positive and negative predictive value and accuracy of 100 % was found. Conclusion: TIC and stereotactically guided CNB showed excellent long-term follow-up in patients with benign breast lesions. The use of TIC to complement CNB can therefore provide immediate cytological diagnosis of breast lesions.
EVALuna2:6752

Towards interactive AI-authoring with prototypical few-shot classifiers in histopathology - Kuritcyn, Petr; Kletzander, Rosalie; Eisenberg, Sophia; Wittenberg, Thomas; Bruns, Volker; Evert, Katja; Keil, Felix; Ziegler, Paul K.; Bankov, Katrin; Wild, Peter; Eckstein, Markus; Hartmann, Arndt; et al. (Journal of Pathology Informatics, 2024)
A vast multitude of tasks in histopathology could potentially benefit from the support of artificial intelligence (AI). Many examples have been shown in the literature and first commercial products with FDA or CE-IVDR clearance are available. However, two key challenges remain: (1) a scarcity of thoroughly annotated images, respectively the laboriousness of this task, and (2) the creation of robust models that can cope with the data heterogeneity in the field (domain generalization). In this work, we investigate how the combination of prototypical few-shot classification models and data augmentation can address both of these challenges. Based on annotated data sets that include multiple centers, multiple scanners, and two tumor entities, we examine the robustness and the adaptability of few-shot classifiers in multiple scenarios. We demonstrate that data from one scanner and one site are sufficient to train robust few-shot classification models by applying domain-specific data augmentation. The models achieved classification performance of around 90% on a multiscanner and multicenter database, which is on par with the accuracy achieved on the primary single-center single-scanner data. Various convolutional neural network (CNN) architectures can be used for feature extraction in the few-shot model. A comparison of nine state-of-the-art architectures yielded that EfficientNet B0 provides the best trade-off between accuracy and inference time. The classification of prototypical few-shot models directly relies on class prototypes derived from example images of each class. Therefore, we investigated the influence of prototypes originating from images from different scanners and evaluated their performance also on the multiscanner database. Again, our few-shot model showed a stable performance with an average absolute deviation in accuracy compared to the primary prototypes of 1.8% points. Finally, we examined the adaptability to a new tumor entity: classification of tissue sections containing urothelial carcinoma into normal, tumor, and necrotic regions. Only three annotations per subclass (e.g., muscle and adipose tissue are subclasses of normal tissue) were provided to adapt the few-shot model, which obtained an overall accuracy of 93.6%. These results demonstrate that prototypical few-shot classification is an ideal technology for realizing an interactive AI authoring system as it only requires few annotations and can be adapted to new tasks without involving retraining of the underlying feature extraction CNN, which would in turn require a selection of hyper-parameters based on data science expert knowledge. Similarly, it can be regarded as a guided annotation system. To this end, we realized a workflow and user interface that targets non-technical users.
CRIS-Team Scopus Importer:2024-07-12
Keywords: Colon adenocarcinoma; Data augmentation; Digital pathology; Few-shot learning; Prototypical networks; Tissue classification; Urothelial carcinoma

Towards the introduction of the 'Immunoscore' in the classification of malignant tumours - Galon, Jerome; Mlecnik, Bernhard; Bindea, Gabriela; Angell, Helen K.; Berger, Anne; Lagorce, Christine; Lugli, Alessandro; Zlobec, Inti; Hartmann, Arndt; Bifulco, Carlo; Nagtegaal, Iris D.; Palmqvist, Richard; et al. (Journal of Pathology, 2014)
The American Joint Committee on Cancer/Union Internationale Contre le Cancer (AJCC/UICC) TNM staging system provides the most reliable guidelines for the routine prognostication and treatment of colorectal carcinoma. This traditional tumour staging summarizes data on tumour burden (T), the presence of cancer cells in draining and regional lymph nodes (N) and evidence for distant metastases (M). However, it is now recognized that the clinical outcome can vary significantly among patients within the same stage. The current classification provides limited prognostic information and does not predict response to therapy. Multiple ways to classify cancer and to distinguish different subtypes of colorectal cancer have been proposed, including morphology, cell origin, molecular pathways, mutation status and gene expression-based stratification. These parameters rely on tumour-cell characteristics. Extensive literature has investigated the host immune response against cancer and demonstrated the prognostic impact of the in situ immune cell infiltrate in tumours. A methodology named 'Immunoscore' has been defined to quantify the in situ immune infiltrate. In colorectal cancer, the Immunoscore may add to the significance of the current AJCC/UICC TNM classification, since it has been demonstrated to be a prognostic factor superior to the AJCC/UICC TNM classification. An international consortium has been initiated to validate and promote the Immunoscore in routine clinical settings. The results of this international consortium may result in the implementation of the Immunoscore as a new component for the classification of cancer, designated TNM-I (TNM-Immune). © 2013 The Authors. Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.
EVALuna2:6551

Transcriptomic and metabolomic profiles in renal cell carcinoma (RCC) tumors reflect ontogeny of RCC subtypes - Fisel, Pascale; Buettner, Florian; Reustle, Anna; Klumpp, Verena; Winter, Stefan; Rausch, Steffen; Hennenlotter, Joerg; Kruck, Stephan; Stenzl, Arnulf; Wahrheit, Judith; Sonntag, Denise; Scharpf, Marcus; et al. (CANCER RESEARCH, 2018)
CRIS-Team WoS Importer:2019-06-18

Transrectal Absorber Guide Raster-Scanning Optoacoustic Mesoscopy for Label-Free In Vivo Assessment of Colitis - Bühler, Adrian; Brown, Emma; Paulus, Lars-Philip; Eckstein, Markus; Thoma, Oana-Maria; Oraiopoulou, Mariam-Eleni; Rother, Ulrich; Hörning, André; Hartmann, Arndt; Neurath, Markus; Wölfle, Joachim; Friedrich, Oliver; et al. (Advanced Science, 2023)
Optoacoustic imaging (OAI) enables microscale imaging of endogenous chromophores such as hemoglobin at significantly higher penetration depths compared to other optical imaging technologies. Raster-scanning optoacoustic mesoscopy (RSOM) has recently been shown to identify superficial microvascular changes associated with human skin pathologies. In animal models, the imaging depth afforded by RSOM can enable entirely new capabilities for noninvasive imaging of vascular structures in the gastrointestinal tract, but exact localization of intra-abdominal organs is still elusive. Herein the development and application of a novel transrectal absorber guide for RSOM (TAG-RSOM) is presented to enable accurate transabdominal localization and assessment of colonic vascular networks in vivo. The potential of TAG-RSOM is demonstrated through application during mild and severe acute colitis in mice. TAG-RSOM enables visualization of transmural vascular networks, with changes in colon wall thickness, blood volume, and OAI signal intensities corresponding to colitis-associated inflammatory changes. These findings suggest TAG-RSOM can provide a novel monitoring tool in preclinical IBD models, refining animal procedures and underlines the capabilities of such technologies to address inflammatory bowel diseases in humans.
CRIS-Team WoS Importer:2023-05-12

Transurethral en bloc submucosal hydrodissection vs conventional resection for resection of non-muscle-invasive bladder cancer (HYBRIDBLUE): a randomised, multicentre trial - Gakis, Georgios; Karl, Alexander; Bertz, Simone; Burger, Maximillian; Fritsche, Hans Martin; Hartmann, Arndt; Jokisch, Friedrich; Kempkensteffen, Carsten; Miller, Kurt; Mundhenk, Jens; Schneevoigt, Birte Swantje; Schubert, Tina; et al. (Bju International, 2020)
Objective: To determine whether transurethral en bloc submucosal hydrodissection of bladder tumours (TUEB) improves the quality of the resection compared to conventional transurethral resection of bladder tumour (TURBT) in patients with non-muscle-invasive bladder cancer (NMIBC). Patients and Methods: A randomised, multicentre trial (HYBRIDBLUE) was conducted with a superiority design. Six German academic centres participated between September 2012 and August 2015. Based on literature analysis, a sample size for accurate histopathological assessment concerning muscle invasion was assumed to be feasible in 50% (P0 = 0.5) of TURBT and 80% of TUEB cases. After pre-screening of a total of 305 patients, participants were allocated to two study arms: Group I: hexaminolevulinate (HAL)-guided TUEB; Group II: conventional HAL-guided TURBT. The primary endpoint was the proportion of specimens that could be reliably evaluated pathologically concerning muscle invasiveness. Secondary endpoints included rates of histopathological completeness of the resection, muscularis propria content, recurrence, and complication rates. Results: A total of 115 patients (TUEB 56; TURBT 59) were eligible for final analysis. Adequate histopathological assessment, which included muscularis propria content and tumour margins (R0 vs R1), was present in 48/56 (86%) TUEB patients compared to 37/59 (63%; P = 0.006) in the TURBT group. R0 was confirmed in 30/56 TUEB patients (57%) and five of 59 TURBT patients (9%; P < 0.001). No complications of Grade ≥III were observed in both arms. At 3 and 12 months, three and 19 patients recurred in the TUEB group vs seven and 11 patients in the TURBT group, respectively (P = 0.33 and P = 0.08). Conclusions: In this randomised study, TUEB was shown to be clinically safe regarding perioperative endpoints. An adequate histopathological assessment concerning muscle invasion was significantly better assessable in the TUEB arm compared to standard TURBT. This finding indicates the clinical potential for reducing the rate of early re-resections. Yet, a larger study with recurrence-free survival as the primary endpoint is needed to assess the oncological efficacy between both techniques.
CRIS-Team Scopus Importer:2020-08-14
Keywords: #BladderCancer; #blcsm; bladder cancer; en bloc; hexaminolevulinate; hydrodissection; photodynamic diagnosis; transurethral; trial

Treatment of generalised vitiligo with tacrolimus 0.1% ointment vs. UVB intense pulsed light phototherapy: a pilot study - Hartmann, Arndt; Löhberg, Lisa; Keikavoussi, Petra; Eichner, Saskia; Schuler, Gerold (Acta Dermato-Venereologica, 2014)
EVALuna2:19436

Treatment of vitiligo using targeted UVB-Intense Pulsed Light (IPL)- phototherapy: evaluation of variables affecting therapeutic success - Hartmann, Arndt; Schmidt-Habel, Anne; Löhberg, Lisa; Zajitschek, Jörg; Englbrecht, Matthias; Eichner, Saskia; Schuler, Gerold (European Journal of Dermatology, 2014)
Targeted UVB intense pulsed light (IPL)-phototherapy has gained interest for repigmentation of vitiligo as it allows selective treatment, sparing the surrounding skin. However, optimal treatment frequency and duration are not known.We compared the efficacy and safety of two treatment protocols, weekly and every two weeks, for a maximum of 12 months. Variables affecting treatment response were evaluated.22 patients (16 female, 6 male; aged 15 - 67 years) with generalised vitiligo were evaluated retrospectively. UVB-IPL had been administered weekly (13 patients, group A), or every second week (9 patients, group B). In cases of no response, treatment stopped after 6 months. Regimentation was evaluated qualitatively and quantitatively.After 6 months, 12/13 patients (A), 3/9 patients (B) showed repigmentation. Due to lack of success, treatment was stopped after 6 months in 1 group A patient and 6/9 group B patients. After 12 months, lesions on the face and trunk in group A showed a mean of 70 ± 27% and 60 ± 29% repigmentation, respectively. Moderate to good repigmentation was seen in 78% of group A patients on the ulnar region on the forearms and the shins. Side effects were minimal. Treatment success depended on treatment frequency, number of treatments and the anatomical site of lesions.UVB-IPL phototherapy seems to be effective and well-tolerated in non-segmental vitiligo. A treatment frequency of weekly intervals rather than every two weeks appears preferable. Our observations will help in designing a sufficiently powered prospective clinical trial to test this hypothesis.
EVALuna2:13137

Treatment Strategy for Newly Diagnosed T1 High-grade Bladder Urothelial Carcinoma: New Insights and Updated Recommendations - Klaassen, Zachary; Kamat, Ashish M.; Kassouf, Wassim; Gontero, Paolo; Villavicencio, Humberto; Bellmunt, Joaquim; van Rhijn, Bas W.G.; Hartmann, Arndt; Catto, James W.F.; Kulkarni, Girish S. (European Urology, 2018)
CONTEXT: High-grade T1 (T1HG) bladder cancer (BCa) has a very high likelihood of disease recurrence and progression to muscle invasion. Radical cystectomy is considered the best chance at cure, albeit with a high risk of morbidity, and is overtreatment for some patients. Treatment with bacillus Calmette-Guerin (BCG) allows bladder preservation but may risk disease progression. OBJECTIVE: To systematically review the current literature on the management of T1HG BCa and provide updated treatment recommendations. EVIDENCE ACQUISITION: Medline, EMBASE, and Epub Ahead of Print databases were searched in November 2017 to identify observational cohort studies and controlled trials, between 1946 and 2017, associated with diagnosis, treatment, and prognosis of T1HG BCa. EVIDENCE SYNTHESIS: Clinical understaging and/or persistence of disease is not uncommon at initial transurethral resection (TUR); thus, a second re-TUR is recommended for cases with T1HG BCa. Patients electing a bladder preservation approach should undergo induction BCG therapy followed by a maintenance schedule, while patients with several high-risk features should consider immediate cystectomy and those with BCG-refractory or BCG-unresponsive disease should be considered for early cystectomy. Current phase I/II clinical trials for T1HG patients may offer future bladder preservation therapy approaches. CONCLUSIONS: T1HG tumours are heterogeneous in nature and challenging to treat. Bladder preservation with BCG induction and maintenance, or radical cystectomy is the current standard treatment modality of choice for these tumours. Promising therapies for BCG-unresponsive disease are currently under investigation. PATIENT SUMMARY: Patients with high-grade T1 bladder cancer are at a high risk of tumour recurrence and progression, requiring more aggressive treatment such as bladder removal. Bladder preservation therapies are available (and new therapies are being tested in clinical trials); however, patients should be aware that currently bladder removal is considered the best opportunity for cancer cure.
EVALuna2:34613

Trophoblast Cell Surface Antigen 2 (Trop2) in Chromophobe Renal Cell Carcinoma - Mikuteit, Marie; Steffens, Sandra; Zschäbitz, Stefanie; Autenrieth, Michael; Weichert, Wilko; Hartmann, Arndt; Erlmeier, Franziska (Oncology, 2022)
BACKGROUND: Overexpression of tumor-associated calcium signal transducer 2 (Trop2) is found in many tumor entities. The prognostic value of Trop2 in renal cell renal carcinoma (RCC), especially in nonclear cell RCC, is still unclear. AIM: The aim of this study was to evaluate the prognostic impact of Trop2 expression in a large cohort of patients with chromophobe (ch)RCC. MATERIALS AND METHODS: Patients who underwent renal surgery due to chRCC were retrospectively evaluated. Tumor specimens were analyzed for Trop2 expression by immunohistochemistry. RESULTS: Eighty-one chRCC patients were eligible for analysis, of these 24 (29.6%) patients were positive for Trop2. No significant associations were found for Trop2 expression and clinical attributes in patients with chRCC. The Kaplan-Meier analysis revealed no differences in 5-year overall survival for Trop2- compared to Trop2+ (89.6% vs. 100.0%; p = 0.288). CONCLUSION: In chRCC, Trop2 expression is not associated with survival and other parameters of aggressiveness. Due to the rare incidence of chRCC, further studies with larger cohorts are warranted.
CRIS-Team Scopus Importer:2022-06-10
Keywords: Chromophobe histology; Renal cell carcinoma; Survival; Trophoblast cell surface antigen 2

Tularemia lymphadenitis. An emerging differential diagnosis of necrotizing granulomatous cervical lymphadenitis - Strehl, Johanna; Schoerner, Christoph; Hartmann, Arndt; Agaimy, A. (Pathologe, 2014)
Tularemia is emerging as an important differential diagnosis of necrotizing granulomatous lymphadenitis, particularly in the head and neck region. The causal organism, Francisella tularensis is a Gram-negative coccoid bacterium. Tularemia usually presents with necrotizing granulomatous purulent lymphadenitis featuring multiple mostly small granulomas with geographic necrosis bordered by palisades of histiocytes. Diagnosis is mainly based on these characteristic but non-pathognomonic histological features in conjunction with negative tests for mycobacterial infections and serological confirmation of tularemia-specific antibodies or detection by polymerase chain reaction (PCR). This article describes our experiences with five patients with tularemia lymphadenitis and gives an overview of the diverse histopathological features and the differential diagnosis of this uncommon but possibly underrecognized disease.
EVALuna2:6582

Tumor budding: A predictor for metastasis in the CAM xenograft model - Muenzner, Julienne K.; Ranjan, Raphela A.; Eckstein, Markus; Erber, Ramona; Kunze, Philipp; Geppert, Carol-Immanuel; Rübner, Matthias; Bäuerle, Tobias; Hartmann, Arndt; Schneider-Stock, Regine (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2019-10-22

Tumor budding correlates with discohesive growth pattern, tumor invasiveness and is associated with worse survival of pT1 Non-Muscle-Invasive Bladder Cancer (NMIBC) - Eckstein, Markus; Kimmel, C.; Bruendl, J.; Weber, F.; Denzinger, S.; Gierth, M.; Burger, M.; Hartmann, Arndt; Otto, W.; Breyer, J. (EUROPEAN UROLOGY, 2021)
CRIS-Team WoS Importer:2021-08-20

Tumor budding correlates with tumor invasiveness and predicts worse survival in pT1 non-muscle-invasive bladder cancer - Eckstein, Markus; Kimmel, Charlotte; Bruendl, Johannes; Weber, Florian; Denzinger, Stefan; Gierth, Michael; Burger, Maximilian; Hartmann, Arndt; Otto, Wolfgang; Breyer, Johannes (Scientific Reports, 2021)
Tumor budding is defined as a single cell or a cluster of up to 5 tumor cells at the invasion front. Due to the difficulty of identifying patients at high risk for pT1 non-muscle-invasive bladder cancer (NMIBC) and the difficulties in T1 substaging, tumor budding was evaluated as a potential alternative and prognostic parameter in these patients. Tumor budding as well as growth pattern, invasion pattern and lamina propria infiltration were retrospectively evaluated in transurethral resection of the bladder (TURB) specimens from 92 patients with stage pT1 NMIBC. The presence of tumor budding correlated with multifocal tumors (p = 0.003), discontinuous invasion pattern (p = 0.039), discohesive growth pattern (p < 0.001) and extensive lamina propria invasion (p < 0.001). In Kaplan–Meier analysis, tumor budding was associated with significantly worse RFS (p = 0.005), PFS (p = 0.017) and CSS (p = 0.002). In patients who received BCG instillation therapy (n = 65), the absence of tumor budding was associated with improved RFS (p = 0.012), PFS (p = 0.011) and CSS (p = 0.022), with none of the patients suffering from progression or dying from the disease. Tumor budding is associated with a more aggressive and invasive stage of pT1 NMIBC and a worse outcome. This easy-to-assess parameter could help stratify patients into BCG therapy or early cystectomy treatment groups.
CRIS-Team Scopus Importer:2021-09-17

Tumor microenvironment-dependent epigenetic imprinting in the vasculature predicts colon cancer outcome - Naschberger, Elisabeth; Fuchs, Maximilian; Dickel, Nicholas; Kunz, Meik; Popp, Bernt; Anchang, Charles Gwellem; Demmler, Richard; Lyu, Yanmin; Uebe, Steffen; Ekici, Arif Bülent; Geppert, Carol-Immanuel; Hartmann, Arndt; et al. (Cancer Communications, 2023)
CRIS-Team Scopus Importer:2023-10-27

Tumor Regression Grading After Preoperative Chemoradiotherapy as a Prognostic Factor and Individual-Level Surrogate for Disease-Free Survival in Rectal Cancer - Fokas, Emmanouil; Stroebel, Philipp; Fietkau, Rainer; Ghadimi, Michael; Liersch, Torsten; Grabenbauer, Gerhard G.; Hartmann, Arndt; Kaufmann, Marco; Sauer, Rolf; Graeven, Ullrich; Hoffmanns, Hans; Raab, Hans-Rudolf; et al. (Journal of the National Cancer Institute, 2017)
Background: We investigated tumor regression grading (TRG) as a prognostic marker and individual-level surrogate for disease-free survival (DFS) in patients with rectal carcinoma treated within the Chirurgische Arbeitsgemeinschaft fur Onkologie/Arbeitsgemeinschaft Radiologische Onkologie/Arbeitsgemeinschaft Internistische Onkologie (CAO/ARO/AIO)-04 randomized trial. Methods: TRG was recorded prospectively using the Dworak classification in 1179 patients after preoperative fluorouracil-based chemoradiotherapy (CRT) with or without oxaliplatin. Multivariable analysis was performed using Cox regression models adjusted for treatment arm, resection status, and pathologic stage. Individual-level surrogacy of TRG for DFS was examined using the four Prentice criteria (PC1-4). All statistical tests were two-sided. Results: With a median follow-up of 50 months, the addition of oxaliplatin to fluorouracil-based CRT led to statistically significantly improved three-year DFS (75.9%, 95% CI = 72.3 to 79.5, vs 71.3%, 95% CI = 67.6 to 74.9, P = .04, PC 1) and a shift toward more advanced TRG groups ( P < .001, PC 2) compared with CRT with fluorouracil alone. The three-year DFS was 64.6% (95% CI = 57.3 to 71.9), 77.6% (95% CI = 74.5 to 80.7), and 92.3% (95% CI = 88.4 to 96.2) for TRG 0 + 1 (poor regression), TRG 2 + 3 (intermediate regression), and TRG 4 (complete regression), respectively ( P < .001, PC 3). TRG constituted an independent prognostic factor for DFS (TRG 2 + 3 vs TRG 0 + 1, HR = 0.68, 95% CI = 0.51 to 0.90, P = .007). Due to multicollinearity, TRG 4 and pathologic stage could not be tested within the same model. The treatment effect on DFS was captured by TRG, satisfying individual-level PC4. Conclusions: Higher TRG after preoperative CRT predicted a favorable long-term outcome. At the individual patient level, TRG was a surrogate marker for DFS. Further phase III trials are needed to validate TRG as a surrogate at trial level.
EVALuna2:32865

Tumor regression grading after preoperative chemoradiotherapy as prognostic factor and individual-level surrogate for disease-free survival in rectal cancer: Results of the CAO/ARO/AIO-04 multicentre, open-label, randomised, phase 3 trial - Fokas, E.; Stroebel, P.; Fietkau, Rainer; Ghadimi, M.; Liersch, T.; Grabenbauer, G.; Hartmann, Arndt; Kaufmann, M.; Sauer, Rolf; Graeven, U.; Hoffmanns, H.; Raab, H-R; et al. (2017)
EVALuna2:32881

Tumor–Stroma Ratio in Colorectal Cancer—Comparison between Human Estimation and Automated Assessment - Firmbach, Daniel; Benz, Michaela; Kuritcyn, Petr; Bruns, Volker; Lang-Schwarz, Corinna; Stübs, Frederik; Merkel, Susanne; Leikauf, Leah-Sophie; Braunschweig, Anna Lea; Oldenburger, Angelika; Gloßner, Laura; Abele, Niklas; et al. (Cancers, 2023)
The tumor–stroma ratio (TSR) has been repeatedly shown to be a prognostic factor for survival prediction of different cancer types. However, an objective and reliable determination of the tumor–stroma ratio remains challenging. We present an easily adaptable deep learning model for accurately segmenting tumor regions in hematoxylin and eosin (H&E)-stained whole slide images (WSIs) of colon cancer patients into five distinct classes (tumor, stroma, necrosis, mucus, and background). The tumor–stroma ratio can be determined in the presence of necrotic or mucinous areas. We employ a few-shot model, eventually aiming for the easy adaptability of our approach to related segmentation tasks or other primaries, and compare the results to a well-established state-of-the art approach (U-Net). Both models achieve similar results with an overall accuracy of 86.5% and 86.7%, respectively, indicating that the adaptability does not lead to a significant decrease in accuracy. Moreover, we comprehensively compare with TSR estimates of human observers and examine in detail discrepancies and inter-rater reliability. Adding a second survey for segmentation quality on top of a first survey for TSR estimation, we found that TSR estimations of human observers are not as reliable a ground truth as previously thought.
CRIS-Team Scopus Importer:2023-06-09
Keywords: colorectal cancer; deep learning; few-shot learning; image analysis; segmentation; tumor–stroma ratio; U-Net

Tumour immune microenvironment drives prognostic relevance correlating with bladder cancer subtypes - Eckstein, Markus; Strissel, Pamela; Pfannstiel, C.; Chiappinelli, K.; Sikic, D.; Wach, S.; Taubert, Helge; Wullich, Bernd; Keck, Bastian; Wirtz, R.; Breyer, J.; Burger, M.; et al. (VIRCHOWS ARCHIV, 2019)
CRIS-Team WoS Importer:2019-09-27

Tumour-infiltrating inflammatory cells in early breast cancer: An underrated prognostic and predictive factor? - Schnellhardt, Sören; Erber, Ramona; Büttner-Herold, Maike; Rosahl, Marie Charlotte; Ott, Oliver; Strnad, Vratislav; Beckmann, Matthias; King, Lillian; Hartmann, Arndt; Fietkau, Rainer; Distel, Luitpold (International Journal of Molecular Sciences, 2020)
The role of tumour-infiltrating inflammatory cells (TIICs) in the disease progression of hormone-receptor-positive breast cancer (HR+ BC) is largely unclear since it is generally regarded as the least immunogenic BC subtype. This study investigated the prognostic significance of CD1a+ dendritic cells, CD20+ B cells, CD45RO+ memory T cells and CD4+ T-helper cells in HR+ BC. One hundred and forty-six patients were treated for early stage, distant-metastases-free HR+ BC in an accelerated partial breast irradiation (APBI) phase II trial. Immunohistochemistry was used to double-stain two adjoining sets of tissue microarrays from pre-RT (radiotherapy) tumour resection samples for CD1a/CD20 and CD45RO/CD4. Cell densities of CD1a+, CD20+, CD45RO+ and CD4+ TIICs in the stromal and intraepithelial compartment were registered semiautomatically. High densities of CD20+ and CD4+ TIICs were strongly associated with reduced disease-free survival (DFS), while high stromal CD45RO+ TIIC densities were indicators of subsequent successful treatment. An immunoscore based on CD20+ and CD45RO+ TIIC densities identified three different risk groups (p < 0.001). Thus, contrary to current assumptions, intratumoural immune cell composition might be an important prognostic indicator and a possible contributing factor in the outcome of HR+ BC and should be the subject of further research. Specifically, B-cell infiltration entailed an increased relapse rate and could play an important role in disease progression.
CRIS-Team Scopus Importer:2020-11-20
Keywords: Accelerated partial breast irradiation; Breast cancer; CD1a; CD20; CD4; CD45RO; Hormone receptor positive; Immunoscore; Prognosis; TIL

Tumour-infiltrating lymphocytes and prognosis in different subtypes of breast cancer: a pooled analysis of 3771 patients treated with neoadjuvant therapy - Denkert, Carsten; Von Minckwitz, Gunter; Darb-Esfahani, Silvia; Lederer, Bianca; Heppner, Barbara I.; Weber, Karsten E.; Budczies, Jan; Huober, Jens; Klauschen, Frederick; Furlanetto, Jenny; Schmitt, Wolfgang D.; Blohmer, Jens-Uwe; et al. (Lancet Oncology, 2018)
BACKGROUND: Tumour-infiltrating lymphocytes (TILs) are predictive for response to neoadjuvant chemotherapy in triple-negative breast cancer (TNBC) and HER2-positive breast cancer, but their role in luminal breast cancer and the effect of TILs on prognosis in all subtypes is less clear. Here, we assessed the relevance of TILs for chemotherapy response and prognosis in patients with TNBC, HER2-positive breast cancer, and luminal-HER2-negative breast cancer. METHODS: Patients with primary breast cancer who were treated with neoadjuvant combination chemotherapy were included from six randomised trials done by the German Breast Cancer Group. Pretherapeutic core biopsies from 3771 patients included in these studies were assessed for the number of stromal TILs by standardised methods according to the guidelines of the International TIL working group. TILs were analysed both as a continuous parameter and in three predefined groups of low (0-10% immune cells in stromal tissue within the tumour), intermediate (11-59%), and high TILs (≥60%). We used these data in univariable and multivariable statistical models to assess the association between TIL concentration and pathological complete response in all patients, and between the amount of TILs and disease-free survival and overall survival in 2560 patients from five of the six clinical trial cohorts. FINDINGS: In the luminal-HER2-negative breast cancer subtype, a pathological complete response (pCR) was achieved in 45 (6%) of 759 patients with low TILs, 48 (11%) of 435 with intermediate TILs, and 49 (28%) of 172 with high TILs. In the HER2-positive subtype, pCR was observed in 194 (32%) of 605 patients with low TILs, 198 (39%) of 512 with intermediate TILs, and 127 (48%) of 262 with high TILs. Finally, in the TNBC subtype, pCR was achieved in 80 (31%) of 260 patients with low TILs, 117 (31%) of 373 with intermediate TILs, and 136 (50%) of 273 with high TILs (p<0·0001 for each subtype, χ2 test for trend). In the univariable analysis, a 10% increase in TILs was associated with longer disease-free survival in TNBC (hazard ratio [HR] 0·93 [95% CI 0·87-0·98], p=0·011) and HER2-positive breast cancer (0·94 [0·89-0·99], p=0·017), but not in luminal-HER2-negative tumours (1·02 [0·96-1·09], p=0·46). The increase in TILs was also associated with longer overall survival in TNBC (0·92 [0·86-0·99], p=0·032), but had no association in HER2-positive breast cancer (0·94 [0·86-1·02], p=0·11), and was associated with shorter overall survival in luminal-HER2-negative tumours (1·10 [1·02-1·19], p=0·011). INTERPRETATION: Increased TIL concentration predicted response to neoadjuvant chemotherapy in all molecular subtypes assessed, and was also associated with a survival benefit in HER2-positive breast cancer and TNBC. By contrast, increased TILs were an adverse prognostic factor for survival in luminal-HER2-negative breast cancer, suggesting a different biology of the immunological infiltrate in this subtype. Our data support the hypothesis that breast cancer is immunogenic and might be targetable by immune-modulating therapies. In light of the results in luminal breast cancer, further research investigating the interaction of the immune system with different types of endocrine therapy is warranted. FUNDING: Deutsche Krebshilfe and European Commission.
EVALuna2:34264

Tumour‐infiltrating lymphocytes (Tils) and pd‐l1 expression correlate with lymph node metastasis, high‐grade transformation and shorter metastasis‐free survival in patients with acinic cell carcinoma (acicc) of the salivary glands - Hiß, Selina; Eckstein, Markus; Segschneider, Paul; Mantsopoulos, Konstantinos; Iro, Heinrich; Hartmann, Arndt; Agaimy, Abbas; Haller, Florian; Müller, Sarina Katrin (Cancers, 2021)
Objectives: The aim of this study was to assess the number of tumour‐infiltrating lympho-cytes (TILs) and the expression of Programmed Cell Death 1 Ligand 1 (PD‐L1) in Acinic Cell Carcinoma (AciCC) of the salivary glands, to enable a correlation with clinico‐pathological features and to analyse their prognostic impact. Methods: This single centre retrospective study represents a cohort of 36 primary AciCCs with long‐term clinical follow‐up. Immunohistochemically defined immune cell subtypes, i.e., those expressing T‐cell markers (CD3, CD4 and CD8) or a B‐cell marker (CD20) were characterized on tumour tissue sections. The number of TILs was quantitatively evaluated using software for digital bioimage analysis (QuPath). PD‐L1 expression on the tumour cells and on immune cells was assessed immunohistochemically employing established scoring criteria: tu-mour proportion score (TPS), Ventana immune cell score (IC‐Score) and combined positive score (CPS). Results: Higher numbers of tumour‐infiltrating T‐ and B‐ lymphocytes were significantly associated with high‐grade transformation. Furthermore, higher counts of T‐lymphocytes correlated with node‐positive disease. There was a significant correlation between higher levels of PD‐ L1 expression and lymph node metastases as well as the occurrence of high‐grade transformation. Moreover, PD‐L1 CPS was associated with poor prognosis regarding metastasis‐free survival (p = 0.049). Conclusions: The current study is the first to demonstrate an association between PD‐L1 expression and lymph node metastases as well as grading in AciCCs. In conclusion, increased immune cell infiltration of T and B cells as well as higher levels of PD‐L1 expression in AciCC in association with high‐grade transformation, lymph node metastasis and unfavourable prognosis suggests a rel-evant interaction between tumour cells and immune cell infiltrates in a subset of AciCCs, and might represent a rationale for immune checkpoint inhibition.
CRIS-Team Scopus Importer:2021-03-05
Keywords: Acinic cell carcinoma; Checkpoint inhibition; Immuno‐oncology; PD‐L1; Tumour‐infiltrating lymphocytes

Un- and dedifferentiated endometrial carcinoma A rare entity with a wide range of differential diagnosis - Hoehn, A. K.; Brambs, C. E.; Opitz, S.; Erber, Ramona; Hartmann, Arndt; Horn, L-C (Pathologe, 2019)
Dedifferentiated endometrial carcinomas (ECs) are composed of undifferentiated EC and a FIGO grade 1 or 2 endometrioid carcinoma. The undifferentiated component represents a malignant epithelial neoplasm with no obvious differentiation and immunohistochemical loss of PAX8, E-cadherin and focal expression of EMA and/or CK18 and the predominant presence of nuclear staining for INI1 (SMARCB1) and BRG1 (SMARCA4). The main differential diagnoses include poorly differentiated endometrioid EC, neuroendocrine carcinoma, lymphoma, plasmocytoma, high-grade endometrial stromal sarcomas, undifferentiated uterine sarcomas (UUS), carcinosarcomas, and metastases to the endometrium. The histogenesis is not yet fully understood and molecular data are still limited. Some tumors represent a loss of MHL1 and PMS2 staining due to MLH1-promotor methylation. Rare cases are associated with Lynch syndrome or POLE mutation. The un- or dedifferentiated EC represents a high-grade endometrial carcinoma that requires extended surgery and indicates a poor prognosis. In cases with mismatch repair protein deficiency or POLE mutation, immuno-oncological treatment with checkpoint inhibitors are a therapeutic option.
CRIS-Team WoS Importer:2019-10-22

Unbiased high-dimensional flow cytometry identified NK and DC immune cell signature in Luminal A-type and triple negative breast cancer - Heger, Lukas; Heidkamp, Gordon Frederik; Amon, Lukas; Nimmerjahn, Falk; Bäuerle, Tobias; Maier, Andreas; Erber, Ramona; Hartmann, Arndt; Hack, Carolin; Rübner, Matthias; Hübner, Hanna; Fasching, Peter; et al. (OncoImmunology, 2024)
Breast cancer is the most common malignancy in women worldwide and a highly heterogeneous disease. Four different subtypes are described that differ in the expression of hormone receptors as well as the growth factor receptor HER2. Treatment modalities and survival rate depend on the subtype of breast cancer. However, it is still not clear which patients benefit from immunotherapeutic approaches such as checkpoint blockade. Thus, we aimed to decipher the immune cell signature of the different breast cancer subtypes based on high-dimensional flow cytometry followed by unbiased approaches. Here, we show that the frequency of NK cells is reduced in Luminal A and B as well as triple negative breast cancer and that the phenotype of residual NK cells is changed toward regulatory CD11b−CD16− NK cells. Further, we found higher frequencies of PD-1+ CD4+ and CD8+ T cells in triple negative breast cancer. Moreover, while Luminal A-type breast cancer was enriched for CD14+ cDC2 (named type 3 DC (DC3)), CD14− cDC2 (named DC2) were more frequent in triple negative breast cancer. In contrast, HER2-enriched breast cancer did not show major alterations in the composition of the immune cell compartment in the tumor microenvironment. These findings suggest that patients with Luminal A- and B-type as well as triple negative breast cancer might benefit from immunotherapeutic approaches targeting NK cells.
CRIS-Team Scopus Importer:2024-01-12
Keywords: Breast cancer; immune cell signature; NK cells; PD-1; tumor microenvironment

Uncovering Hereditary Tumor Syndromes: Emerging Role of Surgical Pathology - Agaimy, Abbas; Hartmann, Arndt (Seminars in Diagnostic Pathology, 2018)
With the increased use of modern next generation sequencing technologies in routine molecular pathology practice, the proportion of cancer cases with a definite or probable hereditary background seems to be steadily increasing. Currently, it is assumed that ≥10% of all malignancies develop in the setting of germline predisposition. Diagnosis and recognition of cancer predisposition syndromes relies not rarely on distinctive histopathological features that proved to be highly valuable and reproducible in uncovering those diseases that would otherwise have gone undetected by clinicians as being hereditary in nature. This is especially true in case of new mutations without suspicious family history. Example of such entities are fumarate hydratase-deficient renal cell carcinoma (RCC), succinate dehydrogenase-deficient RCC, hereditary gastrointestinal stromal tumor syndromes and many other diseases. It is remarkable that many of these inherited cancer syndromes do present as unifocal disease with highly variable age of onset so that many of them are misinterpreted as sporadic on clinical grounds. Availability of specialized cancer screening programs and disease-specific follow-up schemes for several hereditary cancer syndromes encourages the recognition of such disorders, so that "at risk patients" can be enrolled in such programs for early detection and timely intervention/ treatment of these malignancies which are in the majority of cases aggressive. In several conditions, as in familial adenomatous polyposis coli (FAP), well established prophylactic surgical interventions may be adopted to prevent the disease manifestations, highlighting the importance of the timely recognition of these potentially life-limiting neoplasms. In this review, the clinicopathological, demographic and histological features that are considered highly suggestive of a hereditary basis of "a neoplasm under consideration" are highlighted and discussed briefly. The details of some of these entities are in addition dealt with in reviews devoted to them in this special issue.
EVALuna2:33963

Understanding PD-L1 Testing in Breast Cancer: A Practical Approach - Erber, Ramona; Hartmann, Arndt (Breast Care, 2020)
Background: Immune checkpoint inhibitors (ICI) have changed therapy strategies for cancer patients tremendously. Some approved ICI acquire testing of PD-L1 expression on tumor and/or immune cells. However, since PD-L1 testing is a comprehensive issue with various assays, antibody clones, scoring methods, and cut-offs, we aimed to summarize the recommendations and technical and histopathological issues of diagnostic PD-L1 assessment with an emphasis on invasive breast cancer (IBC). Summary: Besides other (pre)analytical considerations, selecting the most adequate PD-L1 immunohistochemical assay/antibody clone is important. In-house assay validation, prediagnostic training, and internal and external quality assurance should be implemented. The current most relevant PD-L1 assays and scores will be explained in this review. Moreover, recommendations for PD-L1 testing in IBC are outlined. Key Messages: Atezolizumab plus nab-paclitaxel therapy is approved for adult patients with locally advanced or metastatic triple negative breast cancer (mTNBC), if the tumor-Associated immune cells express PD-L1.-This PD-L1 immune cell positivity is defined as an immune cell (IC) score, which refers to the area occupied by PD-L1 positive immune cells (lymphocytes, dendritic cells, macrophages, and granulocytes) as a percentage of the whole tumor area. The cut-off is an IC score ≥1%. In the approval study for atezolizumab in mTNBC, IC score was assessed using the Ventana PD-L1 SP142 assay. Other assays or laboratory developed tests may be used depending on country-specific drug approvals. However, harmonization studies have to show whether other PD-L1 tests are reliable and of clinical value to predict the response of breast cancer patients to ICI.
CRIS-Team Scopus Importer:2020-10-30

Undifferentiated and dedifferentiated urological carcinomas: lessons learned from the recent developments - Agaimy, Abbas; Hartmann, Arndt; Trpkov, Kiril; Hes, Ondrej (Seminars in Diagnostic Pathology, 2021)
Loss of the morphological and immunophenotypic characteristics of a neoplasm is a well-known phenomenon in surgical pathology and occurs across different tumor types in almost all organs. This process may be either partial, characterized by transition from well differentiated to undifferentiated tumor component (=dedifferentiated carcinomas) or complete (=undifferentiated carcinomas). Diagnosis of undifferentiated carcinoma is significantly influenced by the extent of sampling. Although the concept of undifferentiated and dedifferentiated carcinoma has been well established for other organs (e.g. endometrium), it still has not been fully defined for urological carcinomas. Accordingly, undifferentiated/ dedifferentiated genitourinary carcinomas are typically lumped into the spectrum of poorly differentiated, sarcomatoid, or unclassified (NOS) carcinomas. In the kidney, dedifferentiation occurs across all subtypes of renal cell carcinoma (RCC), but certain genetically defined RCC types (SDH-, FH- and PBRM1- deficient RCC) seem to have inherent tendency to dedifferentiate. Histologically, the undifferentiated component displays variable combination of four patterns: spindle cells, pleomorphic giant cells, rhabdoid cells, and undifferentiated monomorphic cells with/without prominent osteoclastic giant cells. Any of these may occasionally be associated with heterologous mesenchymal component/s. Their immunophenotype is often simple with expression of vimentin and variably pankeratin or EMA. Precise subtyping of undifferentiated (urothelial versus RCC and the exact underlying RCC subtype) is best done by thorough sampling supplemented as necessary by immunohistochemistry (e.g. FH, SDHB, ALK) and/ or molecular studies. This review discusses the morphological and molecular genetic spectrum and the recent develoments on the topic of dedifferentiated and undifferentiated genitourinary carcinomas.
CRIS-Team Scopus Importer:2021-10-08
Keywords: Dedifferentiated carcinoma; FH; Fumarate hydratase; Renal cell carcinoma; SDH; SDHB; SMARCB1; Succinate dehydrogenase; SWI/SNF; Undifferentiated carcinoma; Urothelial carcinoma

Undifferentiated large cell/rhabdoid carcinoma presenting in the intestines of patients with concurrent or recent non-small cell lung cancer (NSCLC): clinicopathologic and molecular analysis of 14 cases indicates an unusual pattern of dedifferentiated metastases - Agaimy, Abbas; Daum, Ondrej; Michal, Michal; Schmidt, Mona W.; Stöhr, Robert; Hartmann, Arndt; Lauwers, Gregory Y. (Virchows Archiv, 2021)
Undifferentiated carcinoma metastatic to the bowel is uncommon in surgical pathology practice and might be confused with primary gastrointestinal carcinoma, melanoma, lymphoma, and others. We present 14 cases of uni- (n = 9) or multifocal (n = 5) undifferentiated large cell/rhabdoid carcinoma presenting in the bowel of patients with concurrent (n = 9) or recent (diagnosed 1 to 25 months earlier; median, 4) non-small cell lung cancer (NSCLC). Patients were 6 females and 8 males, aged 52 to 85 years. Primary NSCLC was verified histologically in 10 cases and by imaging in 4. The undifferentiated histology was present in the lung biopsy in 4/10 patients (as sole pattern in 3 and combined with adenocarcinoma in 1) and was limited to the intestinal metastases in the remainder. PDL1 was strongly expressed in 7/9 cases (CPS: 41 to 100). Loss of at least one SWI/SNF subunit was detected in 7/13 cases (54%). SMARCA2 loss (n = 6) was most frequent and was combined with SMARCA4 loss in one case. PBRM1 loss was observed in one tumor. Successful molecular testing of 11 cases revealed BRAF mutations in 4 (3 were non-V600E variants), KRAS mutations in 3, and wildtype in 4. None had EGFR mutations. Analysis of 4 paired samples revealed concordant KRAS (2) and BRAF (1) mutations or wildtype (1). Our study indicates that undifferentiated carcinoma within the intestines of patients with concurrent/recent NSCLC represents dedifferentiated metastasis from the NSCLC. Recognition of this unusual presentation is cardinal to avoid misdiagnosis with inappropriate therapeutic and prognostic implications.
CRIS-Team Scopus Importer:2021-02-05
Keywords: Anaplastic carcinoma; Gastrointestinal; Intestine; Large cell carcinoma; Metastasis; NSCLC; Rhabdoid carcinoma; SMARCA4; SWI/SNF; Undifferentiated carcinoma

Uninflamed immunologic microenvironment of muscle-invasive bladder cancer associates with activating FGFR3 gene alterations. - Weyerer, Veronika; Stöhr, Robert; Strissel, Pamela; Strick, Reiner; Bolenz, Christian; Hartmann, Arndt; Erben, Philipp; Eckstein, Markus (CLINICAL CANCER RESEARCH, 2020)
CRIS-Team WoS Importer:2020-08-28

Updated analysis of the phase II CheckRad-CD8 trial: First-line treatment of locally advanced head and neck squamous cell carcinoma with induction chemoimmunotherapy followed by radioimmunotherapy - Hecht, Markus; Eckstein, Markus; Kallies, Annett; von der Grün, Jens; Illmer, Thomas; Klautke, Gunther; Laban, Simon; Hautmann, Matthias; Brunner, Thomas; Tamaskovics, Bálint; Hinke, Axel; Zhou, Jianguo; et al. (35. Deutscher Krebskongress, Krebsmedizin: Schnittstellen zwischen Innovation und Versorgung, 2022)
CRIS-Team WoS Importer:2022-12-16

Update for the practicing pathologist: The International Consultation On Urologic Disease-European association of urology consultation on bladder cancer - Amin, Mahul B.; Smith, Steven C.; Reuter, Victor E.; Epstein, Jonathan I.; Grignon, David J.; Hansel, Donna E.; Lin, Oscar; Mckenney, Jesse K.; Montironi, Rodolfo; Paner, Gladell P.; Al-Ahmadie, Hikmat A.; Algaba, Ferran; et al. (Modern Pathology, 2015)
The International Consultations on Urological Diseases are international consensus meetings, supported by the World Health Organization and the Union Internationale Contre le Cancer, which have occurred since 1981. Each consultation has the goal of convening experts to review data and provide evidence-based recommendations to improve practice. In 2012, the selected subject was bladder cancer, a disease which remains a major public health problem with little improvement in many years. The proceedings of the 2nd International Consultation on Bladder Cancer, which included a 'Pathology of Bladder Cancer Work Group,' have recently been published; herein, we provide a summary of developments and consensus relevant to the practicing pathologist. Although the published proceedings have tackled a comprehensive set of issues regarding the pathology of bladder cancer, this update summarizes the recommendations regarding selected issues for the practicing pathologist. These include guidelines for classification and grading of urothelial neoplasia, with particular emphasis on the approach to inverted lesions, the handling of incipient papillary lesions frequently seen during surveillance of bladder cancer patients, descriptions of newer variants, and terminology for urine cytology reporting.
EVALuna2:6755

Uropathology - Hartmann, Arndt; Knuechel-Clarke, R.; Kristiansen, G. (Pathologe, 2016)
EVALuna2:6787

Urothelial Bladder Cancer: An Update on Molecular Pathology with Clinical Implications - Bertz, Simone; Eckstein, Markus; Stoehr, Robert; Weyerer, Veronika; Hartmann, Arndt (European Urology Supplements, 2017)
Urothelial bladder cancer is a heterogenous disease with distinct clinical and histopathological features. In the last few years it became clear that papillary, mostly noninvasive, disease with few molecular changes and aggressive urothelial carcinoma are genomically separate diseases. Recently, several studies found that invasive bladder cancer can also be separated into several molecular subgroups. In the present review we summarize molecular alterations, diagnostic markers, and molecular subgroups in urothelial bladder cancer and discuss their clinical relevance for prognosis, prediction of recurrence and progression, and therapeutic response to chemotherapy, radiotherapy, and immunotherapy. (C) 2017 European Association of Urology. Published by Elsevier B.V. All rights reserved.
EVALuna2:33791

Use of NGS Gene Panel Analyzes for molecularly targeted System Therapy - Roesch, Johannes; Haller, Florian; Lettmaier, Sebastian; Haderlein, Marlen; Hartmann, Arndt; Moskalev, Evgeny; Tögel, Lars; Putz, Florian; Weissmann, T.; Schubert, P.; Höfler, Daniel; Fietkau, Rainer; et al. (STRAHLENTHERAPIE UND ONKOLOGIE, 2020)
CRIS-Team WoS Importer:2020-10-02

Using Probability for Pathological Complete Response (pCR) as a Decision Support Marker for Neoadjuvant Chemotherapy in HER2 Negative Breast Cancer Patients - a Survey Among Physicians - Gaß, Paul; Untch, Michael; Mueller, Volkmar; Moebus, Volker; Thomssen, Christoph; Häberle, Lothar; Erber, Ramona; Hein, Alexander; Jud, Sebastian; Lux, Michael P.; Hack, Carolin; Hartmann, Arndt; et al. (Geburtshilfe und Frauenheilkunde, 2018)
Background: In women with early breast cancer, a pathological complete response (pCR) after neoadjuvant chemotherapy is reported to be associated with an improvement of the survival. The aim of this survey among physicians was to investigate whether the probability of achieving pCR in patients with a hormone receptor-positive, HER2-negative disease encourages physicians to recommend neoadjuvant chemotherapy. Methods: The study was conducted via an online survey that was sent to 493 physicians, who were either known as members of national guideline committees, heads of breast cancer centers, being high recruiters in clinical trials or leading a private practice. Participants were asked about a specific case that should resemble patients for whom it is unclear, whether they should be treated with chemotherapy. Results: 113 (24.5%) physicians participated at the survey, out of which 96.5% had a work experience of more than 10 years and 94.7% were board certified in their specialty. A total of 84.1% would consider pCR for a decision concerning neoadjuvant chemotherapy. With regard to the pCR probability, 2.7 and 10.6% of the participants demanded at least a pCR rate of 5 and 10%, respectively, while 25.7% were satisfied with 20% probability, and another 25.7% with a pCR rate of 30%. Conclusions: The vast majority of the long-term experienced physicians would embrace the implementation of a further method such as the prediction of pCR probability in clinical routine to support decision making regarding the necessity of neoadjuvant chemotherapy. The cut-off of around 30% pCR probability seems to be a realizable rate to distinguish patient groups.
EVALuna2:34856

Utility of stromal tumor infiltrating lymphocyte scoring (sTILs) for risk stratification of patients with muscle-invasive urothelial bladder cancer after radical cystectomy - Sikic, Danijel; Weyerer, Veronika; Geppert, Carol-Immanuel; Bertz, Simone; Lange, Fabienne; Taubert, Helge; Wach, Sven; Schmitz-Draeger, Bernd J.; Wullich, Bernd; Hartmann, Arndt; Eckstein, Markus (Urologic Oncology-Seminars and Original Investigations, 2021)
Background: Multi-omics analyses of muscle-invasive bladder cancer (MIBC) demonstrated that specific patterns of tumor infiltrating lymphocytes (TILs) associates with improved outcomes in patients treated with radical cystectomy. However, methodologies for simple and robust quantification of TILs, especially for daily practice purposes, are lacking. Thus, we investigated the feasibility of stromal TIL scoring on hematoxylin/eosin stained (HE) slides in MIBC. Materials and methods: sTILs were scored on HE whole slides of 241 MIBC patients treated with radical cystectomy and adjuvant chemotherapy. Median infiltration of 10% was used as objective cut-off. Additionally, immunohistochemistry was performed on spatially organized tissue microarrays to quantify key immune cell populations objectively for correlational analyses with sTIL scoring results (CD3+/Pan-T-cells, CD8+/cytotoxic T-Cells, CD56+/NK-cells, CD68+/macrophages). sTILs amounts were correlated with clinicopathological features, recurrence-free (RFS), disease-specific (DSS), and overall survival (OS). Results: sTIL amounts correlated moderately to strongly with quantitatively estimated amounts of pan-T-cells (r = 0.73, P <0.0001), cytotoxic T-cells (r = 0.73, P <0.0001), NK-cells (r = 0.68, P <0.0001), macrophages (r = 0.55, P <0.0001) and with pan-cytotoxic immune infiltration (r = 0.78, P <0.0001), thus reflecting overall infiltration with key immune cell populations. sTIL infiltration ≥10% was associated with significantly higher 5-year OS (45.5% vs. 19.8%), DSS (56.6% vs. 25.6%) and RFS (56.2% vs. 18.9%; P <0.0001 for all three comparisons) rates, and lower pT-stage (P = 0.015), lower pN-stage (P = 0.028), lower rates of lymphovascular invasion (P = 0.0003) and blood vessel invasion (P = 0.01) when compared to sTIL infiltration of <10%. Multivariable regressions models confirmed sTILs as strongest independent predictor for improved outcomes following radical cystectomy. Conclusions: HE based sTIL scoring is a reliable tool to assess MIBC inflammation status and to stratify the survival of MIBC patients undergoing radical cystectomy. sTIL amount is an independent predictor for improved survival, and might be an useful, routinely applicable tool to identify patients benefiting from perioperative platinum-based chemotherapy and checkpoint inhibitor therapy. However, external validation of our data is required.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Bladder cancer; Cystectomy; Prognosis; sTILs; TILs; Urothelial cancer

Validation of the 'Inflammatory Bowel Disease-Distribution, Chronicity, Activity [IBD-DCA] Score' for Ulcerative Colitis and Crohn ' s Disease - Lang-Schwarz, Corinna; Angeloni, Miriam; Agaimy, Abbas; Atreya, Raja; Becker, Christoph; Dregelies, Theresa; Danese, Silvio; Flejou, Jean-Francois; Gassler, Nikolaus; Grabsch, Heike; Hartmann, Arndt; Kamaradova, Katerina; et al. (Journal of Crohns & Colitis, 2021)
Background and Aims: Histological scoring plays a key role in the assessment of disease activity in ulcerative colitis [UC] and is also important in Crohns disease [CD]. Currently, there is no common scoring available for UC and CD. We aimed to validate the Inflammatory Bowel Disease [IBD]-Distribution [D], Chronicity [C], Activity [A] score [IBD-DCA score] for histological disease activity assessment in IBD.
CRIS-Team WoS Importer:2021-11-12

Variable expression of the disialoganglioside gd2 in breast cancer molecular subtypes - Erber, Ramona; Kailayangiri, Sareetha; Hübner, Hanna; Rübner, Matthias; Hartmann, Arndt; Häberle, Lothar; Meyer, Julia; Völkl, Simon; Mackensen, Andreas; Landgraf, Laura; Geppert, Carol-Immanuel; Schulz-Wendtland, Rüdiger; et al. (Cancers, 2021)
The disialoganglioside GD2 is a tumor-associated antigen that may allow for the application of targeted immunotherapies (anti-GD2 antibodies, GD2 CAR T cells) in patients with neuroblastoma and other solid tumors. We retrospectively investigated GD2 expression in a breast cancer cohort, using immunohistochemistry (IHC) and immunofluorescence (IF) on tissue microarrays (TMAs), and its impact on survival. GD2 expression on IHC (n = 568) and IF (n = 503) was investigated in relation to subtypes and patient outcome. Overall, 50.2% of the 568 IHC-assessed samples and 69.8% of the 503 IF-assessed samples were GD2-positive. The highest proportion of GD2-positive tumors was observed in luminal tumors. Significantly fewer GD2-positive cases were detected in triple-negative breast cancer (TNBC) compared with other subtypes. The proportion of GD2-expressing tumors were significantly lower in HER2-positive breast cancer in comparison with luminal tumors on IF staining (but not IHC). GD2 expression of IHC or IF was not significantly associated with disease-free or overall survival, in either the overall cohort or in individual subtypes. However, GD2 expression can be seen in more than 50% of breast cancer cases, with the highest frequency in hormone receptorpositive tumors. With this high expression frequency, patients with GD2-positive advanced breast cancer of all subtypes may benefit from GD2-targeting immunotherapies, which are currently subject to clinical testing.
CRIS-Team Scopus Importer:2021-11-12
Keywords: Breast cancer; Disialoganglioside; GD2; Immunofluorescence; Immunohistochemistry; Prognosis

Variant morphology and random chromosomal integration of BK polyomavirus in posttransplant urothelial carcinomas - Bertz, Simone; Enßer, Armin; Stöhr, Robert; Eckstein, Markus; Apel, Hendrik; Mayr, Doris; Büttner-Herold, Maike; Gaisa, Nadine Therese; Comperat, Eva; Wullich, Bernd; Hartmann, Arndt; Knöll, Antje (Modern Pathology, 2020)
BK polyomavirus (BKPyV) causes major complications in solid organ transplant recipients but little is known about its role in the development of urothelial carcinoma (UC) during immunosuppression. Immunohistochemistry (IHC) screening for polyomavirus large T antigen (LTag) was performed in 94 micropapillary UC (MPUC), 480 unselected UC, 199 muscle invasive UC (including 83 UC with variant differentiation), 76 cases of plasmocytoid, nested and large nested UC and 15 posttransplant UC. LTag expressing UC were reevaluated regarding their histomorphological features and characterized by IHC for p53 and HER2, chromogenic in situ hybridization for HER2 and SNaPshot analysis of the TERT promoter and HRAS. Real-time PCR and next generation sequencing (NGS) were performed to search for BKPyV-DNA and for variants in the tumor and viral genomes. We detected five LTag expressing UC which were diagnosed between 2 and 18 years after kidney (n = 4) or heart (n = 1) transplantation. 89 MPUC without history of organ transplantation and overall 755 UC (including cases with variant histology) were LTag negative. Of the five LTag expressing UC, three were MPUC, one showed extensive divergent differentiation with Mullerian type clear cell carcinoma, and one displayed focal villoglandular differentiation. All five tumors had aberrant nuclear p53 expression, 2/5 were HER2-amplified, and 3/5 had TERT promoter mutations. Within the 50 most common cancer related genes altered in UC we detected very few alterations and no TP53 mutations. BKPyV-DNA was present in 5/5 UC, chromosomal integration of the BKPyV genome was detectable in 4/5 UC. Two UC with BKPyV integration showed small deletions in the BKPyV noncoding control region (NCCR). The only UC without detectable BKPyV integration had a high viral load of human herpesvirus 6 (HHV-6). Our results suggest that LTag expression of integrated BKPyV genomes and resulting p53 inactivation lead to aggressive high-grade UC with unusual, often micropapillary morphology.
CRIS-Team WoS Importer:2020-02-28

Vascular occlusion by neutrophil extracellular traps in COVID-19 - Leppkes, Moritz; Knopf, Jasmin; Naschberger, Elisabeth; Lindemann, Aylin; Singh, Jeeshan; Herrmann, Irmgard; Stürzl, Michael; Staats, Léonie; Mahajan, Aparna; Kremer, Anita; Amann, Kerstin Ute; Evert, Katja; et al. (EBioMedicine, 2020)
Background: Coronavirus induced disease 2019 (COVID-19) can be complicated by severe organ damage leading to dysfunction of the lungs and other organs. The processes that trigger organ damage in COVID-19 are incompletely understood. Methods: Samples were donated from hospitalized patients. Sera, plasma, and autopsy-derived tissue sections were examined employing flow cytometry, enzyme-linked immunosorbent assays, and immunohistochemistry. Patient findings: Here, we show that severe COVID-19 is characterized by a highly pronounced formation of neutrophil extracellular traps (NETs) inside the micro-vessels. Intravascular aggregation of NETs leads to rapid occlusion of the affected vessels, disturbed microcirculation, and organ damage. In severe COVID-19, neutrophil granulocytes are strongly activated and adopt a so-called low-density phenotype, prone to spontaneously form NETs. In accordance, markers indicating NET turnover are consistently increased in COVID-19 and linked to disease severity. Histopathology of the lungs and other organs from COVID-19 patients showed congestions of numerous micro-vessels by aggregated NETs associated with endothelial damage. Interpretation: These data suggest that organ dysfunction in severe COVID-19 is associated with excessive NET formation and vascular damage. Funding: Deutsche Forschungsgemeinschaft (DFG), EU, Volkswagen-Stiftung
CRIS-Team Scopus Importer:2020-08-14
Keywords: Aggregated neutrophil extracellular traps; Coagulopathy; Endothelialitis; Immunothrombosis; SARS-CoV-2

VEGFR2 Signaling Prevents Colorectal Cancer Cell Senescence to Promote Tumorigenesis in Mice With Colitis - Försch, Sebastian; Sperka, Tobias; Lindner, Christina; Taut, Astrid; Rudolph, Karl L.; Breier, Georg; Boxberger, Frank; Rau, Tilman; Hartmann, Arndt; Stürzl, Michael; Wittkopf, Nadine; Haep, Lisa; et al. (Gastroenterology, 2015)
Senescence prevents cellular transformation. We investigated whether vascular endothelial growth factor (VEGF) signaling via its receptor, VEGFR2, regulates senescence and proliferation of tumor cells in mice with colitis-associated cancer (CAC).CAC was induced in VEGFR2(?IEC) mice, which do not express VEGFR2 in the intestinal epithelium, and VEGFR2(fl/fl) mice (controls) by administration of azoxymethane followed by dextran sodium sulfate. Tumor development and inflammation were determined by endoscopy. Colorectal tissues were collected for immunoblot, immunohistochemical, and quantitative polymerase chain reaction analyses. Findings from mouse tissues were confirmed in human HCT116 colorectal cancer cells. We analyzed colorectal tumor samples from patients before and after treatment with bevacizumab.After colitis induction, VEGFR2(?IEC) mice developed significantly fewer tumors than control mice. A greater number of intestinal tumor cells from VEGFR2(?IEC) mice were in senescence than tumor cells from control mice. We found VEGFR2 to activate phosphatidylinositol-4,5-bisphosphate-3-kinase and AKT, resulting in inactivation of p21 in HCT116 cells. Inhibitors of VEGFR2 and AKT induced senescence in HCT116 cells. Tumor cell senescence promoted an anti-tumor immune response by CD8(+) T cells in mice. Patients whose tumor samples showed an increase in the proportion of senescent cells after treatment with bevacizumab had longer progression-free survival than patients in which the proportion of senescent tumor cells did not change before and after treatment.Inhibition of VEGFR2 signaling leads to senescence of human and mouse colorectal cancer cells. VEGFR2 interacts with phosphatidylinositol-4,5-bisphosphate-3-kinase and AKT to inactivate p21. Colorectal tumor senescence and p21 level correlate with patient survival during treatment with bevacizumab.
EVALuna2:1356

Vitiligo in Childhood and Adolescence - Hartmann, Arndt (JOURNAL DER DEUTSCHEN DERMATOLOGISCHEN GESELLSCHAFT, 2019)
CRIS-Team WoS Importer:2019-05-17

What is new in the diagnosis and therapy of renal cell carcinoma? Was ist neu bei der Diagnostik und Therapie des Nierenzellkarzinoms? - Ahrens, Marit; Hartmann, Arndt; Bergmann, Lothar (Deutsche Medizinische Wochenschrift, 2020)
Renal cell carcinomas (RCC) include different tumor entities, of which clear cell RCC is the most common tumor with approx. 75 % followed by the papillary RCC with 10-15 %. RCC are increasingly being diagnosed incidental in the context of abdominal diagnostics from other indications using sonography or cross-sectional imaging.The prognosis of metastatic RCC has improved significantly due to new therapy options, especially through the use of immune checkpoint inhibitors (IO). In the first line, combination therapies of the tyrosine kinase inhibitor (TKI) axitinib with the PD-1 antibody pembrolizumab or the PDL-1 antibody avelumab apply regardless of the risk profile and histological entity, as well as the combination of the CTLA4 antibody ipilimumab with the PD-1 antibody nivolumab in patients with intermediate and high risk as new standards in therapy. The combinations lead to a higher response rate and longer survival. In the second line and subsequent lines, there is no evidence-based data after combination therapies, but drugs can be used that were not yet part of the first-line therapy.
CRIS-Team Scopus Importer:2020-06-16

WHO 1973 grade 3 and infiltrative growth pattern proved, aberrant E-cadherin expression tends to be of predictive value for progression in a series of stage T1 high-grade bladder cancer after organ-sparing approach - Otto, Wolfgang; Breyer, Johannes; Herdegen, Sonja; Eder, Fabian; Bertz, Simone; May, Matthias; Mayr, Roman; Lausenmeyer, Eva M.; Denzinger, Stefan; Van Rhijn, Bas W. G.; Burger, Maximilian; Hartmann, Arndt (International Urology and Nephrology, 2017)
Stage pT1 urothelial bladder cancer (UBC) is characterized as a challenging subentity of urothelial carcinoma with an unforeseeable clinical course. In addition to more or less established clinical and histopathological features, we evaluated the role of epithelial-mesenchymal transition (EMT) marker E-cadherin, shown to be of prognostic value in muscle-invasive disease, regarding the prognosis of stage pT1 high-grade (hg) UBC.Tissue of 226 stage pT1 hg UBC patients from transurethral resection could be immunostained for E-cadherin. Kaplan-Meier analysis and univariate and multivariate Cox regression analyses regarding progression-free (PFS) and cancer-specific survival (CSS) were performed.Aberrant expression of E-cadherin was recognized in 74% of patients. Kaplan-Meier analysis showed that aberrant E-cadherin expression was associated with worse 10-year PFS (62 vs. 90%, p = 0.045). In univariate analysis, aberrant E-cadherin staining, associated carcinoma in situ, grading 3 after WHO classification 1973 and infiltrative growth pattern at the invasion front were the statistically significant predictive factors for worse PFS, only infiltrative growth pattern for CSS. With regard to progression, grading 3 after WHO classification of 1973 (HR 6.49; CI 1.54-27.28, p = 0.011) and infiltrative tumor invasion pattern (HR 2.06; CI 1.10-3.86, p = 0.024) revealed as independent factors for PFS, and there was a trend also for E-cadherin expression (HR 0.45; CI 0.19-1.06; p = 0.068). Regarding CSS, infiltrative tumor growth pattern (HR 3.79; CI 1.67-8.60, p = 0.001) was the only statistically significantly independent predictive factor in multivariate Cox regression analysis.Beside invasion growth pattern and WHO grading 1973 that achieved to be independent prognostic factors, there was a trend for the parameter E-cadherin expression to be of predictive value for PFS in stage pT1 hg urothelial bladder carcinoma after organ-sparing approach. Further studies on genetic level are warranted to define the distinct role of EMT in early-invasive UBC.
EVALuna2:6872

WHO 2022 classification of penile and scrotal cancers: updates and evolution - Menon, S.; Moch, H.; Berney, D. M.; Cree, I. A.; Srigley, J. R.; Tsuzuki, T.; Comperat, E.; Hartmann, Arndt; Netto, G.; Rubin, M. A.; Gill, A. J.; Turajlic, S.; et al. (Histopathology, 2022)
Squamous cell carcinoma (SCC) is the most common malignant tumour of the penis. The 2022 WHO classification reinforces the 2016 classification and subclassifies precursor lesions and tumours into human papillomavirus (HPV)-associated and HPV-independent types. HPV-associated penile intraepithelial neoplasia (PeIN) is a precursor lesion of invasive HPV- associated SCC, whereas differentiated PeIN is a precursor lesion of HPV-independent SCC. Block-type positivity of p16 immunohistochemistry is the most practical daily utilised method to separate HPVassociated from HPVindependent penile SCC. If this is not feasible, the term SCC, not otherwise specified (NOS) is appropriate. Certain histologies that were previously classified as "subtypes" are now grouped, and coalesced as "patterns", under the rubric of usual type SCC and verrucous carcinoma (e.g. usual-type SCC includes pseudohyperplastic and acantholytic/pseudoglandular carcinoma, and carcinoma cuniculatum is included as a pattern of verrucous carcinoma). If there is an additional component of the usual type of invasive SCC (formerly termed hybrid histology), the tumour would be a mixed carcinoma (e.g. carcinoma cuniculatum or verrucous carcinoma with usual invasive SCC); in such cases, reporting of the relative percentages in mixed tumours may be useful. The consistent use of uniform nomenclature and reporting of percentages will inform the refinement of future reporting classification schemes and guidelines/recommendations. The classification of scrotal tumours is provided for the first time in the fifth edition of the WHO Blue book, and it follows the schema of penile cancer classification for both precursor lesions and the common SCC of the scrotum. Basal cell carcinoma of the scrotum may have a variable clinical course and finds a separate mention.
CRIS-Team WoS Importer:2022-11-25

WHO 2022 landscape of papillary and chromophobe renal cell carcinoma - Lobo, João; Ohashi, Riuko; Amin, Mahul B.; Berney, Daniel M.; Compérat, Eva M.; Cree, Ian A.; Gill, Anthony J.; Hartmann, Arndt; Menon, Santosh; Netto, George J.; Raspollini, Maria R.; Rubin, Mark A.; et al. (Histopathology, 2022)
The 5th edition of the WHO Classification of Tumours of the Urinary and Male Genital Systems contains relevant revisions and introduces a group of molecularly defined renal tumour subtypes. Herein we present the World Health Organization (WHO) 2022 perspectives on papillary and chromophobe renal cell carcinoma with emphasis on their evolving classification, differential diagnosis, and emerging entities. The WHO 2022 classification eliminated the type 1/2 papillary renal cell carcinoma (pRCC) subcategorization, given the recognition of frequent mixed tumour phenotypes and the existence of entities with a different molecular background within the type 2 pRCC category. Additionally, emerging entities such as biphasic squamoid alveolar RCC, biphasic hyalinising psammomatous RCC, papillary renal neoplasm with reverse polarity, and Warthin-like pRCC are included as part of the pRCC spectrum, while additional morphological and molecular data are being gathered. In addition to oncocytomas and chromophobe renal cell carcinoma (chRCC), a category of ‘other oncocytic tumours’ with oncocytoma/chRCC-like features has been introduced, including emerging entities, most with TSC/mTOR pathway alterations (eosinophilic vacuolated tumour and so-called ‘low-grade’ oncocytic tumour), deserving additional research. Eosinophilic solid and cystic RCC was accepted as a new and independent tumour entity. Finally, a highly reproducible and clinically relevant universal grading system for chRCC is still missing and is another niche of ongoing investigation. This review discusses these developments and highlights emerging morphological and molecular data relevant for the classification of renal cell carcinoma.
CRIS-Team Scopus Importer:2022-06-17
Keywords: chromophobe renal cell carcinoma; emerging entities; molecular pathology; papillary renal cell carcinoma; renal tumours

WHO Classification of Tumours fifth edition: evolving issues in the classification, diagnosis, and prognostication of prostate cancer - Kench, James G.; Amin, Mahul B.; Berney, Daniel M.; Compérat, Eva M.; Cree, Ian A.; Gill, Anthony J.; Hartmann, Arndt; Menon, Santosh; Moch, Holger; Netto, George J.; Raspollini, Maria R.; Rubin, Mark A.; et al. (Histopathology, 2022)
The fifth edition of the WHO Classification of Tumours of the Urinary and Male Genital Systems encompasses several updates to the classification and diagnosis of prostatic carcinoma as well as incorporating advancements in the assessment of its prognosis, including recent grading modifications. Some of the salient aspects include: (1) recognition that prostatic intraepithelial neoplasia (PIN)-like carcinoma is not synonymous with a pattern of ductal carcinoma, but better classified as a subtype of acinar adenocarcinoma; (2) a specific section on treatment-related neuroendocrine prostatic carcinoma in view of the tight correlation between androgen deprivation therapy and the development of prostatic carcinoma with neuroendocrine morphology, and the emerging data on lineage plasticity; (3) a terminology change of basal cell carcinoma to “adenoid cystic (basal cell) cell carcinoma” given the presence of an underlying MYB::NFIB gene fusion in many cases; (4) discussion of the current issues in the grading of acinar adenocarcinoma and the prognostic significance of cribriform growth patterns; and (5) more detailed coverage of intraductal carcinoma of prostate (IDC-P) reflecting our increased knowledge of this entity, while recommending the descriptive term atypical intraductal proliferation (AIP) for lesions falling short of IDC-P but containing more atypia than typically seen in high-grade prostatic intraepithelial neoplasia (HGPIN). Lesions previously regarded as cribriform patterns of HGPIN are now included in the AIP category. This review discusses these developments, summarising the existing literature, as well as the emerging morphological and molecular data that underpins the classification and prognostication of prostatic carcinoma.
CRIS-Team Scopus Importer:2022-08-12
Keywords: pathology; prostate carcinoma; WHO Classification

Wild type Kirsten rat sarcoma is a novel microRNA-622-regulated therapeutic target for hepatocellular carcinoma and contributes to sorafenib resistance - Dietrich, Peter; Koch, Andreas; Fritz, Valerie; Hartmann, Arndt; Boßerhoff, Anja Katrin; Hellerbrand, Claus (Gut, 2017)
Sorafenib is the only effective therapy for advanced hepatocellular carcinoma (HCC). Combinatory approaches targeting mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK)- and phosphatidylinositol-4,5-bisphosphate-3-kinase (PI3K)/protein-kinase B(AKT) signalling yield major therapeutic improvements. RAS proteins regulate both RAF/MAPK and PI3K/AKT signalling. However, the most important RAS isoform in carcinogenesis, Kirsten rat sarcoma (KRAS), remains unexplored in HCC.Human HCC tissues and cell lines were used for expression and functional analysis. Sorafenib-resistant HCC cells were newly generated. RNA interference and the novel small molecule deltarasin were used for KRAS inhibition both in vitro and in a murine syngeneic orthotopic HCC model.Expression of wild type KRAS messenger RNA and protein was increased in HCC and correlated with extracellular-signal regulated kinase (ERK) activation, proliferation rate, advanced tumour size and poor patient survival. Bioinformatic analysis and reporter assays revealed that KRAS is a direct target of microRNA-622. This microRNA was downregulated in HCC, and functional analysis demonstrated that KRAS-suppression is the major mediator of its inhibitory effect on HCC proliferation. KRAS inhibition markedly suppressed RAF/ERK and PI3K/AKT signalling and proliferation and enhanced apoptosis of HCC cells in vitro and in vivo. Combinatory KRAS inhibition and sorafenib treatment revealed synergistic antitumorigenic effects in HCC. Sorafenib-resistant HCC cells showed elevated KRAS expression, and KRAS inhibition resensitised sorafenib-resistant cells to suppression of proliferation and induction of apoptosis.KRAS is dysregulated in HCC by loss of tumour-suppressive microRNA-622, contributing to tumour progression, sorafenib sensitivity and resistance. KRAS inhibition alone or in combination with sorafenib appears as novel promising therapeutic strategy for HCC.
EVALuna2:4776

XCR1 expression distinguishes human conventional dendritic cell type 1 with full effector functions from their immediate precursors - Heger, Lukas; Hatscher, Lukas; Liang, Chunguang; Lehmann, Christian; Amon, Lukas; Lühr, Jennifer J.; Kaszubowski, Tomasz; Nzirorera, Rayk; Schaft, Niels; Dörrie, Jan; Irrgang, Pascal; Tenbusch, Matthias; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2023)
Dendritic cells (DCs) are major regulators of innate and adaptive immune responses. DCs can be classified into plasmacytoid DCs and conventional DCs (cDCs) type 1 and 2. Murine and human cDC1 share the mRNA expression of XCR1. Murine studies indicated a specific role of the XCR1-XCL1 axis in the induction of immune responses. Here, we describe that human cDC1 can be distinguished into XCR1- and XCR1+ cDC1 in lymphoid as well as nonlymphoid tissues. Steady-state XCR1+ cDC1 display a preactivated phenotype compared to XCR1- cDC1. Upon stimulation, XCR1+ cDC1, but not XCR1- cDC1, secreted high levels of inflammatory cytokines as well as chemokines. This was associated with enhanced activation of NK cells mediated by XCR1+ cDC1. Moreover, XCR1+ cDC1 excelled in inhibiting replication of Influenza A virus. Further, under DC differentiation conditions, XCR1- cDC1 developed into XCR1+ cDC1. After acquisition of XCR1 expression, XCR1- cDC1 secreted comparable level of inflammatory cytokines. Thus, XCR1 is a marker of terminally differentiated cDC1 that licenses the antiviral effector functions of human cDC1, while XCR1- cDC1 seem to represent a late immediate precursor of cDC1.
CRIS-Team Scopus Importer:2023-08-25
Keywords: antiviral immunity; cDC1; DC differentiation; IL-12; XCR1

Xpert bladder cancer monitor to predict the need for a second TURB (MoniTURB trial) - Breyer, Johannes; Eckstein, Markus; Sikic, Danijel; Wezel, Felix; Roghmann, Florian; Brehmer, Mirco; Wirtz, Ralph M.; Jarczyk, Jonas; Erben, Philipp; Bahlinger, Veronika; Goldschmidt, Franziska; Fechner, Guido; et al. (Scientific Reports, 2023)
To determine whether Xpert bladder cancer monitor, a noninvasive PCR-based biomarker test, can predict the need for 2nd transurethral resection of the bladder (TURB) better than clinical assessment. Patients scheduled for TURB were prospectively screened. After initial TURB, patients were assigned to 2nd TURB or follow-up cystoscopy at 3 months (FU) by clinicians’ discretion. Central urine cytology and Xpert monitor tests were performed prior to the 1st TURB and 2nd TURB or FU, respectively. Statistical analysis to compare clinical assessment and Xpert monitor comprised sensitivity (SENS), specificity (SPEC), NPV and PPV. Of 756 screened patients, 171 were included (114 with 2nd TURB, 57 with FU). Residual tumors were detected in 34 patients who underwent 2nd TURB, and recurrent tumors were detected in 2 patients with FU. SENS and SPEC of Xpert monitor were 83.3% and 53.0%, respectively, PPV was 32.6% and NPV was 92.1%. Clinical risk assessment outperformed Xpert monitor. In patients with pTa disease at initial TURB, Xpert monitor revealed a NPV of 96%. Xpert monitor was not superior than clinical assessment in predicting the need for 2nd TURB. It might be an option to omit 2nd TURB for selected patients with pTa disease.
CRIS-Team Scopus Importer:2023-09-29

YAP1-MAML2-Rearranged Poroid Squamous Cell Carcinoma (Squamoid Porocarcinoma) Presenting as a Primary Parotid Gland Tumor - Agaimy, Abbas; Stöhr, Robert; Tögel, Lars; Hartmann, Arndt; Cramer, Thomas (Head and Neck Pathology, 2020)
Porocarcinoma (synonym: malignant eccrine poroma) is a rare aggressive carcinoma type with terminal sweat gland duct differentiation. The squamous variant of porocarcinoma is even less frequent and might be indistinguishable from conventional squamous cell carcinoma (SCC). We herein describe the first case of a carcinoma presenting as a primary parotid gland malignancy in a 24-year-old male without any other primary tumor. Total parotidectomy and neck dissection were performed followed by adjuvant chemoradiation. The patient remained alive and well 10 months after diagnosis. Histology showed keratinizing SCC infiltrating extensively the parotid gland with subtle poroid cell features. Oncogenic HPV infection was excluded by DNA-based testing. NGS analysis using the TruSight RNA fusion panel (Illumina) revealed a novel YAP1-MAML2 gene fusion. This gene fusion was reported recently in a subset of cutaneous porocarcinoma and poroma. This case of poroid SCC (or squamoid porocarcinoma) adds to the differential diagnosis of SCC presenting as parotid gland tumor and highlights the value of molecular testing in cases with unusual presentation.
CRIS-Team Scopus Importer:2020-06-16
Keywords: Head and neck; MAML2; Parotid; Porocarcinoma; Poroma; Salivary glands; Squamous cell carcinoma; YAP1

ypN0 nodal status after neoadjuvant chemoradiotherapy for rectal carcinoma is not associated with adverse prognosis as compared with pN0 after primary surgery - Erlenbach-Wuensch, Katharina; Semrau, Sabine; Fietkau, Rainer; Weber, Klaus; Hohenberger, Werner; Rau, Tilman; Hartmann, Arndt; Merkel, Susanne; Agaimy, Abbas (International Journal of Colorectal Disease, 2014)
Neoadjuvant chemoradiotherapy (nCRT) has been established as standard treatment for locally advanced rectal cancer (cT3/4 or cN+ cM0, distance from circumferential resection margin <=1 mm) to enhance local disease control and minimize the rate of locoregional recurrence. As a consequence of downstaging, a significant proportion of patients show non-viable tumor deposits within regional lymph nodes that qualify as ypN0 according to the current TNM classification irrespective of the actual pre-treatment status. Accordingly, the prognostic relevance of ypN0 status as compared with true pN0 without preceding nCRT is not known.We retrospectively analyzed 132 patients who underwent standard total mesorectal excision (TME) surgery after nCRT for rectal carcinoma and were classified as ypN0, and compared their prognoses with those of 341 patients with pN0 without nCRT.Re-evaluation of regional lymph nodes after nCRT showed no evidence of previous metastasis in 91 cases (ypN0(-)), sure but non-viable metastasis in 14 patients (ypN0(+)), and unsure status in 27 patients (ypN0(X)). The local recurrence rate, distant metastases, and disease-free, observed, and cancer-related survival were similar in all subgroups (p = 0.447, 0.695, 0.759, 0.655, and 0.354, respectively).Our results showed a similar outcome in patients with ypN0 and in the control group with pN0 regarding local recurrence rate, distant metastases, and disease-free, observed, and cancer-related survival. Validation of these results is necessary to clarify the questions regarding postoperative adjuvant chemotherapy for patients with ypN0(+).
EVALuna2:6516

Zukunft mammographie-basierter Bildgebung [Future of mammography-based imaging] - Schulz-Wendtland, Rüdiger; Wittenberg, Thomas; Michel, Thilo; Hartmann, Arndt; Beckmann, Matthias; Rauh, Claudia; Judt, Sebastian; Brehm, Barbara; Meier-Meitinger, Martina; Anton, Gisela; Uder, Michael; Fasching, Peter (Radiologe, 2014)
Mammography is the central diagnostic method for clinical diagnostics of breast cancer and the breast cancer screening program. In the clinical routine complementary methods, such as ultrasound, tomosynthesis and optional magnetic resonance imaging (MRI) are already combined for the diagnostic procedure. Future developments will utilize investigative procedures either as a hybrid (combination of several different imaging modalities in one instrument) or as a fusion method (the technical fusion of two or more of these methods) to implement fusion imaging into diagnostic algorithms. For screening there are reasonable hypotheses to aim for studies that individualize the diagnostic process within the screening procedure. Individual breast cancer risk prediction and individualized knowledge about sensitivity and specificity for certain diagnostic methods could be tested. The clinical implementation of these algorithms is not yet in sight. (orig.) [German] Die Mammographie ist die zentrale diagnostische Methode der klinischen symptombezogenen Abklaerung von Brusterkrankungen und des Brustkrebsscreenings. In der klinischen Diagnostik wird sie heute schon oft durch zusaetzliche Untersuchungsmethoden wie dem Ultraschall, der Tomosynthese und ggf. auch der MRT-Bildgebung unterstuetzt. Zukuenftige Entwicklungen gehen in die Richtung, dass diese Kombination aus 2 oder mehr Untersuchungsverfahren entweder in Hybrid- (Aufnahme mehrerer unterschiedlicher Bildmodalitaeten in einem einzigen Geraet) oder in Fusionsmethoden (Zusammenfuehrung und Registrierung von Bilddaten aus verschiedenen Modalitaeten) technisch professionalisiert werden. Des Weiteren koennten an subgruppenbezogene Erkrankungsrisiken und individuelle Sensitivitaeten und Spezifitaeten angepasste Diagnostikkombinationen fuer eine Screeningdiagnostik Gegenstand kuenftiger Studien sein. Wir stellen die aktuellen Entwicklungen auf diesen Gebieten und deren momentane Relevanz fuer die klinische Praxis und Entwicklungspotenzial fuer die Zukunft dar. (orig
UnivIS-Import:2015-04-14:Pub.2014.tech.IMMD.IMMD9.zukunf
Keywords: MAMMOgraphy